Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley - Seidel, Andrew Colin; Carr, Christopher; Stojanowski, Christopher M; Buikstra, Jane E; Aguilera, Miguel (Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley)
Federal legislation prioritizes the repatriation of culturally unidentifiable human remains to federally-recognized Indian tribes that are linked geographically to the region from which the remains were removed. Such linkages are typically based on a Eurocentric notion of the exclusive use and occupancy of an area of land - a space-based approach to land use. Contemporary collaborations between anthropologists and indigenous communities suggest, however, that indigenous patterns of land use are better characterized as place-based and are therefore more complex and fluid than is reflected in current legislation. Despite these insights, space-based approaches remain common within archaeology. One example is the inference of territorial behavior from the presence of monuments within the archaeological record. Drawing on osteological and mortuary data derived from a sample of Adena mounds located in northern Kentucky, this dissertation adopts a place-based approach in order to evaluate the archaeological association between monumentality and territoriality. The relative amounts of skeletal and phenotypic variability present at various spatial scales are quantified and compared and the degree to which mortuary and phenotypic data exhibit spatial structure consistent with the expectations of an isolation-by-distance model is assessed. Results indicate that, while burial samples derived from some mounds exhibit amounts of phenotypic variability that are consistent with the expectations of a territorial model, data from other mounds suggest that multiple groups participated in their construction. Further, the general absence of spatial structure within the phenotypic data suggests that the individuals interred in these mounds are perhaps better characterized as representing an integrated regional population rather than localized groups. Untested archaeological inferences of territoriality may therefore mischaracterize regional population dynamics. In addition, these results suggest that the prioritization criteria for the repatriation of culturally unidentifiable human remains may merit revision.
Doctoral Dissertation Anthropology 2019
Keywords: Adena; Archaeology; Biodistance; Kentucky; Mortuary Practices; Physical anthropology

Improving Ionplus MICADAS performance with recessed graphite - Broek, Taylor A. B.; Roberts, Mark L. (Radiocarbon, 2024)
Cathodes with recessed sample surfaces have several benefits in cesium sputter ion sources, including higher output, more efficient use of sample material, and improved focusing of the extracted ion beam. However, the Ionplus MICADAS uses cathodes with a graphite surface that is essentially flush with the sample holder. To evaluate the performance of recessed graphite with the MICADAS and determine the optimal surface depth, we tested four different depths, including the standard (flush) pressing method, 0.5 mm, 1.0 mm, and 1.5 mm. We found that recessed depths of 1.0 and 1.5 mm resulted in 20% higher ion beam current compared to the standard method under the same source conditions. The results are consistent with the beam produced from the recessed targets being more narrowly focused with a lower emittance, resulting in better transmission through the accelerator. Small graphite samples (200 mu g C) with recessed surfaces produced higher currents for longer, leading to a 2-3x increase in sample ionization efficiency. Additionally, there was some evidence that isotopic ratio measurements of recessed samples were more stable over time. Overall, samples recessed to 1 mm depth offered numerous advantages over the standard pressing method and we have subsequently started pressing all MICADAS graphite using this approach.
Place: EDINBURGH BLDG, SHAFTESBURY RD, CB2 8RU CAMBRIDGE, ENGLAND Publisher: CAMBRIDGE UNIV PRESS Type: Article; Early Access
Keywords: AMS; MICADAS; radiocarbon

Comparability of Radiocarbon Measurements in Dissolved Inorganic Carbon of Seawater Produced at ETH-Zurich - Castrillejo, Maxi; Hansman, Roberta L.; Graven, Heather D.; Lester, Joanna G.; Bollhalder, Silvia; Kündig, Kayley; Wacker, Lukas (Radiocarbon, 2023)
Radiocarbon observations (Δ14C) in dissolved inorganic carbon (DIC) of seawater provide useful information about ocean carbon cycling and ocean circulation. To deliver high-quality observations, the Laboratory of Ion Beam Physics (LIP) at ETH-Zurich developed a new simplified method allowing the rapid analysis of radiocarbon in DIC of small seawater samples, which is continually assessed by following internal quality controls. However, a comparison with externally produced 14C measurements to better establish an equivalency between methods was still missing. Here, we make the first intercomparison with the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility based on 14 duplicate seawater samples collected in 2020. We also compare with prior deep-water observations from the 1970s to 1990s. The results show a very good agreement in both comparisons. The mean Δ14C of 12 duplicate samples measured by LIP and NOSAMS were statistically identical within one sigma uncertainty while two other duplicate samples agreed within two sigma. Based on this small number of duplicate samples, LIP values appear to be slightly lower than the NOSAMS values, but more measurements will be needed for confirmation. We also comment on storage and preservation techniques used in this study, including the freezing of samples collected in foil bags.
Publisher: Cambridge University Press
Keywords: 14C; comparison; DIC; dissolved inorganic carbon; radiocarbon; SEAWATER

Earthquake-enhanced dissolved carbon cycles in ultra-deep ocean sediments - Chu, Mengfan; Bao, Rui; Strasser, Michael; Ikehara, Ken; Everest, Jez; Maeda, Lena; Hochmuth, Katharina; Xu, Li; McNichol, Ann; Bellanova, Piero; Rasbury, Troy; Kölling, Martin; et al. (Nature Communications, 2023)
Hadal trenches are unique geological and ecological systems located along subduction zones. Earthquake-triggered turbidites act as efficient transport pathways of organic carbon (OC), yet remineralization and transformation of OC in these systems are not comprehensively understood. Here we measure concentrations and stable- and radiocarbon isotope signatures of dissolved organic and inorganic carbon (DOC, DIC) in the subsurface sediment interstitial water along the Japan Trench axis collected during the IODP Expedition 386. We find accumulation and aging of DOC and DIC in the subsurface sediments, which we interpret as enhanced production of labile dissolved carbon owing to earthquake-triggered turbidites, which supports intensive microbial methanogenesis in the trench sediments. The residual dissolved carbon accumulates in deep subsurface sediments and may continue to fuel the deep biosphere. Tectonic events can therefore enhance carbon accumulation and stimulate carbon transformation in plate convergent trench systems, which may accelerate carbon export into the subduction zones., Earthquakes enhance dissolved carbon production and fuel the microbial activities in hadal trench subsurface sediments, and ultimately strengthen carbon accumulation and transformation in the subduction zones.

Independent age estimates resolve the controversy of ancient human footprints at White Sands - Pigati, Jeffrey S.; Springer, Kathleen B.; Honke, Jeffrey S.; Wahl, David; Champagne, Marie R.; ZIMMERMAN, SUSAN R. H.; Gray, Harrison J.; Santucci, Vincent L.; Odess, Daniel; Bustos, David; Bennett, Matthew R. (Science, 2023)
Human footprints at White Sands National Park, New Mexico, USA, reportedly date to between ~23,000 and 21,000 years ago according to radiocarbon dating of seeds from the aquatic plant Ruppia cirrhosa. These ages remain controversial because of potential old carbon reservoir effects that could compromise their accuracy. We present new calibrated 14C ages of terrestrial pollen collected from the same stratigraphic horizons as those of the Ruppia seeds, along with optically stimulated luminescence ages of sediments from within the human footprint–bearing sequence, to evaluate the veracity of the seed ages. The results show that the chronologic framework originally established for the White Sands footprints is robust and reaffirm that humans were present in North America during the Last Glacial Maximum.
Publisher: American Association for the Advancement of Science

Machine learning based anomaly detection for sedimentological data: Application to a Holocene multi-proxy paleoenvironmental reconstruction from Laguna Boquita, Jalisco, Mexico - Bianchette, Thomas A.; Pandey, Vijitashwa; Mollan, Calahan; Hall, Sawyer; McCloskey, Terrence A.; Liu, Kam-biu (Marine Geology, 2023)
Paleoenvironmental reconstructions are critical to determine past climatological and hydrological conditions, such as sea-level rise (SLR) and extreme events including hurricanes and tsunamis. While established quantitative methods, such as principal components analysis and discriminant analysis, have effectively aided reconstructions by demarcating stratigraphic zones, they suffer from limitations due to the underlying assumptions (linearity, normality). Here, we introduce the machine learning technique anomaly detection for sedimentological reconstructions, capable of objectively pinpointing events (anomalies) in sediment cores. We tested this technique on five sediment cores extracted from Laguna Boquita, located along the Pacific coast of Mexico. Each core was subjected to high resolution loss-on-ignition, while the most representative core (core 1) was deemed the training core and scanned with a handheld XRF unit. In general, the sediment cores were dominated by thick units of peat and/or clay, and most cores contained sand layers. This reconstruction represents many environmental settings, ranging from a sandy terrestrial environment (∼6830- ∼ 6370 cal yr BP), organic-rich wetland (∼6370- ∼ 5170 cal yr BP), and clastic-rich backbarrier lagoon (∼5170 cal yr BP to present). The anomaly detection technique proved effective in marking many events, including marine transgression, evidence of SLR, transitions separating dominant depositional environments, and, perhaps most notably, a faded blue clay layer with minimal LOI variability that may represent a shift in backbarrier water level. The anomaly detection also registered anomalies when events were not visually distinct nor present in the LOI datasets (false positives), which represent sediment core sections that require further investigation with multiple proxies. However, anomaly detection failed to register anomalies in certain core sections that should have registered as events due to their distinct nature. Future efforts will look to improve anomaly detection by choosing different train cores and adding additional proxy datasets.
Keywords: Loss-on-ignition; Machine learning; Paleoclimate; peat; Radiocarbon dating; x-ray fluorescence

Organic carbon and planktic foraminifera radiocarbon derived Holocene sediment accumulation rates in the northern slopes of the Gulf of Mexico - Schwing, Patrick; Chanton, Jeffrey; Bosman, Samantha; Brooks, Gregg; Larson, Rebekka A.; Romero, Isabel; Diercks, Arne (Deep Sea Research Part I: Oceanographic Research Papers, 2023)
In the context of climate regulation and anthropogenic waste detoxification (e.g. oil spills), estimates of deep ocean sedimentation and carbon sequestration are of the utmost importance. Radiocarbon (14C) is a common radioisotope that can be used to establish millennial scale sediment accumulation rates. The objectives of this study were to: 1) establish ages for co-occurring total organic carbon (TOC) and planktic foraminifera (carbonate) in the northeastern Gulf of Mexico (GoM), 2) use these ages to estimate accumulation rates independently, 3) identify any evidence of redistribution, and 4) examine any offset between TOC and carbonate 14C ages as a tool to potentially identify selective TOC transport. Sediment samples were collected in May 2018 from the RV Point Sur using an Ocean Instruments MC-800 multi corer. Radiocarbon measurements of both planktic foraminifera and TOC subsamples were made at the National Ocean Science Accelerator Mass Spectrometry Facility (NOSAMS). Radiocarbon ages, calibrated using the OxCal 4.4, ranged from recent to 6407 BP. Linear (LAR: 4–24 cm/kyr) and mass accumulation rates (MAR: 1.5–11.5 g/cm2/kyr) were generally consistent with those reported by other recent studies in the GoM. At two sites, C14 ages decreased from the surface to the second sampling increment which was consistent with sediment redistribution. The TOC-carbonate offsets, which are indicative of lateral advection and organic matter aging, were lower than those found in the majority of other regions, which was consistent with less lateral transport or a more oligotrophic setting. The magnitude in radiocarbon age offsets with depth could potentially be used as a relative aging or transport assessment tool in areas with little resuspension.
Keywords: accumulation rates; Foraminifera; Gulf of Mexico; radiocarbon; Radiogeochemistry

Pre-aged terrigenous organic carbon biases ocean ventilation-age reconstructions in the North Atlantic - Liu, Jingyu; Wang, Yipeng; Jaccard, Samuel L.; Wang, Nan; Gong, Xun; Fang, Nianqiao; Bao, Rui (Nature Communications, 2023)
Changes in ocean ventilation have been pivotal in regulating carbon sequestration and release on centennial to millennial timescales. However, paleoceanographic reconstructions documenting changes in deep-ocean ventilation using 14C dating, may bear multidimensional explanations, obfuscating the roles of ocean ventilation played on climate evolution. Here, we show that previously inferred poorly ventilated conditions in the North Atlantic were linked to enhanced pre-aged organic carbon (OC) input during Heinrich Stadial 1 (HS1). The 14C age of sedimentary OC was approximately 13,345 ± 692 years older than the coeval foraminifera in the central North Atlantic during HS1, which is coupled to a ventilation age of 5,169 ± 660 years. Old OC was mainly of terrigenous origin and exported to the North Atlantic by ice-rafting. Remineralization of old terrigenous OC in the ocean may have contributed to, at least in part, the anomalously old ventilation ages reported for the high-latitude North Atlantic during HS1.
Number: 1 Publisher: Nature Publishing Group
Keywords: Carbon cycle; Marine chemistry; Palaeoceanography

Refractory Dissolved Organic Matter has Similar Chemical Characteristics but Different Radiocarbon Signatures With Depth in the Marine Water Column - White, Margot E.; Nguyen, Tran B.; Koester, Irina; Lardie Gaylord, Mary C.; Beman, J. Michael; Smith, Kenneth L.; McNichol, Ann P.; Beaupré, Steven R.; Aluwihare, Lihini I. (Global Biogeochemical Cycles, 2023)
The >5,000-year radiocarbon age (14C-age) of much of the 630 ± 30 Pg C oceanic dissolved organic carbon (DOC) reservoir remains an enigma in the marine carbon cycle. The fact that DOC is significantly older than dissolved inorganic carbon at every depth in the ocean forms the basis of our current framing of the marine DOC cycle, where some component persists over multiple cycles of ocean mixing. As a result, 14C-depleted, aged DOC is hypothesized to be present as a uniform reservoir with a constant 14C signature and concentration throughout the water column. However, key requirements of this model, including direct observations of DOC with similar 14C signatures in the surface and deep ocean, have never been met. Despite decades of research, the distribution of Δ14C values in marine DOC remains a mystery. Here, we applied a thermal fractionation method to compare operationally defined refractory DOC (RDOC) from different depths in the North Pacific Ocean. We found that RDOC shares chemical characteristics (as recorded by OC bond strength) throughout the water column but does not share the same 14C signature. Our results support one part of the current paradigm—that RDOC is comprised of structurally related components throughout the ocean that form a “background” reservoir. However, in contrast to the current paradigm, our results are consistent with a vertical concentration gradient and a vertical and inter-ocean Δ14C gradient for RDOC. The observed Δ14C gradient is compatible with the potential addition of pre-aged DOC to the upper ocean.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022GB007603
Keywords: marine dissolved organic matter; radiocarbon; ramped pyrolysis oxidation

A Tropical Cocktail of Organic Matter Sources: Variability in Supraglacial and Glacier Outflow Dissolved Organic Matter Composition and Age Across the Ecuadorian Andes - Holt, Amy D.; Kellerman, Anne M.; Battin, Tom. I.; McKenna, Amy M.; Hood, Eran; Andino, Patricio; Crespo-Pérez, Verónica; Peter, Hannes; Schön, Martina; De Staercke, Vincent; Styllas, Michail; Tolosano, Matteo; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
The biogeochemistry of rapidly retreating Andean glaciers is poorly understood, and Ecuadorian glacier dissolved organic matter (DOM) composition is unknown. This study examined molecular composition and carbon isotopes of DOM from supraglacial and outflow streams (n = 5 and 14, respectively) across five ice capped volcanoes in Ecuador. Compositional metrics were paired with streamwater isotope analyses (δ18O) to assess if outflow DOM composition was associated with regional precipitation gradients and thus an atmospheric origin of glacier DOM. Ecuadorian glacier outflows exported ancient, biolabile dissolved organic carbon (DOC), and DOM contained a high relative abundance (RA) of aliphatic and peptide-like compounds (≥27%RA). Outflows were consistently more depleted in Δ14C-DOC (i.e., older) compared to supraglacial streams (mean −195.2 and −61.3‰ respectively), perhaps due to integration of spatially heterogenous and variably aged DOM pools across the supraglacial environment, or incorporation of aged subglacial OM as runoff was routed to the outflow. Across Ecuador, Δ14C-DOC enrichment was associated with decreased aromaticity of DOM, due to increased contributions of organic matter (OM) from microbial processes or atmospheric deposition of recently fixed and subsequently degraded OM (e.g., biomass burning byproducts). There was a regional gradient between glacier outflow DOM composition and streamwater δ18O, suggesting covariation between regional precipitation gradients and the DOM exported from glacier outflows. Ultimately, this highlights that atmospheric deposition may exert a control on glacier outflow DOM composition, suggesting regional air circulation patterns and precipitation sources in part determine the origins and quality of OM exported from glacier environments.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007188
Keywords: cryosphere; dissolved organic carbon; Dissolved organic matter; Ecuador; FT-ICR MS; glaciers; δ13C-DOC; Δ14C-DOC

An 11,300 yr record of paleoclimatology and paleoceanography of the central California coast in a gravity core from Pioneer Seamount - Barron, John A.; Addison, Jason A.; Heusser, Linda E.; Bukry, David; Schwartz, Valerie; Wagner, Amy (Quaternary International, 2022)
Diatom, pollen, silicoflagellate, and biogenic opal analyses from a 155 cm-long gravity core from Pioneer Seamount, offshore Santa Cruz, California (PS1410-06 GC, latitude 37.3°N, longitude 123.4°W, water depth 2165 m) are compiled for the last ~11,300 years and compared with those of ODP 1019 and TN062-O550 from northern California. The relative abundance record of the subtropical diatom Fragilariopsis doliolus has similar bimodal Holocene patterns in all three cores, suggesting that sea surface temperatures (SST) were lower during the middle part of the Holocene than they were during the later and earlier parts. The relative abundance of coastal redwood (Sequoia sempervirens) pollen, a proxy for fog and coastal upwelling, displays stepwise increases in ODP 1019 and TN062-O550 between ~ 4000 and 3000 cal yr. BP, but its relative abundance in PS1410-06 GC increases gradually throughout the past 10,200 yr without any major steps. Similarly, biogenic silica (opal) displays stepwise increases at ~3600 and 2900 cal yr. BP in ODP 1019 and TN062-O550, respectively, whereas opal increases more gradually in PS1410-06 GC during the past 10,100 yr with relatively minor steps at ~3100 and ~2600 cal yr. BP. Together, coastal redwood and opal argue for a more gradual late Holocene increase in coastal upwelling along the coast of central California compared with that off northern California, where onshore-offshore gradients are more distinct.

A 4000-year paleoenvironmental reconstruction and extreme event record from Laguna Nuxco, Guerrero, Mexico - Bianchette, Thomas A.; Liu, Kam-biu; McCloskey, Terrence A. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
Reconstructing paleoenvironments on Mexico's Pacific coast is crucial to determine past climate conditions and natural hazard periodicities, vital for predicting future activities. Two sediment cores extracted from Laguna Nuxco, a coastal lagoon in Guerrero, were analyzed to provide a 4000-year paleoenvironmental record. Sediments dominated by shelly clay with low water and organic content, high carbonate content, low Ti/Ca ratio and the presence of Anomalocardia subrugosa suggest that a sheltered bay existed from ~4000–~1300 cal yr BP. During this stage, intermittent beach ridge gaps facilitated the deposition of storm-induced shell deposits, likely from tropical cyclones. Frequent thick shell hash deposition toward the top of the lithologic unit indicates heightened storminess likely from an increase in ENSO activity. An intense tropical cyclone, or perhaps multiple storms during an active period deposited a thick shell hash layer at ~1500 cal yr BP, which helped strengthen the beach ridge system and lead to the modern lagoon phase (~1300 cal yr BP to present), as suggested by the presence of Mytella sp. A more isolated lagoon with significant terrestrial sediment input was reflected by the predominance of lagoonal clay with decreased shell and carbonate contents, increased water and organic contents, and increased Ti/Ca ratio. A quiet period with lower tropical cyclone activity occurred from 1300 to 800 cal yr BP and from 300 cal yr BP to the present, as inferred from no or relatively few shell hash deposits, respectively. A period of hyperactivity occurred from 800 to 300 cal yr BP, as evidenced by seven shell hash layers. During the modern lagoon phase, shell hash deposition was not caused by marine inundation processes, but rather ‘blowout’ events driven by intense precipitation during heightened ENSO activity. Findings shed additional light on Late Holocene environmental changes in a dynamic coastal zone related to regional controlling factors such as tropical cyclone activity, ENSO, and beach ridge development.

Carbon Accumulation, Flux, and Fate in Stordalen Mire, a Permafrost Peatland in Transition - Holmes, M. E.; Crill, P. M.; Burnett, W. C.; McCalley, C. K.; Wilson, R. M.; Frolking, S.; Chang, K.‐Y.; Riley, W. J.; Varner, R. K.; Hodgkins, S. B.; McNichol, A. P.; Saleska, S. R.; et al. (Global Biogeochemical Cycles, 2022)
Stordalen Mire is a peatland in the discontinuous permafrost zone in arctic Sweden that exhibits a habitat gradient from permafrost palsa, to Sphagnum bog underlain by permafrost, to Eriophorum‐dominated fully thawed fen. We used three independent approaches to evaluate the annual, multi‐decadal, and millennial apparent carbon accumulation rates (aCAR) across this gradient: seven years of direct semi‐continuous measurement of CO2 and CH4 exchange, and 21 core profiles for 210Pb and 14C peat dating. Year‐round chamber measurements indicated net carbon balance of −13 ± 8, −49 ± 15, and −91 ± 43 g C m−2 y−1 for the years 2012–2018 in palsa, bog, and fen, respectively. Methane emission offset 2%, 7%, and 17% of the CO2 uptake rate across this gradient. Recent aCAR indicates higher C accumulation rates in surface peats in the palsa and bog compared to current CO2 fluxes, but these assessments are more similar in the fen. aCAR increased from low millennial‐scale levels (17–29 g C m−2 y−1) to moderate aCAR of the past century (72–81 g C m−2 y−1) to higher recent aCAR of 90–147 g C m−2 y−1. Recent permafrost collapse, greater inundation and vegetation response has made the landscape a stronger CO2 sink, but this CO2 sink is increasingly offset by rising CH4 emissions, dominated by modern carbon as determined by 14C. The higher CH4 emissions result in higher net CO2‐equivalent emissions, indicating that radiative forcing of this mire and similar permafrost ecosystems will exert a warming influence on future climate. Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon

Community practice and religion at an Early Islamic cemetery in highland Central Asia - Bullion, Elissa; Maksudov, Farhod; Henry, Edward R.; Merkle, Ann; Frachetti, Michael (Antiquity, 2022)
Archaeological studies of Early Islamic communities in Central Asia have focused on lowland urban communities. Here, the authors report on recent geophysical survey and excavation of an Early Islamic cemetery at Tashbulak in south-eastern Uzbekistan. AMS dating places the establishment of the cemetery in the mid-eighth century AD, making it one of the earliest Islamic burial grounds documented in Central Asia. Burials at Tashbulak conform to Islamic prescriptions for grave form and body deposition. The consistency in ritual suggests the existence of a funerary community of practice, challenging narratives of Islamic conversion in peripheral areas as a process of slow diffusion and emphasising the importance of archaeological approaches for documenting the diversity of Early Islamic communities.

Contemporary sources dominate carbonaceous aerosol on the North Slope of Alaska - Moffett, Claire E.; Mehra, Manisha; Barrett, Tate E.; Gunsch, Matthew J.; Pratt, Kerri A.; Sheesley, Rebecca J. (Science of The Total Environment, 2022)
As the Arctic continues to change and warm rapidly, it is increasingly important to understand the organic carbon (OC) contribution to Arctic aerosol. Biogenic sources of primary and secondary OC in the Arctic will be impacted by climate change, including warming temperatures and earlier snow and ice melt. This study focuses on identifying potential sources and regional influences on the seasonal concentration of organic aerosol through analysis of chemical and isotopic composition. Aerosol samples were collected at two sites on the North Slope of Alaska (Utqiaġvik, UQK, and Oliktok Point, OLK, which is in an Arctic oilfield) over three summers from 2015 to 2017. The elemental carbon (EC) trends at each site were used to understand local combustion influences. Local sources drove EC concentrations at Oliktok Point, where high EC was attributed to oil and gas extraction activity, including diesel combustion emissions. Utqiaġvik had very low EC in the summer. OC was more similar in concentration and well correlated between the two sites with high contributions of contemporary carbon by radiocarbon apportionment (UQK = 74%, OLK = 63%), which could include both marine and terrestrial sources of contemporary carbon (e.g. primary and secondary biogenic, biomass burning and/or associated SOA, and bioaerosols). OC concentrations are strongly correlated to maximum ambient temperatures on the NSA during the summer, which may have implications for predicting future OC aerosol concentrations in a warming Arctic. Biomass burning was determined to be an episodic influence at both sites, based on interpretation of combined aerosol composition, air mass trajectories, and remote sensing of smoke plumes. The results from this study overall strongly suggests contribution from regional sources of contemporary organic aerosol on the NSA, but additional analysis is needed to better constrain contributions from both biogenic sources (terrestrial and/or marine) and bioaerosol to better understand temperature-related aerosol processes in the Arctic.

Cultural Keystone Places and the Chumash Landscapes of Kumqaq’, Point Conception, California - Rick, Torben C.; Braje, Todd J.; Graham, Lain; Easterday, Kelly; Hofman, Courtney A.; Holguin, Brian E.; Mychajliw, Alexis M.; Reeder-Myers, Leslie A.; Reynolds, Mark D. (American Antiquity, 2022)
The places in which people live and spend time are steeped in history, memory, and meaning from the intersection of daily life, environmental interactions, cultural practices, and ritual. Geologic features, plants, animals, and ecosystems merge with these cultural histories, forming critical parts of the landscape and areas of “high cultural salience,” or “cultural keystone places” (CKPs). We identify Kumqaq’ (Point Conception) and the surrounding area in California as a Chumash CKP. Ethnohistoric accounts and contemporary Chumash community members have long demonstrated the importance of Point Conception in Chumash worldview and identity, whereas biologists, ecologists, and conservationists reference the area's rich biodiversity and significance as a biogeographical boundary. Recent archaeological survey of the coastline surrounding Kumqaq’ highlights these connections, identifying over 50 archaeological sites—including shell middens, villages, lithic scatters, and rock art—with at least 9,000 years of occupation. Ongoing collaborations among archaeologists, the Nature Conservancy, and Chumash community members help document and understand the long-term linkages between cultural and biological diversity and how integrating these perspectives can help ensure the resilience of this nexus of human and natural history in the Anthropocene future.

Geochemistry and Provenance of Springs in a Baja California Sur Mountain Catchment - Lerback, Jory C.; Bowen, Brenda B.; Humphrey, C. E.; Fernandez, Diego. P.; Bernau, Jeremiah A.; Macfarlan, Shane J.; Schniter, Eric; Garcia, J. J. (Groundwater, 2022)
Fractured rock aquifers cover much of Earth's surface and are important mountain sites for groundwater recharge but are poorly understood. To investigate groundwater systematics of a fractured-dominated aquifer in Baja California Sur, Mexico, we examined the spatial patterns of aquifer recharge and connectivity using the geochemistry of springs. We evaluate a range of geochemical data within the context of two endmember hypotheses describing spatial recharge patterns and fracture connectivity. Hypothesis 1 is that the aquifer system is segmented, and springs are fed by local recharge. Hypothesis 2 is that the aquifer system is well connected, with dominant recharge occurring in the higher elevations. The study site is a small <15 km2 catchment. Thirty-four distinct springs and two wells were identified in the study area, and 24 of these sites were sampled for geochemical analyses along an elevation gradient and canyon transect. These analyses included major ion composition, trace element and strontium isotopes, δ18 O and δ2 H isotopes, radiocarbon, and tritium. δ18 O and δ2 H isotopes suggest that the precipitation feeding the groundwater system has at least two distinct sources. Carbon isotopes showed a change along the canyon transect, suggesting that shorter flowpaths feed springs in the top of the transect, and longer flowpaths discharge near the bottom. Geochemical interpretations support a combination of the two proposed hypotheses. Understanding of the connectivity and provenance of these springs is significant as they are the primary source of water for the communities that inhabit this region and may be impacted by changes in recharge and use.

The giant 1960 tsunami in the context of a 6000‐year record of paleotsunamis and coastal evolution in south‐central Chile - Matos‐Llavona, Pedro I.; Ely, Lisa L.; MacInnes, Breanyn; Dura, Tina; Cisternas, Marco A.; Bourgeois, Joanne; Bruce, David; DePaolis, Jessica; Dolcimascolo, Alexander; Horton, Benjamin P.; Melnick, Daniel; Nelson, Alan R.; et al. (Earth Surface Processes and Landforms, 2022)
The tsunami associated with the giant 9.5 Mw 1960 Chile earthquake deposited an extensive sand layer above organic‐rich soils near Queule (39.3°S, 73.2°W), south‐central Chile. Using the 1960 tsunami deposits, together with eye‐witness observations and numerical simulations of tsunami inundation, we tested the tsunami inundation sensitivity of the site to different earthquake slip distributions. Stratigraphically below the 1960 deposit are two additional widespread sand layers interpreted as tsunami deposits with maximum ages of 4960–4520 and 5930–5740 cal BP. This >4500‐year gap of tsunami deposits preserved in the stratigraphic record is inconsistent with written and geological records of large tsunamis in south‐central Chile in 1575, 1837, and possibly 1737. We explain this discrepancy by: (1) poor preservation of tsunami deposits due to reduced accommodation space from relative sea‐level fall during the late Holocene; (2) recently evolved coastal geomorphology that increased sediment availability for tsunami deposit formation in 1960; and/or (3) the possibility that the 1960 tsunami was significantly larger at this particular location than other tsunamis in the past >4500 years. Our research illustrates the complexities of reconstructing a complete stratigraphic record of past tsunamis from a single site for tsunami hazard assessment. The coastal geomorphology near Queule, Chile preserves evidence of the giant Mw 9.51960 Chile earthquake and two buried paleotsunami deposits within the last 6000 years. Using the 1960 tsunami deposits, eye‐witness observations, and numerical simulations of tsunami inundation, we tested the sensitivity of the site to different earthquake slip distributions. We consider the role of coastal geomorphic evolution, sea‐level history, and tsunami magnitude in the preservation of paleotsunami depositional records.

Glacial isostatic adjustment near the center of the former Patagonian Ice Sheet (48°S) during the last 16.5 kyr - Troch, Matthias; Bertrand, Sébastien; Lange, Carina B.; Cárdenas, Paola; Arz, Helge; Pantoja-Gutiérrez, Silvio; De Pol-Holz, Ricardo; Kilian, Rolf (Quaternary Science Reviews, 2022)
Our understanding of glacial isostatic rebound across Patagonia is highly limited, despite its importance to constrain past ice volume estimates and better comprehend relative sea-level variations. With this in mind, our research objective is to reconstruct the magnitude and rate of Late Glacial and Holocene glacial isostatic adjustment near the center of the former Patagonian Ice Sheet. We focus on Larenas Bay (48°S; 1.26 km2), which is connected to Baker Channel through a shallow (7.4 m) and narrow (ca. 150 m across) inlet, and hence has the potential to record periods of basin isolation and marine ingression. The paleoenvironmental evolution of the bay was investigated through a sedimentological analysis of a 9.2 m long radiocarbon-dated sediment core covering the last 16.8 kyr. Salinity indicators, including diatom paleoecology, alkenone concentrations and CaCO3 content, were used to reconstruct the bay's connectivity to the fjord. Results indicate that Larenas Bay was a marine environment before 16.5 cal kyr BP and after 9.1 cal kyr BP, but that it was disconnected from Baker Channel in-between. We infer that the postglacial rebound started before 16.5 cal kyr BP and that it outpaced global sea-level rise until slightly before 9.1 cal kyr BP. During the Late Glacial and early Holocene, the center of the former Patagonian Ice Sheet experienced an absolute uplift of ca. 96 m, at an average rate of 1.3 cm/yr. During the remainder of the Holocene, glacial isostatic adjustment continued (ca. 20 m), but at a slower average pace of 0.2 cm/yr. Comparisons between multi-millennial variations in the salinity indicators and existing records of global sea-level rise suggest that the glacial isostatic adjustment rate also fluctuated within these time intervals, likely in response to glacier dynamics. More specifically, most of the glacial isostatic adjustment registered between 16.5 – 9.1 cal kyr BP seems to have occurred before meltwater pulse 1A (14.5 – 14.0 kyr BP). Likewise, it appears that the highest glacial isostatic rebound rates of the last 9.1 kyr occurred during the late Holocene, most likely in response to glacier recession from their Neoglacial maxima. This implies a relatively rapid response of the local solid earth to ice unloading, which agrees with independent modelling studies investigating contemporary uplift. We conclude that the center of the former Patagonian Ice Sheet experienced a glacial isostatic adjustment of ca. 116 m over the last 16.5 kyr, and that >80% occurred during the Late Glacial and early Holocene.

Heterogeneous Patterns of Aged Organic Carbon Export Driven by Hydrologic Flow Paths, Soil Texture, Fire, and Thaw in Discontinuous Permafrost Headwaters - Koch, Joshua C.; Bogard, Matthew J.; Butman, David E.; Finlay, Kerri; Ebel, Brian; James, Jason; Johnston, Sarah Ellen; Jorgenson, M. Torre; Pastick, Neal J.; Spencer, Robert G. M.; Striegl, Robert; Walvoord, Michelle; et al. (Global Biogeochemical Cycles, 2022)
Climate change is thawing and potentially mobilizing vast quantities of organic carbon (OC) previously stored for millennia in permafrost soils of northern circumpolar landscapes. Climate‐driven increases in fire and thermokarst may play a key role in OC mobilization by thawing permafrost and promoting transport of OC. Yet, the extent of OC mobilization and mechanisms controlling terrestrial‐aquatic transfer are unclear. We demonstrate that hydrologic transport of soil dissolved OC (DOC) from the active layer and thawing permafrost to headwater streams is extremely heterogeneous and regulated by the interactions of soils, seasonal thaw, fire, and thermokarst. Repeated sampling of streams in eight headwater catchments of interior Alaska showed that the mean age of DOC for each stream ranges widely from modern to ∼2,000 years B.P. Together, an endmember mixing model and nonlinear, generalized additive models demonstrated that Δ14C‐DOC signature (and mean age) increased from spring to fall, and was proportional to hydrologic contributions from a solute‐rich water source, related to presumed deeper flow paths found predominantly in silty catchments. This relationship was correlated with and mediated by catchment properties. Mean DOC ages were older in catchments with >50% burned area, indicating that fire is also an important explanatory variable. These observations underscore the high heterogeneity in aged C export and difficulty of extrapolating estimates of permafrost‐derived DOC export from watersheds to larger scales. Our results provide the foundation for developing a conceptual model of permafrost DOC export necessary for advancing understanding and prediction of land‐water C exchange in changing boreal landscapes. In high latitude environments, soils that have been frozen for millennia are thawing, releasing organic carbon (OC). Thawing and export of OC to downstream aquatic ecosystems is a potential biogeochemical feedback that may accelerate climate warming if large amounts of ancient OC are transformed and released to the atmosphere as greenhouse gases. The magnitude and timing of ancient OC thaw and mobilization are not well defined, so predicting these patterns at local to global scales is challenging. Using a suite of diverse headwater catchments in the discontinuous permafrost zone of Alaska, USA, we identify the main controls on the mobilization of ancient OC from thawing landscapes into adjacent streams. Our surveys show that ancient OC export depends on the complex interaction between fire history, soil type and thawing characteristics, and seasonal warming. We find that all of these factors play a role, resulting in highly heterogeneous release of ancient OC to headwater streams. Aged dissolved organic carbon (DOC) in headwater streams in interior Alaska is heterogeneous across permafrost landscapes indicating the interplay of multiple drivers Aged DOC concentrations increase from spring to fall and are highest in catchments with >50% burned extent and dominated by silty uplands Aged DOC is proportional to stream solute loads, indicating that deeper flow paths deliver permafrost C to streams Aged dissolved organic carbon (DOC) in headwater streams in interior Alaska is heterogeneous across permafrost landscapes indicating the interplay of multiple drivers Aged DOC concentrations increase from spring to fall and are highest in catchments with >50% burned extent and dominated by silty uplands Aged DOC is proportional to stream solute loads, indicating that deeper flow paths deliver permafrost C to streams

In-phase millennial-scale glacier changes in the tropics and North Atlantic regions during the HoloceneAbstract - Jomelli, V.; Swingedouw, D.; Vuille, M.; Favier, V.; Goehring, B.; Shakun, J.; Braucher, R.; Schimmelpfennig, I.; Menviel, L.; Rabatel, A.; Martin, L. C. P.; Blard, P.-H.; et al. (Nature Communications, 2022)
Based on new and published cosmic-ray exposure chronologies, we show that glacier extent in the tropical Andes and the north Atlantic regions (TANAR) varied in-phase on millennial timescales during the Holocene, distinct from other regions. Glaciers experienced an early Holocene maximum extent, followed by a strong mid-Holocene retreat and a re-advance in the late Holocene. We further explore the potential forcing of TANAR glacier variations using transient climate simulations. Since the Atlantic Meridional Overturning Circulation (AMOC) evolution is poorly represented in these transient simulations, we develop a semi-empirical model to estimate the “AMOC-corrected” temperature and precipitation footprint at regional scales. We show that variations in the AMOC strength during the Holocene are consistent with the observed glacier changes. Our findings highlight the need to better constrain past AMOC behavior, as it may be an important driver of TANAR glacier variations during the Holocene, superimposed on other forcing mechanisms.

Not all permafrost microbiomes are created equal: Influence of permafrost thaw on the soil microbiome in a laboratory incubation study - Barbato, R.A.; Jones, R.M.; Douglas, T.A.; Doherty, S.J.; Messan, K.; Foley, K.L.; Perkins, E.J.; Thurston, A.K.; Garcia-Reyero, N. (Soil Biology and Biochemistry, 2022)
Permafrost is thawing at unprecedented rates, significantly altering landscapes and ecosystem trajectories by changing subsurface conditions, vegetation characteristics, and soil properties. Dormant microbes become active as temperatures rise and permafrost soils warm and thaw. To determine the effects of sample location and warming on the permafrost microbiome, we collected permafrost from five distinct locations within the Cold Regions Research and Engineering Laboratory's Permafrost Tunnel (PT) near Fairbanks, Alaska and warmed them in a laboratory incubation study. Heterotrophic respiration was continuously monitored and metagenomes were analyzed at select incubation temperatures. Under frozen conditions, microbial respiration rates from different PT locations were similar, ranging from 2 to 12 mg C–CO2 kg−1 d−1. During thaw, respiration increased in samples from three PT locations, but remained stable for two locations. Analysis of the shotgun metagenomes showed how the microbial communities and their potential function changed as a function of location and incubation temperature. This indicates a differential response of permafrost microbes based on their origin. These findings have important implications for developing accurate forecasts of microbial community assemblages during thaw in that location should be considered as a strong influencing factor.

The occupation history of the longest-dwelling Adélie penguin colony reflects Holocene climatic and environmental changes in the Ross Sea, Antarctica - Gao, Yuesong; Salvatore, Maria Cristina; Xu, Qibin; Yang, Lianjiao; Sun, Liguang; Xie, Zhouqing; Baroni, Carlo (Quaternary Science Reviews, 2022)
As a result of climate changes, penguins are predicted to be at risk of losing their breeding habitats. Changes in penguin colony distribution suggest that some colonies have withstood environmental changes better than others, serving as initial post-glacial settlements or refuges in adverse climatic conditions. Here we have synthesized over 200 dates (including 91 new dates) of penguin remains and of guano in 107 ornithogenic profiles from abandoned nests on Inexpressible Island, one of the longest persisting Adélie penguin colonies in Antarctica, to investigate the dynamics of population size and the role of this island in the ecological history of this species. The results indicate that, following the retreat of Ross Ice Shelf, the Adélies first colonized this island at ∼8.6 kyr BP, documenting the earliest known breeding site in the Ross Sea since deglaciation. During ∼7-3 kyr BP the reconstructed population on Inexpressible Island was generally consistent with the change in pack ice, reaching relative peaks at 5.5–5.0 and 4.0–3.5 kyr BP. After brief decline at 3.5–3.0 kyr, substantial enlargement of the penguin colony occurred between 3.0 and 1.5 kyr BP, attributed to the immigration from the abandoned colonies along the Scott Coast. During this time, the persistent efficiency of Terra Nova Bay polynya offered conditions favourable to the expansion of the penguin population on Inexpressible Island, which probably represented a refuge area under increased coastal sea-ice. This longest-dwelling penguin colony may provide a valuable refuge for the Adélie penguin if the recurrent Terra Nova Bay polynya persists under future climatic and environmental changes, as occurred in the past.

Optimization of the LLNL/CAMS gas-accepting ion source and 1 MV compact AMS for natural abundance radiocarbon analysis of CO2 - Broek, Taylor A. B.; Moreland, Kimber C.; Ognibene, Ted J.; McFarlane, Karis J.; Brown, Thomas A. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2022)
The Lawrence Livermore National Laboratory – Center for Accelerator Mass Spectrometry (LLNL/CAMS) 1 MV AMS system was converted from a biomedical AMS instrument to a natural abundance 14C spectrometer. The system is equipped with a gas-accepting hybrid ion source capable of measuring both solid (graphite) and gaseous (CO2) samples. Here we describe a series of experiments intended to establish and optimize 14CO2 measurement capabilities at natural abundance levels. A maximum instantaneous ionization efficiency of 8 % was achieved with 3 % CO2 in helium at a flow rate of approximately 220 µL/min (3.5 µg C/min). For modern materials (e.g., OX I) we measured an average of 240 ± 50 14C counts/µg C, equivalent to a total system efficiency of approximately 3 %. Experimental CO2 samples with F14C values ranging from 0.20 to 1.05 measured as both graphite and directly as CO2 gas produced equivalent values with an average offset of < 2σ.
Keywords: Accelerator mass spectrometry; CO; Gas-accepting ion source; radiocarbon

Over a third of groundwater in USA public-supply aquifers is Anthropocene-age and susceptible to surface contamination - Jurgens, Bryant C.; Faulkner, Kirsten; McMahon, Peter B.; Hunt, Andrew G.; Casile, Gerolamo; Young, Megan B.; Belitz, Kenneth (Communications Earth & Environment, 2022)
The distribution of groundwater age is useful for evaluating the susceptibility and sustainability of groundwater resources. Here, we compute the aquifer-scale cumulative distribution function to characterize the age distribution for 21 Principal Aquifers that account for ~80% of public-supply pumping in the United States. The aquifer-scale cumulative distribution function for each Principal Aquifer was derived from an ensemble of modeled age distributions (~60 samples per aquifer) based on multiple tracers: tritium, tritiogenic helium-3, sulfur hexafluoride, chlorofluorocarbons, carbon-14, and radiogenic helium-4. Nationally, the groundwater is 38% Anthropocene (since 1953), 34% Holocene (75 – 11,800 years ago), and 28% Pleistocene (>11,800 years ago). The Anthropocene fraction ranges from <5 to 100%, indicating a wide range in susceptibility to land-surface contamination. The Pleistocene fraction of groundwater exceeds 50% in 7 eastern aquifers that are predominately confined. The Holocene fraction of groundwater exceeds 50% in 5 western aquifers that are predominately unconfined. The sustainability of pumping from these Principal Aquifers depends on rates of recharge and release of groundwater stored in fine-grained layers.
Keywords: Environmental impact; hydrology; Sustainability

Radiocarbon dating of the historic Emperor’s Beech from Muncel, Baia de Aries, Romania - Patrut, Adrian; Bocos-Bintintan, Victor; Patrut, Roxana T.; Partila, Doriana; Ratiu, Ileana-Andreea; Rakosy, Laszlo; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of the historic Emperor’s Beech (Fagul Împăratului) from Muncel, Baia de Arieş, Romania. Two wood samples were collected from the large tree, out of which four segments were extracted and analysed by AMS radiocarbon. The oldest dated sample segment had a radiocarbon date of 233 ± 18 BP, which corresponds to a calibrated age of 365 ± 5 years. This value suggests an age of 420 ± 20 years for the Emperor’s Beech. Thus, the historic beech started growing around the year 1600.
Publisher: Babes-Bolyai University

Radiocarbon investigation of two large African baobabs from Kizimkazi, Zanzibar, Tanzania - Patrut, Adrian; Patrut, Roxana T.; Rakosy, Laszlo; Ratiu, Ileana-Andreea; Bodis, Jenő; Nassor, Nassor Mahmoud; von Reden, Karl F. (Studia Universitatis Babes-Bolyai Chemia, 2022)
The article reports the AMS (accelerator mass spectrometry) radiocarbon dating results of Kizimkazi Big tree and Kizimkazi II baobab, two large African baobabs from Zanzibar, Tanzania. Unfortunately, both baobabs toppled and died in 2018 and 2020, during violent storms. The investigation of the two baobabs evinced that the first of them, which was also the biggest tree of Tanzania, consisted of 5 stems, out of which 2 were false ones, and had a closed ring-shaped structure. The second baobab was composed of 4 fused stems and had a cluster structure. Several wood samples were collected from the two baobabs. Seven segments were extracted from the samples and dated by radiocarbon. The oldest segment from Kizimkazi Big tree had a radiocarbon date of 312 ± 18 BP, corresponding to a calibrated age of 380 ± 10 calendar years. According to dating results, the Kizimkazi Big tree died at the age of 400 ± 25 years. The oldest segment from Kizimkazi II baobab had a radiocarbon date of 137 ± 17 BP, corresponding to a calibrated age of 190 ± 10 calendar years. This value indicates that the Kizimkazi II baobab was 250 ± 25 years old when it died.

RADIOCARBON INVESTIGATION OF TWO OLD ELMS FROM ROMANIA - Patrut, A; Patrut, RT; Bocos-Bintintan, V; Ratiu, IA; Rakosy, L; Zdrob, G; Vanca, E; von Reden, KF (STUDIA UNIVERSITATIS BABES-BOLYAI CHEMIA, 2022)
The paper reports the AMS (accelerator mass spectrometry) radiocarbon investigation results of two superlative elms from Romana, the very large field elm of Calafat, with a wood volume of 85 m(3), and the wych elm of Sadova. Two wood samples were extracted from each elm and were analysed by AMS radiocarbon. The oldest dated sample from the elm of Calafat had a radiocarbon date of 350 +/- 19 BP, which corresponds to a calibrated age of 415 +/- 25 years, while the oldest sample from the elm of Sadova had a radiocarbon date of 188 +/- 24 BP, corresponding to a calibrated age of 260 +/- 25 years. These values indicate high ages for the two elms, namely 430 +/- 25 years or the elm of Calafat and 400 +/- 25 years for the elm of Sadova.
Keywords: Age; Age determination; AMS radiocarbon dating; BAOBABS; carbon; dendrochronology; PEDUNCULATE OAK; PERFORMANCE; Romania; Trees; Ulmus glabra; Ulmus minor

Radiocarbon measurement of CO2 from carbonate minerals using a hybrid gas ion source with an open split interface - Longworth, Brett E.; Burton, Joshua R.; Pendleton, Simon L.; Moser, Sydney D.; Roberts, Mark L.; Kurz, Mark D. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2022)
We have developed a method for measuring radiocarbon in carbonate minerals as CO2 gas via a NEC MCSNICS hybrid sputter gas ion source (HGIS). The method uses helium as a carrier gas to displace CO2 from sample vials to an open split, where a glass capillary samples the mixture for delivery directly to the HGIS. This method skips the gas transfer and quantification steps used in a closed inlet HGIS system, simplifying sample measurement. Samples larger than 8 mg carbonate can be measured. Results from measurements of consensus standards (TIRI I, IAEA C2, and an internal modern shell standard), and samples from a marine core (F14C = 0.4–1.15) show that the method agrees well with traditional AMS measurement of the same samples as graphite, and that the 1σ uncertainty is about 1%. We discuss advantages and disadvantages of continuous flow sample introduction, and the effect of reduced precision on calibrated age-depth models produced using gas-source data.
Keywords: Carbonate; Hybrid gas ion source; radiocarbon

Relative sea-level change in South Florida during the past ~5000 years - Khan, Nicole S.; Ashe, Erica; Moyer, Ryan P.; Kemp, Andrew C.; Engelhart, Simon E.; Brain, Matthew J.; Toth, Lauren T.; Chappel, Amanda; Christie, Margaret; Kopp, Robert E.; Horton, Benjamin P. (Global and Planetary Change, 2022)
A paucity of detailed relative sea-level (RSL) reconstructions from low latitudes hinders efforts to understand the global, regional, and local processes that cause RSL change. We reconstruct RSL change during the past ~5 ka using cores of mangrove peat at two sites (Snipe Key and Swan Key) in the Florida Keys. Remote sensing and field surveys established the relationship between peat-forming mangroves and tidal elevation in South Florida. Core chronologies are developed from age-depth models applied to 72 radiocarbon dates (39 mangrove wood macrofossils and 33 fine-fraction bulk peat). RSL rose 3.7 m at Snipe Key and 5.0 m at Swan Key in the past 5 ka, with both sites recording the fastest century-scale rate of RSL rise since ~1900 CE (~2.1 mm/a). We demonstrate that it is feasible to produce near-continuous reconstructions of RSL from mangrove peat in regions with a microtidal regime and accommodation space created by millennial-scale RSL rise. Decomposition of RSL trends from a network of reconstructions across South Florida using a spatio-temporal model suggests that Snipe Key was representative of regional RSL trends, but Swan Key was influenced by an additional local-scale process acting over at least the past five millennia. Geotechnical analysis of modern and buried mangrove peat indicates that sediment compaction is not the local-scale process responsible for the exaggerated RSL rise at Swan Key. The substantial difference in RSL between two nearby sites highlights the critical need for within-region replication of RSL reconstructions to avoid misattribution of sea-level trends, which could also have implications for geophysical modeling studies using RSL data for model tuning and validation.
Keywords: Holocene; mangrove; Proxy reconstruction; Reproducibility; sea level

Relative sea-level data preclude major late Holocene ice-mass change in Pine Island Bay - Braddock, Scott; Hall, Brenda L.; Johnson, Joanne S.; Balco, Greg; Spoth, Meghan; Whitehouse, Pippa L.; Campbell, Seth; Goehring, Brent M.; Rood, Dylan H.; Woodward, John (Nature Geoscience, 2022)
The rapidly retreating Thwaites and Pine Island glaciers together dominate present-day ice loss from the West Antarctic Ice Sheet and are implicated in runaway deglaciation scenarios. Knowledge of whether these glaciers were substantially smaller in the mid-Holocene and subsequently recovered to their present extents is important for assessing whether current ice recession is irreversible. Here we reconstruct relative sea-level change from radiocarbon-dated raised beaches at sites immediately seawards of these glaciers, allowing us to examine the response of the earth to loading and unloading of ice in the Amundsen Sea region. We find that relative sea level fell steadily over the past 5.5 kyr without rate changes that would characterize large-scale ice re-expansion. Moreover, current bedrock uplift rates are an order of magnitude greater than the rate of long-term relative sea-level fall, suggesting a change in regional crustal unloading and implying that the present deglaciation may be unprecedented in the past 5.5 kyr. While we cannot preclude minor grounding-line fluctuations, our data are explained most easily by early Holocene deglaciation followed by relatively stable ice positions until recent times and imply that Thwaites and Pine Island glaciers have not been substantially smaller than present during the past 5.5 kyr.

Review article: Existing and potential evidence for Holocene grounding line retreat and readvance in Antarctica - Johnson, Joanne S.; Venturelli, Ryan A.; Balco, Greg; Allen, Claire S.; Braddock, Scott; Campbell, Seth; Goehring, Brent M.; Hall, Brenda L.; Neff, Peter D.; Nichols, Keir A.; Rood, Dylan H.; Thomas, Elizabeth R.; et al. (The Cryosphere, 2022)
Widespread existing geological records from above the modern ice sheet surface and outboard of the current ice margin show that the Antarctic Ice Sheet (AIS) was much more extensive at the Last Glacial Maximum (∼20 ka) than at present. However, whether it was ever smaller than present during the last few millennia, and (if so) by how much, is known only for a few locations because direct evidence lies within or beneath the ice sheet, which is challenging to access. Here, we describe how retreat and readvance (henceforth “readvance”) of AIS grounding lines during the Holocene could be detected and quantified using subglacial bedrock, subglacial sediments, marine sediment cores, relative sea-level (RSL) records, geodetic observations, radar data, and ice cores. Of these, only subglacial bedrock and subglacial sediments can provide direct evidence for readvance. Marine archives are of limited utility because readvance commonly covers evidence of earlier retreat. Nevertheless, stratigraphic transitions documenting change in environment may provide support for direct evidence from subglacial records, as can the presence of transgressions in RSL records, and isostatic subsidence. With independent age control, ice structure revealed by radar can be used to infer past changes in ice flow and geometry, and therefore potential readvance. Since ice cores capture changes in surface mass balance, elevation, and atmospheric and oceanic circulation that are known to drive grounding line migration, they also have potential for identifying readvance. A multidisciplinary approach is likely to provide the strongest evidence for or against a smaller-than-present AIS in the Holocene.
Publisher: Copernicus GmbH

Sediment Accumulation and Carbon Burial in Four Hadal Trench Systems - Oguri, Kazumasa; Masqué, Pere; Zabel, Matthias; Stewart, Heather A.; MacKinnon, Gillian; Rowden, Ashley A.; Berg, Peter; Wenzhöfer, Frank; Glud, Ronnie N. (Journal of Geophysical Research: Biogeosciences, 2022)
Hadal trenches are considered to act as depocenters for organic material, although pathways for the material transport and deposition rates are poorly constrained. Here we assess focusing, deposition and accumulation of material and organic carbon in four hadal trench systems underlying different surface ocean productivities; the eutrophic Atacama and Kuril-Kamchatka trenches, the mesotrophic Kermadec trench and the oligotrophic Mariana Trench. The study is based on the distributions of naturally occurring 210Pbex, 137Cs and total organic carbon from recovered sediment cores and by applying previously quantified benthic mineralization rates. Periods of steady deposition and discreet mass-wasting deposits were identified from the profiles and the latter were associated with historic recorded seismic events in the respective regions. During periods without mass wasting, the estimated focusing factors along trench axes were elevated, suggesting more or less continuous downslope focusing of material towards the interior of the trenches. The estimated organic carbon deposition rates during these periods exhibited extensive site-specific variability, but were generally similar to values encountered at much shallower settings such as continental slopes and margins. Organic carbon deposition rates during periods of steady deposition were not mirrored by surface ocean productivity, but appeared confounded by local bathymetry. The inclusion of deposition mediated by mass-wasting events enhanced the sediment and organic carbon accumulations for the past ∼150 years by up to a factor of ∼4. Thus, due to intensified downslope material focusing and infrequent mass-wasting events, hadal trenches are important sites for deposition and sequestration of organic carbon in the deep sea.
e2022JG006814 2022JG006814
Keywords: focusing factor; Hadal trench; mass accumulation rate; mass-wasting event; organic carbon deposition rate; radionuclides

Understanding the Water Resources of a Mountain‐block Aquifer: Tucson Mountains, Arizona - Eastoe, Christopher J.; Beisner, Kimberly R. (Journal of Contemporary Water Research & Education, 2022)
Water resources are limited in arid locations such as Tucson Basin. Residential development in the Tucson Mountains to the west of Tucson, Arizona, is limited by groundwater resources. Groundwater samples were collected from fractured bedrock and alluvial aquifers surrounding the Tucson Mountains to assess water quality and recharge history through measurement of stable O, H, and S isotopes; tritium; and 14C. Most groundwater is a mixture of different ages but is commonly several thousand years old. A few sampling locations indicated a component of water recharged after the above‐ground nuclear testing of the mid 1950s, and these sites may represent locations near where the aquifer receives present‐day recharge. The Tucson Mountains also host sulfide deposits associated with fractures and replacement zones; these locally contribute to poor‐quality groundwater. Projections of future climate predict intensifying drought in southwestern North America. In the study area, a combination of strategies such as rainwater harvesting, exploitation of renewable water, and low groundwater use could be used for sustainable use of the groundwater supply.

Use of δ18Oatm in dating a Tibetan ice core record of Holocene/Late Glacial climate - Thompson, Lonnie G.; Severinghaus, Jeffrey P.; Yao, Tandong; Davis, Mary E.; Mosley-Thompson, Ellen; Beaudon, Emilie; Sierra-Hernández, M. Roxana; Porter, Stacy E. (Proceedings of the National Academy of Sciences, 2022)
Ice cores from the northwestern Tibetan Plateau (NWTP) contain long records of regional climate variability, but refrozen meltwater and dust in these cores has hampered development of robust timescales. Here, we introduce an approach to dating the ice via the isotopic composition of atmospheric O2 in air bubbles (δ18Oatm), along with annual layer counting and radiocarbon dating. We provide a robust chronology for water isotope records (δ18Oice and d-excess) from three ice cores from the Guliya ice cap in the NWTP. The measurement of δ18Oatm, although common in polar ice core timescales, has rarely been used on ice cores from low-latitude, high-altitude glaciers due to (1) low air pressure, (2) the common presence of refrozen melt that adds dissolved gases and reduces the amount of air available for analysis, and (3) the respiratory consumption of molecular oxygen (O2) by micro-organisms in the ice, which fractionates the δ18O of O2 from the atmospheric value. Here, we make corrections for melt and respiration to address these complications. The resulting records of water isotopes from the Guliya ice cores reveal climatic variations over the last 15,000 y, the timings of which correspond to those observed in independently dated lake and speleothem records and confirm that the Guliya ice cap existed before the Holocene. The millennial-scale drivers of δ18Oice are complex and temporally variable; however, Guliya δ18Oice values since the mid-20th century are the highest since the beginning of the Holocene and have increased with regional air temperature.
Publisher: Proceedings of the National Academy of Sciences

Centennial-scale age offsets of plant wax n-alkanes in Adirondack lake sediments - Freimuth, Erika J.; Diefendorf, Aaron F.; Lowell, Thomas V.; Schartman, Anna K.; Landis, Joshua D.; Stewart, Alexander K.; Bates, Benjamin R. (Geochimica et Cosmochimica Acta, 2021)

Climate control on terrestrial biospheric carbon turnover - Eglinton, Timothy I.; Galy, Valier V.; Hemingway, Jordon D.; Feng, Xiaojuan; Bao, Hongyan; Blattmann, Thomas M.; Dickens, Angela F.; Gies, Hannah; Giosan, Liviu; Haghipour, Negar; Hou, Pengfei; Lupker, Maarten; et al. (Proceedings of the National Academy of Sciences, 2021)
Terrestrial vegetation and soils hold three times more carbon than the atmosphere. Much debate concerns how anthropogenic activity will perturb these surface reservoirs, potentially exacerbating ongoing changes to the climate system. Uncertainties specifically persist in extrapolating point-source observations to ecosystem-scale budgets and fluxes, which require consideration of vertical and lateral processes on multiple temporal and spatial scales. To explore controls on organic carbon (OC) turnover at the river basin scale, we present radiocarbon (C-14) ages on two groups of molecular tracers of plant-derived carbon-leaf-wax lipids and lignin phenols-from a globally distributed suite of rivers. We find significant negative relationships between the C-14 age of these biomarkers and mean annual temperature and precipitation. Moreover, riverine biospheric-carbon ages scale proportionally with basin-wide soil carbon turnover times and soil C-14 ages, implicating OC cycling within soils as a primary control on exported biomarker ages and revealing a broad distribution of soil OC reactivities. The ubiquitous occurrence of a long-lived soil OC pool suggests soil OC is globally vulnerable to perturbations by future temperature and precipitation increase. Scaling of riverine biospheric-carbon ages with soil OC turnover shows the former can constrain the sensitivity of carbon dynamics to environmental controls on broad spatial scales. Extracting this information from fluvially dominated sedimentary sequences may inform past variations in soil OC turnover in response to anthropogenic and/or climate perturbations. In turn, monitoring riverine OC composition may help detect future climate-change-induced perturbations of soil OC turnover and stocks.
Keywords: Carbon cycle; carbon turnover times; fluvial carbon; plant biomarkers; radiocarbon

CTD profiles and discrete water-column measurements collected off California and Oregon during NOAA cruise SH-18-12 (USGS field activity 2018-663-FA) from October to November 2018 (ver. 3.0, July 2022) - Prouty, Nancy G; Baker, Miranda C (U.S. Geological Survey, 2021)
Various water column variables, including salinity, dissolved inorganic nutrients, pH, total alkalinity, dissolved inorganic carbon, radio-carbon isotopes were measured in samples collected using a Niskin-bottle rosette at selected depths from sites offshore of California and Oregon from October to November 2018 during NOAA cruise SH-18-12 on the R/V Bell M. Shimada (USGS field activity 2018-663-FA). CTD (Conductivity Temperature Depth) data were also collected at each depth that a Niskin-bottle sample was collected and are presented along with the water sample data. This data release supersedes version 2.0, published in September 2021 at https://doi.org/10.5066/P99DIQZ5. Versioning details are documented in the accompanying VersionHistory_P99MJ096.txt file.
Keywords: Earth and related environmental sciences; Geochemistry

Evidence of humans in North America during the Last Glacial Maximum - Bennett, Matthew R.; Bustos, David; Pigati, Jeffrey S.; Springer, Kathleen B.; Urban, Thomas M.; Holliday, Vance T.; Reynolds, Sally C.; Budka, Marcin; Honke, Jeffrey S.; Hudson, Adam M.; Fenerty, Brendan; Connelly, Clare; et al. (Science, 2021)
Archaeologists and researchers in allied fields have long sought to understand human colonization of North America. Questions remain about when and how people migrated, where they originated, and how their arrival affected the established fauna and landscape. Here, we present evidence from excavated surfaces in White Sands National Park (New Mexico, United States), where multiple in situ human footprints are stratigraphically constrained and bracketed by seed layers that yield calibrated radiocarbon ages between ~23 and 21 thousand years ago. These findings confirm the presence of humans in North America during the Last Glacial Maximum, adding evidence to the antiquity of human colonization of the Americas and providing a temporal range extension for the coexistence of early inhabitants and Pleistocene megafauna.
Publisher: American Association for the Advancement of Science

Geomorphic expression and slip rate of the Fairweather fault, southeast Alaska, and evidence for predecessors of the 1958 rupture - Witter, Robert C.; Bender, Adrian M.; Scharer, Katherine M.; DuRoss, Christopher B.; Haeussler, Peter J.; Lease, Richard O. (Geosphere, 2021)
Active traces of the southern Fairweather fault were revealed by light detection and ranging (lidar) and show evidence for transpressional deformation between North America and the Yakutat block in southeast Alaska. We map the Holocene geomorphic expression of tectonic deformation along the southern 30 km of the Fairweather fault, which ruptured in the 1958 moment magnitude 7.8 earthquake. Digital maps of surficial geology, geomorphology, and active faults illustrate both strike-slip and dip-slip deformation styles within a 10°–30° double restraining bend where the southern Fairweather fault steps offshore to the Queen Charlotte fault. We measure offset landforms along the fault and calibrate legacy 14C data to reassess the rate of Holocene strike-slip motion (≥49 mm/yr), which corroborates published estimates that place most of the plate boundary motion on the Fairweather fault. Our slip-rate estimates allow a component of oblique-reverse motion to be accommodated by contractional structures west of the Fairweather fault consistent with geodetic block models. Stratigraphic and structural relations in hand-dug excavations across two active fault strands provide an incomplete paleoseismic record including evidence for up to six surface ruptures in the past 5600 years, and at least two to four events in the past 810 years. The incomplete record suggests an earthquake recurrence interval of ≥270 years—much longer than intervals <100 years implied by published slip rates and expected earthquake displacements. Our paleoseismic observations and map of active traces of the southern Fairweather fault illustrate the complexity of transpressional deformation and seismic potential along one of Earth's fastest strike-slip plate boundaries.

Molluscan aminostratigraphy of the US Mid-Atlantic Quaternary coastal system: Implications for onshore-offshore correlation, paleochannel and barrier island evolution, and local late Quaternary sea-level history - Wehmiller, John F.; Brothers, Laura L.; Ramsey, Kelvin W.; Foster, David S.; Mattheus, C.R.; Hein, Christopher J.; Shawler, Justin L. (Quaternary Geochronology, 2021)
The Quaternary record of the US Mid-Atlantic coastal system includes onshore emergent late Pleistocene shoreline deposits, offshore inner shelf and barrier island units, and paleovalleys formed during multiple glacial stage sea-level lowstands. The geochronology of this coastal system is based on uranium series, radiocarbon, amino acid racemization (AAR), and optically stimulated luminescence (OSL) methods. We report over 600 mollusk AAR results from 93 sites between northeastern North Carolina and the central New Jersey shelf, representing samples from both onshore cores or outcrops, sub-barrier and offshore cores, and transported shells from barrier island beaches. AAR age estimates are constrained by paired C-14 analyses on specific shells and associated U-series coral ages from onshore sites. AAR data from offshore cores are interpreted in the context of detailed seismic stratigraphy. The distribution of Pleistocene-age shells on the island beaches is linked to the distribution of inner shelf or sub-barrier source units. Age mixing over a range of time-scales (similar to 1 ka to similar to 100 ka) is identified by AAR results from onshore, beach, and shelf collections, often contributing insights into the processes forming individual barrier islands. The regional aminostratigraphic framework identifies a widespread late Pleistocene (Marine Isotope Stage 5) aminozone, with isolated records of middle and early Pleistocene deposition. AAR results provide age estimates for the timing of formation of the three major paleochannels that underlie the Delmarva Peninsula: Persimmon Point paleochannel >= 800 ka; Exmore paleochannel similar to 400-500 ka (MIS 12); and Eastville paleochannel > 125 ka (MIS 6). The results demonstrate the value of synthesizing abundant AAR chronologic data across various coastal environments, integrating multiple distinct geologic studies. The ages and elevations of the Quaternary units are important for current hypotheses about relative sea level history and crustal dynamics in the region, which was likely influenced by the Laurentide ice sheet, the margin just similar to 400 km to the north.

A NEW RAMPED PYROXIDATION/COMBUSTION FACILITY AT 14 CHRONO, BELFAST: SETUP DESCRIPTION AND INITIAL RESULTS - Keaveney, Evelyn M; Barrett, Gerard T; Allen, Kerry; Reimer, Paula J (Radiocarbon, 2021)

The Preservation of Climate‐Driven Landslide Dams in Western Oregon - Struble, William T.; Roering, Joshua J.; Burns, William J.; Calhoun, Nancy C.; Wetherell, Logan R.; Black, Bryan A. (Journal of Geophysical Research: Earth Surface, 2021)
Bedrock landsliding, including the formation of landslide dams, is a predominant geomorphic process in steep landscapes. Clarifying the importance of hydrologic and seismic mechanisms for triggering deep-seated landslides remains an ongoing effort, and formulation of geomorphic metrics that predict dam preservation is crucial for quantifying secondary landslide hazards. Here, we identify >200 landslide-dammed lakes in western Oregon and utilize dendrochronology and enhanced C-14 dating ("wiggle matching") of "ghost forests" to establish slope failure timing at 20 sites. Our dated landslide dataset reveals bedrock landsliding has been common since the last Cascadia Subduction Zone earthquake in January 1700 AD. Our study does not reveal landslides that date to 1700 AD. Rather, we observe temporal clustering of at least four landslides in the winter of 1889/1890 AD, coincident with a series of atmospheric rivers that generated one of the largest regionally recorded floods. We use topographic and field analyses to assess the relation between dam preservation and topographic characteristics of the impounded valleys. In contrast to previous studies, we do not observe systematic scaling between dam size and upstream drainage area, though dam stability indices for our sites correspond with "stable" dams elsewhere. Notably, we observe that dams are preferentially preserved at drainage areas of similar to 1.5 to 13 km(2) and valley widths of similar to 25 to 80 m, which may reflect the reduced downstream influence of debris flows and the accumulation of mature conifer trees upstream from landslide-dammed lake outlets. We suggest that wood accumulation upstream of landslide dams tempers large stream discharges, thus inhibiting dam incision.

Radiocarbon dates, charcoal, and polycyclic aromatic hydrocarbon (PAH) data from Great Dismal Swamp Sites GDS-519 and GDS-520 - Willard, Debra A; Jones, Miriam C; Vachula, Richard S; Balascio, Nicholas L; Canuel, Elizabeth A (U.S. Geological Survey, 2021)
Sediment cores were collected in Great Dismal Swamp National Wildlife Refuge in November, 2017 to advance understanding of climate- and land-management driven changes in vegetation, hydrology, and fire regimes. Radiocarbon dates were obtained from samples in two cores (GDS-519-3-21-2017 and GDS-520-3-21-2017) to generate age models for the cores. Bulk sediment samples, charcoal, plant macrofossils, and pollen residue were selected at the USGS in Reston, Virginia and submitted to Beta Analytic, Inc. and the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) laboratories for radiocarbon dating. Those laboratories provided both radiocarbon ages and stable carbon isotope (delta 13C) results, which can be used to generate calibrated ages. Bulk density was measured for each core at the USGS in Reston, Virginia. Cores were sectioned at 1-cm increments. One cubic centimeter of wet sediment was extracted from each 1-cm increment downcore and weighed. Samples were subsequently dried at 100 degrees C for at least 24 hours to obtain dry weights, and bulk density was calculated by dividing original 1-cc volume by the dry weight. Polycyclic aromatic hydrocarbons (PAHs) and sedimentary charcoal were analyzed at the Virginia Institute of Marine Science at Gloucester Point, Virginia. PAH analysis began with freeze-drying of samples and extraction of their lipid contents using a Dionex 350 Accelerated Solvent Extractor (9:1; dicholoromethane:methanol). Total lipid extracts were separated into three fractions using silica gel columns and eluents of increasing polarity (F1: hexane, F2: 25% toluene in hexane, F3: methanol). Combined F1 and F2 fractions were analyzed to quantify PAHs using an Agilent 7890A gas chromatograph coupled with a 5975C mass selective detector (GC-MSD). The GC was equipped with a DB-5MS capillary column (30 m length; 320 micrometres outer diameter; 0.25 micrometres film thickness), which was heated using the following temperature program: 16 degrees C/minute to 150 degrees C and 5 degrees C/minute to 300 degrees C. Flow rate was 1.1 mL/minute. Individual PAH abundances were quantified using select ion monitoring mode (SIM) and relative to an external calibration curve constructed with a PAH calibration standard (Sigma-Aldrich CRM47940). Sixteen PAHs were quantified: naphthalene (Na), acenaphthylene (Ayl), acenaphthene (Ace), anthracene (An), phenanthrene (Phe), fluoranthene (Fla), pyrene (Py), benz[a]anthracene (Ba), chrysene (Ch), retene (Ret), benzo[k]fluoranthene (BkF), benzo[a]pyrene (BaP), benzo[b]fluoranthene (BbF), benzo[g,h,i]perylene (Bghi), dibenzo[a,h]anthracene (DiAn), and ideno[1,2,3-cd]pyrene (IP). PAH accumulation rates were quantified using the dry sediment concentration of PAHs and the age-depth model of the sediment cores. Sedimentary charcoal analysis followed a modified version of standard methodologies for isolating and identifying sedimentary charcoal particles. Dried sediment samples were weighed and then subjected to a light chemical treatment (1:1, by volume mixture of 1M sodium hexametaphosphate solution and 2% sodium hypochlorite solution) for 24 hours, in accordance with standard methods (Vachula et al., 2019, 2018). Samples were washed over two nested sieves (63 micrometre and 125 micrometre mesh sizes) to isolate an intermediate size fraction (63-125 micrometres), in which charcoal particles were enumerated using a dissection microscope and gridded petri dishes. Charcoal accumulation rates were quantified using the numeric concentration of charcoal particles, the bulk density of the sediments, and the age-depth model of the sediment cores. References Vachula, R.S., Russell, J.M., Huang, Y. and Richter, N., 2018. Assessing the spatial fidelity of sedimentary charcoal size fractions as fire history proxies with a high-resolution sediment record and historical data. Palaeogeography, Palaeoclimatology, Palaeoecology, 508, pp.166-175. Vachula, R.S., Russell, J.M. and Huang, Y., 2019. Climate exceeded human management as the dominant control of fire at the regional scale in California's Sierra Nevada. Environmental Research Letters, 14(10), p.104011.
Keywords: Climatology

Revisiting the marine reservoir age in Baja California continental margin sediments using 14C and 210Pb dating - Treinen-Crespo, Christina; Barbara, Loïc; Villaescusa, Julio A.; Schmidt, Sabine; Pearson, Ann; Carriquiry, José D. (Quaternary Geochronology, 2021)
Knowledge of the Marine Reservoir Effect (MRE) correction is fundamental in palaeoceanographic research to establish an accurate age-depth model for marine sedimentary records. However, during the last decades different MRE corrections have been applied in inconsistent ways for the same locality and same sediment cores, at Soledad Basin, Baja California, Mexico, creating confusion about the proper correction value of the marine reservoir effect (Delta R) to be applied. In contrast with the empirical approach previously used for assessing the Delta R value in Soledad Basin, in this study we applied an analytical approach based on the concurrent application of AMS-14C and 210Pbxs dating techniques made on sedimentary total organic carbon and foraminifera to determine new regional Delta R values from newly collected sediment cores from this site. Our results from Soledad Basin show a Delta R of 206 +/- 32 years for foraminifera and 706 +/- 42 years for organic carbon. Modeled ages using these results, and compared with those previously applied for the basin, highlight the relevance of the correct use of the local reservoir age as it can generate an offset of approximately 150 years if the other published Delta R were used. These differences can shift core chronologies by several decades and thus yield significant errors in palaeoceanographic reconstructions, which will be important to remedy in future work.

The triple argon isotope composition of groundwater on ten-thousand-year timescales - Seltzer, Alan M.; Krantz, John A.; Ng, Jessica; Danskin, Wesley R.; Bekaert, David V.; Barry, Peter H.; Kimbrough, David L.; Kulongoski, Justin T.; Severinghaus, Jeffrey P. (Chemical Geology, 2021)
Understanding the age and movement of groundwater is important for predicting the vulnerability of wells to contamination, constraining flow models that inform sustainable groundwater management, and interpreting geochemical signals that reflect past climate. Due to both the ubiquity of groundwater with order ten-thousand-year residence times and its importance for climate reconstruction of the last glacial period, there is a strong need for improving geochemical dating tools on this timescale. Whereas 14C of dissolved inorganic carbon and dissolved 4He are common age tracers for Late Pleistocene groundwater, each is limited by systematic uncertainties related to aquifer composition and lithology, and the extent of water-rock interaction. In principle, radiogenic 40Ar in groundwater acquired from decay of 40K in aquifer minerals should be insensitive to some processes that impact 14C and 4He and thus represent a useful, complementary age tracer. In practice, however, detection of significant radiogenic 40Ar signals in groundwater has been limited to a small number of studies of extremely old groundwater (>100 ka). Here we present the first high-precision (<1‰) measurements of triple Ar isotopes (40Ar, 38Ar, 36Ar) in groundwater. We introduce a model that distinguishes radiogenic 40Ar from atmospheric 40Ar by using the non-radiogenic Ar isotopes (36Ar, 38Ar) to correct for mass-dependent fractionation. Using this model, we investigate variability in radiogenic 40Ar excess (Δ40Ar) across 58 groundwater samples collected from 36 wells throughout California (USA). We find that Δ40Ar ranges from ~0‰ (the expected minimum value) to +4.2‰ across three study areas near Fresno, San Diego, and the western Mojave Desert. Based on measurements from a network of 23 scientific monitoring wells in San Diego, we find evidence for a strong dependence of Δ40Ar on aquifer lithology. We suggest that Δ40Ar is fundamentally controlled by the weathering of old K-bearing minerals and thus reflects both the degree of groundwater-rock interaction, which is related to groundwater age, and the integrated flow through different geological formations. Future studies of Late Pleistocene groundwater may benefit from high-precision triple Ar isotope measurements as a new tool to better interpret 14C- and 4He-based constraints on groundwater age and flow.
Keywords: groundwater; Groundwater dating; Isotope geochemistry; Noble gas

The Zealandia Switch: Ice age climate shifts viewed from Southern Hemisphere moraines - Denton, George H.; Putnam, Aaron E.; Russell, Joellen L.; Barrell, David J. A.; Schaefer, Joerg M.; Kaplan, Michael R.; Strand, Peter D. (Quaternary Science Reviews, 2021)
Two fundamental questions about the ice-age climate system await satisfactory resolution. First, if summer solar radiation intensity truly controls the orbital signature of the last glacial cycle, then why were major climatic shifts, including the last termination, globally synchronous? Second, what caused the millennial-scale climate oscillations superimposed on this cycle? We address these questions from a Southern Hemisphere perspective focused on mid-latitude mountain ice fields. We put particular emphasis on the last glacial termination, which involved both orbital-scale and millennial-scale climate elements and has generally well-resolved chronological control. Sustained retreat of mountain glaciers, documented by detailed mapping and chronology of glacial landforms in the Southern Alps and southern Andes, marked the termination of the last ice age, beginning ∼18 kyrs ago and involved a change from glacial to near-interglacial atmospheric temperature within a millennium or two. A rapid poleward shift of the Subtropical Front, delineating the northern margin of the Southern Ocean, ∼18 kyrs ago implies a concurrent poleward shift of the austral westerlies and leads us to hypothesize a southern origin for the dominant phase of the last glacial termination. Together with interhemispheric paleoclimate records and with results of coupled ocean-atmosphere climate modeling, these findings suggest a big, fast, and global end to the last ice age in which a southern-sourced warming episode linked the hemispheres. We posit that a shift in the Southern Ocean circulation and austral westerly wind system, tied to southern orbital forcing, caused this global warming episode by affecting the tropical heat engine and hence global climate. Central to this hypothesis, dubbed the ‘Zealandia Switch’, is the location of the Australia and Zealandia continents relative to Southern Hemisphere oceanic and atmospheric circulation. Coupled ocean-atmosphere climate modeling shows that the locus of the austral westerlies, whether in a more equatorward position representing a glacial-mode climate or in a poleward-shifted position marking interglacial-mode climate, has profound effects on oceanic and associated atmospheric linkages between the tropical Pacific and the Southern Ocean. Shifts in the austral westerlies have global climatic consequences, especially through resulting changes in the greenhouse gas content of the atmosphere and altered heat flux from the tropical Pacific into the Northern and Southern Hemispheres. We suggest that the last glacial termination was a global warming episode that led to extreme seasonality in northern latitudes by stimulating a flush of meltwater and icebergs into the North Atlantic from adjoining ice sheets. This fresh-water influx resulted in widespread North Atlantic sea ice that caused very cold boreal winters, thus amplifying the annual southward shift of the Intertropical Convergence Zone and the monsoonal rain belts. We further suggest that muted manifestations of the Zealandia Switch mechanism were responsible for smaller, recurring millennial-scale climate oscillations within the last glacial cycle.
Keywords: Climate dynamics; Climate modeling; Cosmogenic isotopes; Geomorphology; Glacial; Glaciation; paleoclimatology; Quaternary; South Pacific Ocean; Southern Hemisphere westerlies; Southern Ocean

Aquifer-Scale Observations of Iron Redox Transformations in Arsenic-Impacted Environments to Predict Future Contamination - Nghiem, Athena A.; Shen, Yating; Stahl, Mason; Sun, Jing; Haque, Ezazul; DeYoung, Beck; Nguyen, Khue N.; Thi Mai, Tran; Trang, Pham Thi Kim; Pham, Hung Viet; Mailloux, Brian; Harvey, Charles F.; et al. (Environmental Science & Technology Letters, 2020)
Iron oxides control the mobility of a host of contaminants in aquifer systems, and the microbial reduction of iron oxides in the subsurface is linked to high levels of arsenic in groundwater that affects greater than 150 million people globally. Paired observations of groundwater and solid-phase aquifer composition are critical to understand spatial and temporal trends in contamination and effectively manage changing water resources, yet field-representative mineralogical data are sparse across redox gradients relevant to arsenic contamination. We characterize iron mineralogy using X-ray absorption spectroscopy across a natural gradient of groundwater arsenic contamination in Vietnam. Hierarchical cluster analysis classifies sediments into meaningful groups delineating weathering and redox changes, diagnostic of depositional history, in this first direct characterization of redox transformations in the field. Notably, these groupings reveal a signature of iron minerals undergoing active reduction before the onset of arsenic contamination in groundwater. Pleistocene sediments undergoing postdepositional reduction may be more extensive than previously recognized due to previous misclassification. By upscaling to similar environments in South and Southeast Asia via multinomial logistic regression modeling, we show that active iron reduction, and therefore susceptibility to future arsenic contamination, is more widely distributed in presumably pristine aquifers than anticipated.
Keywords: BANGLADESH; BENGAL BASIN; groundwater; PLEISTOCENE AQUIFER; POLLUTION; RELEASE; RIVER DELTA; Sediment; TRANSPORT; VIETNAM

Arctic amplification of global warming strengthened by sunlight oxidation of permafrost carbon to CO2 - Bowen, J. C.; Ward, C. P.; Kling, G. W.; Cory, R. M. (Geophysical Research Letters, 2020)
Once thawed, up to 15% of the ∼1,000 Pg of organic carbon (C) in arctic permafrost soils may be oxidized to carbon dioxide (CO2) by 2100, amplifying climate change. However, predictions of this amplification strength ignore the oxidation of permafrost C to CO2 in surface waters (photomineralization). We characterized the wavelength dependence of permafrost dissolved organic carbon (DOC) photomineralization and demonstrate that iron catalyzes photomineralization of old DOC (4,000-6,300 a BP) derived from soil lignin and tannin. Rates of CO2 production from photomineralization of permafrost DOC are two-fold higher than for modern DOC. Given that model predictions of future net loss of ecosystem C from thawing permafrost do not include the loss of CO2 to the atmosphere from DOC photomineralization, current predictions of an average of 208 Pg C loss by 2299 may be too low by ~14%.

Arsenic contamination of Bangladesh aquifers exacerbated by clay layers - Mihajlov, Ivan; Mozumder, M. Rajib H.; Bostick, Benjamín C.; Stute, Martin; Mailloux, Brian J.; Knappett, Peter S. K.; Choudhury, Imtiaz; Ahmed, Kazi Matin; Schlosser, Peter; van Geen, Alexander (Nature Communications, 2020)
Confining clay layers typically protect groundwater aquifers against downward intrusion of contaminants. In the context of groundwater arsenic in Bangladesh, we challenge this notion here by showing that organic carbon drawn from a clay layer into a low-arsenic pre-Holocene (>12 kyr-old) aquifer promotes the reductive dissolution of iron oxides and the release of arsenic. The finding explains a steady rise in arsenic concentrations in a pre-Holocene aquifer below such a clay layer and the repeated failure of a structurally sound community well. Tritium measurements indicate that groundwater from the affected depth interval (40–50 m) was recharged >60 years ago. Deeper (55–65 m) groundwater in the same pre-Holocene aquifer was recharged only 10–50 years ago but is still low in arsenic. Proximity to a confining clay layer that expels organic carbon as an indirect response to groundwater pumping, rather than directly accelerated recharge, caused arsenic contamination of this pre-Holocene aquifer.

Asian summer monsoon influence on chemical weathering and sediment provenance determined by clay mineral analysis from the Indus Submarine Canyon - Li, Yuting; Clift, Peter D.; Murray, Richard W.; Exnicios, Elise; Ireland, Thomas; Böning, Philipp (Quaternary Research, 2020)
Clay minerals from the Indus Canyon and eastern clinoform since ~12 ka are uniformly rich in smectite and illite, similar to those from the Holocene Indus flood plains. A systematic enrichment of smectite in the proximal delta compared to the canyon and eastern clinoform argues for preferential capture of smectite close to the river mouth since ~12 ka. There is a rapid shift to a more smectite-rich assemblage in the canyon and eastern clinoform after ~5 ka. This change is probably caused by a change in sediment source, with less direct flux from the Himalaya and more erosion of older, weathered, smectite-rich sediment from the Indus River flood plains, driven by incision of the Indus and its tributaries into the floodplain as summer monsoon rains weakened. This influx of smectite is consistent with lower kaolinite/smectite values since ~5 ka. The onset of large-scale agricultural activities since ~5 ka, especially starting with the Harappan Civilization, may also have enhanced incision and erosion of floodplain sediments over the same time period. This study reports for the first time how monsoon strength variations since ~12 ka affected the clay mineral assemblages and sediment provenance in a major submarine canyon.
Keywords: Clay minerals; Holocene; monsoon; Provenance; Reworking; Submarine canyon

Biomass-Derived Provenance Dominates Glacial Surface Organic Carbon in the Western HimalayaBiomass-Derived Provenance Dominates Glacial Surface Organic Carbon in the Western Himalaya - Nizam, Sarwar; Sen, Indra S.; Vinoj, Velu; Galy, Valier; Selby, David; Azam, Mohammad F.; Pandey, Satyendra K.; Creaser, Robert A.; Agarwal, Avinash K.; Singh, Akhilendra P.; Bizimis, Michael (Environmental Science & Technology, 2020)
The origin, transport pathway, and spatial variability of total organic carbon (OC) in the western Himalayan glaciers are poorly understood compared to those of black carbon (BC) and dust, but it is critically important to evaluate the climatic role of OC in the region. By applying the distribution of OC activation energy; C-14 activity; and radiogenic isotopes of Pb-208/Pb-204, (207)pb/(204)pb and (206)pb/Pb-204 in glacial debris and atmospheric particulate matter (PM10 size fraction), we demonstrate that 98.3 +/- 1.6 and 1.7 +/- 1.6% of OC in western Himalayan glaciers are derived from biomass and petrogenic sources, respectively. The (delta C-13 and N/C composition indicates that the biomass is a complex mixture of C3 vegetation and autochthonous photoautotrophic input modified by heterotrophic microbial activity. The data set reveals that the studied western Himalayan glacier has negligible contributions from fossil-fuel- derived particles, which contrasts to the central and eastern Himalayan glaciers that have significant contributions from fossil fuel sources. We show that this spatial variability of OC sources relates to regional differences in air mass transport pathways and precipitation regimes over the Himalaya. Moreover, our observation suggests that biomass-derived carbon could be the only primary driver of carbon-induced glacier melting in the western Himalaya.
Keywords: MASS BALANCES; AEROSOLS; ALBEDO REDUCTION; ATMOSPHERIC LEAD; BLACK CARBON; DUST TRANSPOR; isotopic composition; PB; SNOW ALBEDO; TIBETAN PLATEAU

Biosignatures Associated with Freshwater Microbialites - White, Richard Allen; Soles, Sarah A.; Brady, Allyson L.; Southam, Gordon; Lim, Darlene S.S.; Slater, Greg F. (Life, 2020)
Freshwater microbialites (i.e., lithifying microbial mats) are quite rare in northern latitudes of the North American continent, with two lakes (Pavilion and Kelly Lakes) of southeastern BC containing a morphological variety of such structures. We investigated Kelly Lake microbialites using carbon isotope systematics, phospholipid fatty acids (PLFAs) and quantitative PCR to obtain biosignatures associated with microbial metabolism. δ13CDIC values (mean δ13CDIC -4.9 ± 1.1‱, n = 8) were not in isotopic equilibrium with the atmosphere; however, they do indicate 13C-depleted inorganic carbon into Kelly Lake. The values of carbonates on microbialite surfaces (δ13C) fell within the range predicted for equilibrium precipitation from ambient lake water δ13CDIC (-2.2 to -5.3‱). Deep microbialites (26 m) had an enriched δ13Ccarb value of -0.3 ± 0.5‱, which is a signature of photoautotrophy. The deeper microbialites (>20 m) had higher biomass estimates (via PLFAs), and a greater relative abundance of cyanobacteria (measured by 16S copies via qPCR). The majority of PLFAs constituted monounsaturated and saturated PLFAs, which is consistent with gram-negative bacteria, including cyanobacteria. The central PLFA δ13C values were highly depleted (-9.3 to -15.7‱) relative to δ13C values of bulk organic matter, suggesting a predominance of photoautotrophy. A heterotrophic signature was also detected via the depleted iso- and anteiso-15:0 lipids (-3.2 to -5.2‱). Based on our carbonate isotopic biosignatures, PLFA, and qPCR measurements, photoautotrophy is enriched in the microbialites of Kelly Lake. This photoautotrophy enrichment is consistent with the microbialites of neighboring Pavilion Lake. This indication of photoautotrophy within Kelly Lake at its deepest depths raises new insights into the limits of measurable carbonate isotopic biosignatures under light and nutrient limitations.
Keywords: Biosignatures; Kelly Lake; microbialites; Pavilion Lake

Carbon Cycling in the World's Deepest Blue Hole - Yao, P.; Wang, X. C.; Bianchi, T. S.; Yang, Z. S.; Fu, L.; Zhang, X. H.; Chen, L.; Zhao, B.; Morrison, E. S.; Shields, M. R.; Liu, Y. N.; Bi, N. S.; et al. (Journal of Geophysical Research: Biogeosciences, 2020)
Blue holes are unique geomorphological features with steep biogeochemical gradients and distinctive microbial communities. Carbon cycling in blue holes, however, remains poorly understood. Here we describe potential mechanisms of dissolved carbon cycling in the world's deepest blue hole, the Yongle Blue Hole (YBH), which was recently discovered in the South China Sea. In the YBH, we found some of the lowest concentrations (e.g., 22 μM) and oldest ages (e.g., 6,810 years before present) of dissolved organic carbon, as well as the highest concentrations (e.g., 3,090 μM) and the oldest ages (e.g., 8,270 years before present) of dissolved inorganic carbon observed in oceanic waters. Sharp gradients of dissolved oxygen, H2S, and CH4 and changes in bacterially mediated sulfur cycling with depth indicated that sulfur‐ and/or methane‐based metabolisms are closely linked to carbon cycling in the YBH. Our results showed that the YBH is a unique and easily accessible natural laboratory for examining carbon cycling in anoxic systems, which has potential for understanding carbon dynamics in both paleo and modern oceans—particularly in the context of global change.
Keywords: anoxia; carbon cycling; dissolved carbon; radiocarbon; sulfur cycling; Yongle blue hole

Chapter 30 - Radiocarbon dating of tsunami and storm deposits - Kelsey, Harvey M.; Witter, Robert C. (Geological Records of Tsunamis and Other Extreme Waves, 2020)
Radiocarbon age determinations can be an expedient and accurate means to assign age to deposits of tsunami or storm origin. Essential to the process of incorporating radiocarbon age determinations in tsunami or coastal storm investigations is an awareness on the part of the investigator that a sample will always return an age from a laboratory, but only carefully selected samples inform deposit age. Samples that inform deposit age are of two fundamentally different sample types, in-growth-position samples and detrital samples. For both in-growth-position samples and detrital samples, stratigraphic context is the critical information needed to evaluate how well sample age can constrain deposit age. Well constrained deposit ages require bracketing samples collected to provide both maximum and minimum limiting ages for the deposit(s) of interest. Therefore, sampling should be carried out with the intention of multiple sample submissions for age in order to optimize the potential for acquiring closely limiting ages. If there are multiple age determinations within a stratigraphic sequence that contains tsunami or storm deposits, then the calibrated radiocarbon ages can be, and should be, framed within a Bayesian model structure to better constrain deposit ages. Such models can be further improved by the incorporation of independent stratigraphic age information.
Keywords: Dating coastal storm deposits; Dating tsunami deposits; Modeling approaches for dating tsunami deposits; Radiocarbon dating; Sampling tsunami deposits; Tsunami Deposits; Tsunami sand

Effects of agricultural and tillage practices on isotopic signatures and fluxes of organic and inorganic carbon in headwater streams - Kelsey, Scott A.; Grottoli, Andrea G.; Bauer, James E.; Lorenz, Klaus; Lal, Rattan; Matsui, Yohei; Huey-Sanders, Teresa M. (Aquatic Sciences, 2020)

Groundwater as a major source of dissolved organic matter to Arctic coastal waters - Connolly, Craig T.; Cardenas, M. Bayani; Burkart, Greta A.; Spencer, Robert G. M.; McClelland, James W. (Nature Communications, 2020)
Groundwater is projected to become an increasing source of freshwater and nutrients to the Arctic Ocean as permafrost thaws, yet few studies have quantified groundwater inputs to Arctic coastal waters under contemporary conditions. New measurements along the Alaska Beaufort Sea coast show that dissolved organic carbon and nitrogen (DOC and DON) concentrations in supra-permafrost groundwater (SPGW) near the land-sea interface are up to two orders of magnitude higher than in rivers. This dissolved organic matter (DOM) is sourced from readily leachable organic matter in surface soils and deeper centuries-to millennia-old soils that extend into thawing permafrost. SPGW delivers approximately 400–2100 m3 of freshwater, 14–71 kg of DOC, and 1–4 kg of DON to the coastal ocean per km of shoreline per day during late summer. These substantial fluxes are expected to increase as massive stocks of frozen organic matter in permafrost are liberated in a warming Arctic.

Holocene earthquake history and slip rate of the southern Teton fault, Wyoming, USAAbstract - DuRoss, Christopher B.; Gold, Ryan D.; Briggs, Richard W.; Delano, Jaime E.; Ostenaa, Dean A.; Zellman, Mark S.; Cholewinski, Nicole; Wittke, Seth J.; Mahan, Shannon A. (GSA Bulletin, 2020)
The 72-km-long Teton normal fault bounds the eastern base of the Teton Range in northwestern Wyoming, USA. Although geomorphic surfaces along the fault record latest Pleistocene to Holocene fault movement, the postglacial earthquake history of the fault has remained enigmatic. We excavated a paleoseismic trench at the Buffalo Bowl site along the southernmost part of the fault to determine its Holocene rupture history and slip rate. At the site, ∼6.3 m of displacement postdates an early Holocene (ca. 10.5 ka) alluvial-fan surface. We document evidence of three surface-faulting earthquakes based on packages of scarp-derived colluvium that postdate the alluvial-fan units. Bayesian modeling of radiocarbon and luminescence ages yields earthquake times of ca. 9.9 ka, ca. 7.1 ka, and ca. 4.6 ka, forming the longest, most complete paleoseismic record of the Teton fault. We integrate these data with a displaced deglacial surface 4 km NE at Granite Canyon to calculate a postglacial to mid-Holocene (14.4–4.6 ka) slip rate of ∼1.1 mm/yr. Our analysis also suggests that the postglacial to early Holocene (14.4–9.9 ka) slip rate exceeds the Holocene (9.9–4.6 ka) rate by a factor of ∼2 (maximum of 3); however, a uniform rate for the fault is possible considering the 95% slip-rate errors. The ∼5 k.y. elapsed time since the last rupture of the southernmost Teton fault implies a current slip deficit of ∼4–5 m, which is possibly explained by spatially/temporally incomplete paleoseismic data, irregular earthquake recurrence, and/or variable per-event displacement. Our study emphasizes the importance of minimizing slip-rate uncertainties by integrating paleoseismic and geomorphic data sets and capturing multiple earthquake cycles.

Holocene Rupture History of the Central Teton Fault at Leigh Lake, Grand Teton National Park, WyomingABSTRACT - Zellman, Mark S.; DuRoss, Christopher B.; Thackray, Glenn D.; Personius, Stephen F.; Reitman, Nadine G.; Mahan, Shannon A.; Brossy, Cooper C. (Bulletin of the Seismological Society of America, 2020)
Prominent scarps on Pinedale glacial surfaces along the eastern base of the Teton Range confirm latest Pleistocene to Holocene surface‐faulting earthquakes on the Teton fault, but the timing of these events is only broadly constrained by a single previous paleoseismic study. We excavated two trenches at the Leigh Lake site near the center of the Teton fault to address open questions about earthquake timing and rupture length. Structural and stratigraphic evidence indicates two surface‐faulting earthquakes at the site that postdate deglacial sediments dated by radiocarbon and optically stimulated luminescence to ∼10–11  ka⁠. Earthquake LL2 occurred at ∼10.0  ka (9.7–10.4 ka; 95% confidence range) and LL1 at ∼5.9  ka (4.8–7.1 ka; 95%). LL2 predates an earthquake at ∼8  ka identified in the previous paleoseismic investigation at Granite Canyon. LL1 corresponds to the most recent Granite Canyon earthquake at ∼4.7–7.9  ka (95% confidence range). Our results are consistent with the previously documented long‐elapsed time since the most recent Teton fault rupture and expand the fault’s earthquake history into the early Holocen

Holocene temperature and landscape history of southwest Greenland inferred from isotope and geochemical lake sediment proxies - Lasher, G. Everett; Axford, Yarrow; Masterson, Andrew L.; Berman, Karalyn; Larocca, Laura J. (Quaternary Science Reviews, 2020)
Terrestrial temperature reconstructions from the ice-free margins of Greenland are critical for constraining the sensitivity of the Greenland ice sheet to past climate change. Numerous investigations have clarified the glacial history of southwest Greenland in recent decades; however, very few local quantitative temperature reconstructions exist as context for changes in the cryosphere. We examine sedimentary records from two lakes south of Nuuk, Greenland (informally named lakes T1 and T2), and investigate millennial scale Holocene climate change using a multi-proxy approach. Changes in X-Ray fluorescence spectroscopy (XRF), δ15N, δ13C and biogenic silica concentrations of bulk lake sediments mark the transition from a marine environment to isolated lakes as relative sea level fell in the early Holocene. δ18O values of subfossil insects (chironomids) from lakes T1 and T2 decreased by 2–3‰ from c. 8.8 ka BP (minimum limiting age for the onset of lacustrine sediment deposition in lake T2; ka BP = thousands of years before 1950) to 1 ka BP. Existing isotope-independent temperature reconstructions from the west coast of Greenland suggest that these changes in δ18O values accompanied gradual cooling of 2–4 °C, concomitant with decreasing summer insolation. There is widespread regional evidence that this cooling resulted in progressive regrowth of local glaciers and of the ice sheet. The regional consensus on the magnitude of this temperature change indicates that the local, modern modeled temperature - precipitation δ18O relationship cannot be used to quantify millennial-scale temperature changes at these sites through the Holocene. This reinforces that studies utilizing δ18O-based proxies to infer temperature change should carefully assess local isotope-temperature relationships over space and time.
Keywords: Chironomids; glaciers; Greenland; Isolation basins; lake sediments; oxygen isotopes; Paleotemperatures; Stable isotopes

The Hooskanaden Landslide: historic and recent surge behavior of an active earthflow on the Oregon Coast - Alberti, Stefano; Senogles, Andrew; Kingen, Kara; Booth, Adam; Castro, Pete; DeKoekkoek, Jill; Glover-Cutter, Kira; Mohney, Curran; Olsen, Michael; Leshchinsky, Ben (Landslides, 2020)
This paper presents an analysis of the Hooskanaden Landslide, an earthflow, which experienced a dramatic surge event beginning on February 24, 2019, closing US Highway 101 near mile point 343.5 for nearly 2 weeks. This ~ 1 km long surge event resulted in horizontal displacements of up to 45 m and uplift of 6 m at the toe located on a gravel beach adjacent to the Pacific Ocean. The Hooskanaden Landslide, likely active since the eighteenth century, exhibits regular activity with a recurrence interval of major surge events of approximately every 20 years, transitioning from slow to relatively rapid velocities. During the 2019 event, maximum displacement rates of approximately 60 cm/h were observed, slowly decreasing to 15 cm/h for a sustained period of approximately 2 weeks before the eventual return to baseline conditions (< 0.02 cm/h).

Identifying the Greatest Earthquakes of the Past 2000 Years at the Nehalem River Estuary, Northern Oregon Coast, USA - Nelson, Alan R.; Hawkes, Andrea D.; Sawai, Yuki; Engelhart, Simon E.; Witter, Rob; Grant-Walter, Wendy C.; Bradley, Lee-Ann; Dura, Tina; Cahill, Niamh; Horton, Ben (Open Quaternary, 2020)
We infer a history of three great megathrust earthquakes during the past 2000 years at the Nehalem River estuary based on the lateral extent of sharp (≤3 mm) peat-mud stratigraphic contacts in cores and outcrops, coseismic subsidence as interpreted from fossil diatom assemblages and reconstructed with foraminiferal assemblages using a Bayesian transfer function, and regional correlation of 14C-modeled ages for the times of subsidence. A subsidence contact from 1700 CE (contact A), sometimes overlain by tsunami-deposited sand, can be traced over distances of 7 km. Contacts B and D, which record subsidence during two earlier megathrust earthquakes, are much less extensive but are traced across a 700-m by 270-m tidal marsh. Although some other Cascadia studies report evidence for an earthquake between contacts B and D, our lack of extensive evidence for such an earthquake may result from the complexities of preserving identifiable evidence of it in the rapidly shifting shoreline environments of the lower river and bay. Ages (95% intervals) and subsidence for contacts are: A, 1700 CE (1.1 ± 0.5 m); B, 942–764 cal a BP (0.7 ± 0.4 m and 1.0 m ± 0.4 m); and D, 1568–1361 cal a BP (1.0 m ± 0.4 m). Comparisons of contact subsidence and the degree of overlap of their modeled ages with ages for other Cascadia sites are consistent with megathrust ruptures many hundreds of kilometers long. But these data cannot conclusively distinguish among different types or lengths of ruptures recorded by the three great earthquake contacts at the Nehalem River estuary.
Keywords: Bayesian transfer function; Cascadia subduction zone; Coseismic subsidence; earthquake hazards; Paleoseismology; salt-marsh stratigraphy; Sea-level changes; tidal foraminifera and diatoms

Influences of upper Floridan aquifer waters on radiocarbon in the otoliths of gray snapper (Lutjanus griseus) in the Gulf of Mexico - Andrews, Allen H; Barnett, Beverly K; Chanton, Jeffrey P; Thornton, Laura A; Allman, Robert J (Radiocarbon, 2020)
The otoliths (ear stones) of fishes are commonly used to describe the age and growth of marine and freshwater fishes. These non-skeletal structures are fortuitous in their utility by being composed of mostly inorganic carbonate that is inert through the life of the fish. This conserved record functions like an environmental chronometer and bomb-produced radiocarbon — a 14C signal created by atmospheric testing of thermonuclear devices — can be used as a time-specific marker in validating fish age. However, complications from the hydrogeology of nearshore marine environments can complicate 14C levels, as was the case with gray snapper (Lutjanus griseus) along the Gulf of Mexico coast of Florida. Radiocarbon of these nearshore waters is influenced by freshwater input from the karst topography of the Upper Floridan Aquifer-estuarine waters that are 14C-depleted from surface and groundwater inputs. Some gray snapper likely recruited to this kind of environment where 14C levels were depleted in the earliest otolith growth, although age was validated for individuals that were not exposed to 14C-depleted waters to an age of at least 25 years with support for a 30-year lifespan.

Late glacial and Holocene paleoenvironments in the midcontinent United States, inferred from Geneva Lake leaf wax, ostracode valve, and bulk sediment chemistry - Puleo, Peter J.K.; Axford, Yarrow; McFarlin, Jamie M.; Curry, B. Brandon; Barklage, Mitchell; Osburn, Magdalena R. (Quaternary Science Reviews, 2020)
Geneva Lake in Wisconsin, USA, is > 20,000 years old and contains a 30-m thick lacustrine sediment record of mid-continent North American climate and environmental change. Here we describe a sediment record from Geneva Lake spanning the past 14,500 years. From scanning X-ray fluorescence, organic C and N concentrations and isotopes, X-ray diffraction, magnetic susceptibility, and grain size of bulk sediments, we infer changes in sediment sources over time including: abrupt decline in inputs of remobilized loess ∼13,400 cal yr BP followed by a gradual transition to organic-rich marl deposition by ∼10,400 cal yr BP as the landscape stabilized following a period of permafrost thaw and vegetation development; deposition of a minerogenic unit at ∼8,200 cal yr BP that may record enhanced eolian activity during the widespread “8.2 ka event; ” and elevated zinc, lead, and arsenic from human activities following regional industrialization. Within the Holocene marl, we also use isotopic (δ18O and δ13C) and trace metal ratio (Sr/Ca and Mg/Ca) analyses of ostracode valves paired with concentrations and hydrogen isotopic composition (δ2H) of leaf wax n-alkanes to infer climate and hydrological change. Groundwater had a large but declining influence on lake water chemistry from 11,800 to 9,700 cal yr BP, precluding inferences of regional climate from our lacustrine proxies during this period. δ2H values of terrestrial n-C29 alkanes show little variability from 9,700 to present, indicating the average isotopic composition of local precipitation was relatively stable, reflecting stable condensation temperatures and source. In contrast, a gradual trend towards more δ18O- and δ2H-depleted lake water and lower lake water Sr/Ca from 9700 cal yr BP to present suggest decreasing evaporation of lake water and increasing precipitation amounts throughout the Holocene and resulting shorter lake water residence times. Lake water Mg/Ca variations over the past 9,700 years broadly parallel regional pollen-based reconstructions of summer temperatures. Neither Mg/Ca nor terrestrial leaf wax δ2H suggest long-term directional shifts in temperature at this site through the middle to late Holocene, as climate became wetter. It appears that precipitation isotopes did not track local temperatures on millennial timescales in this part of mid-continent North America through the Holocene, and instead may have covaried with changes in Northern Hemisphere latitudinal temperature gradients driven by large Arctic temperature changes.
Keywords: Holocene; Inorganic geochemistry; Loess; North America; Organic geochemistry; paleoclimatology; paleolimnology; Pleistocene; sedimentology; Stable isotopes

Life and its traces in Antarctica's McMurdo Dry Valley paleolakes: a survey of preservation - Greenfield, Samuel R.; Tighe, Scott W.; Bai, Yu; Goerlitz, David S.; Von Turkovich, Michele; Taatjes, Douglas J.; Dragon, Julie A.; Johnson, Sarah Stewart (Micron, 2020)
The extremely cold and arid conditions of Antarctica make it uniquely positioned to investigate fundamental questions regarding the persistence of life in extreme environments. Within the McMurdo Dry Valleys and surrounding mountain ranges are multiple ancient relict lakes, paleolakes, with lacustrine deposits spanning from thousands to millions of years in age. Here we present data from light microscopy, scanning electron microscopy, electron dispersive x-ray spectroscopy, and radiocarbon dating to catalog the remarkable range of life preserved within these deposits. This includes intact microbes and nanobacteria-sized cocci, CaCO3 precipitations consistent with biogenic calcium, previously undescribed net-like structures, possible dormant spores, and long-extinct yet exquisitely preserved non-vascular plants. These images provide an important reference for further microbiome investigations of Antarctic paleolake samples. In addition, these findings may provide a visual reference for the use of subsurface groundwater microbial communities as an analog for paleolake subsurface water on planets such as Mars.
Keywords: Antarctica; Biosignatures; Microbes; Paleolakes; SEM

Life history of northern Gulf of Mexico Warsaw grouper Hyporthodus nigritus inferred from otolith radiocarbon analysis - Barnett, Beverly K.; Chanton, Jeffrey P.; Ahrens, Robert; Thornton, Laura; Patterson, William F. (PLOS ONE, 2020)
Warsaw grouper, Hyporthodus nigritus, is a western Atlantic Ocean species typically found at depths between 55 and 525 m. It is listed as a species of concern by the U.S. National Marine Fisheries Service and as near threatened by the International Union for the Conservation of Nature. However, little information exists on the species’ life history in the northern Gulf of Mexico (nGOM) and its stock status in that region is currently unknown. Age of nGOM Warsaw grouper was investigated via opaque zone counts in otolith thin sections (max age = 61 y), and then the bomb 14C chronometer was employed to validate the accuracy of age estimates. Otolith cores (n = 14) were analyzed with accelerator mass spectrometry and resulting Δ14C values overlain on a loess regression computed for a regional coral and known-age red snapper Δ14C time series. Residual analysis between predicted Δ14C values from the loess regression versus Warsaw grouper otolith core Δ14C values indicated no significant difference in the two data series. Therefore, the accuracy of otolith-based aging was validated, which enabled growth and longevity estimates to be made for nGOM Warsaw grouper. Dissolved inorganic carbon (DIC) Δ14C values collected from the nGOM support the inference that juvenile Warsaw grouper occur in shelf waters (<200 m) since DIC Δ14C values in this depth range are enriched in 14C and similar to the Δ14C values from otolith cores. A Bayesian model was fit to fishery-dependent age composition data and produced von Bertalanffy growth function parameters of L1 = 1,533 mm, k = 0.14 y-1, and t0 = 1.82 y. Fishing mortality also was estimated in the model, which resulted in a ratio of fishing to natural mortality of 5.1:1. Overall, study results indicate Warsaw grouper is a long-lived species that is estimated to have experienced significant overfishing in the nGOM, with the age of most landed fish being <10 y.

Local glaciers record delayed peak Holocene warmth in south Greenland - Larocca, Laura J.; Axford, Yarrow; Bjørk, Anders A.; Lasher, G. Everett; Brooks, Jeremy P. (Quaternary Science Reviews, 2020)
Local glaciers and ice caps (GICs) respond sensitively and quickly, on the scale of decades to centuries, to climate variations. Continuous records of past fluctuations in GIC size provide information on the timing and magnitude of Holocene climate shifts, and a longer-term perspective on 21st century glacier retreat. Although there is broad-scale agreement on millennial-scale trends in Holocene climate variability and fluctuations in local GICs in Greenland, regional variations are only loosely constrained. Here we present three Holocene proglacial lake sediment records from South Greenland, an area with abundant local glaciers but few Holocene-length paleoclimate records. In addition, we use geospatial analysis to model past equilibrium-line altitudes (ELAs) and thereby constrain the magnitude of ablation-season temperature change during the warmest and coolest periods of the Holocene. Physical and geochemical sedimentary characteristics show that two of the proglacial lakes continued to receive glacial meltwater input until ∼7.3 and ∼7.1 ka BP. The survival of local glaciers implies that South Greenland remained relatively cool, and that summer temperatures gradually warmed, but did not warm well beyond 1.2 °C above present in the early Holocene. In the mid-Holocene, from ∼7.1 to 5.5 ka BP, organic sedimentation at these two sites indicates that local glaciers became very small, or more likely melted away completely. The glaciers within the third lake’s catchment melted away prior to ∼5.2 ka BP, as sediments deposited earlier in the Holocene could not be dated at this site. We estimate that summer temperatures increased by at least 1.2–1.8 °C above present by ∼7.3–7.1 ka BP. Our results are consistent with other observations that suggest a north-to-south gradient in the timing of Holocene thermal maximum conditions, with southern Greenland experiencing a delayed warming relative to other regions in Greenland. As summer temperatures cooled in the Neoglacial, our records show that sustained glacier regrowth began ∼3.1 ka BP with glaciers in the southernmost catchment, which at present, receive the most precipitation. In the other two catchments, which host smaller glaciers in a drier environment, regrowth began at ∼1.3 and ∼1.2 ka BP, the timing of which is in agreement with other glacial records from the Arctic Atlantic region. Local glaciers reached their maximum late Holocene extents during a cooler, second phase of the Little Ice Age (LIA) ∼0.2-0.1 ka BP, that we estimate was at least 0.4–0.9 °C cooler than present. Overall, these findings improve understanding of the spatio-temporal dynamics of Holocene glacier and climate change in Greenland, potentially yielding valuable information about their future response.
Keywords: Equilibrium-line altitudes; Greenland; Holocene thermal maximum; lake sediments; Little ice age; Mountain glaciers; Paleotemperatures

Neotectonic and Paleoseismic Analysis of the Northwest Extent of Holocene Surface Deformation along the Meers Fault, OklahomaABSTRACT - Hornsby, Kristofer T.; Streig, Ashley R.; Bennett, Scott E. K.; Chang, Jefferson C.; Mahan, Shannon (Bulletin of the Seismological Society of America, 2020)
The Meers fault (Oklahoma) is one of few seismogenic structures with evidence for Holocene surface rupture in the stable continental region of North America. The 37-kilometer-long southeast section of the full 54-kilometer-long Meers fault is interpreted to be Holocene active. The 17-kilometer-long northwest section is considered Quaternary active, but not Holocene active.We reevaluate surface expression and earthquake timing of the northwest Meers fault to improve seismic source characterization.We use airborne light detection and ranging and historical stereo paired aerial photos to evaluate the fault scarp and local fault zone geomorphology. In the northwest, complex surface deformation includes fault splays, subtle monoclinal warping, and a minor change in fault strike. We interpret that the along strike transition from surface faulting on the southeast Meers fault to surface folding on the northwest Meers fault occurs at the lithologic contact between Permian Post Oak conglomerate and Hennessey shale. We excavated a paleoseismic trench to evaluate the timing of surface-deforming earthquakes on the northwest section of the fault. The excavation revealed weathered Permian Hennessey shale and an ∼1–2-meter-thick veneer of Holocene alluvial deposits that were progressively deformed during two surface-folding earthquakes likely related to blind fault rupture beneath the site. Repeated onlapping to overlapping stratigraphic sequences and associated unconformities are intimately related to folding events along the monocline. OxCal paleoearthquake age modeling indicates that earthquakes occurred 4704–3109 yr B.P. and 5955–4744 yr B.P., and that part of the northwest section of the Meers fault is Holocene active. We find the Holocene-active section of the Meers fault should be lengthened 6.1 km to the northwest, to a total Holocene-active fault length of 43 km. Empirical scaling relationships between surface rupture length and magnitude reveal that the fault could generate an Mw 7.0 earthquake.

Origin of Groundwater Arsenic in a Rural Pleistocene Aquifer in Bangladesh Depressurized by Distal Municipal Pumping - Mozumder, M. R. H.; Michael, H. A.; Mihajlov, I.; Khan, M. R.; Knappett, P. S. K.; Bostick, B. C.; Mailloux, B. J.; Ahmed, K. M.; Choudhury, I.; Koffman, T.; Ellis, T.; Whaley‐Martin, K.; et al. (Water Resources Research, 2020)
Across South Asia, millions of villagers have reduced their exposure to high‐arsenic (As) groundwater by switching to low‐As wells. Isotopic tracers and flow modeling are used in this study to understand the groundwater flow system of a semi‐confined aquifer of Pleistocene (>10 kyr) age in Bangladesh that is generally low in As but has been perturbed by massive pumping at a distance of about 25 km for the municipal water supply of Dhaka. A 10‐ to 15‐m‐thick clay aquitard caps much of the intermediate aquifer (>40‐ to 90‐m depth) in the 3‐km2 study area, with some interruptions by younger channel sand deposits indicative of river scouring. Hydraulic heads in the intermediate aquifer below the clay‐capped areas are 1–2 m lower than in the high‐As shallow aquifer above the clay layer. In contrast, similar heads in the shallow and intermediate aquifer are observed where the clay layer is missing. The head distribution suggests a pattern of downward flow through interruptions in the aquitard and lateral advection from the sandy areas to the confined portion of the aquifer. The interpreted flow system is consistent with 3H‐3He ages, stable isotope data, and groundwater flow modeling. Lateral flow could explain an association of elevated As with high methane concentrations within layers of gray sand below certain clay‐capped portions of the Pleistocene aquifer. An influx of dissolved organic carbon from the clay layer itself leading to a reduction of initially orange sands has also likely contributed to the rise of As.
Keywords: Arsenic; Dhaka Bangladesh; groundwater pumping; modeling

RADIOCARBON RESERVOIR AGES IN THE HOLOCENE DEAD SEAABSTRACT - Weber, Nurit; Lazar, Boaz; Stern, Ofra; Burr, George; Gavrieli, Ittai; Roberts, Mark; Kurz, Mark D; Yechieli, Yoseph; Stein, Mordechai (Radiocarbon, 2020)
The sources and fate of radiocarbon (C-14) in the Dead Sea hypersaline solution are evaluated with C-14 measurements in organic debris and primary aragonite collected from exposures of the Holocene Ze'elim Formation. The reservoir age (RA) is defined as the difference between the radiocarbon age of the aragonite at time of its precipitation (representing lake's dissolved inorganic carbon pig) and the age of contemporaneous organic debris (representing atmospheric radiocarbon). Evaluation of the data for the past 6000 yr from Dead Sea sediments reveal that the lake's RA decreased from 2890 yr at 6 cal kyr BP to 2300 yr at present. The RA lies at similar to 2400 yr during the past 3000 yr, when the lake was characterized by continuous deposition of primary aragonite, which implies a continuous supply of freshwater-bicarbonate into the lake. This process reflects the overall stability of the hydrological-climate conditions in the lake's watershed during the late Holocene where bicarbonate originated from dissolution of the surface cover in the watershed that was transported to the Dead Sea by the freshwater runoff. An excellent correlation (R-2=0.98) exists between aragonite ages and contemporaneous organic debris, allowing the estimation of ages of various primary deposits where organic debris are not available.
Keywords: aragonite; Dead Sea; Holocene; radiocarbon; reservoir ages

Resolving sea ice dynamics in the north-western Ross Sea during the last 2.6 ka: From seasonal to millennial timescales - Tesi, T.; Belt, S.T.; Gariboldi, K.; Muschitiello, F.; Smik, L.; Finocchiaro, F.; Giglio, F.; Colizza, E.; Gazzurra, G.; Giordano, P.; Morigi, C.; Capotondi, L.; et al. (Quaternary Science Reviews, 2020)
Time-series analyses of satellite images reveal that sea ice extent in the Ross Sea has experienced significant changes over the last 40 years, likely triggered by large-scale atmospheric anomalies. However, resolving how sea ice in the Ross Sea has changed over longer timeframes has until now remained more elusive. Here we used a laminated sediment piston core (14.6 m) collected from the Edisto inlet (Western Ross Sea) to reconstruct fast ice dynamics over the last 2.6 ka. Our goal was to first understand the climate expression of selected well-defined sediment laminae and then use these characteristics for reconstructing past sea ice behaviour across the whole sedimentary sequence. We used the recently established sea ice diatom biomarker proxy IPSO25 in combination with diatom census counts and bulk analyses. Analyses performed on a suite of discrete laminae revealed statistically significant differences between dark and light laminae reflecting different depositional conditions. Based on their respective biogeochemical fingerprints, we infer that dark laminae accumulated during sea ice thaws in early summer. Under these conditions, laminae contain relatively high concentrations of IPSO25 and display an enriched δ13C composition for the bulk organic matter (OM). While diatom assemblages in dark laminae are relatively homogenous, as the thaw continues later in the summer, Corethron pennatum becomes the dominant diatom species, resulting in the formation of light laminae characterized by low IPSO25 concentrations. Since C. pennatum can migrate vertically through the water column to uptake nutrients and avoid competition in oligotrophic waters, its high concentration likely reflects stratified and ice-free surface waters typical of late summer. Down-core trends show that the correlation between sediment brightness and geochemical fingerprint (i.e., IPSO25 and δ13C) holds throughout the record. Based on the knowledge gained at lamina level, our down-core high-resolution reconstruction shows that the summer fast ice coverage changed dramatically during the late Holocene. Specifically, we conclude that the Edisto inlet experienced regular early summer opening between 2.6 ka, and ca. 0.7 ka, after which, coastal fast ice persisted during summer months and ice-free conditions became less frequent. Comparison with previous regional ice core data suggests that the sudden cooling recorded over the Victoria Land Coast region since 0.7 ka might potentially explain our observation of persistent summer fast ice in the Western Ross Sea. Our study has shown that multi-proxy data derived from laminated sediments can provide hitherto unknown detail regarding past summer sea ice dynamics in coastal Antarctic regions.
Keywords: Fast ice; IPSO25; Laminated sediments; Ross Sea; Sea ice

Sedimentary evidence of prehistoric distant‐source tsunamis in the Hawaiian Islands - La Selle, SeanPaul; Richmond, Bruce M.; Jaffe, Bruce E.; Nelson, Alan R.; Griswold, Frances R.; Arcos, Maria E. M.; Chagué, Catherine; Bishop, James M.; Bellanova, Piero; Kane, Haunani H.; Lunghino, Brent D.; Gelfenbaum, Guy (Sedimentology, 2020)
Over the past 200 years of written records, the Hawaiian Islands have experienced tens of tsunamis generated by earthquakes in the subduction zones of the Pacific ‘Ring of Fire’ (for example, Alaska–Aleutian, Kuril–Kamchatka, Chile and Japan). Mapping and dating anomalous beds of sand and silt deposited by tsunamis in low‐lying areas along Pacific coasts, even those distant from subduction zones, is critical for assessing tsunami hazard throughout the Pacific basin. This study searched for evidence of tsunami inundation using stratigraphic and sedimentological analyses of potential tsunami deposits beneath present and former Hawaiian wetlands, coastal lagoons, and river floodplains. Coastal wetland sites on the islands of Hawai΄i, Maui, O΄ahu and Kaua΄i were selected based on historical tsunami runup, numerical inundation modelling, proximity to sandy source sediments, degree of historical wetland disturbance, and breadth of prior geological and archaeological investigations. Sand beds containing marine calcareous sediment within peaty and/or muddy wetland deposits on the north and north‐eastern shores of Kaua΄i, O΄ahu and Hawai΄i were interpreted as tsunami deposits. At some sites, deposits of the 1946 and 1957 Aleutian tsunamis are analogues for deeper, older probable tsunami deposits. Radiocarbon‐based age models date sand beds from three sites to ca 700 to 500 cal yr bp, which overlaps ages for tsunami deposits in the eastern Aleutian Islands that record a local subduction zone earthquake. The overlapping modelled ages for tsunami deposits at the study sites support a plausible correlation with an eastern Aleutian earthquake source for a large prehistoric tsunami in the Hawaiian Islands.
Keywords: Aleutians; deposit; distant source; extreme events; Hawai΄i; palaeotsunami

The southern Gulf of Mexico: A baseline radiocarbon isoscape of surface sediments and isotopic excursions at depth - Bosman, Samantha H.; Schwing, Patrick T.; Larson, Rebekka A.; Wildermann, Natalie E.; Brooks, Gregg R.; Romero, Isabel C.; Sanchez-Cabeza, Joan-Albert; Ruiz-Fernández, Ana Carolina; Machain-Castillo, Maria Luisa; Gracia, Adolfo; Escobar-Briones, Elva; Murawski, Steven A.; et al. (PLOS ONE, 2020)
The southern Gulf of Mexico (sGoM) is home to an extensive oil recovery and development infrastructure. In addition, the basin harbors sites of submarine hydrocarbon seepage and receives terrestrial inputs from bordering rivers. We used stable carbon, nitrogen, and radiocarbon analyses of bulk sediment organic matter to define the current baseline isoscapes of surface sediments in the sGoM and determined which factors might influence them. These baseline surface isoscapes will be useful for accessing future environmental impacts. We also examined the region for influence of hydrocarbon deposition in the sedimentary record that might be associated with hydrocarbon recovery, spillage and seepage, as was found in the northern Gulf of Mexico (nGoM) following the Deepwater Horizon (DWH) oil spill in 2010. In 1979, the sGoM experienced a major oil spill, Ixtoc 1. Surface sediment δ13C values ranged from -22.4‰ to -19.9‰, while Δ14C values ranged from -337.1‰ to -69.2‰. Sediment δ15N values ranged from 2.8‰ to 7.2‰, while the %C on a carbonate-free basis ranged in value of 0.65% to 3.89% and %N ranged in value of 0.09% to 0.49%. Spatial trends for δ13C and Δ14C were driven by water depth and distance from the coastline, while spatial trends for δ15N were driven by location (latitude and longitude). Location and distance from the coastline were significantly correlated with %C and %N. At depth in two of twenty (10%) core profiles, we found negative δ13C and Δ14C excursions from baseline values in bulk sedimentary organic material, consistent with either oil-residue deposition or terrestrial inputs, but likely the latter. We then used 210Pb dating on those two profiles to determine the time in which the excursion-containing horizons were deposited. Despite the large spill in 1979, no evidence of hydrocarbon residue remained in the sediments from this specific time period.
Keywords: Gulf of Mexico; hydrocarbons; Oil spills; Oils; Petroleum; Sediment

Stable source of Holocene spring precipitation recorded in leaf wax hydrogen-isotope ratios from two New York lakes - Schartman, Anna K.; Diefendorf, Aaron F.; Lowell, Thomas V.; Freimuth, Erika J.; Stewart, Alexander K.; Landis, Joshua D.; Bates, Benjamin R. (Quaternary Science Reviews, 2020)
Changes in synoptic atmospheric circulation patterns are thought to play a role in establishing millennial scale climate periods during the end of the late glacial and the Holocene. In the northeastern United States, multi-proxy evidence documents fluctuations in effective moisture and temperatures for this time period, but constraining the relationship between atmospheric processes and these climate regimes is not straightforward. Because the hydrogen-isotope ratios of sedimentary terrestrial leaf waxes can reflect precipitation δD, these long-chain hydrocarbon compounds are an excellent tool to investigate moisture sourcing. Here we present lake sediment and leaf wax carbon- and hydrogen-isotope records that span the past ∼14.0 thousand years from Heart Lake and Moose Pond in the Adirondack Mountains (ADK), New York. High initial lake productivity after basin inception is reflected in low C:N ratios (<15), and higher relative short chain n-alkane (n-C17, n-C19, and n-C21) to long chain n-alkane (n-C27, n-C29 and n-C31) concentration ratios. The Holocene record is characterized by low bulk and n-alkane δ13C (∼ −28‰, ∼ −31‰, respectively), high ACL25-35 (∼28), and high relative concentrations of long chain n-alkane homologues, indicating a dominantly terrestrial source of organic matter for this time period. Hydrogen-isotope ratios of n-C29 n-alkane from both lake basins range only ∼20‰ through the Holocene and reconstructed precipitation δD (δDprecip) from both basins is in good agreement with that of modern modeled spring precipitation. This suggests there may have been no major changes in the sourcing of spring precipitation for the ADK throughout the time of record.
Keywords: Holocene; Hydrogen isotopes; late glacial; Leaf wax; North America; Organic geochemistry; paleoclimatology; Precipitation sourcing

Two-Phase Synthesis of Taxol - Kanda, Yuzuru; Nakamura, Hugh; Umemiya, Shigenobu; Puthukanoori, Ravi Kumar; Murthy Appala, Venkata Ramana; Gaddamanugu, Gopi Krishna; Paraselli, Bheema Rao; Baran, Phil S. (Journal of the American Chemical Society, 2020)
Taxol (a brand name for paclitaxel) is widely regarded as among the most famed natural isolates ever discovered, and has been the subject of innumerable studies in both basic and applied science. Its documented success as an anticancer agent, coupled with early concerns over supply, stimulated a furious worldwide effort from chemists to provide a solution for its preparation through total synthesis. Those pioneering studies proved the feasibility of retrosynthetically guided access to synthetic Taxol, albeit in minute quantities and with enormous effort. In practice, all medicinal chemistry efforts and eventual commercialization have relied upon natural (plant material) or biosynthetically derived (synthetic biology) supplies. Here we show how a complementary divergent synthetic approach that is holistically patterned off of biosynthetic machinery for terpene synthesis can be used to arrive at Taxol.
Keywords: 1ST TOTAL-SYNTHESIS; ANALOGS; chemistry; DIMETHYLDIOXIRANE; ENANTIOSELECTIVE TOTAL-SYNTHESIS; FORMAL TOTAL-SYNTHESIS; PINENE PATH; RING; STEREOCONTROLLED SYNTHESIS; TAXANES

A 12,700-year history of paleolimnological change from an Andean microrefugium - de Novaes Nascimento, Majoi; Laurenzi, Anne Gail; Valencia, Bryan G; Van, Robert; Bush, Mark (The Holocene, 2019)
We present a 12,6700-yr limnological history of Lake Miski, a high-elevation lake in a wet section of the Peruvian Andes. While many shallow Andean lakes dried up during the mid-Holocene, loss-on-ignition, magnetic susceptibility, and diatom analysis showed that Lake Miski was a constant feature in the landscape. Overall, fluctuations in the fossil diatom communities of Lake Miski tracked changes in insolation, but this was not the only mechanism influencing observed variability. We identify periods when insolation and interactions with the Pacific Ocean may have played a role in structuring local climate and diatom assemblages. The true mid-Holocene Dry Event (MHDE) is manifested in this record between 8000 and 5000 cal BP, but the carbonate stratigraphy and the diatom community indicated that although the level of the lake decreased, it never completely dried out, instead there was higher availability of planktic habitat and stronger mixing than in much of the Holocene. High rates of biological change observed during the late-Holocene in other records from Peru associated with human amplification of climatic signals were not observed in Lake Miski, as this lake may have been too wet and remote to be strongly influenced by human activity. Because of the presence of a woodland microrefugium, Lake Miski was suggested to have been an unusually climatically stable and wet location during the regional drying associated with the MHDE. Our new limnological information provides additional insights relating to this discussion. The presence of the observed woodland apparently withstood fluctuations that induced state changes in the lake and diatom flora, underscoring that microrefugia do not equate to ‘unchanging’ hydrologies or climates.
Keywords: Andes; diatoms; drought; enso; Holocene; limnology; microrefugia; mid-Holocene dry event; paleoecology

Abrupt mid-Holocene ice loss in the western Weddell Sea Embayment of Antarctica - Johnson, Joanne S.; Nichols, Keir A.; Goehring, Brent M.; Balco, Greg; Schaefer, Joerg M. (Earth and Planetary Science Letters, 2019)
The glacial history of the westernmost Weddell Sea sector of Antarctica since the Last Glacial Maximum is virtually unknown, and yet it has been identified as critical for improving reliability of glacio-isostatic adjustment models that are required to correct satellite-derived estimates of ice sheet mass balance. Better knowledge of the glacial history of this region is also important for validating ice sheet models that are used to predict future contribution of the Antarctic ice sheet to sea level rise. Here we present a new Holocene deglacial chronology from a site on the Lassiter Coast of the Antarctic Peninsula, which is situated in the western Weddell Sea sector. Samples from 12 erratic cobbles and 18 bedrock surfaces from a series of presently-exposed ridges were analysed for cosmogenic Be-10 exposure dating, and a smaller suite of 7 bedrock samples for in situ C-14 dating. The resulting Be-10 ages are predominantly in the range 80-690 ka, whereas bedrock yielded much younger in situ C-14 ages, in the range 6.0-7.5 ka for samples collected from 138-385 m above the modern ice surface. From these we infer that the ice sheet experienced a period of abrupt thinning over a short time interval (no more than 2700 years) in the mid-Holocene, resulting in lowering of its surface by at least 250 m. Any late Holocene change in ice sheet thickness - such as re-advance, postulated by several modelling studies - must lie below the present ice sheet surface. The substantial difference in exposure ages derived from Be-10 and C-14 dating for the same samples additionally implies ubiquitous Be-10 inheritance acquired during ice-free periods prior to the last deglaciation, an interpretation that is consistent with our glacial-geomorphological field observations for former cold-based ice cover. The results of this study provide evidence for an episode of abrupt ice sheet surface lowering in the mid-Holocene, similar in rate, timing and magnitude to at least two other locations in Antarctica.
Keywords: Antarctica; cosmogenic dating in situ 14C; Holocene; Weddell Sea ice sheet

Analysis of multiple cosmogenic nuclides constrains Laurentide Ice Sheet history and process on Mt. Mansfield, Vermont's highest peak - Corbett, Lee B.; Bierman, Paul R.; Wright, Stephen F.; Shakun, Jeremy D.; Davis, P. Thompson; Goehring, Brent M.; Halsted, Christopher T.; Koester, Alexandria J.; Caffee, Marc W.; Zimmerman, Susan R. (Quaternary Science Reviews, 2019)
Constraining glacial history and process on Mt Mansfield, the highest peak in Vermont (1339 m a.s.l.), provides insight into how the Laurentide Ice Sheet shaped the underlying landscape, when latest Pleistocene ice retreated, and how upland and lowland glacial histories relate. Here, we quantify in situ cosmogenic 10Be in 20 bedrock and boulder surfaces, as well as in situ cosmogenic 14C in three of those surfaces, to assess subglacial erosion and exposure history. Isotopic concentrations indicate that Mt. Mansfield's lower elevations (∼400–1200 m a.s.l.) were deeply eroded by at least several meters during the last glaciation and then deglaciated rapidly; 10Be ages across this elevation span are indistinguishable and average 13.9 ± 0.6 ka (n = 15), suggesting that 800 m of ice thinning occurred within at most about a millennium. Conversely, the higher elevations (>1200 m a.s.l.) preserve a more complex geomorphic history. Mt. Mansfield's summit surfaces contain 10Be from previous periods of exposure, indicating that the mountaintop landscapes were likely preserved beneath cold-based, weakly-erosive glacial ice. Exposure ages from the shorter-lived isotope, 14C, are younger (9.7 and 11.7 ka), suggesting that Mt. Mansfield's summit was covered until the early Holocene, perhaps by snowfields, ice carapaces, and/or till. Our findings, in context of previous work, suggest that thinning Laurentide ice flowed through the valleys for at most hundreds of years following deglaciation of the uplands, but that the summit remained shielded by ice or sediment for millennia after the valleys became ice-free.
Keywords: Cosmogenic isotopes; erosion; Geochronology; Glaciation; Last glacial maximum; North America; Pleistocene

Antarctic Relic Microbial Mat Community Revealed by Metagenomics and Metatranscriptomics - Zaikova, Elena; Goerlitz, David S.; Tighe, Scott W.; Wagner, Nicole Y.; Bai, Yu; Hall, Brenda L.; Bevilacqua, Julie G.; Weng, Margaret M.; Samuels-Fair, Maya D.; Johnson, Sarah Stewart (Frontiers in Ecology and Evolution, 2019)
Buried upslope from the modern lakes in the McMurdo Dry Valleys of Antarctica are relict lake deposits embedded in valley walls. Within these relict deposits, ancient microbial mats, or paleomats, have been preserved under extremely arid and cold conditions since the receding of larger paleolakes thousands of years ago, and now serve as a sheltered niche for microbes in a highly challenging oligotrophic environment. To explore whether paleomats could be repositories for ancient lake cells or were later colonized by soil microbes, determine what types of metabolic pathways might be present, analyze potential gene expression, and explore whether the cells are in a vegetative or dormant state, we collected paleomat samples from ancient lake facies on the northern slopes of Lake Vanda in Wright Valley in December 2016. Using a gentle lysis technique optimized to preserve longer molecules, combined with a polyenzymatic treatment to maximize yields from different cell types, we isolated high-molecular weight DNA and RNA from ancient paleomat samples. Community composition analysis suggests that the paleomat community may retain a population of indigenous mat cells that may flourish once more favorable conditions are met. In addition to harboring a diverse microbial community, paleomats appear to host heterotrophs in surrounding soils utilizing the deposits as a carbon source. Whole genome long-read PacBio sequencing of native DNA and Illumina metagenomic sequencing of size-sorted DNA (>2,500 nt) indicated possible cell viability, with mat community composed of bacterial taxa. Metagenome assemblies identified genes with predicted roles in nitrogen cycling and complex carbohydrate degradation, and we identified key metabolic pathways such as stress response, DNA repair, and sporulation. Metatranscriptomic data revealed that the most abundant transcripts code for products involved in genetic information processing pathways, particularly translation, DNA replication, and DNA repair. Our results lend new insight into the functional ecology of paleomat deposits, with implications for our understanding of cell biology, Antarctic microbiology and biogeography, and the limits of life in extremely harsh environments.

Bigmouth Buffalo Ictiobus cyprinellus sets freshwater teleost record as improved age analysis reveals centenarian longevity - Lackmann, Alec R.; Andrews, Allen H.; Butler, Malcolm G.; Bielak-Lackmann, Ewelina S.; Clark, Mark E. (Communications Biology, 2019)
Understanding the age structure and population dynamics of harvested species is crucial for sustainability, especially in fisheries. The Bigmouth Buffalo (Ictiobus cyprinellus) is a fish endemic to the Mississippi and Hudson Bay drainages. A valued food-fish for centuries, they are now a prized sportfish as night bowfishing has become a million-dollar industry in the past decade. All harvest is virtually unregulated and unstudied, and Bigmouth Buffalo are declining while little is known about their biology. Using thin-sectioned otoliths and bomb-radiocarbon dating, we find Bigmouth Buffalo can reach 112 years of age, more than quadrupling previous longevity estimates, making this the oldest known freshwater teleost (~12,000 species). We document numerous populations that are comprised largely (85-90%) of individuals over 80 years old, suggesting long-term recruitment failure since dam construction in the 1930s. Our findings indicate Bigmouth Buffalo require urgent attention, while other understudied fishes may be threatened by similar ecological neglect.
Keywords: Ageing; Conservation biology; Freshwater ecology; Ichthyology

Comparing and improving methods for reconstructing peatland water-table depth from testate amoebae - Nolan, Connor; Tipton, John; Booth, Robert K; Hooten, Mevin B; Jackson, Stephen T (The Holocene, 2019)
Proxies that use changes in the composition of ecological communities to reconstruct temporal changes in an environmental covariate are commonly used in paleoclimatology and paleolimnology. Existing methods, such as weighted averaging and modern analog technique, relate compositional data to the covariate in very simple ways, and different methods are seldom compared systematically. We present a new Bayesian model that better represents the underlying data and the complexity in the relationships between species’ abundances and a paleoenvironmental covariate. Using testate amoeba–based reconstructions of water-table depth as a test case, we systematically compare new and existing models in a cross-validation experiment on a large training dataset from North America. We then apply the different models to a new 7500-year record of testate amoeba assemblages from Caribou Bog in Maine and compare the resulting water-table depth reconstructions. We find that Bayesian models represent an improvement over existing methods in three key ways: more complete use of the underlying compositional data, full and meaningful treatment of uncertainty, and clear paths toward methodological improvements. Furthermore, we highlight how developing and systematically comparing methods lead to an improved understanding of the proxy system. This paper focuses on testate amoebae and water-table depth, but the framework and ideas are widely applicable to other proxies based on compositional data.
Keywords: Bayesian statistics; compositional data; Holocene; hydrology; North America; Northeast United States; Paleoclimate; peatlands; statistical methods; testate amoebae

Coupled ocean and atmospheric changes during Greenland stadial 1 in southwestern Europe - Naughton, F.; Costas, S.; Gomes, S.D.; Desprat, S.; Rodrigues, T.; Sanchez Goñi, M.F.; Renssen, H.; Trigo, R.; Bronk-Ramsey, C.; Oliveira, D.; Salgueiro, E.; Voelker, A.H.L.; et al. (Quaternary Science Reviews, 2019)
Paleoclimate reconstructions suggest that the complex variability within the Greenland stadial 1 (GS-1) over western Europe was governed by coupled ocean and atmospheric changes. However, few works from the North Atlantic mid-latitudes document both the GS-1 onset and its termination, which are often considered as single abrupt transition events. Here, we present a direct comparison between marine (alkenone-based sea surface temperatures) and terrestrial (pollen) data, at very high resolution (28 years mean), from the southwestern Iberian shelf record D13882. Our results reveal a rather complex climatic period with internally changing conditions. The GS-1 onset (GS-1a: 12890-12720 yr BP) is marked by a progressive cooling and drying; GS-1b (12720-12390 yr BP) is the coldest and driest phase; GS-1c (12390-12030 yr BP) is marked by a progressive warming and increase in moisture conditions; GS-1 termination (GS-1d: 12030-11770 yr BP) is marked by rapid switches between cool wet, cold dry and cool wet conditions. Although hydroclimate response was very unsteady throughout the GS-1 and in particular during its termination phase, the persistence of an open temperate and Mediterranean forest in southwestern Iberia during the entire episode suggests that at least some moisture was delivered via the Westerlies. We propose coupled ocean and atmospheric mechanisms to reproduce these scenaria. Changes in the strength of the Atlantic Meridional Overturning Circulation (AMOC) as well as variations in the North Atlantic sea-ice growth have favoured the displacement of the polar jet stream's latitudinal position and contributed to a complex spatial pattern and strength of the Westerlies across western Europe.
Keywords: Climate variability; Greenland stadial; Iberian margin; Jet stream; Moisture availability; North Atlantic; Paleoclimate; Westerlies; Younger Dryas Complex

Evaluating the Radiocarbon Reservoir Effect in Lake Kutubu, Papua New GuineaABSTRACT - Schneider, Larissa; Pain, Colin F; Haberle, Simon; Blong, Russell; Alloway, Brent V; Fallon, Stewart J; Hope, Geoff; Zawadzki, Atun; Heijnis, Henk (Radiocarbon, 2019)
Conceptual models predict a tight coupling between the Intertropical Convergence Zone (ITCZ) and the Southern Westerly Winds (SWW) in response to glacial-interglacial transitions, yet little is known about this relationship under Holocene boundary conditions. Here we present a synthesis of Holocene pollen data from the southwest Pacific mid-latitudes that tracks changes in the SWW. Comparison of our SWW paleoclimate records with data tracking the ITCZ, oceanic circulation, and insolation reveals clearly synchronous and in-phase ITCZ-SWW dynamics between 12 and 5 ka, indicating a tight coupling between the tropics and southern mid-latitudes in response to ocean circulation and insolation. An apparent decoupling of the SWW and ITCZ in the Pacific region after 5 ka is attributable to the overriding influence of the El Niño–Southern Oscillation (ENSO) over the proxy data.

Evidence for frequent, large tsunamis spanning locked and creeping parts of the Aleutian megathrust - Witter, Rob; Briggs, Rich; Engelhart, Simon E.; Gelfenbaum, Guy; Koehler, Rich D.; Nelson, Alan; Selle, SeanPaul La; Corbett, Reide; Wallace, Kristi (GSA Bulletin, 2019)
At the eastern end of the 1957 Andreanof Islands, Alaska, USA, moment magnitude 8.6 earthquake rupture, Driftwood Bay (Umnak Island) and Stardust Bay (Sedanka Island) lie along presently locked and creeping parts of the Aleutian megathrust, respectively, based on satellite geodesy onshore. Both bays, located 200 km apart, face the Aleutian trench and harbor coastal evidence for tsunami inundation in 1957. Here we describe the evidence at Driftwood Bay, including eight sheets of landward-fining, normally-graded marine sand that extend up to 375 m inland and 23 m above mean tide level. Drift logs that corroborate historical accounts of 1957 tsunami runup on Umnak Island’s Pacific coast overlie the youngest sand sheet, which 137Cs activity shows was deposited in the decade before 1963. The older sand sheets probably record tsunamis prior to 1957 because an emergent coastal terrace lacks evidence for storm-wave erosion and overwash since ca. 2 ka. Comparisons of the Driftwood Bay and Stardust Bay tsunami histories suggest that at least twice in the past 1700 years inundation occurred at one site but not the other. In contrast, Bayesian age-depth modeling suggests that the two bays may record five tsunamis like the 1957 tsunami, generated by earthquake ruptures that spanned the presently locked and creeping parts of the Aleutian megathrust. However, serial tsunamis occurring within days to centuries cannot be precluded. Our findings imply 164–257-year recurrence intervals for large eastern Aleutian tsunamis and challenge the notion that creeping parts of the megathrust, inferred from geodesy onshore, pose lower earthquake and tsunami hazards than locked areas.

Examining Coastal Dynamics and Archaeological Site Evidence at a Drowned Cirque Basin Influenced by Earthquakes and Little Ice Age Glaciation - Maio, Christopher V.; Crowell, Aron L.; Sullivan, Richard M.; Buzard, Richard M.; Whitley, Matthew A.; Bogardus, Reyce C.; Wit, Cary W. de (Journal of Coastal Research, 2019)
This study contributes baseline information regarding the framework geology, drivers of coastal change, and archaeological record along the fjord-indented coastlines of southcentral Alaska. Field data were collected in July 2015 from James Lagoon, a 30-m-deep drowned cirque valley adjacent to McCarty Fjord in the Nuka Bay region of Kenai Fjords National Park. A 1790 CE terminal moraine deposited by McCarty Glacier extends across the cirque opening and delimits the lagoon. Acoustic surveys of the lagoon reveal bedrock overlain by deltaic, lacustrine, and marine facies containing beds that indicate past submarine landslides. Lagoon and marsh sediment cores contain coarse sand horizons interbedded with silt and peat, evidence of repeated low-frequency, high-intensity events. The largest of the event beds in the marine cores occurs near the surface and is likely associated with the 1964 Great Alaska Earthquake (moment magnitude 9.2). Trees killed during the 1964 earthquake fringe the coastline and indicate ∼2 m of coseismic subsidence. Radiocarbon ages of five exposed subfossil stumps indicate two pre-1964 subsidence events occurring between 1710 and 1789 and 1078 and 1125 median probability calendar year CE (cal CE). A Sugpiaq culture archaeological site dated to 1565 cal CE existed on the western shore of James Lagoon in the interval between these two events, possibly for proximity to an ice floe harbor seal rookery at McCarty Glacier. Archaeological site elevation above mean high water at James Lagoon and around Nuka Bay is inversely related to the extent of cumulative site erosion caused by coastal submergence during the last two great earthquakes. These combined findings lay the groundwork for future research and provide context to ongoing coastal hazards and their effects on cultural resources.

A fluvially derived flood deposit dating to the Kamikaze typhoons near Nagasaki, Japan - Ladlow, Caroline; Woodruff, Jonathan D.; Cook, Timothy L.; Baranes, Hannah; Kanamaru, Kinuyo (Natural Hazards, 2019)
Previous studies in western Kyushu revealed prominent marine-derived flood deposits that date to the late thirteenth-century and are interpreted to be a result of two legendary typhoons linked to the failed Mongol invasions of Japan in 1274 and 1281. The regional persistence and prominence of sediments dating to these “Kamikaze” typhoon events (meaning divine wind) raise questions about the origins of these late thirteenth-century deposits. This is due in part to uncertainty in distinguishing between tsunami and storm-induced deposition. To provide additional insight into the true cause of prominent late thirteenth-century flood deposits in western Kyushu, we present a detailed assessment of an additional event deposit dating to the late thirteenth-century from Lake Kawahara near Nagasaki, Japan. This particular deposit thickens landward towards the primary river flowing into Lake Kawahara and exhibits anomalously low Sr/Ti ratios that are consistent with a fluvial rather than a marine sediment source. When combined with previous flood reconstructions, results support the occurrence of an extreme, late thirteenth-century event that was associated with both intense marine- and river-derived flooding. Results therefore contribute to a growing line of evidence for the Kamikaze typhoons resulting in widespread flooding in the region, rather than the late thirteenth-century deposit being associated with a significant tsunami impact to western Kyushu.

Four centuries of vegetation change in the mid-elevation Andean forests of Ecuador - Huisman, Seringe N.; Bush, Mark B.; McMichael, Crystal N. H. (Vegetation History and Archaeobotany, 2019)
Mid-elevation Andean ecosystems have immense species richness and endemism. Taxonomic composition is known to change through time on the eastern slopes of the Andes as a result of climatic change and disturbance events, both natural and by human actions. Fossil phytoliths can capture local scale vegetation changes, especially among monocotyledonous plants. Phytolith production is high in grasses and palms, plant groups that are particularly sensitive to climatic changes and disturbance events in Andean ecosystems. Here, we reconstruct four centuries of local-scale vegetation change and the corresponding fire history from lake sediment records retrieved from Lagunas Cormorán and Chimerella, located at ca. 1,700 m a.s.l. in the mid-elevation Andean forests of eastern Ecuador. The charcoal analysis of the lake sediments showed no sign of past fires, and no evidence of cultivation was found at either lake. The phytolith assemblages indicated changes in the relative abundances of palms, grasses and trees over the last few centuries, suggesting that mid-elevation Andean phytolith assemblages are sensitive to local scale vegetation dynamics. The largest change in vegetation occurred at the end of the Little Ice Age, at which point the diversity of palm phytoliths decreases. These phytolith assemblages are probably responding to changes in the cloud base position through time, which strongly influences the distributions of many plants and animals.

Four Major Holocene Earthquakes on the Reelfoot Fault Recorded by Sackungen in the New Madrid Seismic Zone, USA - Gold, Ryan D.; DuRoss, Christopher B.; Delano, Jaime E.; Jibson, Randall W.; Briggs, Richard W.; Mahan, Shannon A.; Williams, Robert A.; Corbett, D. Reide (Journal of Geophysical Research: Solid Earth, 2019)
Three sequences of well‐documented, major ~M7+ earthquakes (1811–1812, ~1450, and ~900 CE) in the New Madrid seismic zone, USA, contribute significantly to seismic hazard in the region. However, it is unknown whether this <550‐year recurrence interval has been constant throughout the Holocene given limited geomorphic evidence of prior earthquakes. We extend the record of paleoearthquakes along the Reelfoot fault via investigation of ridgetop gravitational failure features, interpreted as sackungen. The sackungen occur in bluffs along the eastern margin of the Mississippi River floodplain and are concentrated near (<15 km) the southwest dipping Reelfoot reverse fault. A paleoseismic trench excavated across sackungen at the Paw Paw site exposed four packages of colluvial sediment that postdate 30‐ to 11‐ka Peoria Loess. We interpret the colluvial packages to have been deposited following episodic failure of the sackungen as a result of strong ground motions from the following sequence of earthquakes: event 4, 1640 ± 1730 BCE; event 3, 270 ± 670 CE; event 2, 1430 ± 380 CE; and event 1, 1810 ± 50 CE (2 sigma). Event timing corresponds to previously documented earthquakes and represents the longest archive of paleoearthquakes on the Reelfoot fault. If the trenched sackungen record all major Reelfoot fault earthquakes, our observations in combination with prior investigations indicate a period of quiescence from at least 11 to 4.4 ka, followed by four major seismic events culminating in the 1811–1812 CE sequence. This clustered earthquake recurrence pattern helps place bounds on seismic hazard and geodynamic models in the New Madrid seismic zone.

Glacial geology and cosmogenic-nuclide exposure ages from the Tucker Glacier - Whitehall Glacier confluence, northern Victoria Land, Antarctica - Balco, Greg; Todd, Claire; Goehring, Brent M.; Moening-Swanson, Isaac; Nichols, Keir (American Journal of Science, 2019)
We describe glacial-geological observations and cosmogenic-nuclide exposure ages from the vicinity of the present grounding line of Tucker Glacier, a large alpine glacier flowing from the mountains of northern Victoria Land, East Antarctica, into the outer Ross Sea. These data are relevant for constraining the extent of ice sheet expansion and retreat in the Ross Sea, and associated eustatic sea level impact, between the Last Glacial Maximum (LGM) and the present. In addition, a terrestrial geological record of ice thickness change from this region could provide evidence for or against the hypothesis that rapid eustatic sea-level rise during meltwater pulse 1A (“MWP-1A”) at 14.6 ka was in part the result of rapid, large-scale thinning or breakup of a marine-based portion of the LGM ice sheet in the outer Ross Sea. Glacial-geological observations, exposure ages on glacial deposits, and a novel application of in-situ-produced cosmogenic 14C in quartz-bearing bedrock to identify the limits of LGM ice cover in the absence of direct geomorphic evidence, show that Tucker Glacier near its present grounding line was 300 to 350 m thicker than present during the LGM and thinned steadily between 17 to 5 ka. The largest possible rapid thickness change in the time period 14 to 15 ka that could be accommodated by the exposure-age data is ∼50 m, which is a small fraction of that predicted for the western Ross Sea by model simulations of the Antarctic contribution to MWP-1A. There do exist possible scenarios in which hypothesized marine ice sheet collapse in the outer Ross Sea during MWP-1A might not be recorded by ice thickness changes at Tucker Glacier. However, our record of ice thickness changes spanning this time period is the closest such record to the outer Ross Sea that is likely to exist, and it agrees with all exposure-age deglaciation chronologies from other regions of the Ross embayment in providing no evidence for such an event.
Keywords: Antarctica; cosmogenic-nuclide geochemistry; exposure-dating; glacial geology; Last glacial maximum; Ross Sea; Tucker Glacier; Victoria Land

Glacial–interglacial Nd isotope variability of North Atlantic Deep Water modulated by North American ice sheet - Zhao, Ning; Oppo, Delia W.; Huang, Kuo-Fang; Howe, Jacob N. W.; Blusztajn, Jerzy; Keigwin, Lloyd D. (Nature Communications, 2019)
The Nd isotope composition of seawater has been used to reconstruct past changes in the contribution of different water masses to the deep ocean. In the absence of contrary information, the Nd isotope compositions of endmember water masses are usually assumed constant during the Quaternary. Here we show that the Nd isotope composition of North Atlantic Deep Water (NADW), a major component of the global overturning ocean circulation, was significantly more radiogenic than modern during the Last Glacial Maximum (LGM), and shifted towards modern values during the deglaciation. We propose that weathering contributions of unradiogenic Nd modulated by the North American Ice Sheet dominated the evolution of the NADW Nd isotope endmember. If water mass mixing dominated the distribution of deep glacial Atlantic Nd isotopes, our results would imply a larger fraction of NADW in the deep Atlantic during the LGM and deglaciation than reconstructed with a constant northern endmember.

Growth and longevity of Hawaiian grouper (Hyporthodus quernus) — input for management and conservation of a large, slow-growing grouper - Andrews, Allen H.; DeMartini, Edward E.; Brodziak, Jon; Nichols, Ryan S.; Humphreys, Robert L. (Canadian Journal of Fisheries and Aquatic Sciences, 2019)
Hawaiian grouper (Hyporthodus quernus) is endemic to the Hawaiian Islands and is regionally important, yet little is known about its life history. This large species is managed within the Deep 7 bottom fish complex, which includes six snapper species that are assumed to have similar life history traits. Previous age estimates were not validated and suggested a maximum age of 34 years. To evaluate the preliminary study and provide a valid basis for life history parameters, we aged otoliths using bomb radiocarbon (14C) dating. Measured 14C values provided ages for smallest to largest fish that differed from the original study. The fundamental information provided here when evaluating Hawaiian grouper conservation status is longevity (valid to 50 years and estimated to 76 years) — no male sampled was <80 cm total length (TL) and younger than 34 years — and age-at-sexual maturity and age-at-sex change, which were indirectly estimated and compared with prior published estimates for this and other groupers. Updated life history parameters (k = 0.078, L∞ = 95.8 cm TL) should be used to improve future management and conservation assessments.

Holocene and Last Interglacial climate of the Faroe Islands from sedimentary plant wax hydrogen and carbon isotopes - Curtin, Lorelei; D'Andrea, William J.; Balascio, Nicholas; Pugsley, Genevieve; de Wet, Gregory; Bradley, Raymond (Quaternary Science Reviews, 2019)
The Last Interglacial period (LIG) is Earth's most recent globally warm period and is analogous in some ways to projected future global warming. However, questions remain regarding the state of the climate during the LIG in the North Atlantic, a region that is extremely sensitive to changes in oceanic and atmospheric circulation. Here, we present hydrogen and carbon isotope (δD and δ13C) records from a suite of plant wax biomarkers preserved in Holocene and LIG lacustrine sediments from the North Atlantic Faroe Islands and interpret them as qualitative proxies for temperature and hydroclimate variability. These data are used to directly compare LIG and Holocene climate using the same proxy approaches from the same terrestrial location. Measuring multiple isotopes on multiple types of waxes elucidates the sources of homologous plant waxes. We deduce that the δD values of long-chain n-alkanes (C27–C33) and mid-chain n-alkanes (C23–C25) in these sedimentary archives reflect leaf water and lake water δD values, respectively, while the δD values for both long-chain (C28–C30) and mid-chain n-alkanoic acids (C24–C26) primarily represent lake water δD values. Plant wax-inferred δD values of precipitation during the early Holocene (10,100 to 8,200  cal  yr BP) are ∼35‰ more positive than late Holocene values, and decline over the Holocene. δD-inferred hydrologic change and δ13C -inferred plant water use efficiency both indicate that the Faroe Islands became drier throughout the Holocene. Comparison with measurements from LIG plant waxes indicates that late LIG in the Faroe Islands was hydrologically similar to the early-to mid-Holocene (8,200 to 4,000  cal  yr BP), with enriched precipitation isotopes and reduced evapotranspiration indicating a warmer, wetter environment.
Keywords: Holocene; interglacial; North Atlantic; Organic geochemistry; paleoclimatology; Stable isotopes

Holocene glacier fluctuations on the northern flank of Cordillera Darwin, southernmost South America - Hall, B.L.; Lowell, T.V.; Bromley, G.R.M.; Denton, G.H.; Putnam, A.E. (Quaternary Science Reviews, 2019)

A human role in Andean megafaunal extinction? - Raczka, M.F.; Mosblech, N.A.; Giosan, L.; Valencia, B.G.; Folcik, A.M.; Kingston, M.; Baskin, S.; Bush, M.B. (Quaternary Science Reviews, 2019)
A new fossil pollen, Sporormiella, and sediment chemistry record from Lake Llaviucu, Ecuador, spanning the period from 16,280–9000 years Before Present, provides a high-resolution record of paleoecological change in the high Andes. The deglacial transition from super-páramo through páramo grasslands, to Andean forest is traced, with near-modern systems being established by c. 11,900 years ago. It is suggested that forest elements probably existed in microrefugial populations close to the ice front. Sporormiella is used as a proxy for megafaunal abundance, and its decline to background levels is inferred to indicate a local extinction event at c. 12,800 years ago. About 1800 years prior to the extinction, charcoal becomes a regular sedimentary component in this very wet valley. An early date for human activity in the valley is suggested, with the direct implication of humans in the extinction of the megafauna.
Keywords: Andes; Deglaciation; Ecuador Extinction; Fossil pollen; Human arrival; Pleistocene megafauna; Sporormiella

Illuminating microbial species‐specific effects on organic matter remineralization in marine sediments - Mahmoudi, Nagissa; Enke, Tim N.; Beaupré, Steven R.; Teske, Andreas P.; Cordero, Otto X.; Pearson, Ann (Environmental Microbiology, 2019)

In situ cosmogenic 3He and 36Cl and radiocarbon dating of volcanic deposits refine the Pleistocene and Holocene eruption chronology of SW Peru - Bromley, Gordon R. M.; Thouret, Jean-Claude; Schimmelpfennig, Irene; Mariño, Jersy; Valdivia, David; Rademaker, Kurt; del Pilar Vivanco Lopez, Socorro; Team, ASTER; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim (Bulletin of Volcanology, 2019)
Constraining the age of young lavas, which generally fall outside the effective range of traditional geochronology methods, remains a key challenge in volcanology, limiting the development of high-resolution eruption chronologies. We present an in situ cosmogenic 3He and 36Cl surface-exposure chronology, alongside new minimum-limiting 14C ages, documenting young eruptions at five sites in the Western Cordillera, southern Peru. Four 3He-dated lavas on the Nevado Coropuna volcanic complex (hitherto thought to be dormant) indicate that the central dome cluster is young and potentially active; two Holocene lavas on the easternmost dome are the youngest directly dated lavas in Peru to date. East of Coropuna, lava domes and block-lava flows represent the most extensive output to date of Nevado Sabancaya, one of Peru’s most active volcanoes. Two 3He measurements confirm the Holocene age of these deposits and expand the chronology for one of the youngest major lava fields in Peru. 36Cl surface-exposure ages from the Purupurini dome cluster and Nevado Casiri document middle-late-Holocene episodes of effusive activity, while basal 14C ages from a lava-dammed wetland constrain an effusive eruption at Mina Arcata, north of Coropuna, to the late-glacial period. These new data advance the recent Western Cordillera volcanic record whilst demonstrating both the considerable potential and fundamental limitations of cosmogenic surface-exposure methods for such applications.

INFLUENCE OF DIFFERENT ACID TREATMENTS ON THE RADIOCARBON CONTENT SPECTRUM OF SEDIMENTARY ORGANIC MATTER DETERMINED BY RPO/ACCELERATOR MASS SPECTROMETRY - Bao, Rui; McNichol, Ann P.; Hemingway, Jordon D.; Gaylord, Mary C. Lardie; Eglinton, I, Timothy (RADIOCARBON, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Influence of Different Acid Treatments on the Radiocarbon Content Spectrum of Sedimentary Organic Matter Determined by RPO/Accelerator Mass SpectrometryABSTRACT - Bao, Rui; McNichol, Ann P; Hemingway, Jordon D; Lardie Gaylord, Mary C; Eglinton, Timothy I (Radiocarbon, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Lake-level variability in Salar de Coipasa, Bolivia during the past ∼40,000 yrAbstract - Nunnery, J. Andrew; Fritz, Sherilyn C.; Baker, Paul A.; Salenbien, Wout (Quaternary Research, 2019)
Various paleoclimatic records have been used to reconstruct the hydrologic history of the Altiplano, relating this history to past variability of the South American summer monsoon. Prior studies of the southern Altiplano, the location of the world’s largest salt flat, the Salar de Uyuni, and its neighbor, the Salar de Coipasa, generally agree in their reconstructions of the climate history of the past ∼24 ka. Some studies, however, have highly divergent climatic records and interpretations of earlier periods. In this study, lake-level variation was reconstructed from a ∼14-m-long sediment core from the Salar de Coipasa. These sediments span the last ∼40 ka. Lacustrine sediment accumulation was apparently continuous in the basin from ∼40 to 6 ka, with dry or very shallow conditions afterward. The fossil diatom stratigraphy and geochemical data (δ13C, δ15N, %Ca, C/N) indicate fluctuations in lake level from shallow to moderately deep, with the deepest conditions correlative with the Heinrich-1 and Younger Dryas events. The stratigraphy shows a continuous lake of variable depth and salinity during the last glacial maximum and latter stages of Marine Oxygen Isotope Stage 3 and is consistent with environmental inferences and the original chronology of a drill core from Salar de Uyuni.
Keywords: Altiplano; Andes; Paleoclimate; paleohydrology; Paleolake; South America

Mapping Isotopic and Dissolved Organic Matter Baselines in Waters and Sediments of the Gulf of Mexico - Chanton, Jeffrey P.; Jaggi, Aprami; Radović, Jagoš R.; Rosenheim, Brad E.; Walker, Brett D.; Larter, Stephen R.; Rogers, Kelsey; Bosman, Samantha; Oldenburg, Thomas B. P. (Springer International Publishing, 2019)
The Deepwater Horizon oil spill released petroleum hydrocarbons that were depleted in δ13C and Δ14C at depth into the Gulf of Mexico. Stable-carbon and radiocarbon isotopic values and high-resolution mass spectrometry were used to follow the distributions of this petroleum and to track its transformation into petrocarbon, a term used to describe crude oil or transformed crude oil following biodegradation, weathering, oxygenation, or loss of lighter components. The term petrocarbon includes oil- or methane-derived carbon assimilated or incorporated into microbial biomass or into the food web as well as degraded and undegraded petroleum constituents. Here we report (1) the increase in the relative abundance of oxygen-containing carbon compounds making up the dissolved organic matter (DOM) with increasing depth through the water column, indicating the biodegradation of DOM as it was transported to depth in the water column, (2) the finding of 14C depletion in DOM indicating petrocarbon inputs, and (3) the decrease and subsequent increase of 14C in the isotopic composition of sinking particles indicating the capture of petrocarbon in sediment traps. In addition, we discuss the 14C depletion of this material once it is sedimented to the seafloor and the implications for oil spill budgets of seafloor petrocarbon deposition.
Keywords: Dissolved organic matter; FTICR-MS; Gulf baselines; High-resolution mass spectrometry; organic carbon; radiocarbon; Ramped pyrolysis; Sediment organic matter

Millennial-scale carbon accumulation and molecular transformation in a permafrost core from Interior Alaska - Hutchings, J.A.; Bianchi, T.S.; Kaufman, D.S.; Kholodov, A.L.; Vaughn, D.R.; Schuur, E.A.G. (Geochimica et Cosmochimica Acta, 2019)
Organic carbon stored in high-latitude permafrost represents a potential positive feedback to climate warming as well as a valuable store of paleoenvironmental information. The below-freezing conditions have effectively removed permafrost organic material from the modern carbon cycle and preserved its pre-freezing bulk and molecular states. The conditions that lead to efficient burial of organic carbon (OC) within permafrost were investigated by measuring OC stocks, past accumulation rates, and biogeochemical composition of a permafrost core taken from Interior Alaska dating back to 40 ka. The post-glacial Marine Isotope Stage 1 is represented by the top 1.2 m of the core and contains 64.7 kg OC/m2 with an accumulation rate of 4.3 g OC/m2/yr. The sediments that accumulated around the Last Glacial Maximum contain 9.9 kg OC/m2 with an accumulation rate of 0.5 g OC/m2/yr. Carbon storage (144.7 kg OC/m2) and accumulation (26.1 g OC/m2/yr) are both observed to be greatest between 35 and 40 ka, late during the Marine Isotope Stage 3 global interstadial. The extent of OC degradation was assessed using lignin and amino acid biomarkers with both approaches indicating well-preserved contemporary active layer and interstadial OC, whereas stadial OC was highly degraded. Lignin compositional indices throughout the core appear altered by sorptive processes that confounded some expected trends in the overall organic matter composition, while amino acids provided a more integrated pattern of change. Significant correlations between carbon-normalized hydroxyproline and total lignin concentrations further support the usefulness of hydroxyproline as an indicator for the abundance of plant organic matter. A novel amino acid plant-microbial index of the ratio of microbial-specific muramic acid and diaminopimelic acid biomarkers to the plant-specific hydroxyproline biomarker, indicate a transition from plant-dominated organic matter in fresh organic soils (index values of 0.01–0.20) to more microbial-dominated organic matter in degraded mineral soils (index values of 0.50–2.50). The branched glycerol dialkyl glycerol tetraether composition is complex and is not immediately compatible with existing temperature transfer functions. Residence time within the active layer is interpreted to integrate key factors such as primary productivity, inorganic sediment delivery, and other climate factors that control soil organic matter degradation. The Marine Isotope Stage 3, mid-Wisconsin interstadial period at this locality was forest-dominated and suggests the currently prevailing tundra ecotone is sensitive to environmental change. The majority of buried permafrost OC is high in degradability and if thawed, would be expected to be highly vulnerable to microbial decomposition.
Keywords: amino acids; biomarkers; branched GDGTs; lignin phenols; organic carbon; permafrost

Multiple independent records of local glacier variability on Nuussuaq, West Greenland, during the Holocene - Schweinsberg, Avriel D.; Briner, Jason P.; Licciardi, Joseph M.; Bennike, Ole; Lifton, Nathaniel A.; Graham, Brandon L.; Young, Nicolás E.; Schaefer, Joerg M.; Zimmerman, Susan H. (Quaternary Science Reviews, 2019)
The sensitivity of mountain glaciers to small-scale climate fluctuations makes records of their past extent among the best proxies for identifying spatio-temporal climate variability. Here we build on the few existing Holocene records of local glacier change in Greenland by using three independent geochronological methods—proglacial lake sediment analysis, cosmogenic 10Be surface-exposure dating, and in situ 14C burial modeling—to reconstruct continuous records of Holocene glacier variability on Nuussuaq, West Greenland. 10Be ages of perched boulders indicate eastern Nuussuaq was deglaciated between ∼11.0 and 10.5 ka. Radiocarbon-dated sediments from two lakes on Nuussuaq contain mineral-rich layers between ∼9.6 and 9.0 and ∼8.7–8.0 cal ka BP that may be correlative with nearby ice sheet moraines deposited in the early Holocene. Multiple proxies for glacier size indicate frequent, high-amplitude glacier fluctuations superimposed on net glacier growth during the late Holocene, with significant ice expansion phases at ∼3.7 ka, 2.8 ka, and throughout the past ∼2 ka. Mean 10Be ages from five nested moraine crests confirm that local glacier extents on Nuussuaq culminated during both the Little Ice Age [∼1470 C.E. (n = 3) and 1750 C.E. (n = 3)] and the preceding centuries (∼520–1320 C.E.; n = 11). Results reveal that local glaciers on Nuussuaq episodically advanced and retreated at centennial timescales throughout the Holocene, most likely in response to regional climate changes in West Greenland superimposed on the progressive insolation-driven cooling trend in the Northern Hemisphere. Our new 10Be moraine chronologies coupled with other glacier-size proxies corroborate an emerging pattern of significant summer cooling and glacier expansion in the centuries prior to the Little Ice Age in the Arctic.
Keywords: Cosmogenic 10Be; Cosmogenic in situ 14C; Greenland; Holocene; lake sediment; Mountain glaciers; Neoglaciation

MULTI-SUBSTRATE RADIOCARBON DATA CONSTRAIN DETRITAL AND RESERVOIR EFFECTS IN HOLOCENE SEDIMENTS OF THE GREAT SALT LAKE, UTAH - Bowen, Gabriel J.; Nielson, Kristine E.; Eglinton, Timothy I. (RADIOCARBON, 2019)
The radiocarbon (C-14) content of simultaneously deposited substrates in lacustrine archives may differ due to reservoir and detrital effects, complicating the development of age models and interpretation of proxy records. Multi-substrate C-14 studies quantifying these effects remain rare, however, particularly for large, terminal lake systems, which are excellent recorders of regional hydroclimate change. We report C-14 ages of carbonates, brine shrimp cysts, algal mat biomass, total organic carbon (TOC), terrestrial macrofossils, and n-alkane biomarkers from Holocene sediments of the Great Salt Lake (GSL), Utah. C-14 ages for co-deposited aquatic organic substrates are generally consistent, with small offsets that may reflect variable terrestrial organic matter inputs to the system. Carbonates and long-chain n-alkanes derived from vascular plants, however, are similar to 1000-4000 C-14 years older than other substrates, reflecting deposition of pre-aged detrital materials. All lacustrine substrates are C-14-depleted compared to terrestrial macrofossils, suggesting that the reservoir age of the GSL was > 1200 years throughout most of the Holocene, far greater than the modern reservoir age of the lake (similar to 300 years). These results suggest good potential for multi-substrate paleoenvironmental reconstruction from Holocene GSL sediments but point to limitations including reservoir-induced uncertainty in( 14)C chronologies and attenuation and time-shifting of some proxy signals due to detrital effects.

New Last Glacial Maximum ice thickness constraints for the Weddell Sea Embayment, Antarctica - Nichols, Keir A.; Goehring, Brent M.; Balco, Greg; Johnson, Joanne S.; Hein, Andrew S.; Todd, Claire (The Cryosphere, 2019)
We describe new Last Glacial Maximum (LGM) ice thickness constraints for three locations spanning the Weddell Sea Embayment (WSE) of Antarctica. Samples collected from the Shackleton Range, Pensacola Mountains, and the Lassiter Coast constrain the LGM thickness of the Slessor Glacier, Foundation Ice Stream, and grounded ice proximal to the modern Ronne Ice Shelf edge on the Antarctic Peninsula, respectively. Previous attempts to reconstruct LGM-to-present ice thickness changes around the WSE used measurements of long-lived cosmogenic nuclides, primarily Be-10. An absence of post-LGM apparent exposure ages at many sites led to LGM thickness reconstructions that were spatially highly variable and inconsistent with flow line modelling. Estimates for the contribution of the ice sheet occupying the WSE at the LGM to global sea level since deglaciation vary by an order of magnitude, from 1.4 to 14.1m of sea level equivalent. Here we use a short-lived cosmogenic nuclide, in situ-produced C-14, which is less susceptible to inheritance problems than Be-10 and other long-lived nuclides. We use in situ C-14 to evaluate the possibility that sites with no post-LGM exposure ages are biased by cosmogenic nuclide inheritance due to surface preservation by cold-based ice and non-deposition of LGM-aged drift. Our measurements show that the Slessor Glacier was between 310 and up to 655m thicker than present at the LGM. The Foundation Ice Stream was at least 800m thicker, and ice on the Lassiter Coast was at least 385m thicker than present at the LGM. With evidence for LGM thickening at all of our study sites, our in situ C-14 measurements indicate that the long-lived nuclide measurements of previous studies were influenced by cosmogenic nuclide inheritance. Our inferred LGM configuration, which is primarily based on minimum ice thickness constraints and thus does not constrain an upper limit, indicates a relatively modest contribution to sea level rise since the LGM of < 4.6 m, and possibly as little as < 1.5 m.

On the Origin of Aged Sedimentary Organic Matter Along a River‐Shelf‐Deep Ocean Transect - Bao, Rui; Zhao, Meixun; McNichol, Ann; Wu, Ying; Guo, Xinyu; Haghipour, Negar; Eglinton, Timothy I. (Journal of Geophysical Research: Biogeosciences, 2019)
To assess the influences of carbon sources and transport processes on the C-14 age of organic matter (OM) in continental margin sediments, we examined a suite of samples collected along a river-shelf-deep ocean transect in the East China Sea (ECS). Ramped pyrolysis-oxidiation was conducted on suspended particulate matter in the Yangtze River and on surface sediments from the ECS shelf and northern Okinawa Trough. C-14 ages were determined on OM decomposition products within different temperature windows. These measurements suggest that extensive amounts of pre-old (i.e., millennial age) organic carbon (OC) are subject to degradation within and beyond the Yangtze River Delta, and this process is accompanied by an exchange of terrestrial and marine OM. These results, combined with fatty acid concentration data, suggest that both the nature and extent of OM preservation/degradation as well as the modes of transport influence the C-14 ages of sedimentary OM. Additionally, we find that the age of (thermally) refractory OC increases during across-shelf transport and that the age offset between the lowest and highest temperature OC decomposition fractions also increases along the shelf-to-trough transect. Amplified interfraction spread or C-14 heterogeneity is the greatest in the Okinawa Trough. Aged sedimentary OM across the transect may be a consequence of several reasons including fossil OC input, selective degradation of younger OC, hydrodynamic sorting processes, and aging during lateral transport. Consequently, each of them should be considered in assessing the C-14 results of sedimentary OM and its implications for the carbon cycle and interpretation of sedimentary records.
Keywords: Carbon cycle; hydrodynamic processes; organic carbon; radiocarbon; sediments

Pacific climate influences on ocean conditions and extreme shell growth events in the Northwestern Atlantic (Gulf of Maine) - Wanamaker, Alan D.; Griffin, Shelly M.; Ummenhofer, Caroline C.; Whitney, Nina M.; Black, Bryan; Parfitt, Rhys; Lower-Spies, Erin E.; Introne, Douglas; Kreutz, Karl J. (Climate Dynamics, 2019)
The Gulf of Maine is undergoing rapid environmental and ecological changes, yet our spatial and temporal understanding of the climatic and hydrographic variability in this region, including extreme events, is limited and biased to recent decades. In this study, we utilize a highly replicated, multi-century master shell growth chronology derived from the annual increments formed in the shells of the long-lived bivalve Arctica islandica collected in 38 m from the central coastal region in the Gulf of Maine. Our results indicate that shell growth is highly synchronous and inversely related to local seawater temperatures. Using composite analyses of extreme shell growth events from CE 1900 to 2013, we extend our understanding of the factors driving oceanic variability and shell growth in the Northwestern Atlantic back to CE 1761. We suggest that extreme shell growth events are primarily controlled by Gulf of Maine sea surface temperature (SST) and stratification conditions, which in turn appear to be largely influenced by SST patterns in the Pacific Ocean through their influence on mid-latitude atmospheric circulation patterns and the location of the eddy-driven jet. The large-scale jet dynamics during these extreme years manifest as precipitation and moisture transport anomalies and regional SST conditions in the Gulf of Maine that either enhance or inhibit shell growth. Pacific climate variability is thus an important, yet understudied, influence on Gulf of Maine ocean conditions.

Petrocarbon evolution: Ramped pyrolysis/oxidation and isotopic studies of contaminated oil sediments from the Deepwater Horizon oil spill in the Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Lardie-Gaylord, Mary; McNichol, Ann; Rosenheim, Brad E.; Montoya, Joseph P.; Chanton, Jeffrey P. (PLOS ONE, 2019)
Hydrocarbons released during the Deepwater Horizon (DWH) oil spill weathered due to exposure to oxygen, light, and microbes. During weathering, the hydrocarbons' reactivity and lability was altered, but it remained identifiable as "petrocarbon" due to its retention of the distinctive isotope signatures (C-14 and C-13) of petroleum. Relative to the initial estimates of the quantity of oil-residue deposited in Gulf sediments based on 2010-2011 data, the overall coverage and quantity of the fossil carbon on the seafloor has been attenuated. To analyze recovery of oil contaminated deep-sea sediments in the northern Gulf of Mexico we tracked the carbon isotopic composition (C-13 and C-14, radiocarbon) of bulk sedimentary organic carbon through time at 4 sites. Using ramped pyrolysis/oxidation, we determined the thermochemical stability of sediment organic matter at 5 sites, two of these in time series. There were clear differences between crude oil (which decomposed at a lower temperature during ramped oxidation), natural hydrocarbon seep sediment (decomposing at a higher temperature; Delta C-14 = -189 parts per thousand) and our control site (decomposing at a moderate temperature; Delta C-14 = -189 parts per thousand), in both the stability (ability to withstand ramped temperatures in oxic conditions) and carbon isotope signatures. We observed recovery toward our control site bulk Delta C-14 composition at sites further from the wellhead in similar to 4 years, whereas sites in closer proximity had longer recovery times. The thermographs also indicated temporal changes in the composition of contaminated sediment, with shifts towards higher temperature CO2 evolution over time at a site near the wellhead, and loss of higher temperature CO2 peaks at a more distant site.
Keywords: C-14 ANALYSES; MARINE SNOW; degradation; fractionation; organic-matter; POLYCYCLIC AROMATIC-HYDROCARBONS; MICROBIAL COMMUNITY RESPONSE; radiocarbon; STABLE CARBON; surface sediments

Radiocarbon age of different photoreactive fractions of freshwater dissolved organic matter - Ishikawa, Naoto F.; Butman, David; Raymond, Peter A. (Organic Geochemistry, 2019)
Dissolved organic carbon (DOC) plays a major role in aquatic carbon cycling. In order to determine if DOC photolability was related to DOC age, we tested the effect of oxidation time using UV irradiation on natural radiocarbon concentrations (Δ14C) of DOC in six US rivers. The most photo-labile DOC was 14C youngest. After a 100 min UV irradiation, most DOC (>93%) was oxidized in two out of the six rivers studied. On the other hand, the other four rivers still had a considerable amount (>20%) of DOC resistant to UV oxidation, which showed lower Δ14C values than those of bulk DOC. We also found that the concentration and Δ14C value of bulk DOC are controlled by the photochemically intermediate fraction. The results suggest that 14C age of organic matter is not homogeneous within DOC, the degree of which may depend on the characteristics unique to rivers.
Keywords: dissolved organic carbon; Mixing model; Oxidation time; UV irradiation; Δ14C

Salt marsh ecosystem restructuring enhances elevation resilience and carbon storage during accelerating relative sea-level rise - Gonneea, Meagan Eagle; Maio, Christopher V.; Kroeger, Kevin D.; Hawkes, Andrea D.; Mora, Jordan; Sullivan, Richard; Madsen, Stephanie; Buzard, Richard M.; Cahill, Niamh; Donnelly, Jeffrey P. (Estuarine, Coastal and Shelf Science, 2019)
Salt marshes respond to sea-level rise through a series of complex and dynamic bio-physical feedbacks. In this study, we found that sea-level rise triggered salt marsh habitat restructuring, with the associated vegetation changes enhancing salt marsh elevation resilience. A continuous record of marsh elevation relative to sea level that includes reconstruction of high-resolution, sub-decadal, marsh elevation over the past century, coupled with a lower-resolution 1500-year record, revealed that relative sea-level rose 1.5 ± 0.4 m, following local glacial isostatic adjustment (1.2 mm/yr). As sea-level rise has rapidly accelerated, the high marsh zone dropped 11 cm within the tidal frame since 1932, leading to greater inundation and a shift to flood- and salt-tolerant low marsh species. Once the marsh platform fell to the elevation favored by low-marsh Spartina alterniflora, the elevation stabilized relative to sea level. Currently low marsh accretion keeps pace with sea-level rise, while present day high marsh zones that have not transitioned to low marsh have a vertical accretion deficit. Greater biomass productivity, and an expanding subsurface accommodation space favorable for salt marsh organic matter preservation, provide a positive feed-back between sea-level rise and marsh platform elevation. Carbon storage was 46 ± 28 g C/m2/yr from 550 to 1800 CE, increasing to 129 ± 50 g C/m2/yr in the last decade. Enhanced carbon storage is controlled by vertical accretion rates, rather than soil carbon density, and is a direct response to anthropogenic eustatic sea-level rise, ultimately providing a negative feedback on climate warming.
Keywords: 14-Carbon; accretion; Carbon storage; Elevation; Salt marsh; Sea level index point; sea-level rise

Sediment accumulation and sedimentation rates in playas on the High Plains of western Kansas, USA - Bowen, Mark W.; Johnson, William C. (Geomorphology, 2019)
Grassland ecosystems are some of the most modified ecosystems in the world, largely due to conversion to cropland, and the High Plains of the central United States is no exception. Playa wetlands are ubiquitous features of the High Plains and have experienced increased sediment accumulation, which is the primary cause of reduced playa ecosystem function. Seven playas on the High Plains of western Kansas, five with cropland-dominated watersheds and two with grassland-dominated watersheds, were examined to quantify the amount of recent (past ~100–175 yr) sediment accumulated within playas and to establish chronologies of playa filling. Thicknesses of recent sediment were determined in the field, and soil cores were extracted from study playas. Four playa cores were analyzed for 210Pb to establish the chronology of recent sediment accumulation and sedimentation rates. Chronologies of pre-agricultural sediments and sedimentation rates were calculated by 14C dating of buried soils preserved within playa cores. Radiocarbon ages indicate playa stratigraphic records span the Holocene and that these playas have persisted on the landscape since at least the Late Pleistocene. Long-term, natural sedimentation rates were highest during the Pleistocene-Holocene transition and early Holocene, at ~2–4 cm/century. During the middle and late Holocene, sedimentation rates averaged ~1 cm/century. Cropland playas accumulated ~10–15 cm of recent sediment at average rates of ~6.5–10 cm/century, while grassland playas accumulated only ~2 cm of recent sediment. Conversion of watersheds to cropland has greatly accelerated sediment accumulation within playas, which is generally resulting in a decline in critical playa ecosystem functions.
Keywords: 210Pb; Agricultural; chronology; Holocene; Radiocarbon dating; sedimentation

Sources of carbon to suspended particulate organic matter in the northern Gulf of Mexico - Rogers, Kelsey L.; Bosman, Samantha H.; Weber, Sarah; Magen, Cedric; Montoya, Joseph P.; Chanton, Jeffrey P. (Elem Sci Anth, 2019)
Suspended particulate organic carbon (POCsusp) in the Gulf of Mexico is unique compared to other seas and oceans. In addition to surface primary production, isotopic analysis indicates that microbial cycling of oil and riverine inputs are primary sources of carbon to POCsusp in the Gulf. To characterize POCsusp from seep sites and non-seep north central Gulf (NCG) sites potentially affected by the Deepwater Horizon (DWH) spill, we analyzed 277 and 123 samples for δ13C and Δ1C signatures, respectively. Depth, partitioned into euphotic (300 m), was the main driver of spatial δ13C differences, with deep depths exhibiting 13C depletion. Both deep depths and proximity to sources of natural seepage resulted in 14C depletion. A two-endmember mixing model based on Δ14C indicated that sources to POCsusp were 14–29% fossil carbon at NCG sites and 19–57% at seep sites, with the balance being modern surface production. A six-component Bayesian mixing model MixSIAR, using both 13C and 14C, suggested that riverine inputs were an important carbon source to POCsusp contributing 34–46%. The influence of seeps was localized. Below the euphotic zone at seep sites, 46 ± 5% (n = 9) of the carbon in POCsusp was derived from environmentally degraded, transformed oil; away from seeps, transformed oil contributed 15 ± 4% (n = 39). We hypothesized that, at NCG sites removed from hydrocarbon seep sources, isotopic signatures would be depleted following the spill and then shift towards background-like enriched values over time. At deep depths we observed decreasing Δ14C signatures in POCsusp from 2010 to 2012, followed by isotopic enrichment from 2012 to 2014 and a subsequent recovery rate of 159‰ per year, consistent with this hypothesis and with biodegraded material from DWH hydrocarbons contributing to POCsusp.

Springwater provenance and flowpath evaluation in Blue Lake, Bonneville basin, Utah - Lerback, Jory Chapin; Hynek, Scott A.; Bowen, Brenda B.; Bradbury, Christopher D.; Solomon, D. Kip; Fernandez, Diego P. (Chemical Geology, 2019)
Water in Utah and Nevada is important for agriculture, municipal use, solute transport, and ecosystem preservation. Large spring wetland systems occur on the playa margin of the Bonneville basin, including Blue Lake, 15 km south of the Bonneville Salt Flats on the Utah-Nevada state border. Large spring systems have historically been studied as water budgets don't apparently balance from direct mountain front recharge (Nelson and Mayo, 2014; Gardner and Heilweil, 2014; and others). Blue Lake is no exception; prior studies here have suggested discharge rates 0.04 - 0.05 km3/yr (Louderback and Rhode, 2009), greater than expected for modelled recharge in the surrounding mountain range (0.03 km3/yr). Three hypothesized recharge mechanisms for Blue Lake are tested: mountain-front recharge, interbasinal groundwater flow, and infiltration from historic Lake Bonneville. Remote sensing suggests that a conservative estimate of Blue Lake discharge constitutes 50-64% of modelled mountain-front recharge (Flint et al., 2011). Major ions, δ18O, δ2H, dissolved gases (14C, 3He, 4He, Ne, Ar, Kr, Xe) and trace elements (Sr and 87Sr/86Sr isotopes) comprehensively constrain recharge conditions, water-rock interactions, flowpaths, and groundwater provenance of this large spring system. 14C signatures suggest that Blue Lake discharge has a transit time between 5,600 and 12,200 years, older than that of Fish Springs. Noble gas concentrations in Blue Lake water suggest an elevated recharge temperature greater than 19°C and low salinity, indicating a deep water table and high geothermal gradient in the recharge area. 87Sr/86Sr ratios of playa-margin springs are elevated from that of mid-playa groundwaters, springwaters from the adjacent mountain range, and alluvial fill groundwater from the valley directly south of Blue Lake. Playa-margin spring Sr isotope values (0.713-0.714) are most similar to direct runoff from the Deep Creek Range granodiorite outcrop (>0.713). Interbasinal groundwater flow in combination with mountain-front recharge is best supported by chemical data rather than mountain-front recharge alone or the slow discharge of regional aquifers recharged by lacustrine infiltration from Lake Bonneville.
Keywords: Bonneville basin; Geochemistry; groundwater; Isotope chemistry

Temporal constraints on lateral organic matter transport along a coastal mud belt - Bao, Rui; Zhao, Meixun; McNichol, Ann; Galy, Valier; McIntyre, Cameron; Haghipour, Negar; Eglinton, Timothy I. (Organic Geochemistry, 2019)
Constraints on timescales of lateral transport of sedimentary organic carbon (OC) over continental shelves and associated influences on the distribution and abundance of OC remain sparse. Preferential degradation of labile, young OC during lateral transport results in apparent “diagenetic aging” of OC. Additionally, sediment translocation can also result in “transport time-associated aging” of associated organic matter (OM) as a function of the lateral transport time (LTT). Here, we use a coupled thermal decomposition and radiocarbon (14C) approach to constrain timescales of lateral transport and concomitant loss of OC associated with different grain size fractions of sediments collected from two locations ∼275 km apart along a dispersal pathway on the inner shelf of the East China Sea. The 14C age contrasts between corresponding thermal fractions are used to distinguish these two components of sedimentary OM “aging”. To minimize interferences from hydrodynamic sorting and diagenetic aging of OC accompanying lateral transport, we assess 14C age differences of decomposition products from the most thermally-refractory OC components associated with specific grain size fractions between locations. We show that LTTs vary among different grain size fractions, and examine relationships between LTTs and sedimentary OC loss in order to assess the decomposition of OC as a consequence of lateral transport. We suggest that the decomposition of OC associated with protracted lateral transport exerts a strong influence on OC burial efficiency, with broad implications for carbon cycling over continental shelves.
Keywords: 14C aging; Continental shelf seas; East China Sea; Mud belt; organic matter; Sediment resuspension

The Utility of Stable and Radioisotopes in Fish Tissues as Biogeochemical Tracers of Marine Oil Spill Food Web Effects - Patterson III, William F.; Chanton, Jeffery P.; Hollander, David J.; Goddard, Ethan A.; Barnett, Beverly K.; Tarnecki, Joseph H. (Springer International Publishing, 2019)
Direct exposure to petroleum compounds was widely reported for a variety of taxa following the DWH. Evidence of exposure ranged from oiling of skin, shells, or feathers, depending on the taxa, to observation of ingested oil in small translucent, invertebrates, to biomarkers of petroleum compounds within an organism’s tissues, such as PAHs in the hepatopancreas of invertebrates or the liver of fishes, or metabolic products of PAH catabolism in the bile of various vertebrate taxa. Development of natural biogeochemical tracers to examine indirect effects, especially over long (months to years) time scales, can be much more problematic. In this chapter, we describe the utility of employing stable isotopes and radioisotopes to 1) examine whether food web effects can be inferred from shifts in stable isotope values measured in vertebrate taxa; 2) examine the assimilation and trophic transfer of petrocarbon in marine food webs; and, 3) serve as long-term biogeochemical tracers either of petrocarbon assimilation or trophic shifts that are indicative of food web effects of marine oil spills. Data and analyses are largely drawn from DWH-related studies but with broader implications to marine oil spills in general.
Keywords: Petrocarbon; radiocarbon; Reef fish; Stable isotopes

Aging and Molecular Changes of Dissolved Organic Matter Between Two Deep Oceanic End-Members - Bercovici, S. K.; Koch, B. P.; Lechtenfeld, O. J.; McCallister, S. L.; Schmitt-Kopplin, P.; Hansell, D. A. (Global Biogeochemical Cycles, 2018)
The global ocean contains a massive reservoir of dissolved organic carbon (DOC), rivaling the atmosphere's pool of CO2. The most recalcitrant fractions have mean radiocarbon ages of ~4,000 years in the Atlantic to ~6,000 years in the Pacific. Knowing the radiocarbon signatures of DOC and the molecular composition of dissolved organic matter (DOM) is crucial to develop understanding of the persistence and lifetime of the DOC pool. In this research, we collected samples from the deep North Pacific in August 2013 (aboard the RV Melville) to couple the Δ14C content of solid‐phase‐extracted DOM (Δ14C‐SPE‐DOM) with its molecular composition in the ocean's oldest deep waters. We find that deep waters in this region held a mean Δ14C‐SPE‐DOM value of −554 ± 9‰ (~6,400 14C years), substantially more depleted than that in the deep Atlantic, which held a mean Δ14C‐SPE‐DOM value of −445 ± 5‰. While we find a more degraded molecular composition of DOM in the deep Pacific than the deep Atlantic, the molecular formulae within the Island of Stability (Lechtenfeld et al., 2014, https://doi.org/10.1016/j.gca.2013.11.009), are largely retained. These results imply that a fraction of deep DOM is resistant to removal and present in both the deep Atlantic and Pacific Oceans.

A centuries-long delay between a paleo-ice-shelf collapse and grounding-line retreat in the Whales Deep Basin, eastern Ross Sea, Antarctica - Bart, Philip J.; DeCesare, Matthew; Rosenheim, Brad E.; Majewski, Wojceich; McGlannan, Austin (Scientific Reports, 2018)
Recent thinning and loss of Antarctic ice shelves has been followed by near synchronous acceleration of ice flow that may eventually lead to sustained deflation and significant contraction in the extent of grounded and floating ice. Here, we present radiocarbon dates from foraminifera that constrain the time elapsed between a previously described paleo-ice-shelf collapse and the subsequent major grounding-line retreat in the Whales Deep Basin (WDB) of eastern Ross Sea. The dates indicate that West Antarctic Ice Sheet (WAIS) grounding-line retreat from the continental shelf edge was underway prior to 14.7 ± 0.4 cal kyr BP. A paleo-ice-shelf collapse occurred at 12.3 ± 0.2 cal kyr BP. The grounding position was maintained on the outer-continental shelf until at least 11.5 ± 0.3 cal kyr BP before experiencing a 200-km retreat. Given the age uncertainties, the major grounding-line retreat lagged ice-shelf collapse by at least two centuries and by as much as fourteen centuries. In the WDB, the centuries-long delay in the retreat of grounded ice was partly due to rapid aggradational stacking of an unusually large volume of grounding-zone-wedge sediment as ice-stream discharge accelerated following ice-shelf collapse. This new deglacial reconstruction shows that ongoing changes to ice shelves may trigger complex dynamics whose consequences are realized only after a significant lag.

Combining Conflicting Bayesian Models to Develop Paleoseismic Records: An Example from the Wasatch Fault Zone, Utah - DuRoss, Christopher B.; Bennett, Scott E. K.; Briggs, Richard W.; Personius, Stephen F.; Gold, Ryan D.; Reitman, Nadine G.; Hiscock, Adam I.; Mahan, Shannon A. (Bulletin of the Seismological Society of America, 2018)
Bayesian statistical analyses of paleoseismic data result in the probabilistic determination of earthquake times using geochronological data evaluated in the context of a stratigraphic model. However, a fundamental problem in paleoseismology is how to use the Bayesian approach to model sparse and/or conflicting geochronological datasets, such as those derived from sites exhibiting episodic sedimentary and pedogenic processes in moderate‐ to high‐energy environments (e.g., a normal‐faulted alluvial fan). Using paleoseismic data for the Corner Canyon site on the Salt Lake City segment of the Wasatch fault zone (Utah), we develop an approach by which multiple Bayesian models are combined to generate an earthquake history at a site. This approach accommodates mutually exclusive interpretations of the geochronological data and thereby limits the influence of sparse data, stratigraphically inconsistent ages, or a single, subjective model interpretation. For the Corner Canyon site, we integrate four OxCal Bayesian models to generate a chronology of six events between ∼4.8 and ∼0.5  ka. Late Holocene (post‐5 ka) mean recurrence and vertical slip‐rate estimates are ∼0.9  ky (0.7–1.0 ky; 95% confidence) and 1.1  mm/yr (0.8–1.7  mm/yr range), respectively. Although our method increases the uncertainty in the timing of individual earthquakes, it more objectively accounts for potential geochronological errors and different interpretations of stratigraphic age control. By relaxing the need to select a single age model, our approach yields more accurate earthquake‐timing results that will better facilitate evaluations of along‐fault event correlation and earthquake rupture length.

Decreased sedimentation efficiency of petro- and non-petro-carbon caused by a dispersant for Macondo surrogate oil in a mesocosm simulating a coastal microbial community - Xu, Chen; Zhang, Saijin; Beaver, Morgan; Wozniak, Andrew; Obeid, Wassim; Lin, Youmin; Wade, Terry L.; Schwehr, Kathleen A.; Lin, Peng; Sun, Luni; Hatcher, Patrick G.; Chin, Wei-Chun; et al. (Marine Chemistry, 2018)
Large amounts of mucous-rich oil-containing marine snow formed in surface waters adjacent to the Deepwater Horizon spill. This marine oil snow (MOS) was implicated in oil delivery to the seafloor. Whether the use of chemical dispersants increased or decreased MOS sedimentation remains controversial. We conducted mesocosm experiments testing the effects of oil and oil plus a dispersant on MOS formation and sedimentation, in coastal seawater. The four treatments used were a surrogate Macondo oil water accommodated fraction (“WAF”), two concentrations of chemically-enhanced WAF (“CEWAF” and diluted CEWAF, “DCEWAF”) containing a dispersant and oil, and Controls (no additions). Based on radiocarbon and 13C NMR results, the presence of dispersants enhanced the amounts of petro-carbon being incorporated into the sinking oil-carrying aggregates (aka MOS). However, most of the chemically-dispersed oil preferentially partitioned into the colloidal and suspended particulate fractions rather than into the rapidly forming MOS. Thus the oil and non-petro-carbon sedimentation efficiency in treatments with a dispersant was much lower, compared to those in the Control and WAF treatments, during the four-day mesocosm experiment. Formation of MOS and its subsequent sinking sequestered the oil in two stages: first via terrestrial-derived detritus containing humic compounds, and subsequently via freshly produced material, such as exopolymeric substances produced by phytoplankton and bacteria.

Dimensions of Radiocarbon Variability within Sedimentary Organic MatterABSTRACT - Bao, Rui; McNichol, Ann P; McIntyre, Cameron P; Xu, Li; Eglinton, Timothy I (Radiocarbon, 2018)
Organic carbon (OC) radiocarbon (14C) signatures in marine surface sediments are highly variable and the causes of this heterogeneity remain ambiguous. Here, we present results from a detailed 14C-based investigation of an Arabian Sea sediment, including measurements on organic matter (OM) in bulk sediment, specific grain size fractions, and OC decomposition products from ramped-pyrolysis-oxidation (RPO). Our results show that 14C ages of OM increase with increasing grain size, suggesting that grain size is an important factor controlling the 14C heterogeneity in marine sediments. Analysis of RPO decomposition products from different grain size fractions reveals an overall increase in age of corresponding thermal fractions from finer to coarser fractions. We suggest that hydrodynamic properties of sediment grains exert the important control on the 14C age distribution of OM among grain size fractions. We propose a conceptual model to account for this dimensionality in 14C variability that invokes two predominant modes of OM preservation within different grain size fractions of Arabian Sea sediment: finer (<63 μm) fractions are influenced by OM-mineral grain aggregation processes, giving rise to relatively uniform 14C ages, whereas OM preserved in coarser (>63 μm) fractions includes materials encapsulated within microfossils and/or entrained fossil (14C-depleted) OC hosted in detrital mineral grains. Our findings highlight the value of RPO for assessment of 14C age variability in sedimentary OC, and for assessing mechanisms of OM preservation in aquatic sediments.
Keywords: arabian sea; grain size; hydrodynamic processes; organicmatter; radiocarbon; ramped pyrolysis-oxidation

Five Younger Dryas black mats in Mexico and their stratigraphic and paleoenvironmental context - Israde-Alcántara, Isabel; Domínguez-Vázquez, G.; Gonzalez, S.; Bischoff, J.; West, A.; Huddart, D. (Journal of Paleolimnology, 2018)
The Younger Dryas interval (YD) was a period of widespread, abrupt climate change that occurred between 12,900 and 11,700 cal yr BP (10,900–10,000 14C BP). Many sites in the Northern Hemisphere preserve a sedimentary record across the onset of the YD interval, including sites investigated in sedimentary basins located in central Mexico (Chapala, Cuitzeo, Acambay), the Basin of Mexico (Tocuila), and northern Mexico (El Cedral). Deposits consist of lacustrine or marginal lake sediments that were deposited during the Pleistocene and the Holocene. At the Tocuila and Acambay sites, Pleistocene fossil vertebrate assemblages, mainly mammoths (Mammuthus columbi), are found in association with a distinctive organic layer, sometimes called the black mat that formed during the YD. At the Chapala, Cuitzeo, Acambay, and Tocuila sites the black mats contain a suite of distinctive microscopic and mineralogical signatures and are accompanied by a sharp change in the depositional environments as supported by diatom and pollen studies reported here. The signatures include magnetic, Fe-rich microspherules, silica melted droplets with aerodynamic shapes (tektites), large amounts of charcoal, and sometimes nanodiamonds (Cuitzeo), all of which were deposited at the onset of the YD. The geochemistry of the microspherules indicates that they are not anthropogenic, authigenic or of cosmic or volcanic origin, and instead, were produced by melting and quenching of terrestrial sediments. Here, we present the stratigraphy at five field sites, the analyses of magnetic microspherules, including major element composition and scanning electron microscopy images. All of these materials are associated with charcoal and soot, which are distinctive stratigraphic markers for the YD layer at several sites in Mexico.

On the Holocene evolution of the Ayeyawady megadelta - Giosan, Liviu; Naing, Thet; Min Tun, Myo; Clift, Peter D.; Filip, Florin; Constantinescu, Stefan; Khonde, Nitesh; Blusztajn, Jerzy; Buylaert, Jan-Pieter; Stevens, Thomas; Thwin, Swe (Earth Surface Dynamics, 2018)
The Ayeyawady delta is the last Asian megadelta whose evolution has remained essentially unexplored so far. Unlike most other deltas across the world, the Ayeyawady has not yet been affected by dam construction, providing a unique view on largely natural deltaic processes benefiting from abundant sediment loads affected by tectonics and monsoon hydroclimate. To alleviate the information gap and provide a baseline for future work, here we provide a first model for the Holocene development of this megadelta based on drill core sediments collected in 2016 and 2017, dated with radiocarbon and optically stimulated luminescence, together with a reevaluation of published maps, charts and scientific literature. Altogether, these data indicate that Ayeyawady is a mud-dominated delta with tidal and wave influences. The sediment-rich Ayeyawady River built meander belt alluvial ridges with avulsive characters. A more advanced coast in the western half of the delta (i.e., the Pathein lobe) was probably favored by the more western location of the early course of the river. Radiogenic isotopic fingerprinting of the sediment suggests that the Pathein lobe coast does not receive significant sediment from neighboring rivers. However, the eastern region of the delta (i.e., Yangon lobe) is offset inland and extends east into the mudflats of the Sittaung estuary. Wave-built beach ridge construction during the late Holocene, similar to several other deltas across the Indian monsoon domain, suggests a common climatic control on monsoonal delta morphodynamics through variability in discharge, changes in wave climate or both. Correlation of the delta morphological and stratigraphic architecture information on land with the shelf bathymetry, as well as its tectonic, sedimentary and hydrodynamic characteristics, provides insight on the peculiar growth style of the Ayeyawady delta. The offset between the western Pathein lobe and the eastern deltaic coast appears to be driven by tectonic–hydrodynamic feedbacks as the extensionally lowered shelf block of the Gulf of Mottama amplifies tidal currents relative to the western part of the shelf. This situation probably activates a perennial shear front between the two regions that acts as a leaky energy fence. Just as importantly, the strong currents in the Gulf of Mottama act as an offshore-directed tidal pump that helps build the deep mid-shelf Mottama clinoform with mixed sediments from the Ayeyawady, Sittaung and Thanlwin rivers. The highly energetic tidal, wind and wave regime of the northern Andaman Sea thus exports most sediment offshore despite the large load of the Ayeyawady River.

Holocene history of the Greenland Ice-Sheet margin in Northern Nunatarssuaq, Northwest Greenland - Farnsworth, Lauren B.; Kelly, Meredith A.; Bromley, Gordon R. M.; Axford, Yarrow; Osterberg, Erich C.; Howley, Jennifer A.; Jackson, Margaret S.; Zimmerman, Susan R. (arktos, 2018)
Records of past Greenland Ice-Sheet (GrIS) extents are important for understanding the response of the ice sheet to climate conditions, providing a longer term perspective on present ice-margin fluctuations, and evaluating ice-sheet models. We present a record of Holocene GrIS extents in Nunatarssuaq, Northwest Greenland, based on geomorphic mapping combined with 10Be surface exposure dating of rock surfaces and 14C dating of subfossil plants. 10Be ages of boulders and bedrock exposed during deglaciation from the Last Glacial Maximum range from ~ 81 to 15 ka. The apparently old ages of some samples and scatter in the dataset indicate the presence of 10Be inherited from prior periods of exposure and suggest that overriding ice was minimally erosive. Subfossil plants exposed on a debris band in the GrIS margin date to ~ 4.7 cal ka BP and register a time when the Northwest GrIS was smaller than at present. Geomorphic evidence, including a drift sheet, grounding-line moraines, and higher levels of Nordsø, document an advance of the Nuna and Tunge Rampen (GrIS outlet glaciers). 14C ages of in situ subfossil plants and 10Be ages of boulders bracket this advance to ~ 3.2–2.1 ka, a period of regional cooling. Unweathered, lichen-free drift occurs < 50 m beyond the present GrIS margin in most locations. 10Be ages of this drift are 2.2–0.5 ka and likely contain inherited nuclides. 14C ages of in situ subfossil plants atop this drift are between cal AD ~ 1640 and 2001, suggesting recent ice-margin fluctuations.

Holocene mountain glacier history in the Sukkertoppen Iskappe area, southwest Greenland - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Lifton, Nathaniel A.; Bennike, Ole; Graham, Brandon L. (Quaternary Science Reviews, 2018)
Mountain glaciers and ice caps (GIC) independent of the Greenland Ice Sheet respond rapidly to climate variations and records of their past extent provide information on the natural envelope of climate variability. Here, we use a multi-proxy approach that combines proglacial lake sediment analysis, cosmogenic nuclide surface-exposure dating (in situ 10Be and 14C), and radiocarbon dating of recently ice-entombed moss to generate a centennial-scale record of Holocene GIC fluctuations in southwestern Greenland. Following local deglaciation ∼10-9 ka, sediments from proglacial Crash Lake record a glacier advance at ∼9 ka that is indistinguishable from nearby ice sheet moraines, implying a synchronous response of GIC and the Greenland Ice Sheet to a centennial-scale climate event. Following this local glacier advance, GIC experienced net recession until ∼4.6 ka. Radiocarbon ages of in situ moss (n = 29) and Crash Lake sediments reveal intervals of glacier expansion at ∼1.8, 1.2 and 0.7 ka that are superimposed on an overall trend of net glacier expansion throughout the late Holocene. In situ 14C concentrations from bedrock adjacent to radiocarbon-dated moss samples further constrain the duration of ice cover through the Holocene in this region. We find that our glacier-size proxy records during the past ∼4 ka are broadly consistent with relatively lower temperatures recorded in GISP2 and occur during, or following, intervals of volcanic perturbations. Thus, we speculate that volcanic activity, although less frequent and intense than in the early Holocene and during the Little Ice Age, may have led to centennial-scale variability imprinted on net glacier expansion due to decreasing summer insolation through the late Holocene.
Keywords: Cosmogenic in situ 14C; Glacier fluctuations; Greenland; Holocene; lake sediment; Neoglaciation

Interstadial Rise and Younger Dryas Demise of Scotland's Last Ice Fields - Bromley, G.; Putnam, A.; Borns, H.; Lowell, T.; Sandford, T.; Barrell, D. (Paleoceanography and Paleoclimatology, 2018)
Establishing the atmospheric expression of abrupt climate change during the last glacial termination is key to understanding driving mechanisms. In this paper, we present a new 14C chronology of glacier behavior during late‐glacial time from the Scottish Highlands, located close to the overturning region of the North Atlantic Ocean. Our results indicate that the last pulse of glaciation culminated between ~12.8 and ~12.6 ka, during the earliest part of the Younger Dryas stadial and as much as a millennium earlier than several recent estimates. Comparison of our results with existing minimum‐limiting 14C data also suggests that the subsequent deglaciation of Scotland was rapid and occurred during full stadial conditions in the North Atlantic. We attribute this pattern of ice recession to enhanced summertime melting, despite severely cool winters, and propose that relatively warm summers are a fundamental characteristic of North Atlantic stadials.
Keywords: late glacial; Loch Lomond Readvance; marine reservoir effect; moraine chronology; radiocarbon; seasonality

Isotopic composition of sinking particles: Oil effects, recovery andbaselines in the Gulf of Mexico, 2010–2015 - Chanton, Jeffrey P.; Giering, Sarah L. C.; Bosman, Samantha H.; Rogers, Kelsey L.; Sweet, Julia; Asper, Vernon L.; Diercks, Arne R.; Passow, Uta (Elem Sci Anth, 2018)
The extensive release of oil during the 2010 Deepwater Horizon spill in the northern Gulf of Mexico perturbed the pelagic ecosystem and associated sinking material. To gauge the recovery and post-spill baseline sources, we measured Δ14C, δ13C and δ34S of sinking particles near the spill site and at a reference site and natural seep site. Particulates were collected August 2010–April 2016 in sediment traps moored at sites with depths of 1160–1660 m. Near the spill site, changes in Δ14C indicated a 3-year recovery period, while δ34S indicated 1–2 years, which agreed with estimates of 1–2 years based on hydrocarbon composition. Under post-spill baseline conditions, carbon inputs to sinking particulates in the northern Gulf were dominated by surface marine production (80–85%) and riverine inputs (15–20%). Near the spill site, Δ14C values were depleted in October 2010 (–140 to –80‰), increasing systematically by 0.07 ± 0.02‰ day–1 until July 2013 when values reached –3.2 ± 31.0‰. This Δ14C baseline was similar to particulates at the reference site (3.8 ± 31.1‰). At both sites, δ13C values stayed constant throughout the study period (–21.9 ± 0.5‰ and –21.9 ± 0.9‰, respectively). δ34S near the spill site was depleted (7.4 ± 3.1‰) during October 2010–September 2011, but enriched (16.9 ± 2.0‰) and similar to the reference site (16.2 ± 3.1‰) during November 2012–April 2015. At the seep site, Δ14C values were –21.7 ± 45.7‰ except during August 2012–January 2013 when a significant Δ14C depletion of –109.0 ± 29.1‰ was observed. We interpret this depletion period, also observed in δ13C data, as caused by the incorporation of naturally seeped oil into sinking particles. Determination of post-spill baselines for these isotopic signatures allows for evaluation of anthropogenic inputs in future.
Keywords: Deep Water Horizon Oil Spill; Gulf of Mexico; isotopes; radiocarbon; sediment trap; sinking particulates

Large‐Scale Intrusion of Circumpolar Deep Water on Antarctic Margin Recorded by Stylasterid Corals - King, Theresa M.; Rosenheim, Brad E.; Post, Alexandra L.; Gabris, Theresa; Burt, Taylor; Domack, Eugene W. (Paleoceanography and Paleoclimatology, 2018)
We present centennial‐scale radiocarbon (14C) records archived by deep sea stylasterid corals from the outer shelf and upper slope of the Antarctic margin. These novel stylasterids (Errina spp.) were collected from the western Ross Sea shelf (500 m) and slope (1,700 m), as well as the eastern Wilkes Land shelf (670 m). We provide two corals from each region and document an abrupt reversal of 14C ages in the upper (younger) part of each coral. We test the statistical robustness of each record and demonstrate the significance of the age reversals, as well as the ability of these corals to record environmental change. We discuss a variety of possible drivers for this 14C reversal and conclude that it is most likely an encroachment of 14C‐depeleted Circumpolar Deep Water (CDW). This water mass has regionally intruded onto the Antarctic margin in recent decades, facilitating loss of grounded Antarctic ice; which has implications for global sea level, deep‐water formation, and carbon sequestration in the Southern Ocean. Thus, understanding the past variability of CDW on the margin is vital to better constrain climate change trajectories in the near future. We estimate large‐scale encroachment of CDW onto the shelf likely commencing after 1830 CE (±120 year). We present possible drivers for the intrusion, but highlight the need for additional chronologic constraint. This study not only demonstrates the utility of a novel coral taxon but also presents the paleoceanographic community with a testable hypothesis concerning a recent, widespread CDW intrusion.

Linear decline in red snapper (Lutjanus campechanus) otolith Δ14C extends the utility of the bomb radiocarbon chronometer for fish age validation in the Northern Gulf of Mexico - Barnett, Beverly K; Thornton, Laura; Allman, Robert; Chanton, Jeffrey P; Patterson, William F (ICES Journal of Marine Science, 2018)
Radiocarbon (D14C) was analyzed in northern Gulf of Mexico (nGOM) red snapper (Lutjanus campechanus) otolith cores (n¼23), otolith edge samples (n¼12), and whole age-0 otoliths (n¼9), with edge samples and whole age-0 otoliths constituting known-age samples. There was no significant difference in the linear relationship of D14C versus year of formation between regional corals and known-age otolith samples, and a linear regression fit to the combined data from 1980 to 2015 extends the utility of the bomb radiocarbon chronometer for age validation. The entire regional coral and known-age otolith data set (1940 to 2015) was then utilized as a reference series to validate otolith-derived red snapper age estimates for cored otolith samples. A loess regression was fit to the reference data and then the sum of squared residuals (SSR) was computed from predicted versus observed birth years for cored adult otolith samples. This process was then repeated for ages biased 61–4 years. Ages with no bias applied had the lowest SSR, thus validating red snapper age estimates and demonstrating the utility of the combined regional coral and known-age red snapper otolith D14C time series for age validation of nGOM marine fishes.
Keywords: Age validation; otoliths; radiocarbon; red snapper

Longitudinal discontinuities in riverine greenhouse gas dynamics generated by dams and urban wastewater - Jin, Hyojin; Yoon, Tae Kyung; Begum, Most Shirina; Lee, Eun-Ju; Oh, Neung-Hwan; Kang, Namgoo; Park, Ji-Hyung (Biogeosciences, 2018)
Surface water concentrations of CO2, CH4, and N2O have rarely been measured simultaneously in river systems modified by human activities, contributing to large uncertainties in estimating global riverine emissions of greenhouse gases (GHGs). Basin-wide surveys of the three GHGs were combined with a small number of measurements of C isotope ratios in dissolved organic matter (DOM), CO2, and CH4 in the Han River basin, South Korea, to examine how longitudinal patterns of the three gases and DOM are affected by four cascade dams along a middle section of the North Han River (hereafter termed “middle reach”) and treated wastewater discharged to the lower Han River (“lower reach”) traversing the Seoul metropolitan area. Monthly monitoring and two-season comparison were conducted at 6 and 15 sites, respectively, to measure surface water gas concentrations and ancillary water quality parameters including concentrations of dissolved organic carbon (DOC) and optical properties of DOM. The basin-wide surveys were complemented with a sampling cruise along the lower reach and synoptic samplings along an urban tributary delivering effluents from a large wastewater treatment plant (WWTP) to the lower reach. The levels of pCO2 were relatively low in the middle reach (51–2465 µatm), particularly at the four dam sites (51–761 µatm), compared with those found in the largely forested upper basin with scattered patches of croplands (163–2539 µatm), the lower reach (78–11298 µatm), and three urban tributaries (2120–11970 µatm). The upper and middle reaches displayed generally low concentration ranges of CH4 and N2O, with some local peaks influenced by agricultural runoff and impoundments. By comparison, the lower reach exhibited exceptionally high concentrations of CH4 (1.2–15766 nmol L−1) and N2O (7.5–1396 nmol L−1), which were significantly correlated with different sets of variables such as DO and PO3−4 for CH4 and NH+4 and NO−3 for N2O. Downriver increases in the levels of DOC and optical properties such as fluorescence index (FI) and protein-like fluorescence indicated an increasing DOM fraction of anthropogenic and microbial origin. The concentrations of the three GHGs and DOC were similar in magnitude and temporal variation at a WWTP discharge and the receiving tributary, indicating a disproportionate contribution of the WWTP effluents to the tributary gas and DOC exports to the lower reach. The values of δ13C in surface water CO2 and CH4 measured during the sampling cruise along the lower reach, combined with δ13C and Δ14C in DOM sampled across the basin, implied a strong influence of the wastewater-derived gases and aged DOM delivered by the urban tributaries. The downstream enrichment of 13C in CO2 and CH4 suggested that the spatial distribution of these gases across the eutrophic lower reach may also be constrained by multiple concomitant processes including outgassing, photosynthesis, and CH4 oxidation. The overall results suggest that dams and urban wastewater may create longitudinal discontinuities in riverine metabolic processes leading to large spatial variations in the three GHGs correlating with different combinations of DOM properties and nutrients. Further research is required to evaluate the relative contributions of anthropogenic and in-stream sources of the three gases and DOM in eutrophic urbanized river systems and constrain key factors for the contrasting impoundment effects such as autotrophy-driven decreases in pCO2 and in-lake production of CH4 and N2O.

A long-term decrease in the persistence of soil carbon caused by ancient Maya land use - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Timothy I.; Brenner, Mark; Curtis, Jason H.; Breckenridge, Andy; Johnston, Kevin (Nature Geoscience, 2018)
The long-term effects of deforestation on tropical forest soil carbon reservoirs are important for estimating the consequences of land use on the global carbon cycle, but are poorly understood. The Maya Lowlands of Mexico and Guatemala provide a unique opportunity to assess this question, given the widespread deforestation by the ancient Maya that began ~4,000 years ago. Here, we compare radiocarbon ages of plant waxes and macrofossils in sediment cores from three lakes in the Maya Lowlands to record past changes in the mean soil transit time of plant waxes (MTTwax). MTTwax indicates the average age of plant waxes that are transported from soils to lake sediments, and comparison of radiocarbon data from soils and lake sediments within the same catchment indicates that MTTwax reflects the age of carbon in deep soils. All three sediment cores showed a decrease in MTTwax, ranging from 2,300 to 800 years, over the past 3,500 years. This decrease in MTTwax, indicating shorter storage times for carbon in lake catchment soils, is associated with evidence for ancient Maya deforestation. MTTwax never recovered to pre-deforestation values, despite subsequent reforestation, implying that current tropical deforestation will have long-lasting effects on soil carbon sinks.

Organic Carbon Aging During Across‐Shelf Transport - Bao, Rui; Uchida, Masao; Zhao, Meixun; Haghipour, Negar; Montlucon, Daniel; McNichol, Ann; Wacker, Lukas; Hayes, John M.; Eglinton, Timothy I. (Geophysical Research Letters, 2018)
Compound-specific radiocarbon analysis (CSRA) was performed on different grain-size fractions of surficial sediments to examine and compare lateral transport times (LTTs) of organic carbon. 14C aging of long-chain leaf wax fatty acids along two dispersal pathways of fluvially-derived material on adjacent continental margins implies LTTs over distances of ~30 to 500 km that range from hundreds to thousands of years. The magnitude of aging differs among grain size fractions. Our finding suggests that LTTs vary both temporally and spatially as a function of the specific properties of different continental shelf settings. Observations suggest that 14C aging is widespread during lateral transport over continental shelves, with hydrodynamic particle sorting inducing age variations among organic components residing in different grain sizes. Consideration of these phenomena is of importance for understanding carbon cycle processes and interpretation on sedimentary records on continental margins.

Paleoseismic Results from the Alpine Site, Wasatch Fault Zone: Timing and Displacement Data for Six Holocene Earthquakes at the Salt Lake City–Provo Segment Boundary - Bennett, S. E. K.; DuRoss, C. B.; Gold, R. D.; Briggs, R. W.; Personius, S. F.; Reitman, N. G.; Devore, J. R.; Hiscock, A. I.; Mahan, S. A.; Gray, H. J.; Gunnarson, S.; Stephenson, W. J.; et al. (Bulletin of the Seismological Society of America, 2018)
To improve the characterization of Holocene earthquakes on the Wasatch fault zone (WFZ), we conducted light detection and ranging (lidar)‐based neotectonic mapping and excavated a paleoseismic trench across an 8‐m‐high fault scarp near Alpine, Utah, located <1  km south of the boundary between the Salt Lake City and Provo segments (SLCS and PS). We document evidence for six paleoearthquakes (AL6–AL1) from scarp‐derived colluvial wedges and crosscutting relations. A ground‐penetrating radar survey across the scarp resolved fault‐zone width, but not paleoearthquake stratigraphy. Bayesian (OxCal) modeling of 13 radiocarbon and 13 optically stimulated luminescence ages indicates that six earthquakes occurred ∼6.2–0.4  ka. Interseismic recurrence ranges from 0.2 to 1.8 ky (mean 1.2 ky). We estimate 6.5±0.7  m of cumulative vertical tectonic displacement across the ≥14‐m‐wide fault zone used near‐field observations of scarp‐derived colluvial‐wedge thicknesses, antithetic faulting, and graben backtilting. This is similar to our independent estimate of 6.5±0.5  m using far‐field observations of the offset ground surface and correlation of alluvial‐fan stratigraphy across the WFZ. These results suggest that colluvial‐wedge thickness at the Alpine site approximates one‐half the original west‐facing fault scarp height. Per‐event vertical displacements range from 0.8 to 1.2 m (mean 1.1 m), which we use to estimate surface rupture lengths that may exceed 50 km from earthquakes as large as moment magnitude (Mw) ∼7.0. The late Holocene average vertical slip rate is 0.9  mm/yr (0.7–1.2  mm/yr range). Earthquake frequency has increased in the past ∼1  ky, whereas displacement per event has been similar for the past ∼6  ky, suggesting that strain accumulation is not the sole factor that controls the frequency and size of earthquakes at the SLCS–PS segment boundary. These findings can be used for a more nuanced characterization of earthquakes at the SLCS–PS boundary and improve earthquake hazard assessments along the Wasatch Front.

Quaternary Glaciation of the Great Lakes Region: Process, Landforms, Sediments, and ChronologyMinimum age of the Mapleton, Tully, and Labrador Hollow moraines indicates correlation with the Port Huron Phase in central New York State - Kehew, Alan E.; Curry, B. Brandon; Kozlowski, Andrew L.; Bird, Brian C.; Lowell, Thomas V.; Smith, Colby A.; Feranec, Robert S.; Graham, Brandon Lars (Geological Society of America, 2018)
The glaciated terrain along the northern edge of the Appalachian Plateau in the eastern Finger Lakes of central New York has long been recognized as an important location for meltwater routing and for proglacial lake development in the Great Lakes region. Despite recognition of multiple ice margins formed by the Ontario Lobe of the Laurentide ice sheet during the late Wisconsinan, numerical age control of several margins has been elusive, particularly in regard to regional readvances of the Port Bruce (ca. 16,980–18,000 cal [calibrated] yr B.P.) and Port Huron (ca. 14,300– 16,000 cal yr B.P.) Phases. Utilizing light detection and ranging (LiDAR) terrain models in the eastern Finger Lakes area, we identified and described the Mapleton, Tully, and Labrador Hollow moraines. Associated ice-marginal landforms include push moraines, fans, and hummocky topography. In places, these features intrude into the northern heads of through valleys. Coring of three basins directly associated with these landforms yielded more than 20 samples of boreal tree needles and twigs, and Dryas leaves. Accelerated mass spectrometry (AMS) radiocarbon assay results indicate that poststadial lacustrine sedimentation began at ca. 15,000 cal yr B.P., consistent with ages of the Port Huron Phase.

Radiocarbon Content of Dissolved Organic Carbon in the South Indian Ocean - Bercovici, S. K.; McNichol, A. P.; Xu, L.; Hansell, D. A. (Geophysical Research Letters, 2018)
We report four profiles of the radiocarbon content of dissolved organic carbon (DOC) spanning the South Indian Ocean (SIO), ranging from the Polar Front (56°S) to the subtropics (29°S). Surface waters held mean DOC Δ14C values of −426 ± 6‰ (~4,400 14C years) at the Polar Front and DOC Δ14C values of −252 ± 22‰ (~2,000 14C years) in the subtropics. At depth, Circumpolar Deep Waters held DOC Δ14C values of −491 ± 13‰ (~5,400 years), while values in Indian Deep Water were more depleted, holding DOC Δ14C values of −503 ± 8‰ (~5,600 14C years). High‐salinity North Atlantic Deep Water intruding into the deep SIO had a distinctly less depleted DOC Δ14C value of −481 ± 8‰ (~5,100 14C years). We use multiple linear regression to assess the dynamics of DOC Δ14C values in the deep Indian Ocean, finding that their distribution is characteristic of water masses in that region.
Keywords: dissolved organic carbon; indian ocean; radiocarbon

Radiocarbon dating of the old ash of Aiton, Romania - Patrut, Adrian; Patrut, Roxana T.; Rakosy, Laszlo; Ratiu, Ileana-Andreea; Lowy, Daniel A.; Bodis, Jenő; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The article reports the AMS (accelerator mass spectrometry) radiocarbon investigation results of the old common ash of Aiton. Five wood samples were collected from the trunk of the tree. The deepest ends of the samples were analysed by AMS radiocarbon. We found radiocarbon dates between 165 ± 20 BP and 240 ± 18 BP, which correspond to calibrated ages of 230 – 360 years. These results, combined with a ring counting estimate, indicate an age of 330 ± 30 years for the ash of Aiton. By this value, the ash of Aiton becomes the oldest known common ash with accurate dating results. © 2018, Universitatea Babes-Bolyai, Catedra de Filosofie Sistematica. All rights reserved.

Rapid precipitation changes in the tropical West Pacific linked to North Atlantic climate forcing during the last deglaciation - Xiong, Zhifang; Li, Tiegang; Chang, Fengming; Algeo, Thomas J.; Clift, Peter D.; Bretschneider, Lisa; Lu, Zhengyao; Zhu, Xiao; Frank, Martin; Sauer, Peter E.; Jiang, FuQing; Wan, Shiming; et al. (Quaternary Science Reviews, 2018)
The cause of rapid hydrological changes in the tropical West Pacific during the last deglaciation remains controversial. In order to test whether these changes were triggered by abrupt climate change events in the North Atlantic Ocean, variations in precipitation during the last deglaciation (18-10 ka) were extracted from proxy records of chemical weathering and terrigenous input in the western Philippine Sea (WPS). The evolution of chemical weathering and terrigenous input since 27 ka was reconstructed using the chemical index of alteration (CIA), elemental ratios (K/Al, TOC/TN and Ti/Ca), δ13Corg, terrigenous fraction abundance and flux data from International Marine Global Change Study Program (IMAGES) core MD06-3054 collected on the upper continental slope of eastern Luzon (northern Philippines). Sediment deposited during the Last Glacial Maximum (LGM) shows weathering equal to or slightly greater than Holocene sediment in the WPS. This unusual state of chemical weathering, which is inconsistent with lower air temperatures and decreased precipitation in Luzon during the LGM, may be due to reworking of poorly consolidated sediments on the eastern Luzon continental shelf during the LGM sea-level lowstand. Rapid changes in chemical weathering, characterized by higher intensity during the Heinrich event 1 (H1) and Younger Dryas (YD) and lower intensity during the Bølling-Allerød (B/A), were linked to rapid variations in precipitation in the WPS during the last deglaciation. The higher terrigenous inputs during the LGM relative to those of the Holocene were controlled by sea-level changes rather than precipitation. The terrigenous inputs show a long-term decline during the last deglaciation, punctuated by brief spikes during the H1 and YD related to sea-level rises and rapid precipitation changes in the WPS, respectively. The proxy records of chemical weathering and terrigenous input from eastern Luzon suggest high rainfall during the H1 and YD events, consistent with inferred rainfall patterns based on Fe/Ca records from offshore Mindanao. Rapid precipitation changes in the WPS did not coincide with migrations of the Intertropical Convergence Zone (ITCZ) but, rather, were related to state shifts of the El Niño-Southern Oscillation (ENSO) during the last deglaciation. Based on proxy records and modeling results, we argue that the Atlantic meridional overturning circulation (AMOC) controlled rapid precipitation changes in the tropical West Pacific through zonal shifts of ENSO or meridional migration of the ITCZ during the last deglaciation. Our findings highlight the dominant role of the North Atlantic Ocean in the tropical hydrologic cycle during the last deglaciation.
Keywords: AMOC; Chemical weathering; enso; ITCZ; Terrigenous input; Western Philippine Sea

Relative sea-level change in Newfoundland, Canada during the past ∼3000 years - Kemp, Andrew C.; Wright, Alexander J.; Edwards, Robin J.; Barnett, Robert L.; Brain, Matthew J.; Kopp, Robert E.; Cahill, Niamh; Horton, Benjamin P.; Charman, Dan J.; Hawkes, Andrea D.; Hill, Troy D.; van de Plassche, Orson (Quaternary Science Reviews, 2018)
Several processes contributing to coastal relative sea-level (RSL) change in the North Atlantic Ocean are observed and/or predicted to have distinctive spatial expressions that vary by latitude. To expand the latitudinal range of RSL records spanning the past ∼3000 years and the likelihood of recognizing the characteristic fingerprints of these processes, we reconstructed RSL at two sites (Big River and Placentia) in Newfoundland from salt-marsh sediment. Bayesian transfer functions established the height of former sea level from preserved assemblages of foraminifera and testate amoebae. Age-depth models constrained by radiocarbon dates and chronohorizons estimated the timing of sediment deposition. During the past ∼3000 years, RSL rose by ∼3.0 m at Big River and by ∼1.5 m at Placentia. A locally calibrated geotechnical model showed that post-depositional lowering through sediment compaction was minimal. To isolate and quantify contributions to RSL from global, regional linear, regional non-linear, and local-scale processes, we decomposed the new reconstructions (and those in an expanded, global database) using a spatio-temporal statistical model. The global component confirms that 20th century sea-level rise occurred at the fastest, century-scale rate in over 3000 years (P > 0.999). Distinguishing the contributions from local and regional non-linear processes is made challenging by a sparse network of reconstructions. However, only a small contribution from local-scale processes is necessary to reconcile RSL reconstructions and modeled RSL trends. We identified three latitudinally-organized groups of sites that share coherent regional non-linear trends and indicate that dynamic redistribution of ocean mass by currents and/or winds was likely an important driver of sea-level change in the North Atlantic Ocean during the past ∼3000 years.

Remobilization of old permafrost carbon to Chukchi Sea sediments during the end of the last deglaciation - Martens, Jannik; Wild, Birgit; Pearce, Christof; Tesi, Tommaso; Andersson, August; Broder, Lisa; O’Regan, Matt; Jakobsson, Martin; Sköld, Martin; Gemery, Laura; Cronin, Thomas M.; Semiletov, Igor; et al. (Global Biogeochemical Cycles, 2018)
Climate warming is expected to destabilize permafrost carbon (PF‐C) by thaw‐erosion and deepening of the seasonally thawed active layer and thereby promote PF‐C mineralization to CO2 and CH4. A similar PF‐C remobilization might have contributed to the increase in atmospheric CO2 during deglacial warming after the last glacial maximum. Using carbon isotopes and terrestrial biomarkers (Δ14C, δ13C, and lignin phenols), this study quantifies deposition of terrestrial carbon originating from permafrost in sediments from the Chukchi Sea (core SWERUS‐L2‐4‐PC1). The sediment core reconstructs remobilization of permafrost carbon during the late Allerød warm period starting at 13,000 cal years before present (BP), the Younger Dryas, and the early Holocene warming until 11,000 cal years BP and compares this period with the late Holocene, from 3,650 years BP until present. Dual‐carbon‐isotope‐based source apportionment demonstrates that Ice Complex Deposit—ice‐ and carbon‐rich permafrost from the late Pleistocene (also referred to as Yedoma)—was the dominant source of organic carbon (66 ± 8%; mean ± standard deviation) to sediments during the end of the deglaciation, with fluxes more than twice as high (8.0 ± 4.6 g·m−2·year−1) as in the late Holocene (3.1 ± 1.0 g·m−2·year−1). These results are consistent with late deglacial PF‐C remobilization observed in a Laptev Sea record, yet in contrast with PF‐C sources, which at that location were dominated by active layer material from the Lena River watershed. Release of dormant PF‐C from erosion of coastal permafrost during the end of the last deglaciation indicates vulnerability of Ice Complex Deposit in response to future warming and sea level changes.
Keywords: carbon isotope; climate change feedback; coastal erosion; Deglaciation; past carbon cycling; permafrost

Riverine Export of Aged Carbon Driven by Flow Path Depth and Residence Time - Barnes, Rebecca T.; Butman, David E.; Wilson, Henry F.; Raymond, Peter A. (Environmental Science & Technology, 2018)
The flux of terrestrial C to rivers has increased relative to preindustrial levels, a fraction of which is aged dissolved organic C (DOC). In rivers, C is stored in sediments, exported to the ocean, or (bio)chemically processed and released as CO2. Disturbance changes land cover and hydrology, shifting potential sources and processing of DOC. To investigate the likely sources of aged DOC, we analyzed radiocarbon ages, chemical, and spectral properties of DOC and major ions from 19 rivers draining the coterminous U.S. and Arctic. DOC optics indicated that the majority is exported as aromatic, high molecular weight, modern molecules while aged DOC tended to consist of smaller, microbial degradation products. Aged DOC exports, observed regularly in arid basins and during base flow in arctic rivers, are associated with higher proportion of mineral weathering products, suggesting deeper flows paths. These patterns also indicate potential for production of microbial byproducts as DOC ages in soil and water with longer periods of time between production and transport. Thus, changes in hydrology associated with landscape alteration (e.g., tilling or shifting climates) that can result in deeper flow paths or longer residence times will likely lead to a greater proportion of aged carbon in riverine exports.

The role of sediment compaction and groundwater withdrawal in local sea-level rise, Sandy Hook, New Jersey, USA - Johnson, Christopher S.; Miller, Kenneth G.; Browning, James V.; Kopp, Robert E.; Khan, Nicole S.; Fan, Ying; Stanford, Scott D.; Horton, Benjamin P. (Quaternary Science Reviews, 2018)
The rate of relative sea-level (RSL) rise at Sandy Hook, NJ (4.0 ± 0.5 mm/yr) was higher than The Battery, NY (3.0 ± 0.3 mm/yr) from 1900 to 2012 despite being separated by just 26 km. The difference cannot be explained by differential glacial isostatic adjustment (GIA; 1.4 ± 0.4 and 1.3 ± 0.4 mm/yr RSL rise, respectively) alone. We estimate the contribution of sediment compaction to subsidence at Sandy Hook using high-resolution grain size, percent organic matter, and porosity data from three upper Quaternary (≤13,350 cal yr) cores. The organic matter content (<2%) is too low to contribute to local subsidence. However, numerical modeling of the grain size-depth-age-porosity relationship indicates that compaction of deglacial silts likely reduced the column thickness by 10–20% over the past 13,350 cal yrs. While compaction rates were high immediately after the main silt deposition (13,350–13,150 cal yrs BP), rates decreased exponentially after deposition to an average 20th century rate of 0.16 mm/yr (90% Confidence Interval (C.I.), 0.06–0.32 mm/yr). The remaining ∼0.7 mm/yr (90% C.I. 0.3–1.2 mm/yr) difference in subsidence between Sandy Hook and The Battery is likely due to anthropogenic groundwater withdrawal. Historical data from Fort Hancock wells (2 km to the southeast of the Sandy Hook tide gauge) and previous regional work show that local and regional water extraction lowered the water levels in the aquifers underlying Sandy Hook. We suggest that the modern order of contribution to subsidence (highest to lowest) appears to be GIA, local/regional groundwater extraction, and compaction of thick Quaternary silts.
Keywords: Marginal marine; North America; numerical modeling; Quaternary; Sea-level change; sedimentology

Seafloor fluid seeps on Kimki Ridge, offshore southern California: Links to active strike-slip faulting - Conrad, James E.; Prouty, Nancy G.; Walton, Maureen A.L.; Kluesner, Jared W.; Maier, Katherine L.; McGann, Mary; Brothers, Daniel S.; Roland, Emily C.; Dartnell, Peter (Deep Sea Research Part II: Topical Studies in Oceanography, 2018)
The Kimki Ridge fluid seeps are located in western Catalina Basin about 60 km southwest of the southern California mainland and at a water depth of approximately 1100 m. Multichannel seismic reflection profiles collected by the U.S. Geological Survey (USGS) in 2014 show acoustic transparency within the Kimki Ridge, suggesting the possibility of fluid seeps and possible sub-seafloor fluid pathways. Subsequent multibeam bathymetric and backscatter intensity data collected during a cooperative University of Washington/USGS cruise in early 2016 show subtle seafloor buildups with high acoustic backscatter (reflectivity) in three places along Kimki Ridge, supporting the existence of fluid seepage. A Remotely Operated Vehicle (ROV) dive, conducted as part of the Nautilus Exploration Program, took place in August 2016 to confirm the presence of these previously unknown seeps and document their characteristics as well as those of any associated biological communities. Two of the three seeps were explored by ROV, and showed abundant evidence of fluid seepage, including characteristic algal mats, chemosynthetic clams, and authigenic carbonate formation. The seeps are comprised of carbonate buildups 1–3 m thick and 300–500 m across. Within these areas, we interpret broad crater-like depressions 30–50 m across and 1–2 m deep to be individual seep vents. The seep areas appear to be broad zones of diffuse seepage that support chemosynthetic biologic communities; however, active venting was not observed. Geochemical analyses of rock samples collected from the seeps indicate microbially driven anaerobic oxidation of methane at or near the sediment water interface. Seismic-reflection profiles show chimney-like fluid pathways along the limbs and in the axis of the fold forming Kimki Ridge, and evidence of methane in shallow sediments can be traced into the adjacent Catalina Basin. A system of closely spaced faults located at the axis of the Kimki Ridge anticline may serve as pathways to allow fluid flow to the seafloor. Our data are consistent with other studies that suggest that transpression is an important component in the formation and localization of fluid seeps in a strike-slip setting, implying that seep formation may be a common occurrence at fault stepovers or transpressional bends in strike-slip systems.
Keywords: California Inner Continental Borderland; E/V Nautilus; Faulting; methane; Seepages

Slope failures within and upstream of Lake Quinault, Washington, as uneven responses to Holocene earthquakes along the Cascadia subduction zoneAbstract - Leithold, Elana L.; Wegmann, Karl W.; Bohnenstiehl, Delwayne R.; Smith, Stephen G.; Noren, Anders; O’Grady, Ryan (Quaternary Research, 2018)
Investigation of Lake Quinault in western Washington, including a reflection seismic survey, analysis of piston cores, and preliminary mapping in the steep, landslide-prone Quinault River catchment upstream of the lake, reveals evidence for three episodes of earthquake disturbance in the past 3000 yr. These earthquakes triggered failures on the lake’s underwater slopes and delta front, as well as subaerial landsliding, partial channel blockage, and forced fluvial sediment aggradation. The ages of the three Lake Quinault disturbance events overlap with those of coseismically subsided, coastal marsh soils nearby in southwest Washington that are interpreted to record ruptures of the Cascadia megathrust. Absent from Lake Quinault, however, are signals of obvious disturbance from five additional subduction earthquakes inferred to have occurred during the period of record. The lack of evidence for these events may reflect the limitations of the data set derived from the detrital, river-dominated lake stratigraphy but may also have bearing on debates about segmentation and the distribution of slip along the Cascadia subduction zone during prior earthquakes.
Keywords: Cascadia; Earthquake; lakes; Paleoseismic; Sediment

Tectonically-triggered sediment and carbon export to the Hadal zone - Bao, Rui; Strasser, Michael; McNichol, Ann P.; Haghipour, Negar; McIntyre, Cameron; Wefer, Gerold; Eglinton, Timothy I. (Nature Communications, 2018)
Sediments in deep ocean trenches may contain crucial information on past earthquake history and constitute important sites of carbon burial. Here we present 14C data on bulk organic carbon (OC) and its thermal decomposition fractions produced by ramped pyrolysis/oxidation for a core retrieved from the >7.5 km-deep Japan Trench. High-resolution 14C measurements, coupled with distinctive thermogram characteristics of OC, reveal hemipelagic sedimentation interrupted by episodic deposition of pre-aged OC in the trench. Low δ13C values and diverse 14C ages of thermal fractions imply that the latter material originates from the adjacent margin, and the co-occurrence of pre-aged OC with intervals corresponding to known earthquake events implies tectonically triggered, gravity-flow-driven supply. We show that 14C ages of thermal fractions can yield valuable chronological constraints on sedimentary sequences. Our findings shed new light on links between tectonically driven sedimentological processes and marine carbon cycling, with implications for carbon dynamics in hadal environments.

Unifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic EcosystemsUnifying Concepts Linking Dissolved Organic Matter Composition to Persistence in Aquatic Ecosystems - Kellerman, Anne M.; Guillemette, François; Podgorski, David C.; Aiken, George R.; Butler, Kenna D.; Spencer, Robert G. M. (Environmental Science & Technology, 2018)
The link between composition and reactivity of dissolved organic matter (DOM) is central to understanding the role aquatic systems play in the global carbon cycle; yet, unifying concepts driving molecular composition have yet to be established. We characterized 37 DOM isolates from diverse aquatic ecosystems, including their stable and radiocarbon isotopes (δ13C-dissolved organic carbon (DOC) and Δ14C-DOC), optical properties (absorbance and fluorescence), and molecular composition (ultrahigh resolution mass spectrometry). Isolates encompassed end-members of allochthonous and autochthonous DOM from sites across the United States, the Pacific Ocean, and Antarctic lakes. Modern Δ14C-DOC and optical properties reflecting increased aromaticity, such as carbon specific UV absorbance at 254 nm (SUVA254), were directly related to polyphenolic and polycyclic aromatic compounds, whereas enriched δ13C-DOC and optical properties reflecting autochthonous end-members were positively correlated to more aliphatic compounds. Furthermore, the two sets of autochthonous end-members (Pacific Ocean and Antarctic lakes) exhibited distinct molecular composition due to differences in extent of degradation. Across all sites and end-members studied, we find a consistent shift in composition with aging, highlighting the persistence of certain biomolecules concurrent with degradation time.

Using Stable and Radiocarbon Analyses as a Forensic Tool to Find Evidence of Oil in the Particulates of the Water Column and on the Seafloor Following the 2010 Gulf of Mexico Oil Spill - Bosman, Samantha H.; Chanton, Jeffrey P.; Rogers, Kelsey L. (Elsevier, 2018)
Over 600 million liters of oil and copious amounts of methane were released into the Gulf of Mexico between April 20, 2010 and July 15, 2010. We used stable and radiocarbon analyses as a forensic tool to trace these hydrocarbons from the Deepwater Horizon (DwH) well into suspended particulate organic carbon (POCsusp), sinking particulate organic carbon (POCsink), and sedimentary organic carbon on the seafloor. POCsusp samples were considerably depleted both in δ13C and Δ14C relative to surface production, with δ13C and Δ14C values as low as −37.2‰ and −618‰, respectively. POCsink time series data revealed a modern Δ14C value due to a large diatom bloom in early September 2010, but values became depleted as oil contaminated particles continued to descend in the water column until the end of the year. Sediment cores collected in the vicinity of the DwH wellhead revealed evidence of oil contamination in the surface layer (0–1 cm), as indicated by a depletion in Δ14C values compared to the layers below the surface. In addition to providing evidence of oil contamination using stable and radiocarbon analyses, our study was consistent with the existence of a pathway by which spilled oil was deposited onto the seafloor.
Keywords: Deepwater Horizon; isotopes; methane; Petrocarbon; POCsin; POCsusp; Sediment

Variability in carbon uptake and (re)cycling in Antarctic cryptoendolithic microbial ecosystems demonstrated through radiocarbon analysis of organic biomarkers - Brady, A. L.; Goordial, J.; Sun, H. J.; Whyte, L. G.; Slater, G. F. (Geobiology, 2018)
Cryptoendolithic lichens and cyanobacteria living in porous sandstone in the high‐elevation McMurdo Dry Valleys are purported to be among the slowest growing organisms on Earth with cycles of death and regrowth on the order of 103–104 years. Here, organic biomarker and radiocarbon analysis were used to better constrain ages and carbon sources of cryptoendoliths in University Valley (UV; 1,800 m.a.s.l) and neighboring Farnell Valley (FV; 1,700 m.a.s.l). Δ14C was measured for membrane component phospholipid fatty acids (PLFA) and glycolipid fatty acids, as well as for total organic carbon (TOC). PLFA concentrations indicated viable cells comprised a minor (<0.5%) component of TOC. TOC Δ14C values ranged from −272‰ to −185‰ equivalent to calibrated ages of 1,100–2,550 years old. These ages may be the result of fractional preservation of biogenic carbon and/or sudden large‐scale community death and extended period(s) of inactivity prior to slow recolonization and incorporation of 14C‐depleted fossil material. PLFA Δ14C values were generally more modern than the corresponding TOC and varied widely between sites; the FV PLFA Δ14C value (+40‰) was consistent with modern atmospheric CO2, while UV values ranged from −199‰ to −79‰ (calibrated ages of 1,665–610 years). The observed variability in PLFA Δ14C depletions is hypothesized to reflect variations in the extent of fixation of modern atmospheric CO2 and the preservation and recycling of older organic carbon by the community in various stages of sandstone recolonization. PLFA profiles and microbial community compositions as determined by molecular genetic characterizations and microscopy differed between the two valleys (e.g., predominance of biomarker 18:2 [>50%] in FV compared to UV), representing microbial communities that may reflect distinct stages of sandstone recolonization and/or environmental conditions. It is thus proposed that Dry Valley cryptoendolithic microbial communities are faster growing than previously estimated.

Variance and Rate-of-Change as Early Warning Signals for a Critical Transition in an Aquatic Ecosystem State: A Test Case From Tasmania, Australia - Beck, Kristen K.; Fletcher, Michael-Shawn; Gadd, Patricia S.; Heijnis, Henk; Saunders, Krystyna M.; Simpson, Gavin L.; Zawadzki, Atun (Journal of Geophysical Research: Biogeosciences, 2018)
Critical transitions in ecosystem states are often sudden and unpredictable. Consequently, there is a concerted effort to identify measurable early warning signals (EWS) for these important events. Aquatic ecosystems provide an opportunity to observe critical transitions due to their high sensitivity and rapid response times. Using palaeoecological techniques, we can measure properties of time series data to determine if critical transitions are preceded by any measurable ecosystem metrics, that is, identify EWS. Using a suite of palaeoenvironmental data spanning the last 2,400 years (diatoms, pollen, geochemistry, and charcoal influx), we assess whether a critical transition in diatom community structure was preceded by measurable EWS. Lake Vera, in the temperate rain forest of western Tasmania, Australia, has a diatom community dominated by Discostella stelligera and undergoes an abrupt compositional shift at ca. 820 cal yr BP that is concomitant with increased fire disturbance of the local vegetation. This shift is manifest as a transition from less oligotrophic acidic diatom flora (Achnanthidium minutissimum, Brachysira styriaca, and Fragilaria capucina) to more oligotrophic acidic taxa (Frustulia elongatissima, Eunotia diodon, and Gomphonema multiforme). We observe a marked increase in compositional variance and rate‐of‐change prior to this critical transition, revealing these metrics are useful EWS in this system. Interestingly, vegetation remains complacent to fire disturbance until after the shift in the diatom community. Disturbance taxa invade and the vegetation system experiences an increase in both compositional variance and rate‐of‐change. These trends imply an approaching critical transition in the vegetation and the probable collapse of the local rain forest system.
Keywords: carbon and nitrogen stable isotopes; critical transitions; diatoms; early warning signals; polleen; Tasmania

Vegetation responses to late Holocene climate changes in an Andean forest - Schiferl, Jacob D.; Bush, Mark B.; Silman, Miles R.; Urrego, Dunia H. (Quaternary Research, 2018)
A paleoecological record from Lake Palotoa (1370 m elevation) in the Andean foothills of Peru spans the last 3800 years. Lake Palotoa lies near the modern cloud base in a location sensitive to changes in atmospheric moisture. In many areas, these forests have been destroyed, but Lake Palotoa shows no sign of human occupation today or in the past. The modern forest surrounding the lake is dominated by the Andean palm, Dictyocaryum lamarckianum, which is also the most abundant taxon in the fossil pollen record. Fossil pollen data show the vegetation assemblages have not experienced strong compositional changes in the late Holocene. Global-scale climatic events such as the Medieval Climate Anomaly (MCA) and the Little Ice Age (LIA) are identified within the record, though the vegetation responses are subtle. Hedyosmum and Sloanea pollen percentages increase near the onset of the MCA and may reflect decreased seasonality. The LIA coincides with increased Hedyosmum pollen percentages, and increases in Clethra and Begonia, two elements that tend to occupy forests now found at higher elevations. Our findings demonstrate the stability of montane forest systems to natural Holocene climate change.
Keywords: Cloud forest; Dictyocaryum; Fossil pollen; Little ice age; Medieval Climate Anomaly; seasonality; Tropical ecology

The 3.6 ka Aniakchak tephra in the Arctic Ocean: a constraint on the Holocene radiocarbon reservoir age in the Chukchi Sea - Pearce, Christof; Varhelyi, Aron; Wastegård, Stefan; Muschitiello, Francesco; Barrientos, Natalia; O'Regan, Matt; Cronin, Thomas M.; Gemery, Laura; Semiletov, Igor; Backman, Jan; Jakobsson, Martin (Climate of the Past, 2017)
The caldera-forming eruption of the Aniakchak volcano in the Aleutian Range on the Alaskan Peninsula at 3.6 cal kyr BP was one of the largest Holocene eruptions worldwide. The resulting ash is found as a visible sediment layer in several Alaskan sites and as a cryptotephra on Newfoundland and Greenland. This large geographic distribution, combined with the fact that the eruption is relatively well constrained in time using radiocarbon dating of lake sediments and annual layer counts in ice cores, makes it an excellent stratigraphic marker for dating and correlating mid–late Holocene sediment and paleoclimate records. This study presents the outcome of a targeted search for the Aniakchak tephra in a marine sediment core from the Arctic Ocean, namely Core SWERUS-L2-2-PC1 (2PC), raised from 57 m water depth in Herald Canyon, western Chukchi Sea. High concentrations of tephra shards, with a geochemical signature matching that of Aniakchak ash, were observed across a more than 1.5 m long sediment sequence. Since the primary input of volcanic ash is through atmospheric transport, and assuming that bioturbation can account for mixing up to ca. 10 cm of the marine sediment deposited at the coring site, the broad signal is interpreted as sustained reworking at the sediment source input. The isochron is therefore placed at the base of the sudden increase in tephra concentrations rather than at the maximum concentration. This interpretation of major reworking is strengthened by analysis of grain size distribution which points to ice rafting as an important secondary transport mechanism of volcanic ash. Combined with radiocarbon dates on mollusks in the same sediment core, the volcanic marker is used to calculate a marine radiocarbon reservoir age offset ΔR = 477 ± 60 years. This relatively high value may be explained by the major influence of typically "carbon-old" Pacific waters, and it agrees well with recent estimates of ΔR along the northwest Alaskan coast, possibly indicating stable oceanographic conditions during the second half of the Holocene. Our use of a volcanic absolute age marker to obtain the marine reservoir age offset is the first of its kind in the Arctic Ocean and provides an important framework for improving chronologies and correlating marine sediment archives in this region. Core 2PC has a high sediment accumulation rate averaging 200 cm kyr throughout the last 4000 years, and the chronology presented here provides a solid base for high-resolution reconstructions of late Holocene climate and ocean variability in the Chukchi Sea.

A ~6000 yr diatom record of mid- to late Holocene fluctuations in the level of Lago Wiñaymarca, Lake Titicaca (Peru/Bolivia)Abstract - Weide, D. Marie; Fritz, Sherilyn C.; Hastorf, Christine A.; Bruno, Maria C.; Baker, Paul A.; Guedron, Stephane; Salenbien, Wout (Quaternary Research, 2017)
A multidecadal-scale lake-level reconstruction for Lago Wiñaymarca, the southern basin of Lake Titicaca, has been generated from diatom species abundance data. These data suggest that ~6500 cal yr BP Lago Wiñaymarca was dry, as indicated by a sediment unconformity. At ~4400 cal yr BP, the basin began to fill, as indicated by the dominance of shallow epiphytic species. It remained somewhat saline with extensive wetlands and abundant aquatic plants until ~3800 cal yr BP, when epiphytic species were replaced by planktic saline-indifferent species, suggesting a saline shallow lake. Wiñaymarca remained a relatively shallow lake that fluctuated on a multidecadal scale until ~1250 cal yr BP, when freshwater planktic species increased, suggesting a rise in lake level with a concomitant decrease in salinity. The lake became gradually fresher, dominated by deep, freshwater species from ~850 cal yr BP. By ~80 cal yr BP, saline-tolerant species were rare, and the lake was dominated by freshwater planktic diatoms, resembling the fresh and deep lake of today. These results reveal a more dynamic and chronologically specific record of lake-level fluctuations and associated ecological conditions that provide important new data for paleoclimatologists and archaeologists, to better understand human-environmental dynamics during the mid- to late Holocene.
Keywords: diatoms; Lago Huiñaimarca; Lago Wiñaymarca; Lake level; lake titicaca; Mid-Holocene; Tropical Andes

A 7000-year history of coastal environmental changes from Mexico’s Pacific coast: A multi-proxy record from Laguna Mitla, Guerrero - Bianchette, Thomas A; McCloskey, Terrence A; Liu, Kam-biu (The Holocene, 2017)
The lack of multi-millennial multi-proxy paleoenvironmental reconstructions from Mexico’s Pacific coast has limited our understanding of the regional response to climate change and sea-level rise. A 479-cm core covering the last 6900 years was extracted from Laguna Mitla in the state of Guerrero on Mexico’s Pacific coast. Beginning as a Rhizophora-dominated salt pan ~6900 yr BP, at ~6500 yr BP, the site transitioned to a mangrove swamp dominated by Laguncularia, which lasted about 300 years. The beach barrier formed from ~6200 to 5200 yr BP, during which time, the site existed as an intermittently sheltered bay, the result of large, rapid changes in wave energy associated with the shifting barrier location and changes in stability. After the beach barrier was stabilized at ~5200 yr BP, water level at the coring site became a function of precipitation rather than sea level. Since that time, deposition has alternated between peat, laid down in a mangrove swamp, and clay intervals characterized by high concentrations of titanium and a predominantly regional pollen signal, representing open-water lagoon phases. Seven periods of increased water level, varying in duration, occurred during the backbarrier period, with El Niño-Southern Oscillation (ENSO) likely the main climatic mechanism causing these periodic shifts in the paleo-precipitation levels. We suggest that the deepest water levels detected over the last ~3200 years correlate with periods of increased ENSO activity. The spatial distribution of tropical cyclone rainfall, which represents a significant percentage of total annual precipitation along Mexico’s Pacific coast, may explain the inconsistencies between our record and paleoclimatic records from Mexico’s interior, but more work is needed to test this hypothesis.
Keywords: El Nino-Southern Oscillation; Laguna Mitla; mangroves; Pacific coast of Mexico; Paleoclimate; paleoenvironmental reconstruction; pollen; Sediment; tropical cyclones; x-ray fluorescence

African Baobabs with a Very Large Number of Stems and False Stems: Radiocarbon Investigation of the Baobab of Warang - Patrut, Adrian; Garnaud, ébastien; Ka, Oumar; Patrut, Roxana T.; Diagne, Tomas; Lowy, Daniel A.; Forizs, Edit; Bodis, ő; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The article presents the AMS (accelerator mass spectrometry) radiocarbon dating results of the baobab of Warang, Senegal. The investigation of the baobab revealed that it consists of 18 partially fused stems, which represents the largest number of stems reported for an African baobab. Three stems build the ring that closes a false cavity, while 15 stems grow outside the ring. Seven wood samples were collected from the false cavity and from the outer part of other stems. The dating results evinced that the stems belong to four different generations, out of which the first generation is around 500 years old. We also documented the presence of false stems, which emerge from a large adjacent stem, are triangular in horizontal section and act as an anchor. The baobab of Warang possesses 12 ordinary stems and 6 false stems.
Keywords: Adansonia digitata; Age determination; AMS radiocarbon dating; inner cavity; multiple stems; tropical trees

Carbon geochemistry of plankton-dominated samples in the Laptev and East Siberian shelves: contrasts in suspended particle composition - Tesi, Tommaso; Geibel, Marc C.; Pearce, Christof; Panova, Elena; Vonk, Jorien E.; Karlsson, Emma; Salvado, Joan A.; Kruså, Martin; Broder, Lisa; Humborg, Christoph; Semiletov, Igor; Gustafsson, Örjan (Ocean Science, 2017)
Recent Arctic studies suggest that sea ice decline and permafrost thawing will affect phytoplankton dynamics and stimulate heterotrophic communities. However, in what way the plankton composition will change as the warming proceeds remains elusive. Here we investigate the chemical signature of the plankton-dominated fraction of particulate organic matter (POM) collected along the Siberian Shelf. POM (> 10 µm) samples were analysed using molecular biomarkers (CuO oxidation and IP25) and dual-carbon isotopes (δ13C and Δ14C). In addition, surface water chemical properties were integrated with the POM (> 10 µm) dataset to understand the link between plankton composition and environmental conditions. δ13C and Δ14C exhibited a large variability in the POM (> 10 µm) distribution while the content of terrestrial biomarkers in the POM was negligible. In the Laptev Sea (LS), δ13C and Δ14C of POM (> 10 µm) suggested a heterotrophic environment in which dissolved organic carbon (DOC) from the Lena River was the primary source of metabolisable carbon. Within the Lena plume, terrestrial DOC probably became part of the food web via bacteria uptake and subsequently transferred to relatively other heterotrophic communities (e.g. dinoflagellates). Moving eastwards toward the sea-ice-dominated East Siberian Sea (ESS), the system became progressively more autotrophic. Comparison between δ13C of POM (> 10 µm) samples and CO2aq concentrations revealed that the carbon isotope fractionation increased moving towards the easternmost and most productive stations. In a warming scenario characterised by enhanced terrestrial DOC release (thawing permafrost) and progressive sea ice decline, heterotrophic conditions might persist in the LS while the nutrient-rich Pacific inflow will likely stimulate greater primary productivity in the ESS. The contrasting trophic conditions will result in a sharp gradient in δ13C between the LS and ESS, similar to what is documented in our semi-synoptic study.

Carbon isotope-constrained seasonality of carbonaceous aerosol sources from an urban location (Kanpur) in the Indo-Gangetic Plain - Bikkina, Srinivas; Andersson, August; Ram, Kirpa; Sarin, M. M.; Sheesley, Rebecca J.; Kirillova, Elena N.; Rengarajan, R.; Sudheer, A. K.; Gustafsson, Örjan (Journal of Geophysical Research: Atmospheres, 2017)
The Indo-Gangetic Plain (IGP) in northern India, Pakistan and Bangladesh is a major source of carbonaceous aerosols in South Asia. However, poorly constrained seasonality of their sources over the IGP leads to large uncertainty in climate and health effects. Here, we present a first dataset for year-round radiocarbon (Δ14C) and stable carbon (δ13C) based source apportionment of total carbon (TC) in ambient PM10 (n = 17) collected from an urban site (Kanpur: 26.5 °N, 80.3 °E) in the IGP during January 2007-January 2008. The year-round 14C-based fraction biomass (fbio-TC) estimate at Kanpur averages ~77 ± 7%, emphasize an impact of biomass burning emissions (BBEs). The highest fbio-TC(%) is observed in fall season (October-November: 85 ± 6%) followed by winter (December-February: 80 ± 4%) and spring (March-May: 75 ± 8%), while lowest values found in summer (June-September: 69 ± 2%). Since biomass/coal combustion and vehicular emissions mostly contribute to carbonaceous aerosols over the IGP, we predict δ13CTC (δ13Cpred) over Kanpur using known δ13C source signatures and the measured Δ14C value of each sample. The seasonal variability of δ13Cobs - δ13Cpred versus Δ14CTC together with air mass back trajectories and MODIS fire count data reveal that carbonaceous aerosols in winter/fall are significantly influenced by atmospheric aging (downwind transport of crop-residue burning/wood combustion emissions in the northern IGP), while local sources (wheat residue combustion/vehicular emissions) dominate in spring/summer. Given the large temporal and seasonal variability in sources and emission strength of TC over the IGP, 14C-based constraints are, thus, crucial for reducing their uncertainties in carbonaceous aerosol budgets in climate models. Carbon isotope-constrained seasonality of carbonaceous aerosol sources from an urban location (Kanpur) in the Indo-Gangetic Plain: 14Capportionment of carbonaceous aerosol. Available from: https://www.researchgate.net/publication/315970418_Carbon_isotope-constrained_seasonality_of_carbonaceous_aerosol_sources_from_an_urban_location_Kanpur_in_the_Indo-Gangetic_Plain_14Capportionment_of_carbonaceous_aerosol [accessed Jun 2, 2017].

Coastal Research LibraryCoastline Changes of the Baltic Sea from South to EastConstraints of Radiocarbon Dating in Southeastern Baltic Lagoons: Assessing the Vital Effects - Bitinas, Albertas; žeika, Jonas; Buynevich, Ilya V.; šytė, Aldona; Molodkov, Anatoly; ė, Alma (Coastline Changes of the Baltic Sea from South to East, 2017)
During the past decades, a suite of radiocarbon (14C), infrared optically stimulated luminescence (IR-OSL), and electron spin resonance (ESR) dates were compiled on a variety of materials from the Curonian and Vistula lagoons and spits of the southeastern Baltic Sea. These dated materials generally included lagoon sediments and mollusc shells, along with samples of fossil fish remains, peat, wood, and water bicarbonates. A growing number of 14C dates (conventional and AMS) demonstrates disparities and contradictions with the associated IR-OSL dates and palaeobotanical investigations of contemporary materials. Detailed analyses of 14C, IR-OSL and ESR chronologies and experimental 14C dating of modern live molluscs and water bicarbonates from the Curonian Lagoon and its main tributary – Nemunas-Neris River system – reveals a substantial influx of “old” carbonates into the lagoon. As a result, the uncertainty of reservoir effect added a considerable error to the 14C ages. Moreover, fossil molluscs of the same species extracted from boreholes and outcrops yield significantly younger ages (up to several millennia) than the enclosing sediments. Both of these trends – aging and rejuvenation – highlight an urgent need for constraining the local reservoir correction (ΔR). Several scenarios are presented to explain the impact of vital effects on radiocarbon chronology of carbonates and to offer strategies to account for them in future studies.
Keywords: Curonian lagoon; ESR; IR-OSL; Molluscs; radiocarbon; Reservoir effect; Vistula lagoon

The De Long Trough: a newly discovered glacial trough on the East Siberian continental margin - O'Regan, Matt; Backman, Jan; Barrientos, Natalia; Cronin, Thomas M.; Gemery, Laura; Kirchner, Nina; Mayer, Larry A.; Nilsson, Johan; Noormets, Riko; Pearce, Christof; Semiletov, Igor; Stranne, Christian; et al. (Climate of the Past, 2017)
Ice sheets extending over parts of the East Siberian continental shelf have been proposed for the last glacial period and during the larger Pleistocene glaciations. The sparse data available over this sector of the Arctic Ocean have left the timing, extent and even existence of these ice sheets largely unresolved. Here we present new geophysical mapping and sediment coring data from the East Siberian shelf and slope collected during the 2014 SWERUS-C3 expedition (SWERUS-C3: Swedish – Russian – US Arctic Ocean Investigation of Climate-Cryosphere-Carbon Interactions). The multibeam bathymetry and chirp sub-bottom profiles reveal a set of glacial landforms that include grounding zone formations along the outer continental shelf, seaward of which lies a  >  65 m thick sequence of glacio-genic debris flows. The glacial landforms are interpreted to lie at the seaward end of a glacial trough – the first to be reported on the East Siberian margin, here referred to as the De Long Trough because of its location due north of the De Long Islands. Stratigraphy and dating of sediment cores show that a drape of acoustically laminated sediments covering the glacial deposits is older than ∼ 50 cal kyr BP. This provides direct evidence for extensive glacial activity on the Siberian shelf that predates the Last Glacial Maximum and most likely occurred during the Saalian (Marine Isotope Stage (MIS) 6).

Deglaciation and ice shelf development at the northeast margin of the Laurentide Ice Sheet during the Younger Dryas chronozone - Furze, Mark F. A.; ńkowski, Anna J.; McNeely, Morgan A.; Bennett, Robbie; Cage, Alix G. (Boreas, 2017)
Core 2011804-0010 from easternmost Lancaster Sound provides important insights into deglacial timing and style at the marine margin of the NE Laurentide Ice Sheet (LIS). Spanning 13.2–11.0 cal. ka BP and investigated for ice-rafted debris (IRD), foraminifera, biogenic silica and total organic carbon, the stratigraphy comprises a lithofacies progression from proximal grounding line and sub-ice shelf environments to open glaciomarine deposition; a sequence similar to deposits from Antarctic ice shelves. These results are the first marine evidence of a former ice shelf in the eastern Northwest Passage and are consistent with a preceding phase of ice streaming in eastern Lancaster Sound. Initial glacial float-off and retreat occurred >13.2 cal. ka BP, followed by formation of an extensive deglacial ice shelf during the Younger Dryas, which acted to stabilize the retreating margin of the NE LIS until 12.5 cal. ka BP. IRD analyses of sub-ice shelf facies indicate initial high input from source areas on northern Baffin Island delivered to Lancaster Sound by a tributary ice stream in Admiralty Inlet. After ice shelf break-up, Bylot Island became the dominant source area. Foraminifera are dominated by characteristic ice-proximal glaciomarine benthics (Cassidulina reniforme, Elphidium excavatum f. clavata), complemented by advected Atlantic water (Cassidulina neoteretis, Neogloboquadrina pachyderma) and enhanced current indicators (Lobatula lobatula). The biostratigraphy further supports the ice shelf model, with advection of sparse faunas beneath the ice shelf, followed by increased productivity under open water glaciomarine conditions. The absence of Holocene sediments in the core suggests that the uppermost deposits were removed, most likely due to mass transport resulting from the site's proximity to modern tidewater glacier margins. Collectively, this study presents important new constraints on the deglacial behaviour of the NE Laurentide Ice Sheet, with implications for past ice sheet stability, ice-rafted sediment delivery, and ice−ocean interactions in this complex archipelago setting.

Elucidating carbon sources driving microbial metabolism during oil sands reclamation - Lauren M. Bradford; Lori A. Ziolkowski; Corey Goad; Lesley A. Warren; Gregory F. Slater (Journal of Environmental Management, 2017)
Abstract Microbial communities play key roles in remediation and reclamation of contaminated environments via biogeochemical cycling of organic and inorganic components. Understanding the trends in in situ microbial community abundance, metabolism and carbon sources is therefore a crucial component of effective site management. The focus of this study was to use radiocarbon analysis to elucidate the carbon sources driving microbial metabolism within the first pilot wetland reclamation project in the Alberta oil sands region where the observation of \{H2S\} had indicated the occurrence of microbial sulphate reduction. The reclamation project involved construction of a three compartment system consisting of a freshwater wetland on top of a sand cap overlying a composite tailings (CT) deposit. Radiocarbon analysis demonstrated that both dissolved and sediment associated organic carbon associated with the deepest compartments (the \{CT\} and sand cap) was primarily fossil (Δ14C = −769 to −955‰) while organic carbon in the overlying peat was hundreds to thousands of years old (Δ14C = −250 to −350‰). Radiocarbon contents of sediment associated microbial phospholipid fatty acids (PLFA) were consistent with the sediment bulk organic carbon pools (Peat: Δ14CPLFA = −257‰; Sand cap Δ14CPLFA = −805‰) indicating that these microbes were using sediment associated carbon. In contrast, microbial \{PLFA\} grown on biofilm units installed in wells within the deepest compartments contained much more modern carbon that the associated bulk carbon pools. This implied that the transfer of relatively more modern carbon was stimulating the microbial community at depth within the system. Correlation between cellular abundance estimates based on \{PLFA\} concentrations and the Δ14CPLFA indicated that the utilization of this more modern carbon was stimulating the microbial community at depth. These results highlight the importance of understanding the occurrence and potential outcomes of the introduction of relatively bioavailable carbon to mine wastes in order to predict and manage the performance of reclamation strategies.
Keywords: Phospholipid fatty acids (PLFA)

Erosion of modern terrestrial organic matter as a major component of sediments in fjords - Cui, Xingqian; Bianchi, Thomas S.; Savage, Candida (Geophysical Research Letters, 2017)
Fjords have recently been recognized as “hot spots” of carbon burial. In this study, we investigated organic carbon (OC) and biomarker radiocarbon values in fjord sediments from New Zealand. Our results showed that OC was mostly modern with the most aged OC in middle reaches of fjords, likely related to hydrodynamic sorting and inputs along adjacent slopes. Radiocarbon ages of sedimentary OC increased from north-to-south, consistent with the Fiordland regional gradients of lower fjord slopes and less rainfall. Our biomarker results suggested that lignin and long-chain fatty acids were preferentially linked with fresh terrestrial debris and degraded soil, respectively, likely due to their chemical and physical properties. Finally, we propose that fjords are a significant sink of modern OC, in contrast to large lowland coastal systems as a major sink of preaged OC. Overall, this study indicated that radiocarbon techniques are critical in investigating carbon dynamics in coastal systems.

The experimental flow to the Colorado River delta: Effects on carbon mobilization in a dry watercourse - Bianchi, Thomas S.; Butman, David; Raymond, Peter A.; Ward, Nicholas D.; Kates, Rory J. S.; Flessa, Karl W.; Zamora, Hector; Arellano, Ana R.; Ramirez, Jorge; Rodriguez, Eliana (Journal of Geophysical Research: Biogeosciences, 2017)
Here we report on the effects of an experimental flood on the carbon cycling dynamics in the dry watercourse of the Colorado River in Mexico. We observed post‐flood differences in the degree of decay, age, and concentration of dissolved organic carbon (DOC), as well as dissolved CH4 and CO2 concentrations throughout the study site. Our results indicate that this flooded waterway was a limited source of CH4 and CO2 to the atmosphere during the event and that DOC age increased with time of flooding. Based on our findings, we suggest that the interplay between storage and mobilization of carbon and greenhouse gases in arid and semiarid regions is potentially sensitive to changing climate conditions, particularly hydrologic variability. Changes in the radiocarbon age of DOC throughout the flooding event suggest that organic matter (OM) that had been stored for long periods (e.g., millennial) was mobilized by the flooding event along with CO2. The OM residing in the dry riverbed that was mobilized into floodwaters had a signature reflective of degraded vascular plant OM and microbial biomass. Whether this microbial OM was living or dead, our findings support previous work in soils and natural waters showing that microbial OM can remain stable and stored in ecosystems for long time periods. As human appropriation of water resources continues to increase, the episodic drying and rewetting of once natural riverbeds and deltas may fundamentally alter the processing and storage of carbon in such systems.
Keywords: carbon cycling; Colorado River; dry watercourse; flooding; greenhouse gases; mobilization

Extended late Holocene relative sea-level histories for North Carolina, \{USA\} - Andrew C. Kemp; Jessica J. Kegel; Stephen J. Culver; Donald C. Barber; David J. Mallinson; Eduardo Leorri; Christopher E. Bernhardt; Niamh Cahill; Stanley R. Riggs; Anna L. Woodson; Ryan P. Mulligan; Benjamin P. Horton (Quaternary Science Reviews, 2017)
Abstract We produced ∼3000-year long relative sea-level (RSL) histories for two sites in North Carolina (USA) using foraminifera preserved in new and existing cores of dated salt-marsh sediment. At Cedar Island, \{RSL\} rose by ∼2.4 m during the past ∼3000 years compared to ∼3.3 m at Roanoke Island. This spatial difference arises primarily from differential \{GIA\} that caused late Holocene \{RSL\} rise to be 0.1–0.2 mm/yr faster at Roanoke Island than at Cedar Island. However, a non-linear difference in \{RSL\} between the two study regions (particularly from ∼0 \{CE\} to ∼1250 CE) indicates that additional local- to regional-scale processes drove centennial-scale \{RSL\} change in North Carolina. Therefore, the Cedar Island and Roanoke Island records should be considered as independent of one another. Between-site differences on sub-millennial timescales cannot be adequately explained by non-stationary tides, sediment compaction, or local sediment dynamics. We propose that a period of accelerating \{RSL\} rise from ∼600 \{CE\} to 1100 \{CE\} that is present at Roanoke Island (and other sites north of Cape Hatteras at least as far as Connecticut), but absent at Cedar Island (and other sites south of Cape Hatteras at least as far as northeastern Florida) is a local-to regional-scale effect of dynamic ocean and/or atmospheric circulation.
Keywords: Salt marsh

Extreme waves in the British Virgin Islands during the last centuries before 1500 CE - Atwater, Brian F.; ten Brink, Uri S.; Cescon, Anna Lisa; Feuillet, Nathalie; Fuentes, Zamara; Halley, Robert B.; ñez, Carlos; Reinhardt, Eduard G.; Roger, Jean H.; Sawai, Yuki; Spiske, Michaela; Tuttle, Martitia P.; et al. (Geosphere, 2017)
Extraordinary marine inundation scattered clasts southward on the island of Anegada, 120 km south of the Puerto Rico Trench, sometime between 1200 and 1480 calibrated years (cal yr) CE. Many of these clasts were likely derived from a fringing reef and from the sandy flat that separates the reef from the island’s north shore. The scattered clasts include no fewer than 200 coral boulders, mapped herein for the first time and mainly found hundreds of meters inland. Many of these are complete colonies of the brain coral Diploria strigosa. Other coral species represented include Orbicella (formerly Montastraea) annularis, Porites astreoides, and Acropora palmata. Associated bioclastic carbonate sand locally contains articulated cobble-size valves of the lucine Codakia orbicularis and entire conch shells of Strombus gigas, mollusks that still inhabit the sandy shallows between the island’s north shore and a fringing reef beyond. italicmbricated limestone slabs are clustered near some of the coral boulders. In addition, fields of scattered limestone boulders and cobbles near sea level extend mainly southward from limestone sources as much as 1 km inland. Radiocarbon ages have been obtained from 27 coral clasts, 8 lucine valves, and 3 conch shells. All these additional ages predate 1500 cal yr CE, all but 2 are in the range 1000–1500 cal yr CE, and 16 of 22 brain coral ages cluster in the range 1200–1480 cal yr CE. The event marked by these coral and mollusk clasts likely occurred in the last centuries before Columbus (before 1492 CE). The pre-Columbian deposits surpass Anegada’s previously reported evidence for extreme waves in post-Columbian time. The coarsest of the modern storm deposits consist of coral rubble that lines the north shore and sandy fans on the south shore; neither of these storm deposits extends more than 50 m inland. More extensive overwash, perhaps by the 1755 Lisbon tsunami, is marked primarily by a sheet of sand and shells found mainly below sea level beneath the floors of modern salt ponds. This sheet extends more than 1 km southward from the north shore and dates to the interval 1650–1800 cal yr CE. Unlike the pre-Columbian deposits, it lacks coarse clasts from the reef or reef flat; its shell assemblage is instead dominated by cerithid gastropods that were merely stirred up from a marine pond in the island’s interior. In their inland extent and clustered pre-Columbian ages, the coral clasts and associated deposits suggest extreme waves unrivaled in recent millennia at Anegada. Bioclastic sand coats limestone 4 m above sea level in areas 0.7 and 1.3 km from the north shore. A coral boulder of nearly 1 m3 is 3 km from the north shore by way of an unvegetated path near sea level. As currently understood, the extreme flooding evidenced by these and other clasts represents either an extraordinary storm or a tsunami of nearby origin. The storm would need to have produced tsunami-like bores similar to those of 2013 Typhoon Haiyan in the Philippines. Normal faults and a thrust fault provide nearby tsunami sources along the eastern Puerto Rico Trench.

Final Radiocarbon Investigation of Platland Tree, the Biggest African Baobab - Patrut, Adrian; Woodborne, Stephan; Patrut, Roxana T.; Rakosy, Laszlo; Hall, Grant; Ratiu, Ileana-Andreea; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The article discloses the main results of our new investigation of Platland tree, a.k.a. Sunland baobab, the largest known African baobab. Our recent research was motivated by the three successive splits of 2016 and 2017, which determined the collapse and demise of the stems that have built the main unit of the tree. According to our new findings concerning the architecture of large and old baobabs, we established that Platland tree has a double closed-ring shaped structure and consists of two units/rings that close two separate false cavities. The larger unit was composed of five fused stems, out of which four toppled and died, while the fifth stem is already broken. The smaller unit, which is still standing, consists of three fused stems. We also determined that the larger unit had an age of 800 yr, while the smaller unit is 1100 yr old.

Greenhouse gas balance over thaw-freeze cycles in discontinuous zone permafrost - Wilson, R. M.; Fitzhugh, L.; Whiting, G. J.; Frolking, S.; Harrison, M. D.; Dimova, N.; Burnett, W. C.; Chanton, J. P. (Journal of Geophysical Research: Biogeosciences, 2017)
Peat in the discontinuous permafrost zone contains a globally significant reservoir of carbon that has undergone multiple permafrost-thaw cycles since the end of the mid-Holocene (~3700 years before present). Periods of thaw increase C decomposition rates which leads to the release of CO2 and CH4 to the atmosphere creating potential climate feedback. To determine the magnitude and direction of such feedback, we measured CO2 and CH4 emissions and modeled C accumulation rates and radiative fluxes from measurements of two radioactive tracers with differing lifetimes to describe the C balance of the peatland over multiple permafrost-thaw cycles since the initiation of permafrost at the site. At thaw features, the balance between increased primary production and higher CH4 emission stimulated by warmer temperatures and wetter conditions favors C sequestration and enhanced peat accumulation. Flux measurements suggest that frozen plateaus may intermittently (order of years to decades) act as CO2 sources depending on temperature and net ecosystem respiration rates, but modeling results suggest that—despite brief periods of net C loss to the atmosphere at the initiation of thaw—integrated over millennia, these sites have acted as net C sinks via peat accumulation. In greenhouse gas terms, the transition from frozen permafrost to thawed wetland is accompanied by increasing CO2 uptake that is partially offset by increasing CH4 emissions. In the short-term (decadal time scale) the net effect of this transition is likely enhanced warming via increased radiative C emissions, while in the long-term (centuries) net C deposition provides a negative feedback to climate warming.

High-resolution climate of the past ∼7300 years of coastal northernmost California: Results from diatoms, silicoflagellates, and pollen - John A. Barron; David Bukry; Linda E. Heusser; Jason A. Addison; Clark R. Alexander (Quaternary International, 2017)
Abstract Piston core TN062-O550, collected about 33 km offshore of Eureka, California, contains a high-resolution record of the climate and oceanography of coastal northernmost California during the past ∼7.34 kyr. Chronology established by nine \{AMS\} ages on a combination of planktic foraminifers, bivalve shell fragments, and wood yields a mean sedimentation rate of 103 cm kyr−1. Marine proxies (diatoms and silicoflagellates) and pollen transported by the nearby Eel River reveal a stepwise development of both modern offshore surface water oceanography and coastal arboreal ecosystems. Beginning at ∼5.4 cal ka the relative abundance of coastal redwood pollen, a proxy for coastal fog, displays a two fold increase suggesting enhanced coastal upwelling. A decline in the relative contribution of subtropical diatoms at ∼5.0 cal ka implies cooling of sea surface temperatures (SSTs). At ∼3.6 cal ka an increase in the relative abundance of alder and oak at the expense of coastal redwood likely signals intensified riverine transport of pollen from inland environments. Cooler offshore \{SSTs\} and increased precipitation characterize the interval between ∼3.6 and 2.8 cal ka. A rapid, stepwise change in coastal climatology and oceanography occurs between ∼2.8 and 2.6 cal ka that suggests an enhanced expression of modern Pacific Decadal Oscillation-like (PDO) cycles. A three-fold increase in the relative abundance of the subtropical diatom Fragilariopsis doliolus at 2.8 cal ka appears to mark an abrupt warming of winter SSTs. Soon afterwards at 2.6 cal ka, a two fold increase in the relative abundance of coastal redwood pollen is suggestive of an abrupt intensification of spring upwelling. After ∼2.8 cal ka a sequence of cool-warm, PDO-like cycles occurs wherein cool cycles are characterized by relative abundance increases in coastal redwood pollen and decreased contributions of subtropical diatoms, whereas opposite proxy trends distinguish warm cycles.

Holocene climate and environmental history of East Greenland inferred from lake sediments - Lusas, Amanda R.; Hall, Brenda L.; Lowell, Thomas V.; Kelly, Meredith A.; Bennike, Ole; Levy, Laura B.; Honsaker, William (Journal of Paleolimnology, 2017)
Prediction of future Arctic climate and environmental changes, as well as associated ice-sheet behavior, requires placing present-day warming and reduced ice extent into a long-term context. Here we present a record of Holocene climate and glacier fluctuations inferred from the paleolimnology of small lakes near Istorvet ice cap in East Greenland. Calibrated radiocarbon dates of organic remains indicate deglaciation of the region before ~10,500 years BP, after which time the ice cap receded rapidly to a position similar to or less extensive than present, and lake sediments shifted from glacio-lacustrine clay to relatively organic-rich gyttja. The lack of glacio-lacustrine sediments throughout most of the record suggests that the ice cap was similar to or smaller than present throughout most of the Holocene. This restricted ice extent suggests that climate was similar to or warmer than present, in keeping with other records from Greenland that indicate a warm early and middle Holocene. Middle Holocene magnetic susceptibility oscillations, with a ~200-year frequency in one of the lakes, may relate to solar influence on local catchment processes. Following thousands of years of restricted extent, Istorvet ice cap advanced to within 365 m of its late Holocene limit at ~AD 1150. Variability in the timing of glacial and climate fluctuations, as well as of sediment organic content changes among East Greenland lacustrine records, may be a consequence of local factors, such as elevation, continentality, water depth, turbidity, and seabirds, and highlights the need for a detailed spatial array of datasets to address questions about Holocene climate change.
Keywords: De Vries cycle; Glacially fed lakes; Greenland; Holocene; Paleoclimate

Holocene sea ice variability driven by wind and polynya efficiency in the Ross Sea - Mezgec, K.; Stenni, B.; Crosta, X.; Masson-Delmotte, V.; Baroni, C.; Braida, M.; Ciardini, V.; Colizza, E.; Melis, R.; Salvatore, M. C.; Severi, M.; Scarchilli, C.; et al. (Nature Communications, 2017)
The causes of the recent increase in Antarctic sea ice extent, characterised by large regional contrasts and decadal variations, remain unclear. In the Ross Sea, where such a sea ice increase is reported, 50% of the sea ice is produced within wind-sustained latent-heat polynyas. Combining information from marine diatom records and sea salt sodium and water isotope ice core records, we here document contrasting patterns in sea ice variations between coastal and open sea areas in Western Ross Sea over the current interglacial period. Since about 3600 years before present, an increase in the efficiency of regional latent-heat polynyas resulted in more coastal sea ice, while sea ice extent decreased overall. These past changes coincide with remarkable optima or minima in the abundances of penguins, silverfish and seal remains, confirming the high sensitivity of marine ecosystems to environmental and especially coastal sea ice conditions.

Holocene temperatures and isotopes of precipitation in Northwest Greenland recorded in lacustrine organic materials - Lasher, G. Everett; Axford, Yarrow; McFarlin, Jamie M.; Kelly, Meredith A.; Osterberg, Erich C.; Berkelhammer, Max B. (Quaternary Science Reviews, 2017)
Reconstructions of Holocene lake water isotopic composition based upon subfossil aquatic organic material offer new insights into Arctic climate. We present quantitative estimates of warmth during the Holocene Thermal Maximum in northwest Greenland, inferred from oxygen isotopes of chironomid head capsules and aquatic moss preserved in lake sediments. delta O-18 values of chironomids from surface sediments of multiple Greenland lakes indicate that these subfossil remains record the delta O-18 values of the lake water in which they grow. Our lake water delta O-18 reconstruction is supported by downcore agreement with delta O-18 values in aquatic moss and chironomid remains. delta O-18 of both organic materials from Secret Lake decrease after 4 ka (ka = thousands of years ago) by 3 parts per thousand into the Neoglacial. We argue that lake water at Secret Lake primarily reflects precipitation delta O-18 values, which is strongly correlated with air temperature in NW Greenland, and that this signal is biased towards summer and early autumn conditions. Other factors may have influenced Secret Lake delta O-18 values through the Holocene, including evaporation of lake water and changing seasonality and source of precipitation. The maximum early Holocene summer and early autumn-biased temperature anomaly at Secret Lake is 2.5-4 degrees C warmer than present from 7.7 (the beginning of our record) to similar to 6 ka. The maximum late Holocene cold anomaly (which includes the Little Ice Age) is 1.5-3 degrees C colder than present. These ranges of possible temperature anomalies reflect uncertainty in the delta O-18 temperature relationship for precipitation at the study site through the Holocene. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Chironomids; Greenland; Holocene; paleoclimatology; paleolimnology; Stable isotopes

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Pedro Brito; Filipa Naughton; Teresa Drago; Joana Raimundo; Bárbara Anes; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2017)
Abstract Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of 206Pb/207Pb ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high 208Pb/206Pb ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of 208Pb/206Pb ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery

Insights of Pb isotopic signature into the historical evolution and sources of Pb contamination in a sediment core of the southwestern Iberian Atlantic shelf - Mil-Homens, ário; Vale, Carlos; Brito, Pedro; Naughton, Filipa; Drago, Teresa; Raimundo, Joana; Anes, árbara; Schmidt, Sabine; Caetano, Miguel (Science of The Total Environment, 2017)
Stable Pb isotopic ratios and concentrations of Al, Cu and Pb were measured in a 5 m long sediment core (VC2B) retrieved at 96 m water depth in the southwestern Iberian Atlantic shelf. Five phases during the last 9.5 kyrs were identified, two of them (Roman Period and modern mining) marked by a decrease of Pb-206/Pb-207 ratios reflecting additional inputs of Pb derived from mining activities. The Roman Period was also characterized by high Pb-208/Pb-206 ratios suggesting the exploitation of the outcropping portion of the orebody intensely weathered when compared with the other formations later mined. The shift of Pb-208/Pb-206 ratios towards linearity took approximately 1.0 kyrs, which may mirror the time of environmental recovery from the impact of Roman mining activities. The application of a mixing model allowed the quantification of the contribution associated with anthropogenic mining activities to the shelf sediments. The maximum values of Pb contamination occurred in the 20th century. This study gives direct evidence of Pb and Cu exploitation over the last 2000 years. The stable Pb isotopic signatures point to legacy of mining activities that are still the prevailing metal source recorded in the southwestern Iberian Atlantic shelf sediments.
Keywords: Environment recovery; Marine sediments; Pb isotopes; Roman and modem mining activities; Southwestern Iberian shelf; Temporal evolution

Investigation of Late Pleistocene and Holocene Activity in the San Gregorio Fault Zone on the Continental Slope North of Monterey Canyon, Offshore Central California - Maier, Katherine L.; Paull, Charles K.; Brothers, Daniel S.; Caress, David W.; McGann, Mary; Lundsten, Eve M.; Anderson, Krystle; Gwiazda, Roberto (Bulletin of the Seismological Society of America, 2017)
We provide an extensive high‐resolution geophysical, sediment core, and radiocarbon dataset to address late Pleistocene and Holocene fault activity of the San Gregorio fault zone (SGFZ), offshore central California. The SGFZ occurs primarily offshore in the San Andreas fault system and has been accommodating dextral strike‐slip motion between the Pacific and North American plates since the mid‐Miocene. Our study focuses on the SGFZ where it has been mapped through the continental slope north of Monterey Canyon. From 2009 to 2015, the Monterey Bay Aquarium Research Institute collected high‐resolution multibeam bathymetry and chirp sub‐bottom profiles using an autonomous underwater vehicle (AUV). Targeted samples were collected using a remotely operated vehicle (ROV) to provide radiocarbon age constraints. We integrate the high‐resolution geophysical data with radiocarbon dates to reveal Pleistocene seismic horizons vertically offset less than 5 m on nearly vertical faults. These faults are buried by continuous reflections deposited after ∼17.5  ka and likely following erosion during the last sea‐level lowstand ∼21  ka⁠, bracketing the age of faulting to ∼32–21  ka⁠. Clearly faulted horizons are only detected in a small area where mass wasting exhumed older strata to within ∼25  m of the seafloor. The lack of clearly faulted Holocene deposits and possible highly distributed faulting in the study area are consistent with previous interpretations that late Pleistocene and Holocene activity along the SGFZ may decrease to the south. This study illustrates the complexity of the SGFZ, offshore central California, and demonstrates the utility of very high‐resolution data from combined AUV (geophysical)–ROV (seabed sampling) surveys in offshore studies of fault activity.

Local and regional wildfire activity in central Maine (USA) during the past 900 years - Miller, Daniel R.; Castañeda, Isla S.; Bradley, Raymond S.; MacDonald, Dana (Journal of Paleolimnology, 2017)
Climatic and environmental change has a direct effect on wildfire frequencies and distributions throughout many regions of the world. Reconstructions from natural archives such as lake sediments can extend temporally limited historical records of regional wildfire activity over longer timescales through sedimentary charcoal analysis or examining polycyclic aromatic hydrocarbon (PAH) concentrations. To date, little work has been completed on sedimentary PAH distributions from lacustrine records in the Northeastern United States, making it difficult to assess how accurately PAHs trace fire activity in the region, the spatial scope of the signal (local vs. regional), or if certain compounds do a more adequate job of tracking fire than others. In this study, we examine PAHs and macrocharcoal from a varved sedimentary record from Basin Pond, Fayette, Maine (USA). We find that a drastic increase in the concentrations of 12 measured PAHs occurred during the nineteenth to twentieth centuries due to industrialization of the region. Additionally, elevated concentrations of the PAH retene were found to be coeval with known large-scale regional wildfire events that occurred in 1761–1762, 1825, and 1947 (A.D.). We used the ratio of the PAHs retene and chrysene to infer differences in biomass burning versus anthropogenic combustion sources because retene is associated with conifer resin whereas chrysene is associated with fossil fuel burning. Our new Basin Pond PAH records, along with a local signal of fire occurrence from charcoal analysis, offers the prospect of using this multi-proxy approach as a method for examining long-term wildfire frequency at both the local and regional scale in the Northeastern US.

Local glaciation in West Greenland linked to North Atlantic Ocean circulation during the Holocene - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Bennike, Ole; Thomas, Elizabeth K. (Geology, 2017)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.

Micromorphology of late Pleistocene and Holocene sediments and a new interpretation of the Holocene chronology at Anderson Pond, Tennessee, USAAbstract - Driese, Steven G.; Horn, Sally P.; Ballard, Joanne P.; Boehm, Mathew S.; Li, Zhenghua (Quaternary Research, 2017)
Thin-section (micromorphological) analysis of samples from the upper 1.5 m of a core obtained in 2007 from Anderson Pond, Tennessee, reveals a coherent but discontinuous record of late Pleistocene and Holocene climate change that supports some interpretations from previous pollen and charcoal analyses but indicates a revised Holocene chronology for this classic pollen site. Legacy sediments recording anthropogenic disturbance compose the upper 65 cm of the core (<160 cal yr BP) and are characterized by mixed, darker-colored, and coarser-grained deposits containing reworked soil aggregates, which sharply overlie finer-grained and lighter-colored, rooted middle Holocene sediments interpreted as a paleosol. These mid-Holocene sediments (95–65 cm; 7100–5600 cal yr BP) record extensive warm-dry subaerial soil conditions during the middle Holocene thermal maximum, manifested by illuviated clay lining root pores, and also contain abundant charcoal. Late Pleistocene sediments (150–95 cm), dark-colored and organic-rich, record open-water conditions and include siliceous aggregate grains at 143–116 cm (14,300–13,900 cal yr BP), recording intense fires. Thin sections are not commonly used in studies of paleoclimate from Quaternary lacustrine sediments, but we advocate for their inclusion in multianalytical approaches because they enhance resolution of depositional and pedogenic processes.

Millennial mode of variability of sea ice conditions in the Okhotsk Sea during the last glaciation (MIS 4–MIS 2) - Vasilenko, Yuriy P.; Gorbarenko, Sergey A.; Bosin, Aleksandr A.; Shi, Xue-fa; Chen, Min-Te; Zou, Jian-jun; Liu, Yan-guang; Artemova, Antonina V.; Yanchenko, Elena A.; Savenko, Mikhail P. (Quaternary International, 2017)
Coarse fraction (CF) content, grain-size distribution, roundness of CF, gravels and pebbles, and examination of surface of pebbles were studied in core LV28-44-4, recovered from the eastern Okhotsk Sea (OS). The age model of the studied core was based on the AMS 14C data, tephrochronology, δ18O benthic foraminifera record, and correlation of peaks of productivity proxies with long-lasted Dansgaard-Oeschger (DO) interstadials. The results show that sea ice was the main transport agent for CF (ice-rafted debris, IRD) in the eastern OS. Published mineralogical studies of clastic material of the OS indicated that the coast of western Kamchatka was the main source of IRD in the eastern OS. We found 19 peaks of IRD, which mostly coincided with DO stadials. The distribution of CF indicates a different pattern of IRD supply during MIS 4, 3, and 2. Comparison of IRD records in the eastern and central parts of the OS allow us to reconstruct millennial changes in ice and wind modes for MIS 4–MIS 2. Significant strengthening of northeastern and eastern winds during DOSs of MIS 3 and of northern and north-western winds during MIS 2 were observed.
Keywords: Ice mode; Ice-rafted debris; Millennial-scale variation; Okhotsk Sea; Wind mode

Open-File ReportOpen-File ReportDeepwater Program: Lophelia II, continuing ecological research on deep-sea corals and deep-reef habitats in the Gulf of Mexico - Demopoulos, Amanda W.J.; Ross, Steve W.; Kellogg, Christina A.; Morrison, Cheryl L.; Nizinski, Martha S.; Prouty, Nancy G.; Bourque, Jill R.; Galkiewicz, Julie P.; Gray, Michael A.; Springmann, Marcus J.; Coykendall, D. Katharine; Miller, Andrew; et al. (2017)
The deep sea is a rich environment composed of diverse habitat types. While deep-sea coral habitats have been discovered within each ocean basin, knowledge about the ecology of these habitats and associated inhabitants continues to grow. This report presents information and results from the Lophelia II project that examined deep-sea coral habitats in the Gulf of Mexico. The Lophelia II project focused on Lophelia pertusa habitats along the continental slope, at depths ranging from 300 to 1,000 meters. The chapters are authored by several scientists from the U.S. Geological Survey, National Oceanic and Atmospheric Administration, University of North Carolina Wilmington, and Florida State University who examined the community ecology (from microbes to fishes), deep-sea coral age, growth, and reproduction, and population connectivity of deep-sea corals and inhabitants. Data from these studies are presented in the chapters and appendixes of the report as well as in journal publications. This study was conducted by the Ecosystems Mission Area of the U.S. Geological Survey to meet information needs identified by the Bureau of Ocean Energy Management.

Paleohydrology of China Lake basin and the context of early human occupation in the northwestern Mojave Desert, USA - Rosenthal, Jeffrey S.; Meyer, Jack; Palacios-Fest, Manuel R.; Young, D. Craig; Ugan, Andrew; Byrd, Brian F.; Gobalet, Ken; Giacomo, Jason (Quaternary Science Reviews, 2017)
Considerable prior research has focused on the interconnected pluvial basins of Owens Lake and Searles Lake, resulting in a long record of paleohydrological change in the lower Owens River system. However, the published record is poorly resolved or contradictory for the period encompassing the terminal Pleistocene (22,000 to 11,600 cal BP) and early Holocene (11,600-8200 cal BP). This has resulted in conflicting interpretations about the timing of lacustrine high stands within the intermediate basin of China Lake, which harbors one of the most extensive records of early human occupation in the western Great Basin and California. Here, we report a broad range of radiocarbon-dated paleoenvironmental evidence, including lacustrine deposits and shoreline features, tufa outcrops, and mollusk, ostracode, and fish bone assemblages, as well as spring and other groundwater-related deposits (a.k.a. "black mats") from throughout China Lake basin, its outlet, and inflow drainages. Based on 98 radiocarbon dates, we develop independent evidence for five significant lake-level oscillations between 18,000 and 13,000 cal BP, and document the persistence of groundwater-fed wetlands from the beginning of the Younger Dryas through the early Holocene (12,900-8200 cal BP); including the transition from ground-water fed lake to freshwater marsh between about 13,000 and 12,600 cal BP. Results of this study support and refine existing evidence that shows rapid, high-amplitude oscillations in the water balance of the Owens River system during the terminal Pleistocene, and suggest widespread human use of China Lake basin began during the Younger Dryas.

Permafrost Organic Carbon Mobilization From the Watershed to the Colville River Delta: Evidence From 14C Ramped Pyrolysis and Lignin Biomarkers - Zhang, Xiaowen; Bianchi, Thomas S.; Cui, Xingqian; Rosenheim, Brad E.; Ping, Chien‐Lu; Hanna, Andrea J. M.; Kanevskiy, Mikhail; Schreiner, Kathryn M.; Allison, Mead A. (Geophysical Research Letters, 2017)
The deposition of terrestrial‐derived permafrost particulate organic carbon (POC) has been recorded in major Arctic river deltas. However, associated transport pathways of permafrost POC from the watershed to the coast have not been well constrained. Here we utilized a combination of ramped pyrolysis‐oxidation radiocarbon analysis (RPO 14C) along with lignin biomarkers, to track the linkages between soils and river and delta sediments. Surface and deep soils showed distinct RPO thermographs which may be related to degradation and organo‐mineral interaction. Soil material in the bed load of the river channel was mostly derived from deep old permafrost. Both surface and deep soils were transported and deposited to the coast. Hydrodynamic sorting and barrier island protection played important roles in terrestrial‐derived permafrost POC deposition near the coast. On a large scale, ice processes (e.g., ice gauging and strudel scour) and ocean currents controlled the transport and distribution of permafrost POC on the Beaufort Shelf.
Keywords: Arctic; carbon cycling; Colville River; Lignin; permafrost; pyrolysis

Proceedings of the International Ocean Discovery ProgramExpedition 357 methods - Früh-Green, G.L.; Orcutt, B.N.; Green, S.L.; Cotterill, C.; Morgan, S.; Akizawa, N.; Bayrakci, G.; Behrmann, J.-H.; Boschi, C.; Brazleton, W.J.; Cannat, M.; Dunkel, K.G.; et al. (International Ocean Discovery Program, 2017)

Reconstructing Common Era relative sea-level change on the Gulf Coast of Florida - Gerlach, Matthew J.; Engelhart, Simon E.; Kemp, Andrew C.; Moyer, Ryan P.; Smoak, Joseph M.; Bernhardt, Christopher E.; Cahill, Niamh (Marine Geology, 2017)
To address a paucity of Common Era data in the Gulf of Mexico, we reconstructed ~ 1.1 m of relative sea-level (RSL) rise over the past ~ 2000 years at Little Manatee River (Gulf Coast of Florida, USA). We applied a regional-scale foraminiferal transfer function to fossil assemblages preserved in a core of salt-marsh peat and organic silt that was dated using radiocarbon and recognition of pollution, 137Cs and pollen chronohorizons. Our proxy reconstruction was combined with tide-gauge data from four nearby sites spanning 1913–2014 CE. Application of an Errors-in-Variables Integrated Gaussian Process (EIV-IGP) model to the combined proxy and instrumental dataset demonstrates that RSL fell from ~ 350 to 100 BCE, before rising continuously to present. This initial RSL fall was likely the result of local-scale processes (e.g., silting up of a tidal flat or shallow sub-tidal shoal) as salt-marsh development at the site began. Since ~ 0 CE, we consider the reconstruction to be representative of regional-scale RSL trends. We removed a linear rate of 0.3 mm/yr from the RSL record using the EIV-IGP model to estimate climate-driven sea-level trends and to facilitate comparison among sites. This analysis demonstrates that since ~ 0 CE sea level did not deviate significantly from zero until accelerating continuously from ~ 1500 CE to present. Sea level was rising at 1.33 mm/yr in 1900 CE and accelerated until 2014 CE when a rate of 2.02 mm/yr was attained, which is the fastest, century-scale trend in the ~ 2000-year record. Comparison to existing reconstructions from the Gulf coast of Louisiana and the Atlantic coast of northern Florida reveal similar sea-level histories at all three sites. We explored the influence of compaction and fluvial processes on our reconstruction and concluded that compaction was likely insignificant. Fluvial processes were also likely insignificant, but further proxy evidence is needed to fully test this hypothesis. Our results indicate that no significant Common Era sea-level changes took place on the Gulf and southeastern Atlantic U.S. coasts until the onset of modern sea-level rise in the late 19th century.

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Maier, Katherine L.; Brothers, Daniel S.; Paull, Charles K.; McGann, Mary; Caress, David W.; Conrad, James E. (Marine Geology, 2017)
Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (~ 100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ = ~ 100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Deep-water channel; Gradient; Holocene; Sediment waves; Turbidite Fault

Reversible adsorption and flushing of arsenic in a shallow, Holocene aquifer of Bangladesh - Kathleen A. Radloff; Yan Zheng; Martin Stute; Beth Weinman; Benjamin Bostick; Ivan Mihajlov; Margaret Bounds; M.Moshiur Rahman; M.Rezaul Huq; Kazi M. Ahmed; Peter Schlosser; Alexander van Geen (Applied Geochemistry, 2017)
Abstract The spatial heterogeneity of dissolved arsenic (As) concentrations in shallow groundwater of the Bengal Basin has been attributed to transport of As (and reactive carbon) from external sources or to the release of As from within grey sand formations. We explore the latter scenario in this detailed hydrological and geochemical study along a 300 m transect of a shallow aquifer extending from a groundwater recharge area within a sandy channel bar to its discharge into a nearby stream. Within the 10–20 m depth range, groundwater ages along the transect determined by the 3H–3He method increase from <10 yr in the recharge area to a maximum of 40 yr towards the stream. Concentrations of groundwater As within the same grey sands increase from 10 to 100 to ∼500 μg/L along this transect. Evidence of reversible adsorption of As between the groundwater and sediment was obtained from a series of push–pull experiments, traditional batch adsorption experiments, and the accidental flooding of a shallow monitoring well. Assuming reversible adsorption and a distribution coefficient, Kd, of 0.15–1.5 L/kg inferred from these observations, a simple flushing model shows that the increase in As concentrations with depth and groundwater age at this site, and at other sites in the Bengal and Red River Basins, can be attributed to the evolution of the aquifer over 100–1000 years as aquifer sands are gradually flushed of their initial As content. A wide range of As concentrations can thus be maintained in groundwater with increases with depth governed by the history of flushing and local recharge rates, without external inputs of reactive carbon or As from other sources.
Environmental and Health Roles of Geogenic Arsenic
Keywords: Push–pull tests

Timing and magnitude of early to middle Holocene warming in East Greenland inferred from chironomids - Axford, Yarrow; Levy, Laura B.; Kelly, Meredith A.; Francis, Donna R.; Hall, Brenda L.; Langdon, Peter G.; Lowell, Thomas V. (Boreas, 2017)
Much of Greenland experienced summers warmer than present in parts of the early to middle Holocene, during a precession‐driven positive anomaly in summer insolation. However, the magnitude of that warmth remains poorly known, and its timing and spatial pattern are uncertain. Here we describe the first quantitative Holocene palaeotemperature reconstruction from central East Greenland based upon insect (chironomid) assemblages preserved in lake sediments. We postulate that landscapes like our study site, characterized by minimal soil and vegetation development through the Holocene and thus little influenced by some important secondary gradients, are especially well suited to the use of chironomids to reconstruct Holocene temperatures. The inferred timing of warmth at our study site near Scoresby Sund agrees well with other nearby evidence, including glacial geological reconstructions and temperatures inferred from precipitation isotopes at Renland ice cap, supporting the use of chironomids to reconstruct temperatures at this site. We infer highest temperatures from c. 10 to 5.5 ka, followed by gradual cooling after 5.5 ka and progressively colder and less productive conditions after 3.5 ka. Models based upon two independent training sets yield similar inferred temperature trends, and suggest an average summer temperature anomaly from c. 10 to 5.5 ka of 3 to 4 °C relative to the preindustrial last millennium. The estimated overall rate of Neoglacial cooling averaged over the period from 5.5 to 0.5 ka was 0.6 to 0.8 °C per thousand years, more than twice the rate previously estimated for the Arctic as a whole. Given strong apparent spatial variability in Holocene climate around the Arctic, and the utility of palaeoclimate data for improving climate and ice‐sheet models, it should be a priority to further quantify past temperature changes around the margins of the Greenland Ice Sheet, where few quantitative reconstructions exist and future warming will affect global sea level.

Trends in catchment processes and lake evolution during the late-glacial and early- to mid-Holocene inferred from high-resolution XRF data in the Yellowstone region - Lu, Yanbin; Fritz, Sherilyn C.; Stone, Jeffery R.; Krause, Teresa R.; Whitlock, Cathy; Brown, Erik T.; Benes, James V. (Journal of Paleolimnology, 2017)
High-resolution records of geochemical data from four lakes in the Greater Yellowstone region were used to investigate watershed and lake history during the late-glacial and early-Holocene periods. Clastic input to regional lakes was high and variable during the early stages of lake development, when the surrounding landscape was geomorphically unstable and sparsely vegetated, and it decreased as vegetation gradually developed in each catchment. The decrease of clastic input was not regionally synchronous but occurred in a time-transgressive pattern from south to north. Long-term organic matter concentration and diatom production were inversely related to catchment erosion during the early stages of lake development and increased as temperatures warmed and in-lake nutrient concentrations increased. Similarly, calcite production usually was low following lake formation and increased over time, driven by climate change and its associated influences on lake-level, algal production, and lake thermal structure. Overall differences in the timing and pattern of geochemical change indicate that once the landscape had stabilized following deglaciation, changes in the geochemical character of the sediments were strongly influenced by local factors.

Tropical Pacific climate variability over the last 6000 years as recorded in Bainbridge Crater Lake, Galápagos - Thompson, Diane M.; Conroy, Jessica L.; Collins, Aaron; Hlohowskyj, Stephan R.; Overpeck, Jonathan T.; Riedinger-Whitmore, Melanie; Cole, Julia E.; Bush, Mark B.; Whitney, H.; Corley, Timothy L.; Kannan, Miriam Steinitz (Paleoceanography, 2017)
Finely laminated sediments within Bainbridge Crater Lake, Galápagos, provide a record of El Niño–Southern Oscillation (ENSO) events over the Holocene. Despite the importance of this sediment record, hypotheses for how climate variability is preserved in the lake sediments have not been tested. Here we present results of long‐term monitoring of the local climate and limnology and a revised interpretation of the sediment record. Brown‐green, organic‐rich, siliciclastic laminae reflect warm, wet conditions typical of El Niño events, whereas carbonate and gypsum precipitate during cool, dry La Niña events and persistent dry periods, respectively. Applying this new interpretation, we find that ENSO events of both phases were generally less frequent during the mid‐Holocene (~6100–4000 calendar years B.P.) relative to the last ~1500 calendar years. Abundant carbonate laminations between 3500 and 3000 calendar years B.P. imply that conditions in the Galápagos region were cool and dry during this period when the tropical Pacific E‐W sea surface temperature (SST) gradient likely strengthened. The frequency of El Niño and La Niña events then intensified dramatically around 1750–2000 calendar years B.P., consistent with a weaker SST gradient and an increased frequency of ENSO events in other regional records. This strong interannual variability persisted until ~700 calendar years B.P., when ENSO‐related variability at the lake decreased as the SST gradient strengthened. Persistent, dry conditions then dominated between 300 and 50 calendar years B.P. (A.D. 1650–1900, ± ~100 years), whereas wetter conditions and frequent El Niño events dominated in the most recent century.
Keywords: Climate variability; El Niño–Southern Oscillation(ENSO); Galápagos archipelago; mid‐Holocene; monitoring; tropical Pacific Ocean

Utility of salt-marsh foraminifera, testate amoebae and bulk-sediment δ13C values as sea-level indicators in Newfoundland, Canada - Kemp, Andrew C.; Wright, Alexander J.; Barnett, Robert L.; Hawkes, Andrea D.; Charman, Dan J.; Sameshima, Colby; King, Alexandra N.; Mooney, Hailey C.; Edwards, Robin J.; Horton, Benjamin P.; van de Plassche, Orson (Marine Micropaleontology, 2017)
We investigated the utility of foraminifera, testate amoebae and bulk-sediment δ13C measurements for reconstructing Holocene relative sea level from sequences of salt-marsh sediment in Newfoundland, Canada. Modern, surface sediment was collected along transects from low to supra-tidal elevations in eastern (at Placentia) and western (at Hynes Brook and Big River) Newfoundland. Consistent with previous work, low-diversity assemblages of foraminifera display an almost binary division into a higher salt-marsh assemblage dominated by Jadammina macrescens and Balticammina pseudomacrescens and a lower salt-marsh assemblage comprised of Miliammina fusca. This pattern and composition resembles those identified at other high latitude sites with cool climates and confirms that foraminifera are sea-level indicators. The lowest occurrence of testate amoebae was at approximately mean higher high water. The composition of high salt-marsh testate amoebae assemblages (Centropyxis cassis type, Trinema spp., Tracheleuglypha dentata type, and Euglypha spp.) in Newfoundland was similar to elsewhere in the North Atlantic, but preservation bias favors removal of species with idiosomic tests over those with xenosomic tests. The mixed high salt-marsh plant community in Newfoundland results in bulk surface-sediment δ13C values that are typical of C3 plants, making them indistinguishable from freshwater sediment. Therefore we propose that the utility of this proxy for reconstructing RSL in eastern North America is restricted to the coastline between Chesapeake Bay and southern Nova Scotia. Using a simple, multi-proxy approach to establish that samples in three radiocarbon-dated sediment cores formed between the lowest occurrence of testate amoebae and the highest occurrence of foraminifera, we generated three example late Holocene sea-level index points at Hynes Brook.

What on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic CarbonWhat on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic Carbon - Hanke, Ulrich M.; Reddy, Christopher M.; Braun, Ana L. L.; Coppola, Alysha I.; Haghipour, Negar; McIntyre, Cameron P.; Wacker, Lukas; Xu, Li; McNichol, Ann P.; Abiven, Samuel; Schmidt, Michael W. I.; Eglinton, Timothy I. (Environmental Science & Technology, 2017)
Humans have interacted with fire for thousands of years, yet the utilization of fossil fuels marked the beginning of a new era. Ubiquitous in the environment, pyrogenic carbon (PyC) arises from incomplete combustion of biomass and fossil fuels, forming a continuum of condensed aromatic structures. Here, we develop and evaluate 14C records for two complementary PyC molecular markers, benzene polycarboxylic acids (BPCAs) and polycyclic aromatic hydrocarbons (PAHs), preserved in aquatic sediments from a suburban and a remote catchment in the United States (U.S.) from the mid-1700s to 1998. Results show that the majority of PyC stems from local sources and is transferred to aquatic sedimentary archives on subdecadal to millennial time scales. Whereas a small portion stems from near-contemporaneous production and sedimentation, the majority of PyC (∼90%) experiences delayed transmission due to “preaging” on millennial time scales in catchment soils prior to its ultimate deposition. BPCAs (soot) and PAHs (precursors of soot) trace fossil fuel-derived PyC. Both markers parallel historical records of the consumption of fossil fuels in the U.S., yet never account for more than 19% total PyC. This study demonstrates that isotopic characterization of multiple tracers is necessary to constrain histories and inventories of PyC and that sequestration of PyC can markedly lag its production.

Younger-Dryas cooling and sea-ice feedbacks were prominent features of the Pleistocene-Holocene transition in Arctic Alaska - Gaglioti, Benjamin V.; Mann, Daniel H.; Wooller, Matthew J.; Jones, Benjamin M.; Wiles, Gregory C.; Groves, Pamela; Kunz, Michael L.; Baughman, Carson A.; Reanier, Richard E. (Quaternary Science Reviews, 2017)
Declining sea-ice extent is currently amplifying climate warming in the Arctic. Instrumental records at high latitudes are too short-term to provide sufficient historical context for these trends, so paleoclimate archives are needed to better understand the functioning of the sea ice-albedo feedback. Here we use the oxygen isotope values of wood cellulose in living and sub-fossil willow shrubs (δ18Owc) (Salix spp.) that have been radiocarbon-dated (14C) to produce a multi-millennial record of climatic change on Alaska's North Slope during the Pleistocene-Holocene transition (13,500–7500 calibrated 14C years before present; 13.5–7.5 ka). We first analyzed the spatial and temporal patterns of δ18Owc in living willows growing at upland sites and found that over the last 30 years δ18Owc values in individual growth rings correlate with local summer temperature and inter-annual variations in summer sea-ice extent. Deglacial δ18Owc values from 145 samples of subfossil willows clearly record the Allerød warm period (∼13.2 ka), the Younger Dryas cold period (12.9–11.7 ka), and the Holocene Thermal Maximum (11.7–9.0 ka). The magnitudes of isotopic changes over these rapid climate oscillations were ∼4.5‰, which is about 60% of the differences in δ18Owc between those willows growing during the last glacial period and today. Modeling of isotope-precipitation relationships based on Rayleigh distillation processes suggests that during the Younger Dryas these large shifts in δ18Owc values were caused by interactions between local temperature and changes in evaporative moisture sources, the latter controlled by sea ice extent in the Arctic Ocean and Bering Sea. Based on these results and on the effects that sea-ice have on climate today, we infer that ocean-derived feedbacks amplified temperature changes and enhanced precipitation in coastal regions of Arctic Alaska during warm times in the past. Today, isotope values in willows on the North Slope of Alaska are similar to those growing during the warmest times of the Pleistocene-Holocene transition, which were times of widespread permafrost thaw and striking ecological changes.
Keywords: alaska; Arctic; Bering Strait; Climate change; dendrochronology; north pacific; oxygen isotopes; Paleoclimate; Sea ice; Younger Dryas

10Be dating reveals early-middle Holocene age of the Drygalski Moraines in central West Greenland - Sandra L. Cronauer; Jason P. Briner; Samuel E. Kelley; Susan R.H. Zimmerman; Mathieu Morlighem (Quaternary Science Reviews, 2016)
Abstract We reconstruct the history of the Greenland Ice Sheet margin on the Nuussuaq Peninsula in central West Greenland through the Holocene using lake sediment analysis and cosmogenic 10Be exposure dating of the prominent Drygalski Moraines. Erratics perched on bedrock outboard of the Drygalski Moraines constrain local deglaciation to ∼9.9 ± 0.6 ka (n = 2). Three Drygalski Moraine crests yield mean 10Be ages of 8.6 ± 0.4 ka (n = 2), 8.5 ± 0.2 ka (n = 3), and 7.6 ± 0.1 ka (n = 2) from outer to inner. Perched erratics between the inner two moraines average 7.8 ± 0.1 ka (n = 2) and are consistent with the moraine ages. Sediments from a proglacial lake with a catchment area extending an estimated 2 km beneath (inland of) the present ice sheet terminus constrain an ice sheet minimum extent from 5.4 ka to 0.6 ka. The moraine chronology paired with the lake sediment stratigraphy reveals that the ice margin likely remained within ∼2 km of its present position from ∼9.9 to 5.4 ka. This unexpected early Holocene stability, preceded by rapid ice retreat and followed by minimum ice extent between ∼5.4 and 0.6 ka, contrasts with many records of early Holocene warmth and the Northern Hemisphere summer insolation maximum. We suggest ice margin stability may instead be tied to adjacent ocean temperatures, which reached an optimum in the middle Holocene.
Special Issue: \{PAST\} Gateways (Palaeo-Arctic Spatial and Temporal Gateways)
Keywords: Holocene

Age of the Mt. Ortles ice cores, the Tyrolean Iceman and glaciation of the highest summit of South Tyrol since the Northern Hemisphere Climatic Optimum - Gabrielli, Paolo; Barbante, Carlo; Bertagna, Giuliano; ó, Michele; Binder, Daniel; Carton, Alberto; Carturan, Luca; Cazorzi, Federico; Cozzi, Giulio; Dalla Fontana, Giancarlo; Davis, Mary; De Blasi, Fabrizio; et al. (The Cryosphere, 2016)
In 2011 four ice cores were extracted from the summit of Alto dell’Ortles (3859 m), the highest glacier of South Tyrol in the Italian Alps. This drilling site is located only 37 km southwest from where the Tyrolean Iceman, ∼5.3 kyrs old, was discovered emerging from the ablating ice field of Tisenjoch (3210 m, near the Italian–Austrian border) in 1991. The excellent preservation of this mummy suggested that the Tyrolean Iceman was continuously embedded in prehistoric ice and that additional ancient ice was likely preserved elsewhere in South Tyrol. Dating of the ice cores from Alto dell’Ortles based on 210Pb, tritium, beta activity and 14C determinations, combined with an empirical model (COPRA), provides evidence for a chronologically ordered ice stratigraphy from the modern glacier surface down to the bottom ice layers with an age of ∼7 kyrs, which confirms the hypothesis. Our results indicate that the drilling site has continuously been glaciated on frozen bedrock since ∼7 kyrs BP. Absence of older ice on the highest glacier of South Tyrol is consistent with the removal of basal ice from bedrock during the Northern Hemisphere Climatic Optimum (6–9 kyrs BP), the warmest interval in the European Alps during the Holocene. Borehole inclinometric measurements of the current glacier flow combined with surface ground penetration radar (GPR) measurements indicate that, due to the sustained atmospheric warming since the 1980s, an acceleration of the glacier Alto dell’Ortles flow has just recently begun. Given the stratigraphic chronological continuity of the Mt. Ortles cores over millennia, it can be argued that this behaviour has been unprecedented at this location since the Northern Hemisphere Climatic Optimum.

Biospheric and petrogenic organic carbon flux along southeast Alaska - Xingqian Cui; Thomas S. Bianchi; John M. Jaeger; Richard W. Smith (Earth and Planetary Science Letters, 2016)
Abstract Holocene fjords store ca. 11–12% of the total organic carbon (OC) buried in marine sediments with fjords along southeast (SE) Alaska possibly storing half of this \{OC\} (Smith et al., 2015). However, the respective burial of biospheric (OCbio) and petrogenic \{OC\} (OCpetro) remains poorly constrained, particularly across glaciated versus non-glaciated systems. Here, we use surface sediment samples to quantify the sources and burial of sedimentary \{OC\} along \{SE\} Alaska fjord-coastal systems, and conduct a latitudinal comparison across a suite of fjords and river-coastal systems with distinctive \{OC\} sources. Our results for \{SE\} Alaska show that surface sediments in northern fjords (north of Icy Strait) with headwater glaciers are dominated by OCpetro, in contrast to marine and terrestrially-derived fresh \{OC\} in non-glaciated southern fjords. Along the continental shelf of the Gulf of Alaska, terrestrial \{OC\} is exported from rivers. Using end-member mixing models, we determine that glaciated fjords have significantly higher burial rates of \{OCpetro\} ( ∼ 1.1 × 10 3   g \{OC\}   m − 2 yr − 1 ) than non-glaciated fjords and other coastal systems, making \{SE\} Alaska potentially the largest sink of \{OCpetro\} in North America. In contrast, non-glaciated fjords in \{SE\} Alaska are effective in burying marine \{OC\} (OCbio-mari) (13–82 g  \{OC\}   m − 2 yr − 1 ). Globally, \{OC\} in fjord sediments are comprised of a mixture of \{OCpetro\} and fresh OCbio, in contrast to the pre-aged \{OC\} from floodplain river-coastal systems. We find that there may be a general latitudinal trend in the role of fjords in processing OC, where high-latitude temperate glacial fjords (e.g., Yakutat Bay, \{SE\} Alaska) rebury \{OCpetro\} and non-glacial mid-latitude fjords (e.g., Doubtful Sound, Fiordland) sequester \{CO2\} from phytoplankton and/or temperate forests. Overall, we propose that fjords are effective in sequestering \{OCbio\} and re-burying OCpetro. Based on our study, we hypothesize that climate change will have a semi-predictable impact on fjords' \{OC\} cycling in the near future.
Keywords: glaciers

Comparison of eastern tropical Pacific TEX 86 and Globigerinoides ruber Mg/Ca derived sea surface temperatures: Insights from the Holocene and Last Glacial Maximum - Hertzberg, Jennifer E.; Schmidt, Matthew W.; Bianchi, Thomas S.; Smith, Richard W.; Shields, Michael R.; Marcantonio, Franco (Earth and Planetary Science Letters, 2016)
The use of the TEX86TEX86 temperature proxy has thus far come to differing results as to whether TEX86TEX86 temperatures are representative of surface or subsurface conditions. In addition, although TEX86TEX86 temperatures might reflect sea surface temperatures based on core-top (Holocene) values, this relationship might not hold further back in time. Here, we investigate the TEX86TEX86 temperature proxy by comparing TEX86TEX86 temperatures to Mg/Ca temperatures of multiple species of planktonic foraminifera for two sites in the eastern tropical Pacific (on the Cocos and Carnegie Ridges) across the Holocene and Last Glacial Maximum. Core-top and Holocene View the MathML sourceTEX86H temperatures at both study regions agree well, within error, with the Mg/Ca temperatures of Globigerinoides ruber , a surface dwelling planktonic foraminifera. However, during the Last Glacial Maximum, View the MathML sourceTEX86H temperatures are more representative of upper thermocline temperatures, and are offset from G. ruber Mg/Ca temperatures by 5.8 °C and 2.9 °C on the Cocos Ridge and Carnegie Ridge, respectively. This offset between proxies cannot be reconciled by using different TEX86TEX86 temperature calibrations, and instead, we suggest that the offset is due to a deeper export depth of GDGTs at the LGM. We also compare the degree of glacial cooling at both sites based on both temperature proxies, and find that View the MathML sourceTEX86H temperatures greatly overestimate glacial cooling, especially on the Cocos Ridge. This study has important implications for applying the TEX86TEX86 paleothermometer in the eastern tropical Pacific.
Keywords: Foraminifera; Holocene; LGM; Pacific Ocean; Mg/Ca; TEX86TEX86

Complex coastal change in response to autogenic basin infilling: An example from a sub-tropical Holocene strandplain - Hein, Christopher J.; FitzGerald, Duncan M.; de Souza, Luis H. P.; Georgiou, Ioannis Y.; Buynevich, Ilya V.; Klein, Antonio H. da F.; de Menezes, ão Thadeu; Cleary, William J.; Scolaro, Thelma L. (Sedimentology, 2016)
Thick bay-fill sequences that often culminate in strandplain development serve as important sedimentary archives of land–ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground-penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes – notably a reduction in wave energy in response to coastal embayment infilling – in coastal evolution and shoreline morphodynamics. Following a regional 2 to 4 m highstand at ca 5·8 ka, the 75 km2 Tijucas Strandplain in southern Brazil built from fluvial sediments deposited into a semi-enclosed bay. Holocene regressive deposits are underlain by fluvial sands and a Pleistocene transgressive–regressive sequence, and backed by a highstand barrier-island. The strandplain is immediately underlain by 5 to 16 m of seaward-thickening, fluvially derived, Holocene-age, basin-fill mud. Several trends are observed from the landward (oldest) to the seaward (youngest) sections of the strandplain: (i) the upper shoreface and foreshore become finer and thinner and shift from sand-dominated to mud-dominated; (ii) beachface slopes decrease from >11° to ca 7°; and (iii) progradation rates increase from 0·4 to 1·8 m yr−1. Hydrodynamic modelling demonstrates a correlation between progressive shoaling of Tijucas Bay driven by sea-level fall and sediment infilling and a decrease in onshore wave-energy transport from 18 to 4 kW m−1. The combination of allogenic (sediment supply, falling relative sea-level and geology) and autogenic (decrease in wave energy due to bay shoaling) processes drove the development of a regressive system with characteristics that are rare, if not unique, in the Holocene and rock records. These findings demonstrate the complexities in architecture styles of highstand and regressive systems tracts. Furthermore, this article highlights the diverse internal and external processes and feedbacks responsible for the development of these intricate marginal marine sedimentary systems.

Conduits, timing and processes of sediment delivery across a high-relief continental margin: Continental shelf to basin in Late Quaternary, Gulf of Papua - Erlangga Septama; Samuel J. Bentley; André W. Droxler (Marine and Petroleum Geology, 2016)
Abstract The Gulf of Papua (GoP), between Australia and Papua New Guinea, is the receiving basin for multiple substantial rivers draining southern Papua New Guinea with collective sediment discharge >> 220 million metric tons (Mt) per year, comparable to a continental-scale river, but draining a combined catchment area of only ∼160,000 km2. This study of the deepest marginal basins in the Gulf of Papua was undertaken to build a regional late Quaternary lithofacies and stratigraphic framework to better understand processes, timing, and conduits of sediment delivery from terrestrial and shelf settings to deep marginal basins, using the GoP as a natural laboratory. Methods include observations of sediment-core stratigraphy and physical properties, accelerometer mass spectrometry (AMS) C-14 dates, core x-radiographs and thin sections. Six lithofacies across the deep water Gulf of Papua (GoP) are identified based on core visual and textural observation. Chronological constraints permit an assessment of changes in sediment supply and depositional environments across time and space, from marine isotope stage (MIS) -3 to -1, or in the last 40 cal ka. The sediment delivery to the deep water GoP is dominated by two mechanisms, gravity-driven flows down slopes and into deep sea basin primarily during lowstands in the western portions of the study area, and hemipelagic sediment accumulation during transgression and highstand. Although the sediment flux appears to be overall dominated by sediment-gravity flows, hemipelagic sediment delivery is widespread during periods of sea level highstand. In the eastern portions of the study area, off-shelf sediment delivery continued into the Holocene in sufficient local volumes to produce turbidity currents. This late, localized sediment delivery appears to have been facilitated by oceanographic processes that allowed seaward sediment transport after flooding of the shelf. A simple sediment budget comparing basinal sediment accumulation to modern estimated river-sediment discharge indicates that peak sediment accumulation in proximal basins occurred during MIS-2; and declined thereafter, generally shifting to upper slope locations, except for the eastern margin of Moresby Trough. There, turbidite deposition continued until 7.4 cal ka, well after drowning of the shelf edge. This continued Holocene deep-sea sediment delivery is likely explained by the local narrow shelf width, and the presence of oceanographic processes capable of transporting sediments from shore to shelf edge.
Keywords: Deep-sea

Differences in coastal subsidence in southern Oregon (USA) during at least six prehistoric megathrust earthquakes - Milker, Yvonne; Nelson, Alan R.; Horton, Benjamin P.; Engelhart, Simon E.; Bradley, Lee-Ann; Witter, Robert C. (Quaternary Science Reviews, 2016)
Stratigraphic, sedimentologic (including CT 3D X-ray tomography scans), foraminiferal, and radiocarbon analyses show that at least six of seven abrupt peat-to-mud contacts in cores from a tidal marsh at Talbot Creek (South Slough, Coos Bay), record sudden subsidence (relative sea-level rise) during great megathrust earthquakes at the Cascadia subduction zone. Data for one contact are insufficient to infer whether or not it records a great earthquake—it may also have formed through local, non-seismic, hydrographic processes. To estimate the amount of subsidence marked by each contact, we expanded a previous regional modern foraminiferal dataset to 174 samples from six Oregon estuaries. Using a transfer function derived from the new dataset, estimates of coseismic subsidence across the six earthquake contacts vary from 0.31 m to 0.75 m. Comparison of subsidence estimates for three contacts in adjacent cores shows within-site differences of ≤0.10 m, about half the ±0.22 m error, although some estimates may be minimums due to uncertain ecological preferences for Balticammina pseudomacrescens in brackish environments and almost monospecific assemblages of Miliammina fusca on tidal flats. We also account for the influence of taphonomic processes, such as infiltration of mud with mixed foraminiferal assemblages into peat, on subsidence estimates. Comparisons of our subsidence estimates with values for correlative contacts at other Oregon sites suggest that some of our estimates are minimums and that Cascadia's megathrust earthquake ruptures have been heterogeneous over the past 3500 years.
Keywords: Cascadia subduction zone; Coseismic subsidence; Megathrust earthquakes; Paleoseismology; Salt-marsh foraminifera; Sea-level change; Transfer functions

Dual carbon isotope characterization of total organic carbon in wintertime carbonaceous aerosols from northern India - Bikkina, Srinivas; Andersson, August; Sarin, M. M.; Sheesley, R. J.; Kirillova, E.; Rengarajan, R.; Sudheer, A. K.; Ram, K.; Gustafsson, Örjan (Journal of Geophysical Research: Atmospheres, 2016)
Large-scale emissions of carbonaceous aerosols (CA) from South Asia impact both regional climate and air quality, yet their sources are not well constrained. Here we use source-diagnostic stable and radiocarbon isotopes (δ13C and Δ14C) to characterize CA sources at a semiurban site (Hisar: 29.2°N, 75.2°E) in the NW Indo-Gangetic Plain (IGP) and a remote high-altitude location in the Himalayan foothills (Manora Peak: 29.4°N, 79.5°E, 1950 m above sea level) in northern India during winter. The Δ14C of total aerosol organic carbon (TOC) varied from −178‰ to −63‰ at Hisar and from −198‰ to −1‰ at Manora Peak. The absence of significant differences in the 14C-based fraction biomass of TOC between Hisar (0.81 ± 0.03) and Manora Peak (0.82 ± 0.07) reveals that biomass burning/biogenic emissions (BBEs) are the dominant sources of CA at both sites. Combining this information with δ13C, other chemical tracers (K+/OC and SO42−/EC) and air mass back trajectory analyses indicate similar source regions in the IGP (e.g., Punjab and Haryana). These results highlight that CA from BBEs in the IGP are not only confined to the atmospheric boundary layer but also extend to higher elevations of the troposphere, where the synoptic-scale circulations could substantially influence their abundances both to the Himalayas and over the downwind oceanic regions such as the Indian Ocean. Given the vast emissions of CA from postharvest crop residue combustion practices in the IGP during early Northeast Monsoon, this information is important for both improved process and model understanding of climate and health effects, as well as in guiding policy decision aiming at reducing emissions.

Evidence for elevated coastal vulnerability following large-scale historical oyster bed harvesting - Brandon, Christine M.; Woodruff, Jonathan D.; Orton, Philip M.; Donnelly, Jeffrey P. (Earth Surface Processes and Landforms, 2016)
Living coastal barriers, such as coral reefs, tidal marshes, mangroves and shellfish beds are widely recognized for their potential role in mitigating flood risk. Limited data exists, however, for assessing the effectiveness of these natural defenses as forms of flood mitigation. In particular, very few mature shellfish beds exist today for modern study due to their destruction in the past few centuries. As an alternative method of study, we present here sedimentary reconstructions of storm overwash from coastal ponds internal to New York Harbor. We use these reconstructions to show that the initial degradation of oyster beds following European settlement of the area coincides with a significant increase in wave-derived overwash deposition at all three of our field sites. Numerical simulations of two flood events of record in the harbor (Hurricane Sandy and a severe winter storm in 1992) were run without and with oyster beds of varying heights (1 m above the seafloor-to-intertidal). Simulations show that the removal of these oyster beds increases wave energy directly off-shore of our field sites by between 30% and 200%. Sedimentary reconstructions and wave modeling experiments therefore both support oyster beds serving as a significant form of coastal protection prior to European disturbance. Copyright © 2016 John Wiley & Sons, Ltd.

Evidence of multiple thermokarst lake generations from an 11 800-year-old permafrost core on the northern Seward Peninsula, Alaska - Lenz, Josefine; Wetterich, Sebastian; Jones, Benjamin M.; Meyer, Hanno; Bobrov, Anatoly; Grosse, Guido (Boreas, 2016)
Permafrost degradation influences the morphology, biogeochemical cycling and hydrology of Arctic landscapes over a range of time scales. To reconstruct temporal patterns of early to late Holocene permafrost and thermokarst dynamics, site-specific palaeo-records are needed. Here we present a multi-proxy study of a 350-cm-long permafrost core from a drained lake basin on the northern Seward Peninsula, Alaska, revealing Lateglacial to Holocene thermokarst lake dynamics in a central location of Beringia. Use of radiocarbon dating, micropalaeontology (ostracods and testaceans), sedimentology (grain-size analyses, magnetic susceptibility, tephra analyses), geochemistry (total nitrogen and carbon, total organic carbon, δ13Corg) and stable water isotopes (δ18O, δD, d excess) of ground ice allowed the reconstruction of several distinct thermokarst lake phases. These include a pre-lacustrine environment at the base of the core characterized by the Devil Mountain Maar tephra (22 800±280 cal. a BP, Unit A), which has vertically subsided in places due to subsequent development of a deep thermokarst lake that initiated around 11 800 cal. a BP (Unit B). At about 9000 cal. a BP this lake transitioned from a stable depositional environment to a very dynamic lake system (Unit C) characterized by fluctuating lake levels, potentially intermediate wetland development, and expansion and erosion of shore deposits. Complete drainage of this lake occurred at 1060 cal. a BP, including post-drainage sediment freezing from the top down to 154 cm and gradual accumulation of terrestrial peat (Unit D), as well as uniform upward talik refreezing. This core-based reconstruction of multiple thermokarst lake generations since 11 800 cal. a BP improves our understanding of the temporal scales of thermokarst lake development from initiation to drainage, demonstrates complex landscape evolution in the ice-rich permafrost regions of Central Beringia during the Lateglacial and Holocene, and enhances our understanding of biogeochemical cycles in thermokarst-affected regions of the Arctic.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bor.12186

Fate of terrigenous organic matter across the Laptev Sea from the mouth of the Lena River to the deep sea of the Arctic interior - Broder, Lisa; Tesi, Tommaso; Salvad?, Joan A.; Semiletov, Igor P.; Dudarev, Oleg V.; Gustafsson, ?rjan (Biogeosciences, 2016)
Ongoing global warming in high latitudes may cause an increasing supply of permafrost-derived organic carbon through both river discharge and coastal erosion to the Arctic shelves. Mobilized permafrost carbon can be either buried in sediments, transported to the deep sea or degraded to CO2 and outgassed, potentially constituting a positive feedback to climate change. This study aims to assess the fate of terrigenous organic carbon (TerrOC) in the Arctic marine environment by exploring how it changes in concentration, composition and degradation status across the wide Laptev Sea shelf. We analyzed a suite of terrestrial biomarkers as well as source-diagnostic bulk carbon isotopes (δ13C, Δ14C) in surface sediments from a Laptev Sea transect spanning more than 800 km from the Lena River mouth (< 10 m water depth) across the shelf to the slope and rise (2000–3000 m water depth). These data provide a broad view on different TerrOC pools and their behavior during cross-shelf transport. The concentrations of lignin phenols, cutin acids and high-molecular-weight (HMW) wax lipids (tracers of vascular plants) decrease by 89–99 % along the transect. Molecular-based degradation proxies for TerrOC (e.g., the carbon preference index of HMW lipids, the HMW acids ∕ alkanes ratio and the acid ∕ aldehyde ratio of lignin phenols) display a trend to more degraded TerrOC with increasing distance from the coast. We infer that the degree of degradation of permafrost-derived TerrOC is a function of the time spent under oxic conditions during protracted cross-shelf transport. Future work should therefore seek to constrain cross-shelf transport times in order to compute a TerrOC degradation rate and thereby help to quantify potential carbon–climate feedbacks.

Footprint of roman and modern mining activities in a sediment core from the southwestern Iberian Atlantic shelf - Mário Mil-Homens; Carlos Vale; Filipa Naughton; Pedro Brito; Teresa Drago; Bárbara Anes; Joana Raimundo; Sabine Schmidt; Miguel Caetano (Science of The Total Environment, 2016)
Abstract A 5-m long sediment core (VC2B), retrieved in the Southwestern Iberian Atlantic shelf, at 96 m water depth, was used to assess major changes in climate and human activities during the last 9.7 kyrs. Analytical measurements included sedimentological (mean grain size, and the contents of sand, silt and clay), geochemical (major, minor, trace and rare earth elements; REEs) and chronological (210Pb and 14C) parameters. Two episodes of increment of fine-grained particles, occurring at 3050 \{BCE\} and 1350 CE, suggest the retreat of the coast line to the present level and the beginning of a wetter phase associated with the “Little Ice Age”. The North American Shale Composite (NASC)-normalized REE-pattern detected in the shelf is similar to that found in the Guadiana estuarine sediments. The possibility of this estuary as a contributor to the sediment load deposited in the adjacent coastal zone was indicated. Trace elements were significantly correlated with Al until 1850 CE, pointing that grain-size rules its distribution in sediments. The depth variation of As, Cu and Pb enrichment factors relative to background values shows two periods of intense human activity that can be mainly linked to mining: (i) across the Roman Period, marked by low enrichments; and (ii) starting on the second half of the 19th century until nowadays with significantly increased enrichments, especially of Pb and Cu. In addition to As, Cu and Pb, this period is also marked by high enrichments of Hg and Zn. Despite the decrease/closure of sulphide massive deposits mining exploitation (e.g., São Domingos, Las Herrerias) during the second half of the 20th century, results showed ongoing input of Pb, Cu, As, Hg and Zn to coastal sediments. Thus, the legacy of contamination by these elements, mainly from leaching of slags and tailings, and remobilization/reworking of contaminated estuarine sediments, is still recorded in marine sediments.
Keywords: mining activities; Rare earth elements

Historical records of organic matter supply and degradation status in the East Siberian Sea - Broder, Lisa; Tesi, Tommaso; Andersson, August; Eglinton, Timothy I.; Semiletov, Igor P.; Dudarev, Oleg V.; Roos, Per; Gustafsson, ?rjan (Organic Geochemistry, 2016)
Destabilization and degradation of permafrost carbon in the Arctic regions could constitute a positive feedback to climate change. A better understanding of its fate upon discharge to the Arctic shelf is therefore needed. In this study, bulk carbon isotopes as well as terrigenous and marine biomarkers were used to construct two centennial records in the East Siberian Sea. Differences in topsoil and Pleistocene Ice Complex Deposit permafrost concentrations, modeled using δ13C and Δ14C, were larger between inner and outer shelf than the changes over time. Similarly, lignin-derived phenol and cutin acid concentrations differed by a factor of ten between the two stations, but did not change significantly over time, consistent with the dual-carbon isotope model. High molecular weight (HMW) n-alkane and n-alkanoic acid concentrations displayed a smaller difference between the two stations (factor of 3–6). By contrast, the fraction for marine OC drastically decreased during burial with a half-life of 19–27 years. Vegetation and degradation proxies suggested supply of highly degraded gymnosperm wood tissues. Lipid Carbon Preference Index (CPI) values indicated more extensively degraded HMW n-alkanes on the outer shelf with no change over time, whereas n-alkanoic acids appeared to be less degraded toward the core top with no large differences between the stations. Taken together, our results show larger across-shelf changes than down-core trends. Further investigation is required to establish whether the observed spatial differences are due to different sources for the two depositional settings or, alternatively, a consequence of hydrodynamic sorting combined with selective degradation during cross-shelf transport.
Keywords: 210Pb; Arctic; East Siberian Arctic Shelf; HMW wax lipids; Lignin; Monte Carlo; δ13C; Δ14C

Inferring skeletal production from time-averaged assemblages: skeletal loss pulls the timing of production pulses towards the modern period - Tomasovych, Adam; Kidwell, Susan M.; Barber, Rina Foygel (PALEOBIOLOGY, 2016)
Age-frequency distributions of dead skeletal material on the landscape or seabed-information on the time that has elapsed since the death of individuals-provide decadal- to millennial-scale perspectives both on the history of production and on the processes that lead to skeletal disintegration and burial. So far, however, models quantifying the dynamics of skeletal loss have assumed that skeletal production is constant during time-averaged accumulation. Here, to improve inferences in conservation paleobiology and historical ecology, we evaluate the joint effects of temporally variable production and skeletal loss on postmortem age-frequency distributions (AFDs) to determine how to detect fluctuations in production over the recent past from AFDs. We show that, relative to the true timing of past production pulses, the modes of AFDs will be shifted to younger age cohorts, causing the true age of past pulses to be underestimated. This shift in the apparent timing of a past pulse in production will be stronger where loss rates are high and/or the rate of decline in production is slow; also, a single pulse coupled with a declining loss rate can, under some circumstances, generate a bimodal distribution. We apply these models to death assemblages of the bivalve Nuculana taphria from the Southern California continental shelf, finding that: (1) an onshore-offshore gradient in time averaging is dominated by a gradient in the timing of production, reflecting the tracking of shallow-water habitats under a sea-level rise, rather than by a gradient in disintegration and sequestration rates, which remain constant with water depth; and (2) loss-corrected model-based estimates of the timing of past production are in good agreement with likely past changes in local production based on an independent sea-level curve.

IsoCaRB: A novel bioreactor system to characterize the lability and natural carbon isotopic (C-14, C-13) signatures of microbially respired organic matter - Beaupré, Steven R.; Mahmoudi, Nagissa; Pearson, Ann (LIMNOLOGY AND OCEANOGRAPHY-METHODS, 2016)
Organic matter is the dominant pool of reduced carbon in marine and freshwater systems. Mineralization of organic matter is largely attributed to complex and diverse microbial communities that mediate degradation and ultimately yield the terminal respiratory product, carbon dioxide (CO2). The factors that constrain the lability and degradation of organic matter remain unclear, but they involve a complex interplay between structural and chemical properties of the compounds, physical properties of the matrices, and the functional potential of the microorganisms that are present. To investigate these relationships, we developed a novel bioreactor system-called Isotopic Carbon Respirometer-Bioreactor (IsoCaRB)-that permits real-time monitoring of microbial CO2 production rates and collects sequential samples of this CO2 for off-line isotopic analyses (C-13, C-14). Application of this system to organic-rich sediments from Salt Pond, MA reveals that organic matter is oxidized both abiotically and microbially, and that the pattern of microbial respiration by the native sediment community is complex, accessing different carbon substrates over the course of incubation. Isotopic measurements show modern organic matter of progressively older ages (<= ca. 50 yr) is consumed, and this material has variable origins (salt marsh grasses, terrestrial, and marine organic matter). Collectively, the IsoCaRB system provides coupled insights into the sources, ages, and inherent biological and abiotic reactivity of natural organic matter.

Last Glacial Maximum sea surface temperature and sea-ice extent in the Pacific sector of the Southern Ocean - Verena Benz; Oliver Esper; Rainer Gersonde; Frank Lamy; Ralf Tiedemann (Quaternary Science Reviews, 2016)
Abstract Sea surface temperatures and sea-ice extent are most critical variables to evaluate the Southern Ocean paleoceanographic evolution in relation to the development of the global carbon cycle, atmospheric \{CO2\} and ocean-atmosphere circulation. Here we present diatom transfer function-based summer sea surface temperature (SSST) and winter sea-ice (WSI) estimates from the Pacific sector of the Southern Ocean to bridge a gap in information that has to date hampered a well-established reconstruction of the last glacial Southern Ocean at circum-Antarctic scale. We studied the Last Glacial Maximum (LGM) at the \{EPILOG\} time slice (19,000–23,000 calendar years before present) in 17 cores and consolidated our \{LGM\} picture of the Pacific sector taking into account published data from its warmer regions. Our data display a distinct east-west differentiation with a rather stable \{WSI\} edge north of the Pacific-Antarctic Ridge in the Ross Sea sector and a more variable \{WSI\} extent over the Amundsen Abyssal Plain. The zone of maximum cooling (>4 K) during the \{LGM\} is in the present Subantarctic Zone and bounded to its south by the 4 °C isotherm. The isotherm is in the \{SSST\} range prevailing at the modern Antarctic Polar Front, representing a circum-Antarctic feature, and marks the northern edge of the glacial Antarctic Circumpolar Current (ACC). The northward deflection of colder than modern surface waters along the South American continent led to a significant cooling of the glacial Humboldt Current surface waters (4–8 K), which affected the temperature regimes as far north as tropical latitudes. The glacial reduction of \{ACC\} temperatures may also have resulted in significant cooling in the Atlantic and Indian Southern Ocean, thus enhancing thermal differentiation of the Southern Ocean and Antarctic continental cooling. The comparison with numerical temperature and sea-ice simulations yields discrepancies, especially concerning the estimates of the sea-ice fields, but some simulations reproduce well our proxy-based temperature data.
Keywords: Pacific Southern Ocean

Late Quaternary evolution of Lago Castor (Chile, 45.6°S): Timing of the deglaciation in northern Patagonia and evolution of the southern westerlies during the last 17 kyr - Maarten Van Daele; Sébastien Bertrand; Inka Meyer; Jasper Moernaut; Willem Vandoorne; Giuseppe Siani; Niels Tanghe; Zakaria Ghazoui; Mario Pino; Roberto Urrutia; Marc De Batist (Quaternary Science Reviews, 2016)
Abstract Even though Patagonia is ideally located to study climate of the southern mid-latitudes, many questions on the late Quaternary climate evolution remain unresolved. The timing of maximum glacier extent is still uncertain in vast areas, and the postglacial evolution of the Southern Westerly Wind Belt (SWWB) remains highly debated. Here, we study the sedimentary infill of a glacigenic lake (Lago Castor; 45.6°S, 71.8°W) located at the leeside of the Andes in Chilean Patagonia to i) reconstruct the deglacial evolution of the eastern flank of the Patagonian Ice Sheet (PIS), and ii) discuss postglacial changes in wind strength at a critical location where westerly wind records are critically lacking. A dense grid of high-resolution reflection-seismic data was used to reconstruct the large-scale infill history of the lake, and a radiocarbon dated sediment core penetrating all lacustrine seismic units, was retrieved. Results indicate that the deglaciation of the lake basin and its catchment occurred no later than ∼28 cal kyr \{BP\} (i.e. an early LGM), but possibly even already after \{MIS\} 4. Afterwards, the Lago Castor area was covered by a large proglacial lake that drained – possibly through an outburst flood – when the \{PIS\} outlet glaciers retreated to a critical location. Subsequently, very dry conditions caused the lake to desiccate, as evidenced by an unconformity visible on the seismic profiles and in the sediment core. This dry period likely resulted from the increased orographic effect of the PIS-covered Andes, accompanied by weaker westerlies. From ∼20 kyr \{BP\} onwards, the combination of a shrinking \{PIS\} and a southward shift of the \{SWWB\} resulted in increased precipitation, which caused the lake level to rise. After ∼17 cal kyr BP, lake sedimentation was more directly influenced by the southern westerlies, with the formation of sediment drifts resulting from strong bottom current during periods of intense westerly winds. Our results suggest a progressive increase in wind strength at 46°S from 11.2 to 4.5 cal kyr BP, which supports the hypothesis that the \{SWWB\} broadened during the early and middle Holocene.
Keywords: Sediment drift

A major increase in winter snowfall during the middle Holocene on western Greenland caused by reduced sea ice in Baffin Bay and the Labrador Sea - Thomas, Elizabeth K.; Briner, Jason P.; Ryan-Henry, John J.; Huang, Yongsong (Geophysical Research Letters, 2016)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.

A new late Quaternary palaeohydrological record from the humid tropics of northeastern Australia - M.A. Burrows; H. Heijnis; P. Gadd; S.G. Haberle (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract High resolution X-ray fluorescence (XRF) is presented as a robust palaeoclimatic proxy, suitable for use on Late Pleistocene to Holocene sediments located in a volcanic crater on the Atherton Tableland in northeastern Queensland, Australia. The proxy allows identification of wet and dry shifts in a complex sedimentary sequence comprised of peat, gyttja, laminated organic rich muds and fine clastic silt-rich sediments. Significant correlation is found between the \{XRF\} record and other proxies including magnetic susceptibility, humification, grain size, macrocharcoal, δ13C and C/N and pollen. Sixteen wetter periods are identified in the 37 ka sedimentary record for Bromfield Swamp. Three wetter periods commence in late Marine Isotope Stage 3, nine in the early glacial, one in the late de-glacial and four in Holocene. Nineteen drier periods are identified, four in late \{MIS\} 3, seven in the early glacial, one during the LGM, one in the late de-glacial period and six in the Holocene. The \{XRF\} record for Bromfield Swamp is specifically used to identify periods of abrupt climate change. Marked changes in effective precipitation are detected at 32,690, 30,080, 24,660, 21,870, 11,880, 10,020, 9170 and 5120 cal. yr BP. The detection of these abrupt climate events may allow correlation with records from terrestrial sites across the Southern Hemisphere and potentially, the Northern Hemisphere.
Keywords: Late Quaternary

A Note on Reporting of Reservoir C-14 Disequilibria and Age Offsets - Soulet, Guillaume; Skinner, Luke C.; Beaupré, Steven R.; Galy, Valier (RADIOCARBON, 2016)
Reservoir age offsets are widely used to correct marine and speleothem radiocarbon age measurements for various calibration purposes. They also serve as a powerful tracer for carbon cycle dynamics. However, a clear terminology regarding reservoir age offsets is lacking, sometimes leading to miscalculations. This note seeks to provide consistent conventions for reporting reservoir C-14 disequilibria useful to a broad range of environmental sciences. This contribution introduces the (FR)-R-14 and R-14 metrics to express the relative C-14 disequilibrium between two contemporaneous reservoirs and the R metric as the associated reservoir age offset.
Keywords: freshwater effect; hardwater effect; radiocarbon; Reservoir age; Reservoir effect; ventilation age

Organic matter cycling across the sulfate-methane transition zone of the Santa Barbara Basin, California Borderland - Komada, Tomoko; Burdige, David J.; Li, Huan-Lei; Magen, édric; Chanton, Jeffrey P.; Cada, Abraham K. (Geochimica et Cosmochimica Acta, 2016)
Consumption of sulfate (SO42−) in the sulfate-methane transition zone (SMTZ) has often been considered to be due solely to anaerobic oxidation of methane (AOM). However, recent studies show SO42− fluxes into the SMTZ that exceed methane (CH4) fluxes, thereby challenging this conceptual model. Co-occurrence of organoclastic SO42− reduction (oSR) with AOM in the SMTZ has been hypothesized to be the cause for this flux imbalance, but conclusive evidence is lacking. To address this knowledge gap, we investigated organic matter cycling in the SMTZ of the organic-rich sediments of the Santa Barbara Basin, California Borderland, and examined the occurrence of oSR within this zone using bulk solute profiles and Δ14C and δ13C values of selected carbon pools. We also tested the hypothesis that the SMTZ acts as an oxidation front not just for CH4, but also for dissolved organic carbon (DOC) that is produced below the SMTZ and migrates upward. Mass balance calculations for the SMTZ based on reaction stoichiometry and Δ14C and δ13C values of associated carbon fluxes indicate that ∼35–45% of total SO42− reduction in the SMTZ occurs via oSR, with the remainder attributable to AOM. The δ13C value of net DOC production is distinct from that of the fraction of bulk POC undergoing degradation, suggesting that pore-water DOC represents a compositionally unique slice of the metabolizable POC pool. DOC diffusing upward at 450 cm is virtually free of 14C and contain low levels of short-chain organic acids. Radiocarbon mass balance shows that >30% of this pre-aged, and presumably refractory, DOC is removed from the pore waters within or immediately below the SMTZ. Although the SMTZ does not appear to be a major net DOC oxidation front, these results show that DOC dynamics provide unique insights into organic matter processing in these subsurface sediments.

RAPID C-14 ANALYSIS OF DISSOLVED ORGANIC CARBON IN NON-SALINE WATERS - Lang, Susan Q.; McIntyre, Cameron P.; Bernasconi, Stefano M.; Fruh-Green, Gretchen L.; Voss, Britta M.; Eglinton, Timothy I.; Wacker, Lukas (RADIOCARBON, 2016)
The radiocarbon content of dissolved organic carbon (DOC) in rivers, lakes, and other non-saline waters can provide valuable information on carbon cycling dynamics in the environment. DOC is typically prepared for C-14 analysis by accelerator mass spectrometry (AMS) either by ultraviolet (UV) oxidation or by freeze-drying and sealed tube combustion. We present here a new method for the rapid analysis of C-14 of DOC using wet chemical oxidation (WCO) and automated headspace sampling of CO2. The approach is an adaption of recently developed methods using aqueous persulfate oxidant to determine the delta C-13 of DOC in non-saline water samples and the C-14 content of volatile organic acids. One advantage of the current method over UV oxidation is higher throughput: 22 samples and 10 processing standards can be prepared in one day and analyzed in a second day, allowing a full suite of C-14 processing standards and blanks to be run in conjunction with samples. A second advantage is that there is less potential for cross-contamination between samples.
Keywords: carbon-cycling; dissolved organic carbon; method development; wet chemical oxidation

Records of continental slope sediment flow morphodynamic responses to gradient and active faulting from integrated AUV and ROV data, offshore Palos Verdes, southern California Borderland - Katherine L. Maier; Daniel S. Brothers; Charles K. Paull; Mary McGann; David W. Caress; James E. Conrad (Marine Geology, 2016)
Abstract Variations in seabed gradient are widely acknowledged to influence deep-water deposition, but are often difficult to measure in sufficient detail from both modern and ancient examples. On the continental slope offshore Los Angeles, California, autonomous underwater vehicle, remotely operated vehicle, and shipboard methods were used to collect a dense grid of high-resolution multibeam bathymetry, chirp sub-bottom profiles, and targeted sediment core samples that demonstrate the influence of seafloor gradient on sediment accumulation, depositional environment, grain size of deposits, and seafloor morphology. In this setting, restraining and releasing bends along the active right-lateral Palos Verdes Fault create and maintain variations in seafloor gradient. Holocene down-slope flows appear to have been generated by slope failure, primarily on the uppermost slope (  100–200 m water depth). Turbidity currents created a low relief (< 10 m) channel, up-slope migrating sediment waves (λ =   100 m, h ≤ 2 m), and a series of depocenters that have accumulated up to 4 m of Holocene sediment. Sediment waves increase in wavelength and decrease in wave height with decreasing gradient. Integrated analysis of high-resolution datasets provides quantification of morphodynamic sensitivity to seafloor gradients acting throughout deep-water depositional systems. These results help to bridge gaps in scale between existing deep-sea and experimental datasets and may provide constraints for future numerical modeling studies.
Keywords: Fault

Seasonal variability of stable carbon isotopes (δ13CDIC) in the Skagerrak and the Baltic Sea: Distinguishing between mixing and biological productivity - Helena L. Filipsson; Daniel C. McCorkle; Andreas Mackensen; Joan M. Bernhard; Lars S. Andersson; Lars-Johan Naustvoll; Angela M. Caballero-Alfonso; Kjell Nordberg; Didrik S. Danielssen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract We documented the annual cycle of the carbon isotopic composition of dissolved inorganic carbon (δ13CDIC) in the water columns of the Skagerrak and Baltic Sea to obtain an increased understanding of the processes involved controlling the carbon isotopic distribution in shelf seas. The lowest δ13CDIC values (− 4.9‰) were found in the low-oxygen, brackish Baltic bottom water whereas the highest values (+ 1.8‰) were observed in the surface water of the Skagerrak during late summer. Photosynthesis drove the high δ13CDIC values (between 1.0 and 1.8‰) noted in the surface waters of both the Skagerrak and the Baltic. The δ13CDIC values below the halocline in the Baltic reflect mixing of brackish water and the more saline water from the Skagerrak, and foremost organic matter remineralization processes that release significant amounts of low-δ13C CO2. Similarly, in the stagnant fjord basins, little deep water exchange and the degradation of terrestrial and marine organic matter set the δ13C composition. Deep-water renewal in the fjord basins resulted in rapid increases of the δ13CDIC on the order of 1‰, whereas remineralization processes caused a decrease in δ13CDIC of 0.1–0.3‰ per month depending on location. The combined effects of water mixing and remineralization processes (estimated using apparent oxygen utilization (AOU) values) yielded the expression: δ13CDIC = 0.032 ∗ S − 0.01 ∗ \{AOU\} − 0.12 for the Baltic – Skagerrak region at water depths below the halocline.
Keywords: Time-series

Sedimentation, stratigraphy and physical properties of sediment on the Juan de Fuca Ridge - K.M. Costa; J.F. McManus; B. Boulahanis; S.M. Carbotte; G. Winckler; P.J. Huybers; C.H. Langmuir (Marine Geology, 2016)
Abstract Sedimentation near mid-ocean ridges may differ from pelagic sedimentation due to the influence of the ridges' rough topography on sediment deposition and transport. This study explores whether the near-ridge environment responds to glacial-interglacial changes in climate and oceanography. New benthic δ18O, radiocarbon, multi-sensor track, and physical property (sedimentation rates, density, magnetic susceptibility) data for seven cores on the Juan de Fuca Ridge provide multiple records covering the past 700,000 years of oceanographic history of the Northeast Pacific Ocean. Systematic variations in sediment density and coarse fraction correspond to glacial-interglacial cycles identified in benthic δ18O, and these observations may provide a framework for mapping the δ18O chronostratigraphy via sediment density to other locations on the Juan de Fuca Ridge and beyond. Sedimentation rates generally range from 0.5 to 3 cm/kyr, with background pelagic sedimentation rates close to 1 cm/kyr. Variability in sedimentation rates close to the ridge likely reflects remobilization of sediment caused by the high relief of the ridge bathymetry. Sedimentation patterns primarily reflect divergence of sedimentation rates with distance from the ridge axis and glacial-interglacial variation in sedimentation that may reflect carbonate preservation cycles as well as preferential remobilization of fine material.
Keywords: Oxygen isotope stratigraphy

Stability of peatland carbon to rising temperatures - Wilson, R. M.; Hopple, A. M.; Tfaily, M. M.; Sebestyen, S. D.; Schadt, C. W.; Pfeifer-Meister, L.; Medvedeff, C.; McFarlane, K. J.; Kostka, J. E.; Kolton, M.; Kolka, R.K.; Kluber, L. A.; et al. (Nature Communications, 2016)
Peatlands contain one-third of soil carbon (C), mostly buried in deep, saturated anoxic zones (catotelm). The response of catotelm C to climate forcing is uncertain, because prior experiments have focused on surface warming. We show that deep peat heating of a 2 m-thick peat column results in an exponential increase in CH4 emissions. However, this response is due solely to surface processes and not degradation of catotelm peat. Incubations show that only the top 20–30 cm of peat from experimental plots have higher CH4 production rates at elevated temperatures. Radiocarbon analyses demonstrate that CH4 and CO2 are produced primarily from decomposition of surface-derived modern photosynthate, not catotelm C. There are no differences in microbial abundances, dissolved organic matter concentrations or degradative enzyme activities among treatments. These results suggest that although surface peat will respond to increasing temperature, the large reservoir of catotelm C is stable under current anoxic conditions.

Tracing the intrusion of fossil carbon into coastal Louisiana macrofauna using natural 14C and 13C abundances - Wilson, Rachel M.; Cherrier, Jennifer; Sarkodee-Adoo, Judith; Bosman, Samantha; Mickle, Alejandra; Chanton, Jeffrey P. (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
The Deepwater Horizon oil spill released a large volume of 13C and radiocarbon depleted organic matter to the northern Gulf of Mexico. Evidence of petroleum-derived carbon entering the offshore planktonic foodweb, as well as widespread oiling of coastal areas documented in previous studies suggests that hydrocarbons could have entered the near shore foodweb. To test this hypothesis, we measured radiocarbon (Δ14C%) and stable carbon isotopes (δ13C) in an assortment of fish tissue, invertebrate tissue and shell samples collected within a year of the spill at seven sites from Louisiana to Florida USA across the northern Gulf of Mexico. We observed a west–east gradient with the most depleted radiocarbon values found in Terrebonne Bay, Louisana and increasingly enriched radiocarbon values in organisms collected at sites to the east. Depleted radiocarbon values as low as −10% in invertebrate soft tissue from Terrebonne suggest assimilation of fossil carbon (2.8±1.2%), consistent with the hypothesis that organic matter from petrochemical reservoirs released during the Deepwater Horizon spill entered the coastal food web to a limited extent. Further there was a significant correlation between radiocarbon and δ13C values in invertebrate tissue consistent with this hypothesis. Both oyster tissue and hard head catfish tissue collected in impacted areas of coastal Louisiana were significantly depleted in 14C and 13C relative to organisms collected in the unaffected Apalachicola Bay, Florida (p<0.014). Alternative explanations for these results include the influence of chronic hydrocarbon pollution along the western gulf coast or that the organisms ingest carbon derived from 14C depleted organic matter mobilized during the erosion of coastal marshes in southern Louisiana.

Unusually large tsunamis frequent a currently creeping part of the Aleutian megathrust - Witter, Robert C.; Carver, Gary A.; Briggs, Richard W.; Gelfenbaum, Guy; Koehler, Richard D.; La Selle, SeanPaul; Bender, Adrian M.; Engelhart, Simon E.; Hemphill-Haley, Eileen; Hill, Troy D. (Geophysical Research Letters, 2016)
Current models used to assess earthquake and tsunami hazards are inadequate where creep dominates a subduction megathrust. Here we report geological evidence for large tsunamis, occurring on average every 300–340 years, near the source areas of the 1946 and 1957 Aleutian tsunamis. These areas bookend a postulated seismic gap over 200 km long where modern geodetic measurements indicate that the megathrust is currently creeping. At Sedanka Island, evidence for large tsunamis includes six sand sheets that blanket a lowland facing the Pacific Ocean, rise to 15 m above mean sea level, contain marine diatoms, cap terraces, adjoin evidence for scour, and date from the past 1700 years. The youngest sheet and modern drift logs found as far as 800 m inland and >18 m elevation likely record the 1957 tsunami. Previously unrecognized tsunami sources coexist with a presently creeping megathrust along this part of the Aleutian Subduction Zone.

Variations in microbial carbon sources and cycling in the deep continental subsurface - Danielle N. Simkus; Greg F. Slater; Barbara Sherwood Lollar; Kenna Wilkie; Thomas L. Kieft; Cara Magnabosco; Maggie C.Y. Lau; Michael J. Pullin; Sarah B. Hendrickson; K. Eric Wommack; Eric G. Sakowski; Esta van Heerden; et al. (Geochimica et Cosmochimica Acta, 2016)
Abstract Deep continental subsurface fracture water systems, ranging from 1.1 to 3.3 km below land surface (kmbls), were investigated to characterize the indigenous microorganisms and elucidate microbial carbon sources and their cycling. Analysis of phospholipid fatty acid (PLFA) abundances and direct cell counts detected varying biomass that was not correlated with depth. Compound-specific carbon isotope analyses (δ13C and Δ14C) of the phospholipid fatty acids (PLFAs) and carbon substrates combined with genomic analyses did identify, however, distinct carbon sources and cycles between the two depth ranges studied. In the shallower boreholes at circa 1 kmbls, isotopic evidence indicated microbial incorporation of biogenic \{CH4\} by the in situ microbial community. At the shallowest site, 1.05 kmbls in Driefontein mine, this process clearly dominated the isotopic signal. At slightly deeper depths, 1.34 kmbls in Beatrix mine, the isotopic data indicated the incorporation of both biogenic \{CH4\} and dissolved inorganic carbon (DIC) derived from \{CH4\} oxidation. In both of these cases, molecular genetic analysis indicated that methanogenic and methanotrophic organisms together comprised a small component (<5%) of the microbial community. Thus, it appears that a relatively minor component of the prokaryotic community is supporting a much larger overall bacterial community in these samples. In the samples collected from >3 kmbls in Tau Tona mine (TT107, \{TT109\} Bh2), the \{CH4\} had an isotopic signature suggesting a predominantly abiogenic origin with minor inputs from microbial methanogenesis. In these samples, the isotopic enrichments (δ13C and Δ14C) of the \{PLFAs\} relative to \{CH4\} were consistent with little incorporation of \{CH4\} into the biomass. The most 13C-enriched \{PLFAs\} were observed in \{TT107\} where the dominant CO2-fixation pathway was the acetyl-CoA pathway by non-acetogenic bacteria. The differences in the δ13C of the \{PLFAs\} and the \{DIC\} and \{DOC\} for \{TT109\} Bh2 were ∼−24‰ and 0‰, respectively. The dominant CO2-fixation pathways were 3-HP/4-HB cycle > acetyl-CoA pathway > reductive pentose phosphate cycle.

Viable Species of Flamella (Amoebozoa: Variosea) Isolated from Ancient Arctic Permafrost Sediments - Lyubov Shmakova; Natalya Bondarenko; Alexey Smirnov (Protist, 2016)
Six viable strains of amoebae belonging to the genus Flamella (Amoebozoa, Variosea) were isolated from permafrost sediments sampled in the Russian Arctic region. Two of them are from late Pleistocene permafrost in North-East Siberia, and four - from Holocene and late Pleistocene in North-West Siberia. Light- and electron-microscopic study and molecular phylogeny show that these isolates represent two new species belonging to the genus Flamella. Both species are cyst-forming. This is a remarkable case of high resistance of protozoan cysts, allowing them to survive and recover an amoebae population after a very long, geologically significant period of rest; a “snapshot” of evolution in time. This study directly shows for the first time that amoeba cysts can be conserved not only for years and decades but for many thousand years and then recover, contributing to the formation of an active microbial community. We propose to name the new species as Flamella pleistocenica n.sp. and Flamella beringiania n.sp. Phylogenetic analysis shows that the genus Flamella is a robust and potentially species-rich group of Variosea.
Keywords: cryptobiosis.

Ancient population genomics and the study of evolution - Parks, M.; Subramanian, S.; Baroni, C.; Salvatore, M. C.; Zhang, G.; Millar, C. D.; Lambert, D. M. (Philosophical Transactions of the Royal Society B: Biological Sciences, 2015)
Recently, the study of ancient DNA (aDNA) has been greatly enhanced by the development of second-generation DNA sequencing technologies and targeted enrichment strategies. These developments have allowed the recovery of several complete ancient genomes, a result that would have been considered virtually impossible only a decade ago. Prior to these developments, aDNA research was largely focused on the recovery of short DNA sequences and their use in the study of phylogenetic relationships, molecular rates, species identification and population structure. However, it is now possible to sequence a large number of modern and ancient complete genomes from a single species and thereby study the genomic patterns of evolutionary change over time. Such a study would herald the beginnings of ancient population genomics and its use in the study of evolution. Species that are amenable to such large-scale studies warrant increased research effort. We report here progress on a population genomic study of the Adélie penguin (Pygoscelis adeliae). This species is ideally suited to ancient population genomic research because both modern and ancient samples are abundant in the permafrost conditions of Antarctica. This species will enable us to directly address many of the fundamental questions in ecology and evolution.

Assessment of branched GDGTs as temperature proxies in sedimentary records from several small lakes in southwestern Greenland - Colcord, Devon E.; Cadieux, Sarah B.; Brassell, Simon C.; Castañeda, Isla S.; Pratt, Lisa M.; White, Jeffrey R. (Organic Geochemistry, 2015)
This study of five small (<3.0 ha) lakes in southwestern Greenland examines the veracity of branched glycerol dialkyl glycerol tetraethers (br GDGTs) as a temperature proxy in lacustrine systems. The proximity (<5 km) of the lakes suggests that their temperature history, and thus their br GDGT records, should be similar. Distributions of br GDGTs in (i) surface sediments from all five lakes, (ii) 14C-dated sediment cores from two lakes (Upper and Lower EVV Lakes) and (iii) soil samples from the area surrounding the lakes were examined. The temporal records of br GDGT-based temperature for the two cores exhibited both similarities and major discrepancies. The differences between the paleotemperature records for the two lakes suggest that br GDGTs are not solely soil-derived, reflecting air temperature, but also indicate an additional br GDGT contribution from another source. Among the broader suite of lake sediments, there was a strong correlation (R2 0.987) between br GDGT-based surface sediment temperatures and measured summer bottom water temperatures for the four lakes with hypoxic/anoxic bottom waters, including Upper EVV Lake. The correlation suggests production of br GDGTs by anaerobic bacteria within the bottom water and/or sediment–water interface, reflecting environmental temperature for the individual lakes and augmenting the uniform, soil-derived signal. Hence, assessment of br GDGTs in Greenland lake sediments provides evidence for their origin from anaerobic autochthonous bacteria and indicates that interpretation of lacustrine br GDGT-based paleotemperature records requires contextual knowledge of individual lake systems and potential source(s) of sedimentary br GDGTs.

Beach ridges as paleoseismic indicators of abrupt coastal subsidence during subduction zone earthquakes, and implications for Alaska-Aleutian subduction zone paleoseismology, southeast coast of the Kenai Peninsula, Alaska - Kelsey, Harvey M.; Witter, Robert C.; Engelhart, Simon E.; Briggs, Richard; Nelson, Alan; Haeussler, Peter; Corbett, D. Reide (Megathrust Earthquakes and Sea-level Change: a Tribute to George Plafker, 2015)
The Kenai section of the eastern Alaska-Aleutian subduction zone straddles two areas of high slip in the 1964 great Alaska earthquake and is the least studied of the three megathrust segments (Kodiak, Kenai, Prince William Sound) that ruptured in 1964. Investigation of two coastal sites in the eastern part of the Kenai segment, on the southeast coast of the Kenai Peninsula, identified evidence for two subduction zone earthquakes that predate the 1964 earthquake. Both coastal sites provide paleoseismic data through inferred coseismic subsidence of wetlands and associated subsidence-induced erosion of beach ridges. At Verdant Cove, paleo-beach ridges record the paleoseismic history; whereas at Quicksand Cove, buried soils in drowned coastal wetlands are the primary indicators of paleoearthquake occurrence and age. The timing of submergence and death of trees mark the oldest earthquake at Verdant Cove that is consistent with the age of a well documented ∼900-year-ago subduction zone earthquake that ruptured the Prince William Sound segment of the megathrust to the east and the Kodiak segment to the west. Soils buried within the last 400–450 years mark the penultimate earthquake on the southeast coast of the Kenai Peninsula. The penultimate earthquake probably occurred before AD 1840 from its absence in Russian historical accounts. The penultimate subduction zone earthquake on the Kenai segment did not rupture in conjunction with the Prince William Sound to the northeast. Therefore the Kenai segment, which is presently creeping, can rupture independently of the adjacent Prince William Sound segment that is presently locked.

Freshening of the Marmara Sea prior to its post-glacial reconnection to the Mediterranean Sea - Aloisi, G.; Soulet, G.; Henry, P.; Wallmann, K.; Sauvestre, R.; Vallet-Coulomb, C.; Lecuyer, C.; Bard, E. (EARTH AND PLANETARY SCIENCE LETTERS, 2015)
During the last glaciation the Marmara Sea was isolated from the Mediterranean Sea because global sea level was below the depth of the Dardanelles sill. Prior to the postglacial reconnection to the Mediterranean Sea (similar to 14.7 cal kyr BP), the surface waters of the Marmara Sea were brackish (Marmara Lake). Freshening of a previously saline Marmara Sea could have happened via spill-out of brackish to fresh water from the surface water of the Black Sea through the Bosphorus Strait. This hypothesis has not been tested against alternative possibilities (salt flushing by river run-off and precipitation). Here we use the dissolved Cl- and stable isotope composition (delta O-18 and delta D) of Marmara Sea sediment pore water to estimate the salinity and stable isotope composition of Marmara Lake bottom water and to evaluate possible freshening scenarios. We use a transport model to simulate pore water Cl-, delta O-18 and delta D in Marmara Sea sediments in the past 130 kyr, which includes the last interglacial (130-75 cal kyr BP), the last glacial (75-14 cal kyr BP) and the current postglacial period. Our results show that the bottom waters of the Marmara Lake were brackish (similar to 4 parts per thousand salinity) and isotopically depleted (delta O-18 similar to -10.2 parts per thousand and delta D similar to -70 parts per thousand, respectively) compared to modern seawater. Their salinity and stable isotope ratios show that they are a mixture of Mediterranean waters and Danube-like waters implying that the freshening took place via spill-out of freshwater through the Bosphorus. Our modelling approach indicates that the transit of fresh water from glacial Eurasia to the Mediterranean via the Marmara Sea started at least 50 cal kyr BP, was continuous throughout most of the last glaciation and persisted up to the post glacial reconnection to the Mediterranean through the Dardanelles sill (14.7 cal kyr BP). These results are consistent with previously published micropaleontological and geochemical investigations of sediment cores that indicate lacustrine conditions in the Marmara Sea from about 75 to 14.7 cal kyr BP. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Black Sea outflow; Last glacial maximum; Marmara Lake; pore water isotope composition

Geochemical Conditions and the Occurrence of Selected Trace Elements in Groundwater Basins Used for Public Drinking-Water Supply, Desert and Basin and Range Hydrogeologic Provinces, 2006–11: California GAMA Priority Basin Project - Wright, M. T.; Fram, M. S.; Belitz, K. (Scientific Investigations Report, 2015)

Glacial-interglacial changes in central tropical Pacific surface seawater property gradients - Lynch-Stieglitz, Jean; Polissar, Pratigya J.; Jacobel, Allison W.; Hovan, Steven A.; Pockalny, Robert A.; Lyle, Mitchell; Murray, Richard W.; Ravelo, A. Christina; Bova, Samantha C.; Dunlea, Ann G.; Ford, Heather L.; Hertzberg, Jennifer E.; et al. (Paleoceanography, 2015)
Much uncertainty exists about the state of the oceanic and atmospheric circulation in the tropical Pacific over the last glacial cycle. Studies have been hampered by the fact that sediment cores suitable for study were concentrated in the western and eastern parts of the tropical Pacific, with little information from the central tropical Pacific. Here we present information from a suite of sediment cores collected from the Line Islands Ridge in the central tropical Pacific, which show sedimentation rates and stratigraphies suitable for paleoceanographic investigations. Based on the radiocarbon and oxygen isotope measurements on the planktonic foraminifera Globigerinoides ruber, we construct preliminary age models for selected cores and show that the gradient in the oxygen isotope ratio of G. ruber between the equator and 8°N is enhanced during glacial stages relative to interglacial stages. This stronger gradient could reflect enhanced equatorial cooling (perhaps reflecting a stronger Walker circulation) or an enhanced salinity gradient (perhaps reflecting increased rainfall in the central tropical Pacific).

High-frequency surface water changes in the Tagus prodelta off Lisbon, eastern North Atlantic, during the last two millennia - Bartels-Jónsdóttir, Helga B.; Voelker, Antje H. L.; Abrantes, Fatima G.; Salgueiro, Emilia; Rodrigues, Teresa; Knudsen, Karen Luise (Marine Micropaleontology, 2015)
A high-resolution sedimentary sequence recovered from the Tagus prodelta has been studied with the objective to reconstruct multi-decadal to centennial-scale climate variability on the western Iberian Margin and to discuss the observations in a wider oceanographic and climatic context. Between ca. 100 BC and AD 400 the foraminiferal fauna and high abundance of Globorotalia inflata indicate advection of subtropical waters via the Azores Current and the winter-time warm Portugal Coastal Current. Between ca. AD 400 and 1350, encompassing the Medieval Climate Anomaly (MCA), enhanced upwelling is indicated by the planktonic foraminiferal fauna, in particular by the high abundance of upwelling indicator species Globigerina bulloides. Relatively light δ18O values and high sea surface temperature (SST) (reconstructed from foraminiferal assemblages) point to upwelling of subtropical Eastern North Atlantic Central Water. Between ca. AD 1350 and 1750, i.e. most of the Little Ice Age, relatively heavy δ18O values and low reconstructed SST, as well as high abundances of Neogloboquadrina incompta, indicate the advection of cold subpolar waters to the area and a southward deflection of the subpolar front in the North Atlantic, as well as changes in the mode of the North Atlantic Oscillation. In addition, the assemblage composition together with the other proxy data reveals less upwelling and stronger river input than during the MCA. Stronger Azores Current influence on the Iberian Margin and strong anthropogenic effect on the climate after AD 1750 is indicated by the foraminiferal fauna. The foraminiferal assemblage shows a significant change in surface water conditions at ca. AD 1900, including enhanced river runoff, a rapid increase in temperature and increased influence of the Azores Current. The Tagus record displays a high degree of similarity to other North Atlantic records, indicating that the site is influenced by atmospheric–oceanic processes operating throughout the North Atlantic, as well as by local changes.

How Unique was Hurricane Sandy? Sedimentary Reconstructions of Extreme Flooding from New York Harbor - Brandon, Christine M.; Woodruff, Jonathan D.; Donnelly, Jeffrey P.; Sullivan, Richard M. (Scientific Reports, 2015)
The magnitude of flooding in New York City by Hurricane Sandy is commonly believed to be extremely rare, with estimated return periods near or greater than 1000 years. However, the brevity of tide gauge records result in significant uncertainties when estimating the uniqueness of such an event. Here we compare resultant deposition by Hurricane Sandy to earlier storm-induced flood layers in order to extend records of flooding to the city beyond the instrumental dataset. Inversely modeled storm conditions from grain size trends show that a more compact yet more intense hurricane in 1821 CE probably resulted in a similar storm tide and a significantly larger storm surge. Our results indicate the occurrence of additional flood events like Hurricane Sandy in recent centuries, and highlight the inadequacies of the instrumental record in estimating current flood risk by such extreme events.
Keywords: Environmental sciences; Geomorphology; Palaeoclimate; sedimentology

The influence of ice marginal setting on early Holocene retreat rates in central West Greenland - KELLEY, SAMUEL E.; Briner, Jason P.; ZIMMERMAN, SUSAN R. H. (Journal of Quaternary Science, 2015)
Ice sheet reconstructions from diverse ice margin settings, spanning multiple millennia, are needed to assess the reaction of the Greenland Ice Sheet (GrIS) to millennial-scale climatic forcing and to place historical records in a longer-term context. Here we present 18 new cosmogenic 10Be exposure ages and five new radiocarbon ages that constrain the early Holocene retreat of the GrIS in the Disko Bugt region in both a marine and a land-based setting. Results indicate similar rates of early Holocene retreat of ∼40–50 m a−1 from transects in Torsukattak fjord (marine setting) and the Naternaq area (land-based setting). We compile seven previously published chronologies of deglaciation from West Greenland, which yield early Holocene retreat rates ranging from 10 to 65 m a−1, similar to those determined for our two study areas. This work demonstrates that when averaged on millennial timescales, retreat rates were remarkably similar along the western GrIS margin. Furthermore, the retreat rates calculated here demonstrate that terrestrial sectors of ice sheets can retreat at net rates comparable to their marine counterparts.

Late Holocene glacial advance and ice shelf growth in Barilari Bay, Graham Land, west Antarctic Peninsula - Christ, Andrew J.; Talaia-Murray, Manique; Elking, Natalie; Domack, Eugene W.; Leventer, Amy; Lavoie, Caroline; Brachfeld, Stefanie; Yoo, Kyu-Cheul; Gilbert, Robert; Jeong, Sun-Mi; Petrushak, Stephen; Wellner, Julia; et al. (GEOLOGICAL SOCIETY OF AMERICA BULLETIN, 2015)
Three marine sediment cores were collected along the length of the fjord axis of Barilari Bay, Graham Land, west Antarctic Peninsula (65 degrees 55'S, 64 degrees 43'W). Multi-proxy analytical results constrained by high-resolution geochronological methods (Pb-210, radiocarbon, Cs-137) in concert with historical observations capture a record of Holocene paleoenvironmental variability. Our results suggest early and middle Holocene (>7022-2815 cal. {[}calibrated] yr B.P.) retreated glacial positions and seasonally open marine conditions with increased primary productivity. Climatic cooling increased sea ice coverage and decreased primary productivity during the Neoglacial (2815 to cal. 730 cal. yr B.P.). This climatic cooling culminated with glacial advance to maximum Holocene positions and expansion of a fjord-wide ice shelf during the Little Ice Age (LIA) (ca. 730-82 cal. yr B.P.). Seasonally open marine conditions were achieved and remnant ice shelves decayed within the context of recent rapid regional warming (82 cal. yr B.P. to present). Our findings agree with previously observed late Holocene cooling and glacial advance across the Antarctic Peninsula, suggesting that the LIA was a regionally significant event with few disparities in timing and magnitude. Comparison of the LIA Antarctic Peninsula record to the rest of the Southern Hemisphere demonstrates close synchronicity in the southeast Pacific and southern most Atlantic region but less coherence for the southwest Pacific and Indian Oceans. Comparisons with the Northern Hemisphere demonstrate that the LIA Antarctic Peninsula record was contemporaneous with pre-LIA cooling and sea ice expansion in the North Atlantic-Arctic, suggesting a global reach for these events.

Late Holocene precipitation variability recorded in the sediments of Reloncaví Fjord (41°S, 72°W), Chile - Rebolledo, Lorena; Lange, Carina B.; Bertrand, Sébastien; Muñoz, Praxedes; Salamanca, Marco; Lazo, Pablo; Iriarte, José L.; Vargas, Gabriel; Pantoja, Silvio; Dezileau, Laurent (Quaternary Research, 2015)
We present reconstructions of late Holocene changes in the source of organic matter and siliceous export production in the Relocanví Fjord (41°S, 72°W), Northern Chilean Patagonia, based on organic carbon content, δ13Corg, N/C ratio, diatom assemblages and biogenic silica contents from three sediment cores. The age models are based on a combination of 210Pb profiles, AMS 14C dating, and on the first occurrence of the diatom Rhizosolenia setigera f. pungens, as a stratigraphic marker in the fjords. The cores span the last 300 to 700 yr. Diatoms dominate the siliceous assemblages in the three cores (98% on average). Our results suggest that precipitation seasonality in the region of Reloncaví was high in CE 1300–1400 and CE 1700–1850, with a clear decreasing trend since CE 1850. The latter trend is in agreement with instrumental records and tree-ring reconstructions. These fluctuations seem to be associated with the Southern Annular Mode (SAM).
Co0ceTimes Cited:1Cited References Count:93

Millennial-scale fluctuations of the European Ice Sheet at the end of the last glacial, and their potential impact on global climate - Toucanne, Samuel; Soulet, Guillaume; Freslon, Nicolas; Jacinto, Ricardo Silva; Dennielou, Bernard; Zaragosi, Sebastien; Eynaud, Frédérique; Bourillet, Jean-Francois; Bayon, Germain (QUATERNARY SCIENCE REVIEWS, 2015)
Reconstructing Northern Hemisphere ice-sheet oscillations and meltwater routing to the ocean is important to better understand the mechanisms behind abrupt climate changes. To date, research efforts have mainly focused on the North American (Laurentide) ice-sheets (LIS), leaving the potential role of the European Ice Sheet (EIS), and of the Scandinavian ice-sheet (SIS) in particular, largely unexplored. Using neodymium isotopes in detrital sediments deposited off the Channel River, we provide a continuous and well-dated record for the evolution of the EIS southern margin through the end of the last glacial period and during the deglaciation. Our results reveal that the evolution of EIS margins was accompanied with substantial ice recession (especially of the SIS) and simultaneous release of meltwater to the North Atlantic. These events occurred both in the course of the EIS to its LGM position (i.e., during Heinrich Stadial -HS- 3 and HS2; similar to 31-29 ka and similar to 26-23 ka, respectively) and during the deglaciation (i.e., at similar to 22 ka, similar to 20-19 ka and from 18.2 +/- 0.2 to 16.7 +/- 0.2 ka that corresponds to the first part of HS1). The deglaciation was discontinuous in character, and similar in timing to that of the southern LIS margin, with moderate ice-sheet retreat (from 22.5 +/- 0.2 ka in the Baltic lowlands) as soon as the northern summer insolation increase (from similar to 23 ka) and an acceleration of the margin retreat thereafter (from similar to 20 ka). Importantly, our results show that EIS retreat events and release of meltwater to the North Atlantic during the deglaciation coincide with AMOC destabilisation and interhemispheric climate changes. They thus suggest that the EIS, together with the LIS, could have played a critical role in the climatic reorganization that accompanied the last deglaciation. Finally, our data suggest that meltwater discharges to the North Atlantic produced by large-scale recession of continental parts of Northern Hemisphere ice sheets during HS, could have been a possible source for the oceanic perturbations (i.e., AMOC shutdown) responsible for the marine-based ice stream purge cycle, or so-called HE's, that punctuate the last glacial period. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Channel River; Deglaciation; European ice-sheet; Meltwater; Neodymium; Termination

PALEO-STORM INDICATORS WITHIN SASYK LIMAN BAYMOUTH BARRIER, UKRAINE - Buynevich, I.V.; Kadurin, S.V. (Geology Bulletin, 2015)
Sedimentary sequences along continental and insular margins serve as archives of coastal erosion by storms and tsunamis. In areas where overwash is limited or precluded by barrier width and height, such as prograded beach-ridge plains (strandplains), geomorphological (scarps) and lithological (heavy-mineral concentrations) indicators provide the only means of assessing the extent and timing of erosional events. This research presents geological evidence of buried erosional scarps along the Black Sea coast of southwestern Ukraine. A distinct paleo-scarp imaged in shore-normal georadar profile and the associated heavy-mineral horizon (magnetic susceptibility >1,700 SI) indicate a storm event that impacted the shoreline of Sasyk Liman baymouth barrier in historical times. Optical dating offers a more reliable chronology of erosional events, whereas radiocarbon-dated reworked early Holocene shells aid in determining the sources of bioclastic material.
Keywords: georadar; heavy-mineral concentration; magnetic susceptibility

Rapid, high-resolution C-14 chronology of ooids - Beaupré, Steven R.; Roberts, Mark L.; Burton, Joshua R.; Summons, Roger E. (GEOCHIMICA ET COSMOCHIMICA ACTA, 2015)
Ooids are small, spherical to ellipsoidal grains composed of concentric layers of CaCO3 that could potentially serve as biogeochemical records of the environments in which they grew. Such records, however, must be placed in the proper temporal context. Therefore, we developed a novel acidification system and employed an accelerator mass spectrometer (AMS) with a gas accepting ion source to obtain radiocarbon (C-14) chronologies extending radially through ooids within one 8-h workday. The method was applied to ooids from Highborne Cay, Bahamas and Shark Bay, Australia, yielding reproducible C-14 chronologies, as well as constraints on the rates and durations of ooid growth and independent estimates of local C-14 reservoir ages. (C) 2015 Elsevier Ltd. All rights reserved.

Sedimentation Pulse in the NE Gulf of Mexico following the 2010 DWH Blowout - Brooks, Gregg R.; Larson, Rebekka A.; Schwing, Patrick T.; Romero, Isabel; Moore, Christopher; Reichart, Gert-Jan; Jilbert, Tom; Chanton, Jeff P.; Hastings, David W.; Overholt, Will A.; Marks, Kala P.; Kostka, Joel E.; et al. (PLOS ONE, 2015)
The objective of this study was to investigate the impacts of the Deepwater Horizon (DWH) oil discharge at the seafloor as recorded in bottom sediments of the DeSoto Canyon region in the northeastern Gulf of Mexico. Through a close coupling of sedimentological, geochemical, and biological approaches, multiple independent lines of evidence from 11 sites sampled in November/December 2010 revealed that the upper ~1 cm depth interval is distinct from underlying sediments and results indicate that particles originated at the sea surface. Consistent dissimilarities in grain size over the surficial ~1 cm of sediments correspond to excess 234Th depths, which indicates a lack of vertical mixing (bioturbation), suggesting the entire layer was deposited within a 4–5 month period. Further, a time series from four deep-sea sites sampled up to three additional times over the following two years revealed that excess 234Th depths, accumulation rates, and 234Th inventories decreased rapidly, within a few to several months after initial coring. The interpretation of a rapid sedimentation pulse is corroborated by stratification in solid phase Mn, which is linked to diagenesis and redox change, and the dramatic decrease in benthic formanifera density that was recorded in surficial sediments. Results are consistent with a brief depositional pulse that was also reported in previous studies of sediments, and marine snow formation in surface waters closer to the wellhead during the summer and fall of 2010. Although sediment input from the Mississippi River and advective transport may influence sedimentation on the seafloor in the DeSoto Canyon region, we conclude based on multidisciplinary evidence that the sedimentation pulse in late 2010 is the product of marine snow formation and is likely linked to the DWH discharge.

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental Science & Technology, 2015)
In 2010, the Deepwater Horizon accident released 4.6–6.0 × 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 × 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 × 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0–4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4–31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

A warm and poorly ventilated deep Arctic Mediterranean during the last glacial period - Thornalley, D. J. R.; Bauch, H. A.; Gebbie, G.; Guo, W.; Ziegler, M.; Bernasconi, S. M.; Barker, S.; Skinner, L. C.; Yu, J. (Science, 2015)
Changes in the formation of dense water in the Arctic Ocean and Nordic Seas [the “Arctic Mediterranean” (AM)] probably contributed to the altered climate of the last glacial period. We examined past changes in AM circulation by reconstructing radiocarbon ventilation ages of the deep Nordic Seas over the past 30,000 years. Our results show that the glacial deep AM was extremely poorly ventilated (ventilation ages of up to 10,000 years). Subsequent episodic overflow of aged water into the mid-depth North Atlantic occurred during deglaciation. Proxy data also suggest that the deep glacial AM was ~2° to 3°C warmer than modern temperatures; deglacial mixing of the deep AM with the upper ocean thus potentially contributed to the melting of sea ice, icebergs, and terminal ice-sheet margins.

Adélie penguin dietary remains reveal Holocene environmental changes in the western Ross Sea (Antarctica) - Lorenzini, Sandra; Baroni, Carlo; Baneschi, Ilaria; Salvatore, Maria Cristina; Fallick, Anthony E.; Hall, Brenda L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Carbon and nitrogen stable isotope analyses were performed on modern and Holocene Adélie penguin guano samples collected from ornithogenic soils along the Scott Coast (Southern Victoria Land, Antarctica), from Cape Irizar to Dunlop Island, and at Cape Bird (Ross Island). Guano samples also were sieved and sorted under stereomicroscope in order to select penguin dietary remains, such as fish bones and otoliths. Carbon and nitrogen stable isotope composition, coupled with the taxonomic identification of fish otoliths from Scott Coast Holocene samples, indicated a mainly fish-based diet for this area, with Pleuragramma antarcticum as the most eaten prey throughout the investigated period (from 390 cal BP to ca 7300 cal BP). The isotopic values of Ross Island samples (from modern to 3850 cal BP) showed a krill consumption increase in the samples younger than 2000 cal BP, with the maximum in modern samples. Scott Coast and Ross Island Holocene samples showed δ13C and δ15N trends similar to those previously published from Terra Nova Bay (northern Victoria Land), whereas modern samples from Ross Island have similar δ15N composition but different δ13C values. This δ13C divergence started at ca 2000 BP and follows the abandonment of the Scott Coast colonies. The δ13C trend observed in Ross Island and Terra Nova Bay samples and the abandonment of the Scott Coast colonies could suggest the stability and the persistence of the previous oceanographic conditions (i.e. polynya) for the Terra Nova Bay area and the establishment of new conditions for water circulation in the Southern Ross Sea since ~ 2000 BP when persistent sea-ice sealed the Scott Coast.
id: 2347

Amino acid ratios in reworked marine bivalve shells constrain Greenland Ice Sheet history during the Holocene - Briner, J. P.; Kaufman, D. S.; Bennike, O.; Kosnik, M. A. (Geology, 2014)
Reconstructions of ice sheet fluctuations during the Holocene, which encompassed cooler and warmer conditions than those that are captured in the historic record, help to elucidate ice margin sensitivity to climate change. We used amino acid geochronology to constrain the history of the western Greenland Ice Sheet margin during intervals of relative warmth in the middle Holocene. We measured the extent of amino acid racemization in 251 ice sheet-reworked marine bivalve shells from three locations spanning western Greenland. A significant relationship between shell age and the ratio of aspartic acid (Asp) isomers (Asp D/L) was revealed using Bayesian model fitting on 20 radiocarbon-dated shell fragments. The range of Asp-inferred bivalve ages at each site corresponds well with independent records of early Holocene ice retreat and late Holocene ice advance. Furthermore, the frequency of Asp-inferred bivalve ages from the three widely separated locations is nearly identical, with most ages between 5 and 3 ka, coinciding with optimum oceanic conditions. Because ice margin changes in western Greenland are tightly linked with oceanographic conditions, the distribution of reworked bivalve ages provides important information about relative ice margin position during smaller-than-present ice sheet configurations. This approach adds a new chronometer to our toolkit for constraining smaller-than-present ice sheet configurations and may have wide applicability around Greenland. Amino acid ratios in reworked marine bivalve shells constrain Greenland Ice Sheet history during the Holocene. Available from: https://www.researchgate.net/publication/270688646_Amino_acid_ratios_in_reworked_marine_bivalve_shells_constrain_Greenland_Ice_Sheet_history_during_the_Holocene [accessed Jun 5, 2017].

Diverse rupture modes for surface-deforming upper-plate earthquakes in the southern Puget Lowland of Washington State - Nelson, Alan R.; Personius, Stephen F.; Sherrod, Brian L.; Kelsey, Harvey M.; Johnson, Samuel Y.; Bradley, Lee-Ann; Wells, Ray E. (Geosphere, 2014)
Earthquake prehistory of the southern Puget Lowland, in the north-south compressive regime of the migrating Cascadia forearc, reflects diverse earthquake rupture modes with variable recurrence. Stratigraphy and Bayesian analyses of previously reported and new 14C ages in trenches and cores along backthrust scarps in the Seattle fault zone restrict a large earthquake to 1040–910 cal yr B.P. (2σ), an interval that includes the time of the M 7–7.5 Restoration Point earthquake. A newly identified surface-rupturing earthquake along the Waterman Point backthrust dates to 940–380 cal yr B.P., bringing the number of earthquakes in the Seattle fault zone in the past 3500 yr to 4 or 5. Whether scarps record earthquakes of moderate (M 5.5–6.0) or large (M 6.5–7.0) magnitude, backthrusts of the Seattle fault zone may slip during moderate to large earthquakes every few hundred years for periods of 1000–2000 yr, and then not slip for periods of at least several thousands of years. Four new fault scarp trenches in the Tacoma fault zone show evidence of late Holocene folding and faulting about the time of a large earthquake or earthquakes inferred from widespread coseismic subsidence ca. 1000 cal yr B.P.; 12 ages from 8 sites in the Tacoma fault zone limit the earthquakes to 1050–980 cal yr B.P. Evidence is too sparse to determine whether a large earthquake was closely predated or postdated by other earthquakes in the Tacoma basin, but the scarp of the Tacoma fault was formed by multiple earthquakes. In the northeast-striking Saddle Mountain deformation zone, along the western limit of the Seattle and Tacoma fault zones, analysis of previous ages limits earthquakes to 1200–310 cal yr B.P. The prehistory clarifies earthquake clustering in the central Puget Lowland, but cannot resolve potential structural links among the three Holocene fault zones.

Holocene earthquakes and right-lateral slip on the left-lateral Darrington-Devils Mountain fault zone, northern Puget Sound, Washington - Personius, S. F.; Briggs, R. W.; Nelson, A. R.; Schermer, E. R.; Maharrey, J. Z.; Sherrod, B. L.; Spaulding, S. A.; Bradley, L.-A. (Geosphere, 2014)
Sources of seismic hazard in the Puget Sound region of northwestern Washington include deep earthquakes associated with the Cascadia subduction zone, and shallow earthquakes associated with some of the numerous crustal (upper-plate) faults that crisscross the region. Our paleoseismic investigations on one of the more prominent crustal faults, the Darrington–Devils Mountain fault zone, included trenching of fault scarps developed on latest Pleistocene glacial sediments and analysis of cores from an adjacent wetland near Lake Creek, 14 km southeast of Mount Vernon, Washington. Trench excavations revealed evidence of a single earthquake, radiocarbon dated to ca. 2 ka, but extensive burrowing and root mixing of sediments within 50–100 cm of the ground surface may have destroyed evidence of other earthquakes. Cores in a small wetland adjacent to our trench site provided stratigraphic evidence (formation of a laterally extensive, prograding wedge of hillslope colluvium) of an earthquake ca. 2 ka, which we interpret to be the same earthquake documented in the trenches. A similar colluvial wedge lower in the wetland section provides possible evidence for a second earthquake dated to ca. 8 ka. Three-dimensional trenching techniques revealed evidence for 2.2 ± 1.1 m of right-lateral offset of a glacial outwash channel margin, and 45–70 cm of north-side-up vertical separation across the fault zone. These offsets indicate a net slip vector of 2.3 ± 1.1 m, plunging 14° west on a 286°-striking, 90°-dipping fault plane. The dominant right-lateral sense of slip is supported by the presence of numerous Riedel R shears preserved in two of our trenches, and probable right-lateral offset of a distinctive bedrock fault zone in a third trench. Holocene north-side-up, right-lateral oblique slip is opposite the south-side-up, left-lateral oblique sense of slip inferred from geologic mapping of Eocene and older rocks along the fault zone. The cause of this slip reversal is unknown but may be related to clockwise rotation of the Darrington–Devils Mountain fault zone into a position more favorable to right-lateral slip in the modern N-S compressional stress field.

Inferring local to regional changes in forest composition from Holocene macrofossils and pollen of a small lake in central Upper Michigan - Jackson, Stephen T.; Booth, Robert K.; Reeves, Kelly; Andersen, Jennifer Jewell; Minckley, Thomas A.; Jones, Rachel A. (Quaternary Science Reviews, 2014)
Vegetational response to climatic change involves processes of population and community dynamics within local stands, which scale up to landscape-level changes in vegetation composition and broad-scale changes in species distributions. Understanding these dynamics poses a critical challenge to paleoecological explanation, because of the broad range of scales at which these dynamics take place and interact. We present an 8600-year paleoecological record of local and regional changes in forest composition from a small (2.6 ha) lake in central Upper Michigan. Plant macrofossils provide a spatially precise record of local forest composition, while pollen data provide a spatially integrated record of regional vegetational changes. Temporal patterns among different macrofossil types within species show overall coherence, indicating that changes in macrofossil abundance generally record changes in local tree abundance. Temporal patterns in macrofossil sequences correspond to patterns in pollen sequences, indicating that local changes contributed to the large-scale changes in the surrounding region. The pollen and macrofossil records show nearly continuous turnover in vegetation composition throughout the past 8600 years; the longest period without major compositional change was ca 1600 years, and dynamics at multidecadal to multicentennial scales are observed during many periods. Coordinated application of temporally precise sequences of pollen and macrofossil data at multiple sites can support inferences concerning vegetation dynamics at multiple spatial and temporal scales, and test mechanistic hypotheses.

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.
Keywords: florida; Foraminifera; Glacio-isostatic adjustment Greenland fingerprint; Salt marsh

Late Holocene sedimentation in a high Arctic coastal setting: Simpson Lagoon and Colville Delta, Alaska - Hanna, Andrea J. M.; Allison, Mead A.; Bianchi, Thomas S.; Marcantonio, Franco; Goff, John A. (Continental Shelf Research, 2014)
Arctic coastal environments near major river outfalls, like Simpson Lagoon, Alaska and the adjacent Colville River Delta, potentially contain high-resolution sediment records useful in elucidating late Holocene Arctic sediment transport pathways and coupled terrestrial-ocean evidence of paleoclimate variability. This study utilizes a multi-tracer geochronology approach (137Cs, 239,240Pu, and 14C) tailored for high-latitude environments to determine the age models for cores collected from Simpson Lagoon, and to date seismic boundaries in shallow acoustic reflection data (CHIRP) to examine late Holocene infill patterns. Modern (~100 y) sediment accumulation rates range from 5 m of late Holocene interbedded sediments, likely derived primarily from the Colville River, with onset of accumulation occurring prior to ~3500 y BP. A paleo-high in central Simpson Lagoon, separating the two depocenters, was subaerially exposed prior to ~600 y BP. The millimeters-per-year sedimentation rates across the lagoon, coupled with the undisturbed, interbedded sediment record, indicate that these settings hold great potential to develop new Arctic paleoenvironmental records.

The late Quaternary environmental evolution of marine Arctic Canada: Barrow Strait to Lancaster Sound - Pieńkowski, Anna J.; England, John H.; Furze, Mark F. A.; MacLean, Brian; Blasco, Steve (Quaternary Science Reviews, 2014)
A marine sediment core from the east-central Canadian Arctic Archipelago (Core 86027-154; 74° 22.01′N 89° 51.26′W; 329 m water depth), studied by a multiproxy approach [lithostratigraphy, biogeochemistry, micropalaeontology (dinoflagellate cysts, other non-pollen palynomorphs, benthic and planktonic foraminifera, ostracods)], and encompassing 14 AMS 14C dates, provides valuable insights into regional deglacial to Holocene palaeoenvironments. Six palaeoenvironmental zones are recognized, based on prominent changes in the litho- and biostratigraphy. The waterlain diamicton of Zone I records immediate deglaciation, being derived from lift-off and calving of previously grounded glacial ice. Though deglacial timing is complicated by the sparsity of dating materials and the Portlandia Effect, age–depth model extrapolation places deglaciation at 11.54 cal ka BP. Zone II (11.5–11.0 cal ka BP) represents a distinct progression from initially ice-proximal to increasingly ice-distal conditions, interrupted by an interval of pervasive sea-ice (11.4–11.2 cal ka BP). Noteworthy biological activity commences in Zone III (11.0–9.7 cal ka BP) with a prominent signal of planktonic foraminifera (Neogloboquadrina pachyderma). This likely signifies penetration of deeper, Atlantic-derived water through the central Canadian Arctic Archipelago upon deglaciation, facilitated by the greater, glacioisostatically-induced water depths (+80 m), and implies separation of Laurentide and Innuitian ice sheets by ∼11.0 cal ka BP. Zone IV (9.7–7.2 cal ka BP) records ameliorated, biologically favourable conditions with reduced seasonal sea-ice accompanied by high microfossil species diversity and the presence of subpolar taxa. Zone V (7.2–6.5 cal ka BP) signals the exclusion of Atlantic-derived water, concomitant with increasing sea-ice, simultaneously representing the termination of the dynamic deglacial to early Holocene environments (zones I–IV). Conditions similar to modern typified by uniform sediment characteristics, present-day microfossil assemblage structures, and sparse benthic foraminifera were established by 5.6 cal ka BP (Zone VI).

Microbial biomarkers support organic carbon transport from methane-rich Amazon wetlands to the shelf and deep sea fan during recent and glacial climate conditions - Wagner, Thomas; Kallweit, Wiebke; Talbot, Helen M.; Mollenhauer, Gesine; Boom, Arnoud; Zabel, Matthias (Organic Geochemistry, 2014)
We have investigated the delivery of terrestrial organic carbon (OC) to the Amazon shelf and deep sea fan based on soil marker bacteriohopanepolyols (BHPs; adenosylhopane and related compounds) and branched glycerol dialkyl glycerol tetraethers (GDGTs), as well as on 14C dating of bulk organic matter. The microbial biomarker records show persistent burial of terrestrial OC, evidenced by almost constant and high BIT values (0.6) and soil marker BHP concentration [80–230 μg/g TOC (total OC)] on the late Holocene shelf and even higher BIT values (0.8–0.9), but lower and more variable soil-marker BHP concentration (40–100 μg/g TOC), on the past glacial deep sea fan. Radiocarbon data show that OC on the shelf is 3–4 kyr older than corresponding bivalve shells, emphasizing the presence of old carbon in this setting. We observe comparable and unexpectedly invariant BHP composition in both marine sediment records, with a remarkably high relative abundance of C-35 amino BHPs including compounds specific for aerobic methane oxidation on the shelf (avg. 50% of all BHPs) and the fan (avg. 40%). Notably, these marine BHP signatures are strikingly similar to those of a methane-producing floodplain area in one of the Amazonian wetland (várzea) regions. The observation indicates that BHPs in the marine sediments may have initially been produced within wetland regions of the Amazon basin and may therefore document persistent export from terrestrial wetland regions, with subsequent re-working in the marine environment, both during recent and past glacial climate conditions.

Phylogeny and phylogeography of functional genes shared among seven terrestrial subsurface metagenomes reveal N-cycling and microbial evolutionary relationships - Lau, Maggie C. Y.; Cameron, Connor; Magnabosco, Cara; Brown, C. Titus; Schilkey, Faye; Grim, Sharon; Hendrickson, Sarah; Pullin, Michael; Lollar, Barbara Sherwood; Van Heerden, Esta; Kieft, Thomas L.; Onstott, Tullis C. (FRONTIERS IN MICROBIOLOGY, 2014)
Comparative studies on community phylogenetics and phylogeography of microorganisms living in extreme environments are rare. Terrestrial subsurface habitats are valuable for studying microbial biogeographical patterns due to their isolation and the restricted dispersal mechanisms. Since the taxonomic identity of a microorganism does not always correspond well with its functional role in a particular community, the use of taxonomic assignments or patterns may give limited inference on how microbial functions are affected by historical, geographical and environmental factors. With seven metagenomic libraries generated from fracture water samples collected from five South African mines, this study was carried out to (1) screen for ubiquitous functions or pathways of biogeochemical cycling of CH4, S, and N; (2) to characterize the biodiversity represented by the common functional genes; (3) to investigate the subsurface biogeography as revealed by this subset of genes; and (4) to explore the possibility of using metagenomic data for evolutionary study. The ubiquitous functional genes are NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN genes. Although these eight common functional genes were taxonomically and phylogenetically diverse and distinct from each other, the dissimilarity between samples did not correlate strongly with geographical or environmental parameters or residence time of the water. Por genes homologous to those of Thermodesulfovibrio yellowstonii detected in all metagenomes were deep lineages of Nitrospirae, suggesting that subsurface habitats have preserved ancestral genetic signatures that inform the study of the origin and evolution of prokaryotes.
Keywords: evolution; functional genes; N-cycle; phylogenetics; phylogeny; phylogeography; terrestrial subsurface

Pre-aged plant waxes in tropical lake sediments and their influence on the chronology of molecular paleoclimate proxy records - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Tim E.; Brenner, Mark; Hodell, David A.; Curtis, Jason H.; Ma, Keith; Breckenridge, Andy (Geochimica et Cosmochimica Acta, 2014)
Sedimentary records of plant-wax hydrogen (δDwax) and carbon (δ13Cwax) stable isotopes are increasingly applied to infer past climate change. Compound-specific radiocarbon analyses, however, indicate that long time lags can occur between the synthesis of plant waxes and their subsequent deposition in marginal marine sediments. The influence of these time lags on interpretations of plant-wax stable isotope records is presently unconstrained, and it is unclear whether such time lags also affect lacustrine sediments. We present compound-specific radiocarbon (14Cwax) data for n-alkanoic acid plant waxes (n-C26 to n-C30) from: 1) a sediment core from Lake Chichancanab, Yucatan Peninsula, Mexico, 2) soils in the Lake Chichancanab catchment, and 3) surface sediments from three other lakes in southeastern Mexico and northern Guatemala. 14Cwax ages in the surface sediments are consistently older than modern, and may be negatively correlated with mean annual precipitation and positively correlated with lake catchment area. 14Cwax ages in soils surrounding Lake Chichancanab increase with soil depth, consistent with deep, subsoil horizons being the primary source of lacustrine aged plant waxes, which are likely delivered to lake sediments through subsurface transport. Plant waxes in the Lake Chichancanab core are 350 to 1200 years older than corresponding ages of bulk sediment deposition, determined by 14C dates on terrestrial plant macrofossils in the core. A δDwax time series is in closer agreement with other regional proxy hydroclimate records when a plant-wax 14C age model is applied, as opposed to the macrofossil-based core chronology. Inverse modeling of plant-wax age distribution parameters suggests that plant waxes in the Lake Chichancanab sediment core derive predominantly from millennial-age soil carbon pools that exhibit relatively little age variance (< 200 years). Our findings demonstrate that high-temporal-resolution climate records inferred from stable isotope measures on plant waxes in lacustrine sediments may suffer from possible chronologic distortions as a consequence of long residence times of plant waxes in soils. They also underscore the importance of direct radiocarbon dating of these organic molecules.

Radiocarbon Data of Funerary Discoveries from Middle Bronze Age Settlement at Miceşti - Cigaş (Alba County, Romania) - Bălan, Gabriel; Quinn, Colin (Annales Universitatis Apulensis Series Historica, 2014)
In the autumn of 2013 fragments of human bone were selected to date the burials in C.7/2009 and C.11/2012 at Miceşti-Cigaș (fig. 1). The dating of bone collagen provides an accurate means of dating the death of the individual. Radiocarbon dates from bone collagen also are unaffected by the ‘old wood’ phenomenon that can affect conventional charcoal dates. They were calibrated with the Oxcal program, version 4.2.3, resulting a timeframe between 1745-1627 BC (95.4%) / 1736-1645 BC (68.1%) for C.11 and 1880-1693 BC (95.4%) / 1872-1700 BC (68.1%) for C.7 (fig. 1-2). Until now there were only 6 radiocarbon dates obtained on samples taken from Wietenberg sites: Oarța de Sus (two dates: 1. Ly 9190 - “1610-1445 B.C., with maximum probability between 1589-1518-1469 B.C.”; 2. Bln 5626: 3507±37, 1931-1701 BC 2 sigma calibrated); Sighișoara-Cartierul viilor (1685 – 1524 BC) and Rotbav-La pârâuț (three dates: Hd-28203 - 3547±24 BP, 1954- 1774 BC calibrated 2 sigma; Hd-27967 - 3195±19 BP, 1501-1430 BC calibrated 2 sigma; Hd-27989 - 3174±16 BP, 1497-1416 BC calibrated 2 sigma).A partial chronological synchronization between the Wietenberg IV phase and Noua culture has been observed by several scholars. To test this, we draw attention to important radiocarbon dates from sites belonging to Noua culture: Mahala, Crasnaleuca, Miciurin-Odaia and Rotbav-La pârâuț. These radiocarbon dates minimally and definitively place the Noua culture between 1500-1200 BC. There are also some other dates which could suggest the beginning of Noua culture in the 16th century BC (fig. 3).On the basis of the radiocarbon dates belonging to Wietenberg and Noua cultures mentioned above, we consider that the Wietenberg IV phase is part of the Middle Bronze Age, while the beginning of the Late Bronze Age is marked through the presence of Noua culture in Transylvania. If we are to take into account the dates from Miceşti, the first manifestations of the last Wietenberg phase can be placed by the beginning of the 17th century BC. The final part of Wietenberg culture is marked by the emergence of Noua culture before 1500 BC, when, for a short period of time, the two pottery styles coexist.
Keywords: Middle Bronze Age; Wietenberg culture; funerary discoveries; 14C data; chronology

Refining the link between the Holocene development of the Mississippi River Delta and the geologic evolution of Cat Island, MS: implications for delta-associated barrier islands - Miselis, Jennifer L.; Buster, Noreen A.; Kindinger, Jack L. (Marine Geology, 2014)
The geologic evolution of barrier islands is profoundly influenced by the nature of the deposits underlying them. Many researchers have speculated on the origin and evolution of Cat Island in Mississippi, but uncertainty remains about whether or not the island is underlain completely or in part by deposits associated with the past growth of the Mississippi River delta. In part, this is due to a lack of comprehensive geological information offshore of the island that could augment previous stratigraphic interpretations based on terrestrial borings. An extensive survey of Cat Island and its surrounding waters was conducted, including shallow-water geophysics (e.g., high-resolution chirp seismic, side-scan sonar, and swath and single-beam bathymetry) and both terrestrial and marine vibracoring. High-resolution seismic data and vibracores from south and east of the island show two horizontally laminated silt units; marine radiocarbon dates indicate that they are St. Bernard delta complex (SBDC) deposits. Furthermore, seismic data reveal that the SBDC deposits taper off toward the southern shoreline of Cat Island and to the west, morphology consistent with the distal edge of a delta complex. The sedimentology and extent of each unit suggest that the lower unit may have been deposited during an earlier period of continuous river flow while the upper unit may represent reduced or sporadic river flow. OSL dates from the island platform (beneath beach ridge complexes) indicate three stages of terrestrial evolution: island emergence resulting from relative sea-level rise (~ 5400 ybp) island aggradation via littoral transport (~ 2500–4000 ybp) and island degradation due to delta-mediated changes in wave direction (present– ~ 3600 ybp). Finally, the combination of terrestrial and marine data shows that portions of Cat Island that are lower in elevation than the central part of the island are younger and are likely underlain by a thin layer of deltaic sediments. This underscores the potential for increased future vulnerability of barrier islands that develop adjacent to major river delta complexes.

Seafloor fault ruptures along the North Anatolia Fault in the Marmara Sea, Turkey: Link with the adjacent basin turbidite record - McHugh, Cecilia M. G.; Braudy, Nicole; Çağatay, M. Namik; Sorlien, Christopher; Cormier, Marie-Helene; Seeber, Leonardo; Henry, Pierre (Marine Geology, 2014)
The relation between seafloor fault ruptures and the generation of turbidity currents was investigated to better understand the structural growth of tectonic basins with direct implications for earthquake hazard assessment. This study focuses on the Holocene earthquake record of transtensional basins in the Marmara Sea, Turkey, that are associated with the North Anatolian Fault system. The physical and chemical composition of three 10 m-long cores recovered from the Central Basin was studied at high-resolution and turbidite–homogenite units were identified. Turbidite–homogenite units (T–H units) are complex deposits that consist of a sharp basal contact and multiple fining upward beds of sand to coarse silt, above. All are capped by a 25 cm to 75 cm thick layer of medium to fine silt. A chronology developed from radiocarbon and short-lived radioisotopes allowed the correlation of these T–H units to the historical record of earthquakes that in Turkey goes back 2000 years. We found that the best location to recover the most complete sedimentation record is in the deepest part of a basin or “depocenter” where T–H units constitute ~ 80% of the sediments. A very good correlation was established between T–H units in Central Basin and proximal inferred historic epicentres along the central Marmara segment of the North Anatolia Fault that occurred in 1343, 860, 740, and 557 AD, and two more distal earthquakes that occurred in 268 and 1963 (or possibly1964). These sedimentation events can then be referred to as “seismo-turbidites”. The results when compared to findings from other transform basins in Marmara Sea reveal a very good correlation between T–H units and historic ruptures. Most importantly, there is a strong correlation between the inferred locations of historical earthquakes and the preservation of turbidite–homogenite units in the basin adjacent to the inferred rupture. The 740 AD earthquake correlates with T–H units in Izmit Gulf and Central Basin and could represent a multi-segment rupture of the NAF. Generally, T–H units appear to be clustered through the Holocene sections, suggesting temporal earthquake clustering in the Marmara Sea region. Such clustering may account for the lack of T–H units and hence large ruptures through the Central Basin since 1343.

Sedimentation patterns on a cold-water coral mound off Mauritania - Eisele, Markus; Frank, Norbert; Wienberg, Claudia; Titschack, Jürgen; Mienis, Furu; Beuck, Lydia; Tisnerat-Laborde, Nadine; Hebbeln, Dierk (Biology and Geology of Deep-Sea Coral Ecosystems: Proceedings of the Fifth International Symposium on Deep Sea Corals, 2014)
An unconformity-bound glacial sequence (135 cm thick) of a coral-bearing sediment core collected from the flank of a cold-water coral mound in the Banda Mound Province off Mauritania was analysed. In order to study the relation between coral framework growth and its filling by hemipelagic sediments, U-series dates obtained from the cold-water coral species Lophelia pertusa were compared to 14C dates of planktonic foraminifera of the surrounding matrix sediments. The coral ages, ranging from 45.1 to 32.3 ka BP, exhibit no clear depositional trend, while on the other hand the 14C dates of the matrix sediment provide ages within a much narrower time window of <3000 yrs (34.6–31.8 cal ka BP), corresponding to the latest phase of the coral growth period. In addition, high-resolution computer tomography data revealed a subdivision of the investigated sediment package into three distinct parts, defined by the portion and fragmentation of corals and associated macrofauna as well as in the density of the matrix sediments. Grain size spectra obtained on the matrix sediments show a homogeneous pattern throughout the core sediment package, with minor variations. These features are interpreted as indicators of redeposition. Based on the observed structures and the dating results, the sediments were interpreted as deposits of a mass wasting event, namely a debris flow. During this event, the sediment unit must have been entirely mixed; resulting in averaging of the foraminifera ages from the whole unit and giving randomly distributed coral ages. In this context, for the first time mass wasting is proposed to be a substantial process of mound progradation by exporting material from the mound top to the flanks. Hence, it may not only be an erosional feature but also widening the base of the mound, thus allowing further vertical mound growth.

Temporal and spatial distributions of cold-water corals in the Drake Passage: Insights from the last 35,000 years - Margolin, Andrew R.; Robinson, Laura F.; Burke, Andrea; Waller, Rhian G.; Scanlon, Kathryn M.; Roberts, Mark L.; Auro, Maureen E.; van de Flierdt, Tina (Deep Sea Research Part II: Topical Studies in Oceanography, 2014)
Scleractinian corals have a global distribution ranging from shallow tropical seas to the depths of the Southern Ocean. Although this distribution is indicative of the corals having a tolerance to a wide spectrum of environmental conditions, individual species seem to be restricted to a much narrower range of ecosystem variables. One way to ascertain the tolerances of corals, with particular focus on the potential impacts of changing climate, is to reconstruct their growth history across a range of environmental regimes. This study examines the spatial and temporal distribution of the solitary scleractinian corals Desmophyllum dianthus, Gardineria antarctica, Balanophyllia malouinensis, Caryophyllia spp. and Flabellum spp. from five sites in the Drake Passage which cross the major frontal zones. A rapid reconnaissance radiocarbon method, cooupled with U-Th dating, extends the age range back more than 100 thousand. Within this age range there are distinct changes in the temporal and spatial distributions of these corals, both with depth and latitude, and on millennial timescales. Two major patterns that emerge are: 1) D. dianthus populations show clear variability in their occurrence through time depending on the latitudinal position within the Drake Passage. North of the Subantarctic Front, D. dianthus first appears in the late deglaciation (~17,000 years ago) and persists to today. South of the Polar Front, in contrast, populations existed during the glacial and early deglacial periods, with only few modern occurrences. A seamount site between the two fronts exhibits characteristics similar to both the north and south sites. This shift across the frontal zones within one species cannot yet be fully explained, but it is likely to be linked to changes in surface productivity, subsurface oxygen concentrations, and carbonate saturation state. 2) at locations where multiple genera were dated, clear differences in age and depth distribution of the populations provide clear evidence that each genus has unique environmental requirements to sustain its population.
id: 2278

Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska) - Briggs, Richard W.; Engelhart, Simon E.; Nelson, Alan R.; Dura, Tina; Kemp, Andrew C.; Haeussler, Peter J.; Corbett, D. Reide; Angster, Stephen J.; Bradley, Lee-Ann (Geophysical Research Letters, 2014)
We report stratigraphic evidence of land-level change and tsunami inundation along the Alaska-Aleutian megathrust during prehistoric and historical earthquakes west of Kodiak Island. On Sitkinak Island, cores and tidal outcrops fringing a lagoon reveal five sharp lithologic contacts that record coseismic land-level change. Radiocarbon dates, 137Cs profiles, computerized tomography scans, and microfossil assemblages are consistent with rapid uplift circa 290–0, 520–300, and 1050–790 cal yr B.P. and subsidence in A.D. 1964 and circa 640–510 cal yr B.P. Radiocarbon, 137Cs, and 210Pb ages bracketing a sand bed traced 1.5 km inland and evidence for sudden uplift are consistent with Russian accounts of an earthquake and tsunami in A.D. 1788. The mixed uplift and subsidence record suggests that Sitkinak Island sits above a nonpersistent boundary near the southwestern limit of the A.D. 1964 Mw 9.2 megathrust rupture.

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental science & technology, 2014)
In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.; In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

11,000 yrs of environmental change in the Northwest Passage: A multiproxy core record from central Parry Channel, Canadian High Arctic - Pieńkowski, A. J.; England, John H.; Furze, Mark F. A.; Blasco, Steve; Mudie, Peta J.; MacLean, Brian (Marine Geology, 2013)
Piston core 97022-004PC (74° 48.0′N 97°05.9′W; 267 m water depth) represents a rare paleoenvironmental archive from the understudied west-central Canadian Arctic Archipelago. Lithological, biogeochemical, and microfossil (dinoflagellate cysts, non-pollen palynomorphs, benthic and planktonic foraminifera) characteristics, in combination with a chronostratigraphy based on seventeen radiocarbon dates, show seven prominent paleoenvironmental episodes since the end of the last regional glaciation. The basal diamict (Zone I) records decoupling of previously grounded glacial ice, followed by ice-proximal conditions (Zone IIa) commencing at ~ 10.8 cal ka BP (age-depth model extrapolation). After an interval of pervasive sea-ice (Zone IIb), ice-distal conditions are established (Zone IIc). Although sparse microfossils are present in glaciomarine sediments (Zone II), noticeable biological activity with heightened abundances and diversities across all groups begins in the postglacial Zone III (10.3–10.0 cal ka BP) when planktonic foraminifera (Neogloboquadrina pachyderma) appear. As planktonics are excluded from the study area today (due to shallow inter-channel sills), this likely signals the inflow of relatively warm and saline Atlantic-derived Arctic Intermediate Water below 250 m, presumably facilitated by glacio-isostatically enhanced deglacial water depths. The subsequent Zone IV (10.0–7.0 cal ka BP), characterized by heightened biological productivity in both plankton and benthos and reduced seasonal sea-ice cover, may correspond to a previously proposed Holocene Thermal Maximum. This apparent amelioration ends by the mid Holocene (Zone V; 7.0–5.7 cal ka BP) when Arctic Intermediate Water is excluded from the study area and water depths approach modern values. High-Arctic conditions with seasonal sea-ice cover, a circulation dominated by Arctic Ocean Surface Water, and microfossil assemblages similar to modern are found from ~ 5.7 cal ka BP onwards (Zones VI–VII). As only minor environmental fluctuations are apparent during the late Holocene, shorter-term climatic episodes (e.g. Little Ice Age) are not recognized in this record.
id: 2343

14C and 13C characteristics of higher plant biomarkers in Washington margin surface sediments - Feng, Xiaojuan; Benitez-Nelson, Bryan C.; Montluçon, Daniel B.; Prahl, Fredrick G.; McNichol, Ann P.; Xu, Li; Repeta, Daniel J.; Eglinton, Timothy I. (Geochimica et Cosmochimica Acta, 2013)
Plant wax lipids and lignin phenols are the two most common classes of molecular markers that are used to trace vascular plant-derived OM in the marine environment. However, their 13C and 14C compositions have not been directly compared, which can be used to constrain the flux and attenuation of terrestrial carbon in marine environment. In this study, we describe a revised method of isolating individual lignin phenols from complex sedimentary matrices for 14C analysis using high pressure liquid chromatography (HPLC) and compare this approach to a method utilizing preparative capillary gas chromatography (PCGC). We then examine in detail the 13C and 14C compositions of plant wax lipids and lignin phenols in sediments from the inner and mid shelf of the Washington margin that are influenced by discharge of the Columbia River. Plant wax lipids (including n-alkanes, n-alkanoic (fatty) acids, n-alkanols, and n-aldehydes) displayed significant variability in both δ13C (−28.3‰ to −37.5‰) and Δ14C values (−204‰ to +2‰), suggesting varied inputs and/or continental storage and transport histories. In contrast, lignin phenols exhibited similar δ13C values (between −30‰ and −34‰) and a relatively narrow range of Δ14C values (−45‰ to −150‰; HPLC-based measurement) that were similar to, or younger than, bulk OM (−195‰ to −137‰). Moreover, lignin phenol 14C age correlated with the degradation characteristics of this terrestrial biopolymer in that vanillyl phenols were on average ∼500 years older than syringyl and cinnamyl phenols that degrade faster in soils and sediments. The isotopic characteristics, abundance, and distribution of lignin phenols in sediments suggest that they serve as promising tracers of recently biosynthesized terrestrial OM during supply to, and dispersal within the marine environment. Lignin phenol 14C measurements may also provide useful constraints on the vascular plant end member in isotopic mixing models for carbon source apportionment, and for interpretation of sedimentary records of past vegetation dynamics.
id: 2267

Assessing microbial carbon sources and potential PAH degradation using natural abundance 14C analysis - Mahmoudi, Nagissa; Fulthorpe, Roberta R.; Burns, Leanne; Mancini, Silvia; Slater, Greg F. (Environmental Pollution, 2013)
Natural abundance 14C analysis was applied to PLFAs collected from an industrial site in southern Ontario in order to assess microbial carbon sources and potential PAH biodegradation in soils. Δ14C of microbial phospholipid fatty acids (PLFA) at the site ranged from +54‰ to −697‰. Comparison of these values to surrounding carbon sources found that microbial carbon sources were derived primarily from vegetation and/or natural organic matter present in the soils rather than PAHs. This study highlights that microbes are able to utilize almost all available pools of organic matter including older pools which are thought to contain recalcitrant compounds. Furthermore, it shows that even with the presence of an active microbial community, there may be little biodegradation of PAHs. This study illustrates challenges in assessing microbial activity in the environment and the advantage of using natural abundance 14C analysis as a tool to elucidate microbial carbon sources.
id: 2268

C-14 and C-13 characteristics of higher plant biomarkers in Washington margin surface sediments - Feng, Xiaojuan; Benitez-Nelson, Bryan C.; Montluçon, Daniel B.; Prahl, Fredrick G.; McNichol, Ann P.; Xu, Li; Repeta, Daniel J.; Eglinton, Timothy I. (GEOCHIMICA ET COSMOCHIMICA ACTA, 2013)
Plant wax lipids and lignin phenols are the two most common classes of molecular markers that are used to trace vascular plant-derived OM in the marine environment. However, their C-13 and C-14 compositions have not been directly compared, which can be used to constrain the flux and attenuation of terrestrial carbon in marine environment. In this study, we describe a revised method of isolating individual lignin phenols from complex sedimentary matrices for C-14 analysis using high pressure liquid chromatography (HPLC) and compare this approach to a method utilizing preparative capillary gas chromatography (PCGC). We then examine in detail the C-13 and C-14 compositions of plant wax lipids and lignin phenols in sediments from the inner and mid shelf of the Washington margin that are influenced by discharge of the Columbia River. Plant wax lipids (including n-alkanes, n-alkanoic (fatty) acids, n-alkanols, and n-aldehydes) displayed significant variability in both delta C-13 (-28.3 parts per thousand to -37.5 parts per thousand) and Delta C-14 values (-204 parts per thousand to +2 parts per thousand), suggesting varied inputs and/or continental storage and transport histories. In contrast, lignin phenols exhibited similar delta C-13 values (between -30 parts per thousand and -34 parts per thousand) and a relatively narrow range of Delta C-14 values (-45 parts per thousand to -150 parts per thousand; HPLC-based measurement) that were similar to, or younger than, bulk OM (-195 parts per thousand to -137 parts per thousand). Moreover, lignin phenol C-14 age correlated with the degradation characteristics of this terrestrial biopolymer in that vanillyl phenols were on average similar to 500 years older than syringyl and cinnamyl phenols that degrade faster in soils and sediments. The isotopic characteristics, abundance, and distribution of lignin phenols in sediments suggest that they serve as promising tracers of recently biosynthesized terrestrial OM during supply to, and dispersal within the marine environment. Lignin phenol C-14 measurements may also provide useful constraints on the vascular plant end member in isotopic mixing models for carbon source apportionment, and for interpretation of sedimentary records of past vegetation dynamics. (C) 2012 Elsevier Ltd. All rights reserved.

Carbon isotopic characterization of hydrophobic dissolved organic carbon in rainwater - Avery Jr, G. Brooks; Biswas, K. Farhana; Mead, Ralph; Southwell, Melissa; Willey, Joan D.; Kieber, Robert J.; Mullaugh, Katherine M. (Atmospheric Environment, 2013)
The 14C and 13C content of the hydrophobic fraction (C18 extractable) of dissolved organic carbon (DOC) in Wilmington North Carolina USA rainwater was determined for six rain events to elucidate potential sources. A two end member mass-balance calculation indicated that 42–61% of the hydrophobic DOC was of fossil fuel origin compared to previously published values (4–24%) for bulk rain DOC indicating a strong anthropogenic contribution to the hydrophobic component. All fossil fuel derived organic carbon in the bulk DOC (∼15% fossil fuel derived) could be accounted for in the hydrophobic fraction (∼52% fossil fuel derived) which represents approximately 1/3 of the bulk DOC. The δ13C values of the hydrophobic DOC were consistent (−28.8 ± 0.9‰) similar to that for terrestrial and fossil fuel derived organic carbon. This is in contrast to previously published bulk rain DOC δ13C values that displayed a strong influence of air-mass back-trajectory with δ13C values ranging from −20.8‰ (typical of marine organic carbon) for marine air-mass back-trajectory rain to −28.2‰ (typical of terrestrial or fossil fuel derived organic carbon) for terrestrial air-mass back-trajectory rain. The combination of 14C and 13C isotopic data strongly suggests that a large fraction of hydrophobic organic material in rain comes from incompletely combusted fossil fuels. Changes in energy usage patterns and efforts to reduce fossil fuel emissions will alter the abundance of this hydrophobic material in the atmosphere which may impact the spectral distribution of sunlight reaching the earth's surface as well as the degree of oceanic primary productivity.
id: 2288

Carbon isotopic evidence for microbial control of carbon supply to Orca Basin at the seawater-brine interface - Shah, S. R.; Joye, S. B.; Brandes, J. A.; McNichol, A. P. (BIOGEOSCIENCES, 2013)
Orca Basin, an intraslope basin on the Texas-Louisiana continental slope, hosts a hypersaline, anoxic brine in its lowermost 200m in which limited microbial activity has been reported. This brine contains a large reservoir of reduced and aged carbon, and appears to be stable at decadal time scales: concentrations and isotopic composition of dissolved inorganic (DIC) and organic carbon (DOC) are similar to measurements made in the 1970s. Both DIC and DOC are more ``aged{''} within the brine pool than in overlying water, and the isotopic contrast between brine carbon and seawater carbon is much greater for DIC than DOC. While the stable carbon isotopic composition of brine DIC points towards a combination of methane and organic carbon remineralization as its source, radiocarbon and box model results point to the brine interface as the major source region for DIC, allowing for only limited oxidation of methane diffusing upwards from sediments. This conclusion is consistent with previous studies that identify the seawater-brine interface as the focus of microbial activity associated with Orca Basin brine. Isotopic similarities between DIC and DOC suggest a different relationship between these two carbon reservoirs than is typically observed in deep ocean basins. Radiocarbon values implicate the seawater-brine interface region as the likely source region for DOC to the brine as well as DIC.

Carbonate as sputter target material for rapid C-14 AMS - Longworth, Brett E.; Robinson, Laura F.; Roberts, Mark L.; Beaupré, Steven R.; Burke, Andrea; W. J. Jenkins (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2013)
This paper describes a technique for measuring the C-14 content of carbonate samples by producing C- ions directly in the negative ion sputter source of an accelerator mass spectrometer CAMS) system. This direct analysis of carbonate material eliminates the time and expense of graphite preparation. Powdered carbonate is mixed with titanium powder, loaded into a target cartridge, and compressed. Beam currents for optimally-sized carbonate targets (0.09-0.15 mg C) are typically 10-20% of those produced by optimally-sized graphite targets (0.5-1 mg C). Modern (>0.8 Fm) samples run by this method have standard deviations of 0.009 Fm or less, and near-modern samples run as unknowns agree with values from traditional hydrolysis/graphite to better than 2%. Targets with as little as 0.06 mg carbonate produce useable ion currents and results, albeit with increased error and larger blank. In its current state, direct sputtering is best applied to problems where a large number of analyses with lower precision are required. These applications could include age surveys of deep-sea corals for determination of historic population dynamics, to identify samples that would benefit from high precision analysis, and for growth rate studies of organisms forming carbonate skeletons. (C) 2012 Elsevier B.V. All rights reserved.
id: 2244; PT: J; CT: 12th International Conference on Accelerator Mass Spectrometry (AMS); CY: MAR 20-25, 2011; CL: Wellington, NEW ZEALAND; TC: 0; UT: WOS:000313234300064

Changes in sub-fossil chironomid assemblages in two Northern Patagonian lake systems associated to the occurrence of historical fires - Araneda, A.; Ortega, C.; Jana, P.; Torrejon, F.; Bertrand, S.; Vargas, P.; Fagel, N.; Alvarez, D.; Urrutia, R. (Journal of Paleolimnology, 2013)
Patagonia is commonly seen as an exceptionally pristine area because of its wildlife and practically unpolluted waters. However, during the twentieth century the burning of natural forests was one of the most important human activities in Northern Chilean Patagonia. Some estimations indicate that three million hectares were burned during the first three decades of the century. Hence the objective of this study was to evaluate the impacts of the historical fires in Lake Burgos (45º42′S) and Lake Thompson (45º38′S) in Chilean Patagonia. The impact was measured by evaluating chironomid assemblage since they are sensitive enough to be used as an indicator of aquatic ecosystem health. Fires have a direct and drastic effect on a lake watershed but also indirectly affect a lake ecosystem, changing sedimentation patterns or increasing nutrient inputs. In the studied lakes the periods with higher prevalence of fires were identified by charcoal analysis, while organic matter and magnetic susceptibility allowed the confirmation of pre-fire and post-fire periods. The chironomid composition was evaluated through a PCA and an analysis of similarity (ANOSIM) to test the significance among periods while a Detrended Correspondence Analysis was applied to the chironomid assemblage downcore to assess compositional structure and taxa turnover. In Lake Burgos the ANOSIM test indicated significant differences between the pre-fire and fire periods (p
id: 2121

Deciphering hemipelagites from homogenites through anisotropy of magnetic susceptibility. Paleoseismic implications (Sea of Marmara and Gulf of Corinth) - Campos, Corina; Beck, Christian; Crouzet, Christian; Demory, François; Van Welden, Aurélien; Eris, Kadir (Sedimentary Geology, 2013)
In closed marine basins and large lakes, gravity re-depositional processes often result in specific turbidites with two abruptly separated layers: a coarse graded lower term and an upper homogenous fine-grained term. An additional mixed term generally occurs in between, indicating to and from particle displacements. The later ones are related to oscillating bottom currents responsible for a high increase of the fine fraction segregation, within the reworked wasted mass. The whole sedimentary event is the association “homogenite + turbidite” (HmTu), which specific a settling condition area here characterized through Anisotropy of Magnetic Susceptibility (AMS). Homogenites's magnetic foliation appears anomalously high with respect to their expected state of compaction, and strikingly higher than hemipelagites's values. We applied this approach to Late Pleistocene/Holocene sediments from the Sea of Marmara and from the Gulf of Corinth. Grain-size and other magnetic parameters related to mineralogy are added to better assess the granular array influence on AMS. As HmTu is considered as often related to earthquake-triggering and tsunami/seiche effects, AMS appears as a useful tool for subaqueous paleoseismic investigations. First, it may evidence the signature of paleo-earthquakes; second, it permits to decipher hemipelagic intervals which are inferred to represent the time elapsed between two successive reworking events.

The deglaciation and neoglaciation of Upernavik Isstrøm, Greenland - Briner, Jason P.; åkansson, Lena; Bennike, Ole (Quaternary Research, 2013)
We constrain the history of the Greenland Ice Sheet margin during the Holocene at Upernavik Isstrøm, a major ice stream in northwestern Greenland. Radiocarbon-dated sediment sequences from proglacial-threshold lakes adjacent to the present ice margin constrain deglaciation of the sites to older than 9.6 ± 0.1 ka. This age of deglaciation is confirmed with 10Be ages of 9.9 ± 0.1 ka from an island adjacent to the historical ice position. The lake sediment sequences also constrain the ice margin to have been less extensive than it is today for the remainder of the Holocene until ~ 1100 to ~ 700 yr ago, when it advanced into two lake catchments. The ice margin retreated back out of these lake catchments in the last decade. The early Holocene deglaciation in Melville Bugt, one of few locations around Greenland where a vast stretch of the current ice margin is marine-based, preceded deglaciation in most other parts of Greenland. Earlier deglaciation in this ice-sheet sector may have been caused by additional ablation mechanisms that apply to marine-based ice margins. Furthermore, despite ice-sheet models depicting this sector of Greenland as relatively stable throughout the Holocene, our data indicate a > 20 km advance-retreat cycle within the last millennium.

Distribution of Radiocarbon Ages in Soil Organic Matter by Thermal Fractionation - Plante, Alain F.; Beaupré, Steven R.; Roberts, Mark L.; Baisden, Troy (Radiocarbon, 2013)
id: 2346; PT: J; TC: 0; UT: WOS:000325752100093

Export of submicron particulate organic matter to mesopelagic depth in an oligotrophic gyre - Close, H. G.; Shah, S. R.; Ingalls, A. E.; Diefendorf, A. F.; Brodie, E. L.; Hansman, R. L.; Freeman, K. H.; Aluwihare, L. I.; Pearson, A. (Proceedings of the National Academy of Sciences, 2013)
Sixty percent of the world ocean by area is contained in oligotrophic gyres [Longhurst A (1995) Prog Oceanog 36:77-16], the biomass of which is dominated by picophytoplankton, including cyanobacteria and picoeukaryotic algae, as well as picoheterotrophs. Despite their recognized importance in carbon cycling in the surface ocean, the role of small cells and their detrital remains in the transfer of particulate organic matter (POM) to the deep ocean remains disputed. Because oligotrophic marine conditions are projected to expand under current climate trends, a better understanding of the role of small particles in the global carbon cycle is a timely goal. Here we use the lipid profiles, radiocarbon, and stable carbon isotopic signatures of lipids from the North Pacific Subtropical Gyre to show that in the surface ocean, lipids from submicron POM (here called extra-small POM) are distinct from larger classes of suspended POM. Remarkably, this distinct extra-small POM signature dominates the total lipids collected at mesopelagic depth, suggesting that the lipid component of mesopelagic POM primarily contains the exported remains of small particles. Transfer of submicron material to mesopelagic depths in this location is consistent with model results that claim the biological origin of exported carbon should be proportional to the distribution of cell types in the surface community, irrespective of cell size [Richardson TL, Jackson GA (2007) Science 315:838-840]. Our data suggest that the submicron component of exported POM is an important contributor to the global biological pump, especially in oligotrophic waters.
Keywords: Biogeochemistry; biomarkers; carbon isotopes; Oceanography

Extensive recession of Cordillera Darwin glaciers in southernmost South America during Heinrich Stadial 1 - Hall, Brenda L.; Porter, Charles T.; Denton, George H.; Lowell, Thomas V.; Bromley, Gordon R. M. (Quaternary Science Reviews, 2013)
The geographic expression and phasing of events during the last termination are important for isolating mechanisms that caused Earth to emerge from the last ice age. Heinrich Stadial 1 (HS1; 14,600–18,000 yr BP) is a key because of the central role that its far-field effects had on the last termination in the Southern Hemisphere. Here, we present new data from Cordillera Darwin that show rapid glacier recession in southern South America during HS1. This retreat was coeval with ice recession elsewhere in South America and New Zealand, with increased upwelling in the Southern Ocean, with warming of SSTs offshore of Chile, and with a rise in atmospheric CO2. Together, these data indicate a coherent and rapid response to the effects of HS1 in the middle and high latitudes of the Southern Hemisphere.
id: 2331

A gas-accepting ion source for Accelerator Mass Spectrometry: Progress and applications - Roberts, M. L.; von Reden, K. F.; Burton, J. R.; McIntyre, C. P.; Beaupre, S. R. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2013)
The National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility at the Woods Hole Oceanographic Institution has developed an Accelerator Mass Spectrometry (AMS) system designed specifically for the analysis of 14C in a continuously flowing stream of carrier gas. A key part of the system is a gas-accepting microwave ion source. Recently, substantial progress has been made in the development of this source, having achieved ion currents rivaling that of a traditional graphite source (albeit at relatively low efficiency). Details and present performance of the gas source are given. Additionally, representative results obtained from coupling the source to both a gas chromatograph and gas bench are presented.
id: 2161

Great longevity of speckled hind ( Epinephelus drummondhayi), a deep-water grouper, with novel use of postbomb radiocarbon dating in the Gulf of Mexico - Andrews, Allen H.; Barnett, Beverly K.; Allman, Robert J.; Moyer, Ryan P.; Trowbridge, Hannah D.; Gillanders, Bronwyn (Canadian Journal of Fisheries and Aquatic Sciences, 2013)
Growth characteristics are poorly understood for speckled hind (Epinephelus drummondhayi), a tropical deep-water grouper of economic importance that is considered overfished. Age has been validated for early growth, but the validity of adult age estimates is unknown. A few studies of growth zones in otoliths have revealed maximum age estimates of 15–35 years, which have been uncritically assumed as longevity. To answer questions about adult age, bomb radiocarbon dating was used to provide validated age estimates. A novel aspect of this study was use of the postbomb radiocarbon decline period (ca. 1980–2004) to age younger fish, an approach that was validated with known-age otoliths. Bomb radiocarbon dating provided valid length-at-age estimates ranging from ∼5 years to more than 45 years. Age was unexpectedly greater than previous estimates for more than half the fish used in this study, and longevity may approach 60–80 years. This study extends the utility of bomb radiocarbon dating by more than 20 years and adds to the growing perspective that deep-water tropical fishes can be long-lived

A High-Throughput, Low-Cost Method for Analysis of Carbonate Samples for C-14 - Roberts, Mark L.; Beaupré, Steven R.; Burton, Joshua R. (Radiocarbon, 2013)
id: 2345; PT: J; TC: 0; UT: WOS:000325752100044

Holocene temperature history at the western Greenland Ice Sheet margin reconstructed from lake sediments - Axford, Yarrow; Losee, Shanna; Briner, Jason P.; Francis, Donna R.; Langdon, Peter G.; Walker, Ian R. (Quaternary Science Reviews, 2013)
Predicting the response of the Greenland Ice Sheet to future climate change presents a major challenge to climate science. Paleoclimate data from Greenland can provide empirical constraints on past cryospheric responses to climate change, complementing insights from contemporary observations and from modeling. Here we examine sedimentary records from five lakes near Jakobshavn Isbræ in central West Greenland to investigate the timing and magnitude of major Holocene climate changes, for comparison with glacial geologic reconstructions from the region. A primary objective of this study is to constrain the timing and magnitude of maximum warmth during the early to middle Holocene positive anomaly in summer insolation. Temperature reconstructions from subfossil insect (chironomid) assemblages suggest that summer temperatures were warmer than present by at least 7.1 ka (the beginning of the North Lake record; ka = thousands of years before present), and that the warmest millennia of the Holocene occurred in the study area between 6 and 4 ka. Previous studies in the Jakobshavn region have found that the local Greenland Ice Sheet margin was most retracted behind its present position between 6 and 5 ka, and here we use chironomids to estimate that local summer temperatures were 2–3 °C warmer than present during that time of minimum ice sheet extent. As summer insolation declined through the late Holocene, summer temperatures cooled and the local ice sheet margin expanded. Gradual, insolation-driven millennial-scale temperature trends in the study area were punctuated by several abrupt climate changes, including a major transient event recorded in all five lakes between 4.3 and 3.2 ka, which overlaps in timing with abrupt climate changes previously documented around the North Atlantic region and farther afield at ∼4.2 ka.

Holocene variability in hydrology, vegetation, fire, and eolian activity in the Nebraska Sand Hills, USA - Schmieder, Jens; Fritz, Sherilyn C; Grimm, Eric C; Jacobs, Kimberly C; Brown, Kendrick J; Swinehart, James B; Porter, Stephen C (The Holocene, 2013)
This study combined multiple aquatic and terrestrial proxies, including diatoms, pollen, grain size, and bulk-sediment chemistry to reconstruct the history of three lake sites located in the central Sand Hills of Nebraska, USA. Long-term changes in effective moisture are evident at all sites, with significant changes occurring at ~6000, ~4000, and ~ 2000 cal. yr BP. Both aquatic and terrestrial indicators suggest that effective moisture was low between 10,000 and ~6000 cal. yr BP, and that this time interval was the driest period of the Holocene. The dominance of benthic and tychoplanktic diatom taxa indicates relatively shallow lake-level, high sand influx indicates moderately high eolian activity, and the pollen assemblage suggests xeric grasslands with abundant mud flats. About 6000 cal. yr BP, all three sites experienced an increase in effective moisture. Lake-level rise is indicated by increases in planktic and tychoplanktic diatoms relative to benthic taxa, while greater abundance of grass pollen and charcoal, and decreased eolian flux indicate stabilized dunes with dense vegetation sufficient to fuel local fires. A significant hydrologic shift recorded at all sites occurred at ~4000 cal. yr BP. This event was characterized by substantial lake-level rise, yet decreased grass cover and fire frequency, and increased eolian activity. Water-table rise may have been caused by a combination of factors including: (1) formation of dune-dams that blocked old drainage channels, (2) reduced grass cover and hence reduced evapotranspiration, and (3) changes in the frequency and duration of drought. The most likely cause(s) of the differential response of the terrestrial and aquatic systems at this time is not clear, none-the-less the late Holocene was not nearly as dry as the interval prior to 6000 cal. yr BP. The last ~2000 yr were characterized by several short-term fluctuations in lake level, including an interval of drought between 950 and 750 cal. yr BP, coincident with increased eolian activity during the latter part of the Medieval Climatic Anomaly.
Keywords: diatoms; drought; Holocene climate change; lakes; Nebraska Sand Hills; pollen

Late Holocene expansion of Istorvet ice cap, Liverpool Land, east Greenland - Lowell, Thomas V.; Hall, Brenda L.; Kelly, Meredith A.; Bennike, Ole; Lusas, Amanda R.; Honsaker, William; Smith, Colby A.; Levy, Laura B.; Travis, Scott; Denton, George H. (Quaternary Science Reviews, 2013)
The Greenland Ice Sheet is undergoing dynamic changes that will have global implications if they continue into the future. In this regard, an understanding of how the ice sheet responded to past climate changes affords a baseline for anticipating future behavior. Small, independent ice caps adjacent to the Greenland Ice Sheet (hereinafter called “local ice caps”) are sensitive indicators of the response of Greenland ice-marginal zones to climate change. Therefore, we reconstructed late Holocene ice-marginal fluctuations of the local Istorvet ice cap in east Greenland, using radiocarbon dates of subfossil plants, 10Be dates of surface boulders, and analyses of sediment cores from both threshold and control lakes. During the last termination, the Istorvet ice cap had retreated close to its maximum Holocene position by ∼11,730 cal yr BP. Radiocarbon dates of subfossil plants exposed by recent recession of the ice margin indicate that the Istorvet cap was smaller than at present from AD 200 to AD 1025. Sediments from a threshold lake show no glacial input until the ice cap advanced to within 365 m of its Holocene maximum position by ∼AD 1150. Thereafter the ice cap remained at or close to this position until at least AD 1660. The timing of this, the most extensive of the Holocene, expansion is similar to that recorded at some glaciers in the Alps and in southern Alaska. However, in contrast to these other regions, the expansion in east Greenland at AD 1150 appears to have been very close to, if not at, a maximum Holocene value. Comparison of the Istorvet ice-cap fluctuations with Holocene glacier extents in Southern Hemisphere middle-to-high latitude locations on the Antarctic Peninsula and in the Andes and the Southern Alps suggests an out-of-phase relationship. If correct, this pattern supports the hypothesis that a bipolar see-saw of oceanic and/or atmospheric circulation during the Holocene produced asynchronous glacier response at some localities in the two polar hemispheres.
id: 2290

Long-term variations in Iceland–Scotland overflow strength during the Holocene - Thornalley, D. J. R.; Blaschek, M.; Davies, F. J.; Praetorius, S.; Oppo, D. W.; McManus, J. F.; Hall, I. R.; Kleiven, H.; Renssen, H.; McCave, I. N. (Climate of the Past, 2013)
The overflow of deep water from the Nordic seas into the North Atlantic plays a critical role in global ocean circulation and climate. Approximately half of this overflow occurs via the Iceland–Scotland (I–S) overflow, yet the history of its strength throughout the Holocene (~ 0–11 700 yr ago, ka) is poorly constrained, with previous studies presenting apparently contradictory evidence regarding its long-term variability. Here, we provide a comprehensive reconstruction of I–S overflow strength throughout the Holocene using sediment grain size data from a depth transect of 13 cores from the Iceland Basin. Our data are consistent with the hypothesis that the main axis of the I–S overflow on the Iceland slope was shallower during the early Holocene, deepening to its present depth by ~ 7 ka. Our results also reveal weaker I–S overflow during the early and late Holocene, with maximum overflow strength occurring at ~ 7 ka, the time of a regional climate thermal maximum. Climate model simulations suggest a shoaling of deep convection in the Nordic seas during the early and late Holocene, consistent with our evidence for weaker I–S overflow during these intervals. Whereas the reduction in I–S overflow strength during the early Holocene likely resulted from melting remnant glacial ice sheets, the decline throughout the last 7000 yr was caused by an orbitally induced increase in the amount of Arctic sea ice entering the Nordic seas. Although the flux of Arctic sea ice to the Nordic seas is expected to decrease throughout the next century, model simulations predict that under high emissions scenarios, competing effects, such as warmer sea surface temperatures in the Nordic seas, will result in reduced deep convection, likely driving a weaker I–S overflow.

A model for drowned terrestrial habitats with associated archeological remains in the northwestern Gulf of Maine, USA - Kelley, Joseph T.; Belknap, Daniel F.; Kelley, Alice R.; Claesson, Stefan H. (Marine Geology, 2013)
Marine geophysical techniques and geological measurement of sea-level change allow detailed mapping of seafloor archeological sites and development of models. In the northwestern Gulf of Maine, the lowstand of sea level is only at − 60 m depth, but a prolonged stasis during the late Quaternary sea-level rise, herein termed the slowstand, occurred between 11,500 and 7500 calibrated years before present (cal yr BP) at depths of 15–25 m. This slowdown caused substantial erosion of glacial deposits and formed terrestrial beaches, wetlands and lakes. These landforms attracted people, whose tools were later discovered during present day scallop-fishing activities. Our study areas at the Green Islands and Bass Harbor are within the lowstand and slowstand depth ranges, but at highly exposed and sheltered sites, respectively. The Green Islands site has lost most of its former terrestrial sediment and there is no longer any context for recovered artifacts. At the protected Bass Harbor site, the remains of eroded moraines are associated with drowned spits and a former lacustrine/estuarine basin. Cores at the Bass Harbor location encountered freshwater peat deposits and numerous shallow subtidal shell and plant fossils all deposited during the slowstand. The two most important controls on the preservation of terrestrial landforms and associated human artifacts in the northwestern Gulf of Maine are the rate of sea-level rise and degree of shelter of the site from waves.
id: 2285

Moisture and temperature changes associated with the mid-Holocene Tsuga decline in the northeastern United States - Marsicek, Jeremiah P.; Shuman, Bryan; Brewer, Simon; Foster, David R.; Oswald, W. Wyatt (Quaternary Science Reviews, 2013)
A decline of hemlock (Tsuga) populations at ca 5.5 ka (thousands of calibrated radiocarbon years before 1950 AD) stands out as the most abrupt vegetation change of the Holocene in North America, but remains poorly understood after decades of study. Recent analyses of fossil pollen have revealed a concurrent, abrupt oak (Quercus) decline and increases in the abundance of beech (Fagus) and pine (Pinus) on Cape Cod in eastern Massachusetts, but the replacement of drought-tolerant oaks by moisture-sensitive beeches appears inconsistent with low lake levels in the region at the same time. The oak and beech changes are also limited to coastal areas, and the coastal-inland differences require an explanation. Here, we develop a new lake-level reconstruction from Deep Pond, Cape Cod by using a transect of sediment cores and ground-penetrating radar (GPR) profiles to constrain the past elevations of the sandy, littoral zone of the pond. The reconstruction shows that a series of multi-century episodes of low water coincide with the abrupt hemlock and oak declines, and interrupt subsequent phases of hemlock recovery. The lake-level variations equal precipitation deficits of ∼100 mm superimposed on a Holocene long moisture increase of >400 mm. However, because moisture deficits do not easily explain the oak and beech changes, we also evaluate how the climate preferences of the regional vegetation changed over time by matching the fossil pollen assemblages from Deep Pond with their modern equivalents. Reconstructions of the precipitation requirements of the vegetation correlate well even in detail with the lake-level record (r = 0.88 at Deep Pond), and indicate close tracking of effective moisture (precipitation minus evapotranspiration) by the vegetation despite the abrupt species declines, which could have decoupled climate and vegetation trends. Reconstructions of the temperature preferences of the vegetation indicate that coastal sites may have cooled by 0.5–2.5 °C after ca 5.5 ka, while inland sites warmed by 0.5–1 °C. The change in coastal temperature preferences agrees with sea surface cooling in the western Atlantic Ocean of >1 °C. Consequently, the persistence of low hemlock abundance after 5.5 ka in the northeast U.S. may have resulted from oceanic changes that produced multi-century droughts and thus delayed the post-decline recovery of hemlock populations.

Onshore-offshore surficial geologic map of the Newburyport East and northern half of the Ipswich Quadrangles, Massachusetts - Hein, C.J.; FitzGerald, D.M.; Barnhardt, W.A.; Stone, B.D. (Geologic Map, 2013)
This geologic map shows the distribution of surficial subaerial and subaqueous materials in the Newburyport East and northern half of the Ipswich 7.5' quadrangles (northeast Massachusetts) and the area of the Gulf of Maine immediately offshore, to an approximate depth of 80 m below modern mean sea level (MSL). This map was compiled from the onshore surficial geologic map of Stone et al. (2006) and the offshore surficial mapping of Barnhardt et al. (2009), and includes newly mapped shallow offshore geologic features. Onshore and offshore units are continuous across the shallow- water zone (0-20 m below MSL). The definition of map units is based on lithologic characteristics (grain size, mineralogy and structure), stratigraphic relationships and relative ages, and sedimentologic processes. The map describes the evolution of the surficial geology in terms of the sediment sources, transportation mechanisms, and depositional, post-depositional and modern processes that have acted on the late Quaternary sediments that compose these units. Cross sections are derived from subsurface data compiled from the literature and collected as part of this study. This maps supersedes MGS OFR 2011-01

Organic carbon export from the Greenland ice sheet - Bhatia, Maya P.; Das, Sarah B.; Xu, Li; Charette, Matthew A.; Wadham, Jemma L.; Kujawinski, Elizabeth B. (Geochimica et Cosmochimica Acta, 2013)
Glacial meltwater exports a unique type of organic carbon to marine systems, distinct from non-glacially derived riverine export, potentially capable of stimulating downstream marine primary productivity. Here, we describe for the first time the bulk-level dissolved organic carbon (DOC) and particulate organic carbon (POC) isotopic composition of glacial meltwater draining the Greenland ice sheet (GrIS). These data, in conjunction with an earlier study that investigated the molecular-level composition of GrIS dissolved organic matter, collectively describe the concentration, radiocarbon content, and lability of organic carbon in subglacial discharge from a land-terminating outlet glacier during a melt season. By scaling up our measurements across the ice sheet, we estimate that the annual DOC flux from the GrIS (0.08 Tg/y) is equivalent to that from a small Arctic river (discharge (Q) 200 km3/y). The DOC flux is derived primarily from beneath the glacier (subglacial) (>75%) in the early season, and from surface ice-melt (up to 100%) transmitting through the subglacial environment at the peak of the meltseason. The POC flux is primarily derived from the subglacial environment throughout the meltseason. The early season (low flow) glacier discharge contains higher DOC concentrations (0.5–4.1 mg L−1), and exports more enriched carbon (Δ14CDOC ∼ −250‰) compared to the peak season (high flow) discharge, when the concentrations are lower (0.1–0.6 mg L−1) and the Δ14C is more depleted (Δ14CDOC ∼ −400‰). Conversely, the POC export (1.4–13.2 mg L−1, Δ14CPOC ∼ −250‰) shows no temporal variation in either concentration or radiocarbon content throughout the meltseason. Dissolved ion loads in concomitant samples reflected the seasonal evolution of the subglacial drainage system, confirming the influence of subglacial hydrology on the composition of the bulk carbon pools. Based on this work, we conclude that (1) different mechanisms control the DOC and POC flux from glacial systems; (2) chemically-distinct DOC pools are accessed by seasonally-evolving hydrological flow-paths; and (3) the GrIS can deliver labile carbon, which may also be 14C-depleted, to downstream proglacial and marine environments.
id: 2276

Persistent export of 231Pa from the deep central Arctic Ocean over the past 35,000 years - Hoffmann, Sharon S.; McManus, Jerry F.; Curry, William B.; Brown-Leger, L. Susan (Nature, 2013)
The Arctic Ocean has an important role in Earth’s climate, both through surface processes1 such as sea-ice formation and transport, and through the production and export of waters at depth that contribute to the global thermohaline circulation2, 3. Deciphering the deep Arctic Ocean’s palaeo-oceanographic history is a crucial part of understanding its role in climatic change. Here we show that sedimentary ratios of the radionuclides thorium-230 (230Th) and protactinium-231 (231Pa), which are produced in sea water and removed by particle scavenging on timescales of decades to centuries, respectively4, record consistent evidence for the export of 231Pa from the deep Arctic and may indicate continuous deep-water exchange between the Arctic and Atlantic oceans throughout the past 35,000 years. Seven well-dated box-core records provide a comprehensive overview of 231Pa and 230Th burial in Arctic sediments during glacial, deglacial and interglacial conditions. Sedimentary 231Pa/230Th ratios decrease nearly linearly with increasing water depth above the core sites, indicating efficient particle scavenging in the upper water column and greater influence of removal by lateral transport at depth. Although the measured 230Th burial is in balance with its production in Arctic sea water, integrated depth profiles for all time intervals reveal a deficit in 231Pa burial that can be balanced only by lateral export in the water column. Because no enhanced sink for 231Pa has yet been found in the Arctic, our records suggest that deep-water exchange through the Fram strait may export 231Pa. Such export may have continued for the past 35,000 years, suggesting a century-scale replacement time for deep waters in the Arctic Ocean since the most recent glaciation and a persistent contribution of Arctic waters to the global ocean circulation.
Keywords: Marine chemistry; Palaeoceanography; Palaeoclimate

Pleistocene sequence stratigraphy of the shallow continental shelf, offshore New Jersey: Constraints of Integrated Ocean Drilling Program Leg 313 core holes - Miller, Kenneth G.; Sugarman, Peter J.; Browning, James V.; Sheridan, Robert E.; Kulhanek, Denise K.; Monteverde, Donald H.; Wehmiller, John F.; Lombardi, Christopher; Feigenson, Mark D. (GEOSPHERE, 2013)
We used cores and logs from Integrated Ocean Drilling Program (IODP) Expedition 313 to generate biostratigraphic, lithofacies, biofacies, and geochemical data that constrain the ages and paleoenvironments of Pleistocene sequences. We integrate sequence stratigraphy on cores with new seismic stratigraphic data to interpret the Pleistocene history of the Hudson shelf valley and paleoenvironmental and sea-level changes on the inner to middle continental shelf. Improved age control compared to previous studies is provided by integrated calcareous nannofossil biostratigraphy, Sr isotopic stratigraphy, and amino acid racemization. We recognize four upper Pleistocene-Holocene sequences: sequence uP1 is correlated with Marine Isotope Chrons (MIC; ``chron{''} is the correct stratigraphic term for a time unit, not ``stage{''}) 7 or 5e, sequence uP2 with MIC 5c, sequence uP3 with MIC 5a, and sequence uP4 with the latest Pleistocene to Holocene (MIC 1-2). However, within our age resolution it is possible that sequences uP2 and uP3 correlate with MIC 4-3c and 3a, respectively, as suggested by previous studies. Lower Pleistocene sequences lP1 and lP2 likely correlate with peak interglacials (e. g., MIC 31 and MIC 45 or 47, respectively). Thus, we suggest that preservation of sequences occurs only during peak eustatic events (e. g., MIC 45 or 47, MIC 31, and MIC 5), unless they are preserved in eroded valleys. The architecture of the Pleistocene deposits at Sites M27 and M29 is one of thin remnants of highstand and transgressive systems tracts, with lowstand deposits only preserved in the thalwegs of incised valleys. Incised valleys at the bases of sequences uP3 (IODP Site M27) and uP2 (IODP Site M29) document more southward courses of the paleo-Hudson valley, compared to the more southeastward course of the MIC 1-2 paleo-Hudson valley. The patchy distribution of Pleistocene sequences beneath the New Jersey inner-middle continental shelf is due to low accommodation during an interval of large eustatic changes; this predicts that sequences in such settings will be discontinuous, patchy, and difficult to correlate, consistent with previous studies in Virginia and North Carolina.

Sea-level change during the last 2500 years in New Jersey, USA - Kemp, Andrew C.; Horton, Benjamin P.; Vane, Christopher H.; Bernhardt, Christopher E.; Corbett, D. Reide; Engelhart, Simon E.; Anisfeld, Shimon C.; Parnell, Andrew C.; Cahill, Niamh (Quaternary Science Reviews, 2013)
Relative sea-level changes during the last ∼2500 years in New Jersey, USA were reconstructed to test if late Holocene sea level was stable or included persistent and distinctive phases of variability. Foraminifera and bulk-sediment δ13C values were combined to reconstruct paleomarsh elevation with decimeter precision from sequences of salt-marsh sediment at two sites using a multi-proxy approach. The additional paleoenvironmental information provided by bulk-sediment δ13C values reduced vertical uncertainty in the sea-level reconstruction by about one third of that estimated from foraminifera alone using a transfer function. The history of sediment deposition was constrained by a composite chronology. An age–depth model developed for each core enabled reconstruction of sea level with multi-decadal resolution. Following correction for land-level change (1.4 mm/yr), four successive and sustained (multi-centennial) sea-level trends were objectively identified and quantified (95% confidence interval) using error-in-variables change point analysis to account for age and sea-level uncertainties. From at least 500 BC to 250 AD, sea-level fell at 0.11 mm/yr. The second period saw sea-level rise at 0.62 mm/yr from 250 AD to 733 AD. Between 733 AD and 1850 AD, sea level fell at 0.12 mm/yr. The reconstructed rate of sea-level rise since ∼1850 AD was 3.1 mm/yr and represents the most rapid period of change for at least 2500 years. This trend began between 1830 AD and 1873 AD. Since this change point, reconstructed sea-level rise is in agreement with regional tide-gauge records and exceeds the global average estimate for the 20th century. These positive and negative departures from background rates demonstrate that the late Holocene sea level was not stable in New Jersey.

Sedimentological and Geophysical Signatures of A Relict Tidal Inlet Complex Along A Wave-Dominated Barrier: Assateague Island, Maryland, U.S.A - Seminack, C. T.; Buynevich, I. V. (Journal of Sedimentary Research, 2013)
Assateague Island is a classic example of a wave-dominated, retrograding barrier island, with its recent geological history punctuated by episodes of overwash and breaching (comparable to the Outer Banks, North Carolina; northern New Jersey coast; Long Island, New York, etc.). This study aims to provide high-resolution data of a paleo-inlet which may lead to a more precise evolutionary model of other wave-dominated barrier islands. The study focuses on a historically stable segment fronting the Green Run Bay. The site lies north of the historical Green Run Inlet (active until 1880); however, there is no morphological or historical evidence of this inlet occupying the more northerly position, thus suggesting that the study site may represent a relict part of the barrier. High-resolution ground-penetrating radar (GPR) images, complemented with sediment cores and multi-dating techniques, were used to reconstruct the geological legacy of the Green Run Bay segment. The findings indicate that a shallow backbarrier channel, still visible within the Green Run Bay, can be traced to a large (> 380 m wide, 3.0–3.5 m thick) channel cut-and-fill structure beneath the barrier. The channel fill consists of tangential- to sigmoidal-oblique, southward-dipping reflections downlapping onto channel lag facies, which overlie subhorizontal bay-fill strata. Mollusks from the bay fill yield calibrated ages of 4419–2018 yr BP. The paleo-channel facies overlying the bay deposits exhibit a fining-upward sequence, with a mean grain size decreasing from 0.44 to 2.43 φ (0.74 to 0.19 mm). Optically stimulated luminescence dating places the middle part of the inlet fill at 730–590 yr BP. The paleo-channel fill does not extend to the south and therefore is a separate relict feature that predates the historical Green Run Inlet. The paleo-tidal prism of the relict channel was at least 17 × 106 m3, which is comparable to many wave-dominated historical and active inlets along the Atlantic Seaboard. Findings in this study provide the geological background for coastal hazard assessments and offer a mesoscale example of inlet-facies architecture in wave-dominated barrier sequences identified in the rock record.

Surface production fuels deep heterotrophic respiration in northern peatlands - Elizabeth Corbett, J.; Burdige, David J.; Tfaily, Malak M.; Dial, Angela R.; Cooper, William T.; Glaser, Paul H.; Chanton, Jeffrey P. (Global Biogeochemical Cycles, 2013)
[1] Multiple analyses of dissolved organic carbon (DOC) from pore waters were conducted to define the processes that govern carbon balance in peatlands: (1) source, reactivity, and transport of DOC with respect to vegetation, peat, and age of carbon substrate, (2) reactivity of DOC with respect to molecular size, and (3) lability to photoxidation of surficial DOC. We found that surface organic production fuels heterotrophic respiration at depth in advection-dominated peatlands, especially in fens. Fen DOC was Δ14C enriched relative to the surrounding fen peat, and fen respiration products were similar to this enriched DOC indicating that DOC was the main microbial substrate. Bog DOC was more variable showing either enrichment in ∆14C at depth or ∆14C values that follow peat values. This variability in bogs is probably controlled by the relative importance of vertical transport of labile carbon substrates within the peat profile versus DOC production from bog peat. These results extended our set of observations to 10 years at one bog-fen pair and add two additional bog-fen pairs to our series of observations. Anaerobic incubations of peat, rinsed free of residual DOC, produced DOC and respiration products that were strikingly similar to the peat values in a bog and two fens. This result demonstrated conclusively that downward advection is the process responsible for the presence of modern DOC found at depth in the peat column. Fen DOC has lower C/N values and up to twice as much LMW (<1 kDa) DOC as bogs due to differences in organic inputs and greater microbial processing. Fluorescence irradiation experiments showed that fen DOC is more photolabile than bog DOC.

Transient stratification as the cause of the North Pacific productivity spike during deglaciation - Lam, Phoebe J.; Robinson, Laura F.; Blusztajn, Jerzy; Li, Camille; Cook, Mea S.; McManus, Jerry F.; Keigwin, Lloyd D. (Nature Geoscience, 2013)
During the Bølling–Allerød warm period of the last deglaciation, about 14 kyr ago, there was a strong and pervasive spike in primary productivity in the North Pacific Ocean1. It has been suggested that this productivity event was caused by an influx of the micronutrient iron from surrounding continental shelves as they were flooded by sea-level rise2. Here we test this hypothesis by comparing numerous proxies of productivity with iron flux and provenance measured from a core from the subarctic Pacific Ocean. We find no evidence for an abrupt deglacial pulse of iron from any source at the time of peak productivity. Instead, we argue that the deglacial productivity peak was caused by two stepwise events. First, deep convection during early deglaciation increased nutrient supply to the surface but also increased the depth of the mixed layer, which pushed surface production deeper in the water column and induced light limitation. A subsequent input of meltwater from northern American ice sheets then stratified the water column, which relieved light limitation while leaving the surface waters enriched in nutrients. We conclude that iron plays, at most, a secondary role in controlling productivity during the glacial and deglacial periods in the subarctic Pacific Ocean.
Keywords: Biogeochemistry; Marine biology; Marine chemistry; Palaeoceanography

Treatise on Geomorphology8.26 Climate Change Impacts on Cold Climates - Baroni, C. (Elsevier, 2013)
Since the onset of Cenozoic ice sheets, cold climate regions have played a leading role in planetary energy balance, atmospheric and global oceanic circulations. Glacial and periglacial processes in polar regions act as morphogenetic agents for landscape sculpting providing landforms and deposits that represent valuable records for investigating the amplitude of key phases of Cenozoic glacial history. Glacio-eustatic sea-level variations induce revolutionary environmental changes across the entire planet. Changes in periglacial processes also influence cold region hydrology, ecosystems, and soil carbon storage. Climatic and environmental changes in cold regions cause adaptation through ecological and evolutionary responses by organisms.
Keywords: Adélie penguins; Antarctica; Arctic; Cenozoic; Climate change; Elephant seals; glacial history; Holocene; Icehouse

Tropical cyclone wind speed constraints from resultant storm surge deposition: A 2500 year reconstruction of hurricane activity from St. Marks, FL - Brandon, Christine M.; Woodruff, Jonathan D.; Lane, D. Phil; Donnelly, Jeffrey P. (Geochemistry, Geophysics, Geosystems, 2013)
[1] Recent work suggests that the patterns of intense (≥category 3 on the Saffir-Simpson scale) hurricane strikes over the last few millennia might differ from that of overall hurricane activity during this period. Prior studies typically rely on assigning a threshold storm intensity required to produce a sedimentological overwash signal at a particular coastal site based on historical analogs. Here, we improve on this approach by presenting a new inverse-model technique that constrains the most likely wind speeds required to transport the maximum grain size within resultant storm deposits. As a case study, the technique is applied to event layers observed in sediments collected from a coastal sinkhole in northwestern Florida. We find that (1) simulated wind speeds for modern deposits are consistent with the intensities for historical hurricanes affecting the site, (2) all deposits throughout the ∼2500 year record are capable of being produced by hurricanes, and (3) a period of increased intense hurricane frequency is observed between ∼1700 and ∼600 years B.P. and decreased intense storm frequency is observed from ∼2500 to ∼1700 and ∼600 years B.P. to the present. This is consistent with prior reconstructions from nearby sites. Changes in the frequency of intense hurricane strikes may be related to the degree of penetration of the Loop Current in the Gulf of Mexico.

An ~11,200 cal yr BP paleolimnological perspective for the archeological findings at Quartz Lake, Alaska - Wooller, M. J.; Kurek, J.; Gaglioti, B. V.; Cwynar, L. C.; Bigelow, N.; Reuther, J. D.; Gelvin-Reymiller, C.; Smol, J. P. (Journal of Paleolimnology, 2012)
Wetlands and lakes in the Tanana Valley, Alaska, have provided important resources for prehistoric humans who inhabited this region. We examine an ~11,200 cal yr BP record of environmental and paleolimnological changes from Quartz Lake in the middle Tanana Valley. Our data are also presented in the context of recent archaeological findings in the lake’s general vicinity that have 18 associated AMS 14C dates. We analyzed the stable-carbon and nitrogen isotope composition of total organic matter from the core, coupled with oxygen and carbon isotope analyses of Pisidiidae shells (fingernail clams), in addition to chironomid assemblage changes. Lacustrine sediments began to accumulate at ~11,200 cal yr BP. Initially, autochthonous production was low and allochthonous organic input was negligible between 11,000 and 10,500 cal yr BP, and were associated with relatively cool conditions at Quartz Lake at ~10,700 cal yr BP. After 10,500 cal yr BP, autochthonous production was higher coincident with a shift to chironomid assemblages dominated by taxa associated with warmer summer climates. A decrease in δ13C values of total organic carbon (TOC) and organic content of the sediment between 9,000 and 4,000 cal yr BP may indicate declining autochthonous primary production. This period ended with an abrupt (~7 ‰) decrease in the δ18O values from Pisidiidae shells at ~3,000 cal yr BP, which we hypothesize represented an episodic connection (flood) of the lake with flow from the nearby (~6 km) Tanana River. Our findings coincide with evidence for major flooding at other locations connected to the Tanana River and further afield in Alaska. From ~3,000 cal yr BP Quartz Lake subsequently appeared to become a relatively closed system, as indicated by the δ18OPisidiidae and δ13CPisidiidae data that are positively correlated and generally higher, which also correlates with a shift to moderately higher abundances of littoral chironomids. The cause of the transition to closed-basin conditions may have been geomorphic rather than climatic. This evidence of a progressively stronger evaporative influence on the lake’s closed hydrology after ~3,000 cal yr BP is consistent with our modern δ18O and δD water data from Quartz Lake that plot along a regional evaporative line we base on isotopic measurements from other local lakes and rivers.
id: 2134

Anthropogenic aerosols as a source of ancient dissolved organic matter in glaciers - Stubbins, Aron; Hood, Eran; Raymond, Peter A.; Aiken, George R.; Sleighter, Rachel L.; Hernes, Peter J.; Butman, David; Hatcher, Patrick G.; Striegl, Robert G.; Schuster, Paul; Abdulla, Hussain A. N.; Vermilyea, Andrew W.; et al. (Nature Geoscience, 2012)
Glacier-derived dissolved organic matter represents a quantitatively significant source of ancient, yet highly bioavailable carbon to downstream ecosystems1. This finding runs counter to logical perceptions of age–reactivity relationships, in which the least reactive material withstands degradation the longest and is therefore the oldest2. The remnants of ancient peatlands and forests overrun by glaciers have been invoked as the source of this organic matter1, 3, 4. Here, we examine the radiocarbon age and chemical composition of dissolved organic matter in snow, glacier surface water, ice and glacier outflow samples from Alaska to determine the origin of the organic matter. Low levels of compounds derived from vascular plants indicate that the organic matter does not originate from forests or peatlands. Instead, we show that the organic matter on the surface of the glaciers is radiocarbon depleted, consistent with an anthropogenic aerosol source. Fluorescence spectrophotometry measurements reveal the presence of protein-like compounds of microbial or aerosol origin. In addition, ultrahigh-resolution mass spectrometry measurements document the presence of combustion products found in anthropogenic aerosols. Based on the presence of these compounds, we suggest that aerosols derived from fossil fuel burning are a source of pre-aged organic matter to glacier surfaces. Furthermore, we show that the molecular signature of the organic matter is conserved in snow, glacier water and outflow, suggesting that the anthropogenic carbon is exported relatively unchanged in glacier outflows.
Keywords: Atmospheric chemistry; Biogeochemistry; Cryospheric science

Carbon dynamics in the western Arctic Ocean: insights from full-depth carbon isotope profiles of DIC, DOC, and POC - Griffith, D. R.; McNichol, A. P.; Xu, L.; McLaughlin, F. A.; Macdonald, R. W.; Brown, K. A.; Eglinton, T. I. (Biogeosciences, 2012)
Arctic warming is projected to continue throughout the coming century. Yet, our currently limited understanding of the Arctic Ocean carbon cycle hinders our ability to predict how changing conditions will affect local Arctic ecosystems, regional carbon budgets, and global climate. We present here the first set of concurrent, full-depth, dual-isotope profiles for dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), and suspended particulate organic carbon (POCsusp) at two sites in the Canada Basin of the Arctic Ocean. The carbon isotope composition of sinking and suspended POC in the Arctic contrasts strongly with open ocean Atlantic and Pacific sites, pointing to a combination of inputs to Arctic POCsusp at depth, including surface-derived organic carbon (OC), sorbed/advected OC, and OC derived from in situ DIC fixation. The latter process appears to be particularly important at intermediate depths, where mass balance calculations suggest that OC derived from in situ DIC fixation contributes up to 22% of POCsusp. As in other oceans, surface-derived OC is still a dominant source to Arctic POCsusp. Yet, we suggest that significantly smaller vertical POC fluxes in the Canada Basin make it possible to see evidence of DIC fixation in the POCsusp pool even at the bulk isotope level.
id: 2254; PT: J; TC: 4; UT: WOS:000302179500026

Characteristics of water-soluble organic carbon associated with aerosol particles in the eastern United States - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M. (Atmospheric Environment, 2012)
Desorption kinetics and sources (fossil vs. contemporary) of the water soluble organic carbon (WSOC) component of aerosol particles were examined at two sites on the east coast of the United States. Experiments revealed that WSOC is released either rapidly as one homogeneous pool or via biphasic kinetics with one rapidly and one slowly desorbing pool. The majority (>85%) of WSOC was desorbed within the first 15 min of immersion in water, suggesting that this material can be rapidly incorporated into rainwater pre-depositionally or surface waters post-depositionally and transported through watersheds. Radiocarbon (14C) measurements showed that on average 12 ± 4% and 14 ± 2% of WSOC from sites in New York and Virginia, respectively, was derived from fossil sources. By contrast, mass balance calculations revealed water-insoluble organic carbon to have significantly greater fossil contributions. These findings suggest that contemporary biogenic aerosol OC is preferentially incorporated into the aqueous phase and may be transported relatively rapidly through watersheds and aquatic systems. In contrast, the more highly aged and fossil aerosol component remains in particulate form and is more likely to be retained on particles or in soils or aquatic sediments.
id: 2153

Chemical and bacteriological analysis of soil from the Middle and Late Weichselian from Western Spitsbergen, Arctic - Singh, Shiv Mohan; Sharma, Jagdev; Gawas-Sakhalkar, Puja; Upadhyay, Ajay K.; Naik, Simantini; Bande, Dnyanesh; Ravindra, Rasik (The environment and chronology of the earliest occupation of north-west Europe: current knowledge, problems and new research directions, 2012)
This paper discusses temporal variability in the biogeochemical properties of the deeper permafrost soils of Western Spitsbergen, Arctic, that dates back up to the Middle Weichselian period (44.8 ka BP). Results indicate that during the mid of the last interstadial (∼37 ka BP) the chemical and biological properties of the soils were different from the stadial period that followed. Trace element concentration during the period remained low. Electrical conductivity along with K, Mg, Na, SO4−2, Cl− and HCO3− content of the soils during this period was high. Mineralizable nitrogen, organic carbon, biomass nitrogen and total bacterial counts were also high. These observations concurrently lead to a conclusion that the soils of Western Spitsbergen during the interstadial period were under marine influence. The culturability of bacterial cells was low which increased later with the onset of the stadial.
id: 2316

Climatic and environmental evolution of Lake Iznik (NW Turkey) over the last ∼4700 years - Ülgen, Umut Barış; Franz, Sven Oliver; Biltekin, Demet; Çağatay, M. Namik; Roeser, Patricia Angelika; Doner, Lisa; Thein, Jean (Temporal and spatial corridors of Homo sapiens sapiens population dynamics during the Late Pleistocene and Early Holocene, 2012)
Magnetic susceptibility, geochemistry, mineralogy and palynology of sediments from Lake Iznik in Northwestern Anatolia, Turkey, provide a 4700 year record of climatic trends and events. The measured proxies allow a reconstruction of variations in humid/dry periods and lake level changes. The Lake Iznik sedimentary sequence points to an oscillating trend of humid periods interrupted by rapid climate change (RCC) to arid periods. Especially abrupt lithologic and geochemical changes at 4.2 and 3.3 ka calBP may outline intense droughts, which extremely lowered the lake level. For the last 2000 years, the effects of the Roman warm period, Dark Age cold period, Medieval Warm Period and Little Ice Age are recorded within Lake Iznik sediments. Besides many similarities of local climatic periods with other records from the Eastern Mediterranean, there are also differences indicating the complex pattern of the climate in the region.
id: 2337

Constraining Holocene 10Be production rates in Greenland - Briner, Jason P.; Young, ás E.; Goehring, Brent M.; Schaefer, Joerg M. (Journal of Quaternary Science, 2012)
The absence of a production rate calibration experiment on Greenland has limited the ability to link 10Be exposure dating chronologies of ice-margin change to independent records of rapid climate change. We use radiocarbon age control on Holocene glacial features near Jakobshavn Isbræ, western Greenland, to investigate 10Be production rates. The radiocarbon chronology is inconsistent with the 10Be age calculations based on the current globally averaged 10Be production rate calibration data set, but is consistent with the 10Be production rate calibration data set from north-eastern North America, which includes a calibration site nearby on north-eastern Baffin Island. Based on the best-dated feature available from the Jakobshavn Isbræ forefield, we derive a 10Be production rate value of 3.98 ± 0.24 atoms g a−1, using the ‘St’ scaling scheme, which overlaps with recently published reference 10Be production rates. We suggest that these 10Be production rate data, or the very similar data from north-eastern North America, are used on Greenland. Copyright © 2011 John Wiley & Sons, Ltd.

Correction to" Isotopic characterization of aerosol organic carbon components over the eastern United States" (vol 117, D13303, 2012) - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M.; Xu, Li; McNichol, Ann P. (Journal of Geophysical Research-Atmospheres, 2012)
id: 2251; PT: J; TC: 0; UT: WOS:000307471700004

The deglacial to postglacial marine environments of SEBarrow Strait, Canadian Arctic Archipelago - Pieńkowski, A. J.; England, John H.; Furze, Mark F. A.; Marret, Fabienne; Eynaud, Frédérique; Vilks, Gustav; MacLean, Brian; Blasco, Steve; Scourse, James D. (Boreas, 2012)
Core 86027-144 (74°15.56?N, 91°14.21?W) represents a rare, continuous record of Late Pleistocene to Holocene sediments from High Arctic Canada extending from the end of the Last Glaciation. Based on microfossils (dinocysts, non-pollen palynomorphs, benthic and planktonic foraminifera), foraminiferal ?18O and ?13C, and sedimentology, seven palaeoenvironmental zones were identified. Zone I (>10.8?cal.?ka BP) records deglaciation, ice-sheet destabilization, float-off and subsequent break-up. Zone II (c.?10.8?10.4?cal.?ka BP) shows ice-proximal to ice-distal glaciomarine conditions, interrupted by pervasive land-fast sea-ice marked by a hiatus in coarse sediment deposition. Significant biological activity starts in Zone III (10.4?9.9?cal.?ka BP), where planktonic foraminifera (Neogloboquadrina pachyderma) suggest early oceanic throughflow. Surface waters flowed NW?SE; however, the deep-water origin remains unclear (potentially NW Arctic Ocean or Baffin Bay). Postglacial amelioration (open-water season greater than present) in Zone IV (9.9?7.8?cal.?ka BP) perhaps corresponds to the regional ?Holocene Thermal Maximum? previously proposed. A transitional period (Zone V; 7.8?6.7?cal. ka BP) of rapid environmental change fluctuating on a scale not observed today is marked by increasing sea-ice and reduced oceanic influence. This probably signals the exclusion of deeper Atlantic water owing to the glacio-isostatic shallowing of inter-island sills, coupled with generally cooling climate. Conditions analogous to those at present, with increased sea-ice and modern microfossil assemblages, commence at c. 6.7?cal.?ka BP (zones VI?VII). Although climate ultimately forces long-term environmental trends, core 86027-144 data imply that regional dynamics, especially changes in sea-level, exert a significant control on marine conditions throughout the Canadian Arctic Archipelago.
id: 2342

Early stall of West Antarctic Ice Sheet advance on the eastern Ross Sea middle shelf followed by retreat at 27,500 14C yr BP - Bart, Philip J.; Cone, Amy N. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Marine geological and geophysical data suggest that the West Antarctic Ice Sheet (WAIS) deposited three thick seismically-resolvable units in the eastern Ross Sea since the Last Glacial Maximum (LGM) but the chronology of these grounding events is debated. Existing ice-retreat chronologies for the eastern Ross Sea are considered suspect because nearly all have been developed using radiocarbon dating of acid-insoluble organics (AIO) from bulk sediment. We used a new strategy to isolate in situ forams from diamict sediment deposited at the middle-shelf grounding-zone wedge (GZW) — a subaqueous ice-marginal landform previously interpreted to represent deposition during the third grounding event since the LGM advance to the shelf edge. Here we present a synthesis of our new radiocarbon dates of foram tests and AIO with previously published radiocarbon dates. We propose that the WAIS's LGM advance in the eastern-Ross Sea sector reached the middle shelf circa 27,500 14C yr BP and that open-marine sedimentation began shortly thereafter. There is as of yet no clear explanation for why WAIS retreat in this sector of Antarctica apparently began prior to the peak of the last glacial cold period. A precipitation deficit, localized warm water intrusion, an ice dynamic response in the absence of climate forcing or another as of yet unknown forcing mechanism could be responsible.
id: 2170

Exploring human subsistence at CA-SMI-575NE: An 8400-year-old shell midden on San Miguel Island, California - Erlandson, Jon M.; Braje, Todd J. (Exploring Methods of Faunal Analysis: Insights from California Archaeology, 2012)
id: 2069

Fine scale sediment structure and geochemical signature between eastern and western North Atlantic during Heinrich events 1 and 2 - Rashid, H.; Saint-Ange, F.; Barber, D. C.; Smith, M. E.; Devalia, N. (Quaternary Science Reviews, 2012)
Heinrich iceberg-rafting events 1 and 2 (H1 and H2) in the Labrador Sea are identified by their typical nepheloid-flow deposit sedimentary structure, high bulk carbonate, increase in iceberg-rafted detritus (IRD), and depletion of δ18O in the surface-dwelling foraminifer, Neogloboquadrina pachyderma (s). H-layers in this region have sedimentological characteristics different than those in the North Atlantic, and consist of IRD interspersed in pelagic sediments. High resolution 14C-AMS dates allowed us to delineate the leads and lags in instability between different ice-streams of the former Laurentide ice-sheet (LIS). Our data suggest that the discharge from the Hudson Strait ice-stream was followed by Cumberland Sound ice-sheet during H1 and H2. New radiogenic isotopes from the ice-proximal and surficial sediments of the greater Hudson Strait region and Labrador Sea H0, H1 and H2 layers suggest that carbonate-rich layers were only derived from Hudson Strait, not Baffin Bay. Fine scale structure of H1 and H2 intervals in Labrador Sea slope cores is characterized by two lithic peaks dominated by detrital carbonate grains and a single peak in cores from the central Labrador Sea. A similar pattern in the structure of H1 and H2 is observed along the western European margin. These findings contrast with North Atlantic H1 and H2 intervals, which are characterized by a peak of carbonate-rich grains, followed by a peak of quartz and volcanic grains. This comparison with North Atlantic and western European margin cores leads us to suggest that the coupling or lack thereof, between the LIS and European ice-sheet, is related to the depositional processes occurring along the margins, as well as the distance from the sources and the ability of the oceanic currents to disperse icebergs. Any significant change in ice-sheet dynamics would be recorded close to the ice-sheet margin, while distal locations would only record extreme events. We hypothesize that the discordance between the findings reported in the literature is most likely similar to the difference between the upper slope/deep Labrador sites and the Flemish Pass site described in this contribution but requires vigorous testing.
id: 2308

Insights into the Holocene environmental setting of Terra Nova Bay region (Ross Sea, Antarctica) from oxygen isotope geochemistry of Adélie penguin eggshells - Lorenzini, Sandra; Baneschi, Ilaria; Fallick, Anthony E.; Salvatore, Maria Cristina; Zanchetta, Giovanni; Dallai, Luigi; Baroni, Carlo (The Holocene, 2012)
An oxygen isotope record of Adélie penguin (Pygoscelis adeliae) eggshells from Terra Nova Bay (Victoria Land, Antarctica) has been reconstructed in order to provide insights into the palaeoenviroment of this region during the last ~8000 years. The d18O values measured in eggshell carbonate show a great variability over the course of the studied period, with maximum values consistently around +27.5‰. Adopting a metabolic enrichment relative to water source of ~+28.5‰, eggshell d18O values can be interpreted in terms of marine water uptake by the penguins. The spread in d18O of eggshell carbonate at any given time toward more negative values reflects the existence of a low d18O water end member, most plausibly snow or snowmelt. Samples younger than 2000 years are characterized by a general lack of very negative d18O values. As also attested by other proxies, this shift toward more positive isotopic values is likely to be related both to a decreasing contribution of snow or meltwater in the seawaters and consequently to an absence or paucity on the boundary of the nesting sites of snow or snowfall and freshwater that could be directly eaten or drunk by penguins.
id: 2348

Isotopic characterization of aerosol organic carbon components over the eastern United States - Wozniak, Andrew S.; Bauer, James E.; Dickhut, Rebecca M.; Xu, Li; McNichol, Ann P. (Journal of Geophysical Research-Atmospheres, 2012)
Carbon isotopic signatures (delta C-13, Delta C-14) of aerosol particulate matter total organic carbon (TOC) and operationally defined organic carbon (OC) components were measured in samples from two background sites in the eastern U. S. TOC and water-soluble OC (WSOC) delta C-13 values (-27 to -24 parts per thousand) indicated predominantly terrestrial C-3 plant and fossil derived sources. Total solvent extracts (TSE) and their aliphatic, aromatic, and polar OC components were depleted in delta C-13 (-30 to -26 parts per thousand) relative to TOC and WSOC. Delta C-14 signatures of aerosol TOC and TSE (-476 to +25 parts per thousand) suggest variable fossil contributions (similar to 5-50%) to these components. Aliphatic OC while comprising a small portion of the TOC (
id: 2252; PT: J; TC: 1; UT: WOS:000306237000001

Late-Pleistocene to Holocene sedimentary fills of the Çınarcık Basin of the Sea of Marmara - Eriş, K. Kadir; Çağatay, Namık; Beck, Christian; Mercier de Lepinay, Bernard; Corina, Campos (Sedimentary Geology, 2012)
A giant RV Marion Dufresne piston core MD01-2425 recovered from the 1276 m-deep Çınarcık Basin of the Sea of Marmara documents characteristics of deep basin sedimentation influenced by large-scale gravity-controlled mass-wasting processes and associated turbidite deposition during the Late Pleistocene to Holocene. A visual lithological description of the core reveals twenty major seismoturbidite layers (> 20 cm thick), intercalated in hemipelagic-type fine-grained calcareous and slightly siliceous clays. The thickness and frequency of the sesimoturbidite layers deposited during the lacustrine period (prior to 12.3 cal ka BP) is much greater than during the Holocene marine period. The sedimentary processes during deposition of seismoturbidites in the basin have been determined in this study using a combination of grain-size parameters. Often the seismoturbidites show strong grain segregation with a sharp boundary between a coarse lower and a homogeneous upper part. The traction carpet deposits formed at the base of a turbulent suspension and were produced in the lower coarse-grained part, whereas the homogeneous upper part was deposited by uniform suspensions following bedload deposition.
id: 2309

Marine climatic seasonality during medieval times (10th to 12th centuries) based on isotopic records in Viking Age shells from Orkney, Scotland - Surge, Donna; Barrett, James H. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Seasonal sea-surface temperature (SST) variability during the Medieval Climate Anomaly (MCA), which corresponds to the height of Viking exploration (800–1200 AD), was estimated using oxygen isotope ratios (δ18O) obtained from high-resolution samples micromilled from archaeological shells of the European limpet, Patella vulgata. Our findings illustrate the advantage of targeting SST archives from fast-growing, short-lived molluscs that capture summer and winter seasons simultaneously. Shells from the 10th to 12th centuries (early MCA) were collected from well-stratified horizons, which accumulated in Viking shell and fish middens at Quoygrew on Westray in the archipelago of Orkney, Scotland. Their ages were constrained based on artifacts and radiocarbon dating of bone, charred cereal grain, and the shells used in this study. We used measured δ18OWATER values taken from nearby Rack Wick Bay (average 0.31 ± 0.17‰ VSMOW, n = 11) to estimate SST from δ18OSHELL values. The standard deviation of δ18OWATER values resulted in an error in SST estimates of ± 0.7 °C. The coldest winter months recorded in the shells averaged 6.0 ± 0.6 °C and the warmest summer months averaged 14.1 ± 0.7 °C. Winter and summer SST during the late 20th century (1961–1990) was 7.77 ± 0.40 °C and 12.42 ± 0.41 °C, respectively. Thus, during the 10th to 12th centuries winters were colder and summers were warmer by ~ 2 °C and seasonality was higher relative to the late 20th century. Without the benefit of seasonal resolution, SST averaged from shell time series would be weighted toward the fast-growing summer season, resulting in the conclusion that the early MCA was warmer than the late 20th century by ~ 1 °C. This conclusion is broadly true for the summer season, but not true for the winter season. Higher seasonality and cooler winters during early medieval times may result from a weakened North Atlantic Oscillation index.
id: 2320

The Medieval Climate Anomaly in the Iberian Peninsula reconstructed from marine and lake records - Moreno, Ana; Pérez, Ana; Frigola, Jaime; Nieto-Moreno, Vanesa; Rodrigo-Gámiz, Marta; Martrat, Belén; González-Sampériz, Penélope; Morellón, Mario; Martín-Puertas, Celia; Corella, Juan Pablo; Belmonte, Ánchel; Sancho, Carlos; et al. (Quaternary Science Reviews, 2012)
Selected multi-proxy and accurately dated marine and terrestrial records covering the past 2000 years in the Iberian Peninsula (IP) facilitated a comprehensive regional paleoclimate reconstruction for the Medieval Climate Anomaly (MCA: 900–1300 AD). The sequences enabled an integrated approach to land–sea comparisons and, despite local differences and some minor chronological inconsistencies, presented clear evidence that the MCA was a dry period in the Mediterranean IP. It was a period characterized by decreased lake levels, more xerophytic and heliophytic vegetation, a low frequency of floods, major Saharan eolian fluxes, and less fluvial input to marine basins. In contrast, reconstruction based on sequences from the Atlantic Ocean side of the peninsula indicated increased humidity. The data highlight the unique characteristics of the MCA relative to earlier (the Dark Ages, DA: ca 500–900 years AD) and subsequent (the Little Ice Age, LIA: 1300–1850 years AD) colder periods. The reconstruction supports the hypothesis of Trouet et al. (2009), that a persistent positive mode of the North Atlantic Oscillation (NAO) dominated the MCA.
id: 2334

Molecular records of climate variability and vegetation response since the Late Pleistocene in the Lake Victoria basin, East Africa - Berke, Melissa A.; Johnson, Thomas C.; Werne, Josef P.; Grice, Kliti; Schouten, Stefan; Sinninghe Damsté, Jaap S. (Quaternary Science Reviews, 2012)
New molecular proxies of temperature and hydrology are helping to constrain tropical climate change and elucidate possible forcing mechanisms during the Holocene. Here, we examine a ∼14,000 year record of climate variability from Lake Victoria, East Africa, the world's second largest freshwater lake by surface area. We determined variations in local hydroclimate using compound specific δD of terrestrial leaf waxes, and compared these results to a new record of temperature utilizing the TEX86 paleotemperature proxy, based on aquatic Thaumarchaeotal membrane lipids. In order to assess the impact of changing climate on the terrestrial environment, we generated a record of compound specific δ13C from terrestrial leaf waxes, a proxy for ecosystem-level C3/C4 plant abundances, and compared the results to previously published pollen-inferred regional vegetation shifts. We observe a general coherence between temperature and rainfall, with a warm, wet interval peaking ∼10–9 ka and subsequent gradual cooling and drying over the remainder of the Holocene. These results, particularly those of rainfall, are in general agreement with other tropical African climate records, indicating a somewhat consistent view of climate over a wide region of tropical East Africa. The δ13C record from Lake Victoria leaf waxes does not appear to reflect changes in regional climate or vegetation. However, palynological analyses document an abrupt shift from a Poaceae (grasses)-dominated ecosystem during the cooler, arid late Pleistocene to a Moraceae-dominated (trees/shrubs) landscape during the warm, wet early Holocene. We theorize that these proxies are reflecting vegetation in different locations around Lake Victoria. Our results suggest a predominantly insolation-forced climate, with warm, wet conditions peaking at the maximum interhemispheric seasonal insolation contrast, likely intensifying monsoonal precipitation, while maximum aridity coincides with the rainy season insolation and the interhemispheric contrast gradient minima. We interpret a shift in conditions at the Younger Dryas to indicate a limited switch in insolation-dominated control on climate of the Lake Victoria region, to remote teleconnections with the coupled Atlantic and Pacific climate system.
id: 2318

Optimizing a microwave gas ion source for continuous-flow accelerator mass spectrometry - von Reden, K. F.; Roberts, M. L.; Burton, J. R.; é, S. R. (Review of Scientific Instruments, 2012)
A 2.45 GHz microwave ion source coupled with a magnesium charge exchange canal (C × C) has been successfully adapted to a large acceptance radiocarbon accelerator mass spectrometry system at the National Ocean Sciences Accelerator Mass Spectrometry (AMS) Facility, Woods Hole Oceanographic Institution. CO2 samples from various preparation sources are injected into the source through a glass capillary at 370 μl/min. Routine system parameters are about 120–140 μA of negative 12C current after the C × C, leading to about 400 14C counts per second for a modern sample and implying a system efficiency of 0.2%. While these parameters already allow us to perform high-quality AMS analyses on large samples, we are working on ways to improve the output of the ion source regarding emittance and efficiency. Modeling calculations suggest modifications in the extraction triode geometry, shape, and size of the plasma chamber could improve emittance and, hence, ion transport efficiency. Results of experimental tests of these modifications are presented.

Paleoenvironmental changes on the northeastern and southwestern Black Sea shelves during the Holocene - Ivanova, Elena V.; Murdmaa, Ivar O.; Karpuk, Maria S.; Schornikov, Eugene I.; Marret, Fabienne; Cronin, Thomas M.; Buynevich, Ilya V.; Platonova, Elena A. (Quaternary International, 2012)
Four paleoceanographic events are distinguished during the Holocene based on changes in macro- and microfossil assemblages studied from three sediment cores (Ak 521, 522, 2571) from the outer northeast shelf and from core MAR02-45 situated on the southwest shelf of the Black Sea, west to the Bosphorus. The lithology and fossils were previously studied from cores Ak 521 and Ak 522 and MAR02-45. However, high resolution ostracod analyses from the AMS-14C dated core, Ak 2571, allowed for a revision of the taxonomy and paleoecological interpretation of this microfaunal group on the NE shelf. Downcore changes in the relative abundance of the polyhaline ostracods are found to be contemporaneous in all three cores from the NE shelf. As a result, centennial-millennial scale fluctuations of the bottom-water salinity are resolved in the area. A broader scale examination of paleoenvironmental changes between the NE and SW shelves is also made and the surface to bottom salinity gradient is discussed. An uncalibrated radiocarbon based chronology is used throughout this paper to facilitate comparison with the regional chronostratigraphy of marine transgression and regressions in the Black Sea. The calibrated ages corrected for the changes in reservoir age through the Holocene are also provided. The first paleoceanographic event is associated with the pulse of Mediterranean water previously established at about 9.8–9.3 ka BP. This event is clearly observed in the SW region but not on the NE shelf due to a hiatus in the longest core, Ak 521. The second event is represented on both the NE and SW shelves as a replacement of brackish benthic fauna and surface phytoplankton with marine ones between 8.4 and 6.9 ka BP, indicating a gradual increase in salinity. The third event is marked by opposing trends in surface and bottom-water salinity changes. On the NE shelf, bottom-water salinity rose to modern values by ∼ 6.5 ka BP and then decreased within the interval ∼6.4–5.3 ka BP as recorded by the ostracod assemblages. On the SW shelf, surface-water salinity reached modern values by 5.6 ka BP and remained constant until present day as inferred from the dinoflagellate cyst assemblages. The fourth event is marked by a recurring increase in bottom-water salinity to modern values indicated by the polyhaline ostracod assemblages at ∼ 5.3 ka BP in the NE region, after which only minor salinity fluctuations are observed.
id: 2123

Paleoseismic and geomorphologic evidence of recent tectonic activity of the Pozohondo Fault (Betic Cordillera, SE Spain) - Rodriguez-Pascua, M. A.; Perez-Lopez, R.; Garduno-Monroy, V. H.; Giner-Robles, J. L.; Silva, P. G.; Perucha-Atienza, M. A.; Hernandez-Madrigal, V. M.; Bischoff, J. (JOURNAL OF IBERIAN GEOLOGY, 2012)
Instrumental and historical seismicity in the Albacete province (External Prebetic Zone) has been scarcely recorded. However, major strike-slip faults showing NW-SE trending provide geomorphologic and paleoseismic evidence of recent tectonic activity (Late Pleistocene to Present). Moreover, these faults are consistently well oriented under the present stress tensor and therefore, they can trigger earthquakes of magnitude greater than M6, according to the lengths of surface ruptures and active segments recognized in fieldwork. Present landscape nearby the village of Hellin (SE of Albacete) is determined by the recent activity of the Pozohondo Fault (FPH), a NW-SE right-lateral fault with 90 km in length. In this study, we have calculated the Late Quaternary tectonic slip-rate of the FPH from geomorphological, sedimentological, archaeoseimological, and paleoseismological approaches. All of these data suggest that the FPH runs with a minimum slip-rate of 0.1 mm/yr during the last 100 kyrs (Upper Pleistocene-Holocene). In addition, we have recognized the last two major paleoearthquakes associated to this fault. Magnitudes of these paleoearthquakes were gretarer than M6 and their recurrence intervals ranged from 6600 to 8600 yrs for the seismic cycle of FPH. The last earthquake was dated between the 1st and 6th centuries, though two earthquakes could be interpreted in this wide time interval, one at the FPH and other from a far field source. Results obtained here, suggest an increasing of the tectonic activity of the Pozohondo Fault during the last 10,000 yrs.
Keywords: Geomorphology; Paleoseismology; Prebetic; Quaternary; SE Spain

Photochemical reactivity of ancient marine dissolved organic carbon - Beaupré, Steven R.; Druffel, Ellen R. M. (Geophysical Research Letters, 2012)
Marine dissolved organic carbon (DOC) is the largest reservoir of reduced carbon in seawater and persists up to 4,000-6,000 conventional radiocarbon (C-14) years on average. Photochemical degradation has been suggested as a geochemical sink for these long-lived molecules, yet there have been no studies relating photochemical lability to the C-14-ages of surface DOC. We observed apparent second order (2 degrees) kinetics with respect to DOC and a strong trend from Delta C-14-enriched to depleted values during exhaustive photomineralization of surface marine DOC with high energy UV light. Geochemically, these results suggest that surface DOC is an isotopically-heterogeneous mixture of molecules for which photochemical lability and C-14 ages are correlated. Photochemical mineralization may therefore be an important control on the persistence of C-14-depleted DOC in the ocean. Citation: Beaupre, S. R., and E. R. M. Druffel (2012), Photochemical reactivity of ancient marine dissolved organic carbon, Geophys. Res. Lett., 39, L18602, doi:10.1029/2012GL052974.
id: 2249; PT: J; TC: 0; UT: WOS:000309136800001

Pre-Columbian fire regimes in lowland tropical rainforests of southeastern Peru - McMichael, C. H.; Correa-Metrio, A.; Bush, M. B. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
We document the fire history of the forests of a well-studied ecological research station (Los Amigos) in western Amazonia through soil charcoal analysis, and compare results with data from a nearby lake district known to have supported pre-Columbian human populations. We present novel methods of soil charcoal analysis that improve on its current limitations by accounting for variability in post-fire charcoal deposition, problematic age–depth relationships, and the presence of weathered or regionally-deposited charcoal particles that allow statistical comparisons of fire history characteristics between regions. The fire histories indicate that the research station experienced less intensive historical fire and pre-Columbian disturbance than the lake district. Dated charcoal particles indicated that while soil depth could not be used to predict fire age, fragments below 20 cm depth were generally older than 500 years. Frequent fires have not occurred in either region during the last 1000 years, but fire events in both regions were significantly synchronous from 1000 to 4000 cal. yr BP. The sampling design and methods that provide an ecologically and statistically valid avenue for comparing fire history characteristics between regions can be modified to suit other ecosystems. The results presented here establish confidence that the patterns and processes of the lowland tropical rainforests studied at Los Amigos are not affected by intense or recurrent historical fires. These data also suggest that forests of Madre de Dios, Peru are not post-successional remnants of a ‘cultural parkland’, as suggested by some Amazonian archeologists.
id: 2307

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J. P.; Cherrier, J.; Wilson, R. M.; Sarkodee-Adoo, J.; Bosman, S.; Mickle, A.; Graham, W. M. (ENVIRONMENTAL RESEARCH LETTERS, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (delta C-13) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5-7 parts per thousand in stable carbon isotope (delta C-13) space, while in radiocarbon (Delta C-14) space these two potential sources are separated by more than 1000 parts per thousand. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Delta C-14 and delta C-13 in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or Sigma CO2) to constrain surface production values. On average, plankton values were depleted in C-14 relative to surface DIC, and we found a significant linear correlation between Delta C-14 and delta C-13 in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.
Keywords: carbon isotope; Gulf oil spill; methane; petroleum hydrocarbon; radiocarbon

Radiocarbon evidence that carbon from the Deepwater Horizon spill entered the planktonic food web of the Gulf of Mexico - Chanton, J P; Cherrier, J; Wilson, R M; Sarkodee-Adoo, J; Bosman, S; Mickle, A; Graham, W M (Environmental Research Letters, 2012)
The Deepwater Horizon (Macondo) oil spill released large volumes of oil and gas of distinct carbon isotopic composition to the northern Gulf of Mexico, allowing Graham et al (2010 Environ. Res. Lett. 5 045301) to use stable carbon isotopes (δ13C) to infer the introduction of spilled oil into the planktonic food web. Surface ocean organic production and measured oil are separated by 5–7‰ in stable carbon isotope (δ13C) space, while in radiocarbon (Δ14C) space these two potential sources are separated by more than 1000‰. Thus radiocarbon isotopes provide a more sensitive tracer by which to infer possible introduction of Macondo oil into the food web. We measured Δ14C and δ13C in plankton collected from within 100 km of the spill site as well as in coastal and offshore DIC (dissolved inorganic carbon or ΣCO2) to constrain surface production values. On average, plankton values were depleted in 14C relative to surface DIC, and we found a significant linear correlation between Δ14C and δ13C in plankton. Cumulatively, these results are consistent with the hypothesis that carbon released from the Deepwater Horizon spill contributed to the offshore planktonic food web. Our results support the findings of Graham et al (2010 Environ. Res. Lett. 5 045301), but we infer that methane input may be important.

Refining the model of barrier island formation along a paraglacial coast in the Gulf of Maine - Hein, Christopher J.; FitzGerald, Duncan M.; Carruthers, Emily A.; Stone, Byron D.; Barnhardt, Walter A.; Gontz, Allen M. (Marine Geology, 2012)
Details of the internal architecture and local geochronology of Plum Island, the longest barrier in the Gulf of Maine, have refined our understanding of barrier island formation in paraglacial settings. Ground-penetrating radar and shallow-seismic profiles coupled with sediment cores and radiocarbon dates provide an 8000-year evolutionary history of this barrier system in response to changes in sediment sources and supply rates as well as variability in the rate of sea-level change. The barrier sequence overlies tills of Wisconsinan and Illinoian glaciations as well as late Pleistocene glaciomarine clay deposited during the post-glacial sea-level highstand at approximately 17 ka. Holocene sediment began accumulating at the site of Plum Island at 7–8 ka, in the form of coarse fluvial channel-lag deposits related to the 50-m wide erosional channel of the Parker River that carved into underlying glaciomarine deposits during a lower stand of sea level. Plum Island had first developed in its modern location by ca. 3.6 ka through onshore migration and vertical accretion of reworked regressive and lowstand deposits. The prevalence of southerly, seaward-dipping layers indicates that greater than 60% of the barrier lithosome developed in its modern location through southerly spit progradation, consistent with a dominantly longshore transport system driven by northeast storms. Thinner sequences of northerly, landward-dipping clinoforms represent the northern recurve of the prograding spit. A 5–6-m-thick inlet-fill sequence was identified overlying the lower stand fluvial deposit; its stratigraphy captures events of channel migration, ebb-delta breaching, onshore bar migration, channel shoaling and inlet infilling associated with the migration and eventual closure of the inlet. This inlet had a maximum cross-sectional area of 2800 m2 and was active around 3.5–3.6 ka. Discovery of this inlet suggests that the tidal prism was once larger than at present. Bay infilling, driven by the import of sediment into the backbarrier environment through tidal inlets, as well as minor sediment contribution from local rivers, led to a vast reduction in the bay tidal prism. This study demonstrates that, prior to about 3 ka, Plum Island and its associated marshes, tidal flats, and inlets were in a paraglacial environment; that is, their main source of sediment was derived from the erosion and reworking of glaciogenic deposits. Since that time, Plum Island has been in a state of dynamic equilibrium with its non-glacial sediment sources and therefore can be largely considered to be in a stable, “post-paraglacial” state. This study is furthermore the first in the Gulf of Maine to show that spit accretion and inlet processes were the dominant mechanisms in barrier-island formation and thus serves as a foundation for future investigations of barrier development in response to backbarrier infilling.
Keywords: barrier-island formation; ground-penetrating radar; inlet processes; inlet-fill sequence; paraglacial; spit accretion

Significance of active growth faulting on marsh accretion processes in the lower Pearl River, Louisiana - Yeager, Kevin M.; Brunner, Charlotte A.; Kulp, Mark A.; Fischer, Dane; Feagin, Rusty A.; Schindler, Kimberly J.; Prouhet, Jeremiah; Bera, Gopal (Geomorphology, 2012)
Neotectonic processes influence marsh accretion in the lower Pearl River valley. Active growth faults are suggested by groupings of ponded river channel sections, transverse and linear river channel sections, and down- and across-valley contrasts in channel sinuosity. Seismic profiles identified several likely, fault-induced structural anomalies, two of which parallel the axes of surface distributary networks. Lithostratigraphy and biostratigraphy of six cores from across a suspected fault in the West Middle River, combined with 14C-based age control, yielded evidence of vertical offsets, indicating that this river section is on the plane of a growth fault. These data were used to estimate fault slip rates over two time intervals, 1.2 mm/y over the last 1300 yr, and 0.2 mm yr− 1 over the last 3700 yr, and delineated a sinusoidal pattern of deformation moving distally from the fault, which we interpret as resulting from fault-propagation folding. Higher rates of sediment accumulation (of the order of cm yr− 1 from 210Pbxs and 137Cs activity data) on the down-thrown side are consistent with sedimentary response to increased accommodation space, and mass-based sediment accumulation rates (g cm− 2 yr− 1) exhibit a pattern inverse of that shown by fault-driven sinusoidal deformation. We contend that near-surface growth faults are critically important to driving accretion rates and marsh response to sea-level rise.
id: 2294

The Southern Ocean's Role in Carbon Exchange During the Last Deglaciation - Burke, Andrea; Robinson, Laura F. (SCIENCE, 2012)
Changes in the upwelling and degassing of carbon from the Southern Ocean form one of the leading hypotheses for the cause of glacial-interglacial changes in atmospheric carbon dioxide. We present a 25,000-year-long Southern Ocean radiocarbon record reconstructed from deep-sea corals, which shows radiocarbon-depleted waters during the glacial period and through the early deglaciation. This depletion and associated deep stratification disappeared by similar to 14.6 ka (thousand years ago), consistent with the transfer of carbon from the deep ocean to the surface ocean and atmosphere via a Southern Ocean ventilation event. Given this evidence for carbon exchange in the Southern Ocean, we show that existing deep-ocean radiocarbon records from the glacial period are sufficiently depleted to explain the similar to 190 per mil drop in atmospheric radiocarbon between similar to 17 and 14.5 ka.

The synchronization of palaeoclimatic events in the North Atlantic region during Greenland Stadial 3 (ca 27.5 to 23.3 kyr b2k) - Austin, W. E. N.; Hibbert, F. D.; Rasmussen, S. O.; Peters, C.; Abbott, P. M.; Bryant, C. L. (Quaternary Science Reviews, 2012)
Two high resolution marine sediment cores located 83 km apart in the NE Atlantic have been studied: MD95-2006 (Barra Fan; 57°01.82 N, 10°03.48 W; 2120 m water depth) and MD04-2822 (Rockall Trough; 56°50.54 N, 11°22.96 W; 2344 m water depth). The records are anchored to the NGRIP ice core stratigraphy and GICC05 chronology by the presence of geochemically characterized Fugloyarbanki tephra and further tested by radiocarbon age control. Replicated sea surface temperature (SST) records show evidence for an abrupt and short-lived warming within Greenland Stadial (GS)-3, to which we tentatively assign an age of ca 25.6–24.8 kyr GICC05 b2k. Based on these and another marine palaeoclimate record (LINK17) from the Faroe-Shetland Channel, we propose a new three-fold event stratigraphy for GS-3 within the North East Atlantic region. The recognition of this warming event within GS-3 in NE Atlantic SST records demonstrates that such events may not readily be identified within the coldest stadials of the Greenland ice cores, highlights the need for carefully constructed event stratigraphies (independently tested by the use of tephra isochrones and radiocarbon) and illustrates pervasive millennial-scale climate variability of the North Atlantic region (Dansgaard-Oeschger (D/O) events) is deeply embedded in the dynamics of Atlantic Meridional Overturning Circulation (AMOC).
id: 2145

A two-dimensional, heart-cutting preparative gas chromatograph facilitates highly resolved single-compound isolations with utility towards compound-specific natural abundance radiocarbon (14C) analyses - Ball, Gregory Ian; Xu, Li; McNichol, Ann P.; Aluwihare, Lihini I. (Journal of Chromatography A, 2012)
Motivated by the need to develop clean, high purity preparative enrichments of individual compounds for micro-scale compound-specific natural abundance isotope and radiocarbon (14C) analyses, we describe a new, two-dimensional, heart-cutting, low-bleed, three-oven, single GC preparative system, demonstrate its resolving capabilities as applied to a typically complex environmental sample matrix, and investigate the robustness with which it preserves the authigenic 13C/12C and 14C/12C ratios of individual compounds it targets for preparative enrichment. The system is comprised of a programmable temperature vaporizing (PTV) inlet, a single GC oven, two modular, door-mounted, resistively heated low thermal mass (LTM) columns, a preparative fraction collector (PFC), and a Deans pneumatic switching device which facilitates heart-cutting between the system's 1° and 2° chromatographic dimensions. Further, the system's inlet and trapping parameters are optimized for the efficient preparative enrichment of the methyl ether and ester derivatives of the lignin phenol compound class. The lignin phenols include such compounds as the vanillyl and syringyl aldehydes, ethanones, and acids and are unrivaled biomarkers of terrestrial organic matter, some of which are also important components of fragrances and flavors. Using this suite of compounds, the suitability of this augmented preparative capillary GC (PCGC) system was investigated for micro-scale compound-specific (CS) stable isotope and natural abundance radiocarbon analyses (RA). Analysis of a >300 injection enrichment scheme reveals the instrument to fractionate 13C in predictable ways and to preserve the authigenic Δ14C of compounds it targets for preparative enrichment to within 6.7 ± 5.0‰, demonstrating the promising new utility of such systems towards micro-scale CSRA investigations for which clean and high resolution separation techniques are prerequisite.
id: 2152

Using the N/C ratio to correct bulk radiocarbon ages from lake sediments: Insights from Chilean Patagonia - Bertrand, Sébastien; Araneda, Alberto; Vargas, Patricia; Jana, Patricia; Fagel, Nathalie; Urrutia, Roberto (Quaternary Geochronology, 2012)
The offset between AMS radiocarbon ages obtained on bulk lake sediments and the true age of deposition was evaluated at four sites in Northern Chilean Patagonia. Our results show that the bulk radiocarbon ages are systematically older by 300 to 1100 years. In this region free of carbonate and carbonaceous rocks, we argue that this difference results from variable inputs of terrestrial organic carbon from the Holocene soils that cover the lake watersheds. For the four studied lakes, the age offset is clearly related to the fraction of terrestrial carbon preserved in the lake sediments, which was estimated using the N/C ratio of the bulk organic matter. We propose that N/C measurements can be used to significantly improve chronologies based on radiocarbon dating of bulk lake sediments.
id: 2296

Bomb-produced radiocarbon validation of growth-increment crossdating allows marine paleoclimate reconstruction - Kastelle, Craig R.; Helser, Thomas E.; Black, Bryan A.; Stuckey, Matthew J.; C. Gillespie, Darlene; McArthur, Judy; Little, Diana; D. Charles, Karen; Khan, Reziah S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The bivalve Pacific geoduck (Panopea generosa) has been used in the eastern North Pacific Ocean to create proxies for environmental factors such as temperature and oceanographic conditions. This type of research depends upon accurate age determination of Pacific geoducks, which historically was based on shell growth-increment counts. A recent study comparing age estimates generated by the dendrochronology (tree-ring science) procedure of crossdating to those estimated from growth-increment counts found a significant difference between the methods for geoduck older than 30 years. Compared to the traditional age determination method of counting growth increments, the crossdating method estimates a greater longevity in this species, with some individuals living in excess of 150 years. In the present study, the accuracy of each method was independently assessed using bomb-produced radiocarbon (14C) techniques. Specimens whose birth years were estimated to be within the era of the bomb-produced marine 14C increase and where the differences between ages estimated by the two methods were greatest were selected for 14C analysis. The difference between age estimates from traditional growth-increment counts and those from crossdating was evaluated using their respective 14C chronologies in comparisons to a reference chronology as a standard. The comparisons relied on Bayesian nonlinear models using Markov Chain Monte Carlo simulation. This method of analysis showed that with a 50% probability geoducks were aged correctly when using the crossdating method, compared to the growth increment counts which had a 50% probability of underestimating the age by 4 years. Therefore, the crossdated age estimates were found to be more accurate than increment counts. Furthermore, these results provide new confidence in using Pacific geoduck biochronologies for paleoclimate and paleoenvironmental reconstruction.
id: 2167

Carbonate veins trace seawater circulation during exhumation and uplift of mantle rock: Results from ODP Leg 209 - Bach, Wolfgang; Rosner, Martin; Jöns, Niels; Rausch, Svenja; Robinson, Laura F.; Paulick, Holger; Erzinger, Jörg (Earth and Planetary Science Letters, 2011)
Carbonate veins hosted in ultramafic basement drilled at two sites in the Mid Atlantic Ridge 15°N area record two different stages of fluid-basement interaction. A first generation of carbonate veins consists of calcite and dolomite that formed syn- to postkinematically in tremolite–chlorite schists and serpentine schists that represent gently dipping large-offset faults. These veins formed at temperatures between 90 and 170 °C (oxygen isotope thermometry) and from fluids that show intense exchange of Sr and Li with the basement (87Sr/86Sr = 0.70387 to 0.70641, δ7LiL-SVEC = + 3.3 to + 8.6‰). Carbon isotopic compositions range to high δ13CPDB values (+ 8.7‰), indicating that methanogenesis took place at depth. The Sr–Li–C isotopic composition suggests temperatures of fluid-rock interaction that are much higher (T > 350–400 °C) than the temperatures of vein mineral precipitation inferred from oxygen isotopes. A possible explanation for this discrepancy is that fluids cooled conductively during upflow within the presumed detachment fault. Aragonite veins were formed during the last 130 kyrs at low-temperatures within the uplifted serpentinized peridotites. Chemical and isotopic data suggest that the aragonites precipitated from cold seawater, which underwent overall little exchange with the basement. Oxygen isotope compositions indicate an increase in formation temperature of the veins by 8–12 °C within the uppermost ~ 80 m of the subseafloor. This increase corresponds to a high regional geothermal gradient of 100–150 °C/km, characteristic of young lithosphere undergoing rapid uplift.
id: 2162

The Deglacial Evolution of North Atlantic Deep Convection - Thornalley, David J. R.; Barker, Stephen; Broecker, Wallace S.; Elderfield, Henry; McCave, I. Nick (SCIENCE, 2011)
Deepwater formation in the North Atlantic by open-ocean convection is an essential component of the overturning circulation of the Atlantic Ocean, which helps regulate global climate. We use water-column radiocarbon reconstructions to examine changes in northeast Atlantic convection since the Last Glacial Maximum. During cold intervals, we infer a reduction in open-ocean convection and an associated incursion of an extremely radiocarbon (C-14)-depleted water mass, interpreted to be Antarctic Intermediate Water. Comparing the timing of deep convection changes in the northeast and northwest Atlantic, we suggest that, despite a strong control on Greenland temperature by northeast Atlantic convection, reduced open-ocean convection in both the northwest and northeast Atlantic is necessary to account for contemporaneous perturbations in atmospheric circulation.

A depositional history of particulate organic carbon in a floodplain lake from the lower Ob’ River, Siberia - Dickens, Angela F.; Baldock, Jeff; Kenna, Timothy C.; Eglinton, Timothy I. (Geochimica et Cosmochimica Acta, 2011)
Northern, high latitude soils have stored vast amounts of organic carbon (OC) in permafrost and peats for many millennia, however, climate change may mobilize and release this particulate OC (POC) to arctic rivers. Deltaic and floodplain lakes that receive fluvial sediments, primarily during the spring freshet, may provide records of such changes in riverine POC. Here, we examine properties of OC in a sediment core from a lake in the lower floodplain of the Ob’ River, west Siberia, to determine how the properties of OC deposited in this lake varied over many decades and to evaluate use of this sedimentary OC as a recorder of riverine POC load and properties. The core predates the most recent, dramatic changes in arctic climate and hence may serve as a benchmark against which to contrast future variations in fluvial POC discharge. Elemental, stable carbon and radiocarbon isotopic analyses, along with nuclear magnetic resonance (NMR) spectroscopy and molecular-level information (lignin phenol composition), indicate two major sources of OC to most of the sediments in this lake: plant-derived OC and algal-derived OC. However, a mixing model indicates that the nature and 14C content of these two sources change with depth in the sediment, resulting in three distinct layers: surface horizons, a “high-OC” layer and “mixing” horizons found above and below the high-OC layer. The plant-derived component is significantly aged throughout the core (14C ages of 1300–3900 years) and appears to derive from primarily local, tundra sources, whereas the algal component is modern. Our analysis suggests that the usual mode of OC deposition, as exemplified by the “mixing” and surface horizons, involved mixing of varying amounts of new algal production (35–65%) with aged permafrost- or peat-derived OC. This deposition was interrupted by an event, such as the collapse of a riverbank, which laid down the compositionally distinct “high-OC” layer in which plant-derived OC mixes with aged mineral-soil-derived OC without clear input from algae. The relative amounts of the plant and algal components in the lake sediments appear to be controlled primarily by local hydrological conditions rather than by river-wide processes, suggesting that comparison of sediment records from multiple lakes within a floodplain will be important to assess changes in POC export by arctic rivers. However, the flux and nature of the higher plant-derived OC may carry important information on the sources and dynamics of OC stored within the drainage basin.
id: 2172

Design and reality: Continuous-flow accelerator mass spectrometry (CFAMS) - von Reden, Karl F.; Roberts, Mark L.; McIntyre, Cameron P.; Burton, Joshua R. (Proceedings of the 10th European Conference on Accelerators in Applied Research and Technology (ECAART10), 2011)
In 2007 we published [1] the design of a novel accelerator mass spectrometry (AMS) system capable of analyzing gaseous samples injected continuously into a microwave plasma gas ion source. Obvious advantages of such a system are drastically reduced processing times and avoidance of potentially contaminating chemical preparation steps. Another paper in these proceedings will present the progress with the development of the microwave gas ion source that has since been built and tested at the National Ocean Sciences AMS Facility in Woods Hole [2]. In this paper we will review the original design and present updates, reflecting our recent encouraging experience with the system. A simple summary: large acceptance ion beam optics design is beneficial to accelerator mass spectrometry in general, but essential to AMS with plasma gas ion sources.
id: 2157

The detailed palaeoecology of a mid-Wisconsinan interstadial (ca. 32 000 (14)C a BP) vegetation surface from interior Alaska - Wooller, Matthew J.; Zazula, Grant D.; Blinnikov, Misha; Gaglioti, Benjamin V.; Bigelow, Nancy H.; Sanborn, Paul; Kuzmina, Svetlana; La Farge, Catherine (Journal of Quaternary Science, 2011)
We present a multi-proxy reconstruction from a well-preserved vegetation surface (ca. 32 000 (14)C a BP) from the Fox Permafrost tunnel near Fairbanks, Alaska. A thick litter layer of plant material on the vegetation surface is consistent with the vegetation lacking evidence of disturbance. Plant macrofossils and graminoid cuticle analysis show the presence of a graminoid assemblage consistent with phytolith data. The pollen data indicate that trees were not local to the site and that Artemisia sp. was present in the region. The insect and bryophyte reconstructions are consistent with the vascular plant reconstruction, indicating the site was at least periodically wet. delta(13)C values from the graminoids present show a large range encompassing both the wet and dry range displayed by modern graminoids in Alaska. Sequential delta(13)C analyses conducted along the length of leaves attached to the vegetation surface indicate a seasonal shift towards relatively higher water use efficiency. The lower water use efficiency earlier in the growing season may have stemmed from the use of winter season meltwater by plants at the site - a scenario consistent with the site's cryostratigraphy. Our multi-proxy reconstruction contributes to the limited palaeoecological data available for graminoid-dominated vegetation present in Eastern Beringia and particularly the interior of Alaska during the mid-Wisconsinan interstadial. Copyright (C) 2011 John Wiley & Sons, Ltd.
id: 2131; PT: J; TC: 1; UT: WOS:000296091300010

Distribution and significance of heavy-mineral concentrations along the southeast Baltic Sea coast - Pupienis, D.; Buynevich, I. V.; Bitinas, A. (Journal of Coastal Research, 2011)
Heavy mineral concentrations (HMCs) in coastal sands are important from both scientific and practical standpoints. On one hand, they may serve as local sources of iron and other economically important metals, and on the other they are good indicators of hydro-meteorological and sedimentological conditions along the coast. A variety of HMC types have been documented in beach, foredune, and relict dune environments of Lithuania. The study region is located along the Curonian Spit (Nida) and mainland coast (Būtingė). The ocean beach sites range from 25 to 35 m in width and are backed by 5-10 m-high foredunes. The Great Dune Ridge on the Curonian Spit consists of relict (mid-late Holocene) dunes which are the highest coastal dunes in Northern Europe (more than 60 m above sea level). The prevailing westerly winds attain speeds of 4.2 m/s in the summer and 5.5 m/s in autumn and winter. Along the southeast Baltic Sea coast, quartz and feldspars-rich sands contain variable amounts (1-8%) of heavy minerals, such as garnet, rutile, zircon, magnetite, ilmenite, hornblende, and other accessory minerals. On the beach, HMCs typically range in thickness from 0.1 to more than 3.0 cm and represent increased wave and run-up regime. Based on previous studies of coastal morphodynamics and field observations during 2005, 2006, 2008 and 2010 enriched horizons near the foot of the foredune are the result of storm reworking and subsequent aeolian deflation. Similar process concentrates almandine garnet and magnetite along the Curonian Lagoon shoreline, on the opposite side from the Nida beach site. Based on their occurrence in the Great Dune Ridge, we suggest that buried HMCs likely represent periods of increased wind activity (storminess). Due to their relatively high fraction of heavy minerals, HMCs have substantially higher magnetic susceptibility (MS) values than background quartz-rich sands and, where well developed, they can be used for spatial correlation of subsurface horizons. Therefore, the MS method was used as a tool for cataloguing the properties of HMCs in the field and in the laboratory. For documenting lithological differences between exposed heavy-mineral concentrations and background quartz-rich sands, this study focused on coastal environments with different sedimentary regimes: 1) surface profile and shallow trenches through the upper berm at Bating (wave run-up setting along the mainland shoreline); 2) a 40-m-long shore-normal beach profile at Nida on the Baltic Sea shoreline of the Curonian Spit, (mixed wave/aeolian conditions) and 3) a short surface profile along a lagoon beach at the base of the Paranidis Dune (the landward side of the spit). The 2008 and 2010 data were compared to previous studies of the HMCs in relict dunes (exclusively aeolian setting). The spatial and temporal distribution of HMCs in different sedimentary environments is a function of: 1) the initial heavy-mineral content prior to high-energy events and 2) hydro-meteorological and sedimentary conditions during the events responsible for removal of lighter minerals and HMC formation as a lag deposit. The thickness, degree of concentration, and rhythmicity of HMC horizons offer opportunities for quantifying the periodicity and intensity of hydrodynamic processes along sandy coasts.
id: 2126

Distribution of radiocarbon ages of soil organic matter by thermal fractionation - Plante, A. F.; Beaupre, S. R.; Fernandez, J. M.; Roberts, M.; Baisden, W. T. (American Geophysical Union, Washington, DC, United States (USA), 2011)
Radiocarbon analysis has become an important tool in quantifying the dynamics of soil organic matter within the terrestrial carbon cycle (Trumbore 2009). Measuring radiocarbon concentrations in bulk soil samples provides only the mean age or residence time of the associated organic matter, but it is well recognized that representing soil organic matter as a single, homogeneous pool is inadequate. Significant effort has gone into separating soil organic matter into pools with different intrinsic turnover rates (i.e., radiocarbon concentrations), but the success of these separation methods has been mixed. Using thermal analysis techniques to characterize soil organic matter is rooted in the hypothesized link between the thermal and biogeochemical stability of the organic matter (Plante et al. 2011). Two grassland topsoil samples under contrasting land uses (native vegetation and long-term cultivation) were sampled in 2005 and submitted for radiocarbon analysis. Results of bulk (super 14) C showed a significant shift in radiocarbon age (94 to 79 pMC in the soil from Indian Head, Saskatchewan; 104 to 89 pMC in the soil from Akron, Colorado), attributable to the depletion of labile organic matter during long-term cultivation. Thermogravimetry and evolved gas analysis of these soil samples also showed distinct patterns in mass loss and CO (sub 2) release during thermal analysis, suggesting significant changes in organic matter composition. Four to five "fractions" associated with different CO (sub 2) -evolution regions have been identified and will be analyzed for radiocarbon via NOSAMS's established "dirt burner" method (Rosenheim et al. 2008), consisting of the recently developed discrete CO (sub 2) fraction collector interface between NOSAMS's dirt burner and microwave gas ion source (GIS) continuous flow AMS system (CFAMS). The research question is: Do the differing patterns in CO (sub 2) release during thermal analysis reflect organic matter of different ages Our working hypothesis is that thermally labile soil organic matter (combusting at low temperatures) will consist of younger carbon than thermally resistant organic matter. References: Plante, A. F., J. M. Fernandez, M. L. Haddix, and R. T. Conant. 2011. Biological, chemical and thermal indices of soil organic matter stability in four grassland soils. Soil Biol. Biochem. 43: 1051-1058. Rosenheim, B. E., M. B. Day, E. Domack, H. Schrum, A. Benthien, and J. M. Hayes. 2008. Antarctic sediment chronology by programmed-temperature pyrolysis: Methodology and data treatment. Geochemistry Geophysics Geosystems 9: 1-16. Trumbore, S. 2009. Radiocarbon and soil carbon dynamics. Annu Rev Earth Pl Sc 37: 47-66.
id: 2207; Source type: scholarlyjournals; Object type: Article; Object type: Conference Paper; Copyright: GeoRef in Process, Copyright 2012, American Geosciences Institute. After editing and indexing, this record will be added to Georef. Reference includes data supplied by, and/or abstract, Copyright, American Geophysical Union, Washington, DC, United States; CSAUnique: 638157-114; AccNum: 638157-114; CODEN: #07548

Evolution of a Pharaonic harbor on the Red Sea: Implications for coastal response to changes in sea level and climate - Hein, Christopher J.; FitzGerald, Duncan M.; Milne, Glenn A.; Bard, Kathryn; Fattovich, Rodolfo (GEOLOGY, 2011)
The evolution of coastal systems during the Holocene resulted from complex interactions and temporal shifts in the relative contribution of sea-level changes, climate change, and sedimentary processes. Along the Red Sea Coast, a 0.5-2 m highstand of sea level at 5 ka can be directly attributed to far-field effects resulting from the reduction in land ice following the last glacial maximum. At the ancient Egyptian harbor of Mersa/Wadi Gawasis, the site of the world's oldest archaeological evidence of long-distance seafaring, stratigraphic and geomorphologic evidence has been identified for this highstand. Here, wadi sediment input, enhanced by a period of wetter climate of the African Humid Period (early to mid-Holocene), forced the closure of coastal embayments, despite ongoing, relatively rapid sea-level rise. A stable, shallow bay persisted at Mersa/Wadi Gawasis as a result of coincidental aridization and a highstand of sea level during the mid-Holocene. This bay served as the primary harbor for ancient Egyptian trade along the Red Sea coast. During the late Holocene, shoreline progradation was dominated by sea-level fall, driven by isostatic processes. These results demonstrate the interplay of various global (sea level), regional (climate, sea level), and local (sedimentation, bathymetry) controls on the coastal evolution of the Red Sea and how these controls dictated the response of a complex civilization. Furthermore, they highlight the crucial role played by sedimentation in governing coastal response to changing sea levels.

Fire history and human activities during the last 3300 cal yr BP in Spain's Central Pyrenees: The case of the Estany de Burg - Bal, Marie-Claude; Pelachs, Albert; Perez-Obiol, Ramon; Julia, Ramon; Cunill, Raquel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The study of macroscopic charcoal particles from peat bogs has led to a better understanding of climate, vegetation and fire history, and human impacts. To determine the relationship between human activities and the role of fire events in vegetation change during the last 3300 cal yr BP, we present the results of a multi-proxy approach based on the analysis of sediment characteristics, sedimentary charcoal, organic matter and pollen, as well as historical sources. This multi-proxy research permits high resolution palaeoenvironmental and fire history reconstruction of a mountain area located in the southern central Pyrenees (Spain). In the Pyrenees, fire is typically attributed to human activities since the beginning of the Bronze Age and may be correlated with slash-and-burn cultivation, metallurgy and pasturing activities. The data indicate a good linkage between high fire signals and Poaceae and Cerealia pollen, which reveals the impact of agro-pastoral practices. This study also shows two periods, 2900–2650 cal yr BP and 1850–1550 cal yr BP, for which higher frequencies of fire occurred, suggested by high arboreal pollen (AP) concentrations, and confirming the need for arboreal biomass to sustain fires. From the beginning of the Middle Ages, it seems that a change occurred in the anthropogenic use of fire, from a tool for agro-pastoral forest clearance to a means of maintaining open spaces.
id: 2196

Geological legacy of storm erosion along a high-energy indented coastline: northern Santa Catarina, Brazil - Buynevich, I. V.; Klein, A. H. F.; FitzGerald, D. M.; Cleary, W. J.; Hein, C.; Veiga, F. A.; Angulo, R. J.; Asp, N. E.; Petermann, R. (Journal of Coastal Research, 2011)
Along moderate to high-energy sandy coasts of the world, periods of accretion are often punctuated by episodes of erosion and retreat. However documenting the legacy of such events in sand-dominated sequences remains a challenge. The present-day moderate-relief coastlines of Camboriú Peninsula (CP) and the adjacent Navegantes coastal plain in Santa Catarina, Brazil, exhibit a variety of geological features related to recent intense storms, such as the Santa Catarina cyclone of record (March 2004) and subsequent events. These systems offer an opportunity to assess the use of modern indicators of storm erosion as a guide to reconstructing their counterparts from the sedimentary record. The 0.5-2.0-km-long, headland-segmented, coarse-grained, reflective beaches of the Camboriú Peninsula contrast with a 10-km-long, fine-grained, dissipative beach of the Navegantes plain. Morphological indicators of erosion include steep dune and berm scarps, as well as ephemeral washout channels produced by rainfall-induced runoff. Where modified by subsequent deposition, these features can still be identified by their diagnostic reflection geometries and variable-angle truncations (disconformities) in highresolution ground-penetrating radar (GPR) images. In addition to morphological indicators of erosion, coastal sedimentary sequences contain distinct lithological anomalies. Heavy-mineral concentrations (HMCs) are easily identifiable in sediment cores and trenches and produce strong reflections on GPR images. Along Estaleiro Beach (CP), a buried disconformity was identified in GPR images beneath a road, approximately 25 m landward of the November 2004 storm scarp. Its geometry is similar to the recent scarp and its strong geophysical signal return is due to a magnetite-enriched horizon at a depth of 2.6 m. At the Navegantes strandplain, patchy thin layers enriched in fine-grained heavy minerals are common on a gently sloping intertidal beach and near the base of foredunes. Moreover, in the landward portion of the plain that developed during the past 2,000 years, the presence of truncated tangential-oblique reflections in GPR records and HMCs reaching 10-30 cm in thickness indicates past reworking of beach and dune sediments by a series of intense erosional episodes. Low-field magnetic susceptibility measurements of vibracores indicate values from thick HMC layers exceeding 1,000 (*10-5 SI) in contrast to 0−15 (*10-5 SI) for background quartz-rich sands. Given the relatively constant background fraction of heavy minerals in beach sands, the thickness and degree of concentration in HMCs can be used as proxies for the relative impact of high-energy events, including their duration and magnitude. Despite the apparent low preservation potential of these features on high-energy coasts, post-storm accretion and rapid progradation increase their chances of being removed from wave action.
id: 2125

Geological slip rates along the North Anatolian Fault in the Marmara region - Gasperini, Luca; Polonia, Alina; Çağatay, M. Namik; Bortoluzzi, Giovanni; Ferrante, Valentina (Tectonics, 2011)
Reliable piercing points on both sides of the Sea of Marmara enabled us to obtain an estimate of the slip-rate over time scales of 10-15 ka on different fault strands of the North Anatolian Fault (NAF) system. We analyzed geomorphic features in the gulfs of Izmit, Gemlik (Sea of Marmara) and Saros (NE Aegean Sea), which were passively displaced by the NAF strands after their abandonment related to the post-glacial sea level rise. Results for the main northern strand, consistently similar on both sides of the Marmara pull-apart, are in the order of 10 mm/yr, about one half of that expected from geodetic measurements and accepted plate-tectonic models. In the southern branch of the NAF, the estimated rate of similar to 4 mm/yr is only slightly higher than that given by geodetic models. Our findings have implications for both neo-tectonic reconstructions of the submerged portion of the NAF system, and fault interactions and seismic hazard estimates in the Marmara region. They suggest that, either the total Anatolia/Eurasia plate motion is more diffuse than previously reported, or geodetic data are not representative of the geological time-scale deformations. Moreover, they suggest that a significant amount of stress is accommodated along the southern strand of the NAF system, on which the last large (M approximate to 7) earthquakes dates back to 1419, 1855 and 1863 AD.
id: 2112; PT: J; TC: 0; J9: TECTONICS; UT: WOS:000296619700001

Geological Society of America Special PapersGeology and Geoarchaeology of the Black Sea Region: Beyond the Flood HypothesisPontic-Baltic pathways for invasive aquatic species: Geoarchaeological implications - Buynevich, Ilya V.; šytė, Aldona; Bitinas, Albertas; Olenin, Sergej; žeika, Jonas; šius, Rimantas (Geological Society of America, 2011)
An accurate chronology for the exchange of aquatic species between water basins is important for paleoenvironmental reconstruction on both regional and continental scales. During the early Holocene, the range of zebra mussels, Dreissena polymorpha, was limited to the Black, Azov, Caspian, and Aral Seas, as well as the estuaries and lower and middle reaches of the Pontic-Caspian rivers. We present new fi ndings that challenge the currently held view that this species migrated into the Baltic Sea watershed during the early 1800s through the canals joining the tributaries of rivers that drain into the Black and Baltic Sea basins. Geological investigations along the southeast Baltic Sea coast (Curonian and Vistula spits and lagoons) have uncovered shells of D. polymorpha that yielded radiocarbon ages older than 1000 radiocarbon yr B.P. We propose two scenarios to explain the new radiocarbon dates for D. polymorpha. The fi rst scenario involves an anomalously large reservoir effect—as large as 600– 800 yr—however, several lines of evidence cast doubt upon the validity of such a large reservoir correction. The second scenario that might explain the old zebra mussel ages is the earlier arrival of Dreissena polymorpha into the Baltic region. Natural exchange may have been facilitated by the proximity of the tributaries draining thePontic and Baltic watersheds. Human-mediated transport is also considered in association with Viking voyages from the Baltic to the Black and Caspian Seas between A.D. 800 and 1000, and the riverine trade exchange during the Lithuanian expansion into the Pontic steppe in subsequent centuries. It is likely that both scenarios played a role, with implications for late Holocene biogeography and paleoecology of the Pontic-Caspian and Baltic basins. Pontic-Baltic pathways for invasive aquatic species: Geoarchaeological implications (PDF Download Available). Available from: https://www.researchgate.net/publication/256375044_Pontic-Baltic_pathways_for_invasive_aquatic_species_Geoarchaeological_implications [accessed May 25, 2017].

Geology and Geoarchaeology of the Black Sea Region: Beyond the Flood Hypothesis - Buynevich, I. V.; Yanko-Hombach, V. V.; Gilbert, A. S.; and Martin, R. E. (Special papers (Geological Society of America), 2011)
id: 2127

Gualas Glacier sedimentary record of climate and environmental change, Golfo Elefantes, Western Patagonia (46.5°S) - Fernandez, Rodrigo; Anderson, John; Bertrand, Sébastien; Wellner, Julia (The Holocene, 2011)
Gualas Glacier is an outlet glacier of the Northern Patagonian Icefield, one of the largest temperate ice bodies on Earth. Golfo Elefantes, the depositional basin of Gualas Glacier, has a sedimentary record that spans, with some hiatuses, at least the last ~11.3±3.0 ka. During this period the gulf remained free of ice, as suggested by the absence of proximal glacimarine sediment and till in the sedimentary section. This implies that the arcuate terminal moraines that occur along the edges of Golfo Elefantes were formed during the waning stages of the local glacial maxima (Late Pleistocene) or the early Holocene. Between ~11.3±3.0 ka and ~4.2±0.3–1.4 ka, the basin received low sediment input consisting of fine-grained sediments in the form of low concentration density currents that filled bathymetric lows. Sediment discharge increased several times in the late Holocene (~
id: 2118

Late Pleistocene paleoecology of arctic ground squirrel (Urocitellus parryii) caches and nests from Interior Alaska's mammoth steppe ecosystem, USA - Gaglioti, Benjamin V.; Barnes, Brian M.; Zazula, Grant D.; Beaudoin, Alwynne B.; Wooller, Matthew J. (Quaternary Research, 2011)
Botanical analyses of fossil and modern arctic ground squirrel (Urocitellus parryii) caches and nests have been used to reconstruct the past vegetation from some parts of Beringia, but such archives are understudied in Alaska. Five modern and four fossil samples from arctic ground squirrel caches and nests provide information on late Pleistocene vegetation in Eastern Beringia. Modern arctic ground squirrel caches from Alaska's arctic tundra were dominated by willow and grass leaves and grass seeds and bearberries, which were widespread in the local vegetation as confirmed by vegetation surveys. Late Pleistocene caches from Interior Alaska were primarily composed of steppe and dry tundra graminoid and herb seeds. Graminoid cuticle analysis of fossil leaves identified Calamagrostis canadensis, Koeleria sp. and Carex albonigra as being common in the fossil samples. Stable carbon isotopes analysis of these graminoid specimens indicated that plants using the C(3) photosynthetic pathways were present and functioning with medium to high water-use efficiency. Fossil plant taxa and environments from ground squirrel caches in Alaska are similar to other macrofossil assemblages from the Yukon Territory, which supports the existence of a widespread mammoth steppe ecosystem type in Eastern Beringia that persisted throughout much of the late Pleistocene. (C) Published by Elsevier Inc. on behalf of University of Washington.
id: 2130; PT: J; TC: 0; UT: WOS:000296672100009

Methane hydrate-bearing seeps as a source of aged dissolved organic carbon to the oceans - Pohlman, John W.; Bauer, James E.; Waite, William F.; Osburn, Christopher L.; Chapman, N. Ross (Nature Geoscience, 2011)
Marine sediments contain about 500-10,000 Gt of methane carbon(1-3), primarily in gas hydrate. This reservoir is comparable in size to the amount of organic carbon in land biota, terrestrial soils, the atmosphere and sea water combined(1,4), but it releases relatively little methane to the ocean and atmosphere(5). Sedimentary microbes convert most of the dissolved methane to carbon dioxide(6,7). Here we show that a significant additional product associated with microbial methane consumption is methane-derived dissolved organic carbon. We use Delta(14)C and delta(13)C measurements and isotopic mass-balance calculations to evaluate the contribution of methane-derived carbon to seawater dissolved organic carbon overlying gas hydrate-bearing seeps in the northeastern Pacific Ocean. We show that carbon derived from fossil methane accounts for up to 28% of the dissolved organic carbon. This methane-derived material is much older, and more depleted in (13)C, than background dissolved organic carbon. We suggest that fossil methane-derived carbon may contribute significantly to the estimated 4,000-6,000 year age of dissolved organic carbon in the deep ocean(8), and provide reduced organic matter and energy to deep-ocean microbial communities.
id: 2030; PT: J; UT: WOS:000285498600015

Paleoecology of mangroves along the Sibun River, Belize - Monacci, Natalie M.; Meier-Grünhagen, Ursula; Finney, Bruce P.; Behling, Hermann; Wooller, Matthew J. (Quaternary Research, 2011)
This study examines a sediment core (SR-63) from a mangrove ecosystem along the Sibun River in Belize, which is subject to both changes in sea-level and in the characteristics of the river's drainage basin. Radiocarbon dates from the core show a decreased sedimentation rate from ~ 6 ka to 1 cal ka BP and a marked change in lithology from primarily mangrove peat to fluvial-derived material at ~ 2.5 cal ka BP. Changes in the sedimentation rates observed in mangrove ecosystems offshore have previously been attributed to changes in relative sea-level and the rate of sea-level rise. Pollen analyses show a decreased abundance of Rhizophora (red mangrove) pollen and an increased abundance of Avicennia (black mangrove) pollen and non-mangrove pollen coeval with the decreased sedimentation rates. Elemental ratios ([N:C]a) and stable isotope analyses (δ15N and δ13C) show that changes in the composition of the organic material are also coeval with the change in lithology. The decrease in sedimentation rate at the site of core SR-63 and at offshore sites supports the idea that regional changes in hydrology occurred during the Holocene in Belize, influencing both mainland and offshore mangrove ecosystems.
id: 2099

Pontic-Baltic pathways for invasive aquatic species: geoarchaeological implications - Buynevich, I. V.; Damušytė, A.; Bitinas, A.; Olenin, S.; Mažeika, J.; Petrošius, R. (Geology and Geoarchaeology of the Black Sea Region: Beyond the Flood Hypothesis, 2011)
An accurate chronology for the exchange of aquatic species between water basins is important for paleoenvironmental reconstruction on both regional and continental scales. During the early Holocene, the range of zebra mussels, Dreissena polymorpha, was limited to the Black, Azov, Caspian, and Aral Seas, as well as the estuaries and lower and middle reaches of the Pontic-Caspian rivers. We present new findings that challenge the currently held view that this species migrated into the Baltic Sea watershed during the early 1800s through the canals joining the tributaries of rivers that drain into the Black and Baltic Sea basins. Geological investigations along the southeast Baltic Sea coast (Curonian and Vistula spits and lagoons) have uncovered shells of D. polymorpha that yielded radiocarbon ages older than 1000 radiocarbon yr B.P. We propose two scenarios to explain the new radiocarbon dates for D. polymorpha. The first scenario involves an anomalously large reservoir effect—as large as 600–800 yr—however, several lines of evidence cast doubt upon the validity of such a large reservoir correction. The second scenario that might explain the old zebra mussel ages is the earlier arrival of Dreissena polymorpha into the Baltic region. Natural exchange may have been facilitated by the proximity of the tributaries draining the Pontic and Baltic watersheds. Human-mediated transport is also considered in association with Viking voyages from the Baltic to the Black and Caspian Seas between A.D. 800 and 1000, and the riverine trade exchange during the Lithuanian expansion into the Pontic steppe in subsequent centuries. It is likely that both scenarios played a role, with implications for late Holocene biogeography and paleoecology of the Pontic-Caspian and Baltic basins.
id: 2122

Precipitation as the main driver of Neoglacial fluctuations of Gualas glacier, Northern Patagonian Icefield - Bertrand, S.; Hughen, K. A.; Lamy, F.; Stuut, J. B. W.; Torrejon, F.; Lange, C. B. (Climate of the Past, 2011)
Glaciers are frequently used as indicators of climate change. However, the link between past glacier fluctuations and climate variability is still highly debated. Here, we investigate the mid- to late-Holocene fluctuations of Gualas Glacier, one of the northernmost outlet glaciers of the Northern Patagonian Icefield, using a multi-proxy sedimentological and geochemical analysis of a 15 m long fjord sediment core from Golfo Elefantes, Chile, and historical documents from early Spanish explorers. Our results show that the core can be sub-divided in three main lithological units that were deposited under very different hydrodynamic conditions. Between 5400 and 4180 cal yr BP and after 750 cal yr BP, sedimentation in Golfo Elefantes was characterized by the rapid deposition of fine silt, most likely transported by fluvio-glacial processes. By contrast, the sediment deposited between 4130 and 850 cal yr BP is composed of poorly sorted sand that is free of shells. This interval is particularly marked by high magnetic susceptibility values and Zr concentrations, and likely reflects a major advance of Gualas glacier towards Golfo Elefantes during the Neoglaciation. Several thin silt layers observed in the upper part of the core are interpreted as secondary fluctuations of Gualas glacier during the Little Ice Age, in agreement with historical and dendrochronological data. Our interpretation of the Golfo Elefantes glaciomarine sediment record in terms of fluctuations of Gualas glacier is in excellent agreement with the glacier chronology proposed for the Southern Patagonian Icefield, which is based on terrestrial (moraine) deposits. By comparing our results with independent proxy records of precipitation and sea surface temperature, we demonstrate that the fluctuations of Gualas glacier during the last 5400 yr were mainly driven by changes in precipitation in the Andes.
id: 2119

Rapid coastal dune migration into temperate and equatorial forests: optical chronology of imaged upper slipface strata - Buynevich, I. V.; Bitinas, A.; Souza Filho, P. W. M.; Pupienis, D.; Asp, N. E.; Goble, R. J.; Kerber, L. E. (Journal of Coastal Research, 2011)
This study presents the first sets of optical dates that constrain dunefield evolution along a temperate, forested, microtidal barrier (Curonian Spit, southeast Baltic Sea, Lithuania) and a macrotidal equatorial mangrove coast (Pará State, northern Brazil). In both areas, high-resolution geophysical (georadar) images were used to map the subsurface architecture, relative chronology, and orientation of dune migration surfaces (slipfaces) and vertical accretion strata. Besides relative chronology of dune accretion, subsurface images reveal bounding (superimposition) surfaces indicative of distinct activity phases. A cross-barrier Preila transect on the Curonian Spit, served as the basis for establishing dune chronology in this historically active part of the Great Dune Ridge. Due to barrier width (> 1km) and dune height (>30 m), aeolian sand transfer, rather than overwash and breaching, has been the dominant process of landward migration for this barrier spit since mid-Holocene. OSL dating of the upper sections of buried slipfaces in shallow trenches revealed dune migration of more than 600 m between mid-1500s and late 1700s at the Preila site. These ages are consistent with historical records and the time of burial of a coastal village near the edge of a lagoon by 1797. In equatorial Brazil (Atalaia Beach), large reactivated parabolic dunes have been migrating over coastal roads and mangrove forests over at least the past 150 years. In geophysical images of a parabolic dune, numerous high-amplitude hyperbolic anomalies produced by buried trees contrast with steeply landward-dipping slipface reflections. Due to water table elevation, the lower older part of the dune sequence has been stabilized in the blowout area. Similarly, interdunal lake has partially arrested the migration of a transverse dune ridge, while the adjacent segment continues to advance onto a sparsely vegetated plain. Our preliminary data indicate that whereas the two regions differ markedly in their precipitation patterns, vegetation types, oceanographic setting, and land-use history, both experienced episodes of rapid (average: 1-2 m/year) migration of massive dunes (10-50 m high), which continues locally at the present time. Aside from their implications to coastal evolution, accurate reconstructions of dune dynamics on decadal to centennial time scales should be integrated into coastal development and management strategies.
id: 2124

Rapid Holocene coastal change revealed by high-resolution micropaleontological analysis, Pamlico Sound, North Carolina, USA - Grand Pre, Candace; Culver, Stephen J.; Mallinson, David J.; Farrell, Kathleen M.; Corbett, D. Reide; Horton, Benjamin P.; Hillier, Caroline; Riggs, Stanley R.; Snyder, Scott W.; Buzas, Martin A. (Quaternary Research, 2011)
Foraminiferal analyses of 404 contiguous samples, supported by diatom, lithologic, geochronologic and seismic data, reveal both rapid and gradual Holocene paleoenvironmental changes in an 8.21-m vibracore taken from southern Pamlico Sound, North Carolina. Data record initial flooding of a latest Pleistocene river drainage and the formation of an estuary 9000 yr ago. Estuarine conditions were punctuated by two intervals of marine influence from approximately 4100 to 3700 and 1150 to 500 cal yr BP. Foraminiferal assemblages in the muddy sand facies that accumulated during these intervals contain many well-preserved benthic foraminiferal species, which occur today in open marine settings as deep as the mid shelf, and significant numbers of well-preserved planktonic foraminifera, some typical of Gulf Stream waters. We postulate that these marine-influenced units resulted from temporary destruction of the southern Outer Banks barrier islands by hurricanes. The second increase in marine influence is coeval with increased rate of sea-level rise and a peak in Atlantic tropical cyclone activity during the Medieval Climate Anomaly. This high-resolution analysis demonstrates the range of environmental variability and the rapidity of coastal change that can result from the interplay of changing climate, sea level and geomorphology in an estuarine setting.
id: 2164

Rapid radiocarbon ((14)C) analysis of coral and carbonate samples using a continuous-flow accelerator mass spectrometry (CFAMS) system - McIntyre, Cameron P.; Roberts, Mark L.; Burton, Joshua R.; McNichol, Ann P.; Burke, Andrea; Robinson, Laura F.; von Reden, Karl F.; W. J. Jenkins (Paleoceanography, 2011)
Radiocarbon analyses of carbonate materials provide critical information for understanding the last glacial cycle, recent climate history and paleoceanography. Methods that reduce the time and cost of radiocarbon ((14)C) analysis are highly desirable for large sample sets and reconnaissance type studies. We have developed a method for rapid radiocarbon analysis of carbonates using a novel continuous-flow accelerator mass spectrometry (CFAMS) system. We analyzed a suite of deep-sea coral samples and compared the results with those obtained using a conventional AMS system. Measurement uncertainty is
id: 1915; PT: J; UT: WOS:000296649300001

Rates and Mechanisms of Mineral Carbonation in Peridotite: Natural Processes and Recipes for Enhanced, in situ CO 2 Capture and Storage - Kelemen, Peter B.; Matter, Juerg; Streit, Elisabeth E.; Rudge, John F.; Curry, William B.; Blusztajn, Jerzy (Annual Review of Earth and Planetary Sciences, 2011)
Near-surface reaction of CO2-bearing fluids with silicate minerals in peridotite and basalt forms solid carbonate minerals. Such processes form abundant veins and travertine deposits, particularly in association with tectonically exposed mantle peridotite. This is important in the global carbon cycle, in weathering, and in understanding physical-chemical interaction during retrograde metamorphism. Enhancing the rate of such reactions is a proposed method for geologic CO2 storage, and perhaps for direct capture of CO2 from near-surface fluids. We review, synthesize, and extend inferences from a variety of sources. We include data from studies on natural peridotite carbonation processes, carbonation kinetics, feedback between permeability and volume change via reaction-driven cracking, and proposed methods for enhancing the rate of natural mineral carbonation via in situ processes ("at the outcrop") rather than ex situ processes ("at the smokestack").

Resilience and reorganization: Archaeology and the historical ecology of California Channel Island sea mammals - Braje, Todd J.; Rick, Torben C.; DeLong, Robert L.; Erlandson, Jon M. (Human Impacts on Seals, Sea Lions, and Sea Otters, 2011)
id: 2068

Response of a marine-terminating Greenland outlet glacier to abrupt cooling 8200 and 9300 years ago - Young, ás E.; Briner, Jason P.; Axford, Yarrow; Csatho, Beata; Babonis, Greg S.; Rood, Dylan H.; Finkel, Robert C. (Geophysical Research Letters, 2011)
Long-term records of Greenland outlet-glacier change extending beyond the satellite era can inform future predictions of Greenland Ice Sheet behavior. Of particular relevance is elucidating the Greenland Ice Sheet's response to decadal- and centennial-scale climate change. Here, we reconstruct the early Holocene history of Jakobshavn Isbræ, Greenland's largest outlet glacier, using 10Be surface exposure ages and 14C-dated lake sediments. Our chronology of ice-margin change demonstrates that Jakobshavn Isbræ advanced to deposit moraines in response to abrupt cooling recorded in central Greenland ice cores ca. 8,200 and 9,300 years ago. While the rapid, dynamically aided retreat of many Greenland outlet glaciers in response to warming is well documented, these results indicate that marine-terminating outlet glaciers are also able to respond quickly to cooling. We suggest that short lag times of high ice flux margins enable a greater magnitude response of marine-terminating outlets to abrupt climate change compared to their land-terminating counterparts.

Response of Jakobshavn Isbrae, Greenland, to Holocene climate change - Young, N. E.; Briner, J. P.; Stewart, H. A. M.; Axford, Y.; Csatho, B.; Rood, D. H.; Finkel, R. C. (Geology, 2011)
Rapid fluctuations in the velocity of Greenland Ice Sheet (GIS) outlet glaciers over the past decade have made it difficult to extrapolate ice-sheet change into the future. This significant short-term variability highlights the need for geologic records of preinstrumental GIS margin fluctuations in order to better predict future GIS response to climate change. Using 10Be surface exposure ages and radiocarbon-dated lake sediments, we constructed a detailed chronology of ice-margin fluctuations over the past 10 k.y. for Jakobshavn Isbræ, Greenland's largest outlet glacier. In addition, we present new estimates of corresponding local temperature changes using a continuous record of insect (Chironomidae) remains preserved in lake sediments. We find that following an early Holocene advance just prior to 8 ka, Jakobshavn Isbræ retreated rapidly at a rate of ∼100 m yr−1, likely in response to increasing regional and local temperatures. Ice remained behind its present margin for ∼7 k.y. during a warm period in the middle Holocene with sustained temperatures ∼2 °C warmer than today, then the land-based margin advanced at least 2–4 km between A.D. 1500–1640 and A.D. 1850. The ice margin near Jakobshavn thus underwent large and rapid adjustments in response to relatively modest centennial-scale Holocene temperature changes, which may foreshadow GIS response to future warming.

Sources of n-alkanes in an urbanized estuary: Insights from molecular distributions and compound-specific stable and radiocarbon isotopes - Ahad, Jason M. E.; Ganeshram, Raja S.; Bryant, Charlotte L.; Cisneros-Dozal, Luz M.; Ascough, Philippa L.; Fallick, Anthony E.; Slater, Greg F. (Marine Chemistry, 2011)
Diagnostic molecular ratios and compound-specific 13C and 14C analyses were used to identify n-alkane sources in surface sediments collected along a transect from an urbanized estuary draining a peat-rich catchment (Tyne, UK). The most abundant homologues were generally C29 or C31, and the carbon preference index (CPI; 1.8 to 6.4) and average chain length (ACL; 28.5 to 29.5) of C25–C33 n-alkanes became progressively lower in samples closer to the mouth of estuary. δ13C signatures of C19–C31 n-alkanes ranged from − 37.1 to − 29.3‰ and in general became more depleted with increasing carbon number. Δ14C values for C21 (− 945 to − 738‰) were significantly more depleted compared to C29 (− 591 to − 65‰) and C31 (− 382 to − 96‰), pointing to a much higher component of fossil (i.e., 14C-free) carbon in the shorter homologue. The radiocarbon contents for these three n-alkanes decreased toward the North Sea, which in conjunction with an up to 4‰ seaward 13C-enrichment in C29 and C31 and seaward decreases in CPI and ACL pointed to petrogenic hydrocarbon contamination in lower estuarine sediments. Independent 13C and 14C mass balances used to calculate the relative proportions of modern (i.e., plant wax) and fossil (i.e., petrogenic) n-alkanes yielded similar results and demonstrated that mixing with marine-derived organic matter (OM) or microbial degradation during estuarine transport led to a seaward decline in modern, longer-chain homologues, resulting in an increasingly larger fossil carbon contribution toward the mouth of estuary. The ability to clearly distinguish anthropogenic from natural inputs suggests that compound-specific radiocarbon analysis can successfully delineate the age of terrigenous OM delivered to the coastal zone even near historically polluted systems such as the Tyne.
id: 2169

Stratigraphic record of Holocene coseismic subsidence, Padang, West Sumatra - Dura, Tina; Rubin, Charles M.; Kelsey, Harvey M.; Horton, Benjamin P.; Hawkes, Andrea; Vane, Christopher H.; Daryono, Mudrik; Pre, Candace Grand; Ladinsky, Tyler; Bradley, Sarah (JOURNAL OF GEOPHYSICAL RESEARCH-SOLID EARTH, 2011)
Stratigraphic evidence is found for two coseismic subsidence events that underlie a floodplain 20 km south of Padang, West Sumatra along the Mentawai segment (0.5 S- 0.3 S) of the Sunda subduction zone. Each earthquake is marked by a sharp soil-mud contact that represents a sudden change from mangrove to tidal flat. The earthquakes occurred about 4000 and 3000 cal years B.P. based on radiocarbon ages of detrital plant fragments and seeds. The absence of younger paleoseismic evidence suggests that late Holocene relative sea level fall left the floodplain too high for an earthquake to lower it into the intertidal zone. Our results point to a brief, few thousand year window of preservation of subsidence events in tidal-wetland stratigraphic sequences, a result that is generally applicable to other emergent coastlines of West Sumatra.

Trace metal enrichments in Lake Tanganyika sediments: Controls on trace metal burial in lacustrine systems - Brucker, Rebecca Poulson; McManus, James; Severmann, Silke; Owens, Jeremy; Lyons, Timothy W. (Geochimica et Cosmochimica Acta, 2011)
We investigate the distributions of several key diagenetic reactants (C, S, Fe) and redox-sensitive trace metals (Mo, Cd, Re, U) in sediments from Lake Tanganyika, East Africa. This study includes modern sediments from a chemocline transect, which spans oxygenated shallow waters to sulfidic conditions at depth, as well as ancient sediments from a longer core (∼2 m) taken at ∼900 m water depth. Modern sediments from depths spanning ∼70–335 m are generally characterized by increasing enrichments of C, S, Mo, Cd, and U with increasing water depth but static Fe distributions. It appears that the sedimentary enrichments of these elements are, to varying degrees, influenced by a combination of organic carbon cycling and sulfur cycling. These modern lake characteristics contrast with a period of high total organic carbon (Corg), total sulfur (STot), and trace metal concentrations observed in the 900 m core, a period which follows the most recent deglaciation (∼18–11 ky). This interval is followed abruptly by an interval (∼11–6 ky) that is characterized by lower C, S, U, and Mo. Consistent with other work we suspect that the low concentrations of S, Mo, and U may indicate a period of intense lake mixing, during which time the lake may have been less productive and less reducing as compared to the present. An alternative, but not mutually exclusive, hypothesis is that changes in the lake’s chemical inventory, driven by significant hydrological changes, could be influencing the distribution of sedimentary trace elements through time.
id: 2144

Aeolian sand invasion in coastal regions: geomorphological and geophysical aspects - Buynevich, I. V.; Souza Filho, P. W. M.; Bitinas, A.; Asp, N. E.; Pupienis, D. (Schukin Conference on Geomorphology, 2010)
id: 2128

Asphalt volcanoes as a potential source of methane to late Pleistocene coastal waters - Valentine, D. L.; Reddy, C. M.; Farwell, C.; Hill, T. M.; Pizarro, O.; Yoerger, D. R.; Camilli, R.; Nelson, R. K.; Peacock, E. E.; Bagby, S. C.; Clarke, B. A.; Roman, C. N.; et al. (Nature Geoscience, 2010)
Every year, natural petroleum seepage emits 0.2-2 Tg of oil to the ocean(1). Significant oil seepage can build large underwater mounds, consisting of tar deposits with morphologies similar to volcanic lava flows, known as asphalt volcanoes(2,3). Such events are typically accompanied by large fluxes of the greenhouse gas methane(4,5). Marine sediments from the Santa Barbara basin, California, contain a record of elevated methane concentrations(6), anoxia and tar deposition(7) during the Pleistocene epoch that had been attributed to dissolution of methane hydrates. However, the region is known to have exhibited oil seepage in the past(7). Here, we document the discovery of seven extinct asphalt volcanoes off the coast of southern California. The morphology of the deposits and geochemistry of samples taken from the two largest structures supports their classification as asphalt volcanoes, derived from a common source. We estimate that the two structures resulted from seepage of 0.07-0.4 Tg of oil, accompanied by the emission of 0.35-1.8 Tg of methane. Radiocarbon dating of carbonate deposits entrained with the asphalt indicates formation of the volcanoes between 44 and 31 kyr ago. The timing and volume of erupted hydrocarbons from the asphalt structures can explain some or all of the documented methane release and tar accumulation in the Santa Barbara basin during the Pleistocene.
id: 1866; Sp. Iss. SI 589XW Times Cited:0 Cited References Count:28; YY

Assessing Microbial Uptake of Petroleum Hydrocarbons in Groundwater Systems Using Natural Abundance Radiocarbon - Ahad, Jason M. E.; Burns, Leanne; Mancini, Silvia; Slater, Greg F. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2010)
Carbon sources utilized by the active microbial communities in shallow groundwater systems underlying three petroleum service stations were characterized using natural abundance radiocarbon ((14)C). Total organic carbon (TOC) Delta(14)C values ranged from -314 to -972 parts per thousand and petroleum-extracted residues (EXT-RES) ranged from -293 to -971 parts per thousand. Phospholipid fatty acids (PLFAs)-biomarkers for active microbial populations-ranged from -405 to -885 parts per thousand and a comparison of these values with potential carbon sources pointed to significant microbial assimilation of (14)C-free fossil carbon. The most (14)C depleted PLFAs were found in the samples with the highest concentrations of total petroleum hydrocarbons (TPHs). A radiocarbon mass balance indicated up to 43% of the carbon in microbial PLFAs was derived from TPHs, providing direct evidence for biodegradation at two of three sites. At lower levels of TPHs. Delta(14)C values of PLFAs were generally similar to or more enriched than all other carbon in the system indicating microbial utilization of a more (14)C-enriched carbon source and no resolvable evidence for microbial incorporation of petroleum-derived carbon. Results from this study suggest that it is possible to delineate petroleum biodegradation in groundwater systems using these techniques even in complex situations where there exists a wide range in the ages of natural organic matter (i.e., EXT-RES).

Calibrating a sedimentary record of overwash from Southeastern New England using modeled historic hurricane surges - Boldt, Katherine V.; Lane, Philip; Woodruff, Jonathan D.; Donnelly, Jeffrey P. (Marine Geology, 2010)
We present a 2000-year record of overwash deposits preserved in a backbarrier salt marsh from southeastern New England. The timing of recent deposits matches well with large hurricane-induced storm surge events documented by local tide gauges in 1991, 1960, 1954, and 1938. Storm surge modeling is used to evaluate the flooding history at the site as well as to assess the pre-instrumental historical record. Storms in 1815, 1727, and 1635 likely caused significant surge that overtopped the barrier, with the timing of coarse-grained overwash deposition correlating well with these events. We infer that twenty-three prehistoric layers mapped across the site were likely also deposited by landfalling hurricanes. Additional records from the area will help to evaluate whether or not temporal trends at the site are a robust representation of hurricane activity for the region. The frequency of overwash at Mattapoisett Marsh, on average 1.5 events per century, is significantly higher than many other overwash-based reconstructions from the western North Atlantic. Further, the Mattapoisett Marsh record does not contain significant multi-centennial gaps in overwash layers. This initial comparison of the data from Mattapoisett marsh with other reconstructions from the western North Atlantic may point toward relatively constant tropical cyclone frequency over the last 2000 years with significant variation in the number of intense tropical cyclones.
Keywords: Holocene; hurricane; Paleotempestology; Salt marsh; storm surge; tropical cyclone

Climatic controls of interannual variability in regional carbon fluxes from top-down and bottom-up perspectives RID B-8211-2009 - Desai, Ankur R.; Helliker, Brent R.; Moorcroft, Paul R.; Andrews, Arlyn E.; Berry, Joseph A. (Journal of Geophysical Research-Biogeosciences, 2010)
Observations of regional net ecosystem exchange (NEE) of CO(2) for 1997-2007 were analyzed for climatic controls on interannual variability (IAV). Quantifying IAV of regional (10(4)-10(6) km(2)) NEE over long time periods is key to understanding potential feedbacks between climate and the carbon cycle. Four independent techniques estimated monthly regional NEE for 10(4) km(2) in a spatially heterogeneous temperate-boreal transition region of the north central United States, centered on the Park Falls, Wisconsin, United States, National Oceanic and Atmospheric Administration tall tower site. These techniques included two bottom-up methods, based on flux tower upscaling and forest inventory based demographic modeling, respectively, and two top-down methods, based on tall tower equilibrium boundary layer budgets and tracer-transport inversion, respectively. While all four methods revealed a moderate carbon sink, they diverged significantly in magnitude. Coherence of relative magnitude and variability of NEE anomalies was strong across the methods. The strongest coherence was a trend of declining carbon sink since 2002. Most climatic controls were not strongly correlated with IAV. Significant controls on IAV were those related to hydrology, such as water table depth, and atmospheric CO(2). Weaker relationships were found with phenological controls such as autumn soil temperature. Hydrologic relationships were strongest with a 1 year lag, potentially highlighting a previously unrecognized predictor of IAV in this region. These results highlight a need for continued development of techniques to estimate regional IAV and incorporation of hydrologic cycling into couple carbon-climate models.
id: 1941; PT: J; UT: WOS:000277259700003

Constant Holocene Southern-Ocean 14C reservoir ages and ice-shelf flow rates - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellogg, Thomas B. (2010)
Southern Ocean radiocarbon reservoir ages (i.e. non-zero radiocarbon ages in seawater) are the highest in the world's surface ocean. Constraining these reservoir ages at present and in the past is important not only because unknown reservoir ages limit the interpretation of Antarctic radiocarbon chronologies, but also because reservoir ages provide information about ocean circulation (as a recorder of past circulation and as an end member for major deep-water masses in today's ocean). In this study, we use paired U/Th and 14C ages of an unusual set of solitary coral samples trapped by fringing ice shelves in the Ross Sea to provide the first detailed study of Holocene reservoir ages for the Southern Ocean. Our results indicate a relatively constant marine radiocarbon reservoir age of 1144 ± 120 years for the past 6000 years. These results are consistent with extrapolation of the relationship between 14C and alkalinity seen elsewhere, supporting the use of this empirical relationship in high latitudes. The results also suggest constant deep-ocean circulation and air–sea exchange during the Holocene and provide a good target for tuning ocean models of modern circulation. Combining the new ages for corals with their distance from the modern-day ice-shelf grounding line provides some of the first long-term records of ice-shelf velocities for any region and indicates constant flow of the McMurdo Ice Shelf during the Holocene, at a rate similar to that observed today.
Keywords: coral; marine reservoir effect; McMurdo Ice Shelf; radiocarbon; Southern Ocean; U/Th dating

Constant Holocene Southern-Ocean C-14 reservoir ages and ice-shelf flow rates - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellogg, Thomas B. (EARTH AND PLANETARY SCIENCE LETTERS, 2010)
Southern Ocean radiocarbon reservoir ages (i.e. non-zero radiocarbon ages in seawater) are the highest in the world's surface ocean. Constraining these reservoir ages at present and in the past is important not only because unknown reservoir ages limit the interpretation of Antarctic radiocarbon chronologies, but also because reservoir ages provide information about ocean circulation (as a recorder of past circulation and as an end member for major deep-water masses in today's ocean). In this study, we use paired U/Th and C-14 ages of an unusual set of solitary coral samples trapped by fringing ice shelves in the Ross Sea to provide the first detailed study of Holocene reservoir ages for the Southern Ocean. Our results indicate a relatively constant marine radiocarbon reservoir age of 1144 +/- 120 years for the past 6000 years. These results are consistent with extrapolation of the relationship between C-14 and alkalinity seen elsewhere, supporting the use of this empirical relationship in high latitudes. The results also suggest constant deep-ocean circulation and air-sea exchange during the Holocene and provide a good target for tuning ocean models of modern circulation. Combining the new ages for corals with their distance from the modern-day ice-shelf grounding line provides some of the first long-term records of ice-shelf velocities for any region and indicates constant flow of the McMurdo Ice Shelf during the Holocene, at a rate similar to that observed today. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: coral; marine reservoir effect; McMurdo Ice Shelf; radiocarbon; Southern Ocean; U/Th dating

Distribution of Isotopic and Environmental Tracers in Groundwater, Northern Ada County, Southwestern Idaho - Adkins, C. B.; Bartolino, J. R. (Scientific Investigations Report, 2010)

Drowned coastal deposits with associated archaeological remains from a sea-level "slowstand": Northwestern Gulf of Maine, USA - Kelley, Joseph T.; Belknap, Daniel F.; Claesson, Stefan (Geology, 2010)
Drowned terrestrial wetland environments, such as lakes, marshes, and beaches, were thought to be rare in formerly glaciated regions like the Gulf of Maine (United States). In the northwestern Gulf of Maine, postglacial relative sea-level changes include a "slowstand" between 11.5 ka and 7.5 ka, when the ocean rose
id: 1996; PT: J; UT: WOS:000279847900006

Eurasian Pastoralists And Their Shifting Regional Interactions at the Steppe Margin: Settlement History At Mukri, Kazakhstan - Frachetti, M.; Benecke, N.; Mar’yashev, A. N.; Doumani, P. (World Archaeology, 2010)
id: 1880In Press

Freshwater Outburst from Lake Superior as a Trigger for the Cold Event 9300 Years Ago - Yu, Shi-Yong; Colman, Steven M.; Lowell, Thomas V.; Milne, Glenn A.; Fisher, Timothy G.; Breckenridge, Andy; Boyd, Matthew; Teller, James T. (Science, 2010)
Paleoclimate proxy records reveal a pervasive cooling event with a Northern Hemispheric extent similar to 9300 years ago. Coeval changes in the oceanic circulation of the North Atlantic imply freshwater forcing. However, the source, magnitude, and routing of meltwater have remained unknown. Located in central North America, Lake Superior is a key site for regulating the outflow of glacial meltwater to the oceans. Here, we show evidence for an similar to 45-meter rapid lake-level fall in this basin, centered on 9300 calibrated years before the present, due to the failure of a glacial drift dam on the southeast corner of the lake. We ascribe the widespread climate anomaly similar to 9300 years ago to this freshwater outburst delivered to the North Atlantic Ocean through the Lake Huron-North Bay-Ottawa River-St. Lawrence River valleys.
id: 1950; PT: J; UT: WOS:000278318600030

From ice age to modern: a record of landscape change in an Andean cloud forest - Valencia, B. G.; Urrego, D. H.; Silman, M. R.; Bush, M. B. (Journal of Biogeography, 2010)
Aim
id: 869; 639ND Times Cited:5 Cited References Count:63Y

A High-Performance (14)c Accelerator Mass Spectrometry System - Roberts, M. L.; Burton, J. R.; Elder, K. L.; Longworth, B. E.; McIntyre, C. P.; von Reden, K. F.; Han, B. X.; Rosenheim, B. E.; W. J. Jenkins; Galutschek, E.; McNichol, A. P. (Radiocarbon, 2010)
A new and unique radiocarbon accelerator mass spectrometry (AMS) facility has been constructed at the Woods Hole Oceanographic Institution. The defining characteristic of the new system is its large-gap optical elements that provide a larger-than-standard beam acceptance. Such a system is ideally suited for high-throughput, high-precision measurements of (14)C. Details and performance of the new system are presented.
id: 2095; PT: J; CT: 20th International Radiocarbon Conference; CY: MAY 31-JUN 05, 2009; CL: Big Isl, HI; SI: 1; UT: WOS:000285437800005

Implications for chloro- and pheopigment synthesis and preservation from combined compound-specific δ13C, δ15N, and Δ14C analysis - Kusch, S.; Kashiyama, Y.; Ogawa, N. O.; Altabet, M.; Butzin, M.; Friedrich, J.; Ohkouchi, N.; Mollenhauer, G. (Biogeosciences, 2010)
Chloropigments and their derivative pheopigments preserved in sediments can directly be linked to photosynthesis. Their carbon and nitrogen stable isotopic compositions have been shown to be a good recorder of recent and past surface ocean environmental conditions tracing the carbon and nitrogen sources and dominant assimilation processes of the phytoplanktonic community. In this study we report results from combined compound-specific radiocarbon and stable carbon and nitrogen isotope analysis to examine the time-scales of synthesis and fate of chlorophyll-a and its degradation products pheophytin-a, pyropheophytin-a, and 132,173-cyclopheophorbide-a-enol until burial in Black Sea core-top sediments. The pigments are mainly of marine phytoplanktonic origin as implied by their stable isotopic compositions. Pigment delta15N values indicate nitrate as the major uptake substrate but 15N-depletion towards the open marine setting indicates either contribution from N2-fixation or direct uptake of ammonium from deeper waters. Radiocarbon concentrations translate into minimum and maximum pigment ages of approximately 40 to 1200 years. This implies that protective mechanisms against decomposition such as association with minerals, storage in deltaic anoxic environments, or eutrophication-induced hypoxia and light limitation are much more efficient than previously thought. Moreover, seasonal variations of nutrient source, growth period, and habitat and their associated isotopic variability are likely at least as strong as long-term trends. Combined triple isotope analysis of sedimentary chlorophyll and its primary derivatives is a powerful tool to delineate biogeochemical and diagenetic processes in the surface water and sediments, and to assess their precise time-scales.

In situ cosmogenic (10)Be production-rate calibration from the Southern Alps, New Zealand RID D-4720-2011 - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (Quaternary Geochronology, 2010)
We present a (10)Be production-rate calibration derived from an early Holocene debris-flow deposit at about 1000 m above sea level in the central Southern Alps, New Zealand, in the mid-latitude Southern Hemisphere. Ten radiocarbon ages on macrofossils from a soil horizon buried by the deposit date the deposit to 9690 +/- 50 calendar years before AD2008. Surface (10)Be concentrations of seven large boulders partially embedded in the stable surface of the deposit are tightly distributed, yielding a standard deviation of similar to 2%. Conversion of the (10)Be measurements to sea level/high-latitude values using each of five standard scaling methods indicates (10)Be production rates of 3.84 +/- 0.08, 3.87 +/- 0.08, 3.83 +/- 0.08, 4.15 +/- 0.09, and 3.74 +/- 0.08 atoms g(-1) a(-1), relative to the '07KNSTD' (10)Be AMS standard, and including only the local time-integrated production-rate uncertainties. When including a sea level high-latitude scaling uncertainty the overall error is similar to 2.5% (1 sigma) for each rate. To test the regional applicability of this production-rate calibration, we measured (10)Be concentrations in a set of nearby moraines deposited before 18060 +/- 200 years before AD2008. The (10)Be ages are only consistent with minimum-limiting (14)C age data when calculated using the new production rates. This also suggests that terrestrial in situ cosmogenic-nuclide production did not change significantly from Last Glacial Maximum to Holocene time in New Zealand. Our production rates agree well with those of a recent calibration study from northeastern North America, but are 12-14% lower than other commonly adopted values. The production-rate values presented here can be used elsewhere in New Zealand for rock surfaces exposed during or since the last glacial period. (C) 2009 Elsevier B.V. All rights reserved.
id: 2031; PT: J; UT: WOS:000280946500002

In situ cosmogenic Be-10 production-rate calibration from the Southern Alps, New Zealand - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (QUATERNARY GEOCHRONOLOGY, 2010)
We present a Be-10 production-rate calibration derived from an early Holocene debris-flow deposit at about 1000 m above sea level in the central Southern Alps, New Zealand, in the mid-latitude Southern Hemisphere. Ten radiocarbon ages on macrofossils from a soil horizon buried by the deposit date the deposit to 9690 +/- 50 calendar years before AD2008. Surface Be-10 concentrations of seven large boulders partially embedded in the stable surface of the deposit are tightly distributed, yielding a standard deviation of similar to 2%. Conversion of the Be-10 measurements to sea level/high-latitude values using each of five standard scaling methods indicates Be-10 production rates of 3.84 +/- 0.08, 3.87 +/- 0.08, 3.83 +/- 0.08, 4.15 +/- 0.09, and 3.74 +/- 0.08 atoms g(-1) a(-1), relative to the `07KNSTD' Be-10 AMS standard, and including only the local time-integrated production-rate uncertainties. When including a sea level high-latitude scaling uncertainty the overall error is similar to 2.5% (1 sigma) for each rate. To test the regional applicability of this production-rate calibration, we measured Be-10 concentrations in a set of nearby moraines deposited before 18060 +/- 200 years before AD2008. The Be-10 ages are only consistent with minimum-limiting C-14 age data when calculated using the new production rates. This also suggests that terrestrial in situ cosmogenic-nuclide production did not change significantly from Last Glacial Maximum to Holocene time in New Zealand. Our production rates agree well with those of a recent calibration study from northeastern North America, but are 12-14% lower than other commonly adopted values. The production-rate values presented here can be used elsewhere in New Zealand for rock surfaces exposed during or since the last glacial period. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Be-10; C-14; Cosmogenic nuclide; Debris flow; Holocene; Last glacial maximum; Moraine; Production rate; South Island

A long history of cloud and forest migration from Lake Consuelo, Peru - Urrego, D. H.; Bush, M. B.; Silman, M. R. (Quaternary Research, 2010)
The complete paleoecological history from Lake Consuelo forest yields a record of ground-level cloud formation and changes in its lower altitudinal limit over the last 46,300 cal yr BP. The timing of early lake level fluctuations prior to 37,000 cal yr BP appears sensitive to North Atlantic temperature oscillations, corresponding to Dansgaard-Oeschger interstadials 11, 10 and 8 recorded in GISP2. After the LGM, the first hint of warming is recorded in Lake Consuelo at 22,000 call yr BP and agrees with other estimates for the region. The mid-Holocene (7400-5000 cal yr BP) was the period of highest rates of change and most significant reorganizations in the Consuelo forest. These community changes resulted from a regionally widespread dry period. Results from Lake Consuelo indicate that moisture availability, mediated through cloud cover, played the most significant role in ecological change in this system. Rates of past climate fluctuations never exceeded the forest capacity to accommodate change. Unfortunately, this might not be the case under predicted scenarios for the end of the current century. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1903; 564VS Times Cited:8 Cited References Count:85Y

Millennial-aged organic carbon subsidies to a modern river food web - Caraco, Nina; Bauer, James E.; Cole, Jonathan J.; Petsch, Steven; Raymond, Peter (Ecology, 2010)
Recent studies indicate that highly aged material is a major component of organic matter transported by most rivers. However, few studies have used natural (14)C to trace the potential entry of this aged material into modern river food webs. Here we use natural abundance (14)C, (13)C, and deuterium ((2)H) to trace the contribution of aged and contemporary organic matter to an important group of consumers, crustacean zooplankton, in a large temperate river (the Hudson River, New York, USA). Zooplankton were highly (14)C depleted (mean Delta(14)C = -240 parts per thousand) compared to modern primary production in the river or its watershed (Delta(14)C = -60 parts per thousand to +50 parts per thousand). In order to account for the observed (14)C depletion, zooplankton must be subsidized by highly aged particulate organic carbon. IsoSource modeling suggests that the range of the aged dietary subsidy is between similar to 57%, if the aged organic matter source was produced 3400 years ago, and similar to 21%, if the organic carbon used is >= 50 000 years in age, including fossil material that is millions of years in age. The magnitude of this aged carbon subsidy to river zooplankton suggests that modern river food webs may in some cases be buffered from the limitations set by present-day primary production.
id: 2032; PT: J; UT: WOS:000280153500022

Millennial-scale climate variability during the Last Glacial period in the tropical Andes - Fritz, S. C.; Baker, P. A.; Ekdahl, E.; Seltzer, G. O.; Stevens, L. R. (Quaternary Science Reviews, 2010)
Millennial-scale climate variation during the Last Glacial period is evident in many locations worldwide, but it is unclear if such variation occurred in the interior of tropical South America. and, if so, how the low-latitude variation was related to its high-latitude counterpart A high-resolution record, derived from the deep drilling of sediments on the floor of Lake Titicaca in the southern tropical Andes, is presented that shows clear evidence of millennial-scale climate variation between similar to 60 and 20 ka BP This variation is manifested by alternations of two interbedded sedimentary units The two units have distinctive sedimentary, geochemical, and paleobiotic properties that are controlled by the relative abundance of terrigenous or nearshore components versus pelagic components The sediments of more terrigenous or nearshore nature likely were deposited during regionally wetter climates when river transport of water and sediment was higher, whereas the sediments of more pelagic character were deposited during somewhat drier climates regionally. The majority of the wet periods inferred from the Lake Titicaca sediment record are correlated with the cold events in the Greenland ice cores and North Atlantic sediment cores. indicating that increased intensity of the South American summer monsoon was part of near-global scale climate excursions (C) 2010 Elsevier Ltd All rights reserved
id: 1886; 584JY Times Cited:5 Cited References Count:59Y

Photosynthetic isotope biosignatures in laminated micro-stromatolitic and non-laminated nodules associated with modern, freshwater microbialites in Pavilion Lake, BC RID B-8520-2011 - Brady, A. L.; Slater, G. F.; Omelon, C. R.; Southam, G.; Druschel, G.; Andersen, D. T.; Hawes, I.; Laval, B.; Lim, D. S. S. (Chemical Geology, 2010)
The influence of microbial activity on carbonate precipitation was investigated within micro-stromatolitic nodules associated with modem, freshwater microbialites located in Pavilion Lake, B.C. Observed carbonate delta(13)C values enriched by up to +3.6 parts per thousand as compared to predicted abiotic carbonate delta(13)C values from measured dissolved inorganic carbon (mean -1.2 parts per thousand, n=13) were consistent with microbial photosynthetic influence on in situ precipitation within the nodule microenvironment. Estimated carbonate precipitation temperatures within the nodules based on delta(18)O were consistent with recorded summertime temperatures, indicative of precipitation during the period of highest levels of photosynthetic activity. Low delta(13)C values of organic matter within the nodules (-30.6 to 21.1 parts per thousand) and an average inorganic to organic carbon Delta delta(13)C value of 26.8 parts per thousand reflected the preferential uptake of (12)C during non-CO(2) limited photosynthesis, supporting the generation of (13)C-enriched DIC. Microelectrode profiles through the nodules showed oxygen supersaturation of up to similar to 275%, elevated pH compared to ambient water and a lack of any observable dissolved sulphide, Mn or Fe further indicated that photosynthetic activity was the predominant metabolic process within the nodule during light exposure. Microbial phospholipid fatty acid profiles of the nodule communities were indicative of bacteria rather than eukaryotes and PLFA delta(13)C values were depleted relative to the bulk cell by 2.6-6.6 parts per thousand, consistent with a predominance of photosynthetic microbes. Scanning electron microscopy images of the relationship between carbonate minerals and filaments indicated that carbonate precipitation had occurred in situ due to microbial influences on the geochemistry within the nodule microenvironment rather than due to cell surface effects or trapping and binding. The observation of photosynthetically induced (13)C-enrichment of in situ precipitated carbonate within the nodule microenvironment is thus a biosignature of the activity of these surface communities and is consistent with the hypothesized role of biology in the formation of microbialites. (C) 2010 Elsevier B.V. All rights reserved.
id: 2056; PT: J; UT: WOS:000279094700005

The potential of New Zealand kauri (Agathis australis) for testing the synchronicity of abrupt climate change during the Last Glacial Interval (60,000-11,700 years ago) - Turney, Chris S. M.; Fifield, L. Keith; Hogg, Alan G.; Palmer, Jonathan G.; Hughen, Konrad; Baillie, Mike G. L.; Galbraith, Rex; Ogden, John; Lorrey, Andrew; Tims, Stephen G.; Jones, Richard T. (Quaternary Science Reviews, 2010)
The latter part of the Last Glacial Interval (LGI; 60,000 to 11,700 years ago) experienced a range of climatic and environment extremes. To elucidate the mechanisms of these changes requires records of past variability that are precisely dated and correlated on the same absolute timescale. However, despite decades of research, it is still not possible to align most marine and terrestrial records of past change with ice-core records, largely because of ongoing uncertainties over the conversion of pre-Holocene (14)C ages on to a calendar timescale and uncertainties with in ice-core chronologies. As a result, it is equivocal whether climate changes in both hemispheres during the LGI led, lagged or were synchronous with one another. A decadally-resolved radiocarbon calibration is urgently required to test these models of the Earth system. Here we report radiocarbon measurements obtained from subfossil New Zealand kauri (Agathis australis) spanning a collective 3500 years dated between 25,000 and 45,000 years ago. The results are compared to the recently published international calibration curve IntCal09 and to the marine Cariaco Basin datasets. We show that kauri have considerable potential for development of a Southern Hemisphere component of a unified global calibration curve suite, and that tree-ring sequences can be superposed on other radiocarbon records to constrain atmospheric marine offsets and precisely test the synchronicity of abrupt climate change. (C) 2010 Elsevier Ltd. All rights reserved.
id: 1982; PT: J; UT: WOS:000285222000001

Radiocarbon Dating of Individual Lignin Phenols: A New Approach for Establishing Chronology of Late Quaternary Lake Sediments - Hou, Juzhi; Huang, Yongsong; Brodsky, Corynn; Alexandre, Marcelo R.; McNichol, Ann P.; King, John W.; Hu, Feng Sheng; Shen, Ji (ANALYTICAL CHEMISTRY, 2010)
The reliability of chronology is a prerequisite for meaningful paleoclimate reconstructions from sedimentary archives. The conventional approach of radiocarbon dating bulk organic carbon in lake sediments is often hampered by the old carbon effect, i.e., the assimilation of ancient dissolved inorganic carbon (DIC) derived from carbonate bedrocks or other sources. Therefore, radiocarbon dating is ideally performed on organic compounds derived from land plants that use atmospheric CO(2) and rapidly delivered to sediments. We demonstrate that lignin phenols isolated from lake sediments using reversed phase high performance liquid chromatography (HPLC) can serve as effective (14)C dating materials for establishing chronology during the late Quaternary. We developed a procedure to purify lignin phenols, building upon a published method. By isolating lignin from standard wood reference substances, we show that our method yields pure lignin phenols and consistent ages as the consensus ages and that our procedure does not introduce radiocarbon contamination. We further demonstrate that lignin phenol ages are compatible with varve counted and macrofossil dated sediment horizons in Steel Lake and Fayetteville Green Lake. Applying the new method to lake sediment cores from Lake Qinghai demonstrates that lignin phenol ages in Lake Qinghai are consistently younger than bulk total organic carbon (TOC) ages which are contaminated by old carbon effect. We also show that the age offset between lignin and bulk organic carbon differs at different Lake Qinghai sedimentary horizons, suggesting a variable hard water effect at different times and that a uniform age correction throughout the core is inappropriate.

Reconnaissance dating A new radiocarbon method applied to assessing the temporal distribution of Southern Ocean deep-sea corals - Burke, Andrea; Robinson, Laura F.; McNichol, Ann P.; W. J. Jenkins; Scanlon, Kathryn M.; Gerlach, Dana S. (Deep-Sea Research Part I-Oceanographic Research Papers, 2010)
We have developed a rapid reconnaissance method of preparing graphite for (14)C/(12)C analysis Carbonate (similar to 15 mg) is combusted using an elemental analyzer and the resulting CO(2) is converted to graphite using a sealed tube zinc reduction method Over 85% (n=45 replicates on twenty-one individual corals) of reconnaissance ages measured on corals ranging in age from 500 to 33 000 radiocarbon years (Ryr) are within two standard deviations of ages generated using standard hydrolysis methods on the same corals and all reconnaissance ages are within 300 Ryr of the standard hydrolysis ages Replicate measurements on three individual aragonitic corals yielded ages of 1076 +/- 35 Ryr (standard deviation n=5) 10 739 +/- 47 Ryr (n=8) and 40 146 +/- 3500 Ryr (n=9) No systematic biases were found using different cleaning methods or variable sample sizes Analysis of (13)C/(12)C was made concurrently with the (14)C/(12)C measurement to correct for natural fractionation and for fractionation during sample processing and analysis This technique provides a new rapid method for making accurate percent-level (14)C/(12)C analyses that may be used to establish the rates and chronology of earth system processes where survey-type modes of age estimation are desirable For example applications may include creation of sediment core-top maps preliminary age models for sediment cores and growth rate studies of marine organisms such as corals or mollusks We applied the reconnaissance method to more than 100 solitary deep-sea corals collected in the Drake Passage in the Southern Ocean to investigate their temporal and spatial distribution The corals used in this study are part of a larger sample set and the subset that was dated was chosen based on species as opposed to preservation state so as to exclude obvious temporal biases Similar to studies in other regions the distribution of deep-sea corals is not constant through time across the Drake Passage Most of the corals from the Burdwood Bank (continental shelf of Argentina) have ages ranging between 0 and 2500 calendar years whereas most of the corals from the Sars Seamount in the Drake Passage have ages between 10 000 and 12 500 calendar years Such differences may be caused in part by sampling biases but may also be caused by changes in larval transport nutrient supply or other environmental pressures (C) 2010 Elsevier Ltd All rights reserved
id: 1924; PT: J; UT: WOS:000284750700012

Reconstructing Holocene conditions under the McMurdo Ice Shelf using Antarctic barnacle shells - Burgess, S. N.; Henderson, G. M.; Hall, B. L. (Earth and Planetary Science Letters, 2010)
This study evaluates the potential of barnacles for paleoceanographic reconstruction and, in particular, of the Antarctic species Bathylasma corolliforme to reconstruct past under ice shelves Like other barnacle species, this Antarctic barnacle secretes a robust low-Mg calcite shell with distinct growth increments on the external surface indicating growth over a number of years (30-50 in samples studied here). The Bathylasma samples used in this study grew in the Ross Sea and became entrained at the grounding line of a coastal ice shelf in McMurdo Sound, offering potential as an archive of changing conditions in this difficult to access environment under the McMurdo ice shelf. Nine barnacle shells were subsampled at high resolution (60 pun) for delta(18)O and delta(13)C analysis. These samples were dated with (14)C and U-Th techniques, although the later did not yield useful age information due to open-system behaviour of barnacle calcite. Measured delta(18)O values indicate that Bathylasma calcifies close to equilibrium with ambient seawater. One older sample (approximate to 200 ka) has similar delta(18)O and delta(13)C values as the eight Holocene samples, suggesting that barnacle calcite is not prone to significant diagenesis in this setting. Apparent isotope equilibrium and lack of diagenesis make barnacles a promising archive for reconstruction of past ocean conditions. Cycles of delta(18)O observed within each sample sometimes correlate with the external growth ridges, but not always, and have amplitudes of typically 0.6 parts per thousand. This magnitude of variation suggests shell growth during a significant portion of the year. although it remains unclear whether growth continues throughout the year. However, the prominent growth bands suggest at least a signficant seasonal slowing in growth rate. Variations in barnacle delta(18)O within each plate and between plates are too large to be caused by temperature. and instead reflect changes in delta(18)O of the seawater, allowing some assessment of seawater salinity under the ice shelf. Salinities are lowered by addition of meltwaters, but the barnacle delta(18)O data suggest values do not go below 33 parts per thousand.. These data indicate that Bathylasma has potential as an archive of paleoclimate information for shallow/intermediate water depths and, in particular, for difficult to reach environments such as below ice-shelves of Antarctica. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved
id: 1960; PT: J; UT: WOS:000283756600013

Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting - Bamberg, A.; Rosenthal, Y.; Paul, A.; Heslop, D.; Mulitza, S.; Ruhlemann, C.; Schulz, M. (Geophysical Research Letters, 2010)
Central waters of the North Atlantic are fundamental for ventilation of the upper ocean and are also linked to the strength of the Atlantic Meridional Overturning Circulation (AMOC). Here, we show based on benthic foraminiferal Mg/Ca ratios, that during times of enhanced melting from the Laurentide Ice Sheet (LIS) between 9.0-8.5 thousand years before present (ka) the production of central waters weakened the upper AMOC resulting in a cooling over the Northern Hemisphere. Centered at 8.54 +/- 0.2 ka and 8.24 +/- 0.1 ka our dataset records two similar to 150-year cooling events in response to the drainage of Lake Agassiz/Ojibway, indicating early slow-down of the upper AMOC in response to the initial freshwater flux into the subpolar gyre (SPG) followed by a more severe weakening of both the upper and lower branches of the AMOC at 8.2 ka. These results highlight the sensitivity of regional North Atlantic climate change to the strength of central-water overturning and exemplify the impact of both gradual and abrupt freshwater fluxes on eastern SPG surface water convection. In light of the possible future increase in Greenland Ice Sheet melting due to global warming these findings may help us to better constrain and possibly predict future North Atlantic climate change. Citation: Bamberg, A., Y. Rosenthal, A. Paul, D. Heslop, S. Mulitza, C. Ruhlemann, and M. Schulz (2010), Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting, Geophys. Res. Lett., 37, L17705, doi: 10.1029/2010GL043878.
id: 874; 649FZ Times Cited:3 Cited References Count:32submittedY

Relative sea-level changes, Schuchert Dal, East Greenland, with implications for ice extent in late-glacial and Holocene times - Hall, B. L.; Baroni, C.; Denton, G. H. (Quaternary Science Reviews, 2010)
The chronology of late-glacial and Holocene ice fluctuations in East Greenland is important for documenting glacier response to climate change and for determining the mechanisms behind abrupt climate switches. Raised marine sediments and landforms suggest culmination of the late-glacial Milne Land Stade in Schuchert Dal alongside Scoresby Sund before similar to 11,900-12,300 cal yr B.P. Ice in Schuchert Dal apparently receded during the later part of the Younger Dryas, consistent with the idea that this period was characterized by strong seasonality. A stillstand or slight readvance probably interrupted overall recession just prior to 11,000 cal yr B.P. In many locations, ice was back close to present positions by the start of the Holocene. The most extensive glacier advance of the Holocene occurred during the Little Ice Age and was restricted to within a few kilometers of present-day ice margins. (C) 2010 Elsevier Ltd. All rights reserved.
id: 1953; PT: J; SI: SI; UT: WOS:000284724400003

Search for a glacial-age (14)C-depleted ocean reservoir - Broecker, Wally; Clark, Elizabeth (Geophysical Research Letters, 2010)
Measurements of the radiocarbon age difference between mixed benthic foraminifera and several coexisting planktic entities were made in hopes of finding evidence for the existence of an isolated glacial-age abyssal ocean reservoir whose demise would explain the large drops in the (14)C to C ratio in atmosphere and surface ocean carbon which occurred during the period of deglaciation. Forty-six new radiocarbon results were obtained at seven depths covering the full range of glacial time (i.e., similar to 27 to 15 (14)C kyrs) from an equatorial Pacific sediment core at 4.4-km water depth. Even though age reversals for foraminifera (but not for coccoliths) at two of the eight depths and large age differences between G. sacculifer and three submixed-layer planktic species mar this data set, there remains little likelihood that such a reservoir existed. Citation: Broecker, W., and E. Clark (2010), Search for a glacial-age (14)C-depleted ocean reservoir, Geophys. Res. Lett., 37, L13606, doi: 10.1029/2010GL043969.
id: 1923; PT: J; UT: WOS:000280043800003

The southern Svalbard Margin sedimentary system: preliminary results from EGLACOM cruise 2008 - Melis, R.; Lucchi, R. G.; Giorgetti, G.; Persico, D.; BÁRcena, M. A. A.; Caburlotto, A.; MacrÌ, P.; Villa, G.; Sagnotti, L.; Rebesco, M. (European Geosciences Union, General Assembly 2010, 2010)
id: 873

Stable isotopes reveal Holocene changes in the diet of Ad,lie penguins in Northern Victoria Land (Ross Sea, Antarctica) - Lorenzini, Sandra; Baroni, Carlo; Fallick, Anthony E.; Baneschi, Ilaria; Salvatore, Maria Cristina; Zanchetta, Giovanni; Dallai, Luigi (Oecologia, 2010)
Ad,lie penguin (Pygoscelis adeliae) modern and fossil eggshells and guano samples collected from ornithogenic soils in Terra Nova Bay (Victoria Land, Ross Sea) were processed for carbon and nitrogen isotopic ratios with the aim of detecting past penguin dietary changes. A detailed and greatly expanded Ad,lie penguin dietary record dated back to 7,200 years BP has been reconstructed for the investigated area. Our data indicate a significant dietary shift between fish and krill, with a gradual decrease from past to present time in the proportion of fish compared to krill in Ad,lie penguin diet. From 7,200 to 2,000 years BP, delta(13)C and delta(15)N values indicate fish as the most eaten prey. The dietary contribution of lower-trophic prey in penguin diet started becoming evident not earlier than 2,000 years BP, when the delta(13)C values reveal a change in the penguin feeding behavior. Modern eggshell and guano samples reveal a major dietary contribution of krill but not a krill-dominated diet, since delta(13)C values remain much too high if krill prevail in the diet. According to the Holocene environmental background attested for Victoria Land, Ad,lie penguin dietary shifts between fish and krill seem to reflect penguin paleoecological responses to different paleoenvironmental settings with different conditions of sea-ice extension and persistence. Furthermore, Ad,lie penguin diet appears to be particularly affected by environmental changes in a very specific period within the breeding season, namely the egg-laying period when penguin dietary and feeding habit shifts are clearly documented by the delta(13)C of eggshell carbonate.
id: 2350; PT: J; TC: 6; UT: WOS:000284271900007

Submarine Mass Transport Within Monterey Canyon: Benthic Disturbance Controls on the Distribution of Chemosynthetic Biological Communities - Paull, C. K.; Schlining, B.; Ussler, W.; Lundste, E.; Barry, J. P.; Caress, D. W.; Johnson, J. E.; McGann, M. (Submarine mass movements and their consequences, 4th International Symposium:, 2010)
Documenting mass transport within Monterey Canyon and Fan has been a focus of remotely operated vehicle (ROV) observations, sampling, monitoring, and multibeam mapping studies. These efforts indicate that major mass transport events occur within upper Monterey Canyon (2 km water depths) and onto Monterey Fan for ~100 years. Simultaneous efforts to document the distribution of benthic taxa observed in the video records from 668 ROV dives conducted by the Monterey Bay Aquarium Research Institute (MBARI) provide a uniquely detailed record of the occurrence of chemosynthetic biological communities (CBC). The combined results of these studies provide an understanding of the relationship between disturbance caused by episodic mass wasting events and the distribution of CBC. CBC are common within the canyon's axis below ~2.5 km water depth, but have not been found within the canyon's axis at depths shallower than 2 km. Moreover, CBC occur on the canyon walls at essentially any depth, primarily within young (~hundreds of years old) slump scars. The distribution of CBC provides evidence about the disturbance history of the seafloor. Major mass transport events will destroy communities that lie in their path. Erosion associated with major mass transport events can create environments to support CBC by exposing methane-bearing strata. This can happen as a result of slumping events on the sidewalls of the canyon or where major gravity flow events have excavated the base of canyon walls. Once fresh strata are exposed, geochemical conditions to support CBC will persist for a few centuries. Because CBC are composed of slow-growing and long-lived organisms, it will take decades for these communities to be established. Their existence indicates that environmental stability has occurred over a similar time scale.
id: 879

Temperature and salinity changes in the deglacial North Atlantic - Benway, H.M.; McManus, J.F.; Oppo, D.W.; Cullen, J.F. (Quaternary Science Reviews, 2010)

Unique Baltic Outcrops Reveal Millennia of Ecological Changes - Buynevich, I. V.; Bitinas, A.; Damušytė, A.; Pupienis, D. (EOS, TRANSACTIONS AMERICAN GEOPHYSICAL UNION, 2010)
Throughout Earth's history, tectonic forces, often violent and unpredictable, have been responsible for exposing geological formations to scientific scrutiny. But forces of uplift are not restricted to plate boundaries. For example, when looking at forested coastal dunes bordering placid Curonian Lagoon along the Lithuanian coast of the Baltic Sea, one hardly suspects that any powerful forces are at work. Yet this is a site where massive migrating hills of sand have put pressure on the deep strata of the ancient lagoon, forcing its sediments to the surface and offering rare access to fossils of the Holocene, which spans the past 10,000 years.
id: 1978

Using proglacial-threshold lakes to constrain fluctuations of the Jakobshavn Isbræ ice margin, western Greenland, during the Holocene - Briner, J.P.; Stewart, H.A.M.; Young, N.E.; Philipps, W.; Losee, S. (Quaternary Science Reviews, 2010)
The future response of the Greenland Ice Sheet (GIS) and its potential contribution to sea level rise are uncertain. Rapid changes of Greenland’s outlet glaciers over the past decade have made it difficult to extrapolate ice sheet change into the future. This significant short-term variability highlights the need for longer-term, geologic (e.g., Holocene) records of ice margin fluctuations. However, a major challenge with reconstructing the GIS during the Holocene stems from it having been smaller than it is at present, thus traditional glacial geologic approaches are not suitable. We use radiocarbon-dated sediment sequences from seven proglacial-threshold lakes spanning ∼50 km of the western GIS margin near Jakobshavn Isbræ to constrain the timing of early Holocene deglaciation, the duration that this sector of the western GIS was smaller than its present configuration, and the timing of its advance during Neoglaciation. Our reconstructions suggest deglaciation ∼7300 cal yr BP, minimum ice extent ∼6000–5000 cal yr BP and smaller-than-present ice configuration until at least ∼2300 cal yr BP for the ice margin south of Jakobshavn Isbræ, and until ∼400 cal yr BP for the ice margin north of Jakobshavn Isbræ. One relatively large proglacial lake that became briefly ice-free during the middle Holocene lies in a catchment that likely extends 10s of km inland beneath the GIS, suggesting significant middle Holocene retreat of this portion of the GIS. The overall pattern of ice sheet change is inconsistent with existing ice sheet model reconstructions for this region, but is consistent with numerous paleoclimate proxy and relative sea level data. These continuous lacustrine records corroborate, but provide closer age control than, existing non-continuous records of radiocarbon-dated reworked bivalves from historical moraines in the region. Reconstructing ice margin change from proglacial-threshold lakes is one of few approaches with the potential to constrain smaller-than-present ice sheet extent.

Were last glacial climate events simultaneous between Greenland and France? A quantitative comparison using non-tuned chronologies RID E-4539-2011 RID A-2643-2010 - Blaauw, Maarten; Wohlfarth, Barbara; Christen, J. Andres; Ampel, Linda; Veres, Daniel; Hughen, Konrad A.; Preusser, Frank; Svensson, Anders (Journal of Quaternary Science, 2010)
Several large abrupt climate fluctuations during the last glacial have been recorded in Greenland ice cores and archives from other regions. Often these Dansgaard-Oeschger events are assumed to have been synchronous over wide areas, and then used as tie-points to link chronologies between the proxy archives. However, it has not yet been tested independently whether or not these events were indeed synchronous over large areas. Here, we compare Dansgaard-Oeschger-type events in a well-dated record from southeastern France with those in Greenland ice cores. Instead of assuming simultaneous climate events between both archives, we keep their age models independent. Even these well-dated archives possess large chronological uncertainties that prevent us from inferring synchronous climate events at decadal to multi-centennial time scales. If possible, comparisons between proxy archives should be based on independent, non-tuned time-scales. Copyright (C) 2009 John Wiley & Sons, Ltd.
id: 1986; PT: J; UT: WOS:000276090800014

Year-round probing of soot carbon and secondary organic carbon contributions and sources to the South Asian Atmospheric Brown Cloud using radiocarbon (14C) measurements - Kirillova, Elena; Sheesley, Rebecca J.; Andersson, August; Kruså, Martin; Safai, P. D.; Budhavant, Krishnakant; Rao, P. S. P.; Praveen, P. S.; Gustafsson, Örjan (EGU General Assembly 2010, held 2-7 May, 2010 in Vienna, Austria, 2010)
South Asia is one region of vital importance for assessing human impact on radiative forcing by atmospheric aerosols. Previous research in the region has indicated that black carbon is a significant component of the regional aerosol load. In contrast, there is more ambiguous information regarding the contribution of secondary organic aerosols (SOA) to the total carbonaceous (TC) aerosol composition. Here we primarily address the SOA component of the South Asian Atmospheric Brown Cloud (ABC) by a combination of measurements of SOA concentrations and the 14C signature of TC. Atmospheric particulate matter was collected during fourteen-month continuous sampling campaigns Jan 2008 - March 2009 at both the Maldives Climate Observatory at Hannimaadho (MCO-H) and at the Sinhagad hilltop sampling site of the Indian Institute of Tropical Meteorology (SIN) in central-western India. The radiocarbon method is an ideal approach to identify fossil sources (14C "dead") compared to biogenic and biomass combustion products (with a contemporary 14C signal). The radiocarbon source apportionment of TC revealed very similar contribution from biogenic/biomass combustion (60-70%) for Indian SIN site and the MCOH receptor regions for much of the year. However, during the summer monsoon season biomass contribution to TC at the Indian Ocean site increases to 70-80%, while it decreases to 40-50% at the Indian site. Source apportionment of a soot carbon (SC) isolate (CTO-375 method; a tracer of black carbon) shows a similar trend. According to preliminary data in summer biomass contribution is higher at the MCOH receptor site (70%) compared to the SIN background site (45%). These unique year-round 14C data will be interpreted in view of the SOA concentration and the varying origin of the air masses.
id: 870Y

A 24,900-year paleolimnological history from the Peruvian Andes - Hillyer, R.; Valencia, B. G.; Bush, M. B.; Silman, M. R.; Steinitz-Kannan, M. (Quaternary Research, 2009)
id: 1902

Age Validation of Freshwater Drum using Bomb Radiocarbon - Davis-Foust, S. L.; Bruch, R. M.; Campana, S. E.; Olynyk, R. P.; Janssen, J. (Transactions of the American Fisheries Society, 2009)
The ages of freshwater drum Aplodinotus grunniens have typically been estimated by counting the growth increments on their scales or otoliths, but the accuracy of these estimates has not been validated. We used accelerator mass spectrometry (AMS) bomb radiocarbon dating to validate age estimates from sagittal otoliths of freshwater drum from the Lake Winnebago system, Wisconsin. The freshwater drum Delta C-14 chronology from the AMS assay closely reflects the timing and shape of other bomb radiocarbon chronologies, thus validating the accuracy of otolith growth increments to at least age 52 +/- 2 years. The progression of a strong 1983 year-class, which was detected every year sampled over the course of the study (1986, 2003-2007), and indices of year-class abundance calculated from trawling assessments on Lake Winnebago (1986-2007) corroborated otolith ages. Age estimate comparisons between scales, anal spines, dorsal spines, and otoliths showed scales and spines to be completely unreliable as aging structures after age 2. Freshwater drum live to very old ages relative to most other Great Lakes fishes; our oldest specimen based on an otolith age estimate was 58 years old.
id: 802; 477EI Times Cited:1 Cited References Count:58Y

Changes in sediment and organic carbon accumulation in a highly-disturbed ecosystem: The Sacramento-San Joaquin River Delta (California, USA) - Canuel, E. A.; Lerberg, E. J.; Dickhut, R. M.; Kuehl, S. A.; Bianchi, T. S.; Wakeham, S. G. (Marine Pollution Bulletin, 2009)
We used the Sacramento-San Joaquin River Delta CA (Delta, hereafter) as a model system for understanding how human activities influence the delivery of sediment and total organic carbon (TOC) over the past 50-60 years. Sediment cores were collected from sites within the Delta representing the Sacramento River (SAC), the San Joaquin River (SJR), and Franks Tract (FT), a flooded agricultural tract. A variety of anthropogenic tracers including (CS)-C-137, total DDE (Sigma DDE) and brominated diphenyl ether (BDE) congeners were used to quantify sediment accumulation rates. This information was combined with total organic carbon (TOC) profiles to quantify rates of TOC accumulation. Across the three sites, sediment and TOC accumulation rates were four to eight-fold higher prior to 1972. Changes in sediment and TOC accumulation were coincident with completion of several large reservoirs and increased agriculture and urbanization in the Delta watershed. Radiocarbon content of TOC indicated that much of the carbon delivered to the Delta is "pre-aged" reflecting processing in the Delta watershed or during transport to the sites rather than an input of predominantly contemporary carbon (e.g., 900-1400 years BP in surface sediments and 2200 yrs BP and 3610 yrs BP at the base of the SJR and FT cores, respectively). Together, these data suggest that human activities have altered the amount and age of TOC accumulating in the Delta since the 1940s. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1845; Sp. Iss. SI 477XX Times Cited:1 Cited References Count:49Y

Comparing glacial and Holocene opal fluxes in the Pacific sector of the Southern Ocean - Bradtmiller, L. I.; Anderson, R. F.; Fleisher, M. Q.; Burckle, L. H. (Paleoceanography, 2009)
The silicic acid leakage hypothesis (SALH) predicts that during glacial periods excess silicic acid was transported from the Southern Ocean to lower latitudes, which favored diatom production over coccolithophorid production and caused a drawdown of atmospheric CO2. Downcore records of Th-230-normalized opal (biogenic silica) fluxes from 31 cores in the Pacific sector of the Southern Ocean were used to compare diatom productivity during the last glacial period to that of the Holocene and to examine the evidence for increased glacial Si export to the tropics. Average glacial opal fluxes south of the modern Antarctic Polar Front (APF) were less than during the Holocene, while average glacial opal fluxes north of the APF were greater than during the Holocene. However, the magnitude of the increase north of the APF was not enough to offset decreased fluxes to the south, resulting in a decrease in opal burial in the Pacific sector of the Southern Ocean during the last glacial period, equivalent to approximately 15 Gt opal ka(-1). This is consistent with the work of Chase et al. (2003a), and satisfies the primary requirement of the SALH, assuming that the upwelled supply of Si was approximately equivalent during the Holocene and the glacial period. However, previous results from the equatorial oceans are inconsistent with the other predictions of the SALH, namely that either the C-org:CaCO3 ratio or the rate of opal burial should have increased during glacial periods. We compare the magnitudes of changes in the Southern Ocean and the tropics and suggest that Si escaping the glacial Southern Ocean must have had an alternate destination, possibly the continental margins. There is currently insufficient data to test this hypothesis, but the existence of this sink and its potential impact on glacial pCO(2) remain interesting topics for future study.
id: 836; 455GX Times Cited:0 Cited References Count:97Y

Constraining carbon sources and growth rates of freshwater microbialites in Pavilion Lake using 14C analysis - Brady, A. L.; Slater, G.; Laval, B.; Lim, D. S. (Geobiology, 2009)
This study determined the natural abundance isotopic compositions (13C, 14C) of the primary carbon pools and microbial communities associated with modern freshwater microbialites located in Pavilion Lake, British Columbia, Canada. The Delta 14C of dissolved inorganic carbon (DIC) was constant throughout the water column and consistent with a primarily atmospheric source. Observed depletions in DIC 14C values compared with atmospheric CO(2) indicated effects due either to DIC residence time and/or inputs of 14C-depleted groundwater. Mass balance comparisons of local and regional groundwater indicate that groundwater DIC could contribute a maximum of 9-13% of the DIC. 14C analysis of microbial phospholipid fatty acids from microbialite communities had Delta 14C values comparable with lake water DIC, demonstrating that lake water DIC was their primary carbon source. Microbialite carbonate was also primarily derived from DIC. However, some depletion in microbialite carbonate 14C relative to lake water DIC occurred, due either to residence time or mixing with a 14C-depleted carbon source. A detrital branch covered with microbialite growth was used to estimate a microbialite growth rate of 0.05 mm year-1 for the past 1000 years, faster than previous estimates for this system. These results demonstrate that the microbialites are actively growing and that the primary carbon source for both microbial communities and recent carbonate is DIC originating from the atmosphere. While these data cannot conclusively differentiate between abiotic and biotic formation mechanisms, the evidence for minor inputs of groundwater-derived DIC is consistent with the previously hypothesized biological origin of the Pavilion Lake microbialites.
id: 2055; PT: J; UT: WOS:000271633500006

Distribution of artificial radionuclides in deep sediments of the Mediterranean Sea - Garcia-Orellana, J.; Pates, J. M.; Masque, P.; Bruach, J. M.; Sanchez-Cabeza, J. A. (Science of the Total Environment, 2009)
Artificial radionuclides enter the Mediterranean Sea mainly through atmospheric deposition following nuclear weapons tests and the Chernobyl accident, but also through the river discharge of nuclear facility effluents. Previous studies of artificial radionuclides impact of the Mediterranean Sea have focussed on shallow, coastal sediments. However, deep sea sediments have the potential to store and accumulate pollutants, including artificial radionuclides. Deep sea marine sediment cores were collected from Mediterranean Sea abyssal plains (depth >2000 m) and analysed for Pu-239,Pu-240 and Cs-137 to elucidate the concentrations, inventories and sources of these radionuclides in the deepest areas of the Mediterranean. The activity - depth profiles of Pb-210, together with 14 C dating, indicate that sediment mixing redistributes the artificial radionuclides within the first 2.5 cm of the sedimentary column. The excess Pb-210 inventory was used to normalize Pu-239,Pu-240 and Cs-137 inventories for variable sediment fluxes. The Pu-239,Pu-240/Pb-210(xs) ratio was uniform across the entire sea, with a mean value of 1.24 x 10(-3), indicating homogeneous fallout of Pu-239,Pu-240. The Cs-137/Pb-210(xs) ratio showed differences between the eastern (0.049) and western basins (0.030), clearly significant impact of deep sea sediments from the Chernobyl accident. The inventory ratios of Pu-239,Pu-240/Cs-137 were 0.041 and 0.025 in the western and eastern basins respectively, greater than the fallout ratio, 0.021, showing more efficient scavenging of Pu-231,Pu-210 in the water column and major sedimentation of Cs-137 in the eastern basin. Although areas with water depths of >2000 m constitute around 40% of the entire Mediterranean basin, the sediments in these regions only contained 2.7% of the Pu-239,Pu-240 and 0.95% of the Cs-137 deposited across the Sea in 2000. These data show that the accumulation of artificial radionuclides in deep Mediterranean environments is much lower than predicted by other studies from the analysis of continental shelf sediments. (C) 2008 Elsevier B.V, All rights reserved.
id: 871; 389FH Times Cited:2 Cited References Count:63Y

Evidence of paleo-cold seep activity from the Bay of Bengal, offshore India - Mazumdar, A.; Dewangan, P.; Joao, H. M.; Peketi, A.; Khosla, V. R.; Kocherla, M.; Badesab, F. K.; Joshi, R. K.; Roxanne, P.; Ramamurty, P. B.; Karisiddaiah, S. M.; Patil, D. J.; et al. (Geochemistry Geophysics Geosystems, 2009)
We report evidence of paleo-cold seep associated activities, preserved in methane-derived carbonates in association with chemosynthetic clams (Calyptogena sp.) from a sediment core in the Krishna-Godavari basin, Bay of Bengal. Visual observations and calculations based on high-resolution wet bulk density profile of a core collected on board R/V Marion Dufresne (May 2007) show zones of sharp increase in carbonate content (10-55 vol%) within 16-20 meters below seafloor (mbsf). The presence of Calyptogena clam shells, chimneys, shell breccias with high Mg calcite cement, and pyrite within this zone suggest seepage of methane and sulfide-bearing fluid to the seafloor in the past. Highly depleted carbon isotopic values (delta C-13 ranges from -41 to -52% VPDB) from these carbonates indicate carbon derived via anaerobic oxidation of methane. Extrapolated mean calendar age (similar to 58.7 ka B. P.) of the clastic sediments at a depth of 16 mbsf is close to the upper limit of the U-Th based depositional age (46.2 +/- 3.7 and 53.0 +/- 1.6 ka) of authigenic carbonates sampled from this level, thereby constraining the younger age limit of the carbonate deposition/methane expulsion events. The observed carbonate deposition might have resulted from the flow of methane-enriched fluids through the fracture network formed because of shale diapirism.
id: 794; 458FC Times Cited:0 Cited References Count:80Y

Field Survey and Geological Effects of the 15 November 2006 Kuril Tsunami in the Middle Kuril Islands - MacInnes, B. T.; Pinegina, T. K.; Bourgeois, J.; Razhigaeva, N. G.; Kaistrenko, V. M.; Kravchunovskaya, E. A. (Pure and Applied Geophysics, 2009)
The near-field expression of the tsunami produced by the 15 November 2006 Kuril earthquake (M-w 8.1-8.4) in the middle Kuril Islands, Russia, including runup of up to 20 m, remained unknown until we conducted a post-tsunami survey in the summer of 2007. Because the earthquake occurred between summer field expeditions in 2006 and 2007, we have observations, topographic profiles, and photographs from three months before and nine months after the tsunami. We thoroughly surveyed portions of the islands of Simushir and Matua, and also did surveys on parts of Ketoi, Yankicha, Ryponkicha, and Rasshua. Tsunami runup in the near-field of the middle Kuril Islands, over a distance of about 200 km, averaged 10 m over 130 locations surveyed and was typically between 5 and 15 m. Local topography strongly affected inundation and somewhat affected runup. Higher runup generally occurred along steep, protruding headlands, whereas longer inundation distances occurred on lower, flatter coastal plains. Sediment transport was ubiquitous where sediment was available-deposit grain size was typically sand, but ranged from mud to large boulders. Wherever there were sandy beaches, a more or less continuous sand sheet was present on the coastal plain. Erosion was extensive, often more extensive than deposition in both space and volume, especially in areas with runup of more than 10 m. The tsunami eroded the beach landward, stripped vegetation, created scours and trim lines, cut through ridges, and plucked rocks out of the coastal plain.
id: 831; 418XP Times Cited:2 Cited References Count:46Y

Fishing from past to present: continuity and resilience of red abalone fisheries on the Channel Islands, California - Braje, Todd J.; Erlandson, Jon M.; Rick, Torben C.; Dayton, Paul K.; Hatch, Marco B. A. (Ecological Applications, 2009)
Archaeological data from coastal shell middens provide a window into the structure of ancient marine ecosystems and the nature of human impacts on fisheries that often span millennia. For decades Channel Island archaeologists have studied Middle Holocene shell middens visually dominated by large and often whole shells of the red abalone (Haliotis rufescens). Here we use modern ecological data, historical accounts, commercial red abalone catch records, and zooarchaeological data to examine long-term spatial and temporal variation in the productivity of red abalone fisheries on the Northern Channel Islands, California (USA). Historical patterns of abundance, in which red abalone densities increase from east to west through the islands, extend deep into the Holocene. The correlation of historical and archaeological data argue for long-term spatial continuity in productive red abalone fisheries and a resilience of abalone populations despite dramatic ecological changes and intensive human predation spanning more than 8000 years. Archaeological, historical, and ecological data suggest that California kelp forests and red abalone populations are structured by a complex combination of top-down and bottom-up controls.
id: 2060; PT: J; UT: WOS:000266281400008

Fishing up the Food Web?: 12,000 Years of Maritime Subsistence and Adaptive Adjustments on California's Channel Islands - Erlandson, Jon M.; Rick, Torben C.; Braje, Todd J. (Pacific Science, 2009)
Archaeologists working on California's northern Channel Islands have produced an essentially continuous record of Native American fishing and nearshore ecological changes spanning die last 12,000 years. To search for evidence of Pauly's "fishing down the foodweb" pattern typical of recent historical fisheries, we analyzed variation in the dietary importance of major marine faunal classes (shellfish, fish, marine mammals) on the islands through time. Faunal data suggest that the Island Chumash and their predecessors focused primarily on low-trophic-level shellfish during the Early and Middle Holocene, before shifting their economic focus to finfish and pinnipeds during the Late Holocene. Replicated in faunal sequences from the adjacent mainland, this trans-Holocene pattern suggests that Native Americans fished Lip the food web, a strategy that may have been more sustainable and had fewer ecological repercussions. Emerging technological data suggest, however, that some of the earliest Channel Islanders focused more heavily on higher-trophic-level animals, including marine mammals, seabirds, and waterfowl. These data emphasize the differences between the primarily subsistence-based foraging strategies of ancient Channel Islanders and the globalized market-based fisheries of modern and historic times, with important implications for understanding the long-term evolution and historical ecology of marine ecosystems.
id: 2059; PT: J; UT: WOS:000270849400011

Formal definition and dating of the GSSP (Global Stratotype Section and Point) for the base of the Holocene using the Greenland NGRIP ice core, and selected auxiliary records RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfus; Rasmussen, Sune Olander; Popp, Trevor; Steffensen, Jorgen-Peder; Gibbard, Phil; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les C.; Hughen, Konrad; et al. (Journal of Quaternary Science, 2009)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an abrupt shift in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11 700 calendar yr b2k (before AD 2000) for the base of the Holocene, with a maximum counting error of 99 yr. A proposal that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) has been ratified by the International Union of Geological Sciences. Five auxiliary stratotypes for the Pleistocene-Holocene boundary have also been recognised. Copyright (C) 2008 John Wiley & Sons, Ltd.
id: 1989; PT: J; UT: WOS:000262615700002

Fragmentary Evidence of Great-Earthquake Subsidence during Holocene Emergence, Valdivia Estuary, South Central Chile - Nelson, Alan R.; Kashima, Kaoru; Bradley, Lee-Ann (Bulletin of the Seismological Society of America, 2009)
A reconnaissance of Holocene stratigraphy beneath fringing marshes of the Valdivia estuary, where an M 9.5 earthquake caused 1-2 m of regional coseismic subsidence in 1960, shows only fragmentary evidence of prehistoric coseismic subsidence. In most of the 150 hand-driven cores that were examined, a distinct unconformity separates 0.5-1.5 m of late Holocene tidal and floodplain mud, peat, and sand from underlying middle Holocene subtidal mud and sand. At the Las Coloradas site, where stratigraphy is best preserved, two A horizons of marsh and meadow soils abruptly overlain by sand and mud probably record coseismic subsidence shortly followed by tsunamis. The amount of subsidence during the earthquakes proved difficult to reconstruct with a diatom transfer function because of differences between modern and fossil diatom assemblages. Maximum (14)C ages on macrofossils from the two A horizons at the Las Coloradas site of 1.7-1.3 ka and 2.7-1.7 ka allow correlation of the younger horizon with either of two of six (14)C-dated A horizons buried by tsunami sand or post-tsunami tidal sand 200 km to the south at Maullin, and with a lake-wide mass wasting event in Lago Puyehue, 100 km to the southeast. Tidal records of prehistoric coseismic subsidence at Valdivia are scarce because of a sea-level fall of 3-8 m over the past 6000 years, erosion of marsh and meadow soils during subsidence-induced flooding of the estuary, and largely complete land-level recovery during cycles of coseismic subsidence and postseismic uplift.
id: 2020; PT: J; UT: WOS:000266181100006

From Sheep To (Some) Horses: 4500 Years Of Herd Structure At The Pastoralist Settlement of Begash (southeastern Kazakhstan) - Frachetti, M. D.; Benecke, N. (Antiquity, 2009)
id: 834

High mitogenomic evolutionary rates and time dependency - Subramanian, Sankar; Denver, Dee R.; Millar, Craig D.; Heupink, Tim; Aschrafi, Angelique; Emslie, Steven D.; Baroni, Carlo; Lambert, David M. (Trends in Genetics, 2009)
Using entire modern and ancient mitochondrial genomes of Adelie penguins (Pygoscelis adeliae) that are up to 44000 years old, we show that the rates of evolution of the mitochondrial genome are two to six times greater than those estimated from phylogenetic comparisons. Although the rate of evolution at constrained sites, including nonsynonymous positions and RNAs, varies more than twofold with time (between shallow and deep nodes), the rate of evolution at synonymous sites remains the same. The time-independent neutral evolutionary rates reported here would be useful for the study of recent evolutionary events.
id: 1917; PT: J; NR: 27; TC: 19; J9: TRENDS GENET; PG: 5; GA: 518TW; UT: WOS:000271717800004

Holocene Adelie penguin diet in Victoria Land, Antarctica - Lorenzini, Sandra; Olmastroni, Silvia; Pezzo, Francesco; Salvatore, Maria Cristina; Baroni, Carlo (Polar Biology, 2009)
Ornithogenic soils (N = 97) dated up to 7000 Before Present (Ebp) were sampled in 16 relict and modern breeding colonies of Ad,lie penguin along the Victoria Land coast (Ross Sea, Antarctica). Taxonomic identification of fish otoliths (N = 677) recovered in these soils allowed to identify the Antarctic silverfish as the most eaten prey (90.1%) throughout the investigated period. A morphometric analysis of the otoliths revealed that the Ad,lie penguin primarily selected prey averaging 67.23 +/- A 23 mm of standard length. Temporal distribution of Pleuragramma antarcticum showed a peak between 2,000 and 4,000 years bp, a period corresponding to the maximum spread of Ad,lie penguin in the Victoria Land. Possible explanations of the variations of the abundance of the fish prey in the diet are discussed in the context of the paleoclimatic events and as possible consequences of dietary shifts due to the temporal variation of prey availability in the Ross Sea ecosystem.
id: 1916; PT: J; NR: 60; TC: 2; J9: POLAR BIOL; PG: 10; GA: 457FQ; UT: WOS:000266914300013

Human impacts, climate change, and aquatic ecosystem response during the past 2000 yr at Lake Wandakara, Uganda - Russell, James M.; McCoy, S. J.; Verschuren, D.; Bessems, I.; Huang, Y. (Quaternary Research, 2009)
Analyses of carbon and hydrogen isotope ratios of terrestrial leaf waxes and the carbon and nitrogen abundance. ratio, and isotopic composition of bulk sediments from Like Wandakara, a crater lake in western Uganda, East Africa. document human and climatic controls on the aquatic system and oil the Surrounding terrestrial vegetation during the past two millennia Our data indicate that Wandakara was a relatively stable, productive lake Surrounded by C(3) vegetation from AD 70 to 1000. Abrupt changes in the delta(13)C of terrestrial leaf waxes indicate a series of abrupt shifts in the relative abundance of C(3) and C(4) vegetation caused by a combination of climate change and human activities around Wandakara beginning at AD 1000. Abrupt shifts in bulk sediment organic geochemistry. particularly C/N ratios and delta(15)N, indicate that human activities at this time caused permanent changes in the limnology of Lake Wandakara. including eutrophication Our results suggest that the biogeochemistry of Like Wandakara was more sensitive to shifting human impacts than to climate variations during the past millennium, highlighting the importance of understanding the intensity of pre-colonial human impacts on Africa's aquatic ecosystems (C) 2009 University of Washington Published by Elsevier Inc All rights reserved
id: 2052; PT: J; UT: WOS:000271254000002

In situ cosmogenic 10Be production-rate calibration from the Southern Alps, New Zealand - Putnam, A. E.; Schaefer, J. M.; Barrell, D. J. A.; Vandergoes, M.; Denton, G. H.; Kaplan, M. R.; Finkel, R. C.; Schwartz, R.; Goehring, B. M.; Kelley, S. E. (Quaternary Geochronology, 2009)
id: 840In pressY

Inputs of Fossil Carbon from Wastewater Treatment Plants to US Rivers and Oceans - Griffith, D. R.; Barnes, R. T.; Raymond, P. A. (Environmental Science & Technology, 2009)
Every day more than 500 million cubic meters of treated wastewater are discharged into rivers, estuaries, and oceans, an amount slightly less than the average flow of the Danube River. Typically, wastewaters have high organic carbon [OC) concentrations and represent a large fraction of total river flow and a higher fraction of river OC in densely populated watersheds. Here, we report the first direct measurements of radiocarbon (C-14) in municipal wastewater treatment plant (WWTP) effluent. The radiocarbon ages of particulate and dissolved organic carbon (POC and DOC) in effluent are old and relatively uniform across a range of WWTPs in New York and Connecticut. Wastewater DOC has a mean radiocarbon age of 1630 +/- 500 years B.P. and a mean delta C-13 of -26.0 +/- 1 parts per thousand. Mass balance calculations indicate that 25% of wastewater DOC is fossil carbon, which is likely derived from petroleum-based household products such as detergents and pharmaceuticals. These findings warrant reevaluation of the "apparent age" of riverine DOC, the total flux of petroleum carbon to U.S. oceans, and OC source assignments in waters impacted by sewage.
id: 1833; 476XR Times Cited:0 Cited References Count:51Y

Intcal09 and Marine09 Radiocarbon Age Calibration Curves, 0-50,000 Years Cal Bp Rid F-4952-2011 Rid B-7298-2008 - Reimer, P. J.; Baillie, M. G. L.; Bard, E.; Bayliss, A.; Beck, J. W.; Blackwell, P. G.; Ramsey, C. Bronk; Buck, C. E.; Burr, G. S.; Edwards, R. L.; Friedrich, M.; Grootes, P. M.; et al. (Radiocarbon, 2009)
The IntCal04 and Marine04 radiocarbon calibration curves have been updated from 12 cal kBP (cal kBP is here defined as thousands of calibrated years before AD 1950), and extended to 50 cal kBP, utilizing newly available data sets that meet the IntCal Working Group criteria for pristine corals and other carbonates and for quantification of uncertainty in both the (14)C and calendar timescales as established in 2002. No change was made to the curves from 0-12 cal kBP. The curves were constructed using a Markov chain Monte Carlo (MCMC) implementation of the random walk model used for IntCal04 and Marine04. The new curves were ratified at the 20th International Radiocarbon Conference in June 2009 and; ire available in the Supplemental Material at www.radiocarbon.org.
id: 1983; PT: J; UT: WOS:000274407500002

Interhemispheric Atlantic seesaw response during the last deglaciation - Barker, S.; Diz, P.; Vautravers, M. J.; Pike, J.; Knorr, G.; Hall, I. R.; Broecker, W. S. (Nature, 2009)
The asynchronous relationship between millennial-scale temperature changes over Greenland and Antarctica during the last glacial period has led to the notion of a bipolar seesaw which acts to redistribute heat depending on the state of meridional overturning circulation within the Atlantic Ocean. Here we present new records from the South Atlantic that show rapid changes during the last deglaciation that were instantaneous (within dating uncertainty) and of opposite sign to those observed in the North Atlantic. Our results demonstrate a direct link between the abrupt changes associated with variations in the Atlantic meridional overturning circulation and the more gradual adjustments characteristic of the Southern Ocean. These results emphasize the importance of the Southern Ocean for the development and transmission of millennial-scale climate variability and highlight its role in deglacial climate change and the associated rise in atmospheric carbon dioxide.
id: 856; Barker, Stephen Diz, Paula Vautravers, Maryline J Pike, Jennifer Knorr, Gregor Hall, Ian R Broecker, Wallace S England Nature. 2009 Feb 26;457(7233):1097-102.Y

Lake Sturgeon Age Validation using Bomb Radiocarbon and Known-Age Fish - Bruch, R. M.; Campana, S. E.; Davis-Foust, S. L.; Hansen, M. J.; Janssen, J. (Transactions of the American Fisheries Society, 2009)
Pectoral fin spines have been the accepted structure for estimating the age of various sturgeon species for nearly 100 years, though other structures have also been used (otoliths, pectoral girdle, scutes, and caudal fulcra). Accuracy of age estimates using any of these structures has not been validated, so we report the first use of bomb radiocarbon (C-14) assays to assess the validity of ages estimated using growth increments on pectoral fin spine and otolith frontal cross sections from lake sturgeon Acipenser fulvescens: we also assessed age estimates from pectoral fin spines of known-age lake sturgeon. Growth increments on pectoral fin spine cross sections underestimated true age of fish older than 14 years and error increased with age, whereas otoliths accurately estimated true age up to at least 52 years. Increment formation on pectoral fin spine and otolith cross sections from juvenile lake sturgeon (ages 2-11) was similar, although pectoral spines were clearer and easier to interpret. A power function (true age = [estimated age](1.054796), where estimated age was determined from pectoral spines; r(2) = 0.98) provides a means for correcting existing age estimates obtained from lake sturgeon pectoral fin spines.
id: 1855; 477EI Times Cited:1 Cited References Count:33Y

Late Holocene Hydrologic and Vegetation Changes at Turneffe Atoll, Belize, Compared with Records from Mainland Central America and Mexico - Wooller, M. J.; Behling, H.; Guerrero, J. L.; Jantz, N.; Zweigert, M. E. (Palaios, 2009)
We present pollen and stable isotope (delta C-13, delta O-18, delta N-15) data from a similar to 4 in core (TNF-1) of primarily mangrove peat taken from Turneffe Atoll, Belize. Radiocarbon (accelerator mass spectrometry) dates show that the record represents ca. 5000 years of sediment accumulation. Vegetation composition varied between dominant mangroves (primarily Rhizophora mangle) and Chenopodiaceae-Amaranthaceae, most likely Salicornia bigelovii. The pollen data, along with inferences from stable isotope analyses of bulk peat and fossil leaf fragments, indicate that marked environmental changes occurred at this location over the past ca. 5000 years. There was a transition between ca. 4100 and 2900 cal yr BP, from vegetation dominated by relatively tall mangroves (R. mangle) to one dominated by Chenopodiaceae-Amaranthaceae and then Myrica, most likely wax myrtle (M. cerifera). These changes bracket a period centered at ca. 3500 calibrated years before present, where there is a peak in the delta O-18 of mangrove leaf fragments. This timing corresponds with other paleoenvironmental records of climate drying in Central America and increases the geographic and habitat scope (i.e., mangrove habitat) of records documenting these changes. Interpretations of shifts in mangrove habitat, however, require consideration of additional environmental influences, including changes in groundwater hydrology and relative inputs of seawater and freshwater (i.e., precipitation) during the Holocene.
id: 1835; 506UH Times Cited:1 Cited References Count:34Y

A late Holocene paleo-productivity record in the western Gulf of Maine, USA, inferred from growth histories of the long-lived ocean quahog (Arctica islandica) - Wanamaker, Alan D. Jr.; Kreutz, Karl J.; Schoene, Bernd R.; Maasch, Kirk A.; Pershing, Andrew J.; Borns, Harold W.; Introne, Douglas S.; Feindel, Scott (INTERNATIONAL JOURNAL OF EARTH SCIENCES, 2009)
To investigate environmental variability during the late Holocene in the western Gulf of Maine, USA, we collected a 142-year-old living bivalve (Arctica islandica) in 2004, and three fossil A. islandica shells of the Medieval Warm Period (MWP) and late MWP / Little Ice Age (LIA) period (corrected C-14(AMS) = 1030 +/- A 78 ad; 1320 +/- A 45 ad; 1357 +/- A 40 ad) in 1996. We compared the growth record of the modern shell with continuous plankton recorder (CPR) time-series (1961-2003) from the Gulf of Maine. A significant correlation (r (2) = 0.55; p < 0.0001) exists between the standardized annual growth index (SGI) of the modern shell and the relative abundance of zooplankton species Calanus finmarchicus. We therefore propose that SGI data from A. islandica is a valid proxy for paleo-productivity of at least one major zooplankton taxa. SGIs from these shells reveal significant periods of 2-6 years (NAO-like) based on wavelet analysis, multitaper method (MTM) analysis and singular spectrum analysis (SSA) during the late Holocene. Based on established physical oceanographic observation in the Gulf of Maine, we suggest that slope water variability coupled with North Atlantic Oscillation (NAO) dynamics is primarily responsible for the observed SGI variability.
Keywords: Arctica islandica; Climate variability; Gulf of Maine; North Atlantic Oscillation (NAO); Paleo-productivity; Shell growth

Late Holocene sea-surface temperature and precipitation variability in northern Patagonia, Chile (Jacaf Fjord, 44 degrees S) - Sepulveda, J.; Pantoja, S.; Hughen, K. A.; Bertrand, S.; Figueroa, D.; Leon, T.; Drenzek, N. J.; Lange, C. (Quaternary Research, 2009)
A high-resolution multi-proxy study including the elemental and isotopic composition of bulk organic matter, land plant-derived biomarkers, and alkenone-based sea-surface temperature (SST) from a marine sedimentary record obtained from the Jacaf Fjord in northern Chilean Patagonia (similar to 44 degrees 20'S) provided a detailed reconstruction of continental runoff, precipitation, and summer SST spanning the last 1750 yr We observed two different regimes of climate variability in our record a relatively dry/warm period before 900 cal yr BP (lower runoff and average SST 1 degrees C warmer than present day) and a wet/cold period after 750 cal yr BP (higher runoff and average SST 1 degrees C colder than present clay). Relatively colder SSTs were found during 750-600 and 450-250 cal yr BP, where the latter period roughly corresponds to the interval defined for the Little Ice Age (LIA) Similar climatic swings have been observed previously in continental and marine archives of the last two millennia from central and southern Chile, suggesting a strong latitudinal sensitivity to changes in the Southern Westerly Winds, the main Source Of precipitation in southern Chile, and validating the regional nature of the LIA Our results reveal the importance of the Chilean fjord system for recording climate changes of regional and global significance (C) 2009 University of Washington Published by Elsevier Inc All rights reserved.
id: 1858; 512MQ Times Cited:0 Cited References Count:53Y

Late Pleistocene-Holocene evolution of the northern shelf of the Sea of Marmara - Cagatay, M. N.; Eris, K.; Ryan, W. B. F.; Sancar, U.; Polonia, A.; Akcer, S.; Biltekin, D.; Gasperini, L.; Gorur, N.; Lericolais, G.; Bard, E. (Marine Geology, 2009)
Chirp sub-bottom profiling, multibeam bathymetric mapping and a combination of faunal and isotopic analysis of molluscs and foraminifera in sediment cores on the northern shelf of the Sea of Marmara (SoM) provide evidence of sea-level excursions, water exchanges between the adjacent Mediterranean and Black Seas, and oscillating salinity over the last 160 ka bp. During the marine isotope stages MIS-2, MIS-3, MIS-4 and MIS-6 the SoM disconnected from the Mediterranean Sea and evolved into a lake. During MIS-1, MIS-5 and MIS-7, the SoM reconnected and became salty once again. Sapropels formed shortly after each invasion of Mediterranean saltwater observed in our cores. Concurrent suboxic-dysoxic conditions prevailed over quite shallow substrates on the shelf. Ancient shorelines are pervasive at -85 m on the northern shelf and in the region of Prince Islands coincident with the elevation of the modern bedrock sill in the Canakkale (Dardanelles) Strait. At times when global (eustatic) sea level dropped below this sill, the surface of the SoM stabilized at its outlet and freshened. Thus this particular shoreline is interpreted as the edge of the most recent SoM lake that existed from about 75 ka bp to 12 ka bp. The freshening is observed in very light (-6 parts per thousand) values of delta O-18 measured on freshwater molluscs and the complete absence of foraminifera. Two brief lacustrine episodes during MIS-5 suggest that the level of the Canakkale outlet might have been as shallow as -50 m in the past, a likelihood supported by submerged terraces along its margins bounding the modern central channel and the presence of an euryhaline biofacies in Unit L4.1 corresponding to MIS-5b. delta O-18 profiles and carbon-14 dating show that salinification of the SoM and the blossoming of bioherms evolved rapidly after the latest connection with the Mediterranean at 12 ka bp. However, freshening proceeded more slowly once the connection was severed. (C) 2009 Elsevier B.V. All rights reserved.
id: 1843; 500UN Times Cited:1 Cited References Count:80Y

Mangrove ecosystem changes during the Holocene at Spanish Lookout Cay, Belize - Monacci, N. M.; Meier-Grunhagen, U.; Finney, B. P.; Behling, H.; Wooller, M. J. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
Mangroves are halophytic plants living at the land-sea interface and are therefore natural trackers of sea-level. Multiple proxies of a continuous (8 m) mangrove peat core (BT-79) from Spanish Lookout Cay, Belize illustrate mangrove ecosystem changes during the Holocene. Radiocarbon measurements show this site was colonized by mangroves similar to 8000 cal. yrs BP, with a significant decrease in the peat accumulation rate from similar to 6000 to 1000 cal. yrs BR Stratigraphic characteristics of this peat core such as bulk density, magnetic susceptibility, and loss on ignition show relative uniformity, inferring an uninterrupted mangrove ecosystem during a majority of the Holocene. This is supported by pollen data from BT-79 that show that the site has been consistently dominated by Rhizophora mangle (red mangrove), with Avicennia germinans (black mangrove) and Laguncularia racemosa (white mangrove) present as well. Subfossil R. mangle leaves are used for stable nitrogen, carbon, and oxygen isotope (delta N-15, delta C-13, and delta O-18) analyses. delta N-15 and delta C-13 values provide a proxy of this plant's past physiology and stand structure showing that dwarf (delta N-15
id: 1834; 496QP Times Cited:1 Cited References Count:50Y

Methane accumulation and release from deep peat: Measurements, conceptual models, and biogeochemical significance - Glaser, Paul H.; Chanton, Jeffrey P. (Carbon Cycling in Northern Peatlands, 2009)
Northern peatlands account for more than half the world's wetlands but are currently estimated to contribute only about a third of the total methane emissions from all wetlands. Increasing data on the dynamics of methane gas bubbles in peat deposits now suggest that these estimates may need to be scaled upward. Rates of methanogenesis may remain high in deep peat strata because of the downward transport of labile root exudates permitting the widespread production of gas bubbles. Recent investigations using an array of methods have reported free-phase gas volumes of 10–20% within both deep and shallow peat strata and episodic ebullition fluxes exceeding 35 g CH4 m−2 per event. Gas bubbles accumulate in overpressured pockets that episodically rupture in response to steep declines in atmospheric pressure or declining water tables. Although these ebullition fluxes are highly variable in both time and space, they appear to dominate the annual methane emissions from northern peatlands and represent a major and underappreciated element of the global methane cycle.
id: 1972
Keywords: Carbon cycle (Biogeochemistry)—Northern Hemisphere; Carbon sequestration—Northern Hemisphere; Greenhouse gases—Northern Hemisphere; Peatlands—Environmental aspects—Northern Hemisphere

Molluscs and mass harvesting in the Middle Holocene: Prey size and resource ranking on San Miguel Island, Alta California - Braje, Todd J.; Erlandson, Jon M. (California Archaeology, 2009)
id: 2070

A multi-proxy paleolimnological reconstruction of Holocene climate conditions in the Great Basin, United States - Reinemann, Scott A.; Porinchu, David F.; Bloom, Amy M.; Mark, Bryan G.; Box, Jason E. (Quaternary Research, 2009)
A sediment core spanning ~†7000†cal yr BP recovered from Stella Lake, a small sub-alpine lake located in Great Basin National Park, Nevada, was analyzed for subfossil chironomids (non-biting midges), diatoms, and organic content (estimated by loss-on-ignition (LOI)). Subfossil chironomid analysis indicates that Stella Lake was characterized by a warm, middle Holocene, followed by a cool "Neoglacial" period, with the last two millennia characterized by a return to warmer conditions. Throughout the majority of the core the Stella Lake diatom-community composition is dominated by small, periphytic taxa which are suggestive of shallow, cool, alkaline, oligotrophic waters with extensive seasonal ice cover. A reconstruction of mean July air temperature (MJAT) was developed by applying a midge-based inference model for MJAT (two-component WA-PLS) consisting of 79 lakes and 54 midge taxa (rjack2†=†0.55, RMSEP†=†0.9∞C). Comparison of the chironomid-inferred temperature record to existing regional paleoclimate reconstructions suggests that the midge-inferred temperatures correspond well to regional patterns. This multi-proxy record provides valuable insight into regional Holocene climate and environmental conditions by providing a quantitative reconstruction of peak Holocene warmth and aquatic ecosystem response to these changes in the Great Basin, a region projected to experience increased aridity and higher temperatures.
id: 880Y

The Mysterious C-14 Decline - Broecker, W. (Radiocarbon, 2009)
Fundamental to the field of radiocarbon dating is not only the establishment of the temporal record of the calendar age-radiocarbon age offsets but also the development of an understanding of their cause. Although part of the decline in the magnitude of this offset over the past 40,000 can be explained by a drop in C-14 production rate associated with a progressive increase in the strength of the Earth's magnetic shielding, it is clear that changes in the distribution of C-14 among the Earth's active carbon reservoirs are also required. In particular, the steep 15% decline in the C-14 to C ratio in atmospheric CO2 and surface ocean Sigma CO2,. which occurred in a 3 kyr-duration interval marking the onset of the last deglaciation, appears to require that a very large amount (at least 5000 gigatons) of C-14-deficient carbon was transferred to or within the ocean during this time interval. As no chemical or stable isotope anomaly associated with this injection appears in either the marine sediment or polar ice records, this injection must involve a transfer within the ocean (i.e. a mixing of 2 ocean reservoirs, one depleted in C-14 and the other enriched in C-14). Although evidence for the existence of a salt-stabilized glacial-age abyssal ocean reservoir exists, a search based on benthic-planktic age differences and C-13 measurements appears to place a limit on its size well below that required to account for the steep C-14 decline.
453wfTimes Cited:18Cited References Count:30

The nature and origin of decadal to millennial scale climate variability in the southern tropics of South America - Baker, P. A.; Fritz, S. C.; Burns, S. J.; Ekdahl, E.; Rigsby, C. A. (Past Climate Variability from the Last Glacial Maximum to the Holocene in South America and Surrounding Regions, 2009)
id: 843

Oceanographic and climatologic controls on the compositions and fluxes of biogenic materials in the water column and sediments of the Cariaco Basin over the Late Holocene - Goñi, M. A.; Aceves, H.; Benitez-Nelson, B.; Tappa, E.; Thunell, R.; Black, D. E.; Muller-Karger, F.; Astor, Y.; Varela, R. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
Materials collected by sediment traps over a 3-y period and sedimentary horizons from a gravity core covering the last 6000y were used to investigate the effects of climate-related processes such as wind-driven upwelling and regional rainfall on the production, export and burial of particulate organic matter in the Cariaco Basin. A variety of chemical analyses, including organic carbon and nitrogen, biogenic opal, calcite, lithogenic contents, stable carbon isotopic ratios of organic matter and the yields of CuO reaction products derived from distinct biochemicals such as amino acids, fatty acids and lignins, were carried out for this purpose. Principal component analyses were used to investigate the trends in this multivariate data set. These analyses reveal marked temporal differences in the composition of the materials sinking through the water column, which were related to distinct oceanographic and climatic forcings. For example, autorchthonous fluxes, characterized by elevated contents of organic carbon and opal as well as high yields of amino acid and fatty acid reaction products, displayed peaks during periods of intense wind-driven upwelling. In contrast, allochthonous materials, characterized by elevated lithogenic contents and elevated yields of lignin-derived products, were more important during periods of high rainfall, low wind and enhanced stratification. In addition to the strong seasonal contrasts, there was significant temporal variability at both shorter (monthly) and longer (inter-annual) time scales. Hence, other factors, such as zooplankton grazing and El Nino effects on local climatology, may also be important. Examination of the gravity core record yielded several significant trends. For example, there was a marked increase in sediment accumulation rates from 5000 to ca. 700 y before present with concomitant increases in the concentrations of organic carbon, opal and most biomarkers. These results suggest that the Cariaco Basin experienced a marked increase in primary productivity and particle flux to the underlying sediments since the Holocene Thermal Maximum. Also within the sedimentary record, we observed distinct variations in the relative contributions of autochthonous and allochthonous organic matter. The frequency of these variations is roughly 1500y and appears to match ice-rafted debris records from the North Atlantic. Such coincidence indicates cold periods within the Holocene, which are related to minima in insolation, may have led to the southern migration of the inter-tropical convergence zone and the enhancement of wind-driven upwelling, primary productivity and autochthonous organic matter flux to the seabed in the Cariaco Basin. Alternatively, during warm periods, the opposite climatic conditions would have increased both the thermal stratification of the water column and average rainfall in the Cariaco Basin, leading to elevated inputs of allochthonous materials. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1871; 430SK Times Cited:0 Cited References Count:69Y

A Paleocoastal Shell Midden at Seal Cave (CA-SMI-604), San Miguel Island, California - Erlandson, Jon M.; Braje, Todd J.; Rick, Torben C.; Davis, Troy; Southon, Troy (Proceedings of the Seventh California Islands Symposium, 2009)
id: 2075

Partitioning of organic matter in continental margin sediments among density fractions - Wakeham, S. G.; Canuel, E. A.; Lerberg, E. J.; Mason, P.; Sampere, T. P.; Bianchi, T. S. (Marine Chemistry, 2009)
Hydrodynamic processes sort and redistribute organic matter (OM) and minerals on continental margins. Density fractionations were conducted on sediments from diverse margins (Mexico margin, Gulf of Mexico, Mississippi River delta, Eel River margin) to investigate the nature, provenance and age of OM among density fractions. Mass. elemental (C and N), lignin, and surface area distributions, as well as stable carbon and radiocarbon isotopic compositions were measured, The lowest density fractions (2.5 g cm(-3)) were OC-poor (%OC -200 parts per thousand). Ratios of vanillic acid to vanillin (Ad/Al)v among lignin oxidation products increase with increasing particle density suggesting variable lignin sources or selective degradation of lignin among the different density fractions. (C) 2009 Elsevier B.V. All rights reserved.
id: 1844; 521ZI Times Cited:0 Cited References Count:99Y

Photochemical changes in chemical markers of sedimentary organic matter source and age - Mayer, L. M.; Schick, L. L.; Bianchi, T. S.; Wysocki, L. A. (Marine Chemistry, 2009)
Several chemical markers of organic matter source and age are shown to be susceptible to light-induced alteration. To test for the photochemical lability of markers previously employed for sediments from the Louisiana Coastal zone, we subjected sediments under resuspension conditions to Simulated Sunlight, and monitored changes in ON and Br:OC ratios, delta C-13, Delta C-14, and lignin composition. Markers of terrigenous origin (high C:N, lignin) decreased and delta C-13 became enriched in sediments containing primarily terrigencrus organic matter, while a marker of marine organic matter (Br:OC) decreased in samples containing significant contributions from this source. Preferential loss of C-14 from all sediments indicated enhanced photochemical lability of organic matter of relatively recent origin, consistent with the changes in chemical markers. Most, but not all, experimental alterations are consistent with field distributions of these markers. Relatively small experimental changes in the markers in combination with confounding processes in the environment, however. prevent these parallel trends from providing any more than a consistency test for the importance of photochemical reactions in this region. (C) 2009 Elsevier B.V. All rights reserved.
id: 793; 425QO Times Cited:0 Cited References Count:40Y

Pre-Columbian settlement of Carriacou, West Indies - Fitzpatrick, S. M.; Kappers, M.; Kaye, Q.; Giovas, C. M.; LeFebvre, M. J.; Harris, M. H.; Burnett, S.; Pavia, J. A.; Marsaglia, K.; Feathers, J. (Journal of Field Archaeology, 2009)
id: 830

Rapid Response of a Marine Mammal Species to Holocene Climate and Habitat Change - de Bruyn, Mark; Hall, Brenda L.; Chauke, Lucas F.; Baroni, Carlo; Koch, Paul L.; Hoelzel, A. Rus (Plos Genetics, 2009)
Environmental change drives demographic and evolutionary processes that determine diversity within and among species. Tracking these processes during periods of change reveals mechanisms for the establishment of populations and provides predictive data on response to potential future impacts, including those caused by anthropogenic climate change. Here we show how a highly mobile marine species responded to the gain and loss of new breeding habitat. Southern elephant seal, Mirounga leonina, remains were found along the Victoria Land Coast (VLC) in the Ross Sea, Antarctica, 2,500 km from the nearest extant breeding site on Macquarie Island (MQ). This habitat was released after retreat of the grounded ice sheet in the Ross Sea Embayment 7,500-8,000 cal YBP, and is within the range of modern foraging excursions from the MQ colony. Using ancient mtDNA and coalescent models, we tracked the population dynamics of the now extinct VLC colony and the connectivity between this and extant breeding sites. We found a clear expansion signal in the VLC population similar to 8,000 YBP, followed by directional migration away from VLC and the loss of diversity at similar to 1,000 YBP, when sea ice is thought to have expanded. Our data suggest that VLC seals came initially from MQ and that some returned there once the VLC habitat was lost, similar to 7,000 years later. We track the founder-extinction dynamics of a population from inception to extinction in the context of Holocene climate change and present evidence that an unexpectedly diverse, differentiated breeding population was founded from a distant source population soon after habitat became available.
id: 1914; PT: J; NR: 58; TC: 11; J9: PLOS GENET; PG: 11; GA: 486SZ; UT: WOS:000269219500031

Recent occurrence of large jokulhlaups at Lake Tuborg, Ellesmere Island, Nunavut - Lewis, Ted; Francus, Pierre; Bradley, Raymond S. (Journal of Paleolimnology, 2009)
The varved sediment record from glacially-fed Lake Tuborg, Ellesmere Island, Nunavut, shows that only three large jokulhlaups have occurred there in the last millennium: 2003, 1993, and 1960. Detailed analyses of sediment microstructure and particle size, combined with in-situ hydrometeorological and limnological process studies, allowed jokulhlaup facies identification and discrimination from deposits from other processes. Deposits from large jokulhlaups are anomalously thick, typically lack internal structure, have sharp bases, and fine upwards. The ice-dammed lake above Lake Tuborg (the source of the jokulhlaups) likely changed its drainage style in 1960, from ice-dam overtopping to ice-dam flotation and glacial tunnel enlargement by melt widening, which allowed the lake to drain completely and catastrophically. Complete drainage of ice-dammed lakes by ice-dam flotation is rare in the region is due to the pervasiveness of cold-based ice. Twentieth century warming is likely responsible for some combination of dam thinning, lake expansion and deepening, and changing the thermal regime at the base of the dam. Anomalously thick individual varves were periodically deposited beginning in the nineteenth century, and their thickness increased with time. This likely reflects a combination of increased ice dam overtopping, subaqueous slope failures, sediment availability and rising air temperature. The varve record presented here significantly correlates with a previous, shorter record from Lake Tuborg. However, generally weak correlations are found between the new varve time series, regional records of air temperature, and glacial melt from ice cores on the Agassiz Ice Cap. It is hypothesized that on short timescales, sedimentation at the coring location reflects a complex and varying integration of multiple hydroclimatic, geomorphic and limnologic influences.
id: 1998; PT: J; UT: WOS:000263543300006

Recently exposed vegetation reveals Holocene changes in the extent of the Quelccaya Ice Cap, Peru - Buffen, Aron M.; Thompson, Lonnie G.; Mosley-Thompson, Ellen; Huh, Kyung In (QUATERNARY RESEARCH, 2009)
Radiocarbon dating of well-preserved, in-place vegetation exposed by the retreating Quelccaya Ice Cap of southeastern Peru constrains the last time the ice cap's extent was smaller than at present. Seventeen plant samples from two sites along the central western margin collectively date to 4700 and 5100 cal yr BP and strongly indicate that current ice cap retreat is unprecedented over the past similar to 5 millennia. Seventeen vegetation samples interbedded in a nearby clastic sedimentary sequence suggest ice-free conditions at this site from similar to 5200 to at least similar to 7000 cal yr BP, and place minimum constraint on early- to mid-Holocene ice cap extent. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
Keywords: 14C dating; Andes; Climate change; Glacier retreat; Holocene; Peru; Quelccaya Ice Cap; South America; Tropical glaciers

Regional beryllium-10 production rate calibration for late-glacial northeastern North America - Balco, Greg; Briner, Jason; Finkel, Robert C.; Rayburn, John A.; Ridge, John C.; Schaefer, Joerg M. (Quaternary Geochronology, 2009)
The major uncertainty in relating cosmogenic-nuclide exposure ages to ages measured by other dating methods comes from extrapolating nuclide production rates measured at globally scattered calibration sites to the sites of unknown age that are to be dated. This uncertainty can be reduced by locating production rate calibration sites that are similar in location and age to the sites to be dated. We use this strategy to reconcile exposure age and radiocarbon deglaciation chronologies for northeastern North America by compiling (10)Be production rate calibration measurements from independently dated late-glacial and early Holocene ice-marginal landforms in this region. 10Be production rates measured at these sites are 6-12% lower than predicted by the commonly accepted global 10Be calibration data set used with any published production rate scaling scheme. In addition, the regional calibration data set shows significantly less internal scatter than the global calibration data set. Thus, this calibration data set can be used to improve both the precision and accuracy of exposure dating of regional late-glacial events. For example, if the global calibration data set is used to calculate exposure ages, the exposure-age deglaciation chronology for central New England is inconsistent with the deglaciation chronology inferred from radiocarbon dating and varve stratigraphy. We show that using the regional data set instead makes the exposure age and radiocarbon chronologies consistent. This increases confidence in correlating exposure ages of ice-marginal landforms in northeastern North America with glacial and climate events dated by other means. (c) 2008 Elsevier Ltd. All rights reserved.
id: 2034; PT: J; UT: WOS:000265163500003

Sinking deltas due to human activities - Syvitski, J. P. M.; Kettner, A. J.; Overeem, I.; Hutton, E. W. H.; Hannon, M. T.; Brakenridge, G. R.; Day, J.; Vorosmarty, C.; Saito, Y.; Giosan, L.; Nicholls, R. J. (Nature Geoscience, 2009)
Many of the world's largest deltas are densely populated and heavily farmed. Yet many of their inhabitants are becoming increasingly vulnerable to flooding and conversions of their land to open ocean. The vulnerability is a result of sediment compaction from the removal of oil, gas and water from the delta's underlying sediments, the trapping of sediment in reservoirs upstream and floodplain engineering in combination with rising global sea level. Here we present an assessment of 33 deltas chosen to represent the world's deltas. We find that in the past decade, 85% of the deltas experienced severe flooding, resulting in the temporary submergence of 260,000 km(2). We conservatively estimate that the delta surface area vulnerable to flooding could increase by 50% under the current projected values for sea-level rise in the twenty-first century. This figure could increase if the capture of sediment upstream persists and continues to prevent the growth and buffering of the deltas.
id: 799; 501BW Times Cited:2 Cited References Count:38; YY

Southward movement of the Pacific intertropical convergence zone AD 1400-1850 - Sachs, J. P.; Sachse, D.; Smittenberg, R. H.; Zhang, Z. H.; Battisti, D. S.; Golubic, S. (Nature Geoscience, 2009)
Tropical rainfall patterns control the subsistence lifestyle of more than one billion people. Seasonal changes in these rainfall patterns are associated with changes in the position of the intertropical convergence zone, which is characterized by deep convection causing heavy rainfall near 10 degrees N in boreal summer and 3 degrees N in boreal winter. Dynamic controls on the position of the intertropical convergence zone are debated, but palaeoclimatic evidence from continental Asia, Africa and the Americas suggests that it has shifted substantially during the past millennium, reaching its southernmost position some time during the Little Ice Age (AD 1400-1850). However, without records from the meteorological core of the intertropical convergence zone in the Pacific Ocean, quantitative constraints on its position are lacking. Here we report microbiological, molecular and hydrogen isotopic evidence from lake sediments in the Northern Line Islands, Galapagos and Palau indicating that the Pacific intertropical convergence zone was south of its modern position for most of the past millennium, by as much as 500 km during the Little Ice Age. A colder Northern Hemisphere at that time, possibly resulting from lower solar irradiance, may have driven the intertropical convergence zone south. We conclude that small changes in Earth's radiation budget may profoundly affect tropical rainfall.
id: 847; 497LS Times Cited:5 Cited References Count:45Y

Surculichnus bifurcauda n. igen., n. isp., a trace fossil from Late Pleistocene glaciolacustrine varves of the Connecticut River Valley, USA, attributed to notostracan crustaceans based on neoichnological experimentation - Knecht, Richard J.; Benner, Jacob S.; Rogers, Christopher; Ridge, John C. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
New trace fossils found in the Late Pleistocene glaciolacustrine varves of the Connecticut River Valley, Vermont, USA represent the first known notostracan presence in glacial Lake Hitchcock. These unique trace fossils warrant a new ichnogenus and ichnospecies Surculichnus bifurcauda. The New England Varve Chronology (NEVC) constrains the initial presence of S. bifurcauda at similar to 13.3-13.2 kyr. The morphology of S. bifurcauda correlates well with notostracan characteristics and behavior. Sieving of bedding planes that contained S. bifurcauda produced one chitinous fossil that is suggestive of a notostracan telson. Neoichnological experimentation was conducted with the species Triops longicaudatus. During the subadult stage, T longicaudatus produced traces representative of locomotion and feeding behaviors, and at the adult stage reproduced S. bifurcauda, as well as Rusophycus. Possible explanations for the productions of these traces are egg laying or predation behaviors that are both related to maturity. Further research in the paleo- and modern ecology of glacial and nearctic lakes may shed more light on the maker of S. bifurcauda. (C) 2008 Elsevier B.V. All rights reserved.
id: 2036; PT: J; UT: WOS:000264010000008

Timing of post-glacial reinhabitation and ecological development of two New England, USA, drainages based on trace fossil evidence - Benner, Jacob S.; Ridge, John C.; Knecht, Richard J. (Palaeogeography Palaeoclimatology Palaeoecology, 2009)
Trace fossils as paleoecological and paleobiogeographical tools in Pleistocene glaciolacustrine sediments have been largely ignored. Combining high resolution varve stratigraphy with trace fossil data can lead to refined paleoenvironmental interpretations during times of rapid climate change. Based on trace fossils from glaciolacustrine varves in the Connecticut and Merrimack River valleys, a new timeline for the reinhabitation of New England by fish and associated invertebrates has been constructed. In addition, it appears that colonization of the recently deglaciated environments occurred in at least four successional stages. If these stages can be recognized elsewhere, it may be possible to accurately model other postglacial migrations using trace fossils and varve chronostratigraphy. (C) 2008 Elsevier B.V. All rights reserved.
id: 2035; PT: J; UT: WOS:000264010000007

Towards a quantitative and independent reconstruction of Holocene temperature and precipitation in Northern Great Plains using novel organic proxies - Toney, J. L.; Huang, Y.; Fritz, S. C.; Baker, P.; Grimm, E. C.; Nyren, P. E. (Eos, Transactions, American Geophysical Union, 2009)
id: 891

A trans-Holocene archaeological record of Guadalupe fur seals (Arctocephalus townsendi) on the California coast - Rick, Torben C.; DeLong, Robert L.; Erlandson, Jon M.; Braje, Todd J.; Jones, Terry L.; Kennett, Douglas J.; Wake, Thomas A.; Walker, Phillip L. (Marine Mammal Science, 2009)
id: 2061; PT: J; UT: WOS:000265228700018

Wind-Driven Upwelling in the Southern Ocean and the Deglacial Rise in Atmospheric CO2 - Anderson, R. F.; Ali, S.; Bradtmiller, L. I.; Nielsen, S. H. H.; Fleisher, M. Q.; Anderson, B. E.; Burckle, L. H. (Science, 2009)
Wind-driven upwelling in the ocean around Antarctica helps regulate the exchange of carbon dioxide (CO2) between the deep sea and the atmosphere, as well as the supply of dissolved silicon to the euphotic zone of the Southern Ocean. Diatom productivity south of the Antarctic Polar Front and the subsequent burial of biogenic opal in underlying sediments are limited by this silicon supply. We show that opal burial rates, and thus upwelling, were enhanced during the termination of the last ice age in each sector of the Southern Ocean. In the record with the greatest temporal resolution, we find evidence for two intervals of enhanced upwelling concurrent with the two intervals of rising atmospheric CO2 during deglaciation. These results directly link increased ventilation of deep water to the deglacial rise in atmospheric CO2.
id: 835; 417TP Times Cited:18 Cited References Count:69Y

Antarctic sediment chronology by programmed-temperature pyrolysis: Methodology and data treatment - Rosenheim, B. E.; Day, M. B.; Domack, E.; Schrum, H.; Benthien, A.; Hayes, J. M. (Geochemistry Geophysics Geosystems, 2008)
We report a detailed programmed-temperature pyrolysis/ combustion methodology for radiocarbon (C-14) dating of Antarctic sub-ice shelf sediments. The method targets the autochthonous organic component in sediments that contain a distribution of acid-insoluble organic components from several sources of different ages. The approach has improved sediment chronology in organic-rich sediments proximal to Antarctic ice shelves by yielding maximum age constraints significantly younger than bulk radiocarbon dates from the same sediment horizons. The method proves adequate in determining isotope ratios of the pre-aged carbon end-member; however, the isotopic compositions of the low-temperature measurements indicate that no samples completely avoided mixing with some proportion of pre-aged organic material. Dating the unresolved but desired young end-member must rely on indirect methods, but a simple mixing model cannot be developed without knowledge of the sedimentation rate or comparable constraints. A mathematical approach allowing for multiple mixing components yields a maximum likelihood age, a first-order approximation of the relative proportion of the autochthonous component, and the temperature at which allochthonous carbon begins to volatilize and mix with the autochthonous component. It is likely that our estimation of the cutoff temperature will be improved with knowledge of the pyrolysis kinetics of the major components. Chronology is improved relative to bulk acid-insoluble organic material ages from nine temperature interval dates down to two, but incorporation of inherently more pre-aged carbon in the first division becomes more apparent with fewer and larger temperature intervals.
id: 1847; 284ON Times Cited:5 Cited References Count:27Y

Biodiesel effects on particulate radiocarbon (C-14) emissions from a diesel engine - Bennett, Maren; Volckens, John; Stanglmaier, Rudy; McNichol, Ann P.; Ellenson, William D.; Lewis, Charles W. (JOURNAL OF AEROSOL SCIENCE, 2008)
The relative amount of C-14 in a sample of atmospheric particulate matter (PM), defined as percent modern carbon (pMC), allows the Environmental Protection Agency (EPA) to infer the fraction of PM derived from anthropogenic pollution sources. With increased use of biofuels that contain C-14, the main assumption of the two-source model, that C-14 is solely derived from biogenic emissions, may become invalid. The goal of this study was to determine the C-14 content of PM emitted from an off-highway diesel engine running on commercial grade biodiesel. Tests were conducted with an off-highway diesel engine running at 80% load fueled by various blends of soy-based biodiesel. A dilution tunnel was used to collect PM10 emissions on quartz filters that were analyzed for their C-14 content using accelerator mass spectrometry. A mobility particle sizer and 5-gas analyzer provided supporting information on the particle size distribution and gas-phase emissions. The pMC of PM10 aerosol increased linearly with the percentage of biodiesel present in the fuel. Therefore, PM emissions resulting from increased combustion of biodiesel fuels will likely affect contemporary C-14 apportionment efforts that attempt to split biogenic vs. anthropogenic emissions based on aerosol C-14 content. Increasing the biodiesel fuel content also reduced emissions of total hydrocarbons (THC), PM10 mass, and particulate elemental carbon. Biodiesel had variable results on oxides of nitrogen (NOx) emissions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: biofuel; EC; OC; PM; source apportionment

Changes in the composition of organic matter from prodeltaic sediments after a large flood event (Po River, Italy) - Tesi, T.; Langone, L.; Goñi, M. A.; Miserocchi, S.; Bertasi, F. (Geochimica et Cosmochimica Acta, 2008)
The Po River (Italy) experienced a 100-year flood in October 2000. Surface sediments (0-1 cm) from cross-shelf transects were collected in the Po prodelta area (Adriatic Sea) in December 2000, in order to describe the distribution of organic matter (OM) along the main sediment dispersal system immediately after the flood event. Stations were subsequently reoccupied in October 2001 and April 2002. This sampling program provided a special opportunity to characterize the initial surficial flood deposit and the evolution of its associated OM over the course of 2 years. CuO oxidation, elemental, delta C-13, Delta C-14, and grain-size analyses were carried out to characterize the source, age, and spatial variability of sedimentary OM. Statistical analysis (PERMANOVA) was then applied to investigate temporal changes in different portions of the Po prodelta area. Isotopic and biomarker data suggest that the sedimentary OM in the flood deposit was initially dominated by aged (Delta C-14(Dec-00) = -298.7 +/- 56.3%,), lignin-poor OM (Lambda(Dec-00) = 1.96 +/- 0.33 mg/100 mg OC), adsorbed on the fine material (clay(Dec-00) = 72.1 +/- 4.8%) delivered by the flood. In the 2 years following the flood, post-depositional processes significantly increased the content of lignin (Lambda(Oct-01) = 2.19 +/- 0.51 mg/100 mg OC; Lambda(Apr-02) = 2.61 +/- 0.63 mg/100 mg OC); and coarse material (silt and sand), while decreasing the contributions from aged OC (Delta C-14(Oct-01) = -255.7 +/- 32.8%.; Delta C-14(Apr-02) = -213.2 +/- 30.4%.) and fine fraction (clay(Oct-01) = 54.8 +/- 9.5%; clay(Apr-02) = 44.6 +/- 13.3%). The major changes were observed in the northern and central portions of the prodelta. (c) 2008 Elsevier Ltd. All rights reserved.
id: 888; 290IO Times Cited:4 Cited References Count:66Y

Constraints on the Pleistocene chronology of sediments from the Lomonosov Ridge - O'Regan, M.; King, J.; Backman, J.; Jakobsson, M.; Palike, H.; Moran, K.; Heil, C.; Sakamoto, T.; Cronin, T. M.; Jordan, R. W. (Paleoceanography, 2008)
[1] Despite its importance in the global climate system, age-calibrated marine geologic records reflecting the evolution of glacial cycles through the Pleistocene are largely absent from the central Arctic Ocean. This is especially true for sediments older than 200 ka. Three sites cored during the Integrated Ocean Drilling Program's Expedition 302, the Arctic Coring Expedition ( ACEX), provide a 27 m continuous sedimentary section from the Lomonosov Ridge in the central Arctic Ocean. Two key biostratigraphic datums and constraints from the magnetic inclination data are used to anchor the chronology of these sediments back to the base of the Cobb Mountain subchron ( 1215 ka). Beyond 1215 ka, two best fitting geomagnetic models are used to investigate the nature of cyclostratigraphic change. Within this chronology we show that bulk and mineral magnetic properties of the sediments vary on predicted Milankovitch frequencies. These cyclic variations record "glacial'' and "interglacial'' modes of sediment deposition on the Lomonosov Ridge as evident in studies of ice-rafted debris and stable isotopic and faunal assemblages for the last two glacial cycles and were used to tune the age model. Potential errors, which largely arise from uncertainties in the nature of downhole paleomagnetic variability, and the choice of a tuning target are handled by defining an error envelope that is based on the best fitting cyclostratigraphic and geomagnetic solutions.
id: 868; 281YL Times Cited:22 Cited References Count:55; YY

Cooling and changing seasonality in the Southern Alps, New Zealand during the Antarctic Cold Reversal - Vandergoes, M. J.; Dieffenbacher-Krall, A. C.; Newnham, R. M.; Denton, G. H.; Blaauw, M. (Quaternary Science Reviews, 2008)
A comprehensively C-14 AMS dated pollen and chironomid record from Boundary Stream Tarn provides the first chironomid-derived temperature reconstruction to quantify temperature change during Lateglacial times (17,500-10,000 cal yr BP) in the Southern Alps, New Zealand. The records indicate a ca 1000-year disruption to the Lateglacial warming trend and an overall cooling consistent with the Antarctic Cold Reversal (ACR). The main interval of chironomid-inferred summer temperature depression (similar to 2-3 degrees C) lasted about 700 years during the ACR. Following this cooling event, both proxies indicate a warming step to temperatures slightly cooler than present during the Younger Dryas chronozone (12,900-11,500 cal yr BP). These results highlight a direct linkage between Antarctica and mid-latitude terrestrial climate systems and the largely asynchronous nature of the interhemispheric climate system during the last glacial transition. The greater magnitude of temperature changes shown by the chironomid record is attributed to the response of the proxies to differences in seasonal climate with chironomids reflecting summer temperature and vegetation more strongly controlled by duration of winter or by minimum temperatures. These differences imply stronger seasonality at times during the Lateglacial, which may explain some of the variability between other paleoclimate records from New Zealand and have wider implications for understanding differences between proxy records for abrupt climate change. (C) 2007 Elsevier Ltd. All rights reserved.
293rhTimes Cited:27Cited References Count:64

Coupled North Atlantic slope water forcing on Gulf of Maine temperatures over the past millennium - Wanamaker, Alan D.; Kreutz, Karl J.; öne, Bernd R.; Pettigrew, Neal; Borns, Harold W.; Introne, Douglas S.; Belknap, Daniel; Maasch, Kirk A.; Feindel, Scott (Climate Dynamics, 2008)
To investigate ocean variability during the last millennium in the Western Gulf of Maine (GOM), we collected a 142-year-old living bivalve (Arctica islandica L.) in 2004, and three fossil A. islandica shells (calibrated 14CAMS = 1030 ± 78 ad; 1320 ± 45 ad; 1357 ± 40 ad) for stable isotope and growth increment analysis. A statistically significant relationship exists between modern GOM temperature records [shell isotope-derived (30 m) (r = −0.79; P < 0.007), Prince 5 (50 m) (r = −0.72; P < 0.019), Boothbay Harbor SST (r = −0.76; P < 0.011)], and Labrador Current (LC) transport data from the Eastern Newfoundland Slope during 1993–2003. In all cases, as LC transport increased, GOM water temperatures decreased the following year. Decadal trends in the North Atlantic Oscillation (NAO) and the Atlantic Multidecadal Oscillation (AMO) influence GOM water temperatures in the most recent period, with water temperatures decreasing during NAO and AMO negative modes most likely linked to LC transport and Gulf Stream interaction. Mean shell-derived isotopic changes (δ18Oc) during the last 1,000 years were +0.47‰ and likely reflect a 1–2°C cooling from 1000 ad to present. Based on these results, we suggest that observed cooling in the GOM during the last millennium was due to increased transport and/or cooling of the LC, and decreased Gulf Stream influence on the GOM.

Dogs, humans and island ecosystems: the distribution, antiquity and ecology of domestic dogs (Canis familiaris) on California's Channel Islands, USA - Rick, Torben C.; Walker, Phillip L.; Willis, Lauren M.; Noah, Anna C.; Erlandson, Jon M.; Vellanoweth, Rene L.; Braje, Todd J.; Kennett, Douglas J. (Holocene, 2008)
Archaeologists have made significant contributions to our understanding of ancient island environments, including the timing and implications of the introduction of non-native animals (pigs, chickens, rats, etc.) by humans. Here, we focus on the historical ecology and biogeography of domestic dogs (Canis familiaris) on California's Channel Islands during the Holocene. Dogs are the only animal known unequivocally to have been introduced by Native Americans to the islands, but relatively little is known about their distribution, antiquity or influence on native island fauna and flora. We identified a minimum of 96 dogs from 42 archaeological sites on six of the eight islands. Dogs were present for at least 6000 years and appear to have increased in abundance through time. Our analysis suggests that dogs, along with humans and island foxes (Urocyon littoralis), would have had an impact on native animals and ecosystems, especially breeding birds and marine mammals, togs and island foxes likely competed with one another for food, however, and the impacts of dogs on island ecosystems may have been reduced by the presence of island foxes and the symbiotic relationship between dogs and humans. Dogs have been removed from all but one of the islands today, eliminating one of the few terrestrial carnivores present for most of the Holocene.
id: 2063; PT: J; UT: WOS:000260339000006

Earthquakes generated from bedding plane-parallel reverse faults above an active wedge thrust, Seattle fault zone - Kelsey, Harvey M.; Sherrod, Brian L.; Nelson, Alan R.; Brocher, Thomas M. (Geological Society of America Bulletin, 2008)
A key question in earthquake hazard analysis is whether individual faults within fault zones represent independent seismic sources. For the Seattle fault zone, an upper plate structure within the Cascadia convergent margin, evaluating seismic hazard requires understanding how north-side-up, bedding-plane reverse faults, which generate late Holocene fault scarps, interact with the north-vergent master-ramp thrust and overlying backthrust of the fault zone. A regional uplift at A.D. 900-930 involved an earthquake that nucleated at depth and included slip on both the master-ramp thrust and the backthrust. This earthquake also included slip on some of the
id: 2019; PT: J; UT: WOS:000260737900015

Environmental and Climatic Controls on the Occurrence and Abundance of Long Chain Alkenones in Lakes of the Interior United States - Toney, J. L.; Fritz, S.; Baker, P.; Grim, E.; Nyren, P.; Theroux, S.; Huang, Y. (Eos, Transactions, American Geophysical Union, 2008)
id: 892

Five Crescents from Cardwell: Context and Chronology of Chipped Stone Crescents at CA-SMI-679, San Miguel Island, California - Erlandson, Jon M.; Braje, Todd J. (Pacific Coast Archaeological Society Quarterly, 2008)
id: 2065

The Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) in the NGRIP ice core RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfu's; Rasmussen, Sune Olander; Steffensen, Jorgen-Peder; Popp, Trevor; Gibbard, Philip; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les; Hughen, Konrad; et al. (Episodes, 2008)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an. abrupt shaft in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11,700 yr b2k (before AD2000) for the base of the Holocene, with, an estimated 2 sigma uncertainty of 99 yr: It is proposed that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period).
id: 1988; PT: J; CT: 17th Congress of the International-Union-for-Quaternary-Research; CY: JUL 28-AUG 03, 2007; CL: Cairns, AUSTRALIA; SP: Int Union Quaternary Res; UT: WOS:000258669100017

Growth analysis and age validation of a deepwater Arctic fish, the Greenland halibut (Reinhardtius hippoglossoides) - Treble, M. A.; Campana, S. E.; Wastle, R. J.; Jones, C. M.; Boje, J. (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
The accuracy of age interpretations on a deep-sea, Arctic fish species, the Greenland halibut (Reinhardtius hippoglossoides) was tested using several age validation methods. Consistent annual growth increments were either not formed or not visible in either whole or sectioned otoliths from three fish marked with oxytetracyline and recaptured after 2-4 years at liberty. Bomb radiocarbon assays based on a local reference chronology indicated that both whole and sectioned otoliths underestimated age by 1-15 years, with an average of 6 years. Growth rates estimated using the tag recapture model GROTAG were consistent with growth rates based on the radiocarbon assays and were less than half that of previously reported growth rates. The failure of otolith sections to provide an accurate age is unusual, but may be symptomatic of very slow-growing species with unusually shaped otoliths. Greenland halibut living in the deep-sea, Arctic environment are slower growing and longer lived than previously suspected, suggesting that the age-structured basis for current fisheries management warrants careful examination. Our results highlight the importance of using rigorous tests of ageing accuracy for exploited species and confirm that such age validation methods can be applied successfully in challenging environments such as the deep sea or the Arctic.
id: 806; 322ER Times Cited:3 Cited References Count:56Y

Holocene erosion of the Lesser Himalaya triggered by intensified summer monsoon - Clift, P. D.; Giosan, L.; Biusztajn, J.; Campbell, I. H.; Allen, C.; Pringle, M.; Tabrez, A. R.; Danish, M.; Rabbani, M. M.; Alizai, A.; Carter, A.; Lueckge, A. (Geology, 2008)
Climate is one of the principal controls setting rates of continental erosion. Here we present the results of a provenance analysis of Holocene sediments from the Indus delta in order to assess climatic controls on erosion over millennial time scales. Bulk sediment Nd isotope analysis reveals a number of changes during the late Pleistocene and early Holocene (at 14-20,11-12 and 8-9 ka) away from erosion of the Karakoram and toward more sediment flux from the Himalaya. Radiometric Ar-Ar dating of muscovite and U-Pb dating of zircon sand grains indicate that the Lesser Himalaya eroded relatively more strongly than the Greater Himalaya as global climate warmed and the summer monsoon intensified after 14 ka. Monsoon rains appear to be the primary force controlling erosion across the western Himalaya, at least over millennial time scales. This variation is preserved with no apparent lag in sediments from the delta, but not in the deep Arabian Sea, due to sediment buffering on the continental shelf.
id: 800; 247YL Times Cited:7 Cited References Count:27; YY

Holocene multidecadal- to millennial-scale hydrologic variability on the South American Altiplano - Ekdahl, E. J.; Fritz, S. C.; Baker, P. A.; Rigsby, C. A.; Coley, K. (Holocene, 2008)
Precipitation on the South American Altiplano varies at a range of temporal scales. A long-term secular increase in moisture availability from the early/mid Holocene to the present, driven by increasing summer insolation resulting from precessional changes in the Earth's orbit, has been documented in earlier studies. However, higher frequency Holocene variability is not yet understood. Here we present high-resolution diatom assemblage data from two small Altiplano lakes, Lago Lagunillas and Lago Umayo, indicating changes in effective moisture in the southern tropical Andes at decadal, centennial and millennial timescales throughout the mid to late Holocene. A strong millennial-scale component, similar in pacing to periods of increased ice-rafted debris flux in the North Atlantic, is observed in both lake records, which suggests that regional precipitation and North Atlantic climate variability are coupled at these scales. The interpretation of the higher frequency variability is hampered by the small number of high-resolution continental and marine records for comparison.
id: 842; ISI Document Delivery No.: 341ZR Times Cited: 1 Cited Reference Count: 49 Ekdahl, Erik J. Fritz, Sherilyn C. Baker, Paul A. Rigsby, Catherine A. Coley, KirstinY

Human impacts on ancient shellfish: a 10,000 year record from San Miguel Island, California - Erlandson, Jon M.; Rick, Torben C.; Braje, Todd J.; Steinberg, Alexis; Vellanoweth, Rene L. (Journal of Archaeological Science, 2008)
We use measurements of more than 11,000 marine shells from 41 archaeological components to construct a 10,000 year record of human impacts on ancient mussel and abalone stocks on San Miguel Island, California. General reductions in the mean size of mussel and abalone shells gathered through time are attributed to growing human population and predation pressure. Based on comparison with historically documented changes in shellfish communities caused by the local extinction of sea otters in the 19th century, changes in mean shell size and the abundance of other shellfish species may have been facilitated by Native American predation on sea otters as early as 7500 years ago. Despite having measurable impacts on local ecosystems, Native Americans on San Miguel harvested huge quantities of shellfish throughout the Holocene. Such longterm harvests appear to have been sustained by an early emphasis on fishing at lower trophic levels, by periodically shifting village locations, and by intensifying the use of finfish and sea mammals through time. This pattern of "fishing up the food web" contrasts with many modern fisheries, suggesting that the study of ancient fisheries can help us better manage our own endangered coastal ecosystems. (c) 2008 Elsevier Ltd. All rights reserved.
id: 2064; PT: J; UT: WOS:000257340000006

The last reconnection of the Marmara Sea (Turkey) to the World Ocean: A paleoceanographic and paleoclimatic perspective - McHugh, C. M. G.; Gurung, D.; Giosan, L.; Ryan, W. B. F.; Mart, Y.; Sancar, U.; Burckle, L.; Cagatay, M. N. (Marine Geology, 2008)
During the late glacial, marine isotope Stage 2, the Marmara Sea transformed into a brackish lake as global sea-level fell below the sill in the Dardanelles Strait. A record of the basin's reconnection to the global ocean is preserved in its sediments permitting the extraction of the paleoceanographic and paleoclimatic history of the region. The goal of this study is to develop a high-resolution record of the lacustrine to marine transition of Marmara Sea in order to reconstruct regional and global climatic events at a millennia] scale. For this purpose, we mapped the paleoshorelines of Marmara Sea along the northern, eastern, and southern shelves at Cekmece. Prince Islands, and Imrali, using data from multibeam bathymetry, high-resolution subbottom profiling (chirp) and ten sediment cores. Detailed sedimentologic, biostratigraphic (foraminifers, mollusk, diatoms), X-ray fluorescence geochemical scanning, and oxygen and carbon stable isotope analyses correlated to a calibrated radiocarbon chronology provided evidence for cold and city conditions prior to 15 ka BP, warm conditions of the Bolling-Allerod from similar to 15 to 13 ka BP, a rapid marine incursion at 12 ka BP, still stand of Marmara Sea and sediment reworking of the paleoshorelines during the Younger Dryas at similar to 11.5 to 10.5 ka BP, and development of strong stratification and influx of nutrients as Black Sea waters spilled into Marmara Sea at 9.2 ka BR Stable environmental conditions developed in Marmara Sea after 6.0 ka BP as sea-level reached its present shoreline and the basin floors filled with sediments achieving their present configuration. (C) 2008 Elsevier B.V. All rights reserved.
id: 801; 370ED Times Cited:4 Cited References Count:104; YY

Late Holocene marine productivity changes in Northern Patagonia-Chile inferred from a multi-proxy analysis of Jacaf channel sediments - Rebolledo, Lorena; Sepulveda, Julio; Lange, Carina B.; Pantoja, Silvio; Bertrand, Sbastien; Hughen, Konrad; Figueroae, Dante (Estuarine Coastal and Shelf Science, 2008)
A multi-proxy approach based on organic (organic carbon, alkenones, and C/N) and inorganic geochemical proxies (biogenic opal, inorganic carbon, Fe, Ti, and Ca) preserved in the sediments of the Jacaf channel (CF7-PC33; 44 degrees 21'S, 72 degrees 58'W, 510 m water depth), Chilean fjords, yields evidence of major past productivity fluctuations in accordance with climatic changes over the last similar to 1800 years. The downcore record clearly shows two productivity/climate modes. The first period, prior to 900 cal yr BP, is characterized by decreased marine productivity and a reduced continental signal, pointing to diminished precipitation and runoff. In contrast, the second period between similar to 750 cal yr BP and the late 1800s (top of core) is illustrated by elevated productivity and an increased continental signal, suggesting higher precipitation and runoff. Both time intervals are separated by a relatively abrupt transition of similar to 150 years which roughly coincides with the beginning of the Little Ice Age. The increased content of freshwater diatoms and Chrysophyte cysts that characterize the last 200 years of the latter mode coincides with a significant decrease in the carbonate content of the sediment; together they further indicate increased terrigenous contributions and decreased marine carbonate productivity at the end of the Little Ice Age. The correspondence between our record and other paleoclimate studies carried out in South America and Antarctica demonstrates that the Chilean fjord area of Northern Patagonia is not just sensitive to local climatic variability but also to regional and possibly global variability. (C) 2008 Elsevier Ltd. All rights reserved.
id: 2117; PT: J; TC: 5; J9: ESTUAR COAST SHELF S; UT: WOS:000261562600002

Late Pleistocene freshwater fish (Cottidae) trackways from New England (USA) glacial lakes and a reinterpretation of the ichnogenus Broomichnium Kuhn - Benner, Jacob S.; Ridge, John C.; Taft, Natalia K. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2008)
New trace fossil material from Late Pleistocene glaciolacustrine varves of the Connecticut River Valley, New England, USA represent the first evidence of freshwater sculpin in glacial Lake Hitchcock. Paleobiogeographic data constrain the timing of the last reinhabitation of freshwater cottids from a Wisconsinan glacial refugium. Freshwater sculpin were present in the area of study by ~ 13.7 ky BP, moving approximately 400 km in 5000 yr, and following the ice margin at distances as close as 35 km. The trace fossils warrant erection of a new ichnospecies, Broomichnium flirii isp. nov. Comparison of this new ichnospecies to Broomichnium permianum reveals distinct similarities, and it is possible that the Permian examples of B. permianum also were made by fish, which would reconcile a long-running controversy. Many groups of fish are demersal and make ventral body contact with the substrate and could potentially leave similar traces. Identifying new forms of trace fossils made by fish that use alternative modes of locomotion will prove useful in paleoenvironmental interpretations.
id: 2129

Late Quaternary paleo-lake fluctuations in westernmost Tibet - Amidon, W.; Blard, P.; Avouac, J.; Schneider, T. (2008 Fall Meeting of the American Geophysical Union (AGU 2008), 2008)
id: 1913; TY: CPAPER; NO: Source type: conferencepapers&proceedings; Object type: Conference Paper; CSAUnique: CPI-5461640; AccNum: 5461640(USA)
Keywords: China, People's Rep., Xizang; Paleo studies; Quaternary

Micropaleontologic record of late pliocene and quaternary paleoenvironments in the northern Albemarle embayment, North Carolina, USA - Culver, S. J.; Farrell, K. M.; Mallinson, D. J.; Horton, B. P.; Willard, D. A.; Thieler, E. R.; Riggs, S. R.; Snyder, S. W.; Wehmiller, J. F.; Bernhardt, C. E.; Hillier, C. (Palaeogeography Palaeoclimatology Palaeoecology, 2008)
Micropaleontological data provide a strong actualistic basis for detailed interpretations of Quaternary paleoenvironmental change. The 90 m-thick Quaternary record of the Albemarle Embayment in the mid-Atlantic coastal plain of the USA provides an excellent opportunity to use such an approach in a region where the details of Quaternary environmental change are poorly known. The foraminiferal record in nine cores from the northern Outer Banks, east of Albemarle Sound, North Carolina, indicates the deposition of subhorizontal, mostly open-marine early to late Pleistocene units unconformably upon a basement of late Pliocene reduced-oxygen, fine-grained, shelf-basin deposits. Pollen data record several warm-cool fluctuations within the early to mid-Pleistocene deposits. Diatom data indicate that some fresh and brackish-water units occur within the generally open-marine Pleistocene succession. A channel cut by the paleo-Roanoke River during the last glacial sea-level lowstand occurs in the northern part of the study area. Pollen indicates that the basal fluvial valley fill accumulated in cooler than modern climate conditions in the latest Pleistocene. Overlying silts and muds accumulated under cool climatic, estuarine conditions according to diatom and pollen data. Radiocarbon ages from the estuarine deposits indicate that the bulk of these sediments accumulated during the latest Pleistocene. The estuarine channel-fill deposits are overlain by Holocene open-marine sands deposited as the rising sea transgressed into the estuary approximately 8.5 to 9.0 kyr BR Within the barrier island drill cores of this study, fully marine sedimentation occurred throughout the Holocene. However, immediately west of the present barrier island, mid- to late Holocene estuarine deposits underlie the modern Albemarle Sound. The islands that currently form a continuous barrier across the mouth of Albemarle Sound have a complex history of Holocene construction and destruction and large portions of them may be less than 3 kyr old. The barrier island sands overlie open-marine sands of Colington Shoal in the north and to the south overlie fluvial and marine sand filling paleo-Roanoke tributary valleys. The Pleistocene sediments underlying the northern Outer Banks study area are mainly of open inner to midshelf origin. If, as is likely, sea level continues to rise, a return to such environmental conditions is likely in the near future. (c) 2008 Elsevier B.V. All rights reserved.
id: 815; 331MZ Times Cited:2 Cited References Count:79Y

The most extensive Holocene advance in the Stauning Alper, East Greenland, occurred in the Little Ice Age - Hall, B. L.; Baroni, C.; Denton, G. H. (Polar Research, 2008)
We present glacial geologic and chronologic data concerning the Holocene ice extent in the Stauning Alper of East Greenland. The retreat of ice from the late-glacial position back into the mountains was accomplished by at least 11 000 cal years B.P. The only recorded advance after this time occurred during the past few centuries (the Little Ice Age). Therefore, we postulate that the Little Ice Age event represents the maximum Holocene ice extent in this part of East Greenland.
id: 823; 327VY Times Cited:1 Cited References Count:45Y

Mutation and evolutionary rates in adelie penguins from the antarctic - Millar, C. D.; Dodd, A.; Anderson, J.; Gibb, G. C.; Ritchie, P. A.; Baroni, C.; Woodhams, M. D.; Hendy, M. D.; Lambert, D. M. (Plos Genetics, 2008)
Precise estimations of molecular rates are fundamental to our understanding of the processes of evolution. In principle, mutation and evolutionary rates for neutral regions of the same species are expected to be equal. However, a number of recent studies have shown that mutation rates estimated from pedigree material are much faster than evolutionary rates measured over longer time periods. To resolve this apparent contradiction, we have examined the hypervariable region (HVR I) of the mitochondrial genome using families of Adelie penguins (Pygoscelis adeliae) from the Antarctic. We sequenced 344 bps of the HVR I from penguins comprising 508 families with 915 chicks, together with both their parents. All of the 62 germline heteroplasmies that we detected in mothers were also detected in their offspring, consistent with maternal inheritance. These data give an estimated mutation rate (micro) of 0.55 mutations/site/Myrs (HPD 95% confidence interval of 0.29-0.88 mutations/site/Myrs) after accounting for the persistence of these heteroplasmies and the sensitivity of current detection methods. In comparison, the rate of evolution (k) of the same HVR I region, determined using DNA sequences from 162 known age sub-fossil bones spanning a 37,000-year period, was 0.86 substitutions/site/Myrs (HPD 95% confidence interval of 0.53 and 1.17). Importantly, the latter rate is not statistically different from our estimate of the mutation rate. These results are in contrast to the view that molecular rates are time dependent.
id: 1195; Millar, Craig D Dodd, Andrew Anderson, Jennifer Gibb, Gillian C Ritchie, Peter A Baroni, Carlo Woodhams, Michael D Hendy, Michael D Lambert, David M PLoS Genet. 2008 Oct 3;4(10):e1000209.2546446

Near constancy of the Pacific Ocean surface to mid-depth radiocarbon-age difference over the last 20 kyr - Broecker, W.; Clark, E.; Barker, S. (Earth and Planetary Science Letters, 2008)
Although C-13 to C-12 and cadmium to calcium ratios provide information regarding the distribution of deep water masses during late glacial time and during the period of deglaciation, our knowledge of the rate at which these water masses were ventilated comes mainly from the difference in radiocarbon-age between coexisting bottom- and surface-dwelling foraminifera. Paired benthic/planktonic foraminiferal radiocarbonage differences covering last 20 kyr in a high-deposition-rate western equatorial Pacific core, MD01-2386, from a water depth of 2.8 km show no significant climate-related variations over this period. This result is surprising for we would have expected a change in this age difference between the last glacial maximum (LGM) and the Holocene and also during the Mystery Interval (17.5-14.5 kyr ago) when the waters in a radiocarbon-depleted abyssal reservoir were presumably being mixed back into the remainder of the ocean. (C) 2008 Elsevier B.V. All rights reserved.
id: 770; 390GV Times Cited:2 Cited References Count:27Y

Radiocarbon ages on deep water corals from the Ross Sea - Burt, T. (Hamilton College, 2008)

Radiocarbon evidence for the importance of surface vegetation on fermentation and methanogenesis in contrasting types of boreal peatlands - Chanton, J. P.; Glaser, P. H.; Chasar, L. S.; Burdige, D. J.; Hines, M. E.; Siegel, D. I.; Tremblay, L. B.; Cooper, W. T. (Global Biogeochemical Cycles, 2008)
We found a consistent distribution pattern for radiocarbon in dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and methane replicated across spatial and temporal scales in northern peatlands from Minnesota to Alaska. The (14)C content of DOC is relatively modern throughout the peat column, to depths of 3 m. In sedge-dominated peatlands, the (14)C contents of the products of respiration, CH(4) and DIC, are essentially the same and are similar to that of DOC. In Sphagnum- and woody plant-dominated peatlands with few sedges, however, the respiration products are similar but intermediate between the (14)C contents of the solid phase peat and the DOC. Preliminary data indicates qualitative differences in the pore water DOC, depending on the extent of sedge cover, consistent with the hypothesis that the DOC in sedge-dominated peatlands is more reactive than DOC in peatlands where Sphagnum or other vascular plants dominate. These data are supported by molecular level analysis of DOC by ultrahigh-resolution mass spectrometry that suggests more dramatic changes with depth in the composition of DOC in the sedge-dominated peatland pore waters relative to changes observed in DOC where Sphagnum dominates. The higher reactivity of DOC from sedge-dominated peatlands may be a function of either different source materials or environmental factors that are related to the abundance of sedges in peatlands.
id: 1949; PT: J; UT: WOS:000262041000002

Recycling of graphite during Himalayan erosion: a geological stabilization of carbon in the crust - Galy, V.; Beyssac, O.; France-Lanord, C.; Eglinton, T. (Science, 2008)
At geological time scales, the role of continental erosion in the organic carbon (OC) cycle is determined by the balance between recent OC burial and petrogenic OC oxidation. Evaluating its net effect on the concentration of carbon dioxide and dioxygen in the atmosphere requires the fate of petrogenic OC to be assessed. Here, we report a multiscale (nanometer to micrometer) structural characterization of petrogenic OC in the Himalayan system. We show that graphitic carbon is preserved and buried in marine sediments, while the less graphitized forms are oxidized during fluvial transport. Radiocarbon dating indicates that 30 to 50% of the carbon initially present in the Himalayan rocks is conserved during the erosion cycle. Graphitization during metamorphism thus stabilizes carbon in the crust over geological time scales.
id: 1876; Galy, Valier Beyssac, Olivier France-Lanord, Christian Eglinton, Timothy New York, N.Y. Science. 2008 Nov 7;322(5903):943-5.; YY

Relative sea-level change, Kjove Land, Scoresby Sund, East Greenland: implications for seasonality in Younger Dryas time - Hall, B.; Baroni, C.; Denton, G.; Kelly, M. A.; Lowell, T. (Quaternary Science Reviews, 2008)
The age of the Milne Land Stade (MLS) moraines in the Scoresby Sund region of East Greenland is key for testing the hypothesis that strong seasonality marked abrupt cooling events, such as the Younger Dryas, registered in Greenland ice cores. The relevant chronology is based on 69 radiocarbon dates of shells from raised beaches and deltas related to marine inundation and isostatic rebound that accompanied glacier retreat from the moraines. Taken together, these dates form the basis for a relative sea-level curve that shows very high rates of emergence typical of recently deglaciated regions. Upward extrapolation of this curve suggests that the marine limit (134 m a.s.l.) dates to about 12,400 cal yr B.R The shorelines that mark the marine limit lie within areas that were ice-covered when the glaciers were at the outer limit of the MLS advance; hence, the moraines that form the outer limit must antedate 12,400 cal yr B.R and probably are from earliest Younger Dryas or Allerod time. At Holger Danskes Briller, an inner moraine grades to a massive ice-contact delta, now at 101 m a.s.l., which is dated to 11,000-11,300 cal yr B.P. The age of the outer MLS moraines, along with constraints on the maximum possible Younger Dryas ice extent and snowline lowering are consistent with the idea that East Greenland climate experienced strong seasonality during Younger Dryas time. (C) 2008 Elsevier Ltd. All rights reserved.
id: 824; 389XX Times Cited:3 Cited References Count:43Y

Reply to Comment on "The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul" by Hiscott et al., Marine Geology 248, 228-236 - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Lericolais, G.; Sancar, U.; Menot, G.; Bard, E. (Marine Geology, 2008)
In their comment Hiscott and co-authors adhere rigidly to ages and sources for sedimentary units in the subsurface of the Marmara shelf that they have previously reported in their publications from 2002 through 2007. This adherence is in spite of a superior age-depth model from our 13 m-long sediment core that penetrated deeply into the deposits under consideration and in disregard to the results of subsequent more-detailed and full-coverage mapping of the region under scrutiny. The age revisions are dismissed by the authors of the comment as representing sediments severely disturbed during coring. We rebut this criticism. The Bosporus source attributed by them to the sedimentary units sampled and dated by us appears to be driven by their conception that the Black Sea had a persistent outflow prior to its two-way connection with Marmara. Irrespective of whether the outflow was persistent, our reply shows that the drawing of the isopachs of the sedimentary units by Hiscott and coauthors was accomplished in a fashion to promote the Bosporus source hypothesis regardless of the geographic limits of their survey. The ages assigned to the units are equally indeterminate because the cores used by them have missing core tops of unknown lengths that are not discussed in their publications. Furthermore, the sub-bottom reflectors at the sites where the reflectors were calibrated to their only core without a missing top are actually hidden by the finite width of the bottom reflecting wavelet. (C) 2008 Elsevier B.V. All rights reserved.
id: 784; 377ZE Times Cited:0 Cited References Count:33Y

The sedimentary record of glacial retreat, Marinelli Fjord, Patagonia: Regional correlations and climate ties - Boyd, B.L.; Anderson, J.B.; Wellner, J.S.; ández, R.A. (Marine Geology, 2008)
The Inland Passage of Chile comprises the most continuous latitudinal transect of ice fields, ice caps, and alpine glaciers in the Southern Hemisphere, providing an excellent natural laboratory for the study of glacial response to climate change during the Holocene. Here we report results from a marine geological investigation of Marinelli Fjord, Tierra del Fuego (54°25 S, 69°35 W) and Ainsworth Fjord, which merges with Marinelli Fjord. Data acquired during July 2005 onboard the RV/IB Nathaniel B. Palmer include high-resolution seismic data, multibeam swath bathymetry data and sediment cores. Post-cruise analyses include detailed seismic facies and lithofacies analysis and radiocarbon dating. The results indicate that a major transition in the glacimarine record from ice-proximal facies to ice-distal facies occurred in the outer basins of the fjord at 15.5 kyr to 12.5 kyr. The ice-proximal facies consists of pebbly mud with abundant laminations and is characterized by high average sedimentation rates (28 mm/yr). In contrast, an ice-distal facies is dominantly bioturbated mud with low average sedimentation rates (0.56 mm/yr). This transition marks the retreat of Marinelli Glacier from the outer basins with no evidence for glacial re-advance. Subsequently, during the mid to late-Holocene, Ainsworth Glacier retreated and exposed Ainsworth Fjord. Our results are consistent with the climatic trends for southern South America where the final deglaciation of the region ended at ~ 12.5 ka. During the Holocene, stable ice conditions persisted until the mid-1960s when Marinelli Glacier began rapidly retreating to its modern day position.

Shell and Bone Artifacts from Two Middle Holocene Red Abalone Middens on San Miguel Island - Braje, Todd J.; Erlandson, Jon M. (Pacific Coast Archaeological Society Quarterly, 2008)
id: 2067

Source and composition of organic matter in the Bari canyon (Italy): Dense water cascading versus particulate export from the upper ocean - Tesi, T.; Langone, L.; Goñi, M. A.; Turchetto, M.; Miserocchi, S.; Boldrin, A. (Deep-Sea Research Part I-Oceanographic Research Papers, 2008)
Recent studies in the southern Adriatic Sea have shown that dense water cascading is an effective off-shelf transport mechanism. In order to evaluate the relative importance of different processes affecting the down-slope transfer of organic matter (OM), a multi-proxy biogeochemical study was carried out in the southern Adriatic. Three sediment traps were deployed on the southern slope in March 2004 for 1 year at 35 m above the seabed. Surficial sediments were collected on the shelf and slope along a shore-normal transect. Suspended material in the water column at different water depths was collected along nine shore-normal transects. Organic carbon (OC), total nitrogen (TN), carbon isotopic composition (delta C-13 and Delta C-14) and CuO reaction products were used to identify the OM sources and to asses the relative importance of vertical and lateral particulate fluxes. Both sinking particulates from the euphotic zone and advected material from the seafloor were collected by the moored instrumentations. During low-mass fluxes, the trapped material exhibited the highest Delta C-14 values (from -162.0 parts per thousand to +42.3 parts per thousand) and OC contents (from 1.13% to 2.17%) while the lignin displayed the lowest content (from 0.160 to 0.285 mg 100 mg(-1) OC). However, during dense water cascading events, the down-slope particulate flux showed different compositional features. In this period the trapped material displayed the most depleted Delta C-14 values (from -275.3 parts per thousand to -171.3 parts per thousand.), the lowest OC content (from 0.87% to 1.31%), and the highest lignin content (from 0.230 to 379 mg 100 mg(-1) OC). Holocene sea-level rise has drastically reduced sediment availability to the Bari canyon, and this in turn has affected the OC composition of the material funneled toward the deep Adriatic Sea. Parameters based on lignin CuO products suggest that the terrestrial material exported down the slope is very different from riverine inputs and inner shelf sediments. This indicates that neither river floods nor sediment resuspension from the inner shelf contributes directly to the down-slope flux. Rather, the material collected in the sediment traps exhibits an OM composition comparable to the surface sediments collected in the southern outer shelf. This correspondence suggests that resuspension of sediments by bottom currents in the southern outer shelf significantly contribute to down-slope OM transfer. Finally, the presence of lignin phenols in all cups indicates that lateral fluxes were constantly active on the slope throughout the deployment. (C) 2008 Elsevier Ltd. All rights reserved.
id: 828; 330FL Times Cited:4 Cited References Count:87Y

14C and 13C isotopic characterization of organic carbon in surface waters of the South Atlantic Bight - De Alteris, J. A.; Bauer, J. E.; Perkey, D. W.; Keesee, E. J.; Cai, W. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 1026

A 1,500-year record of North Atlantic storm activity based on optically dated relict beach scarps - Buynevich, I. V.; FitzGerald, D. M.; Goble, R. J. (Geology, 2007)
Understanding of long-term dynamics of intense coastal storms is important for determining the frequency and impact of these events on sandy coasts. We use optically stimulated luminescence (OSL) dates on relict scarps within a prograded barrier sequence to reconstruct the chronology of large-magnitude erosional events in the western Gulf of Maine. OSL dates obtained on quartz-rich sediments immediately overlying relict scarps indicate severe beach erosion and retreat due to erosional events ca. 1550, 390, 290, and 150 cal yr B.P. Our data provide new evidence of increased storm activity (most likely frequency and/or intensity of extratropical storms) during the past 500 yr, which was preceded by a relatively calm period lasting ∼1000 yr. The width of the coastal sequence preserved between successive paleoscarps shows strong correlation with the time interval elapsed between storms. Our findings indicate that diagnostic geophysical and sedimentological signatures of severe erosional events offer new opportunities for assessing the impact and timing of major storms along sandy coasts.
id: 1083
Keywords: barrier; erosion; ground-penetrating radar; heavy minerals; Maine; OSL dating

A 190% drop in atmosphere's Delta(14) C during the "Mystery Interval" (17.5 to 14.5 kyr) - Broecker, Wallace; Barker, Stephen (Earth and Planetary Science Letters, 2007)
Reconstructions of atmospheric Delta(14)C for the deglacial period reveal a 190 +/- 10%. drop between 17.5 and 14.5 kyr before present, during the 'mystery interval'. While it appears that the major contributor must be the mixing between an isolated low radiocarbon abyssal reservoir and the remainder of the ocean, a combination of (14)C measurements on coexisting benthic and planktic foraminifera shells and (13)C/(12)C measurements on benthic foraminifera make it difficult to identify a sufficiently large volume for this reservoir. An alternative scenario, based on higher (14)C production rates between about 38 and 18 kyr ago, would escape the need for a large, isolated reservoir prior to the mystery interval but instead would call for a better ventilated ocean afterwards. The addition of (14) C-deficient sedimentary carbon appears not to be an important contributor. While the unlikely explanation that the half-life of (14)C is 15% greater than the accepted value (5730 yr) would eliminate the steady decrease in the (14)C/C over the last 40 kyr, it would not explain the steep drop which occurred between 17.5 and 14.5 kyr. (c) 2007 Elsevier B.V. All rights reserved.
id: 1921; PT: J; UT: WOS:000246051000009

A 28-ka history of sea surface temperature, primary productivity and planktonic community variability in the western Arabian Sea - Pourmand, Ali; Marcantonio, Franco; Bianchi, Thomas S.; Canuel, Elizabeth A.; Waterson, Elizabeth J. (Paleoceanography, 2007)
Uranium series radionuclides and organic biomarkers, which represent major groups of planktonic organisms, were measured in western Arabian Sea sediments that span the past 28 ka. Variability in the past strength of the southwest and northeast monsoons and its influence on primary productivity, sea surface temperature (SST), and planktonic community structure were investigated. The average alkenone-derived SST for the last glacial period was ∼3°C lower than that measured for the Holocene. Prior to the deglacial, the lowest SSTs coincide with the highest measured fluxes of organic biomarkers, which represent primarily a planktonic suite of diatoms, coccolithophorids, dinoflagellates, and zooplankton. We propose that intensification of winter northeast monsoon winds during the last glacial period resulted in deep convective mixing, cold SSTs and enhanced primary productivity. In contrast, postdeglacial (<17 ka) SSTs are warmer during times in which biomarker fluxes are high. Associated with this transition is a planktonic community structure change, in which the ratio of the average cumulative flux of diatom biomarkers to the cumulative flux of coccolithophorid biomarkers is twice as high during the deglacial and Holocene than the average ratio during the last glacial period. We suggest that this temporal transition represents a shift from a winter northeast monsoon-dominated (pre-17 ka) to a summer southwest monsoon-dominated (post-17 ka) wind system.

Carbon nanotube foils for electron stripping in tandem accelerators - von Reden, K.; Zhang, M.; Meigs, M.; Sichel, E.; Fang, S.; Baughman, R. (Nucl. Inst. & Meth. in Physics Research B., 2007)
id: 690

Century-to-millennial scale climatic variability in Lake Malawi revealed by isotope records - Barker, P. A.; Leng, M. J.; Gasse, F.; Huang, Y. (Earth and Planetary Science Letters, 2007)
Diatom-based oxygen isotope data ( delta super(1) super(8)O sub(d) sub(i) sub(a) sub(t) sub(o) sub(m)) from Lake Malawi show multi-centennial scale wet-dry intervals spaced approximately every 2.3 ka throughout a 25 ka sequence. The delta super(1) super(8)O sub(d) sub(i) sub(a) sub(t) sub(o) sub(m) record is supported by a lower resolution deuterium ( delta D sub(p) sub(a))isotope curve derived from palmitic acid. We interpret these isotope data in terms of major shifts in precipitation and evaporation moderated by seasonal controls on the host organisms. Dry periods marked by relatively positive isotope values, represent the extension of abrupt Holocene events noted from northern and equatorial Africa to 10-15 super(o)S. These events in Lake Malawi correspond to cool episodes in Greenland, thereby demonstrating teleconnections generated by meridional temperature gradients. Sea surface temperatures are likely to be the primary transmitter of deglacial climate changes, although trade wind strength and direction is critical in controlling precipitation patterns in tropical regions. Conversely, the global hydrological cycle, driven by low latitude regions represents an important positive feedback amplifying deglacial processes.
id: 2222; Source type: scholarlyjournals; Object type: Article; Object type: Feature; CSAUnique: OB-MD-0006626237; AccNum: 7631572; DOI: 10.1016/j.epsl.2007.06.010; ISSN: 0012-821X; Peer Reviewed: true

Deposition and reactivity of aerosol-derived organic carbon in temperate watersheds - Wozniak, A. W.; Bauer, J. E.; Dickhut, R. M.; Keesee, E. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 1029

Early Maritime Technology on California’s San Miguel Island: Arena Points from - Erlandson, Jon M.; Braje, Todd (Current Research in the Pleistocene, 2007)
id: 2071

Evolution and latitudinal diversity gradient: Speciation, extinction, and biogeography - Mittelbach, G. G.; Schemske, D. W.; Cornell, H. V.; Allen, A. P.; Brown, J. M.; Bush, M. B. (Ecology Letters, 2007)
id: 456

Field and laboratory data from an earthquake history study of scarps of the Lake Creek-Boundary Creek fault between the Elwha River and Siebert Creek, Clallam County, Washington - Nelson, A. R.; Personius, S. F.; Buck, Jason; Bradley, L. A.; Wells, R. E.; Schermer, E. R. (U. S. Geological Survey Scientific Investigations Report 2004, 2007)
id: 433

Global human impacts or climate change? : explaining the Sooty Shearwater decline at the Minard site, Washington State, USA - Bovy, K. M. (Journal of Archaeological Science, 2007)
Sooty Shearwater (Puffinus griseus) remains decrease throughout the occupation (AD 1000-1600) of the Minard site (45-GH-15) on the southern Washington coast, USA. Given that New Zealand is one of the major breeding locations for this long-distant migrant, the decline at the Minard site may be due to human impacts on a global scale. In particular, the Maori practice of muttonbirding, the killing and preparation of fledgling shearwaters for storage, may have affected the number of summer migrants reaching the Pacific Northwest Coast. A second hypothesis attributes the decline in Sooty Shearwaters at the site to increasing sea surface temperatures and/or increased frequency of ENSO events during this period. Understanding how Sooty Shearwaters responded to human hunting and/or climate events in the past may be useful for the current management of this species, which has faced dramatic declines in recent decades. (c) 2006 Elsevier Ltd. All rights reserved.
id: 445; 170KG Times Cited:4 Cited References Count:104

Historical ecology and human impacts on coastal ecosystems of the Santa Barbara Channel region, California - Rick, Torben C.; Erlandson, Jon M.; Braje, Todd J.; Estes, James; Graham, Michael; Vellanoweth, Rene (Ancient Human Impacts on Marine Environments: A Global Perspective, 2007)
id: 577

Holocene fire and occupation in Amazonia: Records from two lake districts - Bush, M. B.; Silman, M. R.; de Toledo, M. B.; Listopad, C. R. S.; Gosling, W. D.; Williams, C.; De Oliveira, P. E.; Krisel, C. (Philosophical Transactions of the Royal Society of London, 2007)
id: 454

Holocene Reworking of a Sand Sheet in the Merrimack Embayment, Western Gulf of Maine - Hein, C. J.; FitzGerald, D. M.; Barnhardt, W. (Journal of Coastal Research, 2007)
Recent bathymetric, backscatter, and seafloor sediment samples demonstrate that a large sand sheet was formed in the inner shelf by the reworking of the Merrimack River lowstand delta (deposited 12 kya; currently at 45 m depth) and braid plain during the Holocene transgression. Asymmetric bedforms and distinct grain size distributions suggest the sand sheet is actively being reworked by inner-shelf processes.Bottom sediments range from silty sand at the submerged delta to coarse sand and fine gravel in the innermost shelf (depth: 10-50 m). Coarse-grained sand comprises an expansive (32 km(2)) featureless sand sheet centered off the Merrimack River. Fine-grained sand discontinuously overlies this sand sheet in many locations and forms long wavelength (100 - 800 m), low amplitude (1-2 m), asymmetrical bedforms. Sets of these bedforms are oriented from slightly oblique offshore to onshore; several bedform sets are located within I km and oriented orthogonally to one another. Along the paleo-delta front north-northwest oriented bedforms are dominant. Inshore of these features, the bedforms become more closely spaced and have orientations to the west and west-southwest. Preliminary data suggest that the combined forces of instantaneous storm-wave generated shear stress and storm-induced currents associated with high energy northeast storm events may be responsible for sand sheet reworking and bedform development.
Sp. Iss. 50V16hi Times Cited:2 Cited References Count:22
Keywords: backscatter; bedforms; shallow seismic; shelf sediment transport

Holocene sedimentation in a kettle lpond breached by rising sea level on Cape Cod - Bratton, John F. (Northeast Section Meeting, Geological Society of America, 2007)
id: 1065; 1

Last millennia sedimentary record on a micro-tidal, low-accumulation prodelta (Tet NW Mediterranean) - Bourrin, F.; Monaco, A.; Aloisi, J. C.; Sanchez-Cabeza, J. A.; Lofi, J.; Heussner, S.; de Madron, X. D.; Jeanty, G.; Buscail, R.; Saragoni, G. (Marine Geology, 2007)
Statistical sequential analysis was performed on a series of sediment cores collected from the Tet prodelta in the Gulf of Lions, northwestern Mediterranean Sea, between October 2003 and October 2004. Seabed changes during that period were correlated to hydrodynamic conditions (waves and currents) and river discharge. Low sediment supply prevents full preservation of new sediment strata on this low-accumulation prodelta located on a microtidal, storm-dorninated inner shelf. Severe meteorological events caused a rapid succession of erosion and deposition phases. For example, the December 2003 flood and storm produced a flood layer deposit that persisted for 2 months with only slight transformations due to early diagenesis and/or bioturbation, until a new, storm event eroded this layer. A typical sedimentary sequence was observed for the secular deposits composed of a 10-cm-thick sandy layer overlaying siltyclayey layers. These characteristic features were used to analyse the last millennia sedimentary record of the Tet prodelta. The low preservation of freshly deposited sediments and variable sedimentation rates during the last millennia period yield a sedimentary sequence formed by the outcropping of muddy prodeltaic units intersected by heterogeneous siltysandy units similar to those formed under present day hydrodynamic conditions. No flood layer was found related to catastrophic flooding of the last century in the sedimentary record. The Little lee Age (similar to 1550-1850 AD) probably favoured the formation of a well-developed muddy prodelta in the mouth of the Tet River. Later on, the decrease of sediment supply by rivers due to climate change and/or human activities (damming, irrigation), and the increase of the number of high-energy storms reaching the coast, induced a coarsening of the top sediment layer on this prodelta. This modem change of the substrate is also observed in the composition of benthic biota found in the substrate. (c) 2007 Elsevier B.V All rights reserved.
id: 1904; 210TU Times Cited:8 Cited References Count:68Y

Late quaternary lake and swamp sediments: records of climate and environment - Horn, S. P. (Central America: Geology, Resources, Hazards, 2007)
id: 622

Linking lithology and land use to sources of dissolved and particulate organic matter in headwaters of a temperate, passive-margin river system - Longworth, B. E.; Petsch, S. T.; Raymond, P. A.; Bauer, J. E. (Geochimica Et Cosmochimica Acta, 2007)
A number of rivers have been found to transport highly aged organic matter [OM]; however, the sources of this aged material remain a matter of debate. One potential source may be erosion and weathering of headwater lithologies rich in ancient sedimentary OM. In this study, waters, suspended particulates, streambed sediments, rocks and soils from fourteen small headwater watersheds of a mid-size, temperate, passive margin river were sampled and characterized by Delta C-14, delta C-13, and POC/TPN ratios to identify sources of particulate and dissolved OM delivered to the river mainstem. These headwater sites encompass a range in lithology (OM-rich shales, OM-lean carbonate/mudstone facies, and OM-free crystalline rocks) and land use types (forested and agricultural), and allow investigation of the influence of agriculture and bedrock types on stream OM characteristics. Streams draining large areas of both agricultural land use and OM-rich lithology contain particulate OM [POM] that is more C-14-depleted than streams draining forested, shale-free watersheds. However, this is not sufficient to account for the significantly lower Delta C-14-POC measured in the river mainstern. Dissolved OM [DOM] Delta C-14 are in all cases enriched compared to POM from the same stream, but are otherwise highly variable and unrelated to either land use or lithology. POC/TPN ratios were likewise highly variable. POC and DOC delta C-13 signatures were similar across all watersheds. Based on isotope mass balance, C-14-free fossil OM sources contribute 0-12% of total stream POM. Although these results do not unequivocally separate the influences of land use and lithology, watershed coverage by shale and agriculture are both important controls on stream A Delta C-14-POC. Thus export of aged, particle-associated OM may be a feature of river systems along both passive and active continental margins. (C) 2007 Elsevier Ltd. All rights reserved.
30
Keywords: ATCHAFALAYA RIVER; ATMOSPHERIC O-2; BLACK SHALE; continental-shelf; GULF-OF-MEXICO; marine-sediments; MINERAL; SPACE-TIME CLIMATE; STABLE-ISOTOPES; surface sediments; SURFACES

Lithological anomalies in a relict coastal dune: Geophysical and paleoenvironmental markers - Buynevich, I. V.; Bitinas, A.; Pupienis, D. (Geophysical Research Letters, 2007)
Ground exposures of migration surfaces (slipfaces) of a relict Holocene coastal dune along the southeastern Baltic Sea coast provide an ideal opportunity for establishing the causes of prominent reflections on geophysical profiles. High-amplitude reflections on high-resolution ground-penetrating radar (GPR) images correlate well with two major lithological anomalies: 1) paleosols developed on dune slipfaces, and 2) slipfaces consisting of heavy-mineral concentrations (HMCs). Paleosols serve as indicators of dune stability, represent datable chronostratigraphic surfaces, and help reconstruct dune paleo-morphology. HMCs have substantially higher magnetic susceptibility values than background quartz-rich sands and, where they are well-developed, can be also used for spatial correlation. Based on their occurrence at the study site, these enriched horizons likely represent periods of increased wind activity ( storminess). Multiple HMCs upwind of paleosol P1 ( 800 670 cal years BP) likely reflect periods of intensified wind activity along the southeast Baltic region during the Medieval Warm Period.
168ajTimes Cited:18Cited References Count:38

A Mid-Holocene environmental change in Amazonian savannas - de Toledo, M. B.; Bush, M. B. (Journal of Biogeography, 2007)
id: 455

A multiproxy peat record of Holocene mangrove palaeoecology from Twin Cays, Belize - Wooller, Matthew J.; Morgan, Rebecca; Fowell, Sarah; Behling, Hermann; Fogel, Marilyn (The HoloceneThe Holocene, 2007)
The extent and function of coastal mangrove ecosystems are likely to be influenced by future changes in sea level. Multiple proxies of past mangrove ecosystems preserved in a 780 cm long peat core (TCC2) taken from Twin Cays, Belize, record palaeoecological changes since ~8000 cal. yr BP. The proxies included pollen and the stable-isotope (C, N and O) compositions of mangrove leaf fragments. Rhizophora mangle (red mangrove) has been dominant at this site on Twin Cays for over ~8000 years. Variations in δ13 C and δ15N suggest past changes in stand structure between dwarf, transition and tall R. mangle through the Holocene. Marked changes in the δ18O (up to ~4?) of mangrove leaf fragments throughout TCC2 most likely record variations in the proportion of seawater versus precipitation taken up by past mangroves, reflecting the degree of inundation of the site with seawater resulting from changes in the rate of Holocene sea-level rise. Notably, a decline in peat accumulation rate at ~7200 cal. yr BP correlates with a decrease in the rate of rise in sea level. This was not accompanied by a marked change in the pollen assemblages. However, changes in assemblage composition began to occur ~6300 cal. yr BP, with an increase in Myrsine-type and Avicennia germinans (black mangrove) pollen. An increase in the δ18O between 6100 and 5300 cal. yr BP, which correlates with other records from Central America, indicates a significant increase in the rate of rise in sea level.The extent and function of coastal mangrove ecosystems are likely to be influenced by future changes in sea level. Multiple proxies of past mangrove ecosystems preserved in a 780 cm long peat core (TCC2) taken from Twin Cays, Belize, record palaeoecological changes since ~8000 cal. yr BP. The proxies included pollen and the stable-isotope (C, N and O) compositions of mangrove leaf fragments. Rhizophora mangle (red mangrove) has been dominant at this site on Twin Cays for over ~8000 years. Variations in δ13 C and δ15N suggest past changes in stand structure between dwarf, transition and tall R. mangle through the Holocene. Marked changes in the δ18O (up to ~4?) of mangrove leaf fragments throughout TCC2 most likely record variations in the proportion of seawater versus precipitation taken up by past mangroves, reflecting the degree of inundation of the site with seawater resulting from changes in the rate of Holocene sea-level rise. Notably, a decline in peat accumulation rate at ~7200 cal. yr BP correlates with a decrease in the rate of rise in sea level. This was not accompanied by a marked change in the pollen assemblages. However, changes in assemblage composition began to occur ~6300 cal. yr BP, with an increase in Myrsine-type and Avicennia germinans (black mangrove) pollen. An increase in the δ18O between 6100 and 5300 cal. yr BP, which correlates with other records from Central America, indicates a significant increase in the rate of rise in sea level.

North Atlantic intermediate depth variability during the Younger Dryas; evidence from benthic foraminiferal Mg/Ca and the GFDL R30 coupled climate model - Came, Rosemarie E.; Curry, William B.; Oppo, Delia W.; Broccoli, Anthony J.; Stouffer, Ronald J.; Lynch-Stieglitz, Jean (Geophysical Monograph, vol. 173, 2007)
id: 857; American Geophysical Union 2005 fall meeting, San Francisco, CA, United States, Dec 5-9, 2005 NSF grants OCE-0096495, ATM-0502428, OCE-0096472, OCE-0220776 and ATM-0501351 References: 72; illus.; Y
Keywords: 24, Quaternary geology; Atlantic Ocean; benthic environment; Cenozoic; chemical ratios; Foraminifera; Glaciation; Gulf of Mexico; ice cores; Invertebrata; isotope ratios; isotopes; Little Bahama Bank; Mg/Ca; microfossils; North Atlantic; O-18/O-16; oxygen; paleo-oceanography; paleobathymetry; paleosalinity; paleotemperature; Pleistocene; Protista; Quaternary; Stable isotopes; Straits of Florida; upper; upper Weichselian; Weichselian; Younger Dryas

Oceanic dispersal and accumulation of river sediment - Sommerfield, C. K.; Agston, A. S.; Mullenbach, B. L.; Drake, D. E.; Alexander, C. R.; Nittrouer, C. A.; Borgeld, J. C.; Wheatcroft, R. A.; Leithold, E. L. (Continental-Margin Sedimentation: from Sediment Transport to Sequence Stratigraphy, 2007)
id: 1119

Organic matter origin and distribution in suspended particulate materials and surficial sediments from the western Adriatic Sea (Italy) - Tesi, T.; Miserocchi, S.; Goñi, M. A.; Langone, L.; Boldrin, A.; Turchetto, M. (Estuarine Coastal and Shelf Science, 2007)
In this study, organic carbon (OC), total nitrogen (TN), stable carbon isotopic (delta C-13(OC)) and CuO reaction product compositions were used to identify the sources of organic matter (OM) and to quantify the relative importance of allochthonous and autochthonous contributions to the western Adriatic Sea, Italy. Suspended particulate material (195 samples) and surficial sediments (0- 1 cm, 70 samples) from shallow cross-shelf transects were collected in February and May 2003, respectively. Vertical water column profiles were acquired along the same transects. Data include depth, potential temperature, salinity, density and chlorophyll fluorimetry. Along the western Adriatic shelf in the near-shore region, the phytoplankton growth was influenced by dynamics of the buoyant plumes from the Po and Appennine rivers. A small amount of very fine terrigenous material remained suspended within the coastal current and was exported southward along the shelf to the slope. High variability in the bulk composition was detected in the Po prodelta surficial sediments, whereas the western Adriatic shelf, although a larger area, exhibited a narrower range of values. A significant decoupling was observed between suspended particles in the water column and surficial deposits. The organic material collected in the water column was compositionally heterogeneous, with contributions from marine phytoplankton, riverine-estuarine phytoplankton and soil-derived OM. Frequent physical reworking of surficial sediments likely leads to the efficient oxidation of marine OC, resulting in the observed accumulation and preservation of refractory soil-derived OC delivered by the Po and Appennine rivers. (c) 2007 Elsevier Ltd. All rights reserved.
id: 1869; 179HX Times Cited:12 Cited References Count:61Y

Paleoenvironmental proxy records from Lake Hovsgol, Mongolia, and a synthesis of Holocene climate change in the Lake Baikal watershed - Prokopenko, A. A.; Khursevich, G. K.; Bezrukova, E. V.; Kuzmin, M. I.; Boes, X.; Williams, D. F.; Fedenya, S. A.; Kulagina, N. V.; Letunova, P. P.; Abzaeva, A. A. (Quaternary Research, 2007)
Here we discuss palcoenvironmental evolution in the Baikal region during the Holocene using new records of aquatic (diatom) and terrestrial vegetation changes from Hovsgol, Mongolia's largest and deepest lake. We reconcile previous contradictory Baikal timescales by constraining reservoir corrections of AMS dates on bulk sedimentary organic carbon. Synthesis of the Holocene records in the Baikal watershed reveals a northward progression in landscape/vegetation changes and an anti-phase behavior of diatom and biogenic silica proxies in neighboring rift lakes. In Lake Baikal, these proxies appear to be responsive to annual temperature increases after 6 ka, whereas in Lake Hovsgol they respond to higher precipitation/runoff from 11 to 7 ka. Unlike around Lake Baikal, warmer summers between 6 and 3.5 ka resulted in the decline, not expansion, of forest vegetation around Lake Hovsgol, apparently as a result of higher soil temperatures and lower moisture availability. The regional climatic proxy data are consistent with a series of 500-yr time slice Holocene GCM simulations for continental Eurasia. Our results allow reevaluation of the concepts of 'the Holocene optimum' and a 'maximum of the Asian summer monsoon', as applied to palcoclimate records from continental Asia. (c) 2007 University of Washington. All rights reserved.
187enTimes Cited:71Cited References Count:58

Paleoenvironmental significance of the eastern mud snail, Ilyanassa obsolete (Say, 1822), from a microtidal coastal sequence of southern New England - Buynevich, I. V. (The Nautilus, 2007)
id: 1082

Quantity, C-14 age and lability of desorbed soil organic carbon in fresh water and seawater - Butman, D.; Raymond, P. A.; Oh, N. H.; Mull, K. (Organic Geochemistry, 2007)
Soil organic carbon (OC) resulting from terrestrial photosynthesis is one of the largest reactive pools of sequestered atmospheric CO2. As an intermediate storage mechanism for organic material through time, the vertical distribution of carbon in a soil profile generally shows an age continuum with depth. Aged soil carbon is often the result of sorptive preservation, a physical mechanism that protects organic matter (OM) from microbial decay. Sorptive preservation is, however, a reversible process. Upon desorption, previously protected OM could be available for decomposition. Here we present simple fresh and salt water desorption experiments designed to determine the amount, 14C age and lability of “reversible” OM. Results suggest that 1.1–3.9% and 1.5–6.7% of OC, and 0.7–3% and 0.6–5% of total soil nitrogen can be desorbed using fresh and salt water, respectively. Radiocarbon data suggest this desorbed carbon is Δ14C-enriched compared to the bulk soil, with Δ14C values close to modern atmospheric Δ14CO2 at the soil surface, and aging with depth. Of this extractable aged carbon, upwards of 23–56% is labile across all treatments and with depth. Additional carbon is extracted with salt water compared to fresh water and this surplus is non-labile and younger than the labile component. Radiocarbon dating shows that the 14C age of soil carbon increases with depth and that there is a pool of Δ14C-depleted OC that is readily remineralized upon entering an aquatic/marine environment. These results indicate that eroded soil particles can release OC and organic N when entering rivers and oceans and that up to 50% of this carbon is available for aquatic metabolism.
id: 1161

Quaternary glaciation and hydrologic variation in the South American tropics as reconstructed from the Lake Titicaca drilling project - Fritz, S. C.; Baker, P. A.; Seltzer, G. O.; Ballantyne, A.; Tapia, P.; Cheng, H.; Edwards, R. L. (Quaternary Research, 2007)
A 136-m-long drill core of sediments was recovered from tropical high-attitude Lake Titicaca, Bolivia-Peru, enabling a reconstruction of past climate that spans four cycles of regional glacial advance and retreat and that is estimated to extend continuously over the last 370,000 yr. Within the errors of the age model, the periods of regional glacial advance and retreat are concordant respectively with global glacial and interglacial stages. Periods of ice advance in the southern tropical Andes generally were periods of positive water balance, as evidenced by deeper and fresher conditions in Lake Titicaca. Conversely, reduced glaciation occurred during periods of negative water balance and shallow closed-basin conditions in the lake. The apparent coincidence of positive water balance of Lake Titicaca and glacial growth in the adjacent Andes with Northern Hemisphere ice sheet expansion implies that regional water balance and glacial mass balance are strongly influenced by global-scale temperature changes, as well as by precessional forcing of the South American summer monsoon. (c) 2007 University of Washington. All rights reserved.
id: 841; 227AJ Times Cited:9 Cited References Count:63Y

Radiocarbon age of late glacial deep water from the equatorial Pacific - Broecker, W.; Clark, E.; Barker, S.; Hajdas, I.; Bonani, G.; Moreno, E. (Paleoceanography, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190% drop in the (14)C/C for atmospheric CO(2), which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, (14)C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the (13)C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO(2) expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.
id: 413; 165MC Times Cited:10 Cited References Count:18

Radiocarbon age offsets of foraminifera resulting from differential dissolution and fragmentation within the sedimentary bioturbated zone - Barker, Stephen; Broecker, Wallace; Clark, Elizabeth; Hajdas, Irka (Paleoceanography, 2007)
Shells of coexisting species of planktonic foraminifera from the Ontong Java Plateau reveal radiocarbon age offsets of up to 2200 years. Similar offsets are found between fragments and whole shells of single species. Steady state modelling of dissolution and bioturbation within the sedimentary mixed layer predicts age differences of up to several kiloyears due to the interplay between differential dissolution and fragmentation of foraminifer shells and bioturbation. The observation that fragile foraminiferal shells are systematically older than those of more robust species is more difficult to explain. Mechanisms of chemical erosion, interface dissolution, and sediment redistribution are all apparently unable to explain this phenomenon. A possible solution is presented in which a particular species may be represented by two distinct classes of shells which are more or less robust. In this case, differential dissolution and fragmentation causes an increase in the mean age as the fragile class contributes less to the remaining intact shells. This study highlights the vulnerability of low sedimentation rate cores to the effects of dissolution and bioturbation.
id: 1920; PT: J; UT: WOS:000246308600002

Radiocarbon analysis confirms the annual nature of sagebrush growth rings - Biondi, F.; Strachan, S. D. J.; Mensing, S.; Piovesan, G. (Radiocarbon, 2007)
In the Great Basin of North America, big sagebrush (Artemisia tridentata Nutt.) growth rings can be used to reconstruct environmental changes with annual resolution in areas where there is otherwise little such information available. We tested the annual nature of big sagebrush wood layers using accelerator mass spectrometry (AMS) radiocarbon dating. Four cross-sections from 3 sagebrush plants were collected near Ely, Nevada, USA, and analyzed using dendrochronological methods. Ten C-14 measurements were then used to trace the location of the 1963-64 "bomb spike." Although the number of rings on each section did not exceed 60, crossdating was possible within a section and between sections. Years assigned to individual wood layers by means of crossdating aligned with their expected C-14 values, matching the location of the C-14 peak. This result confirmed the annual nature of growth rings formed by big sagebrush, and will facilitate the development of spatially explicit, well-replicated proxy records of environmental change, such as wildfire regimes, in Great Basin valleys.
258usTimes Cited:9Cited References Count:48

Radiocarbon and stable isotope geochemistry of organic matter in the Amazon headwaters, Peruvian Andes - Townsend-Small, A.; Noguera, J. L.; McClain, M. E.; Brandes, J. A. (Global Biogeochemical Cycles, 2007)
[1] We used delta C-13, delta N-15, and Delta C-14 to determine the sources of riverine organic matter in the Pozuzo River, a tributary of the Pachitea River located in the mountainous headwaters of the Amazon. Particulate organic matter (POM) Delta C-14 decreased downstream, suggesting that young organic matter (OM) introduced in small headwaters is respired preferentially in rivers or is diluted downstream with older material. The delta C-13 and delta N-15 of POM in headwater rivers were heterogeneous and also isotopically distinct from the main stem, suggesting that differences in landscape processes in small catchments impact the concentration and composition of POM in streams. The delta C-13 of dissolved organic matter (DOM) closely mirrored that of POM in the headwaters, with an apparent decoupling of dissolved and particulate OM in the river main stem. The delta C-13 of POM sampled in 2004 had a much different relationship with altitude than observed during previous years: In 2004, a very dry year, we observed enrichment from the headwaters to the main stem, and the opposite pattern in 2002, when rain fell heavily throughout the sampling campaign. This suggests that during dry conditions, in-stream processes ( such as resuspension or photosynthesis) may control riverine POM composition as opposed to terrestrial processes, which dominate during high runoff. Thus a decrease in runoff in Andean headwaters could result in less terrestrial POM transfer to rivers in the Andes foothills and lowland Amazon with a corresponding decrease in aquatic CO2 evasion.
185aaTimes Cited:12 Cited References Count:37
Keywords: amino-acids; atlantic-ocean; carbon; drainage-basin; land-use; nitrogen; particulate; river system; sediments; streams

Rapid sea level rise and ice sheet response to 8,200-year climate event - Cronin, T. M.; Vogt, P. R.; Willard, D. A.; Thunell, R.; Halka, J.; Berke, M.; Pohlman, J. (Geophysical Research Letters, 2007)
The largest abrupt climatic reversal of the Holocene interglacial, the cooling event 8.6 - 8.2 thousand years ago (ka), was probably caused by catastrophic release of glacial Lake Agassiz-Ojibway, which slowed Atlantic meridional overturning circulation (AMOC) and cooled global climate. Geophysical surveys and sediment cores from Chesapeake Bay reveal the pattern of sea level rise during this event. Sea level rose similar to 14 m between 9.5 to 7.5 ka, a pattern consistent with coral records and the ICE- 5G glacio-isostatic adjustment model. There were two distinct periods at similar to 8.9 - 8.8 and similar to 8.2 - 7.6 ka when Chesapeake marshes were drown as sea level rose rapidly at least similar to 12 mm yr(-1). The latter event occurred after the 8.6 - 8.2 ka cooling event, coincided with extreme warming and vigorous AMOC centered on 7.9 ka, and may have been due to Antarctic Ice Sheet decay.
id: 810; 225MA Times Cited:4 Cited References Count:32Y

Reactivation of Coastal Dunes Documented by Subsurface Imaging of the Great Dune Ridge, Lithuania - Buynevich, I.; Bitinas, A.; Pupienis, D. (Journal of Coastal Research, 2007)
Large coastal and inland dunefields often consist of multiple generations defined by periods of stability and reactivation. Where earlier phases of aeolian activity are masked by subsequent deposition, continuous high-resolution geophysical images help to reconstruct the history of landscape change. Ground-penetrating radar (GPR) profiles from relict Holocene dunes on the northern Curonian Spit, Lithuania reveal distinct contacts between older deposits (barrier-spit facies, older aeolian strata, paleosols) and overlying dune sands. Early stages of dune migration began prior to 6,000 years B.P. followed by several periods of stabilisation and subsequent reactivation. Parabolic and transverse dunes, some attaining heights of 40-60 m, have migrated to the east in response to westerly winds from the Baltic Sea. In several places, similar to a number of sites in Northern Europe, the upper sections of large dunes have been deflated leaving near-horizontal exposures where subsurface imaging extends the continuity of key stratigraphic horizons. Within dune sequences, oblique lateral accretion surfaces indicate the direction of earlier migration phases and exhibit distinct meso-scale geometries. In GPR images and shallow trenches, buried slipfaces have dip angles varying from 10-15 degrees to 31-34 degrees, the latter being similar to the angle of repose maintained by modem unvegetated dunes. A series of cores taken through sequences of stacked buried slipfaces show little visible variation in sediment properties with depth, suggesting that minor changes in texture, mineralogy and grain packing may be responsible for individual reflections in geophysical records. Occasionally, laterally extensive horizons enriched in heavy minerals produce prominent subsurface reflections and are indicative of periods of increased wind activity.
Sp. Iss. 50V16hi Times Cited:10 Cited References Count:30
Keywords: curonian spit; gpr; medieval; reflection geometry; slipface; truncation

A regional study of Holocene climate change and human occupation in Peruvian Amazonia - Bush, M. B.; Listopad, M. C. S.; Silman, M. R. (Journal of Biogeography, 2007)
id: 453

Regional variability in the ages and reactivities of riverine dissolved and particulate organic matter exported to a temperate ocean margin - Bauer, J. E.; Raymond, P. A.; Cole, J. J.; Petsch, S. T.; Longworth, B. E.; Caraco, N. F.; Keesee, E. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 477

Reply to comment by L. D. Stott on "Anomalous radiocarbon ages for foraminifera shells": A correction to the western tropical Pacific MD9821-81 record - Broecker, W. S.; Barker, S. (Paleoceanography, 2007)
id: 2015; PT: J; UT: WOS:000244478900002

Sea level rise in Tampa Bay - Cronin, Thomas M.; Edgar, N. Terence; Brooks, Gregg; Hastings, David; Larson, Rebekka; Hine, Albert; Locker, Stanley; Suthard, Beau; Flower, Benjamin; Hollander, David; Wehmiller, John; Willard, Debra A.; et al. (Eos, Transactions, American Geophysical Union, 2007)
id: 1899; References: 14; illus. incl. geol. sketch map Latitude:N272700,N280200 Longitude:W0822200,W0825100Y

Sedimentary iron cycling and the origin and preservation of magnetization in platform carbonate muds, Andros Island, Bahamas - Maloof, A. C.; Kopp, R. E.; Grotzinger, J. P.; Fike, D. A.; Bosak, T.; Vali, H.; Poussart, P. M.; Weiss, B. P.; Kirschvink, J. L. (Earth and Planetary Science Letters, 2007)
Carbonate muds deposited on continental shelves are abundant and well-preserved throughout the geologic record because shelf strata are difficult to subduct and peritidal carbonate units often form thick, theologically strong units that resist penetrative deformation. Much of what we know about pre-Mesozoic ocean chemistry, carbon cycling, and global change is derived from isotope and trace element geochemistry of platform carbonates. Paleomagnetic data from the same sediments would be invaluable, placing records of paleolatitude, paleogeography, and perturbations to the geomagnetic field in the context and relative chronology of chemostratigraphy. To investigate the depositional and early diagenetic processes that contribute to magneitzation in carbonates, we surveyed over 500 core and surface samples of peritidal, often microbially bound carbonate muds spanning the last similar to 1000 yr and deposited on top of Pleistocene aeolianites in the Triple Goose Creek region of northwest Andros Island, Bahamas. Sedimentological, geochemical, magnetic and ferromagnetic resonance properties divide the sediment columns into three biogeochemical zones. In the upper sediments, the dominant magnetic mineral is magnetite, produced by magnetotactic bacteria and dissimiliatory microbial iron metabolism. At lower depths, above or near mean tide level, microbial iron reduction dissolves most of the magnetic particles in the sediment. In some cores, magnetic iron sulfides precipitate in a bottom zone of sulfate reduction, likely coupled to the oxidation of decaying mangrove roots. The remanent magnetization preserved in all oriented samples appears indistinguishable from the modem local geomagnetic field, which reflects the post-depositional origin of magnetic particles in the lower zone of the parasequence. While we cannot comment on the effects of late-stage diagenesis or metamorphism on remanence in carbonates, we postulate that early-cemented, thin-laminated parasequence tops in ancient peritidal carbonates are mostly likely to preserve syn-depositional paleomagnetic directions and magnetofossil stratigraphies. (c) 2007 Published by Elsevier B.V.
id: 787; 197DX Times Cited:9 Cited References Count:47Y

Stable carbon isotope compositions of Eastern Beringian grasses and sedges: Investigating their potential as paleoenvironmental indicators - Wooller, M. J.; Zazula, G. D.; Edwards, M.; Froese, D. G.; Boone, R. D.; Parker, C.; Bennett, B. (Arctic Antarctic and Alpine Research, 2007)
The nature of vegetation cover present in Beringia during the last glaciation remains unclear. Uncertainty rests partly with the limitations of conventional paleoecological methods. A lack of sufficient taxonomic resolution most notably associated with the grasses and sedges restricts the paleoccological inferences that can be made. Stable isotope measurements of subfossil plants are frequently used to enhance paleoenvironmental reconstructions. We present an investigation of the stable carbon isotope composition (delta C-13) of modern and subfossil grasses and sedges (graminoids) from Eastern Beringia. Modern grasses from wet habitats had a mean delta C-13 of -29.1 parts per thousand. (standard deviation [SD] = 2.1 parts per thousand, n = 75), while those from dry habitats had a mean of -26.9 parts per thousand (SD = 1.19, n = 27). Sedges (n = -50) from dry, wet, marsh, and sand dune habitats had specific habitat ranges. Four modern C-4 grasses had delta C-13 values typical Of C4 plants. Analyses were also conducted using subfossil graminoid remains from several sedimentary paleoecological contexts (e.g., arctic ground squirrel nests, loess, permafrost, and paleosols) in Eastern Beringia. Results from these subfossil samples, ranging in age from > 40,000 to ca. 11,000 cal. yr BP, illustrate that the delta C-13 of graminoid remains has altered during the past. The range of variation in the subfossil samples is within the range from modern graminoid specimens from dry and wet habitats. The results indicate that stable isotopes could contribute to a comprehensive and multiproxy reconstruction of Beringian paleoenvironments.
170fwTimes Cited:20Cited References Count:73

Strandplain evolution along the southern coast of Santa Caterina, Brazil - FitzGerald, D. M.; Cleary, W. J.; Buynevich, I. V.; Hein, C. J.; Kleins, A. H. F.; Asp, N.; Angulo, R. (Journal of Coastal Research, 2007)
id: 1099

A study of secondary organic aerosol formation in the anthropogenic-influenced southeastern United States - Weber, R. J.; Sullivan, A. P.; Peltier, R. E.; Russell, A.; Yan, B.; Zheng, M.; de Gouw, J.; Warneke, C.; Brock, C.; Holloway, J. S.; Atlas, E. L.; Edgerton, E. (Journal of Geophysical Research-Atmospheres, 2007)
[1] The formation of secondary organic aerosol (SOA) in an anthropogenic-influenced region in the southeastern United States is investigated by a comparison with urban plumes in the northeast. The analysis is based on measurements of fine-particle organic compounds soluble in water (WSOC) as a measure of secondary organic aerosol. Aircraft measurements over a large area of northern Georgia, including the Atlanta metropolitan region, and in plumes from New York City and surrounding urban regions in the northeast show that fine-particle WSOC are spatially correlated with vehicle emission tracers (e.g., CO), yet the measurements indicate that vehicles do not directly emit significant particulate WSOC. In addition to being correlated, WSOC concentrations were in similar proportions to anthropogenic tracers in both regions, despite biogenic volatile organic compounds (VOCs) that were on average 10-100 times higher over northern Georgia. In contrast, radiocarbon analysis on WSOC extracted from integrated filters deployed in Atlanta suggests that roughly 70-80% of the carbon in summertime WSOC is modern. If both findings are valid, the combined results indicate that in northern Georgia, fine-particle WSOC was secondary and formed through a process that involves mainly modern biogenic VOCs but which is strongly linked to an anthropogenic component that may largely control the mass of SOA formed. Independent of the radiocarbon results, a strong association between SOA and anthropogenic sources has implications for control strategies in urban regions with large biogenic VOC emissions.
id: 788; 187XB Times Cited:47 Cited References Count:39Y

A study of secondary organic aerosol formation in the anthropogenic-influenced southeastern United States - Weber, R. J.; Sullivan, A. P.; Peltier, R. E.; Russell, A.; Yan, B.; Zheng, M.; de Gouw, J.; Warneke, C.; Brock, C.; Holloway, J. S.; Atlas, E. L.; Edgerton, E. (Journal of Geophysical Research-Atmospheres, 2007)
[1] The formation of secondary organic aerosol (SOA) in an anthropogenic-influenced region in the southeastern United States is investigated by a comparison with urban plumes in the northeast. The analysis is based on measurements of fine-particle organic compounds soluble in water (WSOC) as a measure of secondary organic aerosol. Aircraft measurements over a large area of northern Georgia, including the Atlanta metropolitan region, and in plumes from New York City and surrounding urban regions in the northeast show that fine-particle WSOC are spatially correlated with vehicle emission tracers (e.g., CO), yet the measurements indicate that vehicles do not directly emit significant particulate WSOC. In addition to being correlated, WSOC concentrations were in similar proportions to anthropogenic tracers in both regions, despite biogenic volatile organic compounds (VOCs) that were on average 10-100 times higher over northern Georgia. In contrast, radiocarbon analysis on WSOC extracted from integrated filters deployed in Atlanta suggests that roughly 70-80% of the carbon in summertime WSOC is modern. If both findings are valid, the combined results indicate that in northern Georgia, fine-particle WSOC was secondary and formed through a process that involves mainly modern biogenic VOCs but which is strongly linked to an anthropogenic component that may largely control the mass of SOA formed. Independent of the radiocarbon results, a strong association between SOA and anthropogenic sources has implications for control strategies in urban regions with large biogenic VOC emissions.
263D13302
Keywords: AMBIENT AEROSOL; atmosphere; C-14; emissions; evolution; GASOLINE; OXIDATION; PARTICLES; RATIOS; ZURICH

The timing and evolution of the post-glacial transgression across the Sea of Marmara shelf south of Istanbul - Eris, K. K.; Ryan, W. B. F.; Cagatay, M. N.; Sancar, U.; Lericolais, G.; Menot, G.; Bard, E. (Marine Geology, 2007)
High-resolution seismic reflection profiles and analyses of the sedimentary substrate at the Sea of Marmara (SoM) entrance to the Strait of Istanbul (Sol, Bosphorus) provide a detailed record of the transgression that took place after the SoM reconnected with the Mediterranean. The sediments progressively fill a paleo shelf valley that incised the margin from the Sol to the shelf break at the time of the pre-Holocene lowstand. We map seven seismic reflection units that can be confidently correlated to sediment cores by lithology and physical properties. Sediments in the cores are dated by radiocarbon methods. Early channel and levee deposits within the paleo valley belong to the Younger Dryas cold stage and record outflow from the Black Sea via the Sol. Small clinoform packages on the valley margin formed in proximity to climbing paleo shorelines. The elevations of these deposits conform to the sealevel history recorded in Barbados corals. The younger part of the succession includes a subaqueous prodelta sourced from the Kurbagalidere River. Its relatively young age when the Holocene sea had almost reached its modem level suggests that the thick progradational and aggradational clinoform development was primarily a response to sediment supply rather than the filling of expanding accommodation space. Our findings refute the hypothesis of Aksu et al. (Aksu, A.E., Hiscott, R.N., Mudie., P.J., Rochon, A., Kaminski, M.A., Abrojano, T., Yasar, D., 2002a. Persistent Holocene outflow fromn the Black Sea to the Eastern Mediterranean contradicts Noah's Flood hypothesis, GSA Today 10,(6), 3-7., Aksu, A.E., Hiscott, R.N., Kaminski, M.A., Mudie, P.J., Gillespie, H., Abrojano, T., Yasar, D., 2002b. Last glacial-Holocene paleoceanography of the Black Sea and Marmara Sea: stable isotopic, foraminiferal and coccolith evidence. Mar. Geol., 190, 119-149.) and Hiscott et al. (Hiscott, R.N., Aksu, A.E., Yasar, D., Kaminski, M.A., Mudie, P.J., Kostylev, V.E., MacDonald, J.C. Isler, F.I., Lord, A.R., 2002. Deltas south of the Bosphorus Strait record persistent Black Sea outflow to the Marmara Sea since similar to 10 ka, Mar. Geol., 190,95-118., Hiscott, R.N., Aksu, A.E., Mudie., P.J., Kaminski, M.A., Abrajano, T, Yasar, D., Rochon, A., 2007. The Marmara Sea gateway since similar to 16 ky BP: non-catastrophic causes of paleoceanographic events in the Black Sea at 8.4 and 7.15 ky BR In Yanko-Hombach,V, Gilbert, A.S., Dolukhanov, P.M. (Eds.), The Black Sea Flood Question, Springer, The Netherlands, 89-117.) that this deposit was supplied from the Sol and that its presence requires a persistent Black Sea outflow since 10 C-14 ka bp (not corrected from the reservoir age or calibrated). (c) 2007 Elsevier B.V All rights reserved.
210tuTimes Cited:36Cited References Count:52

Variability of major carbon pools in the Mississippi River: importance of tributary inputs and regional land use on carbon and organic matter biogeochemistry - Perkey, D. W.; Bauer, J. E.; Keesee, E. J. (ASLO Aquatic Sciences Meeting, 2007)
id: 484

Variability of the marine ITCZ over the eastern Pacific during the past 30,000 years: Regional perspective and global context - Koutavas, Athanasios; Lynch-Stieglitz, Jean (The Hadley Circulation: Present, Past and Future, 2007)
id: 642

Abrupt tropical climate change: past and present - Thompson, L. G.; Mosley-Thompson, E.; Brecher, H.; Davis, M.; Leon, B.; Les, D.; Lin, P. N.; Mashiotta, T.; Mountain, K. (Proc Natl Acad Sci U S A, 2006)
Three lines of evidence for abrupt tropical climate change, both past and present, are presented. First, annually and decadally averaged delta(18)O and net mass-balance histories for the last 400 and 2,000 yr, respectively, demonstrate that the current warming at high elevations in the mid- to low latitudes is unprecedented for at least the last 2 millennia. Second, the continuing retreat of most mid- to low-latitude glaciers, many having persisted for thousands of years, signals a recent and abrupt change in the Earth's climate system. Finally, rooted, soft-bodied wetland plants, now exposed along the margins as the Quelccaya ice cap (Peru) retreats, have been radiocarbon dated and, when coupled with other widespread proxy evidence, provide strong evidence for an abrupt mid-Holocene climate event that marked the transition from early Holocene (pre-5,000-yr-B.P.) conditions to cooler, late Holocene (post-5,000-yr-B.P.) conditions. This abrupt event, approximately 5,200 yr ago, was widespread and spatially coherent through much of the tropics and was coincident with structural changes in several civilizations. These three lines of evidence argue that the present warming and associated glacier retreat are unprecedented in some areas for at least 5,200 yr. The ongoing global-scale, rapid retreat of mountain glaciers is not only contributing to global sea-level rise but also threatening freshwater supplies in many of the world's most populous regions.
Thompson, Lonnie GMosley-Thompson, EllenBrecher, HenryDavis, MaryLeon, BlancaLes, DonLin, Ping-NanMashiotta, TracyMountain, KeithengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2006/07/04 09:00Proc Natl Acad Sci U S A. 2006 Jul 11;103(28):10536-43. Epub 2006 Jun 30.

Abrupt vegetation changes in tropical South America over the last 120,000 years - Hughen, K. A.; Drenzek, N.; Bice, M.; Eglinton, T. I. (EOS Abstracts, 2006 Ocean Sciences Meeting, 2006)
id: 1078

Absence of 14C in PM2.5 Emissions from Gasohol Combustion in Small Engines - Lewis, C. W.; Volkens, J.; Braddock, J. N.; Crews, W. S.; Lonneman, W. A.; McNichol, A. P. (Aerosol Science and Technology, 2006)
id: 1699

Age mixing among sympatrick bivalves and brachiopods from the Brazilian South Atlantic - Krause R.A, Jr.; Barbour-Wood, S.; Kowalewski, M.; Simoes, M. G.; Kaufman, D.; Romanek, C. S.; Wehmiller, J. R. (Geological Society of America Abstracts with Programs, 2006)
id: 1170

Ahead of the Game: Middle and upper palaeolithic hunting behaviors in the southern Caucasus - Adler, Daniel S.; Bar-Oz, Guy; Belfer-Cohen, Anna; Bar-Yosef, Ofer (Current Anthropology, 2006)
id: 1137

Anomalous radiocarbon ages for foraminifera shells - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G. (Paleoceanography, 2006)
The causes for discordant radiocarbon results on multiple species of planktonic foraminifera from high-sedimentation-rate marine sediments are investigated. We have documented two causes for these anomalous results. One is the addition of secondary radiocarbon for which we have, to date, only one firm example. It involves an opal-rich sediment. The other is the incorporation of reworked material. Again, we have, to date, only one firm example. It involves a rapidly deposited ocean margin sediment. However, we have three other examples where reworking is the most likely explanation. On the basis of this study it is our conclusion that, where precise radiocarbon dating of high-deposition-rate marine sediment is required, a prerequisite is to demonstrate that concordant ages can be obtained on pairs of fragile and robust planktic shells. For sediment rich in opal, it is advisable to check for secondary calcite by comparing ages obtained on acid-leached samples with those on unleached samples.
id: 980; 041JB Times Cited:7 Cited References Count:7

Aspartic acid racemization dating of Holocene brachiopods and bivalves from the southern Brazilian shelf, South Atlantic - Barbour-Wood, S. L.; Krause R.A, Jr.; Kowalewski, M.; Wehmiller, J. F.; Simoes, M. G. (Quaternary Research, 2006)
The extent of racemization of aspartic acid (Asp) has been used to estimate the ages of 9 shells of the epifaunal calcitic brachiopod Bouchardia rosea and 9 shells of the infaunal aragonitic bivalve Semele casali. Both taxa were collected concurrently from the same sites at depths of 10 m and 30 m off the coast of Brazil. Asp D/L values show an excellent correlation with radiocarbon age at both sites and for both taxa (r2Site 9 B. rosea = 0.97, r2Site 1 B. rosea = 0.997, r2Site 9 S. casali = 0.9998, r2Site 1 S. casali = 0.93). The Asp ratios plotted against reservoir-corrected AMS radiocarbon ages over the time span of multiple millennia can thus be used to develop reliable and precise geochronologies not only for aragonitic mollusks (widely used for dating previously), but also for calcitic brachiopods. At each collection site, Bouchardia specimens display consistently higher D/L values than specimens of Semele. Thermal differences between sites are also notable and in agreement with theoretical expectations, as extents of racemization for both taxa are greater at the warmer, shallower site than at the cooler, deeper one. In late Holocene marine settings, concurrent time series of aragonitic and calcitic shells can be assembled using Asp racemization dating, and parallel multi-centennial to multi-millennial records can be developed simultaneously for multiple biomineral systems.
id: 1168
Keywords: Amino acid racemization; Aspartic; Bouchardia; Brachiopods; Brazil; Holocene; Mollusks; Radiocarbon dating; Semele; Ubatuba Bay

Atmospheric fossil sources of river and estuarine organic carbon transported to the coastal ocean - Wozniak, A. S.; Bauer, J. E.; Dickhut, R. M.; Keesee, E. J. (Ocean Sciences Meeting, 2006)
id: 1028

Bioreactivity of estuarine dissolved organic matter: A combined geochemical and microbiological approach - McCallister, S. L.; Bauer, J. E.; Canuel, E. A. (Limnology and Oceanography, 2006)
An integrated multidisciplinary study utilizing geochemical and microbial ecological approaches was conducted to characterize the origins, chemical nature, and quantities of dissolved and particulate organic matter (OM) utilized by heterotrophic bacteria in a temperate estuary. C: N, stable isotope (delta C-13), and lipid biomarker analyses revealed differences in the inferred reactivity of autochthonous versus allochthonous OM sources. Isotopic comparison of OM size fractions and bacterial nucleic acids suggests that high-molecular-weight dissolved OM (DOM) is consistently linked to bacterial biomass synthesis along the estuarine salinity gradient. Polyunsaturated fatty acids (as percent of total fatty acids, FA) were a reliable predictor of DOM decomposition in bioassays, thus providing an indicator directly linking DOM reactivity to its composition. Significant positive correlations between FA diagnostic of bacterial sources and lipid biomarker compounds diagnostic of planktonic origin indicate a systematic bacterial response to autochthonous DOM sources along the estuarine continuum. These findings further suggest that, although the geochemical signature of algal-derived OM in the dissolved phase may appear quantitatively insignificant, this fraction may nevertheless represent a principal source of bioreactive OM to heterotrophic bacteria in estuarine waters.
040scTimes Cited:39 Cited References Count:32
Keywords: acids; bacteria; bay; bioavailability; carbon-isotope analysis; extraction; food webs; sediments

Carbon remineralization in the Amazon-Guianas tropical mobile mudbelt: A sedimentary incinerator - Aller, R. C.; Blair, N. E. (Continental Shelf Research, 2006)
The Amazon River spawns a vast mobile mudbelt extending similar to 1600 km from the equator to the Orinoco delta. Deposits along the Amazon-Guianas coastline are characterized by some of the highest C-org remineralization rates reported for estuarine, deltaic, or shelf deposits, however, paradoxically, except where stabilized by mangroves or intertidal algal mats, they are usually suboxic and nonsulfidic. A combination of tides, wind-driven waves, and coastal currents forms massive fluid muds and mobile surface sediment layers similar to 0.5-2m, thick which are dynamically refluxed and frequently reoxidized. Overall, the seabed functions as a periodically mixed batch reactor, efficiently remineralizing organic matter in a gigantic sedimentary incinerator of global importance. Amazon River material entering the head of this dynamic dispersal system carries an initial terrestrial sedimentary Corg loading of similar to 0.7 mg Cm-2 particle surface area. Total C-org loading is lowered to similar to 0.2 mg Cm-2 in the proximal delta topset, similar to 60-70% of which remains of terrestrial origin. Loading decreases further to 0.12-0.14 mg Cm-2 (similar to 60% terrestrial) in mudbanks similar to 600 km downdrift along French Guiana, values comparable to those found in the oligotrophic deepsea. DOC/Sigma CO2 ratios in pore waters of French Guiana mudbanks indicate that > 90% of metabolized organic substrates are completely oxidized. Within the Amazon delta topset at the head of the dispersal system, both terrestrial and marine organic matter contribute substantially to early diagenetic remineralization, although reactive marine substrate dominates (similar to 60-70%). The conditional rate constant for terrestrial C-org in the delta topset is similar to 0.2 a(-1). As sedimentary C-org is depleted during transit, marine sources become virtually the exclusive substrate for remineralization except very near the mangrove shoreline. The delta C-13 and Delta C-14 values of pore water Sigma CO2 in mudbanks demonstrate that the primary source of remineralized organic matter within similar to 1 km of shore is a small quantity of bomb signature marine plankton (+ 80 parts per thousand). Thus, fresh marine organic material is constantly entrained into mobile deposits and increasingly drives early diagenetic reactions along the transit path. Relatively refractory terrestrial C-org is lost more slowly but steadily during sedimentary refluxing and suboxic diagenesis. Amazon Fan deposits formed during low sea level stand largely bypassed this suboxic sedimentary incinerator and stored material with up to similar to 3X the modern high stand inner shelf C-org load (Keil et al., 1997b. Proceedings of the Ocean Drilling Program, Scientific Results. Vol. 155. pp. 531-537). Sedimentary dynamics, including frequency and magnitude of remobilization, and the nature of dispersal systems are clearly key controls on diagenetic processes, biogeochemical cycling, and global C storage along the continental margins. (c) 2006 Elsevier Ltd. All rights reserved.
id: 979; 109UE Times Cited:28 Cited References Count:93

Chemical composition of the graphitic black carbon fraction in riverine and marine sediments at submicron scales using carbon X-ray spectromicroscopy - Haberstroh, P. R.; Brandes, J. A.; Gelinas, Y.; Dickens, A. F.; Wirick, S. (Geochimica et Cosmochimica Acta, 2006)
id: 1703

Chronologie des variations climatiques repides pendant la derniere periode glaciaire - Bard, E.; Rostek, F.; G, Menot-Combes (Comptes Rendus de l'Academie des Sciences, 2006)
id: 398

Deglaciation and Holocene climate change in the western Peruvian Andes - Weng, C. Y.; Bush, M. B.; Curtis, J. H.; Kolata, A. L.; Dillehay, T. D.; Binford, M. W. (Quaternary Research, 2006)
Pollen, charcoal, magnetic susceptibility, and bulk density data provide the first paleoecological record spanning the last 33,000 years from the western cordillera of the Peruvian Andes. Sparse super-puna vegetation existed before 30,000 cat yr B.P. around Lake Compuerta (3950 m elevation), prior to a sedimentary hiatus that lasted until c. 16,200 cat yr B.P. When sedimentation resumed, a glacial foreland or super-puna flora is represented in which Polylepis was a significant element. Glacial outwash, marked by high sedimentary magnetic susceptibility, increased from c. 16,200 cat yr B.P. and reached a peak at c. 13,200 cat yr B.P. Between c. 12,500 cat yr B.P. and 10,000 cat yr B.P., magnetic susceptibility was reduced. Vegetation shifts suggest a cool dry time, consistent with regional descriptions of the Younger Dryas event. Deglaciation resumes by 10,000 cat yr B.P. and the last ice is lost from the catchnient at similar to 7500 cat yr B.P. During the early Holocene warm and dry period between 10,000 and 5500 cat yr B.P., Alnus expanded in downslope forests. Alnus declined in abundance at 5500 cat yr B.P. when wetter and cooler conditions returned and human activity intensified. Maize (Zea mays) pollen first occurred in the core at similar to 2600 cat yr B.P., indicating a minimum age for local agriculture. An increase in Alnus pollen abundance at similar to 1000 cat yr B.P. could be due to human activity or perhaps due to a regional climate change associated with cultural turnover elsewhere in the Andes at this time. (c) 2006 University of Washington. All rights reserved.
058upTimes Cited:27Cited References Count:55

Dissolved and particulate organic matter source-age characterization in the upper and lower Chesapeake Bay: A combined isotope and biochemical approach - Loh, A. N.; Bauer, J. E.; Canuel, E. A. (Limnology and Oceanography, 2006)
In order to characterize the sources and ages of organic matter contributing to river and estuarine outflow waters, the present study investigated Delta C-14 and delta C-13 signatures of the major operationally defined biochemical classes of ultrafiltered dissolved organic matter (UDOM) in conjunction with lipid biomarker and elemental compositions of UDOM and suspended particulate organic matter (POM) in the Chesapeake Bay. Freshwater (Susquehanna River) UDOM was dominated by a molecularly uncharacterized (MUC) fraction, followed by total carbohydrate (TCHO), total hydrolysable amino acid (THAA) and total lipid (TLE) components. In contrast, UDOM at the bay mouth (salinity similar to 22-24) was comprised mainly of TCHO, followed by MUC, THAA, and TLE. The Delta C-14 and delta C-13 signatures of both UDOM and its major biochemical classes indicate that Susquehanna DOM is derived in part from old allochthonous terrestrial sources, whereas young marine sources dominate at the bay mouth. In contrast to the other biochemical classes, lipophilic DOM at both sites was very old (similar to 5,000-7,000 years B.P.). In addition, factor analysis of lipid biomarker compounds revealed unique signatures for the UDOM and POM pools that imply disparate source and/or recycling properties as well as potential influences due to physical partitioning. Lipid biomarker compounds showed that although autochthonous riverine/estuarine sources dominated both the UDOM and POM pools, terrigenous lipids were elevated in the Susquehanna during high flow conditions. The presence of lipid biomarkers diagnostic of "fresh" algal material in UDOM further suggested its greater reactivity than POM. The observed biochemical and lipid biomarker compositions and isotopic signatures of UDOM and POM are consistent with previous findings suggesting that these two major organic matter pools have dissimilar reactivities and cycling times, and they derive from comparatively unique source-age materials in rivers and estuaries.
045nhTimes Cited:24 Cited References Count:37
Keywords: biomarkers; carbon; delta-c-13; lipid-composition; ocean; radiocarbon; river; san-francisco; sediments; variability

Elemental and isotopic characterization of organic matter and carbon in the South Atlantic bight, a net heterotrophic ocean margin - De Alteris, J.; Bauer, J. E.; Perkey, D. W.; Keesee, E. J.; Cai, W. J. (Ocean Sciences Meeting, 2006)
id: 481

Evaluating the Holocene c=dynamics of oceanographic processes in the Southeast Brazilian Bight using accumulations of calcitic and aragonitic shells - Krause R.A, Jr.; Barbour-Wood, S.; Kowalewski, M.; Simoes, M. G.; Kaufman, D.; Romanek, C. S.; Wehmiller, J. F. (American Geophysical Union, Fall Meeting, 2006)
PP43A-01233
id: 716

Flooding of Bering Strait and Holocene climate in the Chukchi Sea - Keigwin, L. D.; Donnelly, J. P.; Cook, M. S.; Driscoll, N. W.; Brigham-Grette, J. (Geology, 2006)
id: 678

Geomorphologic controls on the age of particulate organic carbon from small mountainous and upland rivers - Leithold, E. L.; Blair, N. E.; Perkey, D. W. (Global Biogeochemical Cycles, 2006)
To assess the role that erosion processes play in governing the character of particulate organic carbon (POC) discharged from small mountainous and upland rivers, a suite of watersheds from Oregon, California, and New Zealand was investigated. The rivers share similar geology, tectonic setting, and climate, but have sediment yields that range over 3 orders of magnitude. The (14)C age of the POC loads is highly correlated with sediment yield. Carbon isotope mass balances reveal that the rivers carry bimodal mixtures of modern-plant-and ancient-rock-derived OC. At lower yields, modern plant OC dominates the material delivered to the river by sheetwash and shallow landsliding. With increasing yield, a progressively larger part of the POC is contributed directly from bedrock erosion via deep gully incision. Our results support the inference that active margin watersheds are important sources of aged POC to the ocean.
082xbTimes Cited:78Cited References Count:77
Keywords: 14C; kerogen recycling; particulate organic carbon

A geostatistical approach to watershed sources of aged riverine organic matter to the Hudson-Mohawk River system - Longworth, B. E.; Petsch, S. T.; Raymond, P. A.; Bauer, J. E. (American Geophysical Union Fall Meeting, 2006)
id: 483

Holocene elephant seal distribution implies warmer-than-present climate in the Ross Sea - Hall, B. L.; Hoelzel, A. R.; Baroni, C.; Denton, G. H.; Le Boeuf, B. J.; Overturf, B.; Topf, A. L. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
We show that southern elephant seal (Mirounga leonina) colonies existed proximate to the Ross Ice Shelf during the Holocene, well south of their core sub-Antarctic breeding and molting grounds. We propose that this was due to warming (including a previously unrecognized period from approximate to 1,100 to 2,300 C-14 yr B.P.) that decreased coastal sea ice and allowed penetration of warmer-than-present climate conditions into the Ross Embayment. If, as proposed in the literature, the ice shelf survived this period, it would have been exposed to environments substantially warmer than present.
id: 1918; PT: J; NR: 25; TC: 14; J9: P NATL ACAD SCI USA; PG: 5; GA: 064DM; UT: WOS:000239069400013

Incorporation of aged dissolved organic carbon (DOC) onto oceanic particulate organic carbon (POC): an experimental approach using carbon isotopes - Hwang, J.; Druffel, E. R. M.; Bauer, J. E. (Marine Chemistry, 2006)
id: 682

Late Holocene climate variability of South America reconstructed by a multi-proxy analysis of Chilean fjord sediments - Bertrand, S.; Hughen, K. A.; Giosan, L.; Tierney, J.; Sepfulveda, J.; Pantoja, S. (Abstracts, EGU General Assembly, 2006)
id: 560

Marine-derived 14C calibration and activity record for the past 50,000 years updated from the Cariaco Basin - Hughen, K. A.; Southon, J. A.; Lehman, S. J.; Bertrand, C. J. H.; Turnbull, J. (Quaternary Science Reviews, 2006)
id: 553

A multiproxy palaeoecological record of Holocene lake sediments from the Rio Tapajos, eastern Amazonia - Irion, G.; Bush, M. B.; de Mello, J. A. N.; Stuben, D.; Neumann, T.; Muller, G.; De, J. O.; Junk, J. W. (Palaeogeography Palaeoclimatology Palaeoecology, 2006)
Two sediment cores up to 42 m in length were raised from the wide, deep, section of the lower Tapajos River, Amazonia, referred to as Lago Tapajos. These cores reveal a history of subtle environmental change that began with the formation of Lago Tapajos as sea level rose about 11,000 years ago. The sediments of the lake were deposited fairly quickly-at a rate of ca. 4 m per millennium and are uniformly fine grained, with low organic content. The fossil pollen record derived from these sediments reveals that forest surrounded this site throughout the Holocene. The largest change in the core took place between ca. 5500 and 4200 cal. years BP and reflects a transition from coarser to finer sediments. Coincident with the change in sediment is a slight transition in the pollen spectra with an increase in Poaceae abundance at the expense of the pioneer tree Cecropia cecropia. A tentative explanation is offered in which increased human activity, possibly spurred by climatic change, resulted in the formation of some local grasslands. However, despite the apparent actions of humans, there is no indication of basin-wide transformation of landscapes in this record. The Holocene persistence of forest as the dominant landscape matrix around Lago Tapajos is supported by low delta C-13 values and by the constant geochemistry and mineralogy of the lake sediments. (c) 2006 Elsevier B.V. All rights reserved.
097fbTimes Cited:40Cited References Count:78

The mystery interval 1.5 to 14.5 kyrs ago - Denton, G. H.; Broecker, W. S.; Alley, R. B. (Pages News, 2006)
id: 701

The North Anatolian fault in the Gulf of Izmit (Turkey): Rapid vertical motion in response to minor bends of a non-vertical continental transform - Cormier, M. H.; Seeber, L.; McHugh, C. M. G.; Polonia, A.; Cagatay, M. N.; Emre, O.; Gasperini, L.; Gorur, N.; Bortoluzzi, G.; Bonatti, E.; Ryan, W. B. F.; Newman, K. R. (Journal of Geophysical Research, 2006)
id: 532

Rapid lateral particle transport in the Argentine Basin: Molecular 14C and 230Th evidence - Mollenhauer, Gesine; McManus, Jerry F.; Benthien, Albert; Muller, Peter J.; Eglinton, Timothy I. (Deep-Sea Research I, 2006)
id: 543

Rapid sea-level rise and Holocene climate in the Chukchi Sea - Keigwin, L. D.; Donnelly, J. P.; Cook, M. S.; Driscoll, N. W.; Brigham-Grette, J. (Geology, 2006)
Three new sediment cores from the Chukchi Sea preserve a record of local paleoenvironment, sedimentation, and flooding of the Chukchi Shelf (similar to-50 m) by glacial-eustatic sea-level rise. Radiocarbon dates on foraminifera provide the first marine evidence that the sea invaded Hope Valley (southern Chukchi Sea, -53 m) as early as 12 ka. The lack of significant sediment accumulation since ca. 7 ka in Hope Valley, southeastern Chukchi Shelf, is consistent with decreased sediment supply and fluvial discharge to the shelf as deglaciation of Alaska concluded. Abundant benthic foraminifera from a site west of Barrow Canyon indicate that surface waters were more productive 4-6 ka, and this productivity varied on centennial time scales. An offshore companion to this core contains a 20 m record of the Holocene. These results show that carefully selected core sites from the western Arctic Ocean can have a temporal resolution equal to the best cores from other regions, and that these sites can be exploited for high-resolution studies of the paleoenvironment.
089zkTimes Cited:67Cited References Count:18

The rise and fall of the refugial hypothesis - Bush, M. B.; De Oliveira, P. E. (Biota Neotropica, 2006)
id: 457

Rotasonic vibracores from northeastern North Carolina, cores OBX-10 through OBX-18 - Hoffman, C. W.; Farrell, K. M.; Pierson, J. A.; Ward, A. N.; Nickerson, J. G.; Brooks, R. W.; Ganey, J. G. (NCGS Open-file Report, 2006)
id: 704

Shell fragmentation as an indicator of benthic conditions - Best, Mairi M. R.; Bibeau, Karine; Spitzberg, Daniel; Thomas, Ellen; Varekamp, Johan C.; Bernatis, Jennifer (GSA Annual Meeting, 2006)
id: 749

Solid-state 13C NMR analysis of size and density fractions of marine sediments: Insight into organic carbon sources and preservation mechanisms - Dickens, A. F.; Baldock, J. A.; Smernik, R. J.; Wakeham, S. G.; Arnarson, T. S.; Gelinas, Y.; Hedges, J. I. (Geochimica et Cosmochimica Acta, 2006)
id: 1702

Sources and potential transformation of estuarine dissolved and particulate organic matter: a multi-tracer approach - McCallister, S. L.; Bauer, J. E.; Ducklow, H. W.; Canuel, E. A. (Organic Geochemistry, 2006)
id: 597

Spacial and temporal variation in cores from Lake Titicaca, Bolivia/Peru during the last 13,000 yrs - Fritz, S. C.; Baker, P. A.; Tapia, P.; Garland, J. (Quaternary International, 2006)
id: 588

Two ecological shifts in Long Island Sound during the industrial period - Thomas, E.; Varekamp, J. C.; Mecray, E. L.; Buchholtzten-Brink, M. R. L.; Cooper, S.; Brinkhuis, H.; Sangioirgio, F. (Long Island Sound Research Center, 2006)
id: 751

An updated 14C calibration and activity record for the past 50,000 years from marine Cariaco Basin, Abstract - Hughen, K. A.; Southon, J. A.; Lehman, S. J.; Bertrand, C. J. H.; Turnbull, J. (19th International Radiocarbon Conference, 2006)
id: 559

Variability in the character, age and reactivity of organic matter exported from rivers and estuaries to ocean margins - Bauer, J. E.; Cole, J. J.; Caraco, N. F.; Raymond, P. A.; Keesee, E. J.; Fernald, S.; Mull, K. (Ocean Sciences Meeting, 2006)
id: 476

Western Atlantic intertropical convergence zone variability over the last full glacial cycle, Abstract - Drenzek, N.; Hughe, K.; Sessions, A.; Bice, M.; Eglinton, T. I. (Eos Trans. AGU 87, Fall Meeting Suppl., 2006)
id: 558

A 17,000 year history of Andean climatic and vegetation change from Laguna de Chochos, Peru - Bush, M. B.; Hansen, B. C. S.; Rodbell, D. T.; Seltzer, G. O.; Young, K. R.; Leon, B.; Abbott, M. B.; Silman, M. R.; Gosling, W. D. (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice-accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global-scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm-dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500-yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600-yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape.
id: 1015

The 8200 year B. P. event in the slop water system, western sublpolar North Atlantic - Keigwin, L. D.; Sachs, J. P.; Rosenthal, Y.; Boyle, E. A. (Paleoceanography, 2005)
id: 1097

Assessing variability in the character and reactivity of DOM and POM delivered to the oceans by rivers and estuaries - Bauer, J. E. (Gordon Research Conference on Chemical Oceanography, 2005)
id: 1025

Beads, bifaces, and boats: an early maritime adaptation on the south coast of San Miguel Island, California - Erlandson, Jon M.; Braje, Todd J.; Rick, Torben C.; Peterson, Jenna (American Anthropologist, 2005)
id: 442

Biogeochemical investigations of marine methane seeps, Hydrate Ridge, Oregon - Valentine, D. L.; Kastner, M.; Wardlaw, G. D.; Wang, X. C.; Purdy, A.; Bartlett, D. H. (Journal of Geophysical Research-Biogeosciences, 2005)
[1] A series of biogeochemical studies were conducted at the southern summit of Hydrate Ridge, offshore Oregon. Using the submersible DSV Alvin, sediment push cores were collected from two distinct seep environments characterized by the presence of clam fields (CF) or microbial mats (MM) at the sediment-water interface; samples were also collected from a nearby reference site characterized by a barren surface at the sediment-water interface. Sediment samples from each setting were analyzed for the depth distributions of total organic carbon (concentrations, delta C-13 and Delta C-14), total sedimentary nitrogen, and microbial abundance. Pore fluids were extracted and analyzed for sulfate, alkalinity, sulfide, organic carbon, and volatile organic acids. These depth distributions clearly indicate the presence of three distinctive biogeochemical settings in the surface sediments of Hydrate Ridge, and provide the basis for a comparative biogeochemical analysis. Both CF and MM sites display properties indicating enhanced microbial activity in the subsurface, compared with the reference site. MM sites display evidence of net biomass production in the subsurface; however, a loss of sediment nitrogen relative to the reference site indicates that mineralization is also enhanced. Calculations based on the removal of nitrogen indicate that greater than 30% of autochthonous organic material is lost to enhanced mineralization in the top 23 cm of one MM site. An isotope mass balance of sediment-bound organic carbon indicates a mixed source, including methane and allochthonous organic carbon dissolved in the seep fluids. The concentrations of organic carbon dissolved in seep fluids reach values of 22 mM and provide a first indication that advective transport of dissolved organic carbon from great depth may supply an important source of energy and carbon to "methane seep'' communities.
090wnTimes Cited:19 Cited References Count:72
Keywords: anaerobic oxidation; authigenic carbonates; cascadia convergent margin; community structure; dissolved organic-carbon; fluid-flow; ne pacific; odp site 892b; phylogenetic analysis; sulfate-reducing bacteria

Coastal foraging at Otter Cave: a 6600 year old shell midden on San Miquel Island, California - Erlandson, Jon M.; Vellanoweth, Rene L.; Rick, Torben C.; Batterson, Melissa R. (Journal of California and Great Basin Anthropology, 2005)
id: 580

Continuous-Flow Accelerator Mass Spectrometry - Roberts, M. L.; von Reden, K. F.; Han, B. X.; Schneider, R. J.; Benthien, A.; Hayes, J. M. (the International Symposium on Utilization of Accelerators, 2005)
id: 767

The demise of the alga Botryococcus Braunii from a Norwegian fjord is due to early eutrophication - Smittenberg, R. H.; Baas, M.; Schouten, S.; Sinninghe-Damste, J. S. (The Holocene, 2005)
id: 1148

Dissolved and particulate organic matter source-age characterization in river and estuarine outflow waters: a combined isotope and biochemical approach - Loh, A. N.; Bauer, J. E.; Canuel, E. A. (ASLO Summer Meeting, 2005)
id: 482

Effects of natural sunlight on decomposition of estuarine dissolved organic C, N and P and bacterial growth - McCallister, S. L.; Bauer, J. E.; Kelly, J.; Ducklow, H. W. (Aquatic Microbial Ecology, 2005)
id: 1101

The Fe3+/ΣFe ratios of MORB glasses and their implications for mantle melting - Bezos, Antoine; Humler, Eric (Geochimica et Cosmochimica Acta, 2005)
The Fe3+/ΣFe ratio of 104 MORB glasses from the Pacific, the Atlantic, the Indian, and the Red Sea spreading centers have been determined using wet chemical Fe2+ analyses and electron microprobe FeOtotal measurements. The data provide a new estimate for the MORB oxygen fugacity (fO2) of 0.41 ± 0.43 (1sigma, N = 100) log units below the fayalite-magnetite-quartz buffer (FMQ), equivalent to a Fe3+/ΣFe = 0.12 ± 0.02 (1sigma, N = 104). This new fO2 estimate is 0.8 log units more oxidized than the average fO2 proposed by Christie et al. (1986) (FMQ-1.20 ± 0.44; Fe3+/ΣFe = 0.07 ± 0.01; N = 87). This slight difference may be related in part to the 3.5% underestimation of the Fe2+ concentration determined by Christie et al. (1986) compared with this study. MORB oxygen fugacity does not display any significant difference between the three main oceanic domains, or between enriched and depleted MORB. Yet, the iron red-ox state ratio shows a broad increase during fractional crystallization. Detailed study of magmatic suites highlights the lack of systematic Fe3+/ΣFe ratio fractionation during differentiation. Despite the large variations of inferred partial melting degrees (from 5 to 20%), the present data set does not provide any evidence of Fe3+/ΣFe relationships with partial melting proxies such as Na8.0. Based on the Fe3+ systematics during partial melting, it is suggested that the oxidation state of MORB reflects a “buffered mantle melting process” resulting in the apparent compatible behavior of Fe3+ during partial melting, and in the relatively constant Fe3+/ΣFe ratio irrespective of the extent of melting. This result implies that partial melting processes may be open relative to oxygen. We propose a model where the Fe3+/ΣFe ratio in the melt is buffered during partial melting. The MORB Fe2O3 systematics can be accounted for by using a fO2 of FMQ-1 that is equivalent to the average fO2 reported for abyssal peridotites.
id: 1578

Geologic implications of Late Quaternary isostatic adjustment in the Penobscot/Kennebec River system, Maine - Kelley, Alice R.; Kelly, Joseph T.; Belknap, Daniel F.; Gontz, Allen M. (Geological Society of America Abstracts with Programs, 2005)
id: 1173

Global ocean data analysis project (GLODAP): Results and data, ORNL/CDIAC-145, NDP-145 - Sabine, C. L.; Key, R. M.; Kozyr, A.; Feely, R. A.; Wanninkhof, R.; Millero, F. J.; Peng, T. H.; Bullister, J. L.; Lee, K. (2005)
id: 529

Holocene aminochronology and time-averaging fro Chesapeake Bay mulinia - Edwards, A. L.; Wehmiller, J. R.; Lockwood, R.; Kaufman, D.; Bright, J.; Cronin, T.; Willard, D. (Geological Society of America Abstracts with Programs, 2005)
id: 585

Holocene hydrologic variation at Lake Titicaca, Bolivia/Peru, and its relationship to North Atlantic climate variation - Baker, P. A.; Fritz, S. C.; Garland, J.; Ekdahl, E. (Journal of Quaternary Science, 2005)
A growing number of sites in the Northern Hemisphere show centennial- to millennial-scale climate variation that has been correlated with change in solar variability or with change in North Atlantic Circulation. However, it is unclear how (or whether) these oscillations in the climate system are manifest in the Southern Hemisphere because of a lack of sites with suitably high sampling resolution. In this paper, we reconstruct the lake-level history of Lake Titicaca, using the carbon isotopic content of sedimentary organic matter, to evaluate centennial- to millennial-scale precipitation variation and its phasing relative to sites in the Northern Hemisphere. The pattern and timing of lake-level change in Lake Titicaca is similar to the ice-rafted debris record of Holocene Bond events, demonstrating a possible coupling between precipitation variation on the Altiplano and North Atlantic sea-surface temperatures (SSTs). The cold periods of the Holocene Bond events correspond with periods of increased precipitation on the Altiplano. Holocene precipitation variability on the Altiplano is anti-phased with respect to precipitation in the Northern Hemisphere monsoon region. More generally, the tropical Andes underwent large changes in precipitation on centennial-to-millennial timescales during the Holocene. Copyright (C) 2005 John Wiley & Sons, Ltd.
id: 1095; 000CQ Times Cited:21 Cited References Count:46

Holocene molluscan aminostratigraphy of Chesapeake Bay sediments - Edwards, A. L.; Lockwood, R.; Wehmiller, J.; Cronin, T.; Kaufman, D.; Bright, J. (Geological Society of America Abstracts with Programs, 2005)
id: 586

The Holocene radiocarbon reservoir effect in the western Ross Sea - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellog, Thomas (Annual West Antarctic Ice Sheet Meeting, 2005)
id: 434

Holocene terebratulid brachiopods from the southern Brazilian Shelf (South Atlantic): Ecology, taphonomy, and time-averaging - Kowalewski, M.; Simoes, M. G.; Barbour-Wood, S. L.; Krause R.A, Jr.; Rodriguez, S. C.; Wehmiller, J. F.; Rodland, D. L.; Carroll, M. (Fifth International Brachiopod Congress, 2005)
id: 1171; Abstracts, p. 34-35

Impact of millennial-scale Holocene climate variability on eastern North American terrestrial ecosystems: pollen-based climatic reconstruction - Willard, D. A.; Bernhardt, C. E.; Korejwo, D. A.; Meyers, S. R. (Global and Planetary Change, 2005)
We present paleoclimatic evidence for a series of Holocene millennial-scale cool intervals in eastern North America that occurred every similar to 1400 years and lasted similar to 300-500 years, based on pollen data from Chesapeake Bay in the mid-Atlantic region of the United States. The cool events are indicated by significant decreases in pine pollen, which we interpret as representing decreases in January temperatures of between 0.2 degrees and 2 degrees C. These temperature decreases include excursions during the Little Ice Age (similar to 1300-1600 AD) and the 8 ka cold event. The timing of the pine minima is correlated with a series of quasi-periodic cold intervals documented by various proxies in Greenland, North Atlantic, and Alaskan cores and with solar minima interpreted from cosmogenic isotope records. These events may represent changes in circumpolar vortex size and configuration in response to intervals of decreased solar activity, which altered jet stream patterns to enhance meridional circulation over eastern North America. (c) 2004 Elsevier B.V All rights reserved.
944zeTimes Cited:48Cited References Count:68

Input of particulate organic and dissolved inorganic carbon from the Amazon to the Atlantic Ocean - Druffel, E. R. M.; Bauer, J. E.; Griffin, S. (Geochemistry Geophysics Geosystems, 2005)
We report concentrations and isotope measurements (radiocarbon and stable carbon) of dissolved inorganic carbon (DIC) and suspended particulate organic carbon (POC) in waters collected from the mouth of the Amazon River and the North Brazil Current. Samples were collected in November 1991, when the Amazon hydrograph was at its annual minimum and the North Brazil Current had retroflected into the equatorial North Atlantic. The DIC D 14 C results revealed postbomb carbon in river and ocean waters, with slightly higher values at the river mouth. The low DIC delta(13)C signature of the river end-member (-11%) demonstrates that about half of the DIC originated from the remineralization of terrestrially derived organic matter. A linear relationship between DIC and salinity indicates that DIC was mixed nearly conservatively in the transition zone from the river mouth to the open ocean, though there was a small amount (<= 10%) of organic matter remineralization in the mesohaline region. The POC Delta(14)C values in the river mouth were markedly lower than those values from the western Amazon region (Hedges et al., 1986). We conclude that the dominant source of POC near the river mouth and in the inner Amazon plume during November 1991 was aged, resuspended material of significant terrestrial character derived from shelf sediments, while the outer plume contained mainly marine-derived POC.
909pwTimes Cited:17 Cited References Count:21
Keywords: accumulation; amazon; C-14; carbon cycling; CO2; continental-shelf; poc; radiocarbon; river system; Sediment; total co(2); water

An investigation of accurate gas exchange measurements for determing a large river carbon isotope mass balance - Raymond, P. A.; McGillis, W. R.; Bauer, J. E.; Caraco, N. F.; Cole, J. J. (37th Liege International Colloquium on Gas Transfer at Water Survaces, 2005)
id: 490

The last glacial maximum: stability and change in an Andean cloud forest - Urrego, D. H.; Silman, M. R.; Bush, M. B. (Journal of Quaternary Science, 2005)
id: 458

Late-Quaternary lowstands of lake Bosumtwi, Ghana: evidence from high-resolution seismic-reflection and sediment-core data - Brooks, K.; Scholz, C. A.; King, J. W.; Peck, J.; Overpeck, J. T.; Russell, J. M.; Amoako, P. Y. O. (Palaeogeography Palaeoclimatology Palaeoecology, 2005)
Results from the first high-resolution, single-channel seismic-reflection survey of tropical Lake Bosumtwi, Ghana, and sedimentological data from a C-14-dated sediment piston core were used to revise and extend the basin's late-Quaternary lake level history. We report four seismic sequence boundaries and an exposure surface from a sediment core. which are interpreted as erosional surfaces formed at times of drastic low lake level. The youngest erosional surf-ace occurs as much as 31 In below present lake level (bpll) and up to 0.7 in below the present sediment-water interface. This most recent unconformity observed in the seismic data is interpreted to be coeval with the basin-wide late-Holocene dry period between 0.5 and 1 cal ky BP (calendar years before present). Another exposure surface observed in a sediment core is based on an abrupt contact separating low density, wet, clay rich sediments from underlying high density, compact, silt-rich and rootlet-rich sediments, and is interpreted to have developed prior to 16.8 cal ky BP when the lake was similar to60 in bpll. Three older, erosional surfaces occur at depths of similar to92 +/- 3, 102 +/- 3, and 107 +/- 4 in bpll, suggesting numerous lowstands in Lake Bosumtwi during the late-Pleistocene. By extrapolation of average sedimentation rates (0.41 m/ky) from the upper similar to10.5 m of sediment, we estimate the ages of these older lowstands to be similar to65, similar to86 similar to108 cal ky BP. The lowstands of Lake Bosumtwi evidenced from the seismic and sediment core data are interpreted as a response to increased aridity in this part of the equatorial tropics and may correlate to other observed continent-wide shifts in African climate over the past 100 ky and possibly to rapid climatic shifts observed at high latitudes. Determining the precise timing of these lowstands will ultimately reveal much about the drought dynamics of tropical and subtropical Africa. (C) 2004 Elsevier B.V. All rights reserved.
892ujTimes Cited:21Cited References Count:54

Mid-Holocene hydrologic change and hypolimnion formation in Lake Erie - Clotts, R. A.; McCambridge, C. E.; Barrera, E.; Saylor, B. Z.; Palmer, D. F.; Coakley, J. P. (Journal of Great Lakes Research, 2005)
id: 688

Millennial scale variability in tropical South American vegetation during the last glaciation - Hughen, K. A.; Drenzek, N.; Bice, M.; Eglinton, T. I. (Eos Trans. AGU, 86(52), Fall Meeting Suppl., 2005)
id: 563

Morphodynamics and evolution of Danube delta - Giosan, L.; Vespremeanu, E.; Donnelly, J. P.; Bhattacharya, J.; Buonaiuto, F. (Journal of Sedimentary Research, 2005)
id: 499

The multi-centennial dynamics of an upwelling system revealed by stable isotope and trace element sclerochronology of amino-acid dated bivalve and brachiopod shells - Krause, R. A., Jr.; Barbour-Wood, S.; Romanek, C. S.; Kowalewski, M.; Simoes, M. G.; Wehmiller, J. F. (Geological Society of America Abstracts with Programs, 2005)
id: 717

Organic matter inputs and metabolism in a large river estuary (the Hudson): Insights from natural abundance isotopes and whole system metabolism - Caraco, N. F.; Cole, J. J.; Raymond, P. A.; Bauer, J. E. (American Society of Limnology and Oceanography, 2005)
id: 478

Pre- and post-industrial environmental changes as revealed by the biogeochemical sedimentary record of Drammensfjord, Norway - Smittenberg, R. H.; Baas, M.; Green, M. J.; Hopmans, E. C.; Schouten, S.; Damste, J. S. S. (Marine Geology, 2005)
The biogeochemical sedimentary record of the anoxic Drammensfjord, Norway, was investigated on a decadal to centennial time scale over the last millennium, in order to reconstruct the pre-industrial fjord environment and ecosystem and human-induced environmental changes. The sediments were dated by a combination of C-14 and Pb-210 analysis and varve counting. Analysis of the bulk sedimentary parameters and of the biomarker distribution revealed that the sedimentary organic matter of the fjord is primarily of terrigetious origin, indicating that the fjord was oligotrophic or mesotrophic. The fjord's bottom water has been continuously euxinic since at least 1000 AD, but photic zone euxinia occurred only irregularly in the fjord. The organic matter flux and composition remained virtually invariable until the 18th century. After that time, the flux of material derived from coniferous trees started to increase, indicated by elevated concentrations of dehydroabietic acid and related compounds, but also by raising levels of C-24 n-alcohols and fatty acids. This marked the onset of sawmill activities in the hinterland. After the beginning of the industrial revolution, around 1850, the flux of organic waste from sawmills and paper mills increased substantially. It is suggested that slow bacterial degradation of this relatively nutrient-poor organic waste caused a gradual eutrophication trend, which is reflected in substantial increased bacterial and moderately increased other aquatic biomarker accumulation rates. After the industrial revolution, this trend accelerated and was possibly enhanced by a growing population of the area with accompanymg agricultural and domestic waste. This promoted primary productivity and changed the phytoplankton composition in the fjord.(C) 2004 Elsevier B.V. All rights reserved.
890unTimes Cited:23Cited References Count:105

Rapid lateral particle transport in the Argintine Basin: Th-230 and molecular C-14 Evidence, Poster - Mollenhauer, Gesine; McManus, J. F.; Benthien, A.; Muller, P. J.; Eglinton, T. I. (EGU General Assembly, 2005)
id: 548

Reassessing human settlement on the south coast of San Miguel Island, California: The use of 14C dating as a reconnaissance tool - Braje, Todd J.; Erlandson, Jon M.; Rick, Torben C. (Radiocarbon, 2005)
Californias San Miguel Island contains over 600 archaeological sites, some occupied as early as 12,000 yr ago and most located along the islands north coast. Archaeologists have long believed the south coast to have been marginal or largely uninhabited. Burial of some landforms by sand dunes deposited after historical overgrazing, the lack of systematic survey, and a dearth of radiocarbon dating have also contributed to an underestimation of the intensity of human land use along the south coast of San Miguel Island. Our recent reconnaissance and dating of shell middens on the islands south coast indicate more intensive occupation than previously thought, with numerous south coast sites spanning at least the past 9000 yr, and demonstrate the utility of combining systematic archaeological reconnaissance and radiometrics in reconstructions of human settlement and historical ecology in coastal environments.
id: 579

Sedimentation and carbon burial on the northern California continental shelf: the signatures of land-use change - Leithold, E. L.; Perkey, D. W.; Blair, N. E.; Creamer, T. N. (Continental Shelf Research, 2005)
The burial of organic carbon (OC) on continental margins is strongly coupled to the supply and accumulation of inorganic mineral particles. It follows that carbon burial on the margins should be impacted by changes in riverine sediment delivery, yet these impacts have not been well documented. In this study, an similar to2000-year record of sedimentation and carbon burial on the continental shelf offshore from the Eel River in northern California was examined. The record reveals a 6-11-fold increase in the rate of sediment accumulation on the mid-shelf beginning about 1955, and a concomitant decrease in grain size and increase in flood-layer preservation. At the same time. the age of buried wood fragments abruptly decreased and their stable carbon isotopic composition became enriched in C-13. We argue that these changes can be explained largely as the result of altered land use in the Eel watershed during the past century and its impacts on shelf sediment dispersal processes.Sedimentary OC on the Eel shelf consists primarily of discrete wood fragments associated with coarse-silt- and sandsized particles, and of organic matter strongly bound to clay-sized mineral grains. The clay fraction is a particularly sensitive recorder of environmental change in the Eel system. Above the 1995 horizon, the clay fraction shows an abrupt decrease in OC concentration and loading (OC content normalized to particle surface area) attendant with the increased accumulation rate. Kerogen carbon constitutes a relatively constant proportion of the clay-associated OC throughout the similar to2000-year record. Increases in mass wasting and input of bedrock material following the onset of intensive industrial logging in the Eel watershed may have resulted in a lower loading of terrestrial plant OC in the clay fraction deposited after 1955 as suggested by isotopic mass balance calculations.The Eel River is representative of small mountainous watersheds worldwide that deliver a major portion of the sediment and carbon flux to the margins and that have been strongly impacted by land-use change during the past century. Our results suggest that such changes leave a distinctive mark in both the sedimentological and geochemical records preserved offshore. (C) 2004 Elsevier Ltd. All rights reserved.
894cyTimes Cited:29Cited References Count:109

Subducting oceanic crust: The source of deep diamonds - Tappert, R.; Stachel, T.; Harris, J. W.; Muehlenbachs, K.; Ludwig, T.; Brey, G. P. (Geology, 2005)
Inclusions of majoritic garnet in diamonds from the Jagersfontein kimberlite formed at unusually great depths of similar to 250 to > 500 km in the asthenosphere and transition zone. The original host rocks were derived from a much shallower, basaltic (eclogitic) source. The presence of negative Eu anomalies in all majoritic garnets requires a crustal origin, thereby linking these very deep diamond sources to subducting oceanic crust. The carbon isotope values (delta(13)C) of the host diamonds fall within a narrow range at similar to -20%, which is fundamentally different from the broad range (-24% to -2%) and bimodal distribution of carbon isotopes of Jagersfontein diamonds that formed in the shallower lithosphere. This indicates that majoritic garnet-bearing diamonds at Jagersfontein inherited their light carbon isotopic composition directly from organic matter contained in a subducting slab. These diamonds were likely formed by direct conversion from graphite, well within the diamond stability field.
938hnTimes Cited:65Cited References Count:26

Submerged paleoshorelines in the southern and western Black Sea - implications for inundated prehistoric archaeological sites - Coleman, Dwight F.; Ballard, Robert D. (The Black Sea Flood Questions: Changes in Coastline, Climate, and Human Settlement, 2005)
id: 1058

48,000 years of climate and forest change from a biodiversity hotspot - Bush, M. B.; Silman, M. R.; Urrego, D. H. (Science, 2004)
A continuous 48,000-year-long paleoecological record from Neotropical lower montane forest reveals a consistent forest presence and an ice-age cooling of ∼5° to 9°C. After 30,000 years of compositional stability, a steady turnover of species marks the 8000-year-long transition from ice-age to Holocene conditions. Although the changes were directional, the rates of community change were no different during this transitional period than in the preceding 30,000-year period of community stability. The warming rate of about 1°C per millennium during the Pleistocene-Holocene transition was an order of magnitude less than the projected changes for the 21st century.
id: 1016

An 8700 year old shell midden from the south coast of San Miguel Island, California - Braje, Todd J.; Erlandson, Jon M.; Rick, Torben C. (Current Research in the Pleistocene, 2004)
id: 1091

Assessing sources and agesof organic matter supporting river and estuarine bacterial production: a multiple isotope (Delta14C, delta13C and delta15N) approach - McCallister, S. L.; Bauer, J. E.; Cherrier, J. C.; Ducklow, H. W. (Limnology and Oceanography, 2004)
id: 1153

A backbarrier overwash record of intense storms from Brigantine, New Jersey - Donnelly, J. P.; Butler, J.; Roll, S.; Wengren, M.; Webb, T. (Marine Geology, 2004)
Analysis of aerial photographs and historic charts indicates that the barrier beach at Brigantine, NJ has migrated landward 300 to 400 m since 1869, primarily as a result of overwash during hurricanes and winter storms. A series of vibracores from the backbarrier salt marsh reveals a millennial-scale stratigraphic record of overwash deposition. Carbon-14 (C-14) and Cesium-137 (Cs-137) radioisotopic methods were used to date over-wash deposits (washovers). The ages of recent washovers are consistent with deposition during intense storms in 1938, 1944, 1950, and 1962. An additional overwash deposit recovered in five of the sediment cores was likely deposited by an intense hurricane strike in 1821 or possibly in 1788. Two prehistoric overwash fans were likely deposited by intense storms striking the New Jersey Coast in the 7th to l4th centuries and 6th to 7th centuries A.D. The landward barrier migration indicates that the older overwash sediments were likely transported a considerably greater distance than the more recent overwash fans. The greater distance of transport may indicate that the prehistoric storms that deposited overwash fans across the study site were more intense than the most intense storm to strike this coast in the historic period, the hurricane of 182 1. The spatially variable occurrence of overwash deposition at this site points to a need for multisite stratigraphic surveys of extensive stretches of the coast in order to develop reliable records of past intense storm frequency from backbarrier environments. (C) 2004 Elsevier B.V. All rights reserved.
Sp. Iss. SI853thTimes Cited:74Cited References Count:37

Busted balls shell midden (CA-SMI-606): an early coastal site on San Miguel Island, California - Erlandson, Jon M.; Rick, Torben C.; Batterson, Melissa R. (North American Archaeologist, 2004)
id: 583

Carbon-isotopic shifts associated with heterotrophy and biosynthetic pathways in direct- and indirect-developing sea urchins - Villinski, J. C.; Hayes, J. M.; Villinski, J. T.; Brassell, S. C.; Raff, R. A. (Marine Ecology Progress Series, 2004)
Natural abundances of C-13 were measured in bulk biomass and in individual lipids isolated from 2 species of sea urchins, Heliocidaris erythrogramma and H. tuberculata, and from calcareous and green benthic algae on which they were feeding. Planktonic larvae of H. erythrogramma are lecithotrophic whereas those of H. tuberculata are planktotrophic. The organisms were collected from a subtidal environment in Botany Bay, Sydney, Australia. The biomass of both consumers was enriched in C-13 relative to their diets by up to 1.8parts per thousand. The carbon skeletons of sterols from the urchins derive at least in part from de novo biosynthesis by the urchins. Depending on chain length and degree of unsaturation, carboxylic acids from the urchins derive from de novo blosynthesis (14:0, unsaturated acids), from the diet (18:0), or from both these sources (16:0). H. tuberculata synthesizes a greater distribution and proportion of unsaturated carboxylic acids. Odd-C and branched-chain carboxylic acids derive in part from bacterial sources and are enriched in C-13 relative to algal lipids and depleted relative to those in urchins. Only H. erythrogramma, which uses wax esters-as storage lipids in its relatively large and buoyant eggs, produces significant quantities of n-alkanols; n-alkanols in H, tuberculata derive from the diet. In terms of molecular distributions and isotopic compositions, the lipids in fecal matter from both heterotrophs resemble those of the diet rather than those of the urchins.
847vnTimes Cited:4Cited References Count:34

CA-SMI-548: A 9500 year old shell midden at Running Springs, San Miquel Island, California - Erlandson, Jon M.; Rick, Torben C.; Vellanoweth, Rene L.; Largaespada, Tony (Emerging from the Ice Age: Early Holocene Occupations on the Central California Coast, 2004)
id: 584

Chronology of sediment deposition in Upper Klamath Lake, Oregon - Colman, S. M.; Bradbury, J. P.; McGeehin, J. P.; Holmes, C. W.; Sarna-Wojcicki, A. M.; Edgington, D. (Journal of Paleolimnology, 2004)
A combination of tephrochronology and 14C, 210Pb, and 137Cs measurements provides a robust chronology for sedimentation in Upper Klamath Lake during the last 45 000 years. Mixing of surficial sediments and possible mobility of the radio-isotopes limit the usefulness of the 137Cs and 210Pb data, but 210Pb profiles provide reasonable average sediment accumulation rates for the last 100–150 years. Radiocarbon ages near the top of the core are somewhat erratic and are too old, probably as a result of detrital organic carbon, which may have become a more common component in recent times as surrounding marshes were drained. Below the tops of the cores, radiocarbon ages in the center of the basin appear to be about 400 years too old, while those on the margin appear to be accurate, based on comparisons with tephra layers of known age.Taken together, the data can be combined into reasonable age models for each site. Sediments have accumulated at site K1, near the center of the basin, about 2 times faster than at site CM2, on the margin of the lake. The rates are about 0.10 and 0.05 cm/yr, respectively. The chronological data also indicate that accumulation rates were slower during the early to middle Holocene than during the late Holocene, consistent with increasing wetness in the late Holocene.
id: 182

Collapse and rapid resumption of Atlantic meridional circulation linked to deglacial climate changes - McManus, J. F.; Francois, R.; Gherardi, J. M.; Keigwin, L. D.; Brown-Leger, S. (Nature, 2004)
The Atlantic meridional overturning circulation is widely believed to affect climate. Changes in ocean circulation have been inferred from records of the deep water chemical composition derived from sedimentary nutrient proxies, but their impact on climate is difficult to assess because such reconstructions provide insufficient constraints on the rate of overturning. Here we report measurements of 231Pa/230Th, a kinematic proxy for the meridional overturning circulation, in a sediment core from the subtropical North Atlantic Ocean. We find that the meridional overturning was nearly, or completely, eliminated during the coldest deglacial interval in the North Atlantic region, beginning with the catastrophic iceberg discharge Heinrich event H1, 17,500 yr ago, and declined sharply but briefly into the Younger Dryas cold event, about 12,700 yr ago. Following these cold events, the 231Pa/230Th record indicates that rapid accelerations of the meridional overturning circulation were concurrent with the two strongest regional warming events during deglaciation. These results confirm the significance of variations in the rate of the Atlantic meridional overturning circulation for abrupt climate changes.
McManus, J FFrancois, RGherardi, J-MKeigwin, L DBrown-Leger, SengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.England2004/04/23 05:00Nature. 2004 Apr 22;428(6985):834-7.

A comparative analysis of time averaging for bivalves and brachiopods from a modern tropical shelf - Krause R.A, Jr.; Barbourl-Wood, S. L.; Wehmiller, J. F.; Kowalewski, M.; Simoes, M. G. (Geological Society of America, Abstracts with Programs, 2004)
36(5):383
id: 718

Controls on the variability of organic matter and dissolved inorganic carbon ages in northeast U.S. rivers - Raymond, P. A.; Bauer, J. E.; Caraco, N. F.; Cole, J. J.; Longworth, B. E.; Petsch, S. T. (Marine Chemistry, 2004)
id: 967

Dating the rise of atmospheric oxygen - Bekker, A.; Holland, H. D.; Wang, P. L.; Rumble, D.; Stein, H. J.; Hannah, J. L.; Coetzee, L. L.; Beukes, N. J. (Nature, 2004)
Several lines of geological and geochemical evidence indicate that the level of atmospheric oxygen was extremely low before 2.45 billion years (Gyr) ago, and that it had reached considerable levels by 2.22 Gyr ago. Here we present evidence that the rise of atmospheric oxygen had occurred by 2.32 Gyr ago. We found that syngenetic pyrite is present in organic-rich shales of the 2.32-Gyr-old Rooihoogte and Timeball Hill formations, South Africa. The range of the isotopic composition of sulphur in this pyrite is large and shows no evidence of mass-independent fractionation, indicating that atmospheric oxygen was present at significant levels (that is, greater than 10(-5) times that of the present atmospheric level) during the deposition of these units. The presence of rounded pebbles of sideritic iron formation at the base of the Rooihoogte Formation and an extensive and thick ironstone layer consisting of haematitic pisolites and oolites in the upper Timeball Hill Formation indicate that atmospheric oxygen rose significantly, perhaps for the first time, during the deposition of the Rooihoogte and Timeball Hill formations. These units were deposited between what are probably the second and third of the three Palaeoproterozoic glacial events.
id: 1534; Bekker, A Holland, H D Wang, P-L Rumble, D 3rd Stein, H J Hannah, J L Coetzee, L L Beukes, N J England Nature. 2004 Jan 8;427(6970):117-20.

Early diagenetic remineralization of sedimentary organic C in the Gulf of Papua deltaic complex (Papua New Guinea): Net loss of terrestrial C and diagenetic fractionation of C isotopes - Aller, R. C.; Blair, N. E. (Geochimica et Cosmochimica Acta, 2004)
Oceania supplies similar to40% of the global riverine flux of organic carbon, approximately half of which is injected onto broad continental shelves and processed in shallow deltaic systems. The Gulf of Papua, on the south coast of the large island of New Guinea, is one such deltaic clinoform complex. It receives similar to4 Mt yr(-1) particulate terrestrial organic carbon with initial particle C-org loading similar to0.7 mg m(-2). C-org loading is reduced to similar to0.3 mg m(-2) in the topset-upper foreset zones of the delta despite additional inputs of mangrove and planktonic detritus, and high net sediment accumulation rates of 1-4 cm yr(-1) . Carbon isotopic analyses (delta(3)C, Delta(14)C) of SigmaCO(2) and C-org demonstrate rapid (
id: 976; 813FD Times Cited:44 Cited References Count:72

The eutrophication of Long Island Sound, abstract - Varekamp, J. C.; Lugolobi, F.; Thomas, E.; Mecray, E.; Buchholtz ten Brink, M. R. (EOS Trans. AGU, 2004)
id: 740

Evaluation of ocean carbon cycle models with data-based metrics - Matsumoto, K.; Sarmiento, J. L.; Key, R. M.; Aumont, O.; Bullister, J. L.; Caldeira, K.; Campin, J. M.; Doney, S. C.; Drange, H.; Dutay, J. C.; Follows, M.; Gao, Y.; et al. (Geophysical Research Letters, 2004)
New radiocarbon and chlorofluorocarbon-11 data from the World Ocean Circulation Experiment are used to assess a suite of 19 ocean carbon cycle models. We use the distributions and inventories of these tracers as quantitative metrics of model skill and find that only about a quarter of the suite is consistent with the new data-based metrics. This should serve as a warning bell to the larger community that not all is well with current generation of ocean carbon cycle models. At the same time, this highlights the danger in simply using the available models to represent the state-of-the-art modeling without considering the credibility of each model.
811adTimes Cited:110 Cited References Count:17
Keywords: anthropogenic co2; pacific-ocean; radiocarbon

Evidence for Late Holocene earthquakes on the Utsalady Point Fault, northern puget lowland, Washington - Johnson, S. Y.; Nelson, A. R.; Personius, S. F.; Wells, R. E.; Kelsey, H. N.; Sherrod, B. L.; Okumura, K.; Koehler, R.; Witter, R. C.; Bradley, L. A.; Harding, D. J. (Bulletin of the Seismological Society of America, 2004)
Trenches across the Utsalady Point fault in the northern Puget Lowland of Washington reveal evidence of at least one and probably two late Holocene earthquakes. The "Teeka"' and "Duffers" trenches were located along a 1.4-km-long. 1- to 4-m-high, northwest-trending, southwest-facing. topographic scarp recognized from Airborne Laser Swath Mapping. Glaciomarine drift exposed in the trenches reveals evidence of about 95 to 150 cm of vertical and 200 to 220 cm of left-lateral slip in the Teeka trench. Radiocarbon ages from a buried soil A horizon and overlying slope colluvium alone, with the historical record of earthquakes suggest that this faulting occurred 100 to 400 calendar years B.P. (A.D. 1550 to 1850). In the Duffers trench, 370 to 450 cm of vertical separation is accommodated by faulting (similar to210 cm) and folding (similar to160 to 240 cm), with probable but undetermined amounts of lateral slip. Stratigraphic relations and radiocarbon ages from buried soil, colluvium. and fissure fill in the hanging wall suggest the deformation at Duffers is most likely from two earthquakes that occurred between 100 to 500 and 1100 to 2200 calendar years B.P., but deformation during a single earthquake is also possible. For the two-earthquake hypothesis, deformation at Teeka trench in the first event involved folding but not faulting. Regional relations suggest that the earthquake(s) were M greater than or equal to similar to6.7 and that offshore rupture may have produced tsunamis. Based on this investigation and related recent studies, the maximum recurrence interval for large ground-rupturing crustal-fault earthquakes in the Puget Lowland is about 400 to 600 years or less.
887giTimes Cited:18Cited References Count:46

Export of young terrigenous dissolved organic carbon from rivers to the Arctic Ocean - Benner, R.; Benitez-Nelson, B.; Kaiser, K.; Amon, R. M. W. (Geophysical Research Letters, 2004)
Soils in the drainage basins of Arctic rivers are a major global reservoir of aged organic carbon. The fate of this old carbon is of growing concern as the effects of climate change become more evident in the Arctic. We report natural abundance C-14 data indicating that dissolved organic carbon (DOC) from several Eurasian and North American rivers is predominantly young and largely derived from recently-fixed C in plant litter and upper soil horizons. Concentrations of dissolved lignin phenols, unique organic tracers of terrestrial plant material, and C-14 content in DOC were strongly correlated throughout the Arctic Ocean, indicating terrigenous DOC is mostly young and widely distributed in polar surface waters. These young ages of terrigenous DOC in rivers and the ocean indicate little of the old carbon stored in Arctic soils is currently being mobilized in the dissolved component of continental runoff.
id: 646; 806KJ Times Cited:60 Cited References Count:34

From bedrock to burial: the evolution of particulate organic carbon across coupled watershed-continental margin systems - Blair, N. E.; Leithold, E. L.; Aller, R. C. (Marine Chemistry, 2004)
Deltas sequester nearly half of the organic carbon (OC) buried in the marine environment. The composition of the buried organic matter reflects both watershed and seabed processes. A conceptual model is presented that describes the evolution of particulate organic carbon (POC) as it travels from its terrestrial source to its burial at sea. Alterations to the POC occur primarily in bioactive reservoirs, such as soils and the surface mixed layer (SML) of the seabed, where new organic matter can be added and older material degraded. Bypassing or rapid passage through the reservoirs is a key parameter because it avoids change. The Eel River of northern California and the Amazon River systems illustrate the importance of reservoir transit time and storage in determining the character of POC delivered to the continental margin. The Eel exemplifies a bypass system. Mass-wasting processes on land deliver unaltered bedrock along with OC derived from extant vegetation directly to the river channel without significant storage in soils. Rapid burial on the shelf occurs as a result of flood events. As a consequence, the buried material appears to be a simple mixture of carbon derived from kerogen (bedrock C), and modem terrestrial and marine sources. This is predicted to be a characteristic of the many similar short rivers on active margins that supply >40% of the fluvial sediment to the world's ocean. Extensive storage and processing of OC in lowland soils is a characteristic of the large Amazon watershed. Upland POC compositions are either overprinted or replaced by lowland sources. Upon delivery to the shelf, over half of the riverine POC is lost as a result of residence in sediment layers that are periodically reworked over time scales of days to months. The addition of fresh reactive marine OC, exposure to oxygen, and the regeneration of metal oxidants during resuspension events fuel the oxidation of the niverme organic matter. The nature of the watershed-shelf processes likely produce a complex mixture of organics possessing a continuum of ages and reactivities. The model illustrates the need to develop tools to measure residence times of particles in the various reservoirs so that the behavior of POC can be calibrated as it moves through a sedimentary system. The ultimate goal is to be able to use the organic geochemistry of soils and sediments to quantitatively infer the history of processes that determine both the composition and amount of POC present in different depositional environments. (C) 2004 Elsevier B.V. All rights reserved.
id: 978; 882IA Times Cited:50 Cited References Count:118

A global ocean carbon climatology: Results from global data analysis project (GLODAP) - Kay, R. M.; Kozyr, A.; Sabine, C. L.; Lee, K.; Wanninkhof, R.; Bullister, J. L.; Feely, R. A.; Millero, F. J.; Mordy, C.; Peng, T. H. (Global Biogeochemical Cycles, 2004)
id: 527

H2-rich fluids from serpentinization: geochemical and biotic implications - Sleep, N. H.; Meibom, A.; Fridriksson, T.; Coleman, R. G.; Bird, D. K. (Proc Natl Acad Sci U S A, 2004)
Metamorphic hydration and oxidation of ultramafic rocks produces serpentinites, composed of serpentine group minerals and varying amounts of brucite, magnetite, and/or FeNi alloys. These minerals buffer metamorphic fluids to extremely reducing conditions that are capable of producing hydrogen gas. Awaruite, FeNi3, forms early in this process when the serpentinite minerals are Fe-rich. Olivine with the current mantle Fe/Mg ratio was oxidized during serpentinization after the Moon-forming impact. This process formed some of the ferric iron in the Earth's mantle. For the rest of Earth's history, serpentinites covered only a small fraction of the Earth's surface but were an important prebiotic and biotic environment. Extant methanogens react H2 with CO2 to form methane. This is a likely habitable environment on large silicate planets. The catalytic properties of FeNi3 allow complex organic compounds to form within serpentinite and, when mixed with atmospherically produced complex organic matter and waters that circulated through basalts, constitutes an attractive prebiotic substrate. Conversely, inorganic catalysis of methane by FeNi3 competes with nascent and extant life.
Sleep, N HMeibom, AFridriksson, ThColeman, R GBird, D KengResearch Support, U.S. Gov't, Non-P.H.S.2004/08/25 05:00Proc Natl Acad Sci U S A. 2004 Aug 31;101(35):12818-23. Epub 2004 Aug 23.

Holocene fault scarps near Tacoma, Washington, USA - Sherrod, B. L.; Brocher, T. M.; Weaver, C. S.; Bucknam, R. C.; Blakely, R. J.; Kelsey, H. M.; Nelson, A. R.; Haugerud, R. (Geology, 2004)
Airborne laser mapping confirms that Holocene active faults traverse the Puget Sound metropolitan area, northwestern continental United States. The mapping, which detects forest-floor relief of as little as 15 cm, reveals scarps along geophysical lineaments that separate areas of Holocene uplift and subsidence. Along one such line of scarps, we found that a fault warped the ground surface between A.D. 770 and 1160. This reverse fault, which projects through Tacoma, Washington, bounds the southern and western sides of the Seattle uplift. The northern flank of the Seattle uplift is bounded by a reverse fault beneath Seattle that broke in A.D. 900-930. Observations of tectonic scarps along the Tacoma fault demonstrate that active faulting with associated surface rupture and ground motions pose a significant hazard in the Puget Sound region.
765ehTimes Cited:50Cited References Count:22

Holocene relative sea-level history of the Southern Victoria Land Coast, Antarctica - Hall, B. L.; Baroni, C.; Denton, G. H. (Global and Planetary Change, 2004)
More than 130 radiocarbon dates of penguin remains and guano, sealskin, shells, and seaweed from raised beach ridges afford relative sea-level information for southern Victoria Land. A new relative sea-level curve suggests that the final unloading of grounded ice from the coast took place about 6600 C-14 years BP, in keeping with previous estimates of the timing of deglaciation. Since this time, the coast has experienced 32 m of relative sea-level fall at rates ranging from 2 to 15 mm/year, consistent with glacioisostatic rebound. (C) 2004 Elsevier B.V. All rights reserved.
845idTimes Cited:40Cited References Count:25

Hydrologic variation during the last 170,000 years in the southern hemisphere tropics of South America - Fritz, S. C.; Baker, P. A.; Lowenstein, T. K.; Seltzer, G. O.; Rigsby, C. A.; Dwyer, G. S.; Tapia, P. M.; Arnold, K. K.; Ku, T. L.; Luo, S. D. (Quaternary Research, 2004)
Despite the hypothesized importance of the tropics in the global climate system, few tropical paleoclimatic records extend to periods earlier than the last glacial maximum (LGM), about 20,000 years before present. We present a well-dated 170,000-year time series of hydrologic variation from the southern hemisphere tropics of South America that extends from modem times through most of the penultimate glacial period. Alternating mud and salt units in a core from Salar de Uyuni, Bolivia reflect alternations between wet and dry periods. The most striking feature of the sequence is that the duration of paleolakes increased in the late Quaternary. This change may reflect increased precipitation, geomorphic or tectonic processes that affected basin hydrology, or some combination of both. The dominance of salt between 170,000 and 140,000 yr ago indicates that much of the penultimate glacial period was dry, in contrast to wet conditions in the LGM. Our analyses also suggest that the relative influence of insolation forcing on regional moisture budgets may have been stronger during the past 50,000 years than in earlier times. (C) 2003 University of Washington. All rights reserved.
776jhTimes Cited:98Cited References Count:43

Inhibited eclogite formation: The key to the rapid growth of strong and buoyant Archean continental crust - Bjornerud, M. G.; Austrheim, H. (Geology, 2004)
Subduction is the principal mechanism by which the hydrosphere and interior of Earth interact. Today, subduction involves the dehydration of ocean crust at depths of 60-120 km depending on the age of the slab. Release of the water leads to generation of arc magmas (future continental crust), and the slab is then transformed into denser eclogite that helps to pull more of the slab into the trench. However, it is unlikely that the first continental crust formed this way. Growing geochemical evidence indicates that large volumes of continental crust were produced over a short period of time in the Archean, when the planet was probably too hot for modern plate tectonics to operate. A significant increase in the kinetics of eclogite-forming reactions may have been the key to the transition from Archean to modern tectonics. Under the higher geothermal gradients of the Archean, tectonically buried ocean crust would have been severely dehydrated before reaching eclogite facies pressures. Because rapid eclogitization is dependent on water as a medium for advective ion transport, the very shallow dehydration in the Archean may have inhibited the formation of eclogite facies minerals. The importance of water in eclogite metamorphism is illustrated by a complex of partly eclogitized malic granulites in Holsnoy, western Norway, in which reaction progress was limited by the availability of water. When water is scarce or absent, metastable granulite facies mineral assemblages can persist at eclogite facies depths owing to the extremely slow reaction kinetics when diffusion is the only chemical transport mechanism. Such dehydrated but uneclogitized mafic crust would have been very strong and too buoyant to sink into the mantle, and it may have formed the substrate for the first continental lithosphere.
id: 1507; 851PG Times Cited:12 Cited References Count:29

Late Quaternary sedimentation and deformation in Santa Monica and Catalina Basins, offshore southern California - Normark, W. R.; Baher, S.; Sliter, R. (Geology and Tectonics of Santa Cataline Island and the California Continental Borderland, 2004)
id: 991

Mangrove ecocystem dynamics and elemental cycling at Twin Cays, Belize, during the Holocene - Wooller, M. J.; Behling, H.; Smallwood, B. J.; Fogel, M. (Journal of Quaternary Science, 2004)
Existing at the transition between the terrestrial environment and hydrosphere, mangroves are sensitive to environmental change (e.g. sea-level rise). We present pollen and stable isotope data from a core (TCC1) of continuous (10 m) mangrove peat from Twin Cays, ∼12 km off of the coast of Belize, Central America. Radiocarbon dates on fragments of mangrove leaves preserved in TCC1 show that the core provides an 8600 14C year record of mangrove ecosystem changes. Variation in the stable carbon and nitrogen isotope composition (δ13C = ∼−30 to −25‰; δ15N = ∼−6 to 2‰) of mangrove leaves imply that the stand structure and nutrient status of the mangroves at the site have changed during the Holocene. Pollen data from the same core show that the floral composition of the site has changed at points during the Holocene, most notably a brief (∼240 years) switch at ∼3860 14C yr BP to dominance by a species of Myrsine (not currently present at the site). Our results are consistent with significant environmental changes (either marked disturbance from hurricanes or fluctuations in sea-level) through the Holocene.
id: 1149
Keywords: Holocene; isotopes; pollen; mangroves; Palaeoecology

Mercury in Connecticut and Long Island Sound: impact of historic hatting industries - Bronsther, R.; Welsh, P.; Varekamp, J. C. (American Geophyscial Union, Joint Assembly, 2004)
id: 733

A new Holocene relative sea-level curve for Terra Nova Bay, Victoria Land, Antarctica - Baroni, C.; Hall, B. L. (Journal of Quaternary Science, 2004)
More than 100 radiocarbon dates of penguin guano and remains, shells and seal skin afford ages for raised beaches adjacent to Terra Nova Bay, Antarctica. These dates permit construction of a new relative sea-level curve that bears on the timing of deglaciation. Recession of the Ross Sea ice-sheet grounding line from Terra Nova Bay occurred no earlier than 7200 C-14 yr (8000 cal. yr) BP. Retreat along the Victoria Land coast may have been rapid, possibly contributing to eustatic sea-level rise centred at ca. 7600 cal. yr BP. The presence of a significant amount of ice remaining in the Ross Sea Embayment in Holocene time lessens the chance that Antarctica contributed significantly to meltwater pulse 1A several thousand years earlier. Copyright (C) 2004 John Wiley Sons, Ltd.
833xiTimes Cited:38Cited References Count:36

New insights into the burial history of organic carbon on the early Earth - Bjerrum, C. J.; Canfield, D. E. (Geochemistry Geophysics Geosystems, 2004)
[1] The isotope record of organic matter and calcium carbonate is often used to infer the burial history of organic carbon through time. As organic carbon burial is widely held to control long-term oxygen production, the isotope record also relates to the production rates of oxygen on Earth. Current interpretations of the record suggest a long-term consistency in the proportion of total carbon buried as organic carbon (f ratio), with some important periods of much higher burial proportions. The isotope record is analyzed here with a new carbon isotope mass balance model, which considers submarine hydrothermal weathering of ocean crust as a significant removal pathway of inorganic carbon. With this model the f ratio is considerably reduced if isotopically depleted inorganic carbon is precipitated during hydrothermal weathering and if hydrothermal weathering dominates inorganic carbon removal from the surface environment. In contrast to previous calculations, our analysis of the carbon isotope record shows that organic carbon burial in the Archean accounted for only between 0% and 10% of the total carbon burial. These low burial proportions would have contributed to a slow accumulation of atmospheric oxygen in the Archean.
id: 1506; 846RU Times Cited:14 Cited References Count:44

NotCal04-Comparison/Calibration 14 C records 26-50 cal kBP - van der Plicht, J.; Beck, J. W.; Bard, E.; Baillie, M. G. L.; Blackwell, P. G.; Buck, C. E.; Friedrich, M.; Guilderson, T. P.; Hughen, K. A.; Kromer, B. (Radiocarbon, 2004)
id: 399

Paleoclimate. A better radiocarbon clock - Bard, E.; Rostek, F.; Menot-Combes, G. (Science, 2004)
id: 974; Bard, Edouard Rostek, Frauke Menot-Combes, Guillemette New York, N.Y. Science. 2004 Jan 9;303(5655):178-9.

The paleo-environmental history of Long Island Sound as traced by organic carbon, biogenic silica and stable isotope/trace element studies in sediment cores - Varekamp, J. C.; Thomas, E.; Lugolobi, F.; Buchholtz ten Brink, M. R. (6th Biennual LIS Res. Conf. Proc., 2004)
id: 1174

The Phanerozoic Carbon Cycle - Berner, Robert A. (Oxford University Press, 2004)
id: 1555

Present status of radiocarbon calibration and comparison records based on Polynesian corals and Iberian Margin sediments - Bard, E.; Menot-Combes, G.; Rostek, F. (Radiocarbon, 2004)
In this paper, we present updated information and results of the radiocarbon records based on Polynesian corals and on Iberian Margin planktonic foraminifera. The latter record was first published by Bard et al. (2004a,b), with the subsequent addition of some data by Shackleton et al. (2004). These data sets are compared with the IntCal98 record (Stuiver et al. 1998) and with data sets based on other archives, such as varves of Lake Suigetsu (Kitagawa and van der Plicht 1998, 2000), speleothems from the Bahamas (Beck et al. 2001), and Cariaco sediments (Hughen et al. 2004). Up to 26,000 cal BP, the Iberian Margin data agree within the errors of the other records. By contrast, in the interval between 33,000 and 41,000 cal BP, the Iberian Margin record runs between the Lake Suigetsu and Bahamian speleothem data sets, but it agrees with the few ImCal98 coral data and the Cariaco record.
956zfTimes Cited:30Cited References Count:33

Radiocarbon calibration beyond 20,000 B.P. by means of planktonic foraminifera of the Iberian Margin - Bard, E.; Rostek, F.; Menot-Combes, G. (Quaternary Research, 2004)
We present a new set of 14C ages obtained by accelerator mass spectrometry (AMS) on planktonic foraminifera from a deep-sea core collected off the Iberian Margin (MD952042). This site, at 37°N, is distant from the high-latitude zones where 14C reservoir age is large and variable. Many independent proxies — alkenones, magnetic susceptibility, ice-rafted debris, foraminifera stable isotopes, abundances of foraminifera, pollen, and dinoflagellates — show abrupt changes correlative with Dansgaard-Oeschger and Heinrich events of the last glacial period. The good stratigraphic agreement of all proxies — from the fine to the coarse-size fractions — indicates that the foraminifera 14C ages are representative of the different sediment fractions. To obtain reliable 14C ages of foraminifera beyond 20,000 14C yr B.P., we leached the shells prior to carbonate hydrolysis and subsequent analysis. For a calendar age scale, we matched the Iberian Margin U37K′ profile with that of Greenland Summit δ18O. Both are proxies for temperature, which in models varies synchronously in the two areas. The match creates no spurious jumps in sedimentation rate and requires only a limited number of tie points. Except for ages older than 40,000 14C yr B.P., Greenland's GISP2 and GRIP records yield similar calendars. The 14C and imported calendar ages of the Iberian Margin record are then compared to data — from lacustrine annual varves and from corals and speleothems dated by U–Th — previously used to extend the calibration beyond 20,000 14C yr B.P. The new record follows a smooth pattern between 23,000 and 50,000 cal yr B.P. We find good agreement with the previous data sets between 23,000 and 31,000 cal yr B.P. In the interval between 33,000 and 41,000 cal yr B.P., for which previous records disagree by up to 5000 cal yr, the Iberian Margin record closely follows the polynomial curve that was previously defined by an interpolation of the coral ages and runs between the Lake Suigetsu and the Bahamian speleothem data sets.
id: 401
Keywords: Dansgaard-Oeschger events; Heinrich events; Laschamp magnetic excursion; Last glacial cycle; North Atlantic; Radiocarbon calibration

Spatial variations in a condensed interval between estuarine and open-marine settings: Holocene Hudson River estuary and adjacent continental shelf - McHugh, C. M. G.; Pekar, S. F.; Christie-Blick, N.; Ryan, W. B. F.; Carbotte, S.; Bell, R. (Geology, 2004)
An interval of stratigraphic condensation extending for 300 km from the fluvially dominated Hudson River estuary to the adjacent continental shelf reveals stratal relationships within an unconformity-rellated depositional sequence that are commonly difficult to resolve in seismic reflection profiles and outcrop. High-resolution side-scan sonar and bathymetry, more than 100 sediment cores similar to2 m long, and radioisotope (C-14, Cs-137) age control show that much of the valley was filled by ca. 3 to 1 ka. The present rate of sediment accumulation averages 1 mm/yr, corresponding with a sea-level rise of similar to1.2 mm/yr relative to local bedrock. Condensation is manifested today by sedimentary bypass in most parts of the estuary and by the trapping of available sediment (1.2-5.6 x 10(5) t/yr [metric tons]) along narrow reaches and primarily in the vicinity of the estuarine turbidity maximum, a part of the estuary located upstream of the salinity intrusion similar to25 km from the mouth (3.0 x 10(5) t/yr). Shelf condensation is due to sediment starvation. The condensed interval merges updip with a nascent sequence boundary as the estuary reaches its final filling phase and downdip with the sequence boundary that developed at the Last Glacial Maximum. Delta progradation may take place as available shelf accommodation is filled, but such sediments are expected to be removed once sea level begins to fall. This sedimentation pattern, in which a condensed interval merges with different sequence boundaries, is consistent with the stratigraphic record of the Atlantic margin back to the Paleogene and may be typical of sediment-starved margins.
772lcTimes Cited:10Cited References Count:30

Temporal variability of Delta 14C, delta13C, and C/N in sinking particulate organic matter at a deep time series station in the northeast Pacific Ocean - Hwang, Jeomshik; Druffel, Ellen R. M.; Griffin, Sheila; L, Smith Kenneth, Jr.; Baldwin, Roberta J.; Bauer, James E. (Global Biogeochemical Cycles, 2004)
id: 531

Time averaging on a shallow subtropical shelf: the search for a taphomomic clock - Barbour-Wood, S. L.; Krause R.A, Jr.; Kowalewski, M.; Wehmiller, J. F.; Simoes, M. G. (Geological Society of America, Abstracts with Programs, 2004)
36(2):134
id: 719

The use of stable carbon isotopes in foraminiferal calcite to trace changes in biological oxygen demand in Long Island Sound - Lugolobi, F.; Varekamp, J. C.; Thomas, E.; Buchholtz ten Brink, M. R. (6th Biennual LIS Res. Conf. Proc., 2004)
id: 723

Variable ageing and storage of dissolved organic components in the open ocean - Loh, A. N.; Bauer, J. E.; Druffel, E. R. M. (Nature, 2004)
Seawater dissolved organic matter (DOM) is the largest reservoir of exchangeable organic carbon in the ocean, comparable in quantity to atmospheric carbon dioxide(1,2). The composition, turnover times and fate of all but a few planktonic constituents of this material are, however, largely unknown(3,4). Models of ocean carbon cycling are thus limited by the need for information on temporal scales of carbon storage in DOM subcomponents, produced via the 'biological pump', relative to their recycling by bacteria(3,4). Here we show that carbohydrate- and protein-like substances in the open Atlantic and Pacific oceans, though often significantly aged, comprise younger fractions of the DOM, whereas dissolved lipophilic material exhibits up to similar to90 per cent fossil character. In contrast to the millennial mean ages of DOM observed throughout the water column, weighted mean turnover times of DOM in the surface ocean are only decadal in magnitude. An observed size-age continuum further demonstrates that small dissolved molecules are the most highly aged forms of organic matter, cycling much more slowly than larger, younger dissolved and particulate precursors, and directly links oceanic organic matter age and size with reactivity(3,5).
847daTimes Cited:93Cited References Count:30

Vegetation and sedimentation in the Lake Edward Basin, Uganda-Congo during the late Pleistocene and early Holocene - Beuning, K. R. M.; Russell, J. M. (Journal of Paleolimnology, 2004)
New palynological and sedimentological data obtained from the basal 3 m of core E96-2P from Lake Edward, Uganda-Congo record conditions wetter than present in the Edward basin from similar to11000 to 6700 yr BP, in phase with other climate and vegetation records of northern hemispheric East Africa. Dominant pollen taxa include Celtis spp., Alchornea spp., Olea spp., and Moraceae indicating a moist semi-deciduous tropical forest. More xeric indicators such as Amaranthaceae and Asteraceae together with Poaceae comprise less than 5% of the pollen sum throughout this interval as compared with between 44 and 50% during a lake lowstand at similar to2000 cal yr BP and at the core top ( near modern). The differences between these two assemblages suggest a similar to25 to 60% increase in annual precipitation during the early- to mid-Holocene as compared to modern (1500-2000 vs. 1200 mm/yr today). Early Holocene sediments in E96-2P are composed of laminated diatom oozes with moderately high total sulfur concentrations (2.8-4.7%) and no authigenic calcite, also indicative of conditions wetter than present. Between similar to9000 and 6700 yr BP, palynological and sedimentary proxies indicate sub-millennial-scale events related to changes in riverine discharge and runoff in the Edward basin. We attribute the variability in runoff, and hence precipitation, to Holocene variability in Indian or Atlantic Ocean SSTs or to shifts in the relative contribution of Indian and Atlantic moisture sources to the western Rift of equatorial Africa.
814suTimes Cited:11Cited References Count:77

Ventilation of the glacial deep Pacific Ocean - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G.; Stott, L. (Science, 2004)
Measurements of the age difference between coexisting benthic and planktic foraminifera from western equatorial Pacific deep-sea cores suggest that during peak glacial time the radiocarbon age of water at 2-kilometers depth was no greater than that of today. These results make unlikely suggestions that a slowdown in deep-ocean ventilation was responsible for a sizable fraction of the increase of the ratio of carbon-14 (14C) to carbon in the atmosphere and surface ocean during glacial time. Comparison of 14C ages for coexisting wood and planktic foraminifera from the same site suggests that the atmosphere to surface ocean 14C to C ratio difference was not substantially different from today's.
Broecker, WallaceBarker, StephenClark, ElizabethHajdas, IrkaBonani, GeorgesStott, Lowelleng2004/11/13 09:00Science. 2004 Nov 12;306(5699):1169-72.

1999 RV Melville Baja California cruise, on the preservation of laminated sediments along the western margin of North America - van Geen, A.; Zheng, Y.; Bernhard, J. M.; Cannariato, K. G.; Carriquiry, J.; Dean, E.; Eakins, B. W.; Ortiz, J. D.; Pike, J. (Paleoceanography, 2003)
id: 1102

Anthropogenically induced changes in sediment and biogenic silica fluxes in Chesapeake Bay - Colman, S. M.; Bratton, J. F. (Geology, 2003)
Sediment cores as long as 20 m, dated by C-14, Pb-210, and Cs-137 methods and pollen stratigraphy, provide a history of diatom productivity and sediment-accumulation rates in Chesapeake Bay. We calculated the flux of biogenic silica and total sediment for the past 1500 yr for two high-sedimentation-rate sites in the mesohaline section of the bay. The data show that biogenic silica flux to sediments, an index of diatom productivity in the bay, as well as its variability, were relatively low before European settlement of the Chesapeake Bay watershed. In the succeeding 300400 yr, the flux of biogenic silica has increased by a factor of 4 to 5. Biogenic silica fluxes still appear to be increasing, despite recent nutrient-reduction efforts. The increase in diatom-produced biogenic silica has been partly masked (in concentration terms) by a similar increase in total sediment flux. This history suggests the magnitude of anthropogenic disturbance of the estuary and indicates that significant changes had occurred long before the twentieth century.
632uhTimes Cited:47Cited References Count:35

Biomass burning and oceanic primary production estimates in the Sulu Sea area over the last 380 kyr and the East Asian monsoon dynamics - Beaufort, L.; de Garidel-Thoron, T.; Linsley, B.; Oppo, D.; Buchet, N. (Marine Geology, 2003)
Coccolithophorid assemblages and micro-charcoal content were analysed in giant piston core MD97-2141 recovered in the Sulu Sea (Philippines). These proxies help to reconstruct respectively the dynamics of the oceanic primary production (PP) and biomass burning in that area. PP in the Sulu Sea intensifies during the East Asian winter monsoon (EAWM) and therefore PP constitutes a proxy for EAWM dynamics. Most of the precipitation in the Sulu Sea region occurs during the East Asian summer monsoon (EASM). Because the intensity of biomass burning is related to dryness of the surrounding area, the sedimentary micro-charcoal content can be used as an inverse proxy for EASM intensity. Our results show that the EAWM intensifies during glacial times in agreement with previous studies. Precessional forcing appears to act directly on EAWN because of the early response of PP in that frequency band. The micro-charcoal record exhibits complex dynamics, which we attribute to the competing influence of the long-term El Nino Southern Oscillation (ENSO)-like forcing and the glacial/interglacial cycle on EASM. These influences create an unusual frequency spectrum with power around 30 kyr and 19 kyr attributed to the non-linear response to the 100-kyr cycle (glacial) and the 23-kyr (ENSO) cycle. A factor of two increase in the amplitude of the micro-charcoal variability between 51 and 10 ka BP could correspond to Homo sapiens biomass burning in the style of the fire-stick farming of the Australian Aborigines. We also find, on precession cycles, an opposite phase between EASM and EAWM records and an advance of -delta(18)O and delta(18)O respectively by 2000 yr. (C) 2003 Elsevier B.V. All rights reserved.
Symposium on Asian Monsoons and Global Linkages on Milankovitch and Sub-Milankovitch Time ScalesMAY 09-11, 2001 BEIJING, PEOPLES R CHINA 70
Keywords: arabian sea; atlantic; climatic-change; EARLY HOLOCENE; EQUATORIAL; fire; GLACIAL MAXIMUM; indian-ocean; late pleistocene; Late Quaternary; monsoon; nannoplankton; Pleistocene; SOUTH CHINA; Sulu Sea; WEST-JAVA

Calcium carbonate budget in the Atlantic Ocean based on water column inorganic carbon chemistry - Chung, S. N.; Lee, K.; Feely, R. A.; Sabine, C. L.; Millero, F. J.; Wanninkhof, R.; Bullister, J. L.; Key, R. M.; Peng, T. H. (Global Biogeochemical Cycles, 2003)
[1] Recent independent lines of evidence suggest that the dissolution of calcium carbonate (CaCO3) particles is substantial in the upper ocean above the calcite 100% saturation horizon. This shallow-water dissolution of carbonate particles is in contrast with the current paradigm of the conservative nature of pelagic CaCO3 at shallow water depths. Here we use more than 20,000 sets of carbon measurements in conjunction with CFC and C-14 data from the WOCE/JGOFS/OACES global CO2 survey to estimate in situ dissolution rates of CaCO3 in the Atlantic Ocean. A dissolution rate is estimated from changes in alkalinity as a parcel of water ages along an isopycnal surface. The in situ CaCO3 dissolution increases rapidly at the aragonite 100% saturation horizon. Estimated dissolution rates north of 40degreesN are generally higher than the rates to the south, which is partly attributable to the production of exported CaCO3 being higher in the North Atlantic than in the South Atlantic. As more CaCO3 particles move down the water column, more particles are available for in situ dissolution. The total water column CaCO3 dissolution rate in the Atlantic Ocean is determined on an annual basis by integrating estimated dissolution rates throughout the entire water column and correcting for alkalinity input of approximately 5.6 x 10(12) mol C yr(-1) from CaCO3-rich sediments. The resulting water column dissolution rate of CaCO3 for the Atlantic Ocean is approximately 11.1 x 10(12) mol C yr(-1). This corresponds to about 31% of a recent estimate (35.8 x 10(12) mol C yr(-1)) of net CaCO3 production by Lee [2001] for the same area. Our calculation using a large amount of high-quality water column alkalinity data provides the first basin-scale estimate of the CaCO3 budget for the Atlantic Ocean.
732egTimes Cited:44 Cited References Count:73
Keywords: alkalinity; anthropogenic co2; caco3 dissolution; calcium carbonate budget; chemical lysocline; Deep-sea; dioxide system; dissociation-constants; dissolution kinetics; dissolution of calcium carbonate; eastern north-atlantic; ocean carbon cycle; organic-carbon; pacific-ocean; saturation state of seawater

Carbon cycling in Long Island Sound over the last 1000 years - Lugolobi, F.; Varekamp, J. C.; Thomas, E.; Buchholtz ten Brink, M. L.; Mecray, E. (AGU, Fall meeting, 2003)
id: 1179

The Catfish Lake scarp: preliminary field data and implications for earthquake hazards posed by the Tacoma fault - Sherrod, B. L.; Nelson, A. R.; Kelsey, H. M.; Brocher, T. M.; Blakely, R. J.; Weaver, C. S.; Rountree, N. K.; Rhea, S.; Jackson, B. S. (U. S. Geological Survey Open-File Report, 2003)
id: 430

A comparison of rates of time averaging between the bivalve Macoma cleryana and brachiopod Bouchardia rosea on a shallow subtropical shelf - Barbour-Wood, S. L.; Krause R.A, Jr.; Kowalewski, M.; Wehmiller, J. F.; Simoes, M. G.; Goodfriend, G. A. (Geological Society of America, Abstracts with Programs, 2003)
35(6):273
id: 720

Composition and syngeneity of molecular fossils from the 2.78 to 2.45 billion-year-old Mount Bruce Supergroup, Pilbara Craton, Western Australia - Brocks, J. J.; Buick, R.; Logan, G. A.; Summons, R. E. (Geochimica Et Cosmochimica Acta, 2003)
Shales of very low metamorphic grade from the 2.78 to 2.45 billion-year-old (Ga) Mount Bruce Supergroup, Pilbara Craton, Western Australia, were analyzed for solvent extractable hydrocarbons. Samples were collected from ten drill cores and two mines in a sampling area centered in the Hamersley Basin near Wittenoom and ranging 200 km to the southeast, 100 km to the southwest and 70 km to the northwest. Almost all analyzed kerogenous sedimentary rocks yielded solvent extractable organic matter. Concentrations of total saturated hydrocarbons were commonly in the range of 1 to 20 ppm ( mug/g rock) but reached maximum values of 1000 ppm. The abundance of aromatic hydrocarbons was similar to1 to 30 ppm. Analysis of the extracts by gas chromatography-mass spectrometry (GC-MS) and GC-MS metastable reaction monitoring (MRM) revealed the presence of n-alkanes, mid- and end-branched monomethylalkanes, omega-cyclohexylalkanes, acyclic isoprenoids, diamondoids, tri- to pentacyclic terpanes, steranes, aromatic steroids and polyaromatic hydrocarbons. Neither plant biomarkers nor hydrocarbon distributions indicative of Phanerozoic contamination were detected. The host kerogens of the hydrocarbons were depleted in C-13 by 2 to 21parts per thousand relative to n-alkanes, a pattern typical of, although more extreme than, other Precambrian samples. Acyclic isoprenoids showed carbon isotopic depletion relative to n-alkanes and concentrations of 2alpha-methylhopanes were relatively high, features rarely observed in the Phanerozoic but characteristic of many other Precambrian bitumens. Molecular parameters, including sterane and hopane ratios at their apparent thermal maxima, condensate-like alkane profiles, high mono- and triaromatic steroid maturity parameters, high methyladamantane and methyldiamantane indices and high methylphenanthrene maturity ratios, indicate thermal maturities in the wet-gas generation zone. Additionally, extracts from shales associated with iron ore deposits at Tom Price and Newman have unusual polyaromatic hydrocarbon patterns indicative of pyrolytic dealkylation.The saturated hydrocarbons and biomarkers in bitumens from the Fortescue and Hamersley Groups are characterized as 'probably syngenetic with their Archean host rock' based on their typical Precambrian molecular and isotopic composition, extreme maturities that appear consistent with the thermal history of the host sediments, the absence of biomarkers diagnostic of Phanerozoic age, the absence of younger petroleum source rocks in the basin and the wide geographic distribution of the samples. Aromatic hydrocarbons detected in shales associated with iron ore deposits at Mt Tom Price and Mt Whaleback are characterized as 'clearly Archean' based on their hypermature composition and covalent bonding to kerogen. Copyright (C) 2003 Elsevier Ltd.
741dvTimes Cited:124Cited References Count:102

Continuous-Flow Accelerator Mass Spectrometry - Roberts, M. L.; Benthien, A.; Schneider, R. J.; von Reden, K. F.; Hayes, J. M. (International Symposium on Radiation Physics, 2003)
id: 1683

East Asian monsoon forcing of suborbital variability in the Sulu Sea during Marine Isotope Stage 3: Link to Northern Hemisphere climate - Dannenmann, S.; Linsley, B. K.; Oppo, D. W.; Rosenthal, Y.; Beaufort, L. (Geochemistry Geophysics Geosystems, 2003)
[1] We have generated a new high-resolution record of variations in planktonic foraminiferal oxygen isotopes (delta(18)O) and Mg/Ca from a sediment core (IMAGES 97-2141) in the Sulu Sea located in the Philippine archipelago of western tropical Pacific. This record reveals distinct, suborbital-scale delta(18)O changes, most notably during Marine Isotope Stage 3 (MIS3) (similar to30,000 to 60,000 years B.P.). The amplitudes of these delta(18)O fluctuations (0.4 to 0.7parts per thousand) exceed that which can be attributed to sea level changes and must be due to changes in sea surface conditions. In the same interval, variations in planktonic foraminifera Mg/Ca suggest that suborbital surface ocean temperature variations of 1 to 1.5degreesC in the Sulu Sea were not in phase with delta(18)O. Combined, this evidence indicates that the MIS3 millennial delta(18)O events in the Sulu Sea were primarily the result of changes in surface water salinity, which today is directly related to the East Asian Monsoon (EAM) and its influence on the balance between surface water contributions from the South China Sea and Western Pacific Warm Pool (WPWP). Within dating uncertainties the MIS3 Sulu Sea delta(18)O suborbital variability indicates that times of fresher surface conditions in the Sulu Sea coincide with similar conditions in the WPWP [Stott et al., 2002] and also with intensifications of the summer EAM as recorded in the U-Th dated Chinese (Hulu Cave) speleothem delta(18)O record [Wang et al., 2001] and thus by inference with interstadials in the Greenland Ice core records. Combined, these results indicate that pronounced suborbital variability in the summer EAM and Intertropical Convergence Zone (ITCZ) during MIS3 was tightly coupled with climate conditions in the northern high latitudes.
631mwTimes Cited:41 Cited References Count:53
Keywords: 1620 global change : climate dynamics (3309); 4267 oceanography : general : paleoceanography; dissolution; equatorial pacific; eurasian snow cover; isotope stage 3; last glacial period; late pleistocene; Mg/Ca; millennial-scale climate change; oxygen isotopes; paleoceanography; planktonic-foraminifera; records; se asian monsoon; south china sea; summer monsoon; surface temperature-variations

Eutrophication and carbon sources in Chesapeake Bay over the last 2700 yr: human impacts in context - Bratton, John F.; Colman, Steven M.; Seal, Robert R. (Geochimica et Cosmochimica Acta, 2003)
To compare natural variability and trends in a developed estuary with human-influenced patterns, stable isotope ratios (δ13C and δ15N) were measured in sediments from five piston cores collected in Chesapeake Bay. Mixing of terrestrial and algal carbon sources primarily controls patterns of δ13Corg profiles, so this proxy shows changes in estuary productivity and in delivery of terrestrial carbon to the bay. Analyses of δ15N show periods when oxygen depletion allowed intense denitrification and nutrient recycling to develop in the seasonally stratified water column, in addition to recycling taking place in surficial sediments. These conditions produced 15N-enriched (heavy) nitrogen in algal biomass, and ultimately in sediment. A pronounced increasing trend in δ15N of +4‰ started in about A.D. 1750 to 1800 at all core sites, indicating greater eutrophication in the bay and summer oxygen depletion since that time. The timing of the change correlates with the advent of widespread land clearing and tillage in the watershed, and associated increases in erosion and sedimentation. Isotope data show that the region has experienced up to 13 wet-dry cycles in the last 2700 yr. Relative sea-level rise and basin infilling have produced a net freshening trend overprinted with cyclic climatic variability. Isotope data also constrain the relative position of the spring productivity maximum in Chesapeake Bay and distinguish local anomalies from sustained changes impacting large regions of the bay. This approach to reconstructing environmental history should be generally applicable to studies of other estuaries and coastal embayments impacted by watershed development.
id: 541

Field and laboratory data from an earthquake history study of the Waterman Point fault, Kitsap County, Washington - Nelson, A. R.; Johnson, S. Y.; Kelsey, S. K.; Wells, R. E.; Sherrod, B. L.; Bradley, L. A.; Okumura, K.; Bogar, R. (U. S. Geological Survey Miscellaneous Field Studies, 2003)
id: 429

Geochemistry of hydrothermally altered oceanic crust: DSDP/ODP Hole 504B - Implications for seawater-crust exchange budgets and Sr- and Pb-isotopic evolution of the mantle - Bach, Wolfgang; Peucker-Ehrenbrink, Bernhard; Hart, STanly R.; Blusztajn, Jerzy S. (Geochemistry, Geophysics, Geosystems G3, 2003)
id: 1536

Late Holocene earthquakes on the Toe Jam Hill fault, Seattle fault zone, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Kelsey, H. M.; Wells, R. E.; Sherrod, B. L.; Pezzopane, S. K.; Bradley, L. A.; Koehler, R. D.; Bucknam, R. C. (Geological Society of America Bulletin, 2003)
Five trenches across a Holocene fault scarp yield the first radiocarbon-measured earthquake recurrence intervals for a crustal fault in western Washington. The scarp, the first to be revealed by laser imagery, marks the Toe Jam Hill fault, a north-dipping backthrust to the Seattle fault. Folded and faulted strata, liquefaction features, and forest soil A horizons buried by hanging-wall-collapse colluvium record three, or possibly four, earthquakes between 2500 and 1000 yr ago. The most recent earthquake is probably the 1050-1020 cal. (calibrated) yr B.P. (A.D. 900930) earthquake that raised marine terraces and triggered a tsunami in Puget Sound. Vertical deformation estimated from strati-graphic and surface offsets at trench sites suggests late Holocene earthquake magnitudes near M7, corresponding to surface ruptures >36 km long. Deformation features recording poorly understood latest Pleistocene earthquakes suggest that they were smaller than late Holocene earthquakes. Postglacial earthquake recurrence intervals based on 97 radiocarbon ages, most on detrital charcoal, range from similar to12,000 yr to as little as a century or less; corresponding fault-slip rates are 0.2 mm/ yr for the past 16,000 yr and 2 mm/yr for the past 2500 yr. Because the Toe Jam Hill fault is a backthrust to the Seattle fault, it may not have ruptured during every earthquake on the Seattle fault. But the earthquake history of the Toe Jam Hill fault is at least a partial proxy for the history of the rest of the Seattle fault zone.
740qwTimes Cited:41Cited References Count:53

Map and data for Quaternary faults and folds in Washington State - Lidke, D. J.; Johnson, S. Y.; McCory, P. A.; Personius, S. F.; Nelson, A. R.; Dart, R. L.; Bradley, L. A.; Haller, K. M.; Machette, M. N. (Geological Survey Open-File Report, 2003)
id: 997

Maps and data from a trench investigation of the Utsalady Point fault, Whidbey Island, Washington - Johnson, S. Y.; Nelson, A. R.; Personius, S. F.; Wells, R. E.; Kelsey, H. M.; Sherrod, B. L.; Okumura, K.; Koehler, R., III; Witter, R. C.; Bradley, L. A.; Harding, D. J. (U. S. Geological Survey Miscellaneous Field Studies, 2003)
id: 996

Mercury contamination chronologies from Connecticut wetlands and Long Island Sound sediments - Varekamp, J. C.; Kreulen, B.; ten Brink, M. R. B.; Mecray, E. L. (Environmental Geology, 2003)
Sediment cores were used to investigate the mercury deposition histories of Connecticut and Long Island Sound. Most cores show background (pre-1800s) concentrations (50-100 ppb Hg) below 30-50 cm depth, strong enrichments up to 500 ppb Hg in the core tops, with lower Hg concentrations in the surface sediments (200-300 ppb Hg). A sediment core from the Housatonic River has peak levels of 1,500 ppb Hg, indicating the presence of a Hg point source in this watershed. The Hg records were translated into Hg contamination chronologies through Pb-210 dating. The onset of Hg contamination occurred in similar to1840-1850 in eastern Connecticut, whereas in the Housatonic River the onset is dated at around 1820. The mercury accumulation profiles show periods of peak contamination at around 1900 and at 1950-1970. Peak Hg* (Hg* = Hg measured minus Hg background) accumulation rates in the salt marshes vary; dependent on the sediment character, between 8 and 44 ng Hg/cm(2) per year, whereas modern Hg* accumulation rates range from 4-17 ng Hg/cm(2) per year; time-averaged Hg* accumulation rates are 15 ng Hg/cm(2) per year. These Hg* accumulation rates in sediments are higher than the observed Hg atmospheric deposition rates (about 1-2 ng Hg/cm(2) per year), indicating that contaminant Hg from the watershed is focused into the coastal zone. The Long Island Sound cores show similar Hg profiles as the marsh cores, but time-averaged Hg* accumulation rates are higher than in the marshes (26 ng Hg/cm(2) a year) because of-the different sediment characteristics. In-situ atmospheric deposition of Hg in the marshes and in Long Island Sound is only a minor component of the total Hg budget. The 1900 peak of Hg contamination is most likely related to climatic factors (the wet period of the early 1900s) and the 1950-1970 peak was caused by strong anthropogenic Hg emissions at that time. Spatial trends in total Hg burdens in cores are largely related to sedimentary parameters (amount of clay) except for the high inventories of the Housatonic River, which are related to Hg releases from hat-making in the town of Danbury. Much of the contaminated sediment transport in the Housatonic River Basin occurs during floods; creating distinct layers of Hg-contaminated sediment in western Long Island Sound. The drop of about 40% in Hg accumulation rates between the 1960s and 1990s seems largely the result of reduced Hg emissions and to a much lesser extent of climatic factors.
643lmTimes Cited:22Cited References Count:45

Modeling the d180 in precipitation over the Americas: 1. Simulation of the stable isotope in Andean ice cores - Vuille, M.; Bradley, R. S.; Healy, R.; Werner, M.; Handy, D. R.; Thompson, L. G.; Keimig, F. (JGR, 2003)
id: 1771

Modeling the d18O in precipitation over the Americas: 1. Simulation of the stable isotope in Andean ice cores - Vuille, M.; Bradley, R. S.; Healy, R.; Werner, M.; Hardy, D. R.; Thompson, L. G.; Keimig, F. (JGR, 2003)
id: 1691

Modeling the d18O in precipitation over the Americas: 2. Interannual variability and climatic controls - Vuille, M.; Bradley, R. S.; Werner, M.; Healy, R.; Keimig, F. (JGR, 2003)
id: 1692

The paleo environmental history of Long Island Sound, Abstract - Varekamp, J. C.; Thomas, E.; Buchholtz ten Brink, M. F.; Altabet, M.; Cooper, S. (Long Island Sound Lobster Research meeting, 2003)
id: 1178

Penetration of anthropogenic carbon into organic particles of the deep ocean - Druffel, E. R. M.; Bauer, J. E.; Griffin, S.; Hwang, J. (Geophysical Research Letters, 2003)
[1] In the late 1980s, bomb C-14 was present in suspended particulate organic carbon (POC) from the North Central Pacific (NCP) and Sargasso Sea ( SS) throughout most of the water column, demonstrating that deep POC had exchanged with atmospheric CO2 in the past 30 years. Upon reoccupation of these sites in 1999 and 2000, respectively, we observed that the delta(13)C values of suspended POC were lower than those measured a decade earlier. This demonstrates that anthropogenic CO2 from fossil fuel and biomass burning has penetrated a major organic matter pool in the deep ocean. Delta(14)C measured in the suspended POC showed similar or higher values in the deep Sargasso Sea and decreased values in the deep NCP compared to those measured previously. We use a box model to show that the differences in the radiocarbon results are likely due to the presence of resuspended sediment that is laterally advected from the continental margin to the deep Sargasso Sea.
709dpTimes Cited:12 Cited References Count:29
Keywords: bomb radiocarbon; C-14; CO2; delta-c-13; MATTER; NORTH PACIFIC-OCEAN; SARGASSO SEA; Sediment; variability; water

The persistence of memory: The fate of ancient sedimentary organic carbon in a modern sedimentary system - Blair, N. E.; Leithold, E. L.; Ford, S. T.; Peeler, K. A.; Holmes, J. C.; Perkey, D. W. (Geochimica Et Cosmochimica Acta, 2003)
The cycle of organic carbon burial and exhumation moderates atmospheric chemistry and global climate over geologic timescales. The burial of organic carbon occurs predominantly at sea in association with clay-sized particles derived from the erosion of uplifted continental rocks. It follows that the history of the fine-grained particles on land may bear on the nature of the organic carbon buried. In this study, the evolution of clay-associated organic matter was followed from bedrock source to the seabed in the Eel River sedimentary system of northern California using natural abundance C-13 and C-14 tracers. Approximately half of the fine-grained organic carbon delivered to the shelf is derived from ancient sedimentary organic carbon found in the uplifted Mesozoic-Tertiary Franciscan Complex of the watershed. The short residence time of friable soils on steep hill slopes, coupled with rapid sediment accumulation rates on the shelf-slope, act to preserve the ancient organic carbon. A comparable quantity of modem organic carbon is added to particles in the watershed and on the shelf and slope. The bimodal mixture of ancient and modem C in soils and sediments may be characteristic of many short, mountainous rivers. If the Eel River chemistry is typical of such rivers, more than 40 Tg of ancient organic C may be delivered to the world's oceans each year. A flux of that magnitude would have a significant influence on marine and global C-cycles. Copyright (C) 2003 Elsevier Science Ltd.
634jvTimes Cited:143Cited References Count:63

A possible record of the Younger Dryas event in deep-sea sediments of the Southern Ocean (Pacific sector) - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (Palaeogeography Palaeoclimatology Palaeoecology, 2003)
The oxygen isotope record combined with radiocarbon dating from two deep-sea cores collected along a transect between New Zealand and the Ross Sea are used to establish a reliable chronostratigraphy for the last 14 kyr. After an integrated geochemical and micropaleontological analysis in this timeframe we detected a cooling interval dated between 12.5 cal kyr BP and 11.4 cal kyr BP. The age control suggests that this event started 1.5 kyr after the onset of the Antarctic Cold Reversal previously observed in several Antarctic ice cores. We infer that the observed cool event corresponds to the Younger Dryas event defined in Northern Europe. This suggests that climate change recorded in this sector of the Southern Hemisphere still shows some synchronicity with Northern Hemisphere variations and that the decoupling of climate change between the two hemispheres likely occurred south of the Polar Front. (C) 2003 Elsevier B.V. All rights reserved.
723feTimes Cited:15Cited References Count:55

On the preservation of laminated sediments along the western margin of North America - van Geen, A.; Zheng, Y.; Bernhard, J. M.; Cannariato, K. G.; Carriquiry, J.; Dean, W. E.; Eakins, B. W.; Ortiz, J. D.; Pike, J. (Paleoceanography, 2003)
id: 1128

Variations in the hydrological regime of Kara-Bogaz-Gol Gulf Lake Issyk-Kul, and the Aral Sea assessed based on data of bottom sediment studies - Ferronskii, V. I.; Polyakov, V. A.; Brezgunov, V. S.; Vlasova, L. S.; Karpychev, Yu A.; Bobkov, A. F.; Romaniovskii, V. V.; Johnson, T. C.; Ricketts, R. D.; Rasmussen, K. A. (Water Resources, 2003)
id: 493

A 20,000-yr sedimentological record from Lake Malawi, East Africa: the Late-Pleistocene/Holocene transition in the southern tropics - Barry, S. L.; Filippi, M. L.; Talbot, M.; Johnson, T. C. (The East African Great Lakes: Limnology, Palaeoclimatology and Biodiversity, 2002)
id: 1478

A 24,600 year diatom record from the northern basin of Lake Malawi - Gasse, F.; Barker, P.; Johnson, T. C. (The East African Great Lakes, Limnology, Palaeoclimatology and Biodiversity, 2002)
id: 1479

A 4000-Year Lacustrine Record of Environmental Change in the Southern Maya Lowlands, Petén, Guatemala - Rosenmeier, Michael F.; Hodell, David A.; Brenner, Mark; Curtis, Jason H.; Guilderson, Thomas P. (Quaternary Research, 2002)
A 4000-yr sediment core record from Lake Salpetén, Guatemala, provides evidence for Maya-induced forest clearance and consequent soil erosion between ∼1700 cal yr B.C. and 850 cal yr A.D. Radiocarbon ages of wood, seeds, and charcoal support an age-depth model with average errors of ±110 cal yr. Relatively low carbonate δ18O values between 1300 and 400 cal yr B.C. coincide with pollen evidence for forest loss, consistent with increased surface and groundwater flow to the lake. Minimum δ18O values between 400 cal yr B.C. and 150 cal yr A.D. suggest a high lake level, as do 14C-dated aquatic gastropods as much as 7.5 m above the present lake stage. High lake levels resulted from reduced evaporation-to-precipitation ratios, increased hydrologic input caused by anthropogenic deforestation, or both. The Preclassic abandonment (150 A.D.) and Early Classic/Late Classic boundary (550 A.D.) are marked by relatively high δ18O values indicating reduced lake levels. Oxygen isotope composition increased further coincident with the Terminal Classic Maya demographic decline between 800 and 900 A.D. This period of high δ18O may have been caused by the greater aridity that has been documented in northern Yucatán lakes or by decreased hydrologic input to the lake as a consequence of forest recovery. Reduced soil erosion after 850 cal yr A.D. coincided with the Terminal Classic Maya demographic decline and permitted forest recovery and resumption of organic sedimentation.
id: 2106

A 6100 14C year record of El Nino activity from the Galapagos Islands - Riedinger, M. A.; Steinitz-Kannan, M.; Last, W. M.; Brenner, M. (Journal of Paleolimnology, 2002)
id: 1485

Assessing the linkages among climate variability, land-use change, and the sedimentary regime of the Upper Chesapeak Bay - Barros, A. P.; Gordon, S. J. (Proceedings Coastal Environment 2002, 2002)
id: 1218

Benthic foraminifera in Long Island Sound as indicators of eutrophication - Abramson, I.; Thomas, E.; Varekamp, J. C.; Buchholtz ten Brink, M. R. (GSA Annual meeting, 2002)
id: 731

Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - Bratton, John F.; Colman, Steven M.; Thieler, E. Robert; Seal, Robert R. (Geo-Marine Letters, 2002)
Two major pulses of sea-level rise are thought to have taken place since the last glacial maximum — meltwater pulses (mwp) 1A (12 cal ka) and 1B (9.5 cal ka). Between mwp 1B and about 6 cal ka, many of the complex coastal ecosystems which ring the world’s oceans began to form. Here we report data for rhenium, carbon isotopes, total organic carbon, and fossil oysters from Chesapeake Bay which span the transition from fresh to brackish water conditions in the bay in the mid-Holocene. These data constrain sea-level change and resulting environmental change in the bay. They indicate that the transition was rapid, and that it was produced by (1) a third pulse of rapid eustatic sea-level rise, or (2) a geometry of the prehistoric Chesapeake Bay basin which predisposed it to a nonlinear response to a steadily rising sea level. Similar nonlinear changes in vulnerable coastal environments are likely to take place in the future due to polar warming, regardless of the timing or rate of sea-level rise.
id: 540

Blackwood Creek Stream restoration project design draft report - Beck, Nicole; Hydrology, Swanson (U.S. Forest Service Lake Tahoe Basin Management Unit, South Lake Tahoe, CA, 2002)
id: 350

Blackwood Creek Strem restoration project design draft report - Beck, N.; Hydrology, S. (2002)
id: 1140

Carbon isotopic composition of DOM - Bauer, J. E. (Biogeochemistry of Marine Dissolved Organic Matter, 2002)
id: 687

Challenges in radiocarbon dating organic carbon in opal-rich marine sediments - Zheng, Y.; Anderson, R. F.; Froelich, P. N.; Beck, W.; McNichol, A. P.; Guilderson, T. (Radiocarbon, 2002)
We explored the reliability of radiocarbon ages obtained on organic carbon phases in opal-rich Southern Ocean sediments. Paired biogenic carbonate and total organic carbon (TOC) C-14 analyses for three Southern Ocean cores showed that the TOC ages were systematically younger than the carbonate ages. Carbonate ages were consistent with oxygen isotopic and bio-stratigraphy, indicating error in TOC ages that could be explained by 5-24% of modern carbon contamination of TOC samples. Two possible sources of contamination are: 1) adsorption of atmospheric CO2 or volatile organic compounds to reactive opal surface sites, and 2) fixation of atmospheric CO2 by chemosynthetic bacteria during core storage. In an effort to reduce the modem carbon contamination, diatoms were separated from sediments, purified, and pre-oxidized by concentrated nitric and perchloric acids to permit dating of opal-intrinsic organic carbon (similar to0.1-0.3% by weight). C-14 ages of chemically pre-oxidized opal showed a significant amount of modem carbon contamination, from 11 to 32%, indicating adsorption from the atmosphere of modem carbon onto opal surfaces that were previously cleaned by acid oxidation. Several experiments designed to eliminate the modern C contamination were attempted, but so far we have not been able to obtain a radiocarbon age on C-14-dead Southern Ocean opal-rich sediments, either bulk TOC or purified diatom opal samples, as old as our procedural blank.
591keTimes Cited:13Cited References Count:28

Chemostratigraphy of Paleoproterozoic carbonate successions of the Wyoming Craton: tectonic forcing of biogeochemical change? - Bekker, A.; Karhu, J. A.; Eriksson, A.; Kaufman, A. J. (Precambrian Research, 2002)
The Archean Wyoming Craton is flanked on the south and east by belts of Paleoproterozoic supracrustal successions whose correlation is complicated by lack of geochronologic constraints and continuous outcrop. However, carbonate units in these successions may be correlated by integrating carbon isotope stratigraphy with lithostratigraphy. The ∼10 km thick Paleoproterozoic Snowy Pass Supergroup in the Medicine Bow Mountains was deposited on the present-day southern flank of the Wyoming Craton; it contains three discrete levels of glacial diamictite correlative with those in the Huronian Supergroup, on the southern margin of the Superior Craton. The Nash Fork Formation of the upper Snowy Pass Supergroup is significantly younger than the uppermost diamictite and was deposited after the end of the Paleoproterozoic glacial epoch. Carbonates at the base of the Nash Fork Formation record remarkable 13C-enrichment, up to +28‰ (V-PDB), whereas those from overlying members of the lower Nash Fork Formation have δ13C values between +6 and +8‰. Carbonates from the upper Nash Fork Formation above the carbonaceous shale have carbon isotope values ranging between 0 and +2.5‰. The transition from high carbon isotope values to those near 0‰ in the Nash Fork Formation is similar to that at the end of the ca. 2.2–2.1 Ga carbon isotope excursion in Fennoscandia. This chemostratigraphic trend and deposition of BIFs, Mn-rich lithologies, carbonaceous shales and phosphorites at the end of the global ca. 2.2–2.1 Ga carbon isotope excursion are likely related to ocean overturn associated with the final breakup of the Kenorland supercontinent. Correlative carbonates from the Slaughterhouse Formation in the Sierra Madre, WY, and from the Whalen Group in the Rawhide Creek area in the Hartville Uplift, WY, have highly positive carbon isotope values. In contrast, carbonates from other exposures of the Whalen Group in the Hartville Uplift and all carbonate units in the Black Hills, SD, have carbon isotope values close to 0‰. Combined with existing geochronologic and stratigraphic constraints, these data suggest that the Slaughterhouse Formation and the succession exposed in the Rawhide Creek area of the Hartville Uplift are correlative with the lower and middle Nash Fork Formation and were deposited during the ca. 2.2–2.1 Ga carbon isotope excursion. The Estes and Roberts Draw formations in the Black Hills and carbonates from other exposures in the Hartville Uplift postdate the ca. 2.2–2.1 Ga positive carbon isotope excursion and are most likely correlative with the upper Nash Fork Formation. The passive margin, on which the carbonates with highly positive carbon isotope values were deposited, extended around the southern flank of the Wyoming Craton through the Sierra Madre, Medicine Bow Mountains and Hartville Uplift. The presence of carbonates with carbon isotope values close to 0‰ in the upper Nash Fork Formation and the Whalen Group indicates that the passive margin persisted on the southern flank of the Wyoming Craton after the carbon isotope excursion. Rifting in the Black Hills, likely related to the final breakup of the Kenorland, succeeded the carbon isotope excursion, since the Estes and Roberts Draw formations, deposited during rifting and ocean opening on the eastern flank of the Wyoming Craton, postdate the carbon isotope excursion.
id: 1586
Keywords: Biogeochemistry; Chemostratigraphy; Kenorland; Paleoproterozoic; Wyoming

Converting AMS data to radiocarbon values: considerations and conventions - McNichol, A. P.; Jull, A. J. T.; Burr, G. S. (Radiocarbon, 2002)
id: 1818

A Critical Evaluation of Interlaboratory Data on Total, Elemental, and Isotopic Carbon in the Carbonaceous Particle Reference Material, NIST SRM 1649a - Currie, L. A.; Benner, B. A., Jr.; Kessler, J. D.; Klinedinst, D. B.; Klouda, G. A.; Marolf, J. V.; Slater, J. F.; Wise, S. A.; Cachier, H.; Cary, R.; Chow, J. C.; Watson, J.; et al. (J Res Natl Inst Stand Technol, 2002)
Because of increased interest in the marine and atmospheric sciences in elemental carbon (EC), or black carbon (BC) or soot carbon (SC), and because of the difficulties in analyzing or even defining this pervasive component of particulate carbon, it has become quite important to have appropriate reference materials for intercomparison and quality control. The NIST "urban dust" Standard Reference Material((R)) SRM 1649a is useful in this respect, in part because it comprises a considerable array of inorganic and organic species, and because it exhibits a large degree of ((14)C) isotopic heterogeneity, with biomass carbon source contributions ranging from about 2 % (essentially fossil aliphatic fraction) to about 32 % (polar fraction). A primary purpose of this report is to provide documentation for the new isotopic and chemical particulate carbon data for the most recent (31 Jan. 2001) SRM 1649a Certificate of Analysis. Supporting this is a critical review of underlying international intercomparison data and methodologies, provided by 18 teams of analytical experts from 11 institutions. Key results of the intercomparison are: (1) a new, Certified Value for total carbon (TC) in SRM 1649a; (2) (14)C Reference Values for total carbon and a number of organic species, including for the first time 8 individual PAHs; and (3) elemental carbon (EC) Information Values derived from 13 analytical methods applied to this component. Results for elemental carbon, which comprised a special focus of the intercomparison, were quite diverse, reflecting the confounding of methodological-matrix artifacts, and methods that tended to probe more or less refractory regions of this universal, but ill-defined product of incomplete combustion. Availability of both chemical and (14)C speciation data for SRM 1649a holds great promise for improved analytical insight through comparative analysis (e.g., fossil/biomass partition in EC compared to PAH), and through application of the principle of isotopic mass balance.
Currie, L ABenner, B A JrKessler, J DKlinedinst, D BKlouda, G AMarolf, J VSlater, J FWise, S ACachier, HCary, RChow, J CWatson, JDruffel, E R MMasiello, C AEglinton, T IPearson, AReddy, C MGustafsson, OQuinn, J GHartmann, P CHedges, J IPrentice, K MKirchstetter, T WNovakow, TPuxbaum, HSchmid, Heng2002/01/01 00:00J Res Natl Inst Stand Technol. 2002 Jun 1;107(3):279-98. doi: 10.6028/jres.107.022. Print 2002 May-Jun.

Data report: Australian Bight - Hine, A. C.; Brooks, G. R.; Mallinson, D.; Brunner, C. A.; James, N. P.; Feary, D. A.; Holbourn, A. E.; Drexler, T. M.; Howd, P. (Proc. ODP, Sci. Results, 2002)
id: 271

Eutrophication of Long Island Sound as traced by benthic foraminifera - Thomas, E.; Abramson, I.; Varekamp, J. C.; Buchholtz ten Brink, M. R. (Long Island Sound/NEERS Research Conference, 2002)
id: 727

Field and laboratory data from an earthquake history study of the Toe Jam Hill fault, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Wells, R. E.; Kelsey, H. M.; Pezzopane, S. K.; Sherrod, B. L.; Bradley, L. A.; Iii, Koehler R. D.; Bucknam, R. C.; Haugerud, R. A.; LaPrade, W. T. (U.S. Geological Survey Open-File Report, 2002)
id: 428

Field and Laboratory data from an earthquake history study of the Toe Jam Hill fault, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Wells, R. E.; Pezzopane, S. K.; Kelsey, H. M.; Sherrod, B. L.; Bradley, L. A.; Koehler, R. D., III; Bucknam, R. C.; Haugerud, R. A.; LaPrade, W. T. (U.S. Geological Survey Open-File Report 02-60, 2002)
id: 259

A high-resolution paleoclimate record spanning the past 25,000 years in southern East Africa - Johnson, T. C.; Brown, E. T.; McManus, J.; Barry, S.; Barker, P.; Gasse, F. (Science, 2002)
High-resolution profiles of the mass accumulation rate of biogenic silica and other geochemical proxies in two piston cores from northern Lake Malawi provide a climate signal for this part of tropical Africa spanning the past 25,000 years. The biogenic silica mass accumulation rate was low during the relatively dry late Pleistocene, when the river flux of silica to the lake was suppressed. Millennial-scale fluctuations, due to upwelling intensity, in the late Pleistocene climate of the Lake Malawi basin appear to have been closely linked to the Northern Hemisphere climate until 11 thousand years ago. Relatively cold conditions in the Northern Hemisphere coincided with more frequent north winds over the Malawi basin, perhaps resulting from a more southward migration of the Intertropical Convergence Zone.
Johnson, Thomas CBrown, Erik TMcManus, JamesBarry, SylviaBarker, PhilipGasse, FrancoisengResearch Support, U.S. Gov't, Non-P.H.S.2002/04/06 10:00Science. 2002 Apr 5;296(5565):113-32.

The historical record of water quality in Long Island Sound - Varekamp, J. C.; Thomas, E.; Mecray, E. L.; Buchholtz ten Brink, M. F. (Long Island Sound workshop, 2002)
id: 726

Holocene chronology of a continental shelf mudbelt off southwestern Africa - Meadows, M. E.; Rogers, J.; Lee-Throp, J. A.; Bateman, M. D.; Dingle, R. V. (The Holocene, 2002)
The Holocene lithostratigraphy and geochronology of sediments on an inner continental-shelf mudbelt off the west coast of southern Africa is presented. Based on a study of seven large gravity cores, numerous grab samples and two vibracores, two distinctive sections of the mudbelt have been identi” ed. The northern section is associated with the Orange River prodelta, and is dominated by laminated clay-rich sediments, while the southern section off Namaqualand is associated with more homogeneous muds. AMS radiocarbon ages of 31 samples from these cores are problematic due to the absence of expected modern material at the sedimentocean interface and numerous age reversals and inconsistencies in some of the cores. Possible mechanisms to explain the apparently anomalously old surface and near-surface samples are suggested. Most likely expla nations appear to lie in a combination of sediment-retrieval problems, the periodic loss of ” ne particulate organic carbon from within the water column, the sampling of possible relic sediments and, most likely of all, the incorporation into the sediments of 14C-depleted terrigenous organic matter. The age reversals are especially evident in the laminated sediments, and the entrainment of ‘old’ carbon from the terrestrial source of these sediments is offered as the most parsimonious explanation. Stable carbon isotope analyses and a single lumi nescence age support the contention that radiocarbon date inconsistencies are a consequence of terrestrial inputs of carbon which is non-contemporaneous with the actual time of sedimentation. In studies of offshore accumulations of terrigenous material, the marine-derived organic fraction may therefore prove a more reliable measure of radiocarbon chronology.
id: 220

In situ calcium carbonate dissolution in the Pacific Ocean - Feely, R. A.; Sabine, C. L.; Lee, K.; Millero, F. J.; Lamb, M. F.; Greeley, D.; Bullister, J. L.; Key, R. M.; Peng, T. H.; Kozyr, A.; Ono, T.; Wong, C. S. (Global Biogeochemical Cycles, 2002)
Over the past several years researchers have been working to synthesize the WOCE/JGOFS global CO(2) survey data to better understand carbon cycling processes in the oceans. The Pacific Ocean data set has over 35,000 sample locations with at least two carbon parameters, oxygen, nutrients, CFC tracers, and hydrographic parameters. In this paper we estimate the in situ CaCO(3) dissolution rates in the Pacific Ocean water column. Calcium carbonate dissolution rates ranging from 0.01-1.1 mumol kg(-1) yr(-1) are observed in intermediate and deepwater beginning near the aragonite saturation horizon. In the North Pacific Intermediate Water between 400 and 800 m, CaCO(3) dissolution rates are more than 7 times faster than observed in middle and deep water depths (average=0.051 m mol kg(-1) yr(-1)). The total amount of CaCO(3) that is dissolved within the Pacific is determined by integrating excess alkalinity throughout the water column. The total inventory of CaCO(3) added by particle dissolution in the Pacific Ocean, north of 40degreesS, is 157 Pg C. This amounts to an average dissolution rate of approximately 0.31 Pg C yr(-1). This estimate is approximately 74% of the export production of CaCO(3) estimated for the Pacific Ocean. These estimates should be considered to be upper limits for in situ carbonate dissolution in the Pacific Ocean, since a portion of the alkalinity increase results from inputs from sediments.
649rqTimes Cited:86 Cited References Count:60
Keywords: anthropogenic co(2); anthropogenic co2; aragonite saturation; atmospheric carbon; caco(3) dissolution; calcite saturation; carbonate lysocline; chemical lysocline; coccolithophore emiliania-huxleyi; indian-ocean; north pacific; organic-matter; Pacific Ocean; panama basin; particulate matter

Influence of Vegetation Change on Watershed Hydrology: Implications for Paleoclimatic Interpretation of Lacustrine d180 Records - Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H.; Martin, J. B.; Anselmetti, F. S.; Ariztegui, D.; Guilderson, T. P. (Journal of Paleolimnology, 2002)
id: 1386

Kilimanjaro ice core records: evidence of holocene climate change in tropical Africa - Thompson, L. G.; Mosley-Thompson, E.; Davis, M. E.; Henderson, K. A.; Brecher, H. H.; Zagorodnov, V. S.; Mashiotta, T. A.; Lin, P. N.; Mikhalenko, V. N.; Hardy, D. R.; Beer, J. (Science, 2002)
Six ice cores from Kilimanjaro provide an approximately 11.7-thousand-year record of Holocene climate and environmental variability for eastern equatorial Africa, including three periods of abrupt climate change: approximately 8.3, approximately 5.2, and approximately 4 thousand years ago (ka). The latter is coincident with the "First Dark Age," the period of the greatest historically recorded drought in tropical Africa. Variable deposition of F- and Na+ during the African Humid Period suggests rapidly fluctuating lake levels between approximately 11.7 and 4 ka. Over the 20th century, the areal extent of Kilimanjaro's ice fields has decreased approximately 80%, and if current climatological conditions persist, the remaining ice fields are likely to disappear between 2015 and 2020.
Thompson, Lonnie GMosley-Thompson, EllenDavis, Mary EHenderson, Keith ABrecher, Henry HZagorodnov, Victor SMashiotta, Tracy ALin, Ping-NanMikhalenko, Vladimir NHardy, Douglas RBeer, Jurgeng2002/10/19 04:00Science. 2002 Oct 18;298(5593):589-93.

A late glacial-Holocene tephrochronology for glacial lakes in southern Ecuador - Rodbell, D. T.; Bagnato, S.; Nebolini, J. C.; Seltzer, G. O.; Abbott, M. B. (Quaternary Research, 2002)
Despite the presence of numerous active volcanoes in the northern half of Ecuador, few, if any, distal tephras have been previously recognized in the southern one third of the country. In this article, we document the presence of thin (0.1-1.0-cm-thick) distal tephras comprising glass and/or phenocrysts of hornblende and feldspar in sediment cores from five glacial lakes and one bog in Las Cajas National Park (2degrees40'-3degrees00'S, 79degrees00'-79degrees25'W). The lake cores contain from 5 to 7 tephras, and each has a diagnostic major element geochemistry as determined from electron microprobe analysis of similar to710 glass shards and similar to440 phenocrysts of feldspar and hornblende. The loss of sodium with exposure to the electron microbeam causes a 10 +/- 7 wt.% (+/-1sigma) reduction in Na content, which we empirically determined and corrected for before correlating tephras among the sediment cores. We use a similarity coefficient to correlate among the sediment cores; pair-wise comparison of all tephras generally yields an unambiguous correlation among the cores. Six tephras can be traced among all or most of the cores, and several tephras are present in only one or two of the cores. Twenty-six accelerator mass spectrometry (14)C dates on macrofossils preserved in the sediment cores provide the basis for establishing a regional tephrochronology. The widespread tephras were deposited similar to9900, 8800,7300,5300,2500, and 2200 cal yr B.P. The oldest tephras were deposited similar to15,500 and 15,100 cal yr B.P., but these are not found in all cores. Two of the tephras appear correlative with volcaniclastic strata on the flanks of Volcan Cotopaxi and one tephra may correlate with strata on the flanks of Volcan Ninahuilca; both volcanoes are in central Ecuador. The absence of tephras in sediment cores correlative with the numerous eruptions of active volcanoes of the past two millennia implies that the earlier eruptions, which did deposit tephras in the lakes, must have been either especially voluminous, or southerly winds must have prevailed at the time of the eruption, or both. (C) 2002 University of Washington.
555kpTimes Cited:25Cited References Count:23

Late-Quaternary lowstands of Lake Titicaca: evidence from high-resolution seismic data - D'Agostino, K.; Seltzer, G.; Baker, P.; Fritz, S.; Dunbar, R. (Palaeogeography Palaeoclimatology Palaeoecology, 2002)
Approximately 600 km of high-resolution seismic reflection data were collected to investigate the late-Quaternary stratigraphic development of Lake Titicaca. The focus of this report is on two seismic sequence boundaries, which are interpreted as erosional surfaces formed at times of low lake level. The younger erosional surface occurs as much as 90 in below the present lake level and up to 8 in below the present sediment-water interface. This erosional surface is interpreted to be coeval with a well-documented early- to mid-Holocene lowstand, dated between similar to 8000 and 3600 cal yr BP. An earlier and previously unknown erosional surface occurs at a sub-bottom depth of approximately 30 m, and as much as 240 in below the present lake level, which implies a major late-Pleistocene lowstand of Lake Titicaca. By extrapolation of sedimentation rates from the upper similar to 14 in of sediment, we estimate the age of this older lowstand at > 90 000 cal yr BP. Both lowstands of Lake Titicaca indicated by the seismic data are likely to have been a response to climatic change in the region. (C) 2002 Elsevier Science B.V. All rights reserved.
560qxTimes Cited:31 Cited References Count:33
Keywords: Andes; bolivian altiplano; central andes; climatic-change; Holocene; lacustrine; lake level change; lake titicaca; level; malawi; Peru; record; seismic reflection data; tropical paleoclimate; tropical south-america

The limits of paleontological resolution - Kowalewski, M.; Bambach, R. K. (High Resolution Approachews in Paleontology: Kluwer Academic/Plenum, 2002)
id: 1415

Mercury in Connecticut and Long Island Sound sediment - Varekamp, J. C.; Buchholtz ten Brink, M. R. (Long Island Sound/NEERS Research Conference, 2002)
id: 729

The nature of 'stone-lines' in the African Quaternary record: archaeological resolution at the rainforest site of Mosumu, Equatorial Guinea - Mercader, J.; Marti, R.; Martinez, J. L.; Brooks, A. (Quaternary International, 2002)
'Stone-lines' are widespread Quaternary features that appear in tropical and subtropical regions. They have a diverse nature and genesis, and are frequently associated with archaeological assemblages. However, archaeological deposition and 'stone-line' configuration may be unrelated geological events separated by thousands of years. The energetics involved in 'stone-line' formation, coarse and fine material translocation across space and in depth, and overall assemblage integrity vary from one site to another. This paper presents quantitative and spatial geoarchaeological data from the site of Mosumu, in the tropical rain forest of continental Equatorial Guinea. Mosumu yielded Middle and Later Stone Age assemblages dated to at least the last 30,000 years in a 'stone-line' context. Special attention to the study of vertical and horizontal variations of artifacts, sedimentary features, and taphonomic indicators allows analysis of the nature, meaning, and archeological resolution at this site. The results are placed in the wider debate over the meaning of 'stone-lines' in the African Quaternary record. (C) 2002 Elsevier Science Ltd and INQUA. All rights reserved.
536zcTimes Cited:15 Cited References Count:89
Keywords: Age; behavior; cameroon; congo; ituri; layers; origin; tools; vegetation

Numerical models, geochemistry and the zero-paradox noble-gas mantle - Ballentine, C. J.; Van Keken, P. E.; Porcelli, D.; Hauri, E. H. (Philos Transact A Math Phys Eng Sci, 2002)
Numerical models of whole-mantle convection demonstrate that degassing of the mantle is an inefficient process, resulting in ca. 50% of the (40)Ar being degassed from the mantle system. In this sense the numerical simulations are consistent with the (40)Ar mass balance between the atmosphere and mantle reservoir. These models, however, are unable to preserve the large-scale heterogeneity predicted by models invoking geochemical layering of the mantle system. We show that the three most important noble-gas constraints on the geochemically layered mantle are entirely dependent on the (3)He concentration of the convecting mantle derived from the (3)He flux into the oceans and the average ocean-crust generation rate. A factor of 3.5 increase in the convecting-mantle noble-gas concentration removes all requirements for: a (3)He flux into the upper mantle from a deeper high (3)He source; a boundary in the mantle capable of separating heat from helium; and a substantial deep-mantle reservoir to contain a hidden (40)Ar rich reservoir. We call this model concentration for the convecting mantle the 'zero-paradox' concentration. The time-integrated flux of (3)He into the oceans is a robust observation, but only representative of the ocean-floor activity over the last 1000 years. In contrast, ocean-floor generation occurs over tens of millions of years. We argue that combining these two observations to obtain the (3)He concentration of the mantle beneath mid-ocean ridges is unsound. Other indicators of mantle (3)He concentration suggest that the real value may be at least a factor of two higher. As the zero-paradox concentration is approached, the noble-gas requirement for mantle layering is removed. We further consider the role that recycled material plays in ocean-island-basalt generation and show that a source with high (3)He and (3)He/(4)He must exist within the mantle. Nevertheless, only a small amount of this material is required to generate both the observed ocean-island (3)He/(4)He ratios and the concentrations inferred from basalt samples for this mantle source.
id: 1579; Ballentine, Chris J Van Keken, Peter E Porcelli, Don Hauri, Erik H England Philos Transact A Math Phys Eng Sci. 2002 Nov 15;360(1800):2611-31.

The Ocean Margins Program: an interdisciplinary study of carbon sources, transformations, and sinks in a temperate continental margin system - Verity, P. G.; Bauer, J. E.; Flagg, C. N.; DeMaster, D. J.; Repeta, D. J. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
The cycling of carbon on the US east coast shelf and upper slope has been studied for 20 years in a variety of interdisciplinary programs focused on the, Mid and South Atlantic Bights. The culmination of this research was a comprehensive field study conducted in 1996 to ascertain whether the Cape Hatteras shelf was a net source or sink for atmospheric CO(2), and the associated transformations and pathways of inorganic and organic carbon. The rationale, objectives, design, and overview of the Ocean Margins Program are given here as a framework to interpret the results of the papers presented in this special issue. (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:26 Cited References Count:96
Keywords: cape-hatteras; chesapeake bay; co2 fluxes; coastal zone; dissolved organic-carbon; gulf-stream; middle atlantic bight; north-carolina; slope sediments; united-states

Organic carbon deposition on the North Carolina continental slope off Cape Hatteras (USA) - Thomas, C. J.; Blair, N. E.; Alperin, M. J.; DeMaster, D. J.; Jahnke, R. A.; Martens, C. S.; Mayer, L. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
The continental slope off Cape Hatteras, NC is a region of high sediment accumulation and organic matter deposition. Sediment accumulation rates range from 3 to 151 cm kyr(-1). Organic carbon deposition rates are 5-13 moles C m(-2) yr(-1), the highest reported for the slope off the eastern US. Burial efficiencies are 3-40%. The organic matter deposited is marine in origin and a mix of old and young particles. High organic carbon deposition rates support remineralization throughout the upper 2-3 m of sediment. Deep bioirrigation to depths of 60-100 cm within the seabed affects the biogeochemistry of the sediments by extending the zone of sulfate reduction and by steepening DIC porewater gradients through the non-local exchange of porewater. Stable and radiocarbon isotope mixing curves for porewater dissolved inorganic carbon (DIC) indicate that the dominant source of DIC accumulating in the upper 2-3 m of the seabed is of nearly uniform delta(13)C (-21.10parts per thousand) and Delta(14)C (-546parts per thousand.). (C) 2002 Elsevier Science Ltd. All rights reserved.
607kxTimes Cited:31 Cited References Count:77
Keywords: anaerobic methane oxidation; early diagenesis; margin; marine-sediments; MATTER; middle-atlantic-bight; sea-floor; shelf; south; waters

Ostracoda and paleoceanography - Cronin, T. M.; Boomer, I.; Dwyer, G. S.; Rodriguez-Lazaro, J. (American Geophysical Union Monograph - The Ostracoda: Applications in Quaternay Research, 2002)
id: 1473

Paleoenvironmental history of Long Island Sound - Varekamp, J. C.; Thomas, E.; Lugolobi, F.; Buchholtz ten Brink, M. R. (Long Island Sound/NEERS Research Conference AGU Fall Meeting, 2002)
id: 1177

Possible biological or physical explanations for decadal scale trends in North Pacific nutrient concentrations and oxygen utilization - Keller, K.; Slater, R. D.; Bender, M.; Key, R. M. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2002)
We analyze North Pacific GEOSECS (1970s) and WOCE (1990s) observations to examine potential decadal trends of the marine biological carbon pump. Nitrate concentrations ([NO3]) and apparent oxygen utilization (AOU) decreased significantly in intermediate waters (by -0.6 and -2.9 mu mol kg(-1) respectively, at sigma (theta) = 27.4 kg m(-3), corresponding to approximate to 1050 m). In shallow waters (above roughly 750 m) [NO3-] and AOU increased, though the changes were not statistically significant. A sensitivity study with an ocean general circulation model indicates that reasonable perturbations of the biological carbon pump due to changes in export production or remineralization. efficiency are insufficient to account for the intermediate water tracer trends. However, changes in water ventilation rates could explain the intermediate water tracer trends and would be consistent with trends of water age derived from radiocarbon. Trends in AOU and [NO3-] provide relatively poor constraints on decadal scale trends in the marine biological carbon pump for two reasons. First, most of the expected changes due to decadal scale perturbations of the marine biota occur in shallow waters, where the available data are typically too sparse to account for the strong spatial and temporal variability. Second, alternative explanations for the observed tracer trends (e.g., changes in the water ventilation rates) cannot be firmly rejected. Our data analysis does not disprove the null-hypothesis of an unchanged biological carbon pump in the North Pacific. (C) 2001 Published by Elsevier Science Ltd.
507ceTimes Cited:24 Cited References Count:71
Keywords: anthropogenic co2 invasion; atmospheric co2; carbon-cycle; el-nino; hydrographic data; organic-matter; redfield ratios; sargasso-sea; subtropical gyre; vertical fluxes

Radiocarbon as a tool to apportion the sources of polycyclic aromatic hydrocarbons and black carbon in environmental samples - Reddy, C. M.; Pearson, A.; Xu, L.; McNichol, A. P.; Benner, B. A.; Wise, S. A.; Klouda, G. A.; Currie, L. A.; Eglinton, T. I. (Environmental Science & Technology, 2002)
To determine the relative inputs of polycyclic aromatic hydrocarbons (PAHs) and black carbon (BC) in environmental samples from the combustion of fossil fuels and biomass we have developed two independent analytical methods for determining the C-14 abundance of PAHs and BC. The 5730 yr half-life of C-14 makes it an ideal tracer for identifying combustion products derived from fossil fuels (C-14-free) versus those stemming from modern biomass (contemporary C-14). The C-14 abundance of PAHs in several environmental Standard Reference Materials was measured by accelerator mass spectrometry after extraction and then purification by high-performance liquid chromatography and preparative capillary gas chromatography. This method yields pure compounds that allow for a high degree of confidence in the C-14 results. The PAHs data were then used to compare and evaluate results from an operationally defined thermal oxidation method used to isolate a BC fraction. The C-14 compositions of PAHs and BC were very similar and suggest that the thermal oxidation method employed for isolating BC is robust and free from interferences by non-BC components. In addition, these data indicate that both the PAHs and the BC species derive mostly from fossil fuels and/or their combustion products.
541gfTimes Cited:133Cited References Count:59

Radiocarbon content of synthetic and natural semi-volatile halogenated organic compounds - Reddy, C. M.; Xu, L.; Eglinton, T. I.; Boon, J. P.; Faulkner, D. J. (Environ Pollut, 2002)
Some halogenated organic compounds, such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins (PCDDs) and polybrominated diphenyl ethers (PBDEs), have been suggested to have natural sources but separating these compounds from their commercially synthesized counterparts is difficult. Molecular-level 14C analysis may be beneficial since most synthetic compounds are manufactured from petrochemicals (14C-free) and natural compounds should have "modern" or "contemporary" 14C levels. As a baseline study, we measured, for the first time, the 14C abundance in commercial PCB and PBDE mixtures, a number of organochlorine pesticides, as well as one natural product 2-(3',5'-dibromo-2'-methoxyphenoxy)-3,5-dibromoanisole. The latter compound was isolated from a marine sponge and is similar in structure to a PBDE. All of the synthetic compounds were 14C-free except for the pesticide toxaphene. which had a modern 14C abundance, as did the brominated natural compound. The result for toxaphene was not surprising since it was commercially synthesized by the chlorination of camphene derived from pine trees. These results suggest that measuring the 14C content of halogenated organic compounds may be quite useful in establishing whether organic compounds encountered in the environment have natural or synthetic origins (or both) provided that any synthetic counterparts derive from petrochemical feedstock.
Reddy, Christopher MXu, Li Eglinton, Timothy I Boon, Jan P Faulkner, D John eng Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. England 2002/10/25 04:00 Environ Pollut. 2002;120(2):163-8.
Keywords: Animals; Carbon Radioisotopes/*analysis; Environmental Pollutants/*analysis; Hydrocarbons, Halogenated/chemical synthesis/*chemistry; Insecticides/chemistry; Polychlorinated Biphenyls/chemistry; Porifera/*chemistry; Toxaphene/chemistry

Radiocarbon dating, chronologic framework, and changes in accumulation rates of Holocene estuarine sediments from Chesapeake Bay - Colman, S. M.; Baucom, P. C.; Bratton, J. F.; Cronin, T. M.; McGeehin, J. P.; Willard, D.; Zimmerman, A. R.; Vogt, P. R. (Quaternary Research, 2002)
Rapidly accumulating Holocene sediments in estuaries commonly are difficult to sample and date. In Chesapeake Bay, we obtained sediment cores as much as 20 m in length and used numerous radiocarbon ages measured by accelerator mass spectrometry methods to provide the first detailed chronologies of Holocene sediment accumulation in the bay. Carbon in these sediments is a complex mixture of materials from a variety of sources. Analyses of different components of the sediments show that total organic carbon ages are largely unreliable, because much of the carbon (including coal) has been transported to the bay from upstream sources and is older than sediments in which it was deposited. Mollusk shells (clams, oysters) and foraminifera appear to give reliable results, although reworking and burrowing are potential problems. Analyses of museum specimens collected alive before atmospheric nuclear testing suggest that the standard reservoir correction for marine samples is appropriate for middle to lower Chesapeake Bay. The biogenic carbonate radiocarbon ages are compatible with (210)Pb and (137)Cs data and pollen stratigraphy from the same sites.Post-settlement changes in sediment transport and accumulation is an important environmental issue in many estuaries, including the Chesapeake. Our data show that large variations in sediment mass accumulation rates occur among sites. At shallow water sites, local factors seem to control changes in accumulation rates with time. Our two relatively deep-water sites in the axial channel of the bay have different long-term average accumulation rates, but the history of sediment accumulation at these sites appears to reflect overall conditions in the bay. Mass accumulation rates at the two deep-water sites rapidly increased by about fourfold coincident with widespread land clearance for agriculture in the Chesapeake watershed.
517wpTimes Cited:57Cited References Count:33

Rates of evolution in ancient DNA from Adelie penguins - Lambert, D. M.; Ritchie, P. A.; Millar, C. D.; Holland, B.; Drummond, A. J.; Baroni, C. (Science, 2002)
Well-preserved subfossil bones of Adelie penguins, Pygoscelis adeliae, underlie existing and abandoned nesting colonies in Antarctica. These bones, dating back to more than 7000 years before the present, harbor some of the best-preserved ancient DNA yet discovered. From 96 radiocarbon-aged bones, we report large numbers of mitochondrial haplotypes, some of which appear to be extinct, given the 380 living birds sampled. We demonstrate DNA sequence evolution through time and estimate the rate of evolution of the hypervariable region I using a Markov chain Monte Carlo integration and a least-squares regression analysis. Our calculated rates of evolution are approximately two to seven times higher than previous indirect phylogenetic estimates.
Lambert, D MRitchie, P AMillar, C DHolland, BDrummond, A JBaroni, CengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, P.H.S.2002/03/23 10:00Science. 2002 Mar 22;295(5563):2270-3.

Reassessment of Lake Victoria–Upper Nile River paleohydrology from oxygen isotope records of lake-sediment cellulose - Beuning, K. R. M.; Kelts, K. R.; Russell, J. M.; Wolfe, B. B. (Geology, 2002)
Reconstruction of lake-water δ18O from analysis of cellulose δ18O in two sediment cores from Lake Victoria, East Africa, shows a large shift to lower values during the terminal Pleistocene. This shift records the transition from closed- to open-basin conditions following desiccation at the Last Glacial Maximum. Although oxygen isotope analysis of cellulose from one core had placed this overflow at 8 ka (7200 14C yr B.P.), reevaluation of the age model for this core, in addition to new stratigraphic and chronological evidence from a second core, suggests that basin overflow was established much earlier, ca. 13 ka. Our refined view of the timing of Lake Victoria overflow inferred from the oxygen isotope records is consistent with other paleolimnological studies, indicating that lake-sediment cellulose is an effective and sensitive isotopic archive of major hydrologic events in this region.
id: 1011
Keywords: cellulose; East Africa; isotope; oxygen; paleohydrology

Slip rates of the Karakorum fault, Ladakh, India, determined using cosmic ray exposure dating of debris flows and moraines - Brown, E. T.; Bendick, R.; Bourles, D. L.; Gaur, V.; Molnar, P.; Raisbeck, G. M.; Yiou, F. (Journal of Geophysical Research-Solid Earth, 2002)
We measure an average slip rate of 4+/-1 mm yr(-1) along the Karakorum fault, heretofore considered one of Earth's greatest strike-slip faults and thought by many to play a key role in Asian deformation kinematics. Levees of a debris flow, and contours of the fan on which it was deposited, have been displaced 40+/-5 m. Concentrations of Be-10 in boulders from the debris flow yield ages of 11-14 ka, implying a slip rate of 4+/-1 mm yr(-1) during that period. A fresher debris flow has been offset 2-2.5 m since 1-2 ka, implying the occurrence of an earthquake with Msimilar to7 since that time. Concentrations of Be-10 in boulders on the crest of the most extensive moraine near Leh imply that the most recent major glacial advance occurred at 90+/-15 ka. This is consistent with the inference of others that alpine glaciers in this region have not necessarily expanded in concert with Northern Hemisphere continental ice sheets. If features, including lateral moraines, that Liu inferred to have been offset 300-350 m by the Karakorum fault date from the same period, they too imply a slip rate of 3-4 mm yr(-1). This slip rate is comparable to rates of extension across grabens within Tibet. With recent evidence that slip along the Altyn Tagh fault occurs at similar to10 mm yr(-1), our rate suggests that slip along the boundaries of Tibet is not significantly more rapid than extension within the plateau. Hence, plate tectonics, in the strictest sense, ought not be applied to Tibet, because Tibet does not behave as a rigid plate.
634wuTimes Cited:104Cited References Count:72

Temporal and regional variability in sources and cycling of DOC and POC in the northwest Atlantic continental shelf and slope - Bauer, J. E.; Druffel, E. R. M.; Wolgast, D. M.; Griffin, S. (Deep-Sea Research II, 2002)
id: 685

Were glacial iceberg surges in the North Atlantic triggered by global climatic warming? - Moros, M.; Kuijpers, A.; Snowball, I.; Lassen, S.; Backstrom, D.; Gingele, F.; McManus, J. F. (Marine Geology, 2002)
id: 712

A 160,000-year record of tropical climate variability from Salar de Uyuni, Bolivia - Fritz, S. C.; Baker, P. A.; Dwyer, G. S. (EOS, Transactions, American Geophysical Union, 2001)
id: 1474

A 700 year sedimentary record of intense hurricane landfalls in southern New England - Donnelly, Jeffrey P.; Bryant, Sarah Smith; Butler, Jessica; Dowling, Jennifer; Fan, Linda; Hausmann, Neil; Newby, Paige; Shuman, Bryan; Stern, Jennifer; Westover, Karlyn; Webb, Thompson, III (GSA Bulletin, 2001)
id: 1343

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

Across forests and savannas: Later Stone Age assemblages from Ituri and Semliki, Northeast Domacratic Republic of Congo - Mercader, J.; Brooks, A. (Journal of Antropological Research, 2001)
id: 1217

Algal and archaeal polyisoprenoids in a recent marine sediment: Molecular isotopic evidence for anaerobic oxidation of methane - Bian, L. Q.; Hinrichs, K. U.; Xie, T. M.; Brassell, S. C.; Iversen, H.; Fossing, H.; Jorgensen, B. B.; Hayes, J. M. (Geochemistry Geophysics Geosystems, 2001)
Analyses of C-13 contents of individual organic molecules in a marine sediment show that crocetane, 2,6,11,15-tetramethylhexadecane, an isomer of phytane, is produced by microorganisms that use methane as their main source of carbon. The sediments lie at a water depth of 68 m in the Kattegat, the strait between Denmark and Sweden. Crocetane appears first 185 cm below the sediment-water interface, in the zone marking the transition from sulfate reduction to methanogenesis. Its delta C-13 value is -90 +/- 10 parts per thousand versus Vienna Pee Dee Belemnite (VPDB). Its structure, which includes four isoprene units arranged symmetrically around a tail-to-tail linkage, suggests that it is produced by a member of the archaea. Growing at the intersection of the diffusion gradients for sulfate and methane in sedimentary pore waters, the source organism apparently function as a methane-consuming member of the microbial consortium responsible for the anaerobic oxidation of methane [Hoehler et al., 1994], in which, as first demonstrated quantitatively in these sediments [Iversen and Jorgensen, 1985], electrons are transferred from methane to sulfate. The presence of archaeal biomass throughout the sediment section is indicated by significant concentrations of 2,6,10,15,19-pentamethylicosane (PMI) and of ether-bound phytane and biphytane. The PMI reaches a minimum delta value of -47 parts per thousand well below the transition zone. Its isotopic depletion could reflect either methanogenic or methanotrophic sources. The ether-bound lipids are isotopically uniform throughout the section and are presumed to derive from archaea that utilize a carbon source unaffected by the oxidation of methane.
458jvTimes Cited:51Cited References Count:79

Carbonate 14C Background: Does it have Multiple Personalities? - Nadeau, Marie-Josee; Grootes, Pieter M.; Voelker, Antje; Bruhn, Frank; Duhr, Alexander; Oriwall, Angelika (Radiocarbon, 2001)
id: 1501

Chronology of the Palmer Deep Site, Antarctic Peninsula: A Holocene Paleoenvironmental reference for the circum-Antarctic - Domack, E. W.; Leventer, A.; Dunbar, R.; Taylory, R.; Brachfeld, S.; Sjunneskog, C. (The Holocene, 2001)
id: 119

Chronology of the Palmer Deep Site, Antarctic Peninsula: A Holocene Paleoenvironmental reference for the circum-Antarctic - Domack, E. W.; Leventer, A.; Dunbar, R.; Taylor, R.; Brachfeld, S.; Sjunneskog, C. (The Holocene, 2001)
Palmer Deep sediment cores are used to produce the first high-resolution, continuous late Pleistocene to Holocene time-series from the Antarctic marine system. The sedimentary record is dated using accelerator mass spectrometer radiocarbon methods on acid insoluble organic matter and foraminiferal calcite. Fifty-four radiocarbon analyses are utilized in the dating which provides a calibrated timescale back to 13 ka BP. Reliability of resultant ages on organic matter is assured because duplicates produce a standard deviation from the surface age of less than laboratory error (i.e., ±50 years). In addition, surface organic matter ages at the site are in excellent agreement with living calcite ages at the accepted reservoir age of 1260 years for the Antarctic Peninsula. Spectral analyses of the magnetic susceptibility record against the age model reveal unusually strong periodicity in the 400,–200 and 50-70 year frequency bands, similar to other high-resolution records from the Holocene but, so far, unique for the circum-Antarctic. Here we show that comparison to icecore records of specific climatic events (e.g., the ’Little Ice Age‘, Neoglacial, Hypsithermal, and the Bølling/Allerød to Younger Dryas transition) provides improved focus upon the relative timing of atmosphere/ocean changes between the northern anid southern high latitudes.
id: 1319

Climate change in the circum-Caribbean (late Pleistocene-to-Present) and implications for regional biogeography - Curtis, J. H.; Brenner, M.; Hodell, D. A. (Biogeography of the West Indies: Patterns and Perspectives, 2nd Edition, 2001)
id: 265

Climatic significance of large lakes on the Altiplano of South America - Baker, P. A.; Seltzer, G. O.; Fritz, S. C.; Rigsby, C. A.; Dwyer, G. S. (EOS, Transactions, American Geophysical Union, 2001)
id: 333

Converting AMS data to radiocarbon values: Considerations and conventions - McNichol, A. P.; Jull, A. J. T.; Burr, G. S. (Radiocarbon, 2001)
We summarize the basic operation of accelerator mass spectrometry (AMS) systems used to measure radiocarbon and discuss the calculations used to convert AMS output to C-14 data.
1531yc Times Cited:24 Cited References Count:19
Keywords: accelerator mass-spectrometry; NOSAMS; ratio

Correction of H3+ contributions in hydrogen isotope ratio monitoring mass spectrometry - Sessions, A. L.; Burgoyne, T. W.; Hayes, J. M. (Anal Chem, 2001)
Two fundamentally different approaches, termed "pointwise" and "peakwise," are currently used to correct hydrogen isotope ratio monitoring data for the presence of H3+ ion contributions. Consideration of the underlying assumptions shows that the peakwise approach is valid only for peaks with the same functional shape and only when background signals do not vary. The pointwise correction is much more versatile and can be used even when peak shapes and sizes, as well as background signals, vary significantly. It is not exact and is limited in accuracy by (1) the signal-broadening effects of electronic time constants, (2) the analog-to-digital conversion frequency, and (3) the highest frequency of the sample signal. To minimize errors for typical gas chromatographic signals, time constants of <500 ms and analog-to-digital sampling intervals of < or =250 ms are needed. Errors are further minimized by matching sample and standard peaks in both amplitude and D/H ratio. Using the pointwise algorithm, we demonstrate that a series of 14 homologous n-alkanes varying in concentration over a 5-fold range can be analyzed with a mean precision of 2.3 per thousand and no systematic errors.
Sessions, A LBurgoyne, T W Hayes, J M eng 2001/02/24 12:00 Anal Chem. 2001 Jan 15;73(2):192-9.

Decadal record of climate variability spanning the last 700 years in the southern tropics of East Africa - Johnson, T. C.; Barry, S. L.; Chan, Y.; Wilkinson, P. (Geology, 2001)
id: 1477

The deglaciation of eastern Maine: in Deglacial history and relative sea-level changes, northern New England and adjacent Canada - Dorion, C. C.; Kaplan, M. R.; Kreutz, K. J.; Balco, G.; Wright, J.; Borns, H. W., Jr. (Deglacial history and relative sea-level changes, northern New England and adjacent Canada, 2001)
id: 1310

Deposition of Bomb C-14 in Continental Slope Sediments: Use of Radiocarbon in Understanding Benthic Food Web Dynamics - DeMaster, D. J.; Blair, N. E.; Smith, C. R.; Fornes, W. L.; Thomas, C. J.; Plaia, G. (Aquatic Sciences Meeting, ASLO, 2001)
id: 1368

Determination of the the H3 factor in hydrogen isotope ratio monitoring mass spectrometry - Sessions, A. L.; Burgoyne, T. W.; Hayes, J. M. (Anal Chem, 2001)
The H3 factor, K, is a parameter required in high-precision, mass spectrometric analyses of hydrogen isotopic abundances. When H2 is used as the sample gas, R* = R - Ki2, where R* is the true HD/H2 ratio, R is the observed (mass 3)/(mass 2) ion-current ratio, and i2 is the ion current at mass 2. Four different methods for the determination of K were defined and tested under conditions characteristic of isotope ratio monitoring systems. Three of these were peak-based. The fourth employed steady flows of H2 from a conventional inlet system. Results obtained using the latter method were more precise (standard deviation of K = 0.1 versus approximately 0.6 ppm mV(-1) for the peak-based methods). However, use of the resulting values of K for correction of isotope ratio monitoring GC/MS results led to systematic errors as large as 9 per thousand, whereas use of the peak-based values led to no systematic errors. Values of K were only weakly dependent on the pressure of He, declining approximately 5% for each 10-fold increase in P(He). Small variations in partial pressures of H2O and CH4, potential contaminants under isotope ratio monitoring conditions, had no significant effect on values of K.
Sessions, A LBurgoyne, T W Hayes, J M eng 2001/02/24 12:00 Anal Chem. 2001 Jan 15;73(2):200-7.

Diastems and time-averaging: The limits of resolution in stratigraphy and paleontology - Kowalewski, M.; Bambach, R. K. (Geological Society of America Abstracts with Programs, 2001)
id: 282

Drainage of late Wisconsin glacial lakes and the morphology and late quaternary stratigraphy of the New Jersey-southern New England continental shelf and slope - Uchupi, E.; Driscoll, N.; Ballard, R. D.; Bolmer, S. T. (Marine Geology, 2001)
We propose that late Wisconsin deposition and erosion (Hudson Shelf and Block Island valleys) on the shelf and slope from New Jersey to southern New England were a consequence of the catastrophic drainage of glacial lakes behind terminal moraine systems and the huge volume of water stored beneath the Laurentian ice sheet and subsequent erosion of the lake sediments by flash floods. The morphology imparted by glaciation regulated the discharge associated with the ablation of the glaciers. Associated with the deposits west of Hudson Shelf Valley are the remains of mammoth and mastodon which were transported from their living habitats along the lake shores to their present burial sites on the shelf. The floods also triggered gravity flows on the upper continental slope which made possible the transportation of coarse debris over hundreds of km into the deep-sea. That these catastrophic hood morphologies can still be recognized on the middle to outer shelf suggest that much of its surface was little modified during the late Pleistocene/Holocene transgression. Thus the late Pleistocene/Holocene transgression may have been characterized by short periods when sea level rose rapidly allowing for the preservation of relict features. (C) 2001 Elsevier Science B.V. All rights reserved.
400trTimes Cited:50Cited References Count:115

The Effect of Different Acid Treatments on the Radiocarbon Age of Sedimentary Organic Matter - Batista, F; McNichol, A P; Gerlach, D S (EOS, Transactions, American Geophysical Union, 2001)
To date the bulk organic carbon in marine sediments it is necessary to first remove any inorganic carbon present by acidification. We tested three different acid treatments to see how the different methods affected the stable and radio-carbon isotopic values of the remaining organic matter. The standard NOSAMS method is to react the sediment with repeated aliquots of1.2N HCl until no visible dissolution reaction is present. The remaining sediment is then rinsed with distilled water. This method leaves a carbonate-free sediment that is easy to combust but suffers from the possible removal of acid-soluble organic matter. We compared this method to two methods that do not require rinsing of the sediments after acid treatment--a vapor phase acidification method using concentrated HCl (Hedges and Stern, 1984) and an in situ acidification with sulfurous acid (Verardo et al., 1990). Scaling these methods up to deal with the amount of sediment required for a radiocarbon date can present challenges that are not evident when dealing with the small quantities required for a percent organic carbon measurement. Vapor phase acidification of high carbonate sediments leaves hygroscopic salts that can impede sample combustion. Sulfurous acid is a weak acid and it is very difficult to determine when all the carbonate has been removed from a sediment sample. We tested sediments from 6 locations in (or near) the Atlantic Ocean that represented riverine, estuarine, and marine environments as well as a range of both organic and inorganic concentrations. We will present the isotopic results for these sediments and evaluate what is the most appropriate method to use. Hedges J.I. and J.H. Stern (1984) Limnol. Oceanogr. 29, 657-663. Verardo D.J., P.N. Froelich and A. McIntyre (1990) Deep-Sea Res. 37, 157-165.
Date revised - 2007-02-01SuppNotes - Session: OS41A 9 The Truth About Paleoceanographic Proxies - What Are They Really Telling Us III Posters.Last updated - 2016-05-27
Keywords: A, Atlantic; Acidification; Brackish; Brackishwater environment; carbon cycling; Chronostratigraphy; Estuarine sedimentation; organic carbon; organic matter; Palaeoceanography; Radioactivity and radioisotopes; Radiocarbon dating; Sediment chemistry; Stable isotopes

Estimates of anthropogenic carbon uptake from four three-dimensional global ocean models - Orr, J. C.; Maier-Reimer, E.; Mikolajewicz, U.; Monfray, P.; Sarmiento, J. L.; Toggweiler, J. R.; Taylor, N. K.; Palmer, J.; Gruber, N.; Sabine, C. L.; Le Quere, C.; Key, R. M.; et al. (Global Biogeochemical Cycles, 2001)
We have compared simulations of anthropogenic CO2 in the four three-dimensional ocean models that participated in the first phase of the Ocean Carbon-Cycle Model Intercomparison Project (OCMIP), as a means to identify their major differences. Simulated global uptake agrees to within +/- 19%, giving a range of 1.85 +/-0.35 Pg C yr(-1) for the 1980-1989 average, Regionally, the Southern Ocean dominates the present-day air-sea flux of anthropogenic CO2 in all models, with one third to one half of the global uptake occurring south of 30 degreesS. The highest simulated total uptake in the Southern Ocean was 70% larger than the lowest. Comparison with recent data-based estimates of anthropogenic CO2 suggest that most of the models substantially overestimate storage in the Southern Ocean; elsewhere they generally underestimate storage by less than 20%. Globally, the OCMIP models appear to bracket the real ocean's present uptake, based on comparison of regional data-based estimates of anthropogenic CO2 and bomb C-14. Column inventories of bomb C-14 have become more similar to those for anthropogenic CO2 with the time that has elapsed between the Geochemical Ocean Sections Study (1970s) and World Ocean Circulation Experiment (1990s) global sampling campaigns. Our ability to evaluate simulated anthropogenic CO2 would improve if systematic errors associated with the data-based estimates could be provided regionally.
417rwTimes Cited:187Cited References Count:64

Evaluation of a protocol for the quantification of black carbon in sediments, soils, and aquatic sediments - Gustafsson, O.; Bucheli, T. D.; Kululska, M.; Andersson, C.; Largeau, C.; Rouzard, J. N.; Reddy, C. M.; Eglinton, T. I. (Global Biogeochem. Cycles, 2001)
id: 1439

Heart Butte Reservoir 1998-2000 Archeological Investigations, Grant County, North Dakota - Jackson, Michael A.; Bales, Jennifer R. (Department of Anthropology, University of North Dakota, Grand Forks, 2001)
id: 200

High frequency dynamics of the East Asian Monsoon during the last 200,000 years - Garidel-Thoron, T. de; Beaaufort, L.; Linsley, B. K.; Dannenmann, S. (Paleoceanography, 2001)
id: 272

The history of South American tropical precipitation for the past 25,000 years - Baker, P. A.; Seltzer, G. O.; Fritz, S. C.; Dunbar, R. B.; Grove, M. J.; Tapia, P. M.; Cross, S. L.; Rowe, H. D.; Broda, J. P. (Science, 2001)
Long sediment cores recovered from the deep portions of Lake Titicaca are used to reconstruct the precipitation history of tropical South America for the past 25,000 years. Lake Titicaca was a deep, fresh, and continuously overflowing lake during the last glacial stage, from before 25,000 to 15,000 calibrated years before the present (cal yr B.P.), signifying that during the last glacial maximum (LGM), the Altiplano of Bolivia and Peru and much of the Amazon basin were wetter than today. The LGM in this part of the Andes is dated at 21,000 cal yr B.P., approximately coincident with the global LGM. Maximum aridity and lowest lake level occurred in the early and middle Holocene (8000 to 5500 cal yr B.P.) during a time of low summer insolation. Today, rising levels of Lake Titicaca and wet conditions in Amazonia are correlated with anomalously cold sea-surface temperatures in the northern equatorial Atlantic. Likewise, during the deglacial and Holocene periods, there were several millennial-scale wet phases on the Altiplano and in Amazonia that coincided with anomalously cold periods in the equatorial and high-latitude North Atlantic, such as the Younger Dryas.
id: 369; Baker, P A Seltzer, G O Fritz, S C Dunbar, R B Grove, M J Tapia, P M Cross, S L Rowe, H D Broda, J P New York, N.Y. Science. 2001 Jan 26;291(5504):640-3.

The Holocene paleolimnology of Lake Issyk-Kul, Kyrgystan: trace element and stable isotope composition of ostracods - Ricketts, R. D.; Johnson, T. C.; Brown, E. T.; Rasmussen, K. A.; Romanovsky, V. V. (Paleogeography, Palaeoclimatology, Palaeocecology, 2001)
The stable isotope and trace element geochemistry of ostracode shells from Lake Issyk-Kul, Kyrgyzstan, provide an important new paleoclimate record for central Asia. The δ18O, δ13C, Sr/Ca, Mg/Ca and U/Ca composition of shells from the species Candona neglecta found in two piston cores constrains the paleohydrology of the lake from 8700 to 1000 calendar yr before present. These data, combined with robust chronologies based on 16 AMS 14C dates, suggest that the region went from a relatively moist climate in the early Holocene to a more arid climate in the late Holocene. Intense freshwater input, presumably glacial runoff, flowed into the lake from 8700 to 8300 cal yr BP as evident from the δ18O and δ13C values. From 8300 to 6900 cal yr BP δ18O and Sr/Ca values indicate that the lake was relatively fresh and an open basin, and U/Ca values suggest that the lake was well-mixed with well-oxygenated bottom waters. There is a transition zone between 6900 and 4900 cal yr BP when δ18O and Sr/Ca values rapidly increase and Mg/Ca and U/Ca values rapidly decrease. During this period the lake evolved from an open, freshwater, well-mixed lake to a closed, more saline, less well-mixed lake. For the remainder of the record δ18O, Sr/Ca, Mg/Ca and U/Ca are relatively constant, implying conditions similar to modern conditions, although the slight increasing trend in Sr/Ca may suggest an increase in salinity over this period. The δ13C values were approximately in equilibrium with atmospheric CO2 in the early part of the record but became relatively negative in the later part of the record. This indicates that the dominant mechanism controlling the isotopic composition of dissolved inorganic carbon shifted from exchange with the atmosphere to variations in biological productivity.
id: 341

Installation of a 134-sample MC-SNICS at the NOSAMS facility and first results - Bellino, Mary; von Reden, Karl F.; Schneider, Robert J.; Long, Patricia Long; Healy, Richard (Symposium of NorthEastern Accelerator Personnel, Oak Ridge National Lab., USA, October 25-28, 1999, 2001)
id: 1718

Late quaternary climate and hydrology of tropical South America inferred from an isotopic and chemical model of Lake Titicaca, Bolivia and Peru - Cross, S. L.; Baker, P. A.; Seltzer, G. O.; Fritz, S. C.; Dunbar, R. B. (Quaternary Research, 2001)
A simple mass balance model provides insight into the hydrologic, isotopic, and chemical responses of Lake Titicaca to past climatic changes. Latest Pleistocene climate of the Altiplano is assumed to have been 20% wetter and 5 degreesC colder than today, based on previous modeling. Our simulation of lacustrine change since 15,000 cal yr B.P. is forced by these modeled climate changes. The latest Pleistocene Lake Titicaca was deep, fresh, and overflowing. The latest Pleistocene riverine discharge from the lake was about 8 times greater than the modern average, sufficient to allow the expansion of the great paleolake Tauca on the central Altiplano. The lake delta O-18 value averaged about -13 parts per thousand SMOW (the modern value is about -4.2 parts per thousand). The early Holocene decrease in precipitation caused Lake Titicaca to fall below its outlet and contributed to a rapid desiccation of paleolake Tauca. Continued evaporation caused the 100-m drop in lake level, but only a slight(1-2 parts per thousand) increase (relative to modern) in delta O-18 Of early Holocene lake waters. This Holocene lowstand level of nearly 100 m was most likely produced by a precipitation decrease, relative to modern, of about 40%, The lake was saline as recently as 2000 cal yr B.P. The timing of these hydrologic changes is in general agreement with calculated changes of insolation forcing of the South American summer monsoon, (C) 2001 University of Washington.
452lzTimes Cited:50Cited References Count:46

Late Quaternary water-level variations and vegetation history at Crooked Pond, southeastern Massachusetts - Shuman, B.; Bravo, J.; Kaye, J.; Lynch, J. A.; Newby, P.; Webb, T. (Quaternary Research, 2001)
Sediment cores collected along a transect in Crooked Pond, southeastern Massachusetts, provide evidence of water-level changes between 15,000 cal yr B.P. and present. The extent of fine-grained, detrital, organic accumulation in the basin, inferred from sediment and pollen stratigraphies, varied over time and indicates low water levels between 11,200 and 8000 cal yr B.P. and from ca. 5300 to 3200 cal yr B.P. This history is consistent with the paleohydrology records from nearby Makepeace Cedar Swamp and other sites from New England and eastern Canada and with temporal patterns of regional changes in effective soil moisture inferred from pollen data. The similarities among these records indicate that (1) regional conditions were drier than today when white pine (Pinus strobus) grew abundantly in southern New England (11,200 to 9500 cal yr B.P.); (2) higher moisture levels existed between 8000 and 5500 cal yr B.P., possibly caused by increased meridonal circulation as the influence of the Laurentide ice sheet waned; and (3) drier conditions possibly contributed to the regional decline in hemlock (Tsuga) abundances at 5300 cal yr B.P. Although sea-level rise may have been an influence, moist climatic conditions during the late Holocene were the primary reason for a dramatic rise in water-table elevations. (C) 2001 University of Washington.
id: 1379; 493FU Times Cited:43 Cited References Count:41

Millennial-scale dynamics of the East Asian winter monsoon during the last 200,000 years - de Garidel-Thoron, Thibault; Beaufort, Luc (Paleoceanography, 2001)
id: 251

Multiple anthropogenic tracer distributions in the ocean - Sabine, C. L.; Key, R. M.; Bullister, J. L.; Feely, R. A.; Lamb, M. F.; Millero, F. J.; Wanninkhof, R.; Peng, T. H.; Lee, K.; Kozyr, A.; Gruber, N. (Sixth International CO2 Conference, 2001)
id: 319

New records show pronounced changes in Arctic Ocean circulation and climate (cover article) - Darby, D.; Bischof, J.; Cutter, G.; de Vernal, A.; Hillaire-Marcel, C.; Dwyer, G.; McManus, J.; Polyak, L.; Osterman, L.; Poore, R. (EOS, Transactions, American Geophysical Union, 2001)
id: 332

Ocean Circulation and Climate - Schlosser, P.; Bullister, J. L.; Fine, R.; Jenkins, W. J.; Key, R.; Lupton, J.; Roether, W.; Smethie, W. M., Jr. (Observing and Modelling the Global Ocean, 2001)
id: 309

Oceanic changes in the southern Pacific Ocean during the last deglaciation time, as recorded by planktic foraminifers and oxigen isotopes. --Extended abstract - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Brilli, M.; Turi, B.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies", 2001)
id: 1428

Origins of lipid biomarkers in Santa Monica Basin surface sediment: A case study using compound-specific D14C analysis - Pearson, A.; McNichol, A. P.; Benitez-Nelson, B. C.; Hayes, J. M.; Eglinton, T. I. (Geochimica et Cosmochimica Acta, 2001)
id: 1419

Paleoceanographic changes in the Southern Ocean, during the last deglaciation time, as recorded by planktic foraminifers and oxygen isotopes--Poster - Morigi, C.; Capotondi, L.; Giglio, F.; Langone, L.; Turi, B.; Brilli, M.; Ravaioli, M. (ANTOSTRAT Symposium on "The geologic record of the Antarctic ice sheet from drilling, coring and seismic studies"--Poster, 2001)
id: 1424

Paleoclimate through the ages from the Cariaco Basin, Abstract - Hughen, K. A.; Peterson, L. C.; Black, D.; Haug, G.; Poore, R. (American Geophysical Union, 2001)
id: 1467

Persistent solar influence on North Atlantic climate during the Holocene - Bond, G.; Kromer, B.; Beer, J.; Muscheler, R.; Evans, M. N.; Showers, W.; Hoffmann, S.; Lotti-Bond, R.; Hajdas, I.; Bonani, G. (Science, 2001)
Surface winds and surface ocean hydrography in the subpolar North Atlantic appear to have been influenced by variations in solar output through the entire Holocene. The evidence comes from a close correlation between inferred changes in production rates of the cosmogenic nuclides carbon-14 and beryllium-10 and centennial to millennial time scale changes in proxies of drift ice measured in deep-sea sediment cores. A solar forcing mechanism therefore may underlie at least the Holocene segment of the North Atlantic's "1500-year" cycle. The surface hydrographic changes may have affected production of North Atlantic Deep Water, potentially providing an additional mechanism for amplifying the solar signals and transmitting them globally.
id: 1397; Bond, G Kromer, B Beer, J Muscheler, R Evans, M N Showers, W Hoffmann, S Lotti-Bond, R Hajdas, I Bonani, G New York, N.Y. Science. 2001 Dec 7;294(5549):2130-6. Epub 2001 Nov 15.

Pleistocene glacial history of the southern Ahklun Mountains, southwestern Alaska: Soil-development, morphometric, and radiocarbon constraints - Manley, W. F.; Kaufman, D. S.; Briner, J. P. (Quaternary Science Reviews, 2001)
Four new AMS ages, glacial mapping, and measurements of soil development, loess thickness, and moraine morphology constrain the age and extent of at least three Quaternary advances by outlet lobes of an ice cap over the Ahklun Mountains of southwestern Alaska. The relative-age data are from 107 sites correlated to 25 ice-marginal positions in the Kanektok, Goodnews, Togiak, and Kulukak River valleys and along the southeastern flank of the range. Radiocarbon ages provide minimum ages for six — and a maximum age for one — of the former ice margins. Soil and morphometric parameters subdivide the ice limits into three relative-age groups. One to three pre-Wisconsin advances, probably middle Pleistocene in age, are represented by drift with relatively thick B horizons (60±5 cm, with Bt horizons), thick loess caps (80±12 cm), and broad moraines (135±134 m) with gentle side slopes (7±5°). An extensive early Wisconsin (sensu lato, s.l.) advance, >39.9 ka, and three associated stillstands or readvances are characterized by intermediate soil and morphometric parameters (Bw and weak Bt horizons with thicknesses of 40±11 cm; loess thicknesses of 69±46 cm; crest widths of 38±13 m; and slope angles of 14±4°). The maximum late Wisconsin advance, >16.9 ka, and two readvances or stillstands are associated with thin (20±5 cm), weakly to moderately developed Bw horizons, thin loess caps (28±8 cm), narrow crest widths (28±9 m), and steep slope angles (18±3°). The data confirm that early-Wisconsin glaciers in southeast Beringia were much more extensive than late Wisconsin glaciers, which were apparently limited by availability of moisture.
id: 1204

Pollen record of the last 500 years from the Doninos coastal lagoon (NW Iberian Peninsula): Changes in the pollinic catchment size versus paleoecological interpretation - Santos, L.; Bao, R.; Goni, M. F. S. (Journal of Coastal Research, 2001)
Pollen, diatom, charcoal and sedimentological analyses of a 4.20-m long core collected in the margin of the Doninos coastal lagoon, northwest Iberian Peninsula, provide information about the environmental evolution of this lagoon during the last 530 yr BP. During this time period, local environmental changes, such as changes in the sand-barrier permeability, alluvial sedimentation and/or anthropogenic activity, played a major role in the evolution of this coastal system. This scenario allows us to test the degree the pollinic signal recorded in the sediments of coastal lagoons is reshaped by the influence of local processes.Diatom and sedimentological data as well as historical archives indicate the development of a lacustrine system at the bottom of the sequence. Therefore, the coring site might be included in the lagoon itself. Pollen data seems to reflect the regional vegetation as a consequence of the large pollinic catchment area. Local Castanea cultivation and anthropogenic deforestation are also recorded. At the top of the sequence, diatom facies suggest increased marine influence at this time as a consequence of the more common events of breaching of a retrograding barrier. This, plus natural silting up by alluvial sedimentation and man-induced drying up of the lagoonal margins, lead to a progressive decrease in the water body extension. The coring point is now outside of the lagoon, implying a reduction in the pollinic catchment area that gave rise to a gradual increase in the local pollinic rainfall of periphytic vegetation. From the pollen diagram of this coastal deposit signatures of regional vegetation are swamped by local pollen input. The fluctuations in the percentages of the different pollen taxa are related to the complex interaction between basin size, human activities and breaching of the barrier. Caution must therefore be taken with direct paleoclimatic inferences from pollinic studies in coastal lagoons as an alternative where other continental deposits are lacking.
479bdTimes Cited:6 Cited References Count:46
Keywords: charcoal; coastal lagoon; diatoms; human impact; Late Holocene; late-holocene; nw iberian peninsula; pollen; representation; source area; vegetation; vegetation history

Rapid shoreward encroachment of salt marsh cordgrass in response to accelerated sea-level rise - Donnelly, J. P.; Bertness, M. D. (Proc Natl Acad Sci U S A, 2001)
The distribution of New England salt marsh communities is intrinsically linked to the magnitude, frequency, and duration of tidal inundation. Cordgrass (Spartina alterniflora) exclusively inhabits the frequently flooded lower elevations, whereas a mosaic of marsh hay (Spartina patens), spike grass (Distichlis spicata), and black rush (Juncus gerardi) typically dominate higher elevations. Monitoring plant zonal boundaries in two New England salt marshes revealed that low-marsh cordgrass rapidly moved landward at the expense of higher-marsh species between 1995 and 1998. Plant macrofossils from sediment cores across modern plant community boundaries provided a 2,500-year record of marsh community composition and documented the migration of cordgrass into the high marsh. Isotopic dating revealed that the initiation of cordgrass migration occurred in the late 19th century and continued through the 20th century. The timing of the initiation of cordgrass migration is coincident with an acceleration in the rate of sea-level rise recorded by the New York tide gauge. These results suggest that increased flooding associated with accelerating rates of sea-level rise has stressed high-marsh communities and promoted landward migration of cordgrass. If current rates of sea-level rise continue or increase slightly over the next century, New England salt marshes will be dominated by cordgrass. If climate warming causes sea-level rise rates to increase significantly over the next century, these cordgrass-dominated marshes will likely drown, resulting in extensive losses of coastal wetlands.
Donnelly, J PBertness, M DengResearch Support, Non-U.S. Gov't2001/11/29 10:00Proc Natl Acad Sci U S A. 2001 Dec 4;98(25):14218-23. Epub 2001 Nov 27.

Sedimentary evidence of intense hurricane strikes from New Jersey - Donnelly, J. P.; Roll, S.; Wengren, M.; Butler, J.; Lederer, R.; Webb, T. (Geology, 2001)
Nine Vibracores from the backbarrier marsh at Whale Beach, New Jersey, reveal three large-scale overwash deposits associated with historic and prehistoric storms. The uppermost and smallest overwash fan was deposited in the Ash Wednesday northeaster of March 5-8, 1962, A second more substantial overwash fan between 100 and 35 cm depth dates to the late eighteenth or early nineteenth century. This fan was most likely deposited during the 1821 hurricane, the only intense hurricane to make landfall in New jersey in the past 350 yr, A third, larger overwash fan between 200 and 300 cm depth was deposited between A.D. 1278 and 1438 and is likely the result of a prehistoric intense hurricane strike. The combination of historical and stratigraphic evidence indicates that two intense hurricanes (winds > 50 m s(-1)) have likely made landfall on the southern New Jersey coast in the past 700 yr, resulting in an annual landfall probability of 0.3%.
449elTimes Cited:102Cited References Count:14

Stratigraphy, paleoceanography, chronology, and paleoenvironment during deglaciation of eastern Maine, Report - Dorion, C. C.; Balco, G.; Kaplan, M. R.; Kreutz, K. J.; Wright, J.; Borns, H. W. (Deglacial History and Relative Sea Level Changes, Northern New England and adjacent Canada, 2001)
id: 1333

Tropical climate changes at millennial and orbital timescales on the Bolivian Altiplano - Baker, P. A.; Rigsby, C. A.; Seltzer, G. O.; Fritz, S. C.; Lowenstein, T. K.; Bacher, N. P.; Veliz, C. (Nature, 2001)
Tropical South America is one of the three main centres of the global, zonal overturning circulation of the equatorial atmosphere (generally termed the 'Walker' circulation1). Although this area plays a key role in global climate cycles, little is known about South American climate history. Here we describe sediment cores and down-hole logging results of deep drilling in the Salar de Uyuni, on the Bolivian Altiplano, located in the tropical Andes. We demonstrate that during the past 50,000 years the Altiplano underwent important changes in effective moisture at both orbital (20,000-year) and millennial timescales. Long-duration wet periods, such as the Last Glacial Maximum—marked in the drill core by continuous deposition of lacustrine sediments—appear to have occurred in phase with summer insolation maxima produced by the Earth's precessional cycle. Short-duration, millennial events correlate well with North Atlantic cold events, including Heinrich events 1 and 2, as well as the Younger Dryas episode. At both millennial and orbital timescales, cold sea surface temperatures in the high-latitude North Atlantic were coeval with wet conditions in tropical South America, suggesting a common forcing.
id: 388

Use of 14C and 13C natural abundances for evaluating riverine, estuarine, and coastal DOC and POC sources and cycling: Review and Synthesis - Raymond, P. A.; Bauer, J. E. (Org. Geochem, 2001)
id: 278

Use of bomb radiocarbon to validate otolith section ages of red snapper Lutjanus campechanus from the northern Gulf of Mexico - Baker, M. S.; Wilson, C. A. (Limnology and Oceanography, 2001)
The red snapper Lutjanus campechanus is an important recreational and commercial fish species in the northern Gulf of Mexico. Management approaches have varied in part because of uncertainty of their longevity. Snapper ages have been based on presumed otolith annuli; however, this methodology has not been validated for all age classes. A recent technique to validate otolith age utilizes the increase in oceanic C-14 resulting from atmospheric testing of nuclear bombs during the 1950s and 1960s. Analyses of annuli from living corals and fish otoliths from 1900 to the present have documented that elevated C-14 input has occurred throughout the world's oceans. We validated otolith section age estimates through accelerator mass spectrometry analysis of bomb-produced C-14 in red snapper (otoliths) hatched before, during, and after the nuclear testing periods. Delta C-14 data from the otoliths of red snapper with presumed birth dates between 1960 and 1973 clearly reflect the sharp increase in oceanic radiocarbon attributable to previous nuclear testing. Similarities between the otolith and nearby coral Delta C-14 chronologies suggest that annulus-based age estimates of red snapper are valid on average to within 1-3 yr. In addition, this study provides the first carbonate bomb radiocarbon time series from the northern Gulf of Mexico.
491vzTimes Cited:36Cited References Count:22

Were Rhyolitic Glasses in the Vedde Ash and in the North Atlantic's Ash Zone 1 produced by the Same Volcanic Eruption? - Bond, G. C.; Mandeville, C.; Hoffmann, S. (Quaternary Science Reviews, 2001)
New evidence from North Atlantic deep-sea sediment cores suggests that rhyolitic glass shards in Ash Zone 1 and in the Vedde Ash may not have been produced by the same eruption as has been widely assumed. Our argument is based on (1) a marine ice-rafted deposit approximately 1000 years older than the Vedde Ash contains rhyolitic shards with the same major element chemistry as the Vedde Ash itself and (2) coincidence of Ash Zone 1 with an abrupt increase in discharge of glacial icebergs into the North Atlantic. Hence, we cannot rule out the possibility that Vedde-like rhyolitic glasses were erupted onto Icelandic glaciers before eruption of the Vedde Ash, stored in the glacial ice, then dispersed by icebergs into the North Atlantic and deposited partly or entirely as Ash Zone 1. While not disproving that Ash Zone 1 and the Vedde Ash came from the same eruption, our findings indicate that further study is needed to establish the exact relation between the two ash deposits.
id: 253

Climate change in the northern American tropics since the last ice age: implications for environment and culture (Book Section) - Hodell, D. A.; Brenner, M.; Curtis, J. H. (Imperfect Balance: Landscape transformations in the Precolumbian Americas, 2000)
id: 198

d13C values and radiocarbon dates of microbial biomarkers as tracers fro carbon recycling in peat deposits - Pancost, R. D.; van Geel, B.; Baas, M.; Damste Sinninghe, J. S. (Geology, 2000)
id: 1330

Detecting holocene changes in thermohaline circulation - Keigwin, L. D.; Boyle, E. A. (Proc Natl Acad Sci U S A, 2000)
Throughout the last glacial cycle, reorganizations of deep ocean water masses were coincident with rapid millennial-scale changes in climate. Climate changes have been less severe during the present interglacial, but evidence for concurrent deep ocean circulation change is ambiguous.
Keigwin, L DBoyle, E A eng Research Support, U.S. Gov't, Non-P.H.S. 2000/03/04 09:00 Proc Natl Acad Sci U S A. 2000 Feb 15;97(4):1343-6.
Keywords: *Climate; *Plankton; Animals; Atlantic Ocean; carbon isotopes; ice; oxygen isotopes; time

Further evidence of abrupt Holocene drowning of the Black Sea shelf - Ballard, R. D.; Coleman, D. F.; Rosenberg, G. D. (Marine Geology, 2000)
A 1999 survey of the Black Sea continental shelf off the north central Turkish seaport of Sinop using a side-scan sonar, small remotely operated vehicles, and a series of dredge lowerings located, inspected and sampled an exposed high-energy paleoshoreline at a depth of 155 m. Radiocarbon dating of mollusk shells collected from this ancient beach revealed that the marine flooding of the Black Sea took place between 7460 and 6820 yr B.P. tall ages are reported in radiocarbon years, not calendar years, without correction for reservoir age or dendro-calibration) changing it from a lacustrine to marine environment. This relic surface remained in contact with the bottom waters of the Black Sea for a long period of time before being draped by a thin layer of sapropel mud. Wood samples recovered from this same location were very well preserved and yielded dates as old as 3580 yr B.P. (C) 2000 Elsevier Science B.V. All rights reserved.
380xeTimes Cited:71Cited References Count:8

High resolution proxy record of late Quaternary climate change from Soledad Basis, northwest Mexico, Abstract - Pike, J.; van Geen, A.; Beaufort, L.; Party, Shipboard Scientific (UK Pages, 2000)
id: 111

Holocene and recent rates of sediment accumulation in southern Lake Michigan - Colman, S. M.; King, J. W.; Jones, G. A.; Reynolds, R. L.; Bothner, M. H. (Quaternary Science Reviews, 2000)
id: 183

Installation of a 134-sample MC-SNICS ion source at NOSAMS and first results - von Reden, K. F.; Bellino, M.; Long, P.; Schneider, R. J.; Loger, R. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2000)
In April 1999, the National Ocean Sciences AMS (NOSAMS) facility received the shipment of a 134-sample MC-SNICS ion source from the National Electrostatics Corporation (NEC). It replaced one of the two 59-sample spherical ionizer sources (US-AMS Model 3090A, HVEE Model 846). In this paper, we will describe the adaptation of the NEC ion source to the US-AMS/HVEE recombinator injector at NOSAMS. This is the first lime that the two leading sputter ion source designs are directly comparable on the same system. We will present ion beam optics calculations for both in comparison with measured results. Once fully operational, the new ion source will assume all of the sputter sample measurements at NOSAMS, while the remaining 59-sample source will be replaced by the newly developed microwave gas ion source. One of the most desirable features of the MC-SNICS design is the smaller cathode geometry. At comparable extracted currents, the surface diameter of the pressed samples is reduced from 1.5 to 1 mm. A new, automatic sample pressing procedure is being developed for this design. This will improve the capability for preparing and analyzing smaller sputter samples (carbon weight <100 <mu>g). Our US-AMS cathodes showed considerable reduction in the extracted currents when the sample diameter was reduced to 1 mm, even with samples of normal size (>200 mug C). (C) 2000 Elsevier Science B.V. All rights reserved.
8th International Conference on Accelerator Mass SpectrometrySEP 06-10, 1999 VIENNA, AUSTRIA
Keywords: AMS; beam extraction/injection; C-14; ion sources; ocean; pacific

Isotopic evidence for Late Glacial and Holocene climatic change in the tropical Andes - Seltzer, G.; Rodbell, D.; Burns, S. (Geology, 2000)
id: 1338

Lake Erie: The Impact of Mid-Holocene Flooding by Upper Great Lake Waters - Kempthorne, R. A.; Barrera, E.; Coakley, J. P.; Palmer, D. F. (EOS, Transactions, American Geophysical Union, 2000)
id: 248

Late Pleistocene and Holocene geological evolution of the central Penobscot River Valley: Surficial geology, geoarchaeology, and water supply (Book Section) - Kelly, A. R.; Dorion, C. C.; Balco, G.; Dieffenbacher-Krall, A.; Garrett, P.; Locke, D.; Tolman, A. (Guidebook for Field Trips in Coastal and East-Central Maine: NEIGC 92nd Annual Meeting, 2000)
id: 152

A New Estimate of the Holocene Lowstand Level of Lake Titicaca and Implications for Tropical Paleohydrology - Cross, S. C.; Baker, P. A.; Seltzer, G. O.; Fritz, S. C. (The Holocene, 2000)
id: 1339

Paleoceanographic changes in the Southern Ocean (Pacific sector) during the last 14 Ka.--Poster - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 2000)
id: 1422

Postglacial and Late Holocene earthquakes on the Toe Jam strand of the Seattle fault, Bainbridge Island Washington - Nelson, A. R.; Johnson, S. Y.; Pezzopane, S. K.; Wells, R. E.; Kelsey, H. M.; Sherrod, B. L.; Koehler, R. D.; Bradley, L. A.; Bucknam, R. C.; LaPrade, W. T.; Cox, J. W.; Narwold, C. F. (Geological Society of America Abstracts with Programs, 2000)
id: 258

Radiocarbon dated Pinus sylvertis L. wood from beyond treeline on the Kola Peninsula, Russia - MacDonald, G. M.; Gervalis, B.; Snyder, J. A.; Tarasov, G. A.; Borisova, O. A. (The Holocene, 2000)
Radiocarbon dates were obtained from 24 samples of Pinus sylvestris L. (Scots pine) wood recovered from sites beyond the modern conifer tree-line on the Kola Peninsula of Russia. Twenty-one of the samples came from the shallow waters and eroding peats at the edges of two small lakes at 68°439N, 35°109E, located north of the modern conifer tree-line. Three samples came from a small pond located above the modern elevational limits of Pinus sylvestris at 68°259N, 35°199E. The radiocarbon dates indicate that pine trees grew approximately 20 km north of the mapped modern limits of the species from 6680 BP to 3830 BP. Pine trees were also growing some 40 m above their modern elevational limits between 5890 BP and 3450 BP. Nineteen of the samples date from 6680 BP to 5070 BP, suggesting that the density of trees north of the modern tree-line was greatest between 7000 and 5000 BP. The timing of tree-line advance and greatest density on the Kola Peninsula are in agreement with the results of similar studies from northern Fennoscandia which indicate that maximum northern and elevational extension of tree-line occurred between 7000 BP and 4000 BP. The general agreement between tree-line reconstructions suggests that the climatic changes that promoted mid-Holocene tree-line extension along the North Atlantic margins in northern Fennoscandia propagated eastward to the Kola Peninsula. The late timing of initial pine expansion on the Kola and in adjacent northern Fennoscandia remains problematic and may relate to lower winter insolation, temperature regimes in the adjacent oceans or slow rates of migration.
id: 376

Radiocarbon dating of Marion-Dufresne cores MD99-2204, 2207, and 2209, Chesapeake Bay - Colman, S. M.; Bratton, J. F.; Baucom, P. C. (Initial Report on IMAGES V Cruise of the Marion-Dufresne to the Chesapeake Bay June 20-22, 1999, 2000)
id: 1414

Turbidite Megabeds in an Oceanic Rift Valley Recording Jokulhlaups of Late Pleistocene Glacial Lakes of the Western United States - Zuffa, G. G.; Normark, W. R.; Serra, F.; Brunner, C. A. (Journal of Geology, 2000)
Escanaba Trough is the southernmost segment of the Gorda Ridge and is filled by sandy turbidites locally exceeding 500 m in thickness. New results from Ocean Drilling Program (ODP) Sites 1037 and 1038 that include accelerator mass spectrometry (AMS) 14C dates and revised petrographic evaluation of the sediment provenance, combined with high-resolution seismic-reflection profiles, provide a lithostratigraphic framework for the turbidite deposits. Three fining-upward units of sandy turbidites from the upper 365 m at ODP Site 1037 can be correlated with sediment recovered at ODP Site 1038 and Deep Sea Drilling Program (DSDP) Site 35. Six AMS 14C ages in the upper 317 m of the sequence at Site 1037 indicate that average deposition rates exceeded 10 m/k.yr. between 32 and 11 ka, with nearly instantaneous deposition of one approximately 60-m interval of sand. Petrography of the sand beds is consistent with a Columbia River source for the entire sedimentary sequence in Escanaba Trough. High-resolution acoustic stratigraphy shows that the turbidites in the upper 60 m at Site 1037 provide a characteristic sequence of key reflectors that occurs across the floor of the entire Escanaba Trough. Recent mapping of turbidite systems in the northeast Pacific Ocean suggests that the turbidity currents reached the Escanaba Trough along an 1100-km-long pathway from the Columbia River to the west flank of the Gorda Ridge. The age of the upper fining-upward unit of sandy turbidites appears to correspond to the latest Wisconsinan outburst of glacial Lake Missoula. Many of the outbursts, or jokulhlaups, from the glacial lakes probably continued flowing as hyperpycnally generated turbidity currents on entering the sea at the mouth of the Columbia River.
id: 162; J Geol. 2000 May;108(3):253-274.

Un registro de 8,000 anos del paleoclima del noroeste de Yucatan, Mexico - Brenner, M.; Leyden, B. W.; Curtis, J. H.; Medina-Gonzalez, R. M.; Dahlin, B. H. (Revista de la Universidad Autonoma de Yucatan, 2000)
id: 264
Keywords: Ciencias de la atmósfera; Geología; México; Paleoclima; Península de Yucatán; Yucatán

Use of bomb produced C-14 to validate otolith section age estimates of red snapper Lutjanus compechanus from the northern Gulf of Mexico, Artwork - Baker, M. Scott; Wilson, Charles A. (53rd Annual Gulf and Carribbean Fisheries Institute Meeting, 2000)

Use of Natural C-14 Measurements to Examine Benthic Food Webs - DeMaster, D. J.; Fornes, W. L.; Smith, C. R.; Plaia, G.; Blair, N. E.; Levin, L. A. (National AGU/ASLO Meeting, 2000)
id: 1367

87Sr/86Sr, delta 18O evolution of Phanerozoic seawater - Veizer, Jan; Davin, Ala; Azmy, Karem; Bruckschen, Peter; Buhl, Dieter; Bruhn, Frank; Carden, Giles A. F.; Diener, Andreas; Ebneth, Stefan; Godderis, Yves; Jasper, Torsten; Korte, Christoph; et al. (Chemical Geology, 1999)
id: 1603

Assessing the importance of subtropical waters in ventilating the Equatorial Pacific thermocline: A combined transient-tracer approach - Peacock, S.; Jenkins, W.; Key, R.; Broecker, W. (International WOCE Newsletter, 1999)
id: 1465

Climate and lake-level history of the northern Altiplano Bolivia, as recorded in Holocene sediments of the Rio Desaguadero - Baucom, P. C.; Rigsby, C. A. (Journal of Sedimentary Research, 1999)
Strata exposed in terraces and modern cutbanks along the Rio Desaguadero contain a variety of lithofacies that were deposited in four distinct facies associations. These facies associations document a history of aggradation and downcutting that is Linked to Holocene climate change on the Altiplano.Braided stream, meandering stream, deltaic and shoreline, and la custrine sediments preserved in multi-level terraces in the northern Rio Desaguadero valley record two high-water intervals: one between 4500 and 3900 yr BP and another between 2000 and 2200 yr BP. These wet periods were interrupted by three periods of fluvial downcutting, centered at approximately 4000 yr BP, 3600 Sr BP, and after 2000 yr BP. Braided-river sediments preserved in a single terrace level in the southern Rio Desaguadero valley record a history of nearly continuous fluvial sedimentation from at least 7000 yr BP until approximately 3200 yr BP that was followed by a single episode (post-3210 ST BP) of down cutting and lateral migration.The deposition and subsequent fluvial downcutting of the northern strata was controlled by changes in effective moisture that can he correlated to Holocene water level fluctuations of Lake Titicaca, The deposition and dissection of braided-stream sediments to the south are more likely controlled by a combination of base-level change and sediment input from the Rio Mauri.
A197atTimes Cited:30Cited References Count:61

Climate change in the Lake Valencia Basin, Venezuela, approximately 12,600 yr BP to present - Curtis, J. H.; Brenner, M.; Hodell, D. A. (The Holocene, 1999)
id: 197

Combined use of bomb radiocarbon and tritium to place constraints on the relative importance of northern- and southern- derived waters in ventilating the equatorial Pacific thermocline - Peacock, S.; Key, R.; Jenkins, W.; Broecker, W. (WOCE-AIMS Tracer Workshop, 1999)
id: 314

Deep-sea sedimentary record of the late Wisconsin cataclysmic floods from the Columbia River - Brunner, C. A.; Normark, W. R.; Zuffa, G. G.; Serra, F. (Geology, 1999)
New results from Ocean Drilling Program Site 1037 and U.S. Geological Survey high-resolution seismic-reflection profiles confirm the great thickness, fast deposition rate, distant source, and convolute path of turbidites that fill the Escanaba Trough, the rift valley of the southernmost segment of the Gorda Ridge. Accelerator mass spectrometry C-14 measurements provide the first direct dating of the Escanaba Trough turbidites, demonstrating an average deposition rate faster than 10 m/k.y. between 32 and 11 ka and as fast as 15 m/k.y. during the oxygen isotope stage 2 lowstand, In the upper 60 m of sediment, the petrology of turbidite sand beds, which are as much as 12 m thick, show that the dominant source for the turbidites is from the Columbia River, which is more than 800 km to the north, rather than from the much closer rivers of northern California. New high-resolution seismic-reflection profiles show that, except for areas of very recent volcanism, the entire Escanaba Trough below 3200 m water depth is floored by the turbidite sequence that was cored in the upper 60 m at Site 1037B, The ages of the upper 120 m of turbidites correspond with the ages of channeled scabland deposits associated with latest Quaternary jokulhlaups from glacial Lake Missoula, The age and source characteristics suggest that these megaturbidite beds in Escanaba Trough are most likely deposits formed by hyperpycnally generated turbidity currents as the largest of the Lake Missoula floods entered the sea.
193qfTimes Cited:40Cited References Count:19

Fractionation of hydrogen isotopes in lipid biosynthesis - Sessions, A. L.; Burgoyne, T. W.; Schimmelmann, A.; Hayes, J. M. (Organic Geochemistry, 1999)
Isotopic compositions of carbon-bound hydrogen in individual compounds from eight different organisms were measured using isotope-ratio-monitoring gas chromatography-mass spectrometry. This technique is capable of measuring D/H ratios at natural abundance in individual lipids yielding as little as 20 nmol of H-2, and is applicable to a wide range of compounds including hydrocarbons, sterols, and fatty acids. The hydrogen isotopic compositions of lipids are controlled by three factors: isotopic compositions of biosynthetic precursors, fractionation and exchange accompanying biosynthesis, and hydrogenation during biosynthesis. delta D values of lipids from the eight organisms examined here suggest that all three processes are important for controlling natural variations in isotopic abundance. n-Alkyl lipids are depleted in D relative to growth water by 113-262 parts per thousand, while polyisoprenoid lipids are depleted in D relative to growth water by 142-376 parts per thousand. Isotopic variations within compound classes (e.g., n-alkanes) are usually less than similar to 50 parts per thousand, but variations as large as 150 parts per thousand are observed among isoprenoid lipids from a single organism. Phytol is consistently depleted in D by up to 50 parts per thousand relative to other isoprenoid lipids. Inferred isotopic fractionations between cellular water and lipids are greater than those indicated by previous studies. (C) 1999 Elsevier Science Ltd. All rights reserved.
254efTimes Cited:281Cited References Count:26

Holocene Environmental changes in the Lake Erie Basis - Kepthorne, R. A.; Barrera, E.; Coakley, J. P.; Tevesz, M. J. S.; Miller, B. B. (International Association for Great Lakes Research Program and Abstract, 1999)
id: 249

Holocene surface faulting in the Seattle fault zone, Bainbridge Island, Washington - Nelson, A. R.; Pezzopane, S. K.; Bucknam, R. C.; Koehler, R. D.; Narwold, C. F.; Kelsey, H. M.; Sherrod, B. L.; LaPrade, W. T.; Wells, R. E.; Johnson, S. Y. (Seismological Research Letters, 1999)
id: 1404

Installation of a 134-Sample MC-SNICS Ion Source at NOSAMS and first results - von Reden, Karl F.; Bellino, Mary; Long, Patricia; Schneider, Robert J.; Loger, Roger (Accelerator Mass Spectrometry, Proceedings of the Eighth International Conference on Accelerator Mass Spectrometry, 1999)
id: 1724

Interdisciplinary environmental project probes Chesapeake Bay down to the core - Cronin, T.; Colman, S. M.; Willard, D.; Kerhin, R.; Holmes, C.; Karlsen, A.; Ishman, S.; Bratton, J. (EOS, 1999)
id: 185

Isotopic and molecular fractionation in combustion; three routes to molecular marker validation, including direct molecular 'dating' (GC/AMS) - Currie, L. A.; Klouda, G. A.; Benner, B. A.; Garrity, K.; Eglinton, T. I. (Atmospheric Environment, 1999)
The identification of unique isotopic, elemental, and molecular markers for sources of combustion aerosol has growing practical importance because of the potential effects of fine particle aerosol on health, visibility and global climate. It is urgent, therefore, that substantial efforts be directed toward the validation of assumptions involving the use of such tracers for source apportionment. We describe here three independent routes toward carbonaceous aerosol molecular marker identification and validation: (1) tracer regression and multivariate statistical techniques applied to field measurements of mixed source, carbonaceous aerosols; (2) a new development in aerosol (14)C metrology: direct, pure compound accelerator mass spectrometry (AMS) by off-line GC/AMS ('molecular dating'); and (3) direct observation of isotopic and molecular source emissions during controlled laboratory combustion of specific fuels. Findings from the combined studies include. independent support for benzo(ghi)perylene as a motor vehicle tracer from the first (statistical) and second (direct 'dating') studies; a new indication, from the third (controlled combustion) study, of a relation between (13)C isotopic fractionation and PAH molecular fractionation, also linked with fuel and stage of combustion; and quantitative data showing the influence of both fuel type and combustion conditions on the yields of such species as elemental carbon and PAH, reinforcing the importance of exercising caution when applying presumed conservative elemental or organic tracers to fossil or biomass burning field data as in the first study. Published by Elsevier Science Ltd.
208duTimes Cited:38Cited References Count:31

Late Wisconsian deep-sea sedimentary record from convulsive geologic events, Northeast Pacific - Serra, Francesca; Normark, William R.; Zuffa, Gian Gaspare; Brunner, Charlotte A. (IAS 19 Regional Meeting of Sedimentology, 1999)
id: 1471

Methane-consuming archaebacteria in marine sediments - Hinrichs, K. U.; Hayes, J. M.; Sylva, S. P.; Brewer, P. G.; DeLong, E. F. (Nature, 1999)
Large amounts of methane are produced in marine sediments but are then consumed before contacting aerobic waters or the atmosphere. Although no organism that can consume methane anaerobically has ever been isolated, biogeochemical evidence indicates that the overall process involves a transfer of electrons from methane to sulphate and is probably mediated by several organisms, including a methanogen (operating in reverse) and a sulphate-reducer (using an unknown intermediate substrate). Here we describe studies of sediments related to a decomposing methane hydrate. These provide strong evidence that methane is being consumed by archaebacteria that are phylogenetically distinct from known methanogens. Specifically, lipid biomarkers that are commonly characteristic of archaea are so strongly depleted in carbon-13 that methane must be the carbon source, rather than the metabolic product, for the organisms that have produced them. Parallel gene surveys of small-subunit ribosomal RNA (16S rRNA) indicate the predominance of a new archael group which is peripherally related to the methanogenic orders Methanomicrobiales and Methanosarcinales.
Hinrichs, K UHayes, J MSylva, S PBrewer, P GDeLong, E FengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.England1999/05/11 02:03Nature. 1999 Apr 29;398(6730):802-5.

The North Atlantic's 1-2 kyr climate rhythm: Relation to Heinrich events, Dansgaard/Oeschger cycles and the Little Ice Age (Book Section) - Bond, G. C.; Showers, W.; Elliot, M.; Evans, M.; Lotti, R.; Hajdas, I.; Bonani, G.; Johnson, S. (Mechanisms of global climate change at mellennial time scales, 1999)
id: 216

Paleoceanographic changes in the Southern Ocean (Pacific Sector) during the last 14 ka.- -Abstract - Morigo, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Langone, L. (Third International SO-JGOFS Symposium, 1999)
id: 1426

Paleoclimate of Southwestern China for the past 50,000 yr inferred from lake sediment records - Hodell, D. A.; Brenner, M.; Kanfoush, S. L.; Curtis, J. H.; Stoner, J. S.; Song, X. L.; Yuan, W.; Whitmore, T. J. (Quaternary Research, 1999)
Long sediment cores (12.5 and 13.5 m) from two lakes in Yunnan Province were used to infer the paleoclimate of southwest China over the past 50,000 yr, During the Holocene and marine isotope stage (MIS 3), bio-induced carbonate precipitation and organic matter (OM) production was high, suggesting warm temperatures and high primary productivity. In contrast, sediment inorganic carbon (IC) and organic carbon (OC) concentrations were low in last glacial deposits from 38,000 to 12,000 cal yr B.P., indicating cool temperatures and low productivity. The 50,000-yr record has alternating peaks of carbonate and coarse-grain (>38 mu m) quartz that reflect warm, moist interglacial or interstadial conditions alternating with cold, dry glacial or stadial conditions, respectively. Spectral analysis of the carbonate and quartz signals reveals power concentrated at periods of 7200 and 8900 cal yr, respectively, that may reflect a nonlinear climate response to precessional forcing at a time of reduced eccentricity modulation (McIntyre and Molfino, 1996). Oxygen isotope values of calcite from Yunnan lake cores indicate the summer monsoon was weak during the last glaciation from 50,000 to 12,000 cal yr B.P. The summer monsoon intensified between 12,000 and 8000 cal yr B.P., but weakened gradually in response to insolation forcing during the mid-to-late Holocene. Our results support the Overpeck ef al. (1996) model that posits a weak summer monsoon during the last glaciation that responded nonlinearly to insolation forcing when its intensity was affected by Eurasian snow cover and ice-sheet extent. The summer monsoon intensified and responded linearly to seasonal insolation forcing in the Holocene when ice volume diminished. (C) 1999 University of Washington.
255ltTimes Cited:85Cited References Count:58

Paleoenvironmental changes during the last 17,000 years in western Patagonia - Markgraf, V.; Bianchi, M. M. (Bamberger Geographische Schriften, 1999)
id: 1382

Planktic foraminifera and oxygen isotope as proxies for paleoceanographic reconstruction in the Southern Ocean during the last deglacial time--Abstract - Morigi, C.; Capotondi, L.; Ravaioli, M.; Giglio, F.; Turi, B.; Brilli, M.; Frignani, M.; Langone, L. (Convegno Glaciologia e Paleoclima, 1999)
id: 1425

Radiocarbon analysis of Pinus lagunae tree rings: Implications for tropical dendrochronology - Biondi, F. (Radiocarbon, 1999)
A promising species for tropical dendrochronology is Pinus lagunae, a pine tree found in Baja California Sur (Mexico) around lat 23.5 degrees N. In 1995, we sampled a total of 27 wood cores from 13 Pinus lagunae trees in Sierra La Victoria (23 degrees 36'N, 109 degrees 56'W),just north of Sierra La Laguna, at an elevation of 1500-1600 m. Selected trees were locally dominant, but their ring-width patterns could not be crossdated. To test the hypothesis that visible growth layers in Pinus lagunae are formed annually, we measured radiocarbon amounts in individual rings by means of accelerator mass spectrometry (AMS). Twenty-three C-14 measurements were used to trace the location of the 1963-64 "bomb spike" in 3 wood increment cores. By comparing the location of that Delta(14)C extreme with the number of visible radial wood increments, it was possible to conclude that 2 cores had a number of locally absent rings, while the 3rd one included a few years with more than one growth layer. Therefore, ring-width patterns of sampled Pinus lagunae were not consistent from one tree to another, most likely because of climatic regime in combination with microsite features. While the possibility of generating Pinus lagunae tree-ring chronologies cannot entirely be ruled out, the development of dendrochronological proxy records of climate from coniferous species in tropical North America should focus on species and sites that experience a more pronounced seasonality.
289tcTimes Cited:16Cited References Count:31

Reconstructing the oceanic 13C Suess effect - Sonnerup, R. E.; Quay, P. D.; McNichol, A. P.; Bullister, J. L.; Westby, T. A.; Anderson, H. L. (Global Biogeochemical Cycles, 1999)
id: 1710

Registro micropaleontologico de los cambios naturales y antropicos (500 anos BP-presente) en us ecosistema de lagoon (Doninos, NO Peninsula Iberica) - Bao, R.; Santos, L.; Sanchez-Goni, M. F. (Actas XV Jornadas Sociedad Espanola de Paleontologia, 1999)
id: 151

Stable isotope and trace element composition of ostracodes from Lake Issyk Kul, Kyrgyzstan - Ricketts, R. D.; Rasmussen, K. A.; Brown, E. T.; Johnson, T. J. (American Geophysical Union Fall Meeting, 1999)
id: 1366

A 25,000-year tropical climate history from bolivian ice cores - Thompson, L. G.; Davis, M. E.; Mosley-Thompson, E.; Sowers, T. A.; Henderson, K. A.; Zagorodnov, V. S.; Lin, P.; Mikhalenko, V. N.; Campen, R. K.; Bolzan, J. F.; Cole-Dai, J.; Francou, B. (Science, 1998)
Ice cores that were recovered from the summit of Sajama mountain in Bolivia provide carbon-14-dated tropical records and extend to the Late Glacial Stage (LGS). Oxygen isotopic ratios of the ice decreased 5.4 per mil between the early Holocene and the Last Glacial Maximum, which is consistent with values from other ice cores. The abrupt onset and termination of a Younger Dryas-type event suggest atmospheric processes as the probable drivers. Regional accumulation increased during the LGS, during deglaciation, and over the past 3000 years, which is concurrent with higher water levels in regional paleolakes. Unlike polar cores, Sajama glacial ice contains eight times less dust than the Holocene ice, which reflects wetter conditions and extensive snow cover.
ThompsonDavis Mosley-Thompson Sowers Henderson Zagorodnov Lin Mikhalenko Campen Bolzan Cole-Dai Francou eng 1998/12/04 03:02 Science. 1998 Dec 4;282(5395):1858-64.

Carbon cycling in sediments from the western equatorial Atlantic: Stable and radiocarbon isotopes in pore waters on the Ceara Rise - McNichol, A. P.; McCorkle, D. C.; Martin, W. R.; Berry, J. N. (EOS, 1998)
id: 108

Challenges in application of radiocarbon dating of organic carbon phases in opal-rich marine sediments from the Southern Ocean - Zheng, Y.; Anderson, R. F.; Froelich, P. N.; Beck, W.; McNichol, A. P.; Guilderson, T. (Trans. AGU 79, 1998)
id: 266

Controls of chemical and isotopic composition of Lake water, Peten, Guatemala and implications for Holocene climatic variability in Central America. Abstracts with Programs - Martin, J. B.; Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H. (Geological Society of America Annual Meeting, 1998)
id: 140

Cultural and climatic history of Coba, a lowland Maya city in Quintana Roo, Mexico - Leyden, B. W.; Brenner, M.; Dahlin, B. H. (Quaternary Research, 1998)
Lake Coba, within the archaeological site of Coba, provides evidence bearing on lowland Maya development, Palynological and geochemical data record multidecadal precipitation cycles from a 8.80-m, >8370-yr lake-sediment sequence terminating on bedrock. Late Classic sedimentation rates are rapid, but an anthropogenically derived colluvium layer is lacking, Initial vegetation was medium semi-deciduous and swamp forest. Forest clearance began 1650 B.C. (Early Preclassic) and maize first occurred at 850 B.C. (Middle Preclassic). Lakeside milpas existed until A.D. 720 (Late Classic) and then were moved from the city center as urbanization intensified and Lake Coba was diked as a reservoir. Coba was at most briefly vacated during the Classic Collapse and was abandoned after A.D. 1240, although some habitation persisted. The paleoecological record matches the archaeological history for Coba, but pervasive disturbance muted the climatic signal, as the Late Classic drought is barely evident. The question whether economic trees were maintained within the city is unresolved, Maize cultivation allowed the Maya to develop a complex society and support a large population, but dependence on maize was ultimately doomed by variable rainfall. Precipitation in extreme years was insufficient to support crops, while native vegetation was not directly affected by drought that devastated Maya agriculture, (C) 1998 University of Washington.
Yz880Times Cited:59Cited References Count:46

Early diagenetic minerals and variables influencing their distributions in two long cores (>40m), Mississippi River delta plain - Bailey, A. M.; Roberts, H. H.; Blackson, J. M. (Journal of Sedimentary Research, 1998)
Two long (>40 m) continuous push cores of sediments from the Mississippi Delta Plain, one at a northern freshwater site and one at a southern marine-influenced site, have provided samples of individual concretions and homogenized bulk samples for a study of early diagenesis. Early (<10,000 y) diagenetic minerals are abundant and include: siderite>pyrite>calcite nearly equal dolomite>vivianite approximately hematite. Siderite formed postburial and contains bands of clastic minerals and accessory diagenetic calcite and dolomite, as well as Ca, Mg, and Mn substituted in the lattice. Values for delta 13 C increase with increasing depth to +11 per mil (PDB) at a depth of 40 m, reflecting the increasing role of methanogenesis with depth. From analyses of bulk samples, pyrite concentrations are higher in organic-rich horizons, do not vary appreciably with depth below one meter when adjusted for organic-carbon control, and are generally higher in the marine-influenced core than at the freshwater site. Conversely, concentrations of siderite are higher in fine-grained siliciclastic horizons, increase with depth to about 20 m, and do not vary with the extent of marine influence in these cores. To a first approximation, distributions of pyrite appear to be controlled by variations in organic carbon concentration in sulfate-sufficient systems that formed through marine incursion into organic-rich layers that cap sediment packages in the deltaic system. Residual pyritic S is sulfate-controlled and lower in the northern, more freshwater organic-rich sediments. Siderite formation appears to be focused in sulfate-deficient systems that formed when siliciclastic wedges that constitute the central parts of sediment packages prograded into lacustrine or bay environments. Low sulfate levels in these horizons in both cores facilitated similar levels of siderite. A juxtaposition of marine versus freshwater diagenetic mineral suites in adjacent horizons resulted from these interactions between physical and geochemical processes.
id: 5

Early to middle Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala - Rosenmeier, M. F.; Hodel, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (EOS: Transactions American Geophysical Union, 1998)
id: 1209

Geoforma Ediciones, Logrono, Barcelona - Valero-Garces, B. L.; Matri Bono, C.; Kelts, K. (Investigaciones recientes de la Geomorfologia esponola, 1998)
id: 384

Glacioisostasy and lake-level change at Moosehead lake, Maine - Balco, G.; Belknap, D. F.; Kelley, J. T. (Quaternary Research, 1998)
Reconstructions of glacioisostatic rebound based on relative sea level in Maine and adjacent Canada do not agree well with existing geophysical models. In order to understand these discrepancies better, we investigated the lake-level history of 40-km-long Moosehead Lake in northwestern Maine. Glacioisostasy has affected the level of Moosehead Lake since deglaciation ca. 12,500 C-14 yr B.P. Lowstand features at the southeastern end and an abandoned outlet at the northwestern end of the lake indicate that the lake basin was tilted down to the northwest, toward the retreating ice sheet, by 0.7 m/km at 10,000 C-14 yr B.P. Water level then rose rapidly in the southeastern end of the lake, and the northwestern outlet was abandoned, indicating rapid relaxation of landscape tilt. Lowstand features at the northwestern end of the lake suggest that the lake basin was tilted to the southeast at ca. 8750 C-14 yr B.P., possibly as the result of a migrating isostatic forebulge. After 8000 C-14 yr B.P., water level at the southeastern end was again below present lake level and rose gradually thereafter. We found no evidence suggesting that postglacial climate change significantly affected lake level. The rebound history inferred from lake-level data is consistent with previous interpretations of nearby relative sealevel data, which indicate a significantly steeper and faster-moving ice-proximal depression and ice-distal forebulge than geophysical models predict. (C) 1998 University of Washington.
Zm315Times Cited:9Cited References Count:46

High-precision Measurements of 14C as a Circulation Tracer in the Pacific, Indian, and Southern Oceans with Accelerator Mass Spectrometry (AMS) - von Reden, K. F.; Peden, J. C.; Schneider, R. J.; Bellino, M.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Morin, T.; Stuart, D.; Hayes, J. M.; et al. (8th International Conference on Heavy Ion Accelerator Technology, 1998)
id: 1636

High-precision radiocarbon age calibration for terrestrial and marine samples - Stuiver, M.; Reimer, P. J.; Braziunas, T. F. (Radiocarbon, 1998)
Single-year and decadal radiocarbon tree-ring ages are tabulated and discussed in terms of C-14 age calibration. The single-year data form the basis of a detailed 14C age calibration curve for the cal AD 1510-1954 interval ("cal" denotes calibrated). The Seattle decadal data set (back to 11,617 cal sp, with 0 sp = AD 1950) is a component of the integrated decadal INTCAL98 C-14 age curve (Stuiver et al. 1998). Atmospheric C-14 ages can be transformed into C-14 ages of the global ocean using a carbon reservoir model. INTCAL98 C-14 ages, used for these calculations, yield global ocean C-14 ages differing slightly from previously published ones (Stuiver and Braziunas 1993b). We include discussions of offsets, error multipliers, regional C-14 age differences and marine C-14 age response to oceanic and atmospheric forcing.
155qrTimes Cited:705 Cited References Count:31
Keywords: ad 1950-500 bc; c-14 data; decadal calibration; reservoir ages; time scale

How much deep water is formed in the Southern Ocean? - Broecker, W. S.; Peacock, S. L.; Walker, S.; Weiss, R.; Fahrbach, E.; Schroeder, M.; Mikolajewicz, U.; Heinze, C.; Key, R.; Peng, T. H.; Rubin, S. (Journal of Geophysical Research-Oceans, 1998)
Three tracers are used to place constraints on the production rate of ventilated deep water in the Southern Ocean. The distribution of the water mass tracer PO4* ("phosphate star") in the deep sea suggests that the amount of ventilated deep water produced in the Southern Ocean is equal to or greater than the outflow of North Atlantic Deep Water from the Atlantic. Radiocarbon distributions yield an export flux of water from the North Atlantic which has averaged about 15 Sv over the last several hundred years. CFC inventories are used as a direct indicator of the current production rate of ventilated deep water in the Southern Ocean. Although coverage is as yet sparse, it appears that the CFC inventory is not inconsistent with the deep water production rate required by the distributions of PO4* and radiocarbon. It has been widely accepted that the major part of the deep water production in the Southern Ocean takes place in the Weddell Sea. However, our estimate of the Southern Ocean ventilated deep water flux is in conflict with previous estimates of the flux of ventilated deep water from the Weddell Sea, which lie in the range 1-5 Sv. Possible reasons for this difference are discussed.
Zz547Times Cited:115Cited References Count:44

Late Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala and implications for Maya cultural evolution; Procedings of the PEP 1 - Rosenmeier, M. F.; Hodell, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (PEP 1 (Pole-Equator-Pole, Paleoclimate of the Americas), 1998)
id: 141

Le torbiditi dell'Escanaba Trough (Juan de Fuca Plate, Pacifico nordorientale): registrazione sedimentaria di piene fluviali catastrofiche del Fiume Columbia durante le fasi di deglaciazione tardo quaternaria - Brunner, C. A.; Normark, W. R.; Zuffa, G. G.; Serra, F. (Giornale di Geologia, 1998)
id: 1470

Manzala lagoon, Nile delta, Egypt: modern sediment accumulation based on radioactive tracers - Benninger, L. K.; Suayah, I. B.; Stanley, D. J. (Environmental Geology, 1998)
This study was undertaken to determine whether recent anthropogenic changes in the Nile basin have affected the modern rate of sediment accumulation in the Nile delta. Excess (210)pb, Cs-137, and Pu-239,Pu-240 were used to develop a sediment chronology for a core from central Manzala lagoon, the delta sector which has had the highest average rate of sediment accumulation during the Holocene (to about 0.7 cm year(-1)). Excess Pb-210 was detected in the top 32 cm of the core, yielding an accumulation rate of 1.2 cm year(-1), higher than the mean rate for the Holocene. A high Cs-137/Pu-239,Pu-240 ratio requires a reactor source (possibly Chernobyl) for these nuclides. Low concentrations of excess (210)pb and weapons-fallout nuclides precluded recognition of changes in sediment accumulation rate in Manzala lagoon during this century and may limit the use of tracer radionuclides for modern sediment chronology in the Nile delta.
id: 1283; Zq055 Times Cited:9 Cited References Count:37

A multi-proxy study of Holocene environmental change in the Maya lowlands of Peten, Guatemala - Curtis, J. H.; Brenner, M.; Hodell, D. A.; Balser, R. A.; Islebe, G. A.; Hooghiemstra, H. (Journal of Paleolimnology, 1998)
We used multiple variables in a sediment core from Lake Peten-Itza, Peten, Guatemala, to infer Holocene climate change and human influence on the regional environment. Multiple proxies including pollen, stable isotope geochemistry, elemental composition, and magnetic susceptibility in samples from the same core allow differentiation of natural versus anthropogenic environmental changes. Core chronology is based on AMS (14)C measurement of terrestrial wood and charcoal and thus avoids the vagaries of hard-water-lake error. During the earliest Holocene, prior to similar to 9000 (14)C yr BP, the coring site was not covered by water and all proxies suggest that climatic conditions were relatively dry. Water covered the coring site by similar to 9000 (14)C yr BP, coinciding with filling of other lakes in Peten and farther north on the Yucatan Peninsula. During the early Holocene (similar to 9000 to similar to 6800 (14)C yr BP), pollen data suggest moist conditions, but high delta(18)O values are indicative of relatively high E/P. This apparent discrepancy may be due to a greater fractional loss of the lake's water budget to evaporation during the early stages of lake filling. Nonetheless, conditions were moist enough to support semi-deciduous lowland forest. Decrease in delta(18)O values and associated change in ostracod species at similar to 6800 (14)C yr BP suggest a transition to even moister conditions. Decline in lowland forest taxa beginning similar to 5780 (14)C yr BP may indicate early human disturbance. By similar to 2800 (14)C yr BP, Maya impact on the environment is documented by accelerated forest clearance and associated soil erosion. Multiple proxies indicate forest recovery and soil stabilization beginning similar to 1100 to 1000 (14)C yr BP, following the collapse of Classic Maya civilization.
Zj856Times Cited:92Cited References Count:96

Physical controls on dissolved inorganic radiocarbon variability in the California Current - Masiello, C. A.; Druffel, E. R. M.; Bauer, J. E. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 1998)
We present depth profiles of Delta(14)C and delta(13)C Of dissolved inorganic carbon (DIC) at Station M in the Eastern North Pacific. Several seasonal profiles are presented for the time period between 1991 and 1996. Comparison with GEOSECS data clearly shows changes in ocean radiocarbon profiles since 1973. The Delta(14)C Of DIC shows the most variability at depths of 450, 85, and 25 m, and the lowest variability at depths of 1600 and 2500 m. The largest variability in DIC Delta(14)C occurs at 450 m, a depth marked by large fluctuations in the radiocarbon signatures of the source waters. The likely controls of DIC Delta(14)C variability are physical changes in the circulation of the California Current System. A simple two-box model is used to show the importance of wind driven mixing at the surface. We discuss the likely effects of mesoscale eddies and ENSO on the DIC Delta(14)C values at this site. We also show that remineralization of organic carbon (dissolved or particulate) is not responsible for the variability in the Delta(14)C Of DIC observed at Station M. (C) 1998 Elsevier Science Ltd. All rights reserved.
102ttTimes Cited:21Cited References Count:43

Quantitative Production of H2 by Pyrolysis of Gas Chromatographic Effluents - Burgoyne, Thomas W.; Hayes, John M. (Analytical Chemistry, 1998)
id: 1731

Radiometrically determined sedimentary fluxes in the sub-polar North Atlantic during the last 140,000 years - McManus, J. F.; Anderson, R. F.; Broecker, W. S.; Fleisher, M. Q.; Higgins, S. M. (Earth and Planetary Science Letters, 1998)
We have examined the record of sediment input during the last 140000 years in a deep-sea core from 49 degrees 27'N, 22 degrees 16'W in the eastern North Atlantic. Using uranium-series disequilibria to constrain time, we have calculated mass fluxes of total sediment, as well as mass and particle fluxes of major sedimentary components. Sediment accumulation rates were generally lower and relatively constant during broadly defined interglacial intervals, driven primarily by the burial of biogenic material. Accumulation rates were higher and more variable during glacial intervals, and were influenced primarily by terrigenous material. Peaks in bulk mass fluxes were associated with particular episodes (Heinrich events) within the last glacial and during each of the last two deglaciations. The flux of ice-rafted debris, as uniquely identified by coarse detrital fragments, was higher during layers representing each of the glacial Heinrich events, with modest increases during events H3 and H6 and dramatic increases during the others, confirming the widespread interpretation of these layers as episodes of enhanced iceberg delivery. The burial flux of foraminifera was markedly lower during each of the glacial Heinrich events, also confirming the original identification of these layers as barren intervals. Ice-rafting events within marine isotope stage 5 left neither a large detrital nor biogenic flux imprint at our study site. Variations in the burial rates of non-carbonate sediments were largely responsible for overall changes in sediment accumulation throughout the last climate cycle. Ice-rafting was apparently an important delivery mechanism for this terrigenous material. The instantaneous chronometer established here for the last 140000 years in the subpolar North Atlantic allows the transformation of existing and subsequent data from relative values to absolute burial fluxes. (C) 1998 Elsevier Science B.V.
Ze160Times Cited:70Cited References Count:55

Status Report of the National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution: Operations and Recent Developments - Bellino, M.; von Reden, K. F.; Schneider, R. J.; Peden, J. C.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Odegaard, A. P.; Stuart, D.; Handwork, S.; et al. (15th International Conference on the Applications of Accelerators in Research and Industry, 1998)
id: 1647

Three Holocene tephras identified in lacustrine sediment cores from the Wonder Lake area, Denali National Park and Preserve AK - Child, J. C.; Beget, J.; Werner, A. (Arctic and Alpine Research, 1998)
id: 235

Un registro de 6,000 anos de manifestaciones intensas del fenomeno de El Nino en sedimentos de lagunas de las Islas Galapagos - Steinitz-Kannan, M.; Riedinger, M. A.; Last, W. M.; Brenner, M.; Miller, M. C. (Bulletin de l'Institut Francais d'Etudes Andines, 1998)
id: 196

A 3,500 14C yr. high-resolution record of lake level changes in Lake Titicaca, South America - Abbott, M. B.; Binford, M. W.; Brenner, M.; Kelts, K. R. (Quaternary Research, 1997)
Sediment cores collected from the southern basin of Lake Titicaca (Bolivia/Peru) on a transect from 4.6 m above overflow level to 15.1 m below overflow level are used to identify a new century-scale chronology of Holocene lake-level variations. The results indicate that lithologic and geochemical analyses on a transect of cores can be used to identify and date century-scale lake-level changes. Detailed sedimentary analyses of subfacies and radiocarbon dating were conducted on four representative cores. A chronology based on 60 accelerator mass spectrometer radiocarbon measurements constrains the timing of water-level fluctuations. Two methods were used to estimate the14C reservoir age. Both indicate that it has remained nearly constant at ∼25014C yr during the late Holocene. Core studies based on lithology and geochemistry establish the timing and magnitude of five periods of low lake level, implying negative moisture balance for the northern Andean altiplano over the last 3500 cal yr. Between 3500 and 3350 cal yr B.P., a transition from massive, inorganic-clay facies to laminated organic-matter-rich silts in each of the four cores signals a water-level rise after a prolonged mid-Holocene dry phase. Evidence of other significant low lake levels occurs 2900–2800, 2400–2200, 2000–1700, and 900–500 cal yr B.P. Several of the low lake levels coincided with cultural changes in the region, including the collapse of the Tiwanaku civilization.
id: 173; jpc

Climate variation and the rise and fall of an Andean civilization - Binford, M. W.; Kolata, A. L.; Brenner, M.; Janusek, J. W.; Seddon, M. T.; Abbott, M.; Curtis, J. H. (Quaternary Research, 1997)
Paleolimnological and archaeological records that span 3500 years from Lake Titicaca and the surrounding Bolivian-Peruvian altiplano demonstrate that the emergence of agriculture (ca. 1500 B.C.) and the collapse of the Tiwanaku civilization (ca. A.D. 1100) coincided with periods of abrupt, profound climate change, The timing and magnitude of climate changes are inferred from stratigraphic evidence of lake-level variation recorded in C-14-dated lake-sediment cores. Paleolake levels provide estimates of drainage basin water balance. Archaeological evidence establishes spatial and temporal patterns of agricultural field use and abandonment. Prior to 1500 B.C., aridity in the altiplano precluded intensive agriculture. During a wetter period from 1500 B.C. to A.D. 1100, the Tiwanaku civilization and its immediate predecessors developed specialized agricultural methods that stimulated population growth and sustained large human settlements, A prolonged drier period (ca. A.D. 1100-1400) caused declining agricultural production, field abandonment, and cultural collapse. (C) 1997 University of Washington.
Wu887Times Cited:148Cited References Count:53

Consistent Fractionation of 13C in Nature and in the Laboratory: Growth-rate Effects in Some Haptophyte Algae - Bidigare, Robert R.; Fluegge, Arnim; Freeman, Katherine H.; Hanson, Kristi L.; Hayes, John M.; Hollander, David; Jasper, John P.; King, Linda L.; Laws, Edward A.; Milder, Jeffrey; Millero, Frank J.; Pancost, Richard; et al. (Global Biogeochemical Cycles, 1997)
The carbon isotopic fractionation accompanying formation of biomass by alkenone-producing algae in natural marine environments varies systematically with the concentration of dissolved phosphate. Specifically, if the fractionation is expressed by єP ≈ δe − δp, where δe and δp are the δ13C values for dissolved CO2 and for algal biomass (determined by isotopic analysis of C37 alkadienones), respectively, and if Ce is the concentration of dissolved CO2, μmol kg−1, then b = 38 + 160*[PO4], where [PO4] is the concentration of dissolved phosphate, μM, and b = (25 − єp)Ce. The correlation found between b and [PO4] is due to effects linking nutrient levels to growth rates and cellular carbon budgets for alkenone-containing algae, most likely by trace-metal limitations on algal growth. The relationship reported here is characteristic of 39 samples (r2 = 0.95) from the Santa Monica Basin (six different times during the annual cycle), the equatorial Pacific (boreal spring and fall cruises as well as during an iron-enrichment experiment), and the Peru upwelling zone. Points representative of samples from the Sargasso Sea ([PO4] ≤ 0.1 μM) fall above the b = f[PO4] line. Analysis of correlations expected between μ (growth rate), єp, and Ce shows that, for our entire data set, most variations in єp result from variations in μ rather than Ce. Accordingly, before concentrations of dissolved CO2 can be estimated from isotopic fractionations, some means of accounting for variations in growth rate must be found, perhaps by drawing on relationships between [PO4] and Cd/Ca ratios in shells of planktonic foraminifera.
id: 1727

Corrections for contamination background in AMS 14C measurements - Brown, T. A.; Southon, J. R. (Nuclear Instruments and Methods in Physics Research B, 1997)
Measurements of ratios were made on samples of Oxalic Acid and 14C “dead” materials spanning the mass range from 10 μg to ∼1 mg. These measurements have allowed the determination of both the amount, and the 14C content, of the contaminant carbon introduced during sample processing in our laboratory. These data were used to correct measured ratios obtained from ANU Sucrose and “∼ one-half-life old” test samples for the influence of the contaminant. The test samples spanned the 10 μg to ∼1 mg mass range and the corrections were made using three different formulae. The results obtained from these calculations allow the accuracy of these background correction formulae to be evaluated.
id: 1493

Determination of the radiocarbon ages of individual PAH extracted from urban aerosol and marine sediment - Pearson, A.; Eglinton, T. I.; McNichol, A. P.; Currie, L. A.; Schneider, R. J.; von Reden, K. F.; Benner, B. A.; Wise, S. A. (16th International Radiocarbon Conference, 1997)
id: 951

The first trans-Arctic 14C section: comparison of the mean ages of the deep waters in the Eurasian and Canadian basins fo the Arctic Ocean - Schlosser, Peter; Kromer, Bernd; Ekwurzel, Brenda; Bonisch, Gerhard; McNichol, Ann; Schneider, Robert; von Reden, Karl; Ostlund, H. G.; Swift, J. H. (Nuclear Instruments and Methods in Physics Research, 1997)
id: 67

The first trans-Arctic 14C section: comparison of the mean ages of the deep waters in the Eurasian and Canadian Basins of the Arctic Ocean; in Proceedings of the 7th International Conference on Accelerator Mass Spectrometry - Schlosser, P.; Kromer, B.; Ekwurzel, B.; Bonisch, G.; McNichol, A.; Schneider, R.; von Reden, K.; Ostlund, H.; Swift, J. (Nuclear Instruments and Methods, 1997)
id: 1751

A high-resolution paleoenvironmental record from Bainbridge Crater Lake, Galapagos Islands - Reidinger, M.; Steinitz-Kannan, M.; Last, W.; Brenner, M. (Wurzburger Geographische Manuscripte, Heft, 1997)
id: 356

Holocene Evolution of Lake Erie Environments - McCambridge, C.; Barrera, E.; Tevesz, M.; Fuller, J. (Geological Society of America, Abstracts with Programs, 1997)
id: 250

Paleoclimatic implications of Holocene lake-level fluctuations, Owasco Lake, New York: Comment - Balco, G.; Belknap, D. F.; Kelley, J. T. (Geology, 1997)
Wu319Times Cited:0Cited References Count:7

Paleogeography and sedimentary evolution of Nauset Marsh estuary, Cape Cod, MA. Final Report to the National Park Service - Allen, J. R.; Boothroyd, J. (1997)
id: 1311

Preliminary results of the first scientific drilling on Lake Baikal, Buguldeika site, southeastern Siberia - Colman, S.; Grachev, M.; Hearn, P.; Horie, S.; Kawai, T.; Kuzmin, M.; Logachov, N.; Fialkov, V.; Gorigljad, A.; Tomilov, B.; Khakhaev, B.; Kochikov, S.; et al. (Quaternary International, 1997)
The Baikal Drilling Project (BDP) is a multinational effort to investigate the paleoclimatic history and tectonic evolution of the Baikal sedimentary basin during the Late Neogene. In March 1993 the Baikal drilling system was successfuly deployed from a barge frozen into position over a topographic high, termed the Buguldeika saddle, in the southern basin of Lake Baikal. The BDP-93 scientific team, made up of Russian, American and Japanese scientists, successfully recovered the first long (>100 m) hydraulic piston cores from two holes in 354 m of water. High quality cores of 98 m (Hole 1) and 102 m (Hole 2), representing sedimentation over the last 500,000 years, were collected in 78 mm diameter plastic liners with an average recovery of 72% and 90%, respectively. Magnetic susceptibility logging reveals an excellent hole-to-hole correlation. In this report the scientific team describes the preliminary analytical results from BDP-93 hole 1 cores. Radiocarbon dating by accelerator mass spectrometry provides an accurate chronology for the upper portion of Hole 1. Detailed lithologic characteristics, rock magnetic properties and inorganic element distributions show a significant change to the depositional environment occuring at 50 m subbottom depth, approximately 250,000 BP. This change may be due to uplift and rotation of the horst block in the Buguldeika saddle. The sedimentary section above 50 m is pelitic with varve-like laminae, whereas the section below 50 m contains a high proportion of sand and gravel horizons often organized into turbidite sequences. Accordingly, high resolution seismic records reveal a change in sonic velocity at this depth. It is inferred that sedimentation prior to 250 ka BP was from the west via the Buguldeika river system. After 250 ka BP the Buguldeika saddle reflects an increase in hemipelagic sediments admired with fine-grained material from the Selenga River drainage basin, east of Lake Baikal. Variations in the spore-pollen assemblage, diatoms, biogenic silica content, rock magnetic properties, clay mineralogy and organic carbon in the upper 50 m of BDP-93-1 reveal a detailed record of climate change over approximately the last 250,000 years. These variables alternate in a pattern characteristic of glacial/interglacial climatic fluctuations. The present age model suggests that the climate signal recorded in Lake Baikal sediments is similar to Late Quaternary signals recorded in Chinese loess sections and in marine sediments. Copyright (C) 1996 INQUA/Elsevier Science Ltd
Vq100Times Cited:44 Cited References Count:29
Keywords: asia; tectonics

Productivity-induced sulphur enrichment of hydrocarbon-rich sediments from the Kimmeridge Clay Formation - Lallier-Verges, E.; Hayes, J. M.; Boussafir, M.; Zaback, D. A.; Tribovillard, N. P.; Connan, J.; Bertrand, P. (Chem Geol, 1997)
This work aims to highlight the relationship between primary productivity, sulphate reduction and organic carbon preservation in cyclic marine sediments from the Kimmeridge Clay Formation. A concomitant increase of the total sulphur content with the preserved organic content (TOC), shows the progressive supply of both metabolisable organic matter and resistant organic matter is linked to primary productivity. However, variations in sulphate reduction efficiency, based on elemental abundance and isotopic composition of sulphur, reveal that the proportion of metabolisable vs. resistant organic matter has varied along the cycles. This is interpreted in terms of the variation in organic delivery. Organic sulphur content is found to be proportional to the organic matter content, whereas concentrations of pyritic sulphur are constant at very high (> 10% TOC) values. This result is explained by a limitation of available iron for pyritisation at times of very high organic flux. Under such conditions, HS- in excess could be responsible for the early formation of organo-sulphur compounds and thus for the preservation of highly aliphatic (i.e. lipid-rich) organic matter.
Lallier-Verges, EHayes, J MBoussafir, MZaback, D ATribovillard, N PConnan, JBertrand, PengResearch Support, Non-U.S. Gov'tNetherlands1997/01/01 00:00Chem Geol. 1997;134:277-88.

Stratigraphic evolution of the inner continental shelf in response to late Quaternary relative sea-level change, northwestern Gulf of Maine - Barnhardt, W. A.; Belknap, D. F.; Kelley, J. T. (Geological Society of America Bulletin, 1997)
Accumulations of deltaic and littoral sediments on the inner continental shelf of Maine, Gulf of Maine, preserve a record of postglacial sea-level changes and shoreline migrations, The depositional response of coastal environments to a cycle of regression, lowstand, and transgression was examined with seismic-reflection profiles, vibracores, and radiocarbon dates collected from sediments at the mouths of the Kennebec and Penobscot Rivers, Sequence-stratigraphic analysis of these data reveals two distinctly different successions of late Quaternary deposits that represent end members in an evolutionary model for this glaciated coast. Seaward of the Kennebec River, coarse-grained shorelines with foreset beds occur at depths of 20-60 m and outline the lobate margin of the Kennebec River paleodelta, a complex, rock-framed accumulation of glaciomarine and deltaic sediments capped by estuarine and marine deposits, Sand derived from this system today supports large barrier spits and extensive salt marshes, In contrast, the mouth of the Penobscot River is characterized by thick deposits of glaciomarine mud overlain by marine mud of Holocene age, including gas-charged zones that have locally evolved into fields of pockmarks, The distinct lark of sand and gravel seaward of the Penobscot River and its abundance seaward of the Kennebec River probably reflect differences in sediment som ces and the physiography of the two watersheds, The contrasting stratigraphic framework of the se systems demonstrates the importance of understanding local and regional differences in sediment supply, sea-level change, bedrock structure, and exposure to waves and tides in older to model river-mouth deposition on glaciated coasts.Evolution of shelf deposits was largely controlled by relative sea level, which locally fell from a highstand (+60 to +70 m at 14 ka) contemporary with deglaciation to a lowstand (-55 m at 10.8 ka), The sea-level lowering was accompanied by fluvial incision of older deposits, producing a regressive, basal unconformity, Major rivers deposited abundant sediment over this surface, Sea level then rose at varying rates, extensively reworking formerly emergent parts of the shelf and producing a shoreface ravinement surface in areas exposed to waves, A tidal ravinement surface has developed in sheltered embayments where erosion is due mainly to tidal currents. Incised valleys in both settings preserve transgressive estuarine deposits that contain lagoonal bivalves and salt-marsh foraminifera at depths of 15-30 m, These deposits accumulated ca, 9.2-7.3 ka, locally a period of relatively slow sea-level rise.
Wy671Times Cited:38Cited References Count:65

Variability in radiocarbon ages of individual organic compounds from marine sediments - Eglinton, T. I.; BenitezNelson, B. C.; Pearson, A.; McNichol, A. P.; Bauer, J. E.; Druffel, E. R. M. (Science, 1997)
Organic carbon (OC) from multiple sources can be delivered contemporaneously to aquatic sediments. The influence of different OC inputs on carbon-14-based sediment chronologies is illustrated in the carbon-14 ages of purified, source-specific (biomarker) organic compounds from near-surface sediments underlying two contrasting marine systems, the Black Sea and the Arabian Sea, In the Black Sea, isotopic heterogeneity of n-alkanes indicated that OC was contributed from both fossil and contemporary sources. Compounds reflecting different source inputs to the Arabian Sea exhibit a 10,000-year range in conventional carbon-14 ages. Radiocarbon measurements of biomarkers of marine photoautotrophy enable sediment chronologies to be constructed independent of detrital OC influences.
Xq247Times Cited:175Cited References Count:37

Cape May site report - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S.; Sugarman, P.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Proc. ODP, Init. Repts, 1996)
id: 55

Chemical weathering and controls on atmospheric O2 and CO2: Fundamental principles were enunciated by J. J. Ebelmen in 1845 - Berner, Robert A.; Maasch, Kirk A. (Geochimica et Cosmochimica Acta, 1996)
id: 1533

Compound specific radiocarbon analysis as a tool to quantitatively apportion modern and fossil sources of polycyclic aromatic hydrocarbons in environmental matrices. - Eglinton, T. I.; Pearson, A.; McNichol, A. P.; Currie, L. A.; Benner, B. A.; Wise, S. A. (Abstracts of Papers of the American Chemical Society, 1996)
1Va915 Times Cited:0 Cited References Count:0

Deep water formation and exchange rates in the Arctic Ocean: Implications from the distribution of 14C - Schlosser, P.; Kromer, B.; Ekwurzel, B.; Boenisch, G.; McNichol, A.; Schneider, R.; von Reden, K.; Oestlund, G. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 947; 1

Distribution of otoliths in surficial sediments of the U. S. Atlantic continental shelf and slope and potential for reconstructing Holocene fish stocks - Elder, K. L.; Jones, G. A.; Bolz, G. (Paleoceanography, 1996)
id: 1755

Gas chromatographic isolation of individual compounds from complex matrices for radiocarbon dating - Eglinton, T. I.; Aluwihare, L. I.; Bauer, J. E.; Druffel, E. R.; McNichol, A. P. (Anal Chem, 1996)
This paper describes the application of a novel, practical approach for isolation of individual compounds from complex organic matrices for natural abundance radiocarbon measurement. This is achieved through the use of automated preparative capillary gas chromatography (PCGC) to separate and recover sufficient quantities of individual target compounds for (14)C analysis by accelerator mass spectrometry (AMS). We developed and tested this approach using a suite of samples (plant lipids, petroleums) whose ages spanned the (14)C time scale and which contained a variety of compound types (fatty acids, sterols, hydrocarbons). Comparison of individual compound and bulk radiocarbon signatures for the isotopically homogeneous samples studied revealed that Delta(14)C values generally agreed well (+/-10%). Background contamination was assessed at each stage of the isolation procedure, and incomplete solvent removal prior to combustion was the only significant source of additional carbon. Isotope fractionation was addressed through compound-specific stable carbon isotopic analyses. Fractionation of isotopes during isolation of individual compounds was minimal (<5 per thousand for delta(13)C), provided the entire peak was collected during PCGC. Trapping of partially coeluting peaks did cause errors, and these results highlight the importance of conducting stable carbon isotopic measurements of each trapped compound in concert with AMS for reliable radiocarbon measurements. The addition of carbon accompanying derivatization of functionalized compounds (e.g., fatty acids and sterols) prior to chromatographic separation represents a further source of potential error. This contribution can be removed using a simple isotopic mass balance approach. Based on these preliminary results, the PCGC-based approach holds promise for accurately determining (14)C ages on compounds specific to a given source within complex, heterogeneous samples.
Eglinton, T IAluwihare, L IBauer, J EDruffel, E RMcNichol, A Peng1996/03/01 00:00Anal Chem. 1996 Mar 1;68(5):904-12. doi: 10.1021/ac9508513.

Holocene climatic and human influences on lakes of the Yucatan Peninsula, Mexico: An interdisciplinary, palaeolimnological approach - Whitmore, T. J.; Brenner, M.; Curtis, J. H.; Dahlin, B. H.; Leyden, B. W. (Holocene, 1996)
We used palaeolimnological techniques to examine effects of Holocene climate change and human influence on lakes of the Yucatan Peninsula, Mexico. The three study lakes are located along a west-east transect that represents a gradient of increasing modern precipitation and density of former Maya settlement. At Lake Coba, an 880-cm sediment core yields a complete record of lacustrine sedimentation that began when the lake first filled similar to 8000 BP as groundwater level rose in response to rising sea level and increased precipitation. Diatom, ostracod, and delta(18)O evidence indicate that Lake Coba was initially shallow and saline. Coba, presently in the region of greatest rainfall, showed more episodic water-level changes than Lake San Jose Chulchaca or Lake Sayaucil. High lake level and fresh water were evident at 440 cm (similar to 2600 BP), followed by a decline in water levels and an increase in total ionic salinity to the present time. In a 613-cm core from Sayaucil, in the intermediate precipitation zone, total salinity was high between 600 and 400 cm (similar to 3050 and 2000 BP), followed by consistently higher water levels. Salinity was high in the lower portion of a 110-cm San Jose Chulchaca core (beginning similar to 1860 BP), followed by a gradual and consistent freshening of water to the present time.Trophic state changes and human influence on lakes were evaluated using diatom, delta(18)O, total P, sedimentary organic matter, and preliminary pollen data. Maximal human disturbance at Lake Coba, a densely settled Maya urban site, occurred during a deep-water event at 440 cm, followed by a decline in human influence and trophic state to the present time. Trophic state and linear sedimentation rates in Sayaucil increased significantly above 400 cm (after similar to 2000 BP), probably associated with initial Maya settlement near Xtojil and subsequent small-scale farming. Limnological disturbance may have preceded the period of maximal human occupation because initial land clearance and consequent soil erosion probably affected water quality substantially. San Jose Chulchaca lacks archaeological evidence of human occupation in the drainage, and shows gradual changes in trophic state not caused by human disturbance. With the exception of a C-14 date on wood from the base of the Coba core, C-14 dates and chronologies may be artificially old as a consequence of hard-water-lake error. Trophic state changes in the study lakes were generally consistent with known patterns of human settlement and population change. Late-Holocene water-level fluctuations were most pronounced in Lake Coba in eastern Yucatan, where modern rainfall is currently greatest, but lake level is generally lower than during much of the past. Lake level was relatively constant in Sayaucil in the central peninsula, whereas lake level in San Jose Chulchaca in the arid western portion of the peninsula increased gradually over time.
Vh189Times Cited:56Cited References Count:65

A Holocene vegetation history from lowland Guatemala - Islebe, G. A.; Hooghiemstra, H.; Brenner, M.; Curtis, J. H.; Hodell, D. A. (Holocene, 1996)
A 5.45-m core from Lake Peten-Irza, lowland Guatemala, contains a near-complete record of Holocene sedimentation. The age-depth relationship for the core is based on AMS C-14 dating of terrestrial wood fragments and provides a reliable chronology in this karst region where hard-water lake error has typically confounded sediment geochronology. In the basal part of the sequence, pollen of the Moraceae-Urticaceae group dominate, indicating the presence of widespread tropical forest during the early Holocene (c. 8600-5600 yr BP). Relative abundance of pollen of high forest taxa declined beginning as early as 5600 yr BP, indicating climatic drying or perhaps initial land clearance. Deforestation by prehistoric Mayan inhabitants is documented clearly in the pollen record beginning about 2000 pr BP (106 cal BC-122 cal Ao, 95.4%, 2 sigmas) by the appearance of disturbance taxa (e.g. Ambrosia and Poaceae) and presence of Zea. Forest regrowth occurred following the Classic Maya collapse, c. AD 900, as reflected by a relative increase in Moraceae-Urticaceae pollen.
Vh189Times Cited:103Cited References Count:44

Increased continental-margin slumping frequency during sea-level lowstands above gas hydrate-bearing sediments - Paull, C. K.; Buelow, W. J.; Ussler, W.; Borowski, W. S. (Geology, 1996)
We present C-14 data on sediment samples from cores of the upper 7 m of the sediment column overlying a major continental-rise gas hydrate field on the southern Carolina Rise and inner Blake Ridge offshore the southeastern United States. The data show that glacial-age sediments are underrepresented in the cores. The observation is consistent with a previously predicted association between sea-level lowstands and increased frequency of sea-floor slumping on continental margins containing gas hydrates.
Tt580Times Cited:86Cited References Count:26

Isolation of Individual Organic Compounds for AMS Radiocarbon Analysis--A Novel Approach - Eglinton, T. I.; McNichol, A. P.; Benitez-Nelson, B. C.; Pearson, A.; von Reden, K. F.; Schneider, R. J.; Bauer, J. E.; Druffel, E. R. M. (Radiocarbon, 1996)
id: 1650

Isolation of Individual Organic Compounds for AMS Radiocarbon Analysis -- A Novel Approach - Eglinton, T. I.; McNichol, A. P.; Benitez-Nelson, B. C.; Pearson, A.; von Reden, K. F.; Schneider, R. J.; Bauer, J. E.; Druffel, E. R. M. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 1800; 1

The "Lake" of Mayran: Reconstructing an Environmental History from Alluvial, Lacustrine, and Soils Records in Northern Mexico - Butzer, K. W. Frederick C. D. Cordova C. E. Butzer E. K. Abbott y J. T. (Annual Meeting, Sociedad Mexicana de Antropologia, 1996)
id: 903; Symposium: "El Hombre y el Lago: Ayer y Hoy"

Late Quaternary deep circulation in the western equatorial Atlantic (Book Section) - Curry, W. B. (The South Atlantic: Present and Past Circulation, 1996)
id: 1336

A long pollen record from lowland Amazonia: Forest and cooling in glacial times - Colinvaux, P. A.; DeOliveira, P. E.; Moreno, J. E.; Miller, M. C.; Bush, M. B. (Science, 1996)
A continuous pollen history of more than 40,000 years was obtained from a lake in the lowland Amazon rain forest. Pollen spectra demonstrate that tropical rain forest occupied the region continuously and that savannas or grasslands were not present during the last glacial maximum. The data suggest that the western Amazon forest was not fragmented into refugia in glacial times and that the lowlands were not a source of dust. Glacial age forests were comparable to modern forests but also included species now restricted to higher elevations by temperature, suggesting a cooling of the order of 5 degrees to 6 degrees C.
Vk748Times Cited:350Cited References Count:42

Preparative capillary gas chromatographic isolation of individual compounds from complex matrices for radiocarbon dating - Eglinton, T. I.; Aluwihare, L. I.; Bauer, J. E.; Druffel, E. R. M.; McNichol, A. P. (Analytical Chemistry, 1996)
id: 1340

Seasonal variability of particulate organic radiocarbon in the northeastern Pacific - Druffel, Ellen R. M.; Bauer, J. E.; Williams, P. M.; Griffin, S.; Wolgast, D. (Journal of Geophysical Research, 1996)
id: 1239

Continental climate response to orbital forcing from biogenic silica records in Lake Baikal, Siberia - Colman, S. M.; Peck, J. A.; B, Karabanov E.; Carter, S. J.; Bradbury, J. P.; King, J. W.; Williams, D. F. (Nature, 1995)
id: 1357

Geological framework, processes, and rates of subsidence in the Mississippi River delta plain - Penland, P. Shea; Jeffress, Williams S.; Roberts, Harry H.; Bailey, Alan; Kuecher, Gerald J.; Suhayda, Joseph N.; Ramsey, Karen E. (AAPG Bulletin, 1995)
id: 65

Late Pleistocene Oxygen-Isotope Records of Biogenic Silica from the Atlantic Sector of the Southern-Ocean - Shemesh, A.; Burckle, L. H.; Hays, J. D. (Paleoceanography, 1995)
We determined the isotopic composition of oxygen in marine diatoms in eight deepsea cores recovered from the Atlantic sector of the Southern Ocean. The analytical reproducibility and core-to-core consistency of the isotopic signal suggests that diatom delta(18)O can be used as a new paleocenographic tool to reconstruct past variations in surface water characteristics and to generate O-18 -isotope-based stratigraphy for the Southern Ocean. The data indicate that diatom delta(18)O reflects sea surface temperature and seawater isotopic composition and that diatoms retain their isotopic signal on timescales of a least 430 ka. The delta(18)O analyses of different diatom assemblages reveal that the isotopic signal is free of species effects and that the common Antarctic species have the same water-opal fractionation. The transition from the last glacial maximum (LGM) to the Holocene is fully recorded in high sedimentation rate cores. An O-18 enrichment during the LGM, a post-LGM meltwater spike and an input of meltwater during the late Holocene are the main isotopic features observed in down core records. The origin of this meltwater was very likely melting icebergs and/or continental ice or by melting sea ice that had accumulated snow. The most pronounced meltwater effects are recorded in cores that are associated with the Weddel gyre. Our results provide the basis for extending isotope studies to oceanic regions devoid of carbonate; further, isotopic stratigraphies may be constructed for records and regions where they were previously not possible.
Rd382Times Cited:82Cited References Count:23

Late Quaternary Relative Sea-Level Change in the Western Gulf of Maine - Evidence for a Migrating Glacial Forebulge - Barnhardt, W. A.; Gehrels, W. R.; Belknap, D. F.; Kelley, J. T. (Geology, 1995)
New radiocarbon-dated cores obtained by Vibracorers in the western Gulf of Maine confirm that a short-lived, relative sea-level lowstand of similar to-55 m occurred at 11-10.5 ka. These cores and younger salt-marsh data also reveal that rates of transgression varied throughout the Holocene, probably due to local variations in glacial isostasy. The isostatic component is resolved by subtracting published approximations of eustatic sea level from our well-determined observations of local relative sea level. A large peek in the isostatic curve coincides with the lowstand and is interpreted as a forebulge 20-25 m in amplitude. Forebulge migration is estimated at 7-11 km/100 yr, based on the timing of lowstands across the region.
Qr847Times Cited:69Cited References Count:32

Possible Role of Climate in the Collapse of Classic Maya Civilization - Hodell, D. A.; Curtis, J. H.; Brenner, M. (Nature, 1995)
THE Maya civilization developed around 3,000 years ago in Mesoamerica, and after flourishing during the so-called Classic period, it collapsed around 750-900 AD(1). It has been speculated(2-6) that climate change may have played a part in this collapse. But efforts to reconstruct the last three millennia of Mesoamerican climate using palynological methods have met with equivocal success, because human-mediated deforestation has altered regional vegetation in ways that mimic climate shifts, making it difficult to discriminate between natural and anthropogenic changes(7-15). Here we use temporal variations in oxygen isotope and sediment composition in a 4.9-m sediment core from Lake Chichancanab, Mexico, to reconstruct a continuous record of Holocene climate change for the central Yucatan peninsula. The interval between 1,300 and 1,100 yr up (AD 800-1,000) was the driest of the middle to late Holocene epoch, and coincided with the collapse of Classic Maya civilization, This continuous climate proxy record thus provides evidence of climate deterioration in the Maya region during the terminal Classic period.
Rb101Times Cited:439Cited References Count:41

A Sea-Level Rise Curve from Guilford, Connecticut, USA - Nydick, K. R.; Bidwell, A. B.; Thomas, E.; Varekamp, J. C. (Marine Geology, 1995)
High-resolution stratigraphic studies based on sediment chemistry, lithology, macroflora, and benthic foraminiferal assemblages in three peat cores from coastal salt marshes at Guilford, Connecticut, show that coastal marshes are ephemeral environments. Marsh-wide environmental variations were common, and century-long episodes of relative submergence alternated with emergence. Despite about 2 m of relative sea-level rise (RSLR) in Connecticut over the last 1500 years, the marshes have expanded both landwards and seawards, and marsh accretion has been outpaced only marginally by RSLR.We used radiocarbon dating and the level of anthropogenic markers (metal pollution, as dated with Pb-210) in the cores for age control. For most of the last 1000 years the rate of RSLR was between 1.3 and 1.8 mm/yr, but over the last 300-400 years it increased to 2.9-3.3 mm/yr, and has been faster than the accretion rate, especially in the middle marsh. The net-submergence rate or ''submergence index'' (ratio of the rate of RSLR and marsh-accretion rate) averaged about 1.15 over the last 1000 years, and increased to about 1.5 over the last 200 years.The rate of RSLR was very sluggish during the early part of the Little Ice Age, but we found a slightly higher rate during the Little Climate Optimum; this excursion is close to the noise level, however. The most significant observation is that RSLR increased strongly around A.D. 1650. The onset of this acceleration falls in the middle to end of the Little Ice Age, and thus preceded the period of modern global warming that started late last century and that has been tentatively correlated with anthropogenic emissions of greenhouse gases.
Rl477Times Cited:71Cited References Count:81

Tree Survival and Growth on Land Reclaimed in Accord with Public-Law-95-87 - Chaney, W. R.; Pope, P. E.; Byrnes, W. R. (Journal of Environmental Quality, 1995)
The objective of this study was to determine survival and growth of black walnut (Juglans nigra L.) and northern red oak (Quercus alba L.) 12 yr after planting on a surface-mined site in southern Indiana reclaimed according to specifications of Public Law 95-87, the Surface Mining Control and Reclamation Act of 1977. A stocking level adequate to meet the requirements for forest land use (1112 trees/ha, or 450 trees/acre) was attained only for black walnut and only if competing ground cover vegetation was controlled in the tree rows. Height of both tree species was significantly greater when ground cover vegetation was controlled during the first 2 yr, but the growth rate, approximately 10 cm/yr, was very slow.
Rj934Times Cited:17 Cited References Count:18

Contamination in Boston Harbor and Massachusetts Bay - Bothner, M. H.; Butman, B.; Signell, R. P. (United States Geological Survey Yearbook, 1994)
id: 1231

Global methanotrophy at the Archean-Proterozoic transition - Hayes, J. M. (Early Life on Earth. Nobel Symposium, 1994)
id: 1565

High-Resolution Climate Records from the North-Atlantic during the Last Interglacial - McManus, J. F.; Bond, G. C.; Broecker, W. S.; Johnsen, S.; Labeyrie, L.; Higgins, S. (Nature, 1994)
THE two deep ice cores recovered by the GRIP(1) and GISP(2) projects at Summit, Greenland, agree in detail over the past 100,000 years(3) and demonstrate dramatic climate variability in the North Atlantic region during the last glacial, before the current period of Holocene stability. This glacial climate instability has subsequently been documented in the marine sedimentary record of surface-ocean conditions in the North Atlantic(4). Before 100 kyr ago the two ice core records are discrepant, however, casting doubt on whether the oxygen isotope fluctuations during the last interglacial (Eemian) seen in the GRIP core(1,5) represent a true climate signal. Here we present high-resolution records of foraminiferal assemblages and ice-rafted detritus from two North Atlantic cores for the interval 65 kyr to 135 kyr ago, extending the surface-ocean record back to the Eemian. The correlation between our records and the Greenland ice-core records is good throughout the period in which the two ice cores agree, suggesting a regionally coherent climate response. During the Eemian, our marine records show a more stable climate than that implied by the GRIP ice core, suggesting that localized phenomena may be responsible for the variability in the latter record during the Eemian.
Ph254Times Cited:313Cited References Count:25

Integrated Dating Techniques to Determine the Age of a Glauconite Deposit on the Modern Seafloor - am Ende, B. A.; Paull, C. K.; Benninger, L. (EOS, Transactions,American Geophysical Union, 1994)
id: 901

La Curva Di Risalta Del Mare Tirreno Negli Ultimi 40 KA Ottenuta Mediante Datazioni Di Speleotemi Sommersi E Dati Archeologici - Alessio, M.; Allegri, L.; Antonioli, F.; Belluomini, G.; Improta, S.; Manfra, L.; Martinez, M. P. (International Meeting on Underwater Geology, 1994)
id: 899

ODP Initial Reports, Leg 150X - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S. F.; Sugarman, P. J.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Ocean Drilling Program, 1994)
id: 1347

Radiocarbon Dating of Marine Deposits on Submerged Speleothems and Sea-Level Oscillation - Alessio, M.; Allegri, L.; Antonioli, F.; Belluomini, G.; Improta, S.; Manfra, L. (15th International Radiocarbon Conference, 1994)
id: 900

Radiocarbon studies of particulate organic carbon in the eastern North Pacific Ocean - Druffel, E. R. M.; Bauer, J. E.; Williams, P. M.; Griffin, S.; Wolgast, C. Lee; Wakeham, S. G. (1994 ocean sciences meeting, 1994)
id: 1240; 3

Radiocarbon Studies of Particulate Organic Carbon in the Eastern North Pacific Ocean - Druffel, E. R. M.; Griffin, S.; Bauer, J. E.; Williams, P. M.; Wolgast, D. M.; Lee, C. (15th International Radiocarbon Conference, Glasgow, Scotland, 1994)
id: 907

Radiocarton Dating of Pollen by Accelerator Mass Spectrometry - Brown, Thomas Alexander (University of Washington, 1994)
id: 1494; Geophysics Program

Subsidence in the Mississippi River Delta - Important influences of valley filling by cyclic deposition, primary consolidation phenomena, and early diagenesis - Roberts, H. H.; Bailey, A.; Kuecher, G. J. (Transactions of the Gulf Coast Association of Geological Societies, 1994)
id: 1273

A synthesis of post-glacial diatom records from Lake Baikal - Bradbury, J. Platt; Bezrukova, Ye V.; Chernyaeva, G. P.; Colman, S. M.; Khursevich, G.; King, J. W.; Likoshway, Y. V. (Journal of Paleolimnology, 1994)
The biostratigraphy of fossil diatoms contributes important chronologic, paleolimnologic, and paleoclimatic information from Lake Baikal in southeastern Siberia. Diatoms are the dominant and best preserved microfossils in the sediments, and distinctive assemblages and species provide inter-core correlations throughout the basin at millennial to centennial scales, in both high and low sedimentation-rate environments. Distributions of unique species, once dated by radiocarbon, allow diatoms to be used as dating tools for the Holocene history of the lake. Diatom, pollen, and organic geochemical records from site 305, at the foot of the Selenga Delta, provide a history of paleolimnologic and paleoclimatic changes from the late glacial (15 ka) through the Holocene. Before 14 ka diatoms were very rare, probably because excessive turbidity from glacial meltwater entering the lake impeded productivity. Between 14 and 12 ka, lake productivity increased, perhaps as strong winds promoted deep mixing and nutrient regeneration. Pollen evidence suggests a cold shrub — steppe landscape dominated the central Baikal depression at this time. As summer insolation increased, conifers replaced steppe taxa, but diatom productivity declined between 11 and 9 ka perhaps as a result of increased summer turbidity resulting from violent storm runoff entering the lake via short, steep drainages. After 8 ka, drier, but more continental climates prevailed, and the modern diatom flora of Lake Baikal came to prominence. On Academician Ridge, a site of slow sedimentation rates, Holocene diatom assemblages at the top of 10-m cores reappear at deeper levels suggesting that such cores record at least two previous interglacial (or interstadial?) periods. Nevertheless, distinctive species that developed prior to the last glacial period indicate that the dynamics of nutrient cycling in Baikal and the responsible regional climatic environments were not entirely analogous to Holocene conditions. During glacial periods, the deep basin sediments of Lake Baikal are dominated by rapidly deposited clastics entering from large rivers with possibly glaciated headwaters. On the sublacustrine Academician Ridge (depth = 300 m), however, detailed analysis of the diatom biostratigraphy indicates that diastems (hiatuses of minor duration) and (or) highly variable rates of accumulation complicate paleolimnologic and paleoclimatic reconstructions from these records.
id: 16
Keywords: Climate change; diatoms; Holocene; Lake Baikal; paleolimnology; palynology

Thermocline Ventilation Rates in the North Pacific - Sonnerup, R. E.; Quay, P. D.; Bullister, J. L.; Key, R. M.; McNichol, A. P.; Jones, G. A. (American Geophysical Union, San Francisco, 1994)
id: 917

The AMS Accelerator at Woods Hole Oceanographic Institution - Schneider, R. J.; von Reden, K. F.; Cohen, G. J.; Jones, G. A. (Symposium of North Eastern Accelerator Personnel, 1992)
id: 1794

Initial Dating and Paleoenvironmental Results From Lake Baikal, Southeastern Siberia - Colman, S. M.; Karabanov, E. B.; Williams, D. F.; Hearn, P. P., Jr.; King, J. W.; Orem, W. H.; Bradbury, J. P.; Shanks, W. C., III; Jones, G. A.; Carter, S. J. (Abstracts With Programs of the American Quaternary Association, 1992)
id: 905

Carbon cycling in coastal sediments: 2. An investigation of the sources of CO2 to pore water using carbon isotopes - McNichol, A. P.; Druffel, E. R. M.; Lee, C. (Organic Substances and Sediments in Water, Processes and Analytical, 1991)
id: 1743

A Model for Atmospheric Co2 over Phanerozoic Time - Berner, R. A. (American Journal of Science, 1991)
A new model has been constructed for calculating the level of atmospheric CO2 over Phanerozoic time which is much simpler mathematically than the BLAG model, but more complex geologically and biologically. Mathematical simplification comes about by following the cycle of carbon only, lumping all carbonate minerals together, combining the ocean and atmosphere into one reservoir, and calculating atmospheric CO2 level as a series of successive ocean-atmosphere steady states. The isotope mass balance model of Garrels and Lerman (1984) is expanded to include the effect of changing area, elevation, and position of the continents as well as the evolution of land plants as they affect weathering rate, and changes in seafloor area generation rate and the relative importance of deep sea versus shallow platform carbonate deposition as they affect global degassing. Atmospheric CO2 level is calculated from a weathering feedback function for silicates which varies with time as vascular land plants arise and evolve.Results suggest that there has been a notable pattern of varying atmospheric CO2 level over the past 570 my with high levels during the Mesozoic and early Paleozoic and low levels during the Permo-Carboniferous and late Cenozoic. Sensitivity analysis shows that, within reasonable limits of the principal governing parameters, this qualitative trend of varying CO2 is relatively insensitive to the actual values chosen for these parameters. Causes of the CO2 variation are multiple, and no single geological or biological process can be called upon to explain all CO2 variation for all time.The calculated trend of CO2 over time agrees well with independent estimations of paleoclimates. Thus, the greenhouse theory of paleoclimate on a long geological time scale is supported by the results of the present study.
Ff648Times Cited:412Cited References Count:61

Quantification and characterization of porewater organic colloids - Chin, Y. P.; McNichol, A. P.; Gschwend, P. M. (Organic Substances and Sediments in Water. Processes and Analytical, 1991)
id: 1744